Quels sont les effets des recettes pétrolières sur le capital humain en zone CEMAC ? - Fompehou, Amadou (MPRA Paper, 2026)
This article examines the effects of oil revenues on human capital in CEMAC countries over the period 1995–2020. The study is based on a dynamic panel of five countries (Cameroon, Congo, Gabon, Equatorial Guinea and Chad). The data are sourced from the IMF, the World Bank (WDI), the UNDP and the Worldwide Governance Indicators (WGI). The author employs the Blundell and Bond (1998) GMM system estimator to address the endogeneity and persistence of human capital, supplemented by interaction term models and robustness tests (stationarity, cross-sectional dependence). The analyses reveal a negative or non-significant effect of oil revenues on human capital indicators (school enrolment, life expectancy, HDI-education). Institutional quality acts as a powerful positive moderator, whilst revenue volatility has a detrimental effect. These results highlight the need for better governance, stabilisation funds and a more efficient allocation of oil revenues towards education and health.
Number: 129352
Keywords: Human capital; Institution; Oil revenue

Restriction des transactions de devises en espèce et effet potentiel sur le pouvoir d’achat des ménages : cas de la RDC - Mavuma, David; Kahambwe, Chris (MPRA Paper, 2026)
Cette étude analyse les effets potentiels des coûts de transaction liés aux paiements électroniques en devises sur le pouvoir d’achat des ménages en République Démocratique du Congo dans le cadre de la réforme envisagée par la Banque Centrale du Congo. À partir d’une approche fondée sur l’analyse des coûts de transaction et la simulation des tarifs appliqués par les principaux opérateurs de Mobile Money, les résultats montrent que les frais de transaction peuvent accroître le coût effectif des biens et services et réduire le pouvoir d’achat des consommateurs. Dans un contexte marqué par la pauvreté, la faible bancarisation et l’importance du secteur informel, l’étude souligne la nécessité d’accompagner la réforme par des mesures d’encadrement et d’inclusion afin de préserver le bien-être des populations vulnérables et de garantir l’atteinte des objectifs de traçabilité financière. This study examines the potential effects of transaction costs associated with electronic payments in foreign currency on household purchasing power in the Democratic Republic of the Congo within the framework of the reform proposed by the Central Bank of Congo. Using a transaction cost analysis and simulations based on the tariff structures of major Mobile Money operators, the findings suggest that transaction fees may increase the effective cost of goods and services and reduce consumers’ purchasing power. In a context characterized by poverty, low banking penetration, and a large informal sector, the study highlights the need for appropriate regulatory and inclusion measures to protect vulnerable populations and ensure the achievement of the reform’s financial traceability objectives.
Number: 129279
Keywords: Coûts de transaction; Democratic Republic of Congo; Financial Inclusion; Inclusion financière; Mobile Money; Payment Reform; Pouvoir d’achat; Purchasing Power; RDC; Réforme des paiements; Transaction Costs

La souscription à un emprunt obligataire : aspects juridiques - Balla Ondoua, Jean Olivier (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La contribution des banques et des institutions financières internationales au budget des pays en voies de développement demeure conséquente. Seulement, il faut le dire, tant le crédit octroyé au travers des banques que l’aide au développement qui y est délivré par le truchement des accords de prêts, n’ont alors jusqu’à date, pas véritablement su s’adapter au contexte social africain. C’est sans doute ce qui justifie l’alternative que propose désormais la finance directe sur le marché financier au moyen de l’emprunt obligataire. En effet, comparativement aux conditionnalités de prêts aigues qu’imposent les banques et les institutions financières internationales que sont la BM et le FMI, l’emprunt au bénéfice du budget de l’Etat par émission des valeurs du Trésor, pose simplement le principe de sa libre accessibilité à tous les ressortissants CEMAC. En revanche, il est porté un ensemble d’obligations au compte de l’Etat débiteur qui organise et veille tours à tour à la conception, l’exécution, au fonctionnement et la bonne fin de l’opération vis-à-vis des différents investisseurs qui souscrivent à l’appel public à l’épargne lancé par lui. Le présent article vise donc à mettre en exergue les différents aspects juridiques liés aux conditions de souscription des adhérents de l’Etat émetteur, des ressortissants CEMAC et même, des investisseurs non ressortissants CEMAC. Dans ce dernier cas de figure, il importe de rappeler dans cette analyse, ce que prévoit le droit positif Camerounais pour ce qui est de la souscription des Obligations du Trésor Assimilables tant par les résidents CEMAC et non-résidents d’une part et l’attrait qu’elle exerce en matière de recette budgétaire aux vues des transactions en monnaie locale et autres actions en convertibilité des devises qu’une telle opération génère d’autre part. The contribution of banks and international financial institutions to the budget of developing countries remains significant. However, it must be said that both the credit granted through banks and the developments have not, to date, truly adapted to the African social context. This is probably what justifies the alternative now proposed by direct finance on the financial market through bond issuance. Indeed, compared to the stringent loan conditions imposed by banks and international financial institutions such as the World Bank and the International Monetary Fund, Borrowing for the benefit of the state budget through the issuance of Treasury securities simply establishes the principle of its free accessibility to all CEMAC nationals. On the other hand, a set of obligations is imposed on the debtor state, which organizes ensures the design, execution, operation, and successful completion of the operation with respect to the public call for saving launched by it. This article therefore aims to highlight the various legal aspects related to the subscription conditions of the issuer state’s members, CEMAC nationals, and even non-CEMAC investors. In the latter case, it is important to recall in this analysis what Cameroonian positive law provides for regarding the subscription of assimilable treasury bond by both CEMAC residents and non-residents, on the one hand, and the appeal it generates in terms of budget revenue in view of local currency actions that such an operation generates, on the other hand.
Keywords: Alternative d’endettement; Autonomie financière; Budgetary sovereignty; Debt alternative; Dette; Direct financing; Financement Directe; Financial autonomy; Souveraineté budgétaire

La hiérarchie des sources textuelles de la fiscalité minière dans les Etats francophones d’Afrique subsaharienne : le cas du Cameroun - Onana Mbida, Rodrigue Davy (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La mondialisation des échanges économiques implique des mutations profondes sur la hiérarchie des sources de la fiscalité dans l’ordre juridique interne des États. Le cas spécifique de la hiérarchie des sources de la fiscalité minière dans les États francophones d’Afrique subsaharienne constitue un exemple emblématique. Pour le démontrer, le présent article essaie d’identifier les éléments qui caractérisent la hiérarchie des sources de la fiscalité minière au Cameroun. Il ressort de cette analyse deux constats. D’un côté, la pluralité des sources légales de la fiscalité minière se précise dans un contexte de recul du monisme législatif. D’un autre côté, la prééminence dommageable des sources contractuelles au détriment des sources légales dans la taxation des activités minières s’impose aux États. Il est donc impératif pour les États d’Afrique subsaharienne comme le Cameroun de bien structurer leurs régimes fiscaux miniers afin de maximiser le prélèvement des recettes qui en découlent. The globalization of economic exchanges entails profound transformations in the hierarchy of tax law sources within the domestic legal systems of States. The specific case of the hierarchy of sources of mining taxation in French-speaking sub-Saharan African countries serves as a representative example. To demonstrate this, the present article seeks to identify the elements that characterize the hierarchy of mining taxation sources in Cameroon. The analysis reveals two main findings. On the one hand, the plurality of legal sources of mining taxation is becoming more evident in a context marked by the decline of legislative monism. On the other hand, the harmful predominance of contractual sources over legal sources in the taxation of mining activities is increasingly imposed on States. It is therefore imperative for sub-Saharan African countries such as Cameroon to properly structure their mining tax regimes in order to maximize the revenue derived from them.
Keywords: Cameroun; Contractual sources; Fiscalité minière; Hiérarchie juridique; Legal hierarchy; Legal sources; Mining taxation; Sources contractuelles; Sources légales

La mobilisation des ressources fiscales dans le district de Bamako : entre insuffisances du cadre juridique et difficultés pratiques - Ballo, Mamadou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La faible mobilisation des ressources financières en générale et, des recettes fiscales en particulier, constitue un obstacle majeur à la mise en œuvre de la politique de décentralisation au Mali. En effet, après plus trente ans de pratique, le processus de décentralisation territoriale au Mali connait toujours des difficultés de fonctionnement qui traduisent une certaine ineffectivité due à l’insuffisance des ressources financières. Les ressources fiscales en constituent une part importante. La présente réflexion se propose d’analyser les difficultés relatives à la mobilisation effective des ressources fiscales en milieu urbain, en l’occurrence le District de Bamako. Elle emprunte fondamentalement la méthode juridique notamment sous l’angle des finances locales centrées sur l’analyse des textes juridiques et des ressources doctrinales. Toutefois, il est fait parfois recours à la méthode empirique (sociologique) afin de mieux appréhender la perception des contribuables à l’égard de la législation fiscale. La première partie analyse les insuffisances du cadre juridique fiscal dont la complexité et l’incohérence contrastent avec le faible niveau d’alphabétisation des populations locales et leur manque de culture administrative. La deuxième partie, analyse les liens entre la défaillance des documents administratifs et le développement des pratiques illégales et l’incivisme fiscal. Au demeurant, la faible mobilisation des ressources fiscales constitue un défi majeur à la réussite du processus de la décentralisation. Elle n’en constitue pas le seul. La crise multidimensionnelle à laquelle le Mali est confrontée parait rédhibitoire du fait du contraste entre sécurité, défense nationale et décentralisation territoriale. Le recours actuel aux délégations spéciales, en lieux et places des Conseils élus, ainsi que la suppression des Communes urbaines et les Cercles comme collectivités, traduisent ce malaise conjoncturel sous la transition politique malienne.

Fiscalité et informalité économique des petites et moyennes entreprises dans la Province de la Tshopo - Ndeli Ndeli, Hilaire; Bofoe Lokangu, Starmans; Tchombe Uyindo, Patrick; Mosema, Ambasu; Mbula Mapanza, Cadette; Milambo, Anifa Monica; Litwanga Ifndjaka, Jean-Pierre; Kalongo Monokela, Jonas (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Cette étude analyse l’interaction qui existe entre la persistance des Petites et Moyennes Entreprises (PME) dans l’informalité et la pression fiscale provinciale à Kisangani. Le constat est que malgré l’existence d’un cadre fiscal sur la formalisation des entreprises, le nombre des entreprises œuvrant dans l’économie informelle est très réduit. La recherche s’interroge sur l’efficacité des mécanismes de mobilisation des recettes provinciales. La présente recherche a fait appel à l’exégèse juridique et à la sociologie du droit comme méthode de recherche et repose sur une approche hybride, combinant une analyse documentaire pour les données secondaires et enquête pour les données primaires (terrain) auprès d’un échantillon raisonné de 40 PME, y compris les agents des administrations fiscales. Les résultats relèvent que 80% des enquêtés considèrent l’impôt comme une charge pour leurs activités et 60% des entreprises fonctionnent dans l’informalité. L’étude met en exergue un paradoxe institutionnel : la province met beaucoup plus l’accent sur la mobilisation des recettes que sur la promotion des PME, provoquant ainsi une pression fiscale et des stratégies de contournement (évitement spatial, corruption et négociation informelles). La recherche démontre que l’informalité des PME à Kisangani n’est pas une question de mauvaise foi ni de manque de civisme fiscal, mais mécanisme rationnel de survie face à un système fiscal inadapté. Elle préconise une transition d’une fiscalité de prélèvement vers une fiscalité de promotion pour éviter le cercle vicieux de dépendance budgétaire. This study analyzes the interaction between the persistence of Small and Medium Enterprises (SME) in informality and provincial tax pressure in Kisangani. The observation is that despite the existence of a tax framework for the formalization of businesses, the number of businesses operating in the informal economy is very small. The research questions the effectiveness of the mechanisms for mobilizing provincial revenue. The present research used legal exegesis and the sociology of law as a research method and is based on a hybrid approach, combining documentary analysis for secondary data and surveys for primary data (field) from a reasoned sample of 40 SMEs, including agents from tax administrations. The results show that 80% of respondents consider tax as a burden on their activities and 60% of businesses operate in informality. The study highlights an institutional paradox: the province places much more emphasis on revenue mobilization than on the promotion of SMEs, thus causing tax pressure and circumvention strategies (spatial avoidance, corruption and informal negotiation). The research demonstrates that the informality of SMEs in Kisangani is not a matter of bad faith or lack of tax compliance, but a rational survival mechanism in the face of an inadequate tax system. It advocates a transition from a levy-based tax system to a promotion-based tax system to avoid the vicious cycle of budgetary dependence.
Keywords: Corruption; Economic Informality; Fiscalité provinciale; Fraude fiscale; Informalité économique; PME; Petites et Moyennes Entreprises; Provincial Taxation; SMEs; Secteur informel; Small and Medium Enterprises; Tax fraud

Le Contrôle des Prix de transfert par les Administrations Fiscales des États de l'Afrique de l'Ouest - Diallo, Mamadou Dian (Université Côte d'Azur, 2025)
Les prix de transfert sont les prix auxquels une entreprise transfère des biens corporels, des actifs incorporels ou rend des services à des entreprises associées situées dans différents pays. En Afrique de l'Ouest, la question des prix de transfert est devenue un enjeu majeur pour les autorités fiscales, dès lors que ces pratiques peuvent être utilisées pour transférer artificiellement des bénéfices vers des juridictions à faible fiscalité, réduisant ainsi les recettes fiscales locales. Les pays de l'Afrique de l'Ouest connaissent une forte présence d'entreprises multinationales, en particulier, dans les secteurs des mines, du pétrole, des télécommunications etc. La faiblesse des capacités de contrôle fiscal, combinée à la complexité des montages fiscaux, rendent difficile la lutte contre l'érosion de la base d'imposition et le transfert de bénéfices à l'étranger.L'imposition des entreprises multinationales est gouvernée par les principes dits, de « territorialité » et de « pleine concurrence ». Il résulte des standards internationaux, que chaque entité d'un groupe multinational doit s'acquitter de l'impôt dans son pays d'implantation, en déterminant son bénéfice local comme si ses transactions avec les autres entités qui lui sont liées étaient effectuées avec des entreprises indépendantes.La présente thèse a pour objectif de traiter du contrôle des prix de transfert par les autorités fiscales des pays de l'Afrique de l'Ouest, dans un contexte où la lutte contre l'évasion fiscale internationale est devenue un enjeu mondial. A cet égard, le projet BEPS initié en 2013 par le G20 a formulé des recommandations à l'endroit des autorités fiscales permettant de traiter efficacement les questions liées aux pratiques BEPS. Ce projet a été intégré dans les principes de l'OCDE applicables en matière de prix de transfert à l'intention des entreprises multinationales et des administrations fiscales, renforcé par le Manuel Pratique de l'ONU sur les prix de transfert à l'intention des pays en voie de développement. Il replace le principe de pleine concurrence au centre de la lutte contre les pratiques BEPS. Transfer pricing refers to the price at which a company transfers tangible or intangible assets, or provides services to associated companies located in different countries. In West Africa, the issue of transfer pricing has become a major challenge for tax authorities, as these practices can be used to artificially shift profits to low-tax jurisdictions, thereby reducing local tax revenues. West African countries have a strong presence of multinational companies, particularly in the mining, oil, and telecommunications sectors. Weak tax audit capacities, combined with the complexity of tax arrangements, make it difficult to combat base erosion and profit shifting abroad.The taxation of multinational companies is governed by the so-called ''territoriality'' and ''arm's length'' principles. International standards stipulate that each entity within a multinational group must pay tax in its country of establishment, determining its local profit as if its transactions with other related entities were conducted with independent companies.This thesis aims to address transfer pricing controls by tax authorities in West African countries, in a context where the fight against international tax evasion has become a global issue. In this regard, the BEPS project initiated in 2013 by the G20 has formulated recommendations for tax authorities to effectively address issues related to BEPS practices. This project was incorporated into the OECD Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations, reinforced by the UN Practical Handbook on Transfer Pricing for Developing Countries. It places the arm's length principle at the center of the fight against BEPS practices.
Keywords: Administration fiscale; Afrique de l'Ouest; Afrique occidentale; Arm's length principle; BEPS; Base d’imposition; Control; Contrôle; Entreprises multinationales; Indirect profit shifting; Multinational enterprises; Pricing; Principe de pleine concurrence; Prix; Prix de cession interne; Prix de transfert (manipulation); Procédures fiscales; Tax authorities; Transfer; Transfer pricing; Transfert; Transfert indirect de bénéfices; West Africa

L'abus de droit en matière fiscale - Silberman, Lauren (Université Paris 12, 2025)
La théorie de l’abus de droit se présente comme un correctif essentiel à l’exercice des droits et un outil pour rétablir l’équilibre entre les intérêts en présence qui sont, en matière fiscale, ceux des contribuables, de l’administration fiscale et de la collectivité. L’abus de droit dépend du droit auquel une limite est apportée, limite pouvant être fixée par le législateur et selon une politique déterminée. Le législateur français a autonomisé la notion d’abus de droit en matière fiscale par la création d’une procédure spéciale de rectification assortie d’une majoration automatique punitive. La multiplication des dispositifs anti-abus d’assiette, qui s’applique dans le cadre de la procédure de rectification de droit commun, et qui n’entrainent pas l’application automatique d’une pénalité, a mené à une évolution de la notion d’abus de droit en matière fiscale. Ces dispositifs encadrent l’exercice de la liberté de choisir la voie la moins imposée, et se distinguent par leur régime et leur sanction. Corrélativement, l’Union européenne a développé sa propre notion d’abus de droit en matière fiscale, d’abord pour apprécier la compatibilité des dispositifs nationaux au droit primaire de l’Union, puis pour encadrer l’exercice des avantages offerts par le droit dérivé. Elle a ainsi dégagé une définition de l’abus de droit dont les critères diffèrent selon le droit abusé. L’OCDE s’est également intéressée à la notion d’abus en matière fiscale dans le cadre de la lutte contre l’érosion de la base d’imposition et le transfert de bénéfices. Son approche, plus pragmatique, se concentre sur les comportements des contribuables et de redevables qui doit être conforme non pas à la législation, mais à la politique fiscale et à l’équité fiscale entre les Etats et les opérateurs sur le marché mondial. L’Union européenne a adopté la même conception de l’abus de droit en matière fiscale par l’adoption d’un paquet de mesures de lutte contre la fraude et l’évasion fiscales. L’approche comportementale et économique de l’abus de droit coexiste aujourd’hui avec l’approche stricte et répressive du droit fiscal français. Cette coexistence a mené à la multiplication des dispositifs anti-abus d’assiette qui font entrer dans le champ de l’abus des comportements identifiés comme abusifs parce que non conformes à la conception internationale et européenne de l’équité fiscale. La notion de fictivité s’est élargie au profit de la notion de validité pour faire entrer dans son champ des comportements autrefois considérés comme de l’optimisation fiscale. Cette nouvelle approche de l’abus de droit en matière fiscale est source d’incertitudes pour les contribuables et les redevables et permet de s’interroger sur l’étendue de la notion d’abus de droit en matière fiscale. The theory of abuse of rights is an essential corrective to the exercise of rights, and a tool for restoring the balance between the interests involved, which, in tax matters, are those of the taxpayer, the tax authorities and the community. Abuse of rights depends on the law to which a limit has been set, a limit that can be set by the legislator according to a specific policy. The French legislator has given autonomy to the notion of abuse of rights in tax matters. It has created a provision to penalize abuse of rights, with a special rectification procedure and an automatic punitive surcharge. But it has also created anti-abuse provisions which apply within the framework of the ordinary rectification procedure and which do not entail the automatic application of a penalty. While all of these measures provide a framework for exercising the freedom to choose the path of least resistance to taxation, they differ in terms of their regimes and penalties. The European Union has also developed its own concept of abuse of rights in tax matters, firstly to assess the compatibility of national provisions with EU primary law, and then to provide a framework for the exercise of the advantages offered by secondary legislation. It has thus established a definition of abuse of rights, the criteria for which differ according to the law being abused. The OECD has also turned its attention to the notion of tax abuse as part of the fight against tax base erosion and profit shifting. Its more pragmatic approach focuses on the behavior of taxpayers and liables, which must be consistent not with legislation, but with tax policy and tax fairness between countries and operators on the global market. The European Union has adopted the same concept of abuse of rights in tax matters, with the adoption of a package of measures to combat tax fraud and evasion. Today, the behavioral and economic approach to abuse of rights coexists with the strict and repressive approach of French tax law. This coexistence has led to a proliferation of anti-abuse provisions that bring into the scope of abuse behaviors identified as abusive because they do not conform to international and European concepts of tax fairness. The notion of fictitiousness has been broadened in favor of the notion of validity, bringing within its scope behaviors previously considered as tax planning. This new approach to abuse of rights in tax matters is a source of uncertainty for taxpayers and liables and raises questions about the scope of the notion of abuse of rights in tax matters.
Keywords: Abus de droit; Abuse of rights; Anti-Abuse mesures; Choice of the path of least taxation; Choix de la voie la moins imposée; Dispositifs anti-Abus; Droit fiscal; Fraude et évasion fiscales; Fraude fiscale; Freedom of movement; Liberté de circulation; Optimisation fiscale; Tax fraud and evasion; Tax planning

La monnaie électronique dans les espaces bancaires européens, sous régionaux africains et OHADA - Fougou, Pierre Damien (Université de Bordeaux, 2025)
En tant qu’innovation majeure, la monnaie électronique s’est imposée dans l’écosystème financier en permettant aux agents économiques de répondre à des besoins distincts mais complémentaires tant en Europe qu’en Afrique. A cet effet, l’analyse de la monnaie électronique à l’aune de ces deux espaces géographiques, et précisément de trois espaces bancaires que sont l’UE, l’UMOA et la CEMAC, a notamment permis de mettre en lumière les différentes dynamiques qu’entraîne cet instrument moderne. En Europe, la monnaie électronique constitue une réponse pragmatique aux micropaiements dans une économie largement bancarisée. En Afrique, elle représente, bien plus qu’une simple solution aux micropaiements, un levier essentiel d'inclusion financière pour des populations majoritairement non bancarisées. Cette thèse propose une analyse juridique comparative de la monnaie électronique dans ces deux espaces géographiques, révélant des contextes socio-économiques contrastés ainsi que des perspectives radicalement différentes malgré une appréhension juridique commune. Afin de mener une analyse intégrant à la fois l’évolution juridique et technologique de la monnaie électronique et des moyens de paiements numériques, l’on consacrera la première partie de l’analyse à étudier les critères de qualification de la monnaie électronique, ce qui permettra de souligner que les espaces bancaires concernés par l’étude disposent d’une appréhension juridique commune en la matière, tout en ayant des appropriations technologiques différentes qui s’illustrent par des formes de monnaie électronique distinctes selon que l’on se trouve en Europe ou dans les espaces bancaires UMOA et CEMAC. Ensuite, l’analyse se poursuivra avec l’étude des innovations technologiques et des mutations juridiques qui ont eu lieu avec l’émergence de la monnaie électronique. Cette analyse sera également le pilier de la posture prospective dans laquelle s’inscrit cette thèse car elle permettra non seulement d’asseoir les réflexions sur la nécessaire évolution des critères monétaires face à l’émergence des moyens de paiements numériques, mais également de plaider pour un changement de paradigme qui consistera principalement à réduire l’ampleur du monopole monétaire traditionnel, et à instaurer une concurrence plus dynamique entre moyens de paiement. Dans cette démarche prospective ayant pour objectif d’améliorer l’efficacité des moyens de paiement et de garantir une inclusion financière plus optimale, l’on proposera également que soit attribué un cours légal à la monnaie électronique en Afrique, et que soit mis sur pied un jeton de monnaie électronique de banque centrale s’appuyant sur la technologie des registres distribués, et ce, afin de favoriser l’intégration économique africaine. En somme, la monnaie électronique constitue bien plus qu'une simple innovation technique. Elle est et peut devenir un véritable vecteur de transformation profonde des systèmes financiers et du droit monétaire. Son encadrement juridique doit donc continuer à évoluer pour accompagner son développement exponentiel. En Afrique particulièrement, les régulateurs gagneraient à en faire un instrument privilégié d'inclusion financière et d'intégration économique régionale, et ce, en optant pour des réformes juridiques et institutionnelles ambitieuses. Cette recherche propose ainsi de repenser les fondements du droit bancaire et monétaire non seulement afin d’adapter la monnaie électronique aux réalités d’une économie de plus en plus numérisée et moins centralisée, mais surtout afin de faire de cet instrument moderne un outil propice aux besoins d’intégration économique en Afrique. As a major innovation, electronic money has established itself in the financial ecosystem by enabling economic agents to meet distinct yet complementary needs in both Europe and Africa. To this end, the analysis of electronic money through the lens of these two geographical areas, and specifically of three banking zones – the EU, WAMU, and CEMAC – has notably highlighted the various dynamics generated by this modern instrument. In Europe, electronic money represents a pragmatic response to micropayments in a largely banked economy. In Africa, it constitutes far more than a simple solution for micropayments; it serves as an essential lever for financial inclusion among predominantly unbanked populations. This thesis offers a comparative legal analysis of electronic money in these two geographical areas, revealing contrasting socio-economic contexts as well as radically different perspectives despite a common legal understanding. In order to conduct an analysis that integrates both the legal and technological evolution of electronic money and digital payment methods, the first part of the analysis will be devoted to examining the qualification criteria for electronic money. This will underscore that the banking zones covered by the study share a common legal understanding of the matter, while having different technological appropriations that are illustrated by distinct forms of electronic money depending on whether one is in Europe or in the WAEMU and CEMAC banking zones. Subsequently, the analysis will continue with the study of technological innovations and legal transformations that have occurred with the emergence of electronic money. This analysis will also serve as the cornerstone of the forward-looking approach that underpins this thesis, as it will not only ground reflections on the necessary evolution of monetary criteria in the face of emerging digital payment methods, but will also advocate for a paradigm shift consisting primarily of reducing the scope of the traditional monetary monopoly and establishing more dynamic competition among payment methods. Within this forward-looking approach aimed at improving the efficiency of payment methods and ensuring more optimal financial inclusion, it will also be proposed that electronic money be granted legal tender status in Africa, and that a central bank electronic money token be established based on distributed ledger technology, in order to promote African economic integration. In sum, electronic money represents far more than a mere technical innovation. It is and can become a genuine vector for profound transformation of financial systems and monetary law. Its legal framework must therefore continue to evolve to support its exponential development. In Africa particularly, regulators would benefit from making it a privileged instrument for financial inclusion and regional economic integration, by opting for ambitious legal and institutional reforms. This research thus proposes to rethink the foundations of banking and monetary law not only to adapt electronic money to the realities of an increasingly digitized and less centralized economy, but especially to make this modern instrument a tool conducive to the needs of economic integration in Africa.
Issue: 2025BORD0334
Keywords: Afrique; Bank; CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; EU; Electronic money; Espace bancaire; Monnaie électonique; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'Union européenne; UE; UMOA; Union économique et monétaire Ouest africaine; WAMU

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

La régularisation fiscale en France des avoirs étrangers non déclarés - Goudarzi, Laurent (Université Paris-Saclay, 2025)
La procédure de régularisation fiscale en France des avoir étrangers non déclarés témoigne du combat de l'administration fiscale contre l'omission des déclarations des comptes bancaires et autres actifs situés hors de l'État de résidence des contribuables.À grand renfort de moyens matériels et humains ainsi que d'un arsenal juridique efficaces assurant une synergie des autorités compétentes à déceler une telle fraude, la présente étude traite également des enjeux et autres failles gravitant autour de cette procédure de mise en conformité fiscale.Dans cette optique, il convient de s'intéresser aux causes de la fraude fiscale et la favorisant, de s'interroger sur la volonté persistante à vouloir dissimuler ses avoirs à l'administration fiscale et enfin, de démontrer en quoi les mécanismes instaurés de dissuasion contre une telle fraude tendent conformément aux valeurs démocratiques. The procedure for the tax regularization of undeclared foreign assets in France testifies to the tax authority its fight against the omission of declarations of bank accounts and other assets located outside the tax residence of taxpayers.With the help of material and human resources as well as an effective legal arsenal ensuring a synergy of the competent authorities to detect such fraud, the present study also deals with the issues and other loopholes revolving around this tax compliance procedure.With this in mind, it is necessary to look at the causes of tax fraud and encourage it, to question the persistent desire to hide one's assets from the tax authorities and finally, to demonstrate how the mechanisms put in place to deter such fraud tend in accordance with democratic values.
Issue: 2025UPASH005
Keywords: Avoirs étrangers; Bank canvassing; Bank secrecy; Compliance; Compliance (droit); Démarchage bancaire; Foreign assets; Fraude fiscale; Lanceur d'alerte; Secret bancaire; Tax fraud; Whistleblower

Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle : enjeux stratégiques et défis juridiques en droit des affaires - Awanvoeke, Larios Borgia Dona (Université de Montréal, 2025)
Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle redéfinissent les modèles économiques et stratégiques du secteur financier. Face aux mutations technologiques, les banques traditionnelles s’associent aux fintechs pour innover, optimiser leurs services et répondre aux attentes des consommateurs. Toutefois, ces collaborations soulèvent des défis juridiques majeurs en matière de responsabilité, de protection des données et de conformité réglementaire. Ce mémoire analyse ces enjeux en adoptant une méthodologie combinant analyse doctrinale, droit comparé et étude des cadres réglementaires existants. L’approche doctrinale a permis d’explorer les concepts clés des fintechs, des banques et de l’IA, en mobilisant les théories économiques et juridiques pertinentes. L’étude comparative entre l’Union européenne, les États-Unis et le Canada a mis en lumière les différences réglementaires, notamment en matière de protection des données et de régulation de l’innovation. Enfin, l’examen des cadres législatifs actuels et des tendances émergentes, telles que les regulatory sandboxes et les innovation hubs, a permis d’anticiper les évolutions nécessaires pour encadrer ces transformations. Les résultats montrent que si l’IA favorise l’innovation et l’automatisation des services financiers, elle pose également des risques en matière de transparence des algorithmes, de cybersécurité et d’équilibre concurrentiel. L’étude met en évidence la nécessité d’une harmonisation réglementaire et de mécanismes de gouvernance adaptés pour garantir un développement équilibré du secteur. Ce mémoire propose plusieurs recommandations, notamment le renforcement des cadres juridiques sur la responsabilité algorithmique, la création de normes internationales harmonisées et la mise en place de collaborations entre banques, fintechs et régulateurs. Ces mesures visent à assurer un environnement financier sécurisé, innovant et conforme aux impératifs de transparence et de protection des utilisateurs. Ainsi, les partenariats fintechs-banques s’imposent comme un levier stratégique incontournable, nécessitant une régulation adaptée pour concilier innovation et stabilité du marché.
Keywords: Algorithm Transparency; Algorithmic Liability; Artificial Intelligence; Automation; Automatisation; Banks; Banques; Business law; Cadre réglementaire; Comparative Law; Competencia; Competition; Concurrence; Cybersecurity; Cybersécurité; Data Protection; Digital Transformation; Droit comparé; Droit des affaires; Financial Governance; Financial Innovation; Fintechs; Gestion des risques; Gouvernance financière; Innovation Hubs; Innovation financière; Innovation hubs; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Partenariats stratégiques; Protection des données; Regulatory Framework; Regulatory Sandboxes; Responsabilité algorithmique; Risk Management; Régulation; Régulatory sandboxes; Strategic Partnerships; Transformation numérique; Transparence des algorithmes

Le sursis de paiement et la protection du contribuable en droit fiscal camerounais - Bidoung Dob, Pierre Landry N. (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Keywords: Cameroun; Contribuable (protection); Droit fiscal; Sursis de paiement

L'obligation d'information du banquier : essai d'une théorie générale - Koyangana Mawoyi, Gracia (Université Paris-Saclay, 2025)
L'obligation d'information du banquier peine à trouver un cadre juridique cohérent. L'objectif principal de cette étude est de proposer l'essai d'une théorie générale de l'obligation d'information du banquier en abordant les questions qui dominent cette notion notamment les interrogations sur son contenu, sa nature et son régime. En effet, l'étude de la notion d'obligation d'information permet d'appréhender son contenu et sa nature marqués par un courant pluraliste qui tend à la multiplication des diligences d'information du banquier et donc à la multiplication des obligations d'information du banquier. Le contenu de l'obligation d'information du banquier va de l'information documentaire au conseil en passant par la mise en garde et l'éclairage selon le type d'opération envisagée et la qualité du bénéficiaire.Par ailleurs, la nature de l'exigence d'information du banquier traduit d'une part, une confusion entre les notions de devoir et d'obligation en droit positif alors qu'une distinction existe entre les deux notions conduisant en principe au régime de responsabilité contractuelle pour une obligation et au régime de responsabilité extracontractuelle pour un devoir. D'autre part, une imprécision peut être relevée concernant la nature extracontractuelle ou contractuelle de l'obligation d'information. Aussi, la pluralité de contenus et de natures de l'obligation d'information du banquier emporte des interrogations sur la cohérence de la notion.Cependant, cette pluralité témoigne de la volonté affichée de protection de la clientèle du banquier au regard de la fonction décisionnelle attachée à l'obligation d'information du banquier qui sert avant tout à contraindre le banquier à apporter des informations aux bénéficiaires, clients ou cautions, afin qu'ils puissent décider au mieux pour leurs intérêts. La recherche d'une cohérence du droit positif est également attendue par rapport au régime de l'obligation d'information du banquier.La controverse pendante ici tient à l'application de la responsabilité contractuelle à l'inexécution de l'obligation d'information du banquier même lorsque celle-ci est intervenue avant la signature du contrat. Cet état du droit positif est l'enjeux central qui fonde le raisonnement prônant la nature contractuelle de l'obligation d'information du banquier. Toutes ces considérations tendent à démontrer que l'obligation d'information du banquier est véritablement une notion fonctionnelle puisque la compréhension de la physionomie de l'obligation d'information se trouve dans la volonté du droit positif, notamment par l'action du juge, qui tend à apporter une solution aux difficultés concrètes rencontrées par les créanciers de l'obligation d'information.
Issue: 2025UPASH002
Keywords: Bank; Banque (responsabilité); Divulgation d'informations; General theory; Information disclosure; Obligation d'information documentaire; Obligation d'éclairer; Obligation de conseil; Obligation de mise en garde; Obligation to advise; Obligation to enlight; Obligation to provide documentary information; Obligation to warn; Théorie générale

Etude comparative de la comptabilisation des stocks en PCGC et en SYSCOHADA - Kambale Kikono, Serge (International Journal of Innovation and Scientific Research, 2025)
Cet article a été consacré à une étude comparative de la comptabilisation des stocks en système comptable congolais et en Système comptable OHADA, avec comme finalité d’établir les points de convergence et de divergence entre ces deux systèmes comptables et dire si de ces deux systèmes comptables sont efficaces dans la comptabilisation des stocks. Ainsi, au terme de nos analyses, nous avons remarqué que les deux systèmes comptables comparés dégagent plus d’éléments de différence que de ressemblance en comptabilisation des stocks. Ces différences constituent, en effet des innovations majeures qu’apporte le Système comptable OHADA au Plan Comptable Général Congolais. D’autres avantages du Système Comptable OHADA sont également dus à des innovations intéressantes apportées par celui-ci en ce qui concerne certains aspects de la vie économique des entreprises. Parmi ces avantages, citons-en: la distinction des stocks, en particulier et la distinction les stocks en activités ordinaires et hors activités ordinaires, l’utilisation d’un compte de variation des stocks pour tout mouvement en rapport avec les stocks et la présence d’un compte pour enregistrer les services encours, etc. This article is devoted to a comparative study of stock accounting in the Congolese accounting system and in SYSCOHADA, with the aim of establishing the points of convergence and divergence between these two accounting systems and determining whether they are effective in stock accounting. At the end of our analysis, we have noted that the two accounting systems compared reveal more differences than similarities in inventory accounting. These differences are, in fact, innovations that SYSCOHADA brings to the PCGC. Other advantages of SYSCOHADA are also due to the major innovations it brings to certain aspects of the economic life of companies. Among these advantages are: the distinction between inventories, in particular, and liabilities and liabilities in general in ordinary and non-ordinary activities, the use of an inventory change account for any movement relating to inventories, the presence of an account to record services in progress, etc.
Keywords: Accounting; Comptabilité; Inventaire; Inventories

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

Problématique d’estimation de valeur actuelle des actifs dans l’espace OHADA - Baya Muzela, Jean Claude; Nyengele Mutambila, Moise; Nkongolo Kaajila, Dieudonné (Revue du contrôle, de la comptabilité et de l’audit, 2025)
Dans un contexte d’absence de procédure claire concernant l’estimation de valeur actuelle des actifs, l’étude a gravité autour de ce questionnement : « Comment estimer la valeur actuelle des actifs dans l’espace OHADA ? Quelles seront les implications de cette estimation sur le résultat des entités ?». Pour répondre à cette question, l’étude a opté la démarche déductive comme méthode de recherche. Elle est contextualisée et illustrée par des données empiriques issues d’un cas pratique enfin de renforcer l’applicabilité. L’objectif assigné consiste à présenter une possibilité aux organisations économiques d’estimer leur patrimoine actif en temps réel en tenant compte de leur contrainte spécifique à l’environnement OHADA. Enfin de mieux agencer la réflexion, trois grandes parties ont constitué l’ossature de cette étude. La première a reposé sur le modèle d’analyse, la deuxième sur le résultat et la discussion de la recherche et la troisième sur les limites de la recherche. Tout compte fait, le résultat de la recherche a révélé qu’il existe une relation inverse entre estimation de valeur actuelle et le résultat des entités. L’estimation entraine une diminution sensible du résultat du fait de la comptabilisation de dépréciations et de ce fait, les hypothèses empiriques émises ont été confirmées. A titre de recommandation, la transposition de la démarche proposée dans cet article est de strict conseil pour toute organisation qui se veut pérenne car, au-delà de l’amincissement du résultat, le maintien de la capacité d’autofinancement demeure une force pour l’entité.
Keywords: Actifs (valeur); OHADA

Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - Almestarehi, Ahmad Abdel Rahim; Al-Ababneh, Hassan Ali; Malkaw, Eyad Mohammad (Theoretical and Practical Research in Economic Fields, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.
Number: 2

Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - Yeboah, Michael; Danquah, Benjamin Adjei; Bawuah, Jonas; Nkwantabisa, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.

La douane malienne : enjeux de la régionalisation - Coulibaly, Youssouf Z; Coulibaly, Alou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La douane est une administration chargée d’établir et de percevoir les droits imposés sur les marchandises à la sortie ou à l’entrée du territoire du pays. Au Mali, le libéralisme économique de la deuxième république a engendré des reformes tant sur le plan organisationnel des douanes. L’assouplissement des procédures douanières et les facilités particulières dans l’octroi des régimes économiques matérialisent ce changement. Force est de constate sur le plan légal et réglementaire, on assista d’une part à la relecture du Code des Douanes et d’autre part à la reforme tarifaire. Ainsi dans cet article nous article, nous faisons une analyse critique des textes réglementaires en vigueur afin de proposer des pistes de solution pour une douane plus efficace et plus performante.
Keywords: Douane; Harmonisation; Régionalisation; Tarif; Taxe

L’impact de l’importation sur l’économie malienne - Dolo, Yamadou; Dolo, Anidjou; Coulibaly, Alou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le Mali importe de nombreux produits en raison du manque de production locale et de la faible compétitivité de certaines industries maliennes. Cette dépendance excessive aux importations affaiblit l'économie nationale et limite les opportunités pour les secteurs agricoles, industriels et commerciaux du pays. Pour remédier à ces problèmes, l’étude recommande de stimuler la production locale, de soutenir les industries et les agriculteurs maliens, et de mettre en place des politiques commerciales et industrielles favorables à la compétitivité des produits nationaux sur le marché international. Ces mesures permettraient de limiter la dépendance aux importations étrangères et de renforcer ainsi l'économie malienne. Ainsi l'objectif que vise cette étude est d'analyser les conséquences économiques et sociales enfin de proposer des solutions idoines. Mali imports many products due to a lack of local production and the low competitiveness of some Malian industries. This excessive dependence on imports weakens the national economy and limits opportunities for the country's agricultural, industrial, and commercial sectors. To address these problems, the study recommends stimulating local production, supporting Malian industries and farmers, and implementing trade and industrial policies that promote the competitiveness of domestic products on the international market. These measures would help limit dependence on foreign imports and thus strengthen the Malian economy. The objective of this study is to analyze the economic and social consequences and propose appropriate solutions.
Keywords: Dependence; Dépendance; Economie; Economy; Import; Import-export; Importation; Taxation

Le droit douanier camerounais à l’ère du terrorisme - Onana, Wafai (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le droit douanier camerounais est traditionnellement tourné vers les missions de perception des recettes et de la protection du tissu économique local. Avec la récente apparition du terrorisme, ce droit doit désormais conjuguer avec la menace sécuritaire ; ce qui suppose une certaine mutation. Ainsi, le changement subi par le droit douanier du fait de sa rencontre avec le phénomène terroriste est tout d’abord théorique ; puisqu’il faut aménager le cadre théorique d’accueil au plan douanier de la dimension sécuritaire. Ce changement est aussi opérationnel en ce sens qu’il induit l’appropriation et l’exercice de la compétence sécuritaire, indicateur du passage d’une prérogative subsidiaire d’aide à la lutte contre l’insécurité à une véritable mission sécuritaire douanière. Cameroonian customs law is traditionally focused on the missions of revenue collection and protection of the local economy. With the recent appearance of terrorism, it must now take into account the security threat, which implies a certain mutation. Thus, the change that customs law must undergo due to the terrorist phenomenon is first of all theoretical, given that it’s necessary to adapt the theoretical framework of reception of the security dimension. This change is also operational in the sense that it induces the appropriation and the effective exercise of security competence, as indicator of the transition from a subsidiary prerogative of aid in the fight against insecurity to a true security mission.
Keywords: Custom law; Droit douanier; Mandat sécuritaire; Protection; Security mandate; Terrorism; Terrorisme

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

Fiscalité dérisoire ou les origines de l’économie informelle dans les pays en voie de développement : éléments de réflexion à partir du cas du Mali - Sissoko, M’Baha Moussa (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Cet article est le fruit des recherches empiriques menées à Bamako, auprès des acteurs publics/institutionnels (notamment l’institut national de statistique) mais aussi de l’exploitation et de l’analyse de la littérature académique sur l’économie informelle. Il n’a pas pour objet de faire une présentation des règles et principes de recouvrement des impôts au Mali, encore moins leur contentieux. Dans un cadre institutionnel normal, nous savons que les finances publiques proviennent de la mobilisation des recettes publiques par les agents assermentés de l’Etat et des collectivités territoriales. Mais, globalement, on constate au Mali que l’Etat central rencontre d’énormes difficultés dans l’application concrète de cette mobilisation des ressources propres alors qu’un tel exercice, relève, rappelons-le, de ses fonctions régaliennes. Cette situation résulte d’une part de la difficulté de recouvrement de certains impôts et taxes et de la rareté de certaines matières imposables d’autre part. Dans ce contexte particulier, [de faible mobilisation des recettes publiques], cet article aide à comprendre les difficultés rencontrées par le l’Etat central en raison notamment de la prédominance de cette économie informelle. This article is the fruit of empirical research carried out in Bamako, with public/institutional players (notably the national statistics institute), as well as the exploitation and analysis of academic literature on the informal economy. It is not intended as a presentation of the rules and principles of tax collection in Mali, still less their litigation. In a normal institutional framework, we know that public finances come from the mobilization of public revenues by sworn agents of the State and local authorities. But, on the whole, we can see that the central government in Mali is encountering enormous difficulties in the practical application of this mobilization of its own resources, even though such an exercise, it should be remembered, falls within its regalian functions. This situation is partly due to the difficulty of collecting certain taxes, and partly to the scarcity of certain taxable materials. In this particular context [of low mobilization of public revenues], this article helps to understand the difficulties encountered by the central government, due in particular to the predominance of the informal economy.
Keywords: Citizen; Citoyen; Economie informelle; Finances publiques; Fiscalité; Impôt; Informal economy; Mali; Public finance; Tax; Taxation

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

Artificial Intelligence in Accounting: Revolutionizing Financial Management in the Digital Landscape - Alnaimat, Mohammad Ahmad; Korsun, Inna; Lutsenko, Kostiantyn; Khodorkovskyi, Oleksandr; Artemchuk, Mykyta (Theoretical and Practical Research in Economic Fields, 2025)
The use of artificial intelligence (AI) builds up the accounting system efficiency, increases data entry accuracy and simplifying the accounting process. The aim of the study is to prove the effectiveness of modern AI-based information technologies (IT) in accounting and the possibilities of AI application for process optimization. The effectiveness and efficiency were proven using comparison methods, statistical analysis, graphical cause-and-effect analysis, modelling using the linear regression method. The assessment was carried out using quantitative and qualitative indicators of labour productivity and process optimization. The results of the study showed that 18 accounting department employees on average are needed to perform standard transactions in the companies studied without AI. With AI, 1 person can handle such a volume of work. Accordingly, with the implementation of AI, the average reduction in Transaction Processing Time per Week is 696.26 hours. Regression analysis confirmed that the implementation of AI increases the companies’ productivity in terms of Transaction Processing Time. Reducing the Data Processing Complexity by one unit leads to a reduction in transaction processing time by 592.69 seconds. Each percent increase in Data Entry Accuracy contributes to a reduction in processing time by 5135.51 seconds. The prospects for implementing AI in accounting include further improving algorithms to increase the accuracy and speed of transaction processing, optimizing material and time consumed.
Keywords: Accounting; Artificial Intelligence; Automation; Data analytics; Digital environment; Financial management; Inteligência artificial; Intelligence Artificielle; Machine learning

Le régime fiscal de la TVA à l’épreuve des activités numériques au Mali - Daou, Yacouba; Camara, Oumar Sinè; Toe, Souleymane (Revue africaine de droit des affaires, 2025)
Le commerce électronique au Mali connaît une forte croissance, mais l’inadaptation du régime fiscal, notamment en matière de TVA, engendre d’importantes difficultés. La nature immatérielle et extraterritoriale des transactions numériques complique leur contrôle, favorisant ainsi l’évasion fiscale et la fraude. De plus, l’identification des acteurs du commerce numérique reste un défi majeur, rendant l’application de la législation fiscale inefficace. Pour y remédier, une réforme s’impose particulièrement par la mise en place d’un mécanisme de collecte de la TVA par les plateformes en ligne, comme l’ont fait le Kenya et le Nigeria. Cette mesure permettrait de mieux encadrer la fiscalité du commerce électronique, d’assurer une concurrence équitable et d’optimiser la mobilisation des recettes fiscales.

La transaction douanière dans les Etats de la sous-région CEMAC - Fonchap Kungang, Clauvis (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Il existe certains litiges en droit douanier où l’on ne peut accéder au juge sans avoir écarté la possibilité d’un recours à la transaction. La transaction a non seulement l’avantage de réduire les délais, mais aussi d’alléger les procédures de résolution des litiges en matière douanière. La question se pose de savoir en quoi consiste la transaction douanière dans la sous-région CEMAC ? En réalité, le problème qui se pose est celui de rechercher l’appréhension de cette procédure qui est également largement appliquée en droit fiscal. Face à cette interrogation, des recherches ont été menées sur le sujet à l’aide de la méthode juridique axée sur l’exégèse des textes de droit douanier de la sous-région, principalement le Code des douanes CEMAC. De ces recherches, il apparait que la transaction est un privilège de l’administration des douanes qui marque l’extinction des poursuites à la fois fréquente et vigoureuse. Il s’agit donc d’une procédure particulière. A ce propos, il est apparu loisible de présenter l’encadrement juridique de la transaction douanière d’une part, avant de faire l’état de sa mise en œuvre d’autre part. L’avènement de la transaction a réduit d’une certaine manière les pouvoirs du juge en contentieux douanier, ce dernier ne pouvant se saisir de manière automatique de certains litiges. Certain disputes in customs law cannot be brought to court without first exploring the possibility of a transaction. Transaction offers the advantage of reducing delays and streamlining the resolution of customs disputes. This raises the question: what constitutes a customs transaction in the CEMAC sub-region? The challenge lies in understanding this procedure, which is also common in tax law. Research into this question employed a legal method, focusing on the interpretation of customs law texts in the sub-region, primarily the CEMAC Customs Code. This research reveals that transactions are a privilege to the customs administration, resulting in the cessation of frequent and vigorous prosecutions. As such, they represent a special procedure. Accordingly, this paper seeks to outline the legal framework for customs transactions and describe their implementation. The advent of transactions has, to some extent, curtailed the powers of judges in customs litigation, as certain disputes can no longer be automatically brought before them.
Keywords: Administration douanière; Customs administration; Customs disputes; Customs users; Financial interests; Intérêts financiers; Litiges Douaniers; Transaction; Usagers douaniers

Money Laundering: New Technologies and Control Challenges (Cryptocurrencies, Blockchain) - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Tackling corruption is a global issue and tackling it effectively requires determination, cooperation and specialised technological knowledge. A significant proportion of global GDP is the sum of the money associated with corruption and fraud. The main objective of this article is to assess how new technologies such as cryptocurrencies and blockchain can combat corruption. The methodology of this article is a literature review. Specifically, scientific articles from databases and international organizations with expertise in new technologies are studied. This article deals with the new ways of corruption and money laundering. New technologies and the knowledge of them are a very important element in order to deal effectively with corruption. Perpetrators of financial crimes are usually ahead of the auditing authorities in terms of techniques and therefore knowledge of the new technology and the possibilities it offers is essential to effectively combat corruption and fraud globally. Cryptocurrencies and blockchain can combat corruption primarily due to their key characteristics of transparency, security, and decentralization. A key prerequisite for the transparency of cryptocurrencies is the application of supervision rules by the responsible authorities and the implementation of blockchain technology. In practice this is often not the case and cryptocurrencies are used as a money laundering tool.
Keywords: Corruption; Cryptocurrencies; Fraud; Money laundering; New technologies

La responsabilité civile des experts-comptables dans le droit de l’OHADA - Ngue, Elise Rolline (Revue africaine de droit des affaires, 2025)
Dans le cadre de l'OHADA, la responsabilité civile des experts-comptables vise à protéger les parties prenantes tout en assurant la sécurité juridique de la profession. Le cadre juridique repose principalement sur l'Acte uniforme portant sur le droit comptable et à l'information financière (AUDCIF), sur l'Acte uniforme relatif au droit commercial général (AUDCG) et sur l'Acte uniforme relatif au droit des sociétés commerciales et du groupement d'intérêt économique (AUSCGIE). Ces textes établissent les fondements de la responsabilité des experts-comptables vis-à-vis des clients et des tiers. La responsabilité civile de l'expert-comptable dans l’espace OHADA est régie par une obligation de moyens. Cela signifie que, bien que l'expert-comptable soit tenu d'utiliser toutes ses compétences pour fournir un service conforme aux règles comptables et juridiques, il n'est pas tenu à une obligation de résultat, sauf dans des cas spécifiques. De plus, il peut être tenu responsable vis-à-vis des tiers lorsqu'une faute commise dans l'exercice de ses fonctions leur cause un préjudice direct. Cependant, des limites existent dans la régulation actuelle, notamment en ce qui concerne la protection des tiers et la question des délais de prescription. En parallèle, des mécanismes de protection sont mis en place pour sécuriser la pratique professionnelle de l'expert-comptable. Ces protections incluent les clauses limitatives de responsabilité, les causes d’exonération (comme la force majeure ou la faute du client), ainsi que des assurances professionnelles couvrant les risques liés à la responsabilité civile. Les ordres professionnels jouent également un rôle clé en encadrant la déontologie et la discipline des experts-comptables, apportant une garantie supplémentaire aux clients et une certaine immunité disciplinaire aux experts-comptables en cas de faute mineure. Enfin, des perspectives d'amélioration du cadre juridique sont nécessaires pour renforcer l’équilibre entre la protection des parties prenantes et la sécurité juridique des professionnels. Cela inclut une réforme visant à clarifier certaines dispositions légales et à encourager une répartition plus juste des risques entre experts-comptables, clients et tiers.

L’infraction douanière en droit camerounais - Sassie Dob, Thomas (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
L’infraction douanière en droit camerounais est une infraction particulière. De quoi tient-t-elle cette particularité ? Voici l’interrogation autour de laquelle la présente étude s’est construite. Il s’est alors révélé que la particularité de l’infraction douanière en droit camerounais a une origine double c’est-à-dire qu’elle le tient aussi bien de ses critères d’identification que de sa qualification légale. Ainsi, contrairement à l’infraction pénale ou de droit commun qui exige la réunion des critères légal, matériel et moral pour sa détermination, l’infraction douanière ne conditionne son identification qu’à la réunion des critères d’ordre légal et matériel qualifiés de critères décisifs. Leur seule mise en évidence suffit pour identifier une infraction douanière. Le critère moral lui n’est qu’adventice ou accessoire. Aussi, dans sa qualification légale, l’infraction douanière répond à une classification bipartite. Ceci sous-entend que le droit douanier ne reconnait que les délits et les contraventions comme infractions. Il n’existe donc pas de crimes en matière douanière comme en matière pénale. Customs offences under Cameroonian public law are special. What makes it so special? This is the question on which this study is based. It has emerged that the special nature of customs offences in Cameroonian public law has a dual origin, i.e., it derives from both the criteria by which they are identified and their legal classification. Thus, unlike a criminal offence or an offence under ordinary law, which requires legal, material and moral criteria to be met in order to be identified, a customs offence can only be identified if the legal and material criteria, described as decisive criteria, are met. Their mere presence is sufficient to identify a customs offence. The moral criterion is only incidental or accessory. In its legal classification, customs offences are classified in two categories. This means that customs law recognizes only misdemeanor ours and contraventions as offences. There are therefore no crimes in customs law as there are in criminal law.
Keywords: Cameroon; Cameroonian law; Cameroun; Customs offence; Droit camerounais; Infraction douanière

Effects of Dynamic Capabilities and Multichannel Integration Quality on Bank Performance; A Moderated Role of Environmental Dynamism : A Moderated Mediation Model Analysis - Geleta, Negash; Amentie, Chalchissa; Getahun, Misganu (African Journal of Economic and Business Research, 2025)
This study investigates the effects of dynamic capabilities (DCs) and multichannel integration quality (MCIQ) on the performance of banks (BP). It also explores the moderating role of environmental dynamism in the banking industry, using a moderated mediation model. Quantitative analyses were employed to examine data collected from multiple banks. Structural equation modeling (SEM) was used to test the relationships between variables, while moderation and mediation effects were analyzed using SEM-AMOS. The findings reveal that dynamic capabilities and MCIQ significantly enhance bank performance. Furthermore, environmental dynamism (ED) moderates the relationship between these variables, intensifying their effects on performance under high levels of dynamism. The mediation analysis shows that MCIQ partially mediates the impact of dynamic capabilities on bank performance. The study is limited by its cross-sectional design, which restricts causal inferences. Additionally, the findings may not be generalizable to non-banking industries or regions with distinct regulatory frameworks. The results provide actionable insights for bank managers, emphasizing the importance of fostering DCs and enhancing MCIQ to sustain performance in rapidly changing environments. The findings highlight significant social benefits, as improved dynamic capabilities (DCs) and critical information quality (MCIQ) enhance bank performance, fostering economic stability, financial inclusion, and customer trust. By enabling resilience and innovation in dynamic environments, banks contribute to broader societal goals, including sustainable development and socio-economic growth. This research contributes to the literature by integrating DCs and MCIQ in a moderated mediation framework, offering a novel perspective on their interplay with environmental dynamism in the banking sector.
Keywords: Dynamic Capabilities; Environmental Dynamism; Moderated Mediation Model; Multichannel integration quality

La citoyenneté fiscale et le numérique en droit camerounais - Gwos, Joachim Ivan (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le Cameroun a entrepris depuis une quinzaine d’années de réglementer et de réguler le secteur du numérique afin de protéger, mais surtout de conserver sa souveraineté dans ce nouvel espace offrant des possibilités quasi infinies et qui n’ont de limites que la force de l’imagination humaine. Cet encadrement juridique vise davantage à sécuriser et à garantir le pouvoir financier de l’Etat qui repose à titre principal sur les prélèvements obligatoires des citoyens. Ainsi, les matières imposables reconnues par le droit camerounais doivent, dans le physique comme dans le numérique, pouvoir être recouvrées par l’Administration fiscale grâce au civisme des citoyens. Le numérique permet ainsi aux citoyens d’accomplir leurs droits et obligations fiscaux avec plus de facilité. Cette modernisation de la citoyenneté fiscale empreinte de facilités, accentue cependant les risques d’incivisme. Ainsi, au-delà de toute volonté d’éviter l’impôt, le droit camerounais est, en l’état actuel, permissible à l’incivisme fiscal. Over the past fifteen years, Cameroon has undertaken to regulate the digital sector in order to protect and, above all, preserve its sovereignty in this new space offering almost infinite possibilities, limited only by the power of the human imagination. The aim of this legal framework is to secure and guarantee the financial power of the State, which is based primarily on compulsory levies on citizens. Thus, the taxable matters recognised by Cameroonian law must, in both physical and digital form, be recoverable by the tax authorities thanks to the civic-mindedness of citizens. Digital technology therefore makes it easier for citizens to fulfil their tax rights and obligations. However, this modernisation of tax citizenship, marked by ease of use, also accentuates the risks of incivility. Thus, beyond any desire to avoid tax, Cameroonian law is, in its current state, open to tax incivility.
Keywords: Cameroonian law; Citoyen fiscal; Citoyenneté fiscale; Civisme fiscal; Droit camerounais; Information fiscale; Tax citizen; Tax citizenship; Tax information

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Emerald Publishing Limited
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

Les principes comptables de l’OHADA à l’ère de la comptabilité informatisée - Tankoano, Gnoari (Revue africaine de droit des affaires, 2025)
Dans un environnement des affaires marqué par l’omniprésence des technologies de l’information et de communication, le législateur OHADA a fait l’option de renforcer et de moderniser son arsenal juridique face aux défis posés par l’usage des outils numériques dans la pratique comptable. En effet, certes, les principes classiques régissant l’élaboration, la tenue et la sécurité des comptes ainsi que les comportements des comptables restent d’application. Du reste, l’étude a dédié à ces principes des analyses appréciables. Cependant, les nouvelles règles permettent de hisser ces principes classiques à la hauteur des défis de la digitalisation de l’activité comptable. Elles concourent à l’impératif de fiabilité, de sécurité, d’authenticité et d’intégrité de l’information comptable, face aux risques d’altération aisée, de fugacité, de surpression et de modification d’une information automatisée. Toutefois, la couverture du droit OHADA à cette nouvelle réalité n’est que partielle et ne parait pas approfondie. Pour une matière qui fait rarement l’objet d’études approfondies par les juristes, notre article, tout en révélant les innovations et les défis, jette les bases de réflexions. Cet exercice est essentiel au regard de la double technicité du sujet abordé, tenant, d’une part, à son objet, à savoir la comptabilité, et d’autre part, à la prise en compte des technologies de l’information et de la communication. En effet, non seulement, l’étude permet aux entités et praticiens d’avoir une meilleure compréhension des principes comptables modernes, mais aussi, elle offre aux contrôleurs des outils d’analyse de la conformité, et aux juges une compréhension et interprétation plus éclairées de cette discipline singulière. Les propositions qui en ressortent permettront au législateur de combler les incohérences et insuffisances juridiques afin de répondre plus efficacement aux défis de la digitalisation de la comptabilité.

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

L’enrichissement sans cause des établissements de crédit dans le droit de la Communauté Economique et Monétaire de l’Afrique Centrale (CEMAC) - Nfoutcha, Georges (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Il ne devrait guère résister de contradiction entre l’enrichissement sans cause et l’enrichissement illicite des établissements de crédit. Le premier relève du Droit civil alors que le second relève indubitablement du Droit pénal. Cette distinction devrait s’estomper en pénalisant l’enrichissement sans cause des établissements bancaires. En ce sens, l’infraction d’enrichissement sans cause des établissements permettrait de renforcer la politique pénale ou criminelle. L’enrichissement sans cause des établissements de crédit, ou l’enrichissement injustifié en Droit français, pose également la difficulté de la justice sociale. La question de la répétition de l’indu semble déjà réglée sous l’emprise de la législation en la matière. Mais, le souci de l’indemnisation mériterait d’être réglementé avec beaucoup d’acuité. Pris à ce titre, la mise en cause de l’enrichissement sans cause, fut-il un établissement de crédit, nécessiterait autant de restituer ce qui est dû, mais également indemniser la victime. Cette mesure devrait s’opérer de la manière la plus juste dans la mesure du possible. Les exigences d’équité y primeraient. Le droit de la Communauté Economique et Monétaire de l’Afrique Centrale gagnerait à se doter d’un véritable fond des dépôts de risques de l’enrichissement sans cause. Cette institution viserait à recevoir ces deniers en toutes fins utiles. Aussi, l’article 1303 du Code civil français résultant de l’ordonnance du 10 février 2016 devrait nourrir notre arsenal juridique sur la mise en œuvre d’une notion d’origine jurisprudentielle en quête de consistance digeste.
Keywords: Civil right; Credit institutions; Criminal law; Criminal policy; Droit civil; Droit pénal; Enrichissement illicite; Enrichissement sans cause; Etablissement de crédit; Illicit enrichment; Institution; Penal policy; Politique criminelle; Politique pénale; Unjust enrichment

Essai sur l'optimisation fiscale : exploration des mécanismes d'optimisation fiscale à travers l'étude des groupes de sociétés - Bakhtous, Siham (Université de Perpignan Via Domitia, 2025)
Cette étude explore les contours et les tensions de l'optimisation fiscale dans un monde globalisé et numérisé, à travers le prisme des groupes de sociétés. En retraçant l'histoire de l'impôt, elle met en lumière les transformations profondes du système fiscal mondial, où les stratégies fiscales transfrontalières se sont progressivement développées, en dehors des prévisions des législations nationales. Bien qu'enraciné dans le principe fondamental de la liberté de choisir la voie fiscale la moins imposée, l'optimisation fiscale a évolué en réponse aux mutations économiques, juridiques et technologiques, donnant lieu à des pratiques parfois controversées qui se situent aux frontières de la légalité et de l'éthique. À l'intersection du droit, de l'économie et de la politique fiscale, l'optimisation fiscale dépasse le simple objectif de réduction de la charge fiscale : elle reflète un processus global où la mobilité des capitaux et des actifs immatériels perturbe les règles fiscales classiques. Bien que souvent conformes à la législation, ces pratiques d'optimisation fiscale dites « agressives » perturbent l'équilibre des systèmes fiscaux mondiaux, contribuant à un phénomène préoccupant : l'érosion de la base d'imposition et le transfert de bénéfices vers des juridictions à faible fiscalité. Cette dérive a mis en évidence les défaillances des systèmes fiscaux nationaux, incapables de suivre le rythme des mutations économiques et de réguler efficacement les pratiques des multinationales. En déconstruisant les mécanismes sous-jacents de l'optimisation fiscale agressive, cette recherche invite à une critique constructive de l'arsenal législatif actuel. Elle souligne l'urgence de repenser les instruments fiscaux dans un contexte où la mobilité du capital et des actifs immatériels redéfinit les règles du jeu économique et de restaurer un équilibre entre les exigences d'efficacité économique des multinationales et la nécessité de garantir une justice fiscale à la hauteur des enjeux mondiaux
Keywords: Base erosion; Digital; Droit fiscal (droit international); Déductions fiscales; Groupes de sociétés; Impôts; Numérique; Optimisation; Optimization; Profit shifting; Restructuration; Restructuring; Réductions fiscales; Tax; Transfert des bénéfices; Érosion de la base d'imposition; Évasion fiscale

The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Impact of the Revision of the OHADA Accounting System on the Decision to Grant Bank Credit to Cameroonian Companies: An Interview with Credit Analysts - Sekadjie, Dedy Christelle; Mbohwa, Charles (Journal of Accounting and Finance in Emerging Economies, 2024)
Purpose: The objective of this study is to evaluate the impact of accounting data produced after the revision of the OHADA accounting system on the decision to grant bank credit to Cameroonian companies. Methodology: qualitative approach was used in this study. We conducted semi-structured interviews with eight credit analysts in eight banks based in Cameroon. We used the Nvivo 10 software to carry out the content analysis. Findings: It emerges from the analysis of the content of the speeches collected that the most used ratios by credit analysts are: activity ratios, debt ratios, operating ratios, financial structure and autonomy ratios, debt ratios and net cash. In addition, the information provided by the new accounting system is increasingly fluid, detailed, and precise and facilitates decision-making. However, when it comes to the completeness and sincerity of the information provided, analysts remain wary because, companies always provide information subjectively based on their interests Implication: This study reveals that despite the revision of the accounting system, users still remain wary face of informations provided because of its subjective nature. It is therefore recommended that Member States promote unified information for all stakeholders.
Keywords: Accounting system; Bank credit; Decision-making; Revision

La compliance en droit bancaire et financier, une fonction juridique et managériale - Amoussou, Henry (Université de Reims Champagne-Ardenne, 2024)
La compliance s’est traduite par une floraison des obligations, des techniques et des procédures, portées par des règles de ''droit dur'' et de ''droit souple''. Leurs mises en œuvre ont été confiées à de nouveaux acteurs. Dans le domaine bancaire et financier, loin de dénaturer la conformité et la régulation, la compliance les renforce en étendant les obligations de cartographie des risques et de vigilance aux risques de corruption et environnementaux. Cependant, le blanchiment de capitaux et le financement du terrorisme restent les risques dominants. Ils sont au cœur de la compliance, notamment au regard de l'activité de sanctions de l’Autorité de contrôle prudentiel et de résolution (ACPR). La prévention de ce risque impose la mise en application des dispositifs normatifs que sont les principes de cartographie des risques et de vigilance. Au-delà de la conformité aux principes normatifs (juridique), la compliance mobilise toutes les fonctions de l’entreprise au niveau opérationnel (management). Ces fonctions opérationnelles sont relatives aux procédures d’alerte, de signalements, de contrôles, de sanctions et constituent des dispositifs procéduraux. Pouvant être qualifiée en ce sens, de « fonction juridique et managériale », la compliance pousse à envisager autrement les régimes de responsabilités en milieu bancaire et financier, fondés sur des défaillances ''obligationnelles'', tant juridiques que managériales. Cela renvoie à l’épineuse obligation de connaissances en management requises pour les juristes et les autorités d’une part, et d'autre part, au caractère inextricable des fonctions juridiques et managériales (d’où les formations en droit des affaires et management).
Keywords: Compliance; Conformité; Droit bancaire; Droit financier

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

Analyse des risques juridiques à l’épreuve de la jurisprudence bancaire : cas des contentieux des voies d’exécution - Luaba Nkuna, Dieudonné (Revue de l'UKA, 2024)
Le domaine bancaire garantit le développement socio-économique des Etats à travers le financement des activités. Bien que les procédures demeurent complexes, elles sont soumises à une autorité de régulation tenant compte des risques et des responsabilités qui en découlent en vue de sécuriser les acteurs intervenants publics comme privés. The banking sector ensures socio-economic development of States, through the financing of activities although the procedures are complex, they are subject to regulatory authority that takes into account the associated risks and responsabilities, aiming to secure the interests of both public and private stakeholders.
Keywords: Banking operations; Banking risks; Bien meuble corporel; Bien meuble incorporel; Contentieux; Enforcement litigation; Execution; Intangible property; Opération bancaire; Precautionary seizure; Risque bancaire; Saisie; Saisie conservatoire; Tangible property; Voie d’exécution

Analyse de la solidité financière du secteur bancaire congolais de 2016 à 2021 - Mutombo Muimbayi, Florent (Revue de l'UKA, 2024)
La solidité bancaire traduit une situation dans laquelle le fonctionnement des différentes composantes du système bancaire et surtout leurs relations réciproques, sont assurées de manière saine et sans perturbations majeures. Cet article se propose d’analyser la solidité financière des banques commerciales en RDC. Les banques commerciales retenues dans le cadre de notre travail ont un ratio de liquidité conforme aux exigences de la BCC. La principale ressource des banques est constituée des dépôts à court terme.
Keywords: Liquidité; Rentabilité; Solidité bancaire; Solvabilité

Le prélèvement de l’impôt à l’épreuve de la digitalisation de l’économie - Moudjongue, Régine Laure (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
L’on convient au fait que le numérique produit des effets indésirés. Ce sentiment s’affirme au vu des difficultés auxquelles fait face le fisc, s’agissant de sa mission originelle de collecte de l’impôt. Ceci est la résultante d’un cadre juridique n’ayant pas tardé à devenir un espoir très vite déçu, à la faveur des transmutations subies, s’agissant de la détermination de l’établissement stable en fiscalité internationale. La conséquence en est que, toute tentative de saisie aux fins d’imposition par un Etat, se bute contre la difficulté de la localisation. De cette manière, ces multinationales et entreprises du numérique pourraient même à tort bénéficier d’une « double non-imposition ». De cette manière, la précarisation du prélèvement par le digital, est confortée par la pérennisation des risques subséquents à la digitalisation.
Keywords: Economie (digitalisation); Etat; Impôt; Territorialité

An Exploration of Selected Anti-Money Laundering Role-Players in Zimbabwe - Chitimira, Howard; Torerai, Elfas; Jana, Vimbai (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Anti-money laundering; Corruption; Financial crimes; Money laundering; Role-players

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

La transaction fiscale au Cameroun - Nanan Lekogmo, Hermann (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
La transaction existe en droit fiscal camerounais. Depuis une dizaine d’années, elle a connu des aménagements en vue de pacifier les relations entre les contribuables et l’administration fiscale et de réduire les restes à recouvrer (RAR). Il s’agit pour les pouvoirs publics d’encourager le recours à la transaction en matière fiscale. Ils ont permis, contrairement à ce qui a généralement cours dans d’autres matières et législations, que la transaction fiscale, au Cameroun, vise, plus qu’une modération des pénalités, une modération des impositions. Or les juridictions sont confrontées à un volume de dossiers à traiter supérieur à leur capacité. Malheureusement, le nombre de transactions reste encore limité. Et cela est dommage ! La transaction fait partie de la justice alternative et est plutôt utilisée en matière fiscale et contractuelle afin d’amener l’administration fiscale et le contribuable à trouver une solution rapide et moins onéreuse qu’un procès. Quelle appréciation peut être faite de la transaction fiscale en droit camerounais ? Il semble que sa nature et les caractères de son identification soient sources de problèmes. Peut-être aussi que la culture de la common law dont elle est sujette semble ne pas trouver un terreau fertile au Cameroun. Si l’instauration de la technique transactionnelle est aisée, son application demeure malaisée. Tax transaction exists in Cameroonian tax law. For about ten years, it has undergone adjustments with a view to pacifying relations between taxpayers and the tax administration and reducing outstanding amounts. The aim of the public authorities is to encourage the use of tax transactions. They have allowed, contrary to what is generally the case in other matters and legislation, that tax transactions in Cameroon aim, more than a moderation of penalties, a moderation of taxes. However, the courts are faced with a volume of cases to process that exceeds their capacity. Unfortunately, the number of transactions is still limited. And that is a shame! La transaction fait partie de la justice alternative et est plutôt utilisée en matière fiscale et contractuelle afin d’amener l’administration fiscale et le contribuable à trouver une solution rapide et moins onéreuse qu’un procès. Quelle appréciation peut être faite de la transaction fiscale en droit camerounais ? It seems that its nature and the characteristics of its identification are sources of problems. Perhaps also that the culture of common law to which it is subject does not seem to find fertile ground in Cameroon. If the establishment of the transactional technique is easy, its application remains difficult.
Keywords: Administration fiscale; Alternative justice; Alternative procedure; Contribuable; Justice alternative; Procédure alternative; Tax administration; Tax transaction; Taxpayer; Transaction fiscale

L’impact de l'adoption des IFRS sur la reconnaissance des pertes en temps opportun : Étude des sociétés cotées à la Bourse de Casablanca - El Idrissi Rioui, Samia; Touicher, Ouardia (Revue du contrôle, de la comptabilité et de l’audit, 2024)
Les Normes Internationales d’Information Financière (IFRS), émises par l'International Accounting Standards Board (IASB), deviennent de plus en plus le régime comptable privilégié parmi les entreprises des pays africains. La recherche sur l’effet de l’adoption des IFRS sur la qualité de l’information comptable dans les économies émergentes est encore rare. Par conséquent, cet article examine l’effet de l’adoption des IFRS sur la reconnaissance rapide des pertes, un indicateur de la qualité de l’information comptable. Les données financières de 34 entreprises cotées à la Bourse de Casablanca, couvrant la période de 2009 à 2019, sont analysées en utilisant une régression logistique dans le cadre d'une méthodologie économétrique quantitative. Deux panels équilibrés ont été constitués : l'un regroupant 14 entreprises ayant adopté les normes IFRS, et l'autre constitué de 20 entreprises suivant les normes comptables marocaines. Les résultats indiquent que la qualité des bénéfices (mesurée par la reconnaissance rapide des pertes) ne s’est pas améliorée après l’adoption des IFRS. Cette constatation implique que les régulateurs comptables et les organismes comptables des pays africains devraient encourager une application rigoureuse des IFRS en formant continuellement les comptables et auditeurs des entreprises cotées sur la mise en œuvre pratique de ces normes. Ces formations devraient être obligatoires et accessibles.
Keywords: Normes IFRS; Normes comptables marocaines; Reconnaissances rapide des pertes; Régression logistique

La loyauté en droit bancaire français - Ketcheuzeu Nana, Soline (Revue africaine de droit des affaires, 2024)
L’éthique des affaires est au cœur des préoccupations contemporaines. Elle varie selon les disciplines et selon les époques, mais certaines de ses valeurs telles l’intégrité, la loyauté sont considérées comme universelles. Dans le domaine commercial, l’éthique met l’accent sur la transparence, l’intégrité et la priorité donnée aux intérêts du client. L’éthique a progressivement imprégné le droit bancaire à travers l’une de ses déclinaisons, qu’est la loyauté. Cette dernière se manifeste à travers les obligations d’information, de conseil et de mise en garde adaptées à chaque situation. La loyauté s’exprime aussi à travers le secret professionnel. Elle vise donc la protection des clients. Cependant, la banque mérite de voir sa liberté contractuelle préservée tout en garantissant la sécurité des contrats bancaires. C’est cet équilibre difficile à trouver qui rend complexe l’application de la loyauté en droit bancaire. Ainsi, est-il important pour les banques de repenser des techniques permettant de rendre aisée, la pratique de la loyauté et d’améliorer la traçabilité du respect de l’obligation de loyauté.

The Impact of Financial Technology (Fin Tech) on Economic Growth: Evidence from Tanzania - Ngeze, Raphael Michael; Seif, Muba (African Journal of Economic and Business Research, 2024)
This research is driven by the rapid spread of fintech, and its contributions to Tanzania’s economic growth. This study uses quantitative quarterly time series data from Tanzania from 2008 to 2022. The Augmented Dicky Fuler (ADF) is used for the stationarity test, Johansen Cointegrations for the hypothesis and Cointegrations test, VAR and VECM for testing both short-run and long-run causality relationships, and Granger Causality for testing variable causality. The Ordinary Least Squares (OLS) regression model is used for parameter estimation, modelling and significance testing. The results show that the model is statistically significant and the independent variables in the regression accounted for around 89% of the overall variation in GDP. Fintech variable subscriptions have a positive impact on Tanzania’s economic growth. Thus, unemployment in Tanzania may be alleviated by the growing sector of financial technology. Fintech has involved many people from all over the world, including Tanzania, and has had a positive impact on both the national economy and per capita growth. Since TTCL and ZANTEL have witnessed a sharp decline in subscriptions, the government, as a fixed-wired broadband service provider, must take the necessary steps to increase the subscriptions.
Keywords: Economic growth; Financial Technology; M-Pesa; OLS; VAR; VECM

Effect of Taxpayer’s Attitudes on Tax Evasion among SMEs in Tanzania: A Case of Singida Tax Region - Chindengwike, James (African Journal of Economic and Business Research, 2024)
Paying taxes is essential to attaining sustainable economic growth and national economic independence, hence tax evasion is a concern for the economies of both wealthy and developing countries. This study examined how tax payer attitudes, particularly in the Singida Tax Region, affect tax evasion in Tanzanian Small and Medium-Sized Enterprises (SMEs). This study employed a survey method in which data collection comprised both qualitative and quantitative research approaches. A multiple regression model was employed in combination with a descriptive study approach to ascertain the outcomes. 145 SMEs taxpayers made up the study's as a sample size. The findings demonstrate that, among SMEs in the Singida Region, peer influence, tax awareness, tax morale, and tax evasion have statistically significant relationships with the taxpayer's attitude. This association is supported by statistics. Consequently, the United Republic of Tanzanian government needs to consider how taxpayer attitudes including peer pressure, tax knowledge, and morale affect tax evasion. This will contribute to the goal of reducing tax avoidance by all taxpayers, including SMEs Taxpayers.
Keywords: SMEs Taxpayers; Tanzania; Tax evasion; Taxpayer’s Attitudes

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

Les attributs de la procédure du contentieux fiscal en droit camerounais - Aba’A Andje, Gullit Jordy (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2024)
Keywords: Cameroun; Contentieux fiscal; Droit camerounais; Droit fiscal

Cross-border banking and bank stability: evidence from Sub-Saharan Africa - Gondwe, Sopani; Gwatidzo, Tendai; Mahonye, Nyasha (Journal of Banking Regulation, 2024)
Based on bank-level data from 29 Sub-Saharan African countries between 2005 and 2019, we apply panel fixed effects (FE) and two-step system GMM estimators to investigate whether increased cross-border banking affects domestic banking sector stability. We find significant evidence that the stability of banks in host countries declines with an increased presence of foreign banks—and the impact is more pronounced on banks that are small and less efficient. The stability impact of foreign banks is also found to depend on the quality of governance institutional factors in the host country. The findings shed some important insights on the downside of financial liberalisation policy in developing countries and the need for increased cross-border collaboration between home and host supervisory authorities in the SSA region—especially in jurisdictions where the foreign bank affiliates are systemically important. The domestic supervisory authorities thus need to effectively manage the inherent trade-off between reaping the benefits from international financial integration while effectively safeguarding domestic banking systems against cross-border contagion and fragility.
Keywords: Bank stability; Consolidated supervision; Cross-border banks; Home-host countries; Systemically important

Mutation Comptable PCGC/OHADA et qualité de l’information financière dans les entreprises publiques en RD Congo - Mposhi, François NGONGO; Chanhoun, Maxime José (Revue du contrôle, de la comptabilité et de l’audit, 2024)
L’Objectif de cette recherche est de comprendre la portée de la mutation comptable sur la production d’une information financière de qualité. Pour ce faire, nous avons opté pour une posture épistémologique interpretativiste adossée sur une démarche qualitative inductive. A l’aide d’un guide d’entretien, nous avons réalisé les entretiens semi-directifs auprès de dix (10) gestionnaires financiers des entreprises publiques en RD Congo. Les données collectées, ont fait l’objet d’une analyse de contenu et automatisée à l’aide du logiciel Nvivo 10. Il ressort de ces analyses que la mutation comptable PCGC/OHADA contribuerait à l’amélioration de la qualité de l’information financière dans les entreprises publiques en RD Congo. Ce qui interpelle les gestionnaires des entreprises publiques d’une part et le conseil permanent de la comptabilité au Congo d’autre part de veiller véritablement à l’applicabilité stricte du SYSCOHADA pour une information financière de qualité. Car la mutation comptable PCGC/OHADA s’implémente avec beaucoup des difficultés dans les entreprises publiques en RD Congo surtout lors des travaux d’inventaires.
Number: 2
Keywords: Entreprises Publiques; Mutation comptable; Qualité d’états financiers; SYSCOHADA

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

Evaluation of Revenue Effect from Tax Components and Economic Growth in Nigeria - Atuma, Emeka; David, Amarachi; Nwibo, Nneamaka; Nkwagu, Chibuike; Udenta, Blessing; Njim, Sunday; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
This research empirically examined the relationship between tax revenue and economic growth in Nigeria for the period 1994-2021. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates long-run and short-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between tax revenue and economic growth in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally showed that both company income tax and value added tax were statistically significant and positively related to economic growth in Nigeria in both shot-run and long-run periods; whereas personal income tax was statistically insignificant and positively related to economic growth in Nigeria in both short-run and long-run. Based on the findings, the study therefore recommended tax authorities responsible for tax administration should upgrade the tax database to capture all potential tax-payers in order to broaden tax income.
Keywords: Autoregressive Distributed Lag Mode; Economic growth; Nigeria; Tax Revenue

Re-Evaluation of the Effectiveness of Exchange Rate Depreciation on Import Demand in Nigeria - Atuma, Emeka; Ebuka, Bright; Nwibo, Fidelia; Nkwagu, Christain; Nancy, Udenta; Njim, Robert; Ogbonna, Nkemdirim; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
The study investigated the impact of exchange rate depreciation on import demand in Nigeria from 1986 to 2021. The data used was sourced from Central Bank of Nigeria. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates short-run and long-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between exchange rate depreciation and import demand in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally found that exchange rate depreciation is statistically not significant and negatively impacted on import demand in Nigeria in the short-run. However, in the long-run, exchange rate depreciation is negatively impacted to import demand and statistically significant. Causal relationship does exist between exchange rate depreciation and import demand in Nigeria with causation running from import demand to exchange rate depreciation. On the basis of the findings, the researcher made the following recommendations among others: Government should consider inward looking to strengthen the imports substitution policies that ensure massive production of goods and services.
Keywords: Autoregressive Distributed Lag; Exchange Rate Depreciation; Import Demand; Mode; Nigeria

Digitalization and Tax Administration in the Gambia - Ogbeta, Oghenekevwe; Ayeni, Oluwadare (African Journal of Politics and Administrative Studies, 2024)
This study extensively explored the potential of digitalization in The Gambia Revenue Authority's tax administration, amidst concerns over the practical application of digital tools and their underutilization, which have hindered the realization of improved revenue mobilization and efficient tax processes in The Gambia. The research, adopting a mixed method design, aimed to understand the intricate relationship between digitalization and tax administration in The Gambia. With specific objectives, including identifying driving factors, examining effects, and evaluating the correlation with GRA's performance, the study adopted quantitative and qualitative analyses. Similarly, the study population is two thousand, one hundred and eighty-eight (2188). Using Krejcie and Morgan (1970) formula, out of 2188 population of the study, three hundred and twenty seven (327) were selected as the sample size. This encompassed individuals drawn from the Ministry of Finance and Economic Affairs, GRA staff, and corporate taxpayers using a stratified and proportionate-to-size sampling approach. Hypotheses analysis revealed a statistically significant and positive effect of digitalization on tax administration, indicating improved efficiency and GRA effectiveness. Also, Spearman's rank-order correlation affirmed a positive relationship between digitalization and tax administration. Furthermore, qualitative insights from stakeholder interviews highlighted drivers such as international financial body stipulations, modernization imperatives, trust-building, accurate record-keeping, and alignment with global standards. Recommendations include training programs for GRA staff, public awareness campaigns, and enhancing user experiences for e-payment systems, among others.
Keywords: Digitalization; Tax Administration; Tax Compliance; Tax Evasion; Taxation

The Relevance of IFRS Accounting Information: Evidence from a Pure IFRS Environment - Abu Alia, Muiz; Amarneh, Khairieh; Abdeljawad, Islam (An-Najah University Journal for Research - B (Humanities), 2024)
The International Financial Reporting Standards (IFRS) are supposed to raise the value relevance of accounting information and thus ensure its usefulness for users. Most of the studies on the relevance of IFRS-based accounting information were conducted in countries that had previous accounting standards before the adoption of IFRS. However, the relevance of accounting information is influenced by the accounting traditions inherited from previous practices. This study provides distinctive evidence on the relevance of IFRS accounting information by examining the association between accounting information prepared by Palestinian companies and share prices. Palestine represents a pure IFRS environment since IFRS is its first financial reporting framework. The study estimates the impact of accounting information, including book value of equity per share, earnings per share, and operating cash flow per share, on the market value of the share. Totally, the results show that the accounting numbers prepared by Palestinian companies are relevant. Precisely, earnings per share and book value of equity per share are the important variables in determining the share market value. Notwithstanding, no significant impact of operating cash flow per share has been observed. Moreover, evidence supporting the existence of conformity and predictive relevance is obtained, but the overall predictive relevance is higher. To enhance the relevance of IFRS information, this paper recommends local regulators and policymakers to work on improving the readiness of the Palestinian environment to fully benefit from the adoption of IFRS. On the other hand, the International Accounting Standards Board should adequately consider the circumstances prevailing in underdeveloped countries when issuing its standards. For future research, larger samples from several countries with different prevailing factors should provide insights into the mechanisms of the relationship between book and market values.
Keywords: Conformity Value; IFRS; Predictive Value; The Palestine Exchange; Value Relevance

L'audit interne et la gouvernance a l’ère de la transformation digitale - Boumeska, Mustapha; Allouli, Nadia (Revue des Études Multidisciplinaires en Sciences Économiques et Sociales, 2024)
Over the last decade, corporate governance has become crucial to solving agency problems and achieving objectives for organisational sustainability . At the heart of this governance, internal audit is recognised as an essential control mechanism for improving business performance. In the face of digitalisation, internal audit must adapt, presenting new challenges and opportunities. This paper explores the impact of digitalisation on the effectiveness of internal audit as a governance mechanism, developing a conceptual model through an extensive literature review.
Keywords: Audit interne; Digitalisation; Digitalization; Efficacité; Efficiency; Gouvernance; Governance; Internal audit

La titrisation - Chambon, Benoît (Université Paris-Est, 2024)
Près de dix ans après la crise des subprimes les opérations de titrisation connaissent un nouvel essor. Ce dernier fait suite notamment à des travaux de la Commission européenne qui, dès 2015, a fait part de son intention de réviser le corpus applicable à ces transactions dans la cadre de son plan d'action pour la construction de l'Union des Marchés de Capitaux. C'est ainsi qu'en 2017 un règlement portant sur les opérations simples transparentes et standardisées a été publié au journal officiel de l'Union européenne. Ce texte a vocation à être complété par un autre règlement relatif à l'opposabilité des cessions de créances. Au niveau international les règles de rétention de fonds propres applicables visant les expositions de titrisations ont été amendées afin de mieux prendre en compte les risques y attachés. En France le régime applicable à la gestion d'actif et au financement par la dette a été remanié. On peut se demander comment ces évolutions normatives ont influencé la manière dont les risques systémiques et idiosyncratiques sont créés, transférés et couverts dans le cadre des opérations de titrisation. Almost ten years after the subprime crisis, securitization transactions are experiencing a new boom. The latter follows notably work of the European Commission which, as early as 2015, announced its intention to revise the legal framework applicable to these transactions as part of its action plan for the Capital Market Union. This led in 2017 to the publication in the Official Journal of the European Union of a regulation on simple, transparent and standardized transactions. This text is intended to be supplemented by another regulation on the enforceability of assignments of receivables. At the international level, the capital retention rules applicable to securitization exposures have been amended to take better account of the risks associated to said exposures. In France, the legal framework applicable to asset management and debt financing has been revised. One can wonder whether the normative developments have influenced the way systemic and idiosyncratic risks are created, transferred and hedged in securitization transactions.
Keywords: Idiosyncratic risks; Risque idiosyncratique; Risque systémique; Securitization; Systemic risks; Titrisation

La gestion des risques inhérents au marché financier - Salim, Medromi; Zakariyae, El Adlouni (African Scientific Journal, 2024)
Aujourd’hui, le marché financier est considéré comme le bouc émissaire du monde des affaires puisqu’il est toujours culpabilisé et pointé de doigt comme la source du malaise et la cause directe de l’effondrement des systèmes économiques. La finalité des marchés financiers est tragiquement déviée dans la perception du grand public. Ce marché qui est censé être l’emblème d’épanouissement, d’entraide et de coopération, est devenu un lieu où règne la mauvaise foi et les manœuvres frauduleuses. Cette stigmatisation n’est pas due au hasard. En effet, le délit d’initié, la publication de comptes inexacts, les crises financières etc. constituent quelques-unes des questions qui ont alimenté le débat actuel autour de crépuscule de la régulation massive du marché financier. La gestion des risques liés aux marchés financiers est devenue une préoccupation majeure afin de se prémunir contre les risques financiers, réputationnels et opérationnels. Today, the financial market is regarded as the scapegoat of the business world, since it is always blamed and pointed at as the source of malaise and the direct cause of the collapse of economic systems. The purpose of financial markets is tragically skewed in the public perception. This market, which is supposed to be the emblem of self-fulfillment, mutual aid and cooperation, has become a place where bad faith and fraudulent maneuvers reign supreme. This stigmatization is no accident. Indeed, insider trading, the publication of inaccurate accounts, financial crises etc. are just some of the issues that have fueled the current debate surrounding the twilight of massive financial market regulation. Financial market risk management has become a major preoccupation in order to guard against financial, reputational and operational risks.
Keywords: Business ethics; Financial markets; Gestion des risques; Marché financier; Moralisation des affaires; Risk management

Plataformas de cuidados a mayores - Egea, Mercedes Navarro (Comares, 2024)
La esperanza de vida en nuestro país es una de las más altas del mundo. Se estima que en treinta años la tasa de dependencia de personas mayores con necesidades de cuidados en la UE alcanzará el sesenta por ciento.Este estudio aborda las cuestiones jurídico-tributarias que plantean las "plataformas digitales de cuidados" que operan en el ámbito nacional y que tienen por destinatarios a los mayores dependientes.Estas fórmulas empresariales, además del potencial que tienen para la generación de empleo y la innovación, contribuyen a mejorar la calidad del envejecimiento, pues la oferta de servicios (cuidados de larga duración, por períodos cortos o por horas) se adapta con mayor flexibilidad a las necesidades individuales de los mayores, preservando su independencia y autonomía en todo el ciclo de la vejez. Unos cuidados que han de ser de calidad, asequibles y accesibles.Interesa, por tanto, adentrarse en los aspectos más significativos de lo que podría ser una fiscalidad de plataformas, focalizada en aquellas que actúan como intermediarias conectando a vendedores o prestadores de servicios con usuarios, y que comprende medidas concretas en el IS y el IVA, así como nuevas obligaciones de suministro de información (DAC 7). En esta categoría de plataformas se reconocen la mayoría de las que operan en el ámbito de los cuidados. Y, puesto que se trata de un sector empresarial en crecimiento, presenta especial interés conocer en qué medida se pueden aprovechar las medidas fiscales introducidas para el fomento de las empresas emergentes (startups), así como para la atracción de inversión privada y la captación de talento extranjero.
https://orcid.org/0000-0001-7441-209X
Keywords: cuidadados; jurídico; mayores; plataformas; tributario

Evaluating bank technical efficiency in SADC region - Abel, Sanderson; Mukarati, Julius; Manenge, Robson; Le Roux, Pierre (Heliyon, 2024)
Efficiency is generally defined as the capacity to deliver desirable results with little effort or input. A bank cannot afford to allocate limited resources at random in a competitive market. Only once the efficiency factors have been identified can resources be allocated in a conscious and effective manner. The study investigates the determinants of technical efficiency of banks in the SADC region. The study is significant in the SADC region as the block is trying to create a robust and stable banking system. This is driven by the desire to stay away from the current global financial system volatility and the region is working to develop an integrated banking system. The results show that the banks are relatively inefficient with the level of inefficiency around 40 percent. The efficiency of the banks is determined by the level of capitalisation, size of the bank, research costs and automation of the banks. The results of the study imply that that there is great scope for the banks in the SADC region to increase their efficiency. Improved efficiency will ensure banks provide services at a lower cost to clients. The study recommends adequately capitalizing banks, increasing the asset base of the banks, investing in research and the automation of the banking systems.
Keywords: Banks; Capitalisation; Data envelopment analysis; Technical efficiency; Tobit

Les jetons participatifs : contribution au droit de la finance participative - Aliyev, Novruz (Université de Rennes, 2024)
Au-delà de l’aspect numérique, Satoshi, fondateur anonyme du bitcoin, évoque l’organisation de « Pair à Pair » (P2P). Elle correspond à l’algorithmique répartie sur laquelle le registre décentralisé de ces nouveaux actifs se fonde. Mais le Règlement MiCA exclut la finance décentralisée et ne donne aucune définition satisfaisante des crypto-actifs. On étend cette observation aux actifs numériques, insuffisamment cernés en droit français. L’analyse de l’organisation P2P s’impose. On a identifié chez certains jetons une organisation participative, distincte des groupements et des contrats-coopération. Elle se caractérise par un degré et une forme d’indépendance nouvelle ainsi que par une socialité orientée vers un objet de nature impersonnelle, ouverte vers l’extérieur et sans structure (ni groupements ni contrats). Elle façonne ainsi la structure d’émission et la forme représentative et négociable de ces jetons. Ils sont des écrits représentant un bien ou un service et non un droit à l’encontre d’une personne émettrice. Ils sont émis dans une organisation participative : sans partage de pertes, de bénéfices, de chiffres d’affaires ou d’autres fruits. Leur qualification civiliste est le produit et non le fruit, contrairement aux titres financiers. L’organisation participative, elle, s’analyse comme un système, une nouvelle catégorie juridique que l’ordre juridique peut accueillir. L’ouverture du système vers l’extérieur nécessite la négociabilité des jetons. Elle concourt à la financiarisation de l’économie réelle. Comme la structure d’émission de ces jetons participatifs, leur infrastructure polycentrique de négociation appelle une régulation par l’organisation. Ces jetons sont aussi hybrides parce que participatifs et monétaires, et en tant que tels peuvent être considérés comme des unités de financement ; nouvelle définition de la monnaie que l’on propose, pour ne pas la réduire à sa seule fonction de paiement. Les jetons participatifs perturbent la summa divisio entre la monnaie et les instruments financiers ainsi que le concept même de droit subjectif.
Keywords: Crypto; Crypto-Actifs; Cryptomonnaie; Decentralised finance; Distributed ledger technology.; Finance décentralisée; Financement participatif; Jeton; Jetons-monnaie; Monnaie; Registre réparti; System; Système; Token

Corporate Income Tax (CIT) and Capital - Agossadou, Stanislas Théodule Médard Dèwanou Comlan (International Journal of Accounting, Finance, Auditing, Management and Economics, 2024)
This research consists of verifying whether CIT has an effect on capital given the financing risk incurred. A review of several capital theories has shown that CIT is one of the main determinants of a firm's capital structure. The inclusion of CIT in capital structure models continues to divide the world of corporate finance. Debt interest deduction in computing CIT reinforces the controversy over the question of the capital structure that optimizes the tax savings provided by this deduction. The consequence is the existence of two opposing groups on the optimum capital structure: on the one hand, the group of those who believe that there is one and only one optimal capital structure, and on the other, the group of those who reject out of hand any possibility of an optimal capital structure. The sample starts with a case study of two hypothetical identical firms, one indebted and the other non-indebted, with the same profitable investment project over a period of time, and ends with 101 pairs of identical firms belonging to different classes of financing risk. The hypothesis of non-gratuity of cost and income is used, and capital markets are assumed to be pure and perfect. The results confirm that CIT has no effect on the structure, value, cost and return of capital for a given financing risk, and reveal the existence of a third source of financing called "public capital", whose cost is the corporate capital tax rate (CCTR). There is no longer any question of thinking about the optimum capital structure, which is a pure financial illusion. This paper is one of the first to show that CIT does not affect capital, and to propose a model that explains capital structure behavior in the presence of CIT. Paper type: Empirical Research Stanislas Théodule Médard Dèwanou Comlan AGOSSADOU, (Researcher) Laboratory for Research on Performance and Development of Organizations (LARPEDO) Faculty of Economics and Management (FASEG) University of Abomey-Calavi (UAC) - Benin,
Keywords: Capital structure; Financial integration of corporate tax; Firm value; Return on investment; Weighted average cost of capital (WACC)

Les financements sur une blockchain : nouveaux défis du droit financier à l'aune de la finance décentralisée - Bonnet, Joris (Université de Strasbourg, 2024)
Alors que la finance traditionnelle peine à se renouveler, les nouveaux applicatifs de finance décentralisée proposent des services financiers basés sur des protocoles innovants, codés et entièrement gérés par les utilisateurs. Les classifications historiques de la finance sont largement inefficaces et des catégories telles que celle des instruments financiers ne permettent pas de construire un encadrement pertinent. Celles-ci doivent être dépassées pour pouvoir encadrer de façon plus inclusive tous les actifs décentralisés. La communication financière est rendue désuète et nécessite une refonte pour prendre en compte les nouvelles motivations des investisseurs et les impératifs environnementaux. Traditional finance is struggling to renew, new decentralized finance applications offer financial services based on coded protocols entirely managed by users. Historical classifications of finance are largely ineffective and categories such as financial instruments do not allow to construct a relevant framework. These must be overcome to be able to regulate all decentralized assets in a more inclusive manner. Financial communication has become obsolete and requires an overhaul to consider the new motivations of investors and environmental imperatives.
Keywords: Actif décentralisé; Asset; Blockchain; Chaine de blocs; Contract; Contrat; Crypto money; Crypto monnaie; Cryptoactif; Cryptomonnaie; DAO; DEEP; DLT; DeFi; Decentralized asset; Decentralized finance; Droit des affaires; Droit financier; Finance décentralisée; Finances; Financial law; Fundraising; ICO; Jeton; Levée de fonds; STO; Security; Token

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

A bibliometric review of IFRS adoption and compliance research in Africa - Effah, Nana Adwoa Anokye (Journal of Business and Socio-economic Development, 2024)
Purpose This article aims to identify and review existing studies on the adoption and compliance of Internat ional Financial Reporting Standards (IFRS) in Africa. Design/methodology/approach The methodology involves a sole focus on studies conducted with an African sample, using a bibliometric method and data from the Web of Science (WoS) database. Visualizations from VOSViewer and Biblioshiny software are employed to identify the dominant authors, journals and countries contributing to research in the region. Findings The findings reveal existing collaborations among authors in the field. However, the study emphasizes the need for additional research to enhance the intellectual structure of the research domain, as the majority of related documents are concentrated within twenty articles with at least one citation. Practical implications The practical implications underscore the importance of collaboration in practice, emphasizing the need for cooperation among corporations, experts and regulatory agencies involved in IFRS adoption and compliance in Africa. By fostering collaborative efforts and knowledge-sharing among corporations, experts and regulatory agencies, practitioners can enhance their understanding, streamline implementation processes and improve compliance methods. Originality/value This review is one of the few to explicitly conduct a bibliometric review of IFRS adoption and compliance studies in Africa, providing a foundation for future research to determine the current direction of IFRS studies in this region.
Keywords: Africa; IFRS adoption; IFRS compliance; Web of science database

Tax Behavior and Financing Behavior of Corporate Managers: Case of Banks and Decentralized Financial Systems (DFSs) in Benin - Agossadou, Stanislas T. Médard D. C. (Journal of Economics, Finance and Management, 2024)
This paper aims to analyzing the influence of tax behavior on financing (financial leverage) behavior of corporate managers. The paper applies the generalized method of moments (GMM) to dynamic panel data. The sample used covers 21 firms, i.e. 11 banks for the period from 2011 to 2020 and 10 DFSs for the period from 2016 to 2021. It turns out that financial leverage behavior is influenced more positively by corporate income tax (CIT), then by dividends (DIVIDEND); and negatively by interest on debt (INTEREST), by cash flow (CASH_FLOW) and by past financial leverage (LEVERAGE(‑1)). This paper is one of the first to extend the literature by identifying the main determinants of financing behavior, notably the positive effect of corporate income tax (CIT).
Keywords: Corporate income tax behavior; Corporate income tax savings; Financial objectives; Leverage behavior; Tax objectives

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 1, Daňové právo v proměnách času - Czudek, Damian (Masarykova Univerzita, 2024)
Sborník příspěvků zabývajících se aplikací a interpretací daňového práva, tvorby daňového práva ve smyslu jeho stability a předvídatelnosti, jak z pohledu daňových subjektů (zejména podnikatelů, ale i fyzických osob nepodnikatelů, ale také státu a jemu podřízených organizací (z pohledu předvídatelnosti příjmů do veřejných rozpočtů a stability veřejných financí).
Keywords: Droit fiscal; E-knihy; Elektronické knihy; Fiscalité; Knihy; Tax law; Čítárna

La relación cooperativa entre las grandes empresas y la Administración Tributaria - Guerrero Pappalardo, Alba Mª (Universidad de Sevilla, 2024)

Girişim şirketlerinin finansmanının hukuki çerçevesi - Günay, Yavuz Selim (Ankara Hacı Bayram Veli Üniversitesi, 2024)
Girişimcilik hem ülkemiz hem de dünya ekonomisi için, ekonomik gelişme sağlaması, istihdamı artırması gibi bir çok sebeple, son derece önemlidir. Girişimcilik ekosisteminde uygulanan finansman yöntemleri, sözleşmeler, hukuk kuralları gibi unsurlar dinamik ve esnek yapısı dolayısıyla geleneksel yöntem ve kurallardan ayrışmaktadır. Girişimcilerin banka kredisi gibi geleneksel finansman yöntemlerine erişememesi dolayısıyla kitle fonlaması, gölge pay, aile ve arkadaşlar, girişim sermayesi ve melek yatırımcı gibi yenilikçi finansman yöntemleri ortaya çıkmıştır. Bu finansman yöntemlerinden en yaygın ve yapısal olarak kullanılanı girişim sermayesidir. Girişim sermayesi, çeşitli fonlar ve şirketlerden toplanan kaynakların, büyüme potansiyeli gösteren ve gelecek vadeden girişim şirketlerine, pay karşılığı yatırım yapılmasını ifade etmektedir. Girişim şirketleri bakımından finansman haricinde de bir çok faydası bulunan girişim sermayesi, Türk hukukunda SPK tarafından GSYO ve GSYF yapıları altında düzenlenmiştir. Girişim sermayesi uygulamasında en çok sorun teşkil eden hususlardan biri ise girişimci ile yatırımcı ilişkileridir. Girişimci ile yatırımcı arasında hem yatırım öncesinde hem de yatırım sonrasında bilgi asimetrisinin ve menfaat farklılaşmasının söz konusu olması, girişimci ile yatırımcı arasında yönetilmesi zorunlu hale gelen bir menfaat çatışması yaratmaktadır. Bu menfaat çatışmasının olumsuz etkilerinin en aza indirilememesi ve yönetilememesi sadece girişim şirketi için değil ülke ekonomisi için de olumsuz sonuçlar doğuracaktır. Girişimci ile yatırımcı arasındaki bu menfaat çatışmasının pay devir sözleşmesi, pay sahipleri sözleşmesi, paya dönüştürülebilir borçlanma araçları gibi çeşitli sözleşmesel düzenlemelerle yönetilmesi mümkündür. Ayrıca, girişimci ile yatırımcının kendi aralarında gerçekleştirecekleri sözleşmesel kurumsal yönetim düzenlemeleri de girişimci ile yatırımcı arasındaki menfaat çatışmasının yönetilmesinde etkili olacaktır. Entrepreneurship is important for both our country and the world economy for many reasons such as providing economic development and increasing employment. Elements such as financing methods, contracts and legal rules applied in the entrepreneurship ecosystem differ from traditional methods and rules due to their dynamic and flexible structure. Since entrepreneurs cannot access traditional financing methods such as bank loans, innovative financing methods such as crowdfunding, phantom share, venture capital and angel investors have emerged. The most widely and structurally used of these financing methods is venture capital. Venture capital refers to the investment of resources collected from various funds and companies in return for shares in promising venture companies with growth potential. Venture capital, which has many benefits other than financing for venture companies, is regulated by the CMB under the structures of GSYO and GSYF in Turkish law. One of the most problematic issues in venture capital implementation is the relationship between the entrepreneur and the investor. The fact that there is information asymmetry and interest differentiation between the entrepreneur and the investor both before and after the investment creates a conflict of interest between the entrepreneur and the investor that must be managed. Failure to minimize and manage the negative effects of this conflict of interest will have negative consequences not only for the venture firm but also for the national economy. It is possible to manage this conflict of interest between the entrepreneur and the investor through various contractual arrangements such as share transfer agreements, shareholders' agreements, convertible debt instruments. In addition, contractual corporate governance arrangements between the entrepreneur and the investor will also be effective in managing the conflict of interest between the entrepreneur and the investor.

Combinaison des apports des cadres conceptuels américain, français et IASB au système comptable OHADA - Nkangi Mbadika, Olivier; Makwala Yanukwa, Octave; Pindi Mayila, Serge; Mantempa Nzinunu, Jocelyn (Mouvements et enjeux sociaux, 2024)
Le Système Comptable OHADA est préconisé afin de répondre aux attentes et satisfaire aux besoins des entités évoluant dans les Etats-parties et des utilisateurs de leurs états financiers annuels. L’analyse faite dans ce papier de recherche consiste à montrer que le Système Comptable OHADA apparaît comme une combinaison des apports positifs du plan comptable général français, des normes internationales (IAS/IFRS) et des normes américaines (US GAAP). Ainsi, il est souvent présenté comme un référentiel qui a connu des avancées notables par rapport aux anciens référentiels comptables africains (Plan comptable général congolais, Plan OCAM, SYSCOA, etc.) pour avoir bénéficié des apports comptables des modèles susmentionnés. Ceci traduit son caractère dynamique au regard de l’évolution de la vie des affaires tant au niveau régional qu’à l’échelle mondiale. La prise en compte des apports positifs des cadres conceptuels dominants a le mérite d’anticiper l’unification du langage comptable dans le monde dans un contexte caractérisé par la mondialisation des économies.
Keywords: Accountability; Comptabilité; Framework; IASB; Norme comptable; Système comptable

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
https://hdl.handle.net/1828/20312
Keywords: Digital economy; International taxation; OECD; Tax

Vergi ceza hukukunda muhasebe hileleri ve hukuki sonuçları - Parlak, Mehmet Ali (İstanbul Üniversitesi, 2024)
Bu çalışma, Vergi Usul Kanunu'nun 359. maddesinin (a) fıkrasının birinci bendinde düzenlenen "hesap ve muhasebe hileleri yapmak" hükmünün, suç ve cezada kanunilik ilkesini karşılayıp karşılamadığı temelinde suçun kapsamı, özellikleri, unsurları ve sonuçlarının doktrin, içtihat ve mevzuat hükümleri ışığında incelenmesini konu edinmektedir. Muhasebe hilesi geniş anlamda, işletmelerde meydana gelen değer hareketlerinin belgelendirilmesinden faaliyet sonuçlarının raporlanmasına kadar olan süreçte, işlemlerin gerçeği yansıtmayacak şekilde değiştirilmesidir. Bu itibarla muhasebe hilesi muhasebe, denetim, ticaret hukuku gibi farklı disiplinlerin inceleme alanlarına giren genel bir kavramdır. Bunun yanında vergi kaçakçılık fiili olarak vergi hukuku doktrininde de önemli bir yer tutan tartışma konusudur. Vergi hukukundaki tartışmalar, hükümdeki muhasebe hilesi kavramının tanımsız, torba suç, kaçakçılık suçlarının en geneli ve işlevsiz bir suç olup olmadığına yöneliktir. Bu tartışmaların kaynağı kanun koyucunun maddede suçun kurucu unsurlarına yer vermemesi ve herhangi bir soyut tipe dair belirleme yapmamasıdır. Bu bakımdan çalışmada farklı disiplinler bakımından muhasebe hilesinin kapsamı, yöntemleri, sebep ve sonuçları karşılaştırmalı olarak ele alınmış; tümden gelim yöntemiyle vergi hukukundaki muhasebe hilesi suçunun içeriği tespit edilmeye çalışılmıştır. Çalışmada ulaşılan sonuç; "hesap ve muhasebe hileleri yapmak" hükmünün suçu tanımlamak bakımından "belirlilik" ilkesini karşılamadığıdır. Dolayısıyla adli ve idari mercilerin subjektif değerlendirmelerinin önüne geçilmesi, hukuki kesinlik ve eşitliğin temini, hukuki güvencenin sağlanabilmesi ve normun işlerlik kazanabilmesi için bir düzenlemeye ihtiyaç duyulmaktadır. This study examines the scope, characteristics, elements and consequences of the crime in the light of doctrine, jurisprudence and legislation on the basis of whether the provision of "committing accounting and accounting fraud" regulated in the first paragraph of paragraph (a) of Article 359 of the Tax Procedure Law meets the principle of legality in crime and punishment. It is about to be examined. Accounting fraud, in broad terms, is changing transactions in a way that does not reflect reality, from the documentation of value movements in businesses to the reporting of activity results. In this respect, accounting fraud is a general concept that falls into the fields of investigation of different disciplines such as accounting, auditing and commercial law. Discussions in tax law are about whether the concept of accounting fraud in the provision is undefined, an omnibus crime, the most general of smuggling crimes, and whether it is a dysfunctional crime. The source of these discussions is that the legislator does not include the constitutive elements of the crime in the article and does not specify any abstract type. In this regard, the scope, methods, causes and consequences of accounting fraud in terms of different disciplines were discussed comparatively in the study; The content of the crime of accounting fraud in tax law has been tried to be determined by deductive method. The result reached in the study; The provision of "committing account and accounting fraud" does not meet the principle of "specificity" in terms of defining the crime. Therefore, a regulation is needed to prevent subjective evaluations of judicial and administrative authorities, to ensure legal certainty and equality, to provide legal assurance and to make the norm functional.
Tez N°857786
Keywords: Accounting; Finance; Fraud; Fraude fiscale; Maliye; Tax fraud

Desenvolvimento Profissional e Afiliação à Ordem dos Contabilistas na Guiné-Bissau: Motivações e Desafios - Sambú, Luís (Instituto Politécnico de Santarém, 2024)
Objetivo: Esta pesquisa tem como objetivo compreender as motivações que levam os contabilistas acreditados da Guiné-Bissau a se afiliarem à Ordem dos Contabilistas, bem como identificar e compreender as barreiras enfrentadas pelos contabilistas que não são afiliados, com o intuito de propor estratégias que incentivem a afiliação e promovam o desenvolvimento profissional do contabilista no país. Método: Foi utilizada uma abordagem qualitativa. Entrevistas semiestruturadas foram conduzidas com contabilistas acreditados e não acreditados para explorar suas percepções e experiências. A análise de conteúdo foi empregada para interpretar os dados, destacando as motivações para a afiliação e as barreiras enfrentadas pelos não afiliados. Resultado: Os resultados demonstram que os contabilistas acreditados entrevistados não consideram a existência de barreiras. Já os contabilistas não inscritos na ordem mostram-se motivados para se inscreverem na ordem, uma vez que isso lhes permite ter acesso à formação contínua e alcançar estatuto como profissionais de qualidade. Contribuição: A contribuição desta pesquisa consiste em enriquecer o estudo da profissionalização da contabilidade. Igualmente, irá contribuir para uma melhor compreensão do estado da profissão contabilística na Guiné-Bissau. Além disso, dada a inexistência de literatura sobre o tema, este estudo irá ajudar a aumentar o conhecimento das difíceis situações com que os contabilistas acreditados e não acreditados se deparam no exercício das suas funções na Guiné-Bissau.
Keywords: Afiliação; Desafios; Desenvolvimento profissional; Guiné-Bissau; Motivaçoes; Ordem dos contabilistas

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců.. Část 8, Regulace, dohled a inovace na finančních trzích a v bankovním sektoru - Schweigl, Johan; Holubářová, Nikol (Masarykova Univerzita, 2024)
- Právní aspekty zavedení Centrální bankovní digitální měny (CBDC) v Evropě: výzvy a; - Novinky ve světě fintech; - Riziko praní špinavých peněz v kryptoprostoru; - Povolenie na poskytovanie služieb kryptoaktív podľa nariadenia MiCA – vybrané regulačné aspekty v podmienkach Slovenskej republiky; - Nekalé obchodní praktiky a nekalosoutěžní jednání v bankovním marketingu; - Finančné inovácie ako determinant súčasnej a anticipovanej regulácie na finančnom trhu v kontexte neoprávneného podnikania; Outsourcing marketingových aktivit v bankovním sektoru; Několik poznámek k dlouhodobému investičnímu produktu.

L'application du droit des obligations en droit fiscal : (contribution à l'étude de l'autonomie et du réalisme du droit fiscal) - Bretaudeau, Valérie (Université Paris 1, 2023)
Le postulat est l’existence d’un principe d’application du droit des obligations en droit fiscal. Puis, la réflexion a porté sur la consécration du principe, soit son existence et son expansion. Concernant son existence, l’origine du principe impliquait de revenir brièvement sur les controverses relatives à l’autonomie et au réalisme du droit fiscal et d’affirmer, à la suite de la doctrine, que ni l’une, ni l’autre n’existait. En effet, le droit fiscal est un droit de superposition. Ainsi, sauf exceptions, il est soumis aux autres disciplines juridiques dont le droit des obligations. Il serait aussi d’interprétation stricte. La thèse mettra en évidence que l’éventail des procédés d’interprétation est large et que le droit fiscal, n’est pas seulement interprété de manière stricte. En outre, une interprétation large du droit fiscal n’exclut pas l’application du droit des obligations, notamment. Quant aux manifestations du principe de l’application du droit des obligations en droit fiscal, et grâce à des exemples, elles se matérialisent par les renvois au droit civil aussi bien à ses définitions qu’à ses qualifications. S’agissant de l’expansion du principe en question, l’accent est mis sur ses deux origines, législative et jurisprudentielle. Là encore des exemples choisis illustreront les propos. Ensuite, la thèse s’intéresse aux fondements des exceptions à l’application du droit des obligations en droit fiscal. Il y a les règles spéciales de la fiscalité, d’une part. Il y a lutte contre la fraude et l’évasion fiscale, d’autre part.
Keywords: Droit des obligations; Droit fiscal; Impôt; Obligations (droit)

La régulation du lobbying en droit économique - Mbaka, Axel (Aix-Marseille Université, 2023)
La question de l’encadrement juridique du lobbying a longtemps été oubliée par le droit Français. Pendant un temps, seuls le droit pénal et l’autorégulation formaient les contours du faisable. Inspirée d’exemples étrangers, la loi n°2016-1691 du 9 décembre 2016 relative à la transparence, à la lutte contre la corruption et à la modernisation de la vie économique, dite « loi Sapin 2 », a renversé le paradigme en créant des obligations de transparence pour les lobbyistes et les pouvoirs publics. Pour contrôler le respect de ces obligations, la loi a aussi créé la Haute Autorité pour la Transparence de la Vie Publique (HATVP). Toutefois, à peine née, la régulation du lobbying est confrontée aux défis contemporains du droit économique. À l’heure des autorités de régulation, de la privatisation du pouvoir normatif et de la résurgence des nations, que peut encore la régulation du lobbying ?
Keywords: Contrôle de l'État; Droit économique; Economic law; Interest representatives; Lobbying; Loi Sapin 2; Lutte contre la corruption; Regulation; Représentants d'intérêts; Régulation; Sapin 2 law; Transparence; Vie publique

Le Conseil d'État et la régulation des marchés financiers - Sevagamy, Romuald (Université de Montpellier, 2023)
La contribution à la régulation des marchés financiers par différents acteurs tels que l’Autorité des marchés financiers (AMF), les institutions européennes ou le juge judiciaire, a fait l’objet d’importants travaux. Toutefois, la juridiction administrative n’a pas reçu les mêmes honneurs. Dans le cadre du contentieux de la régulation des marchés financiers, la compétence du Conseil d’État a été davantage décriée que saluée. En effet, d’aucuns ont pu soutenir que les difficultés résultant du dualisme juridictionnel en matière financière, justifieraient la suppression de la compétence de l’ordre administratif. La compétence unique de l’ordre judiciaire pour connaître des décisions individuelles de l’AMF, telles que les sanctions, étant présentée comme un remède à la complexité du contentieux de la régulation financière. Si bien que l’on est amené à se demander si la présence du juge administratif dans cette matière est véritablement indispensable. En d’autres termes, se pose la question de savoir si le Conseil d’État est nécessaire à la régulation des marchés financiers. La présente thèse a pour ambition d’apporter une réponse résolument affirmative. Depuis la création de l’AMF, la compétence en premier et dernier ressort du juge administratif a été étendue de manière importante. Ce dernier étant désormais compétent pour connaître des recours contre les décisions individuelles, prises à l’encontre des professionnels des marchés. La jurisprudence administrative constitue également une source d’enrichissement significative du droit de la régulation financière. En effet, tant les garanties procédurales que les règles de fond, qui encadrent le pouvoir de sanction de l’AMF, ont été consolidées par le juge administratif. Ainsi, le Conseil d’État s’est affirmé en tant qu’acteur incontournable de la régulation des marchés financiers.
Keywords: Administrative litigation; Administrative penalties; Autorité des marchés financiers; Contentieux administratif; Dualisme juridictionnel; Financial markets regulation; Jurisdictional dualism; Office du juge; Office of the judge; Places financières; Régulation des marchés financiers; Sanctions administratives

La subjectivisation du droit fiscal camerounais - Agbele Ntsengue, Sébastien (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Le droit fiscal camerounais n’est plus ce qu’il était il y a plus d’une décennie, à savoir un droit essentiellement objectif et qui était structuré autour de l’idéologie de l’intérêt général et qui mettait un accent tout particulier sur la protection de la légalité objective. Sous l’effet conjugué des mutations sociales, de l’idéologie droit-de-l’hommiste véhiculée par la mondialisation et de la crise de l’intérêt général, le droit fiscal camerounais tend, de plus en plus, par un processus de « subjectivisation », à prendre en compte de façon accrue, les intérêts particuliers, parfois, au détriment de l’intérêt général. Il tend ainsi, à multiplier les droits subjectifs (ou droits à), ceux des contribuables en particulier, et à impliquer étroitement ces derniers à la prise de la décision fiscale. Si, dans l’ensemble, ce phénomène inflationniste des droits subjectifs en matière fiscale peut être regardé comme une avancée notable du droit, une source de son progrès, il y a en revanche lieu de craindre un affaiblissement de l’Etat.
Keywords: Contractualisation; Contrat; Droit objectif; Droit subjectif; Droits personnels; Droits réels; Subjectivisation; Summa divisio

Qualité de l'information comptable des entreprises RD congolaises : perception des experts comptables et des financiers - Bakenge Mungu Chiruza, Papy; Mpereboye Mpere, Seblon (International Multilingual Journal of Science and Technology, 2023)
Cet article se penche sur la qualité de l'information comptable dans les entreprises de la République Démocratique du Congo (RDC) et explore les perceptions des experts comptables et des financiers à ce sujet. L'objectif principal de l'étude est d'évaluer la qualité de l'information comptable produite par les entreprises congolaises et de comprendre comment cette information est perçue par les parties prenantes clés. La méthodologie de l'étude repose sur une enquête menée auprès d'experts comptables et de financiers en vue de recueillir leurs appréciations sur les différents items du questionnaire composé notamment des items ayant trait aux caractéristiques de l’entreprises, ceux ayant trait à la situation économique de l’entreprises, ceux se rapportant à la situation financière de l’entreprise, les items sur les perspectives de développement et les prévisions de l’entreprises mais aussi en dernier, les items portant sur les informations segmentées. L’observation du résultat obtenu de la perception des experts comptables et financiers nous a conduit à regrouper les items en deux catégories explicitées ci-après, cette démarche étant volontaire. 1. Un groupe d’items pour lesquels les experts comptables et financiers ont une perception commune de l’importance de l’item. La moyenne est de 1 à 2 (plus de 1 et moins de 2) ; 2. Un groupe d’items pour lesquels les experts et les financiers donnent moins d’importance à l’item par rapport au premier groupe. La classification de ce groupe dépend de la moyenne obtenue (entre 2 et 2,5).
Keywords: Accountants; Accounting information; Experts Comptables; Financial; Financiers; Information comptable; Quality of information; Qualité de l’information

Le droit bancaire islamique : quelle particularité ? - Boly, Oumar (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Aujourd’hui, le développement des fonds d’investissement privés de plus ou moins grande amplitude dont contribué à démocratiser, si l’on peut dire, le recours au fonctionnement islamique. L’avènement de grandes fortunes privées font de certaines familles des investisseurs incontournables tentés par des placements conformes à la charia. On estime que le total de leurs avoirs dans le monde dépasse 250 milliards de dollars et qu’il augmente. Le développement du besoin du financement dans les pays de droit musulman s’explique par deux faits géopolitiques majeurs survenus à la fin du siècle dernier. D’une part, la manne pétrolière a engendré des accumulations de capital gigantesque qu’il faut placer et investir sans cesse. Today, the development of private investment funds of varying magnitude has contributed to democratizing, so to speak, the use of Islamic functioning. The advent of large private fortunes makes certain families essential investors tempted by investments that comply with Sharia law. Their total assets worldwide are estimated to exceed $250 billion and growing. The development of the need for financing in countries under Muslim law can be explained by two major geopolitical events that occurred at the end of the last century. On the one hand, the oil windfall has generated accumulations of gigantic capital that must be constantly placed and invested.
Keywords: Banking law; Chari'a; Chari'a law; Droit bancaire; Financement islamique; Financing Islam; Sharia

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Le particularisme de la répression pénale de la fraude fiscale - Cocly, Camille (Université de Saint-Etienne, 2023)
Le particularisme de la répression pénale de la fraude fiscale ressort de l’agrégation d’une pléthore de particularismes générés par la mise en œuvre d’un dispositif singulier de déclenchement des poursuites pénales. Le pouvoir discrétionnaire de l’administration fiscale de mettre en œuvre le dispositif de déclenchement des poursuites pénales pour fraude fiscale, plus connu sous l’appellation de verrou de Bercy, aura des répercussions sur toutes les étapes de la procédure pénale à l’instar d’un effet papillon. L’administration fiscale est en mesure de mettre en œuvre trois types de procédures administratives en cas de fraude fiscale : une procédure de recherche, une procédure de sanction et une procédure de recouvrement. Par conséquent, le recours à la répression pénale n’intervient qu’à titre subsidiaire afin de garantir le succès des procédures fiscales. Dans le cadre de la répression pénale de la fraude fiscale, dès lors que seule l’administration fiscale est en mesure de déclencher des poursuites pénales, la mise en œuvre du droit de punir est décidée par cette autorité administrative qui n’est pas indépendante car subordonnée au pouvoir exécutif en la personne du ministre du Budget. En conséquence, la répression pénale se retrouve détournée de son objectif primordial de rétribution afin de servir les impératifs budgétaires de l’administration fiscale dictés par le pouvoir exécutif. Outre un tel détournement, cette répression pénale sera exercée de façon inégalitaire puisqu’elle ne sera amenée à punir que les justiciables qui n’auront pas conclu une transaction avec l’administration. Le verrou de Bercy, en tant que pouvoir de faire obstacle à la répression pénale, s’il permet à l’administration de recouvrer l’impôt par transaction, il lui permet également de protéger les proches du pouvoir exécutif de poursuites pénales pour fraude fiscale. Le particularisme de la répression pénale de la fraude fiscale se nourrit de la réaction du législateur et de l’autorité judiciaire face à l’immoralisme qui s’évince du pouvoir de l’administration de permettre la mise en mouvement de l’action publique. En ce qui concerne le législateur, il va prendre un ensemble de mesures pour moraliser la vie politique, dont l’objectif est d’assurer la transparence sur les patrimoines des membres du pouvoir exécutif et des responsables politiques, de sanctionner plus sévèrement la fraude fiscale en renforçant la répression pénale de cette infraction. S’agissant de l’autorité judiciaire, si l’on peut remarquer une certaine détermination des autorités de poursuites à mettre en mouvement l’action publique lorsqu’elles sont saisies par l’administration fiscale, il convient de remarquer pareillement une certaine opiniâtreté du juge pénal à prononcer des condamnations pour fraude fiscale. D’autre part, les autorités de poursuites sont en mesure de s’affranchir des exigences procédurales du verrou de Bercy afin de poursuivre la fraude fiscale sous les qualifications de droit commun d’escroquerie et de blanchiment. Cependant, le constat de la faiblesse des peines d’emprisonnement prononcées ainsi que les possibilités d’aménagement de leur exécution soulèvent le curieux paradoxe d’une justice déterminée à condamner la fraude fiscale sans pour autant faire subir au fraudeur la violence légitime qu’il mérite. On peut se poser la question de savoir si une telle démarche moraliste de l’autorité judiciaire ne contribue pas à garantir le paiement de la dette fiscale. Cette réflexion est corroborée par l’avènement de la justice pénale négociée pour fraude fiscale, cadre dans lequel l’autorité judiciaire, à l’instar de l’administration fiscale, instrumentalise la répression pénale afin de recouvrer l’impôt.
Keywords: Bercy; Criminal-fiscal; Dispositions pénales; Droit; Droit fiscal; Fraud; Fraude; Fraude fiscale; Impôts; Instrumentalisation; Instrumentalization; Law; Lawsuits; Lock; Poursuites; Poursuites judiciaires; Pénal-fiscal; Taxes; Verrou

La fin de la fiscalité locale - Nazon, Romaric (Université de Montpellier, 2023)
Les impôts locaux avec pouvoir fiscal pour les collectivités territoriales sont progressivement démantelés par des allègements fiscaux de l'État qui aboutissent à la suppression de ces impôts. Le financement de la décentralisation dépend dès lors de plus en plus du partage de recettes fiscales nationales. L'impossible autonomie fiscale locale pousse à repenser les relations fiscales complexes entre l'État et les collectivités. La recréation d'un pouvoir fiscal local passerait par la concertation et la codécision entre l'État et les collectivités locales mais aussi, notamment, avec la crise de la démocratie représentative, entre des élus locaux et des citoyens. Cependant, la verticalité caractérise aujourd'hui les relations entre ces acteurs.
Keywords: Collectivités locales; Collectivités territoriales; Decentralization; Décentralisation; Décentralisation administrative; Finances publiques locales; Fiscalité locale; Impôt local; Local public finance; Local tax system; Territorial collectivities

The impacts of IFRS 16 on airlines - Ribeiro, José; Ribeiro, Francisco; Ribeiro, Fernando (Accounting and Management Review | Revista de Contabilidade e Gestão, 2023)
This study addresses the effects of the adoption of IFRS 16 on the passenger air transport sector. With practical effects for financial years beginning on or after 1 January 2019, IFRS 16 established the standardisation of a single accounting modelfor all leases, whether operating or financial. With this new adoption, IFRS 16 aims to increase the transparency and quality of the information that is presented in the financial statements for the most diverse stakeholders. This study aimed to assess the effects of adopting this new international standard in a specific sector and to identify whether the changes in some of the financial indicators are felt in the same way by all companies, this being the main focus of this study. Based on a sample of 12 airlines from various countries in Europe and South America, the financial indicators were interpreted by analysing the reports and accounts before and after the application of IFRS 16. The main conclusions obtained are: i) the adoption of IFRS 16 led to an increase in assets, liabilities and EBITDA, however in different proportions for each of these items; ii) companies with negative equity and, therefore, with greater risks of bankruptcy or greater information asymmetry, tend to resort more to leasing as a way of financing their assets; iii) the financial autonomy and solvency ratios showed significant variations for companies that resort more to operating leasing.
Keywords: Airline industry; Finance leases; IFRS 16; Information asymmetry.

Emergence de la comptabilité environnementale: l’engagement et la compétence des professionnels comptables - Mayegle Ngo Nguidjol, Solange (Revue Française d'Economie et de Gestion, 2023)
La comptabilité environnementale (CE) se présente comme un nouveau défi à relever par les professionnels comptables avec comme objectif, de compléter la comptabilité financière par la mise sur un pied d’égalité les performances environnementales et sociales de l’entreprise. C’est une vision d’innovation internationale, sujet polémique dont la base conceptuelle reste encore à définir et à normaliser. Le but de cet article est de relever l'implication des professionnels comptables dans le domaine de la CE, sur les moyens auxquelles ils ont recours pour construire une compétence, et sur leurs aptitudes à mobiliser des partenaires dans ce domaine. Sur la base d’une étude qualitative à partir d’un échantillon de 16 entreprises, trois techniques de CE et deux formes d’engagement du professionnel comptable ont été identifiées. Il s’agit de la comptabilisation de l'emploi de l'énergie, de l’élaboration des budgets environnementaux, et de l’évaluation d'investissement environnemental. Concernant les formes d’engagement du professionnel comptable, nous avons identifié la divulgation des informations environnementales et, la comptabilisation des coûts environnementaux. Ainsi, une normalisation de la CE devrait contraindre les professionnels comptables à se soucier des activités reliées à la CE dans l’établissement des états financiers et tout autre modèle de rapport.
Number: 11
Keywords: Comptabilité environnementale; Normalisation comptable; Professionnel comptable; Systèmes comptable

La fraude à la loi en droit fiscal - Bach, Laurène (Université de Bordeaux, 2023)
Face aux crises et aux scandales financiers des dernières années, les préoccupations budgétaires des États ont évolué. En marge de la lutte contre la double imposition, il est apparu nécessaire de lutter contre les stratégies fiscales frauduleuses pour préserver la base imposable des États. D’abord reconnue par la jurisprudence européenne et française, la lutte contre la fraude à la loi s’est intensifiée avec l’ambitieux projet BEPS de l’OCDE. Les diverses initiatives se sont concrétisées par l’adoption de la directive « ATAD », la signature d’un instrument multilatéral reprenant les actions du projet BEPS ou encore l’instauration d’une nouvelle procédure d’abus de droit en droit interne. Il en a résulté une multiplication des moyens de lutte contre la fraude à la loi.Alors que la démarche poursuivie par les États était celle de la convergence au service de la lutte contre la fraude à la loi, l’intégration de nouveaux fondements en droit interne et les divergences rédactionnelles présentes au sein de ces fondements ont entraîné une fragmentation apparente de la notion de fraude à la loi, ainsi que des interrogations sur l’articulation des différents fondements désormais applicables.Toutefois, en comparant et en analysant le sens de chacun des termes employés dans les différents fondements, une définition unifiée de la fraude à la loi peut être retenue autour de deux critères : une volonté déterminante d’obtenir un avantage fiscal et le détournement de l’intention des auteurs des textes. Par ailleurs, une première grille d’articulation peut être développée à partir de critères d’articulation issus des éléments distinctifs des fondements de lutte contre la fraude à la loi. Cette dernière devra ensuite être confirmée par les différentes instances ainsi que la jurisprudence tant interne, qu’européenne.
Keywords: Abus de droit; Anti-abuse clause; Articulation; Clause anti-abus; Droit fiscal; Fraude; Fraude à la loi; Montage; Substance; Tax avoidance; Tax law evasion; Tax planning

L’efficacité du système normatif de régulation du secteur bancaire et financier - Coulibaly, Alou; Yalcouyé, Seydou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Il convient de retenir que la promotion de modes de régulation privés tels que l’autorégulation et la corégulation est inévitable et nécessaire pour faire face à l’internationalisation du droit et au renforcement du dispositif de sanctions des autorités de régulation bancaires et financières. Pour autant, il importe que les enjeux liés à la mise en place d’une régulation informelle évoluent pour tenir compte davantage des intérêts de l’ensemble des parties prenantes et non seulement de la loi du marché. Il faut rappeler que les pouvoirs publics imposent aujourd’hui aux établissements bancaires et financiers la défense d’intérêts publics telle que la lutte contre le crime financier qui relève à l’origine de buts poursuivis par les autorités publiques. It should be remembered that the promotion of private modes of regulation such as self regulation and co-regulation is inevitable and necessary to cope wthih the internationalization of the law and the strengthening of the sanction system of the banking and financial regulatory authorities. However, it is important that the issues linked to the establishment of informal regulation evolve to take greater account of the interests of all stakeholders and not only the law of the market. It must be remembered that public authorities today impose on banking and financial establishment the defense of public interests such as the fight against financial crime which is originally part of the goals pursued by public authorities.
Keywords: Autorité de régulation financière; Bank; Banking establishment; Banking sector (regulation); Banque; Compliance; Conformité; Etablissement bancaire et financier; Financial establishment; Financial regulatory authorities; Financial sector (regulation); Secteur bancaire (régulation); Secteur financier (régulation)

Les grands principes du droit fiscal en Afrique - Coulibaly, Souleymane S; Diarra, Lassina Y; Boly, Oumar (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Les Etats doivent être des véritables acteurs de l’économie nationale grâce à une politique budgétaire rigoureuse, efficace et transparente pour créer ou financer les infrastructures nécessaires pour un vrai décollage économique et social des pays africains tant ambitionné par les populations. Ils doivent être enfin des vrais promoteurs des investissements privés capables de générer les richesses pouvant être fiscalisées tant en taxe sur les valeurs ajoutées (TVA) qu’en impôt sur le revenu. States must be real players in the national economy thanks to a rigorous, effective and transparent budgetary policy to create or finance the infrastructures necessary for a real economic and social take-off of African countries so much aspired by the populations. Finally, they must be real promoters of private investments capable of generating wealth that can be taxed both in value added tax (VAT) and in income tax.
Keywords: Africa; Afrique; Droit fiscal; Grands principes; Main principles; Tax law

Contribution à l'amélioration du cadre juridique du processus de passation des marchés publics au Cameroun - Dicka, John Eric (Université Paris-Saclay, 2023)
Un des maux endémiques de certains pays africains est la faiblesse du dispositif législatif et réglementaire de l'achat public, face aux nombreux et variés défis de développement et de satisfaction de l'intérêt général. Partout dans le monde, la gestion de la commande publique est sujette à des dérives (corruption, détournements de deniers publics, sous-consommation des crédits publics, favoritisme, collusion, etc.), tant les enjeux sont majeurs pour l'État, les entreprises, et l'économie. Mais le rôle de l'achat public réduit à l'assainissement de la dépense publique progresse et épouse de plus en plus la sphère de la gouvernance et d'autres missions d'intérêt général ; Si dans ce secteur sensible, certains États réussissent mieux que d'autres à calibrer et concilier ces objectifs, cela tient en grande partie à leur appareil légal et réglementaire et à la capacité des administrations comme des juridictions à l'appliquer. Ainsi ce sujet, quoique centré sur le droit camerounais, traite d'une problématique bien plus large qui concerne plusieurs États et dont les analyses comparatives faites dans ce travail avec d'autres systèmes proches, justifient un lien commun et profond.À partir du contexte d'application et des faiblesses Recensées du cadre normatif camerounais au niveau de la phase de conclusion de l'achat public, il s'agit d'étayer un constat : le droit camerounais des marchés publics ne semble pas permettre que les marchés publics soient conclus en garantissant à l'administration une certaine efficacité d'action dans l'atteinte de ses objectifs variés.Si ce constat aura pour effet d'identifier ces principaux enjeux, il doit se servir d'une analyse sérieuse de la politique et de l'idéologie des marchés au Cameroun que révèle avec force le processus de passation, afin de déboucher sur des moyens conséquents devant assurer aux textes leur capacité à concilier les fonctions initiales des marchés publics avec celles qui semblent de plus en plus émerger ces derniers temps ; le tout, en conférant aux textes des garanties d'effectivité dans ce sens.L'exemple (ou le contre-exemple ?) du Cameroun doit permettre de mettre en lumière des phénomènes très répandus à travers le monde, à savoir l'ineffectivité d'un dispositif légal et réglementaire et bien plus l'inadéquation normative par rapport aux objectifs d'intérêt général inhérents à l'action publique. L'étude ne tend donc pas seulement au constat statique d'une situation insatisfaisante et dommageable pour le pays, bien plus il vise une analyse valable par-delà les frontières du Cameroun : un droit positif aux multiples finalités - à mettre en lumière -, dont l'impact est insuffisant sur la pratique, et une proposition d'outils juridiques et de management public pour y remédier.
Issue: 2023UPASH010
Keywords: Afrique centrale; Approvisionnement public; Cadre juridique; Cameroon; Cameroun; Contribution; Intégration économique; Legal framework; Marchés publics; Marchés publics (droit); Passation; Process; Processus; Public contracts; Public procurement

Le dispositif de normalisation comptable dans la zone Ohada : un état des lieux - Kouame, Komoudh David Yann (Revue Française d’Economie et de Gestion, 2023)
Cet article analyse le dispositif de normalisation comptable dans la zone Ohada en le comparant aux formes dominantes existantes, la forme « comité d'experts » et la forme « représentant des parties prenantes ». Cette étude basée sur une étude documentaire permet de mettre en évidence les principaux traits caractéristiques de la normalisation comptable dans la zone Ohada afin de faire des recommandations normatives. Dans l'Ohada, le dispositif de normalisation présente les principaux traits suivants : une normalisation interétatique par un comité d'experts, placé sous la tutelle des pouvoirs publics ; une normalisation à partir d'un plan comptable qui inclut un cadre conceptuel explicite ; le plan comptable est une annexe à la loi comptable. Nous recommandons l'inclusion des différentes parties prenantes afin d'accroitre la légitimité politique de la CNC Ohada, un normalisateur interétatique.
The accounting standard-setting system in the Ohada zone: an inventory
Keywords: CNC Ohada; Interstate standard-setter; Légitimité politique; Légitimité technique; Normalisateur interétatique; Political legitimacy; Technical legitimacy

Droit à l'eau et partenariats internationaux : réflexions aux confluences des droits de l'homme et du droit international économique - Meireles, Gustavo Fernandes (Université Paris-Saclay, 2023)
L'eau représente un besoin vital pour l'homme. Sous l'effet du changement climatique et en raison de sa mauvaise utilisation, sa disponibilité pour l'utilisation humaine est gravement menacée. En outre, mobiliser les moyens techniques pour en assurer l'accès est coûteux. En conséquence, l'accès à l'eau constitue un enjeu largement investi par les programmes de développement mis en avant par les institutions internationales, à l'instar des Objectifs du Millénaire définis en 2000 et des Objectifs de développement durable de 2015. Les partenariats y sont proposés comme des moyens adaptés pour pallier les déficits d'infrastructures, notamment dans des États en développement. Solution particulièrement encouragée par la Banque mondiale et d'autres institutions financières internationales, la participation privée par le biais de partenariats internationaux est prônée comme une solution de nature à associer les entités publiques généralement chargées des services de l'eau et de l'assainissement avec les entreprises du secteur ayant un savoir-faire reconnu en vue de développer l'accès à l'eau potable. Alors que les partenariats internationaux ont joué un rôle de premier plan dans l'agenda de développement pour favoriser l'accès à l'eau, sont-ils des instruments adaptés pour réaliser le droit à l'eau ? Le droit à l'eau n'a été reconnu que de manière progressive dans le système onusien de protection des droits de l'homme. L'étude met en perspective l'originalité des partenariats internationaux dans le secteur de l'eau et souligne la difficulté à les inscrire dans le cadre normatif qui s'impose pour la réalisation du droit à l'eau. Les partenariats internationaux constituent des ensembles complexes d'instruments juridiques mis en place pour l'accès à l'eau. Malgré des avancées récentes en faveur de la consolidation de la responsabilité des entreprises en matière de de droits de l'homme, la pratique témoigne de ce qu'ils sont insuffisants pour mettre en œuvre pleinement le droit à l'eau.
Keywords: Accès à l'eau; Droit à l'eau; Droit à l'eau (droit international); Droits de l'homme; Développement; Développement durable; Partenariats internationaux; Personnes morales (responsabilité); Responsabilité des entreprises

Le droit applicable sur le chèque dans l’espace de l’Union économique et monétaire Ouest africaine (UEMOA) - Coulibaly, Souleymane S; Gakou, Kissima (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
L’Union Economique et Monétaire Ouest Africaine (UEMOA), en tant qu’organisation internationale, a été consacrée dans la Zone Franc en vue d’atteindre des objectifs de développement économiques et sociaux. Dans le but de créer entre eux une Union Economique d’une part, et un espace juridique uniforme d’autre part, les auteurs respectifs des traités de Dakar, a institué des communautés supra nationales dotées d’attributions propres et de pouvoirs réels découlant du transfert de souveraineté de leurs États membres. Il est évident que l’intégration juridique est un support non négligeable de l’intégration économique. The West African Economic and Monetary Union (UEMOA), as an international organization, was established in the Franc Zone with a view to achieving economic and social development objectives. With the aim of creating between them an Economic Union on the one hand, and a uniform legal space on the other hand, the respective authors of the Dakar treaties, established supranational communities endowed with their own attributions and real powers arising from the transfer of sovereignty of their member states. It is obvious that legal integration is a significant support for economic integration.
Keywords: Chèque (droit); UEMOA; WAEMU

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

Les aspects fiscaux des opérations de restructuration d'entreprise - Khouma, Mor Talla (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2023)
Le droit communautaire de l’OHADA prévoit un ensemble de règles propres à la restructuration d’entreprise qui peut prendre la forme d’une fusion, d’une scission ou d’un apport partiel d’actif. Ces opérations entraînent, pour la plupart, la dissolution sans liquidation des sociétés qui disparaissent, la transmission universelle de leur patrimoine aux sociétés bénéficiaires ainsi que l’acquisition par les associés des sociétés qui disparaissent, de la qualité d’associés des sociétés bénéficiaires. En principe, les conséquences fiscales applicables sont celles de la cessation d’entreprise, avec un coût fiscal dissuasif. Afin d’alléger les conséquences fiscales de telles opérations, il a été mis en place un régime fiscal de faveur propre à permettre la prise en compte du caractère intercalaire de telles opérations en leur faisant bénéficier d’une neutralité fiscale. OHADA Community law provides for a set of rules specific to the restructuring of a company which may take the form of a merger, a division, or a partial contribution of assets. These operations lead, for the most part, to the dissolution without liquidation of the companies that disappear, the universal transfer of their assets to the beneficiary companies and the acquisition by the members of the companies that disappear of the status of partners of the beneficiary companies. In principle, the applicable tax consequences are those of the cessation of business, with a dissuasive tax cost. To reduce the tax consequences of such transactions, a favorable tax regime has been set up to allow the intercalary nature of such transactions to be considered by allowing them to benefit from fiscal neutrality.
Keywords: Apport partiel d’actifs; Division; Favorable tax regime; Fusion; Merger; Partial contribution of assets; Régime fiscal de faveur; Scission

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

L'immobilier, une source de revenus captifs soumise à une fiscalité punitive, confirmant l'inconsistance du droit de propriété - Guenfici, Alexandre (Université de Perpignan, 2023)
Le point de gravité fixant mutuellement Nation et Citoyen est le sol. Sur ce sol est institué un droit, celui de la propriété foncière privée, un lien juridique primordial unissant Citoyen et Nation. Au cours de l'histoire ce point de fixation qu'est la propriété foncière devient également économique, l'État fondant une grande partie de ses recettes fiscales sur le propriétaire et son patrimoine immobilier. Dans une société moderne où la propriété est intriquée avec son rendement économique, cette propriété se mue en un placement économique subissant désormais une fiscalité punitive, voire confiscatoire. La fiscalité immobilière montre cette appropriation par l'État d'une grande partie des fruits de la propriété privée ; transformant cet objet en un simple droit d'occupation, voire un droit de garde, chargé d'obligations sans plus de droits réels. D’un droit réel à un droit personnel la fiscalité immobilière, par le jeu de l'impôt sur les revenus et de celui sur le patrimoine, transforme ce droit en une obligation fiscale. Dans cette relation nécessairement léonine entre propriétaire immobilier et État, ce dernier propose des régimes de faveur encourageant à investir dans l'immobilier. Ces incitations emprisonnent dans une relation de longue durée l'investisseur, puis l'investissement réalisé, l'État modifie en cours de relations les clauses de ces régimes à son plus grand profit. Or, le contribuable s'engageant dans cette relation n'est pas informé que ces règles peuvent changer d'une manière unilatérale, sans préavis et rétroactivement. Ce modus operandi est particulièrement illustré par la location meublée, la location para-hôtelière, l'impôt sur la fortune immobilière et la transmission de ces biens et activités via le pacte Dutreil. Ce dispositif Dutreil, donné comme un pacte, ne garantit aucune sécurité lors de son exécution ; d'autant que rédigé par une seule partie, le contribuable, l'autre, l'État, n'intervient qu'a posteriori pour éventuellement le remettre en cause
Keywords: Fiscal; Fiscalité; Fiscalité immobilière; Immobilière; Location; Propriété immobilière et impôt; Real estate; Rental; Transmission

Le principe de la présomption d’innocence et les sanctions administratives fiscales au Mali - N'Goro Koné, Idrissa (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
La présomption d’innocence s’apprécie au regard de l’ensemble de la procédure contentieuse partant de la procédure contradictoire où le pouvoir de l’administration demeure très large jusqu’au stade judicaire du litige au cours duquel le juge reprend les reines et impose son pouvoir de contrôle des actes de l’administration et de protection des droits fondamentaux.
Keywords: Mali; Présomption d’innocence; Sanctions administratives; Sanctions fiscales

La douane malienne à l’aune de l’intégration - Diallo, Hamadi; Fofana, Modibo Mohamed (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
La douane est une administration chargée d’établir et de percevoir les droits imposés sur les marchandises à la sortie ou à l’entrée du territoire du pays. Au Mali, le libéralisme économique de la deuxième république a engendré des reformes tant sur le plan organisationnel que structurel et de profonds changements dans la philosophie et dans la conception du tarif des douanes. L’assouplissement des procédures douanières et les facilités particulières dans l’octroi des régimes économiques matérialisent ce changement. Force est de constate sur le plan légal et réglementaire, on assista d’une part à la relecture du Code des Douanes et d’autre part à la reforme tarifaire. Ainsi dans cet article, nous faisons une analyse critique des textes réglementaires en vigueur afin de proposer des pistes de solution pour une douane plus efficace et plus performante.
Keywords: Douane; Harmonisation; Régionalisation; Tarif; Taxe

La lutte contre la fraude fiscale par voie des conventions - N'Goro Koné, Idrissa (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Nous pouvons dire aujourd’hui que la lutte contre la fraude fiscale est effective dans la mesure où le renforcement des conventions non seulement sur le plan communautaire mais aussi le renforcement des conventions entre le Mali et beaucoup d’autres États. En effet, il faut reconnaitre que sur le plan de la sanction pénale en matière de la fraude fiscale le juge malien est largement en retard par rapport à son homologue français qui a rendu une multiplicité des décisions relations aux sanctions pénales en matière de la fraude fiscale.
Keywords: Convention; Fraude fiscale (droit international); Mali; Sanction pénale

Corporate Finance, Governance, and Social Responsibility - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers 27 papers published in the Special Issue entitled Corporate Finance, Governance, and Social Responsibility, which examines several topics related to corporate finance, financial modeling, corporate governance, and corporate social responsibility. Corporate finance-related articles (Anton and Afloarei Nucu, 2021; Bae et al., 2023; Kedzior et al., 2020; Lts and Lukason, 2022; Miglo, 2020; Mihail et al., 2021; Mota and Moreira, 2023; Tsolas, 2021; Tudose et al., 2021; and Wen et al., 2021) focus on the drivers of the capital structure and firm performance, the effect of working capital management on profitability, and the link between derivative use and profitability. Regarding financial modeling, stock market volatility was explored during COVID-19 (Gherghina et al., 2021). Corporate governance studies (Aluchna and Kuszewski, 2020; Ararat et al., 2021; Ding and Chea, 2021; Kjrland et al., 2020; Loureno et al., 2021; Lukason and Camacho-Miano, 2020; Maier and Yurtoglu, 2022; Mihail and Dumitrescu, 2021; Mihail et al., 2022; Mihail and Micu, 2021; and Pourmansouri et al., 2022) examine the effect of corporate governance compliance practices, board attributes, or employee stock option plans on bankruptcy risk, performance, firm value, or earnings management. Regarding CSR (Bozos et al., 2022; Rossi et al., 2021; Saeed and Sroufe, 2021; Singh and Hong, 2023; and Tseng and Shih, 2022), the research focuses on how CSR affects financial performance, risk management, or analyst profits estimates.
Keywords: CSR; Corporate Finance; Financial performance

L’adoption des normes IFRS et qualité de l’information comptable publiée : Revue de la littérature - Ndudi Ndudi Kambu, Pascal; Nanizayawo, Augustin; Tsiku Malonda, Job Valère; Maphana Musa, Trésor; Khabi Ndudi, Gabriel (Mouvements et Enjeux Sociaux, 2023)
L’influence des international financial reporting standard (IFRS) est très remarquable actuellement dans le monde. L’adoption de certaines normes IFRS et la présentation des états financiers selon les dispositifs de ces normes par les entreprises cotées dans l’espace OHADA depuis la révision de 2017 en est un exemple. L’objet de cette étude est d’analyser théoriquement l’incidence de l’adoption des normes IFRS sur la qualité de l’information financière publiée. L’analyse de la revue de littérature nous permet de constater que les résultats des recherches antérieures ne convergent pas. Certains travaux de recherche affirment que les normes IFRS confèrent la qualité aux chiffres comptables publiés alors que d’autres rejettent cette affirmation. Ainsi, le fait d’adopter un référentiel de qualité à l’instar des IFRS, ne garantit pas forcément la qualité des chiffres comptables publiés. Toutefois, elle peut renforcer la crédibilité aux comptes.
Keywords: Comptabilité; Information comptable; Normalisateur; Normalisation comptable

Artificial Intelligence: Challenges and Opportunities for the Accounting Profession in Nigeria - Nkwede, Maria; Aniuga, Chukwuma (African Journal of Politics and Administrative Studies, 2023)
Artificial intelligence with its fifth industrial revolution is fast griping the African continent. The emergence and adoption of artificial intelligence applications and systems is fast becoming a normal trend in emerging markets landscape across Africa. This paper is borne out of the need to identify challenges that professional grapple with in their quest to surmount the challenges posed by the realities of artificial intelligence applications in Africa. The study adopted the thematic style in presenting the challenges as well as the prospects of artificial intelligence applications for the accounting professional in emerging market. Some of the challenges of artificial intelligence application identified in this study include: complex algorithms, reduced investment, and software failure, lack of political will and limitations amongst others. On the other hand, opportunities of artificial intelligence in emerging market include transportation automation, technological cyborgs and robotic companions amongst others. From the findings, accounting professional are advised to strive harder in order to beat competition by delivering quality services to her clients through harnessing opportunities for rebranding, reengineering and radically improving the business and investment decisions which is the ultimate purpose of the profession. More so, they are encouraged to develop a novel set of proficiency revolving around data in the profession
Keywords: AI; Accounting Profession; Artificial Intelligence; Challenges; Fifth Industrial Revolution; Inteligência artificial; Intelligence Artificielle; Opportunities

From non-financial information to corporate sustainability information: formal or substantial evolution? - Dalmau, Rémi (Revue Juridique de la Sorbonne, 2023)

From non-financial reporting to corporate sustainability reporting: formal or substantial evolution? - Desbat, Manon (Revue Juridique de la Sorbonne, 2023)
Far from delimiting or fencing off, as the etymology of the verb “to define” would have us do, the definition of sustainability as it emerges from the directive is destined to spread to an exponential number of neighbouring lands. Sustainability is spreading to affect governance factors, and is now pollinating a growing number of companies, particularly SMEs and non-EU companies. Moreover, while a hasty reading of Article 2 of the CSRD might lead to conclude that sustainability can be summed up in a list of five factors, sustainability above all questions the contribution of the company, and the law governing it, to the sustainable development of societies. Indeed, it penetrates the companies, through the channel of “corporate sustainability”, seeking to ensure that environmental, social, human rights and governance issues are levers in decision-making within the companies, thus inviting them to act, beyond communicating. This renewal of sustainability is reinforced by a redefinition of the obligations imposed on companies: the fields covered by the required information are multiplied, the “comply or explain” principle is largely abandoned, and assurance on sustainability information becomes compulsory. La directive (UE) 2022/2464 en ce qui concerne la publication d’informations en matière de durabilité par les entreprises, ci-après dite « directive CSRD » (pour Corporate Sustainability Reporting Directive), réforme la directive 2014/95 (dite NFRD pour Non Financial Reporting Directive), laquelle avait instauré le premier cadre de reporting extra-financier de l’Union européenne. La directive CSRD opère un changement terminologique en renommant les informations précédemment désignées par la directive NFRD comme « non financières » en « informations en matière de durabilité ». Or, un changement terminologique peut advenir sans pour autant observer un glissement sémantique qui opèrerait une évolution dans le sens et la signification des termes employés. A contrario, un changement sémantique peut aboutir sans qu’une substitution de terme n’accompagne l’évolution. Dès lors, le changement terminologique opéré par la directive CSRD s’accompagne-t-il d’un changement sémantique ? Par ailleurs, constitue-t-il un changement formel ou substantiel ? Autrement dit, le changement de mot permet-il une plus ample considération et une meilleure gestion des maux ? La question se pose dans la mesure où cette terminologie n’est en réalité pas inédite. La directive NFRD évoquait effectivement déjà « les informations sur la durabilité ». Par la suite, les lignes directrices de la Commission européenne sur l’information non financière de 2017 fixant une méthodologie pour la communication desdites informations ainsi que celles de 2019 sur les informations en rapport avec le climat2 avaient repris la formule. L’expression n’apparaît qu’au stade des considérants de la directive NFRD, et qu’à une seule reprise dans les lignes directrices précitées. Le terme était néanmoins présent et, surtout, il était employé comme synonyme de « non financière ». Partant, deux présuppositions en découlent : l’adoption du terme par la directive CSRD ne revêtirait qu’une modification formelle et le changement terminologique ne serait pas soutenu par une évolution sémantique. La présente contribution met à l’épreuve ces deux présuppositions en concluant que l’évolution ne se réduit pas à un simple changement de terme. Loin de borner ou clôturer, comme l’étymologie du verbe « définir » l’invite pourtant à le faire3 , la définition de la durabilité telle qu’elle ressort de la directive a plutôt vocation à se répandre sur un nombre exponentiel de terres avoisinantes. La durabilité se déploie pour toucher les facteurs de gouvernance et pollinise désormais un nombre croissant d’entreprises, notamment les PME et les entreprises de pays tiers. Par ailleurs, si une lecture hâtive de l’article 2 de la directive CSRD pourrait conclure que la durabilité se résume à l’énumération de cinq facteurs, la durabilité interroge surtout la contribution de l’entreprise et du droit l’encadrant au développement durable des sociétés. Elle pénètre en effet les murs de l’entreprise par le canal de la « durabilité de l’entreprise », en cherchant à ce que les thématiques environnementales, sociales, de droits de l’homme et de gouvernance soient des leviers dans la prise de décision à l’intérieur de l’entreprise les invitant ainsi à agir, au-delà de communiquer. Ce renouvellement de la durabilité est renforcé par une redéfinition des obligations à l’égard des entreprises : les champs couverts par l’information exigée sont multipliés, le « comply or explain » majoritairement abandonné, et l’assurance sur les informations en matière de durabilité devient obligatoire. Pour de plus amples informations, le présent article est disponible intégralement en français à la Revue trimestrielle de droit financier, sous la référence suivante : insérer ici la référence exacte quand elle sera disponible.
Keywords: Communication des informations; Corporate sustainability; Durabilité de l’entreprise; First set of draft ESRS; Normalisation de l’information; Projets de normes de l’EFRAG; Reinforcing obligations; Renforcement des obligations; Standardized sustainability information; Sustainability reporting

The application of the CSRD to third-country undertakings - Didry-Barca, Julien (Revue Juridique de la Sorbonne, 2023)
L’extension des obligations d’information en matière de durabilité aux entreprises de pays tiers est présentée comme l’un des principaux apports de la directive CSRD, permettant de saisir les impacts sociaux et environnementaux du groupe transnational de sociétés. L’effectivité de la directive à l’égard de ces groupes semble toutefois relative. D’un côté, la directive saisit le groupe comme unité au travers de la filiale européenne en l’obligeant à publier une information couvrant le groupe entier. Mais d’un autre côté, elle laisse une large place à l’autonomie de la filiale en retenant une limitation de l’obligation au stade de l’exécution : si la société mère ne lui fournit pas l’information, la filiale peut se contenter de publier une information partielle accompagnée du refus de la société mère. La directive se contente donc d’exercer une contrainte réputationnelle sur le groupe transnational. Ce manque d’effectivité invite à réfléchir à des moyens d’y remédier, dont le principal semble être une restriction de l’accès au marché européen en l’absence d’une information consolidée suffisante en matière de durabilité. Parallèlement, la directive CSRD pourrait se trouver renforcée par la multiplication des obligations « ascendantes » en matière de durabilité, invitant le groupe transnational à rationnaliser la publication d’information afin de satisfaire les exigences des différents systèmes auxquels il est soumis. The extension of the sustainability reporting obligations to non-EU companies is presented as one of the CSRD’s major contributions, making it possible to grasp the social and environmental impacts of transnational corporate groups. However, the effectiveness of the Directive with regard to these groups seems relative. On the one hand, the Directive captures the group as a unit through the European subsidiary, binding it to publish consolidated information at a global level. On the other hand, it leaves room for the subsidiary’s autonomy, by limiting the obligation at the performance stage: if the parent company fails to provide the information, the subsidiary can simply publish a partial information, accompanied by the parent company’s refusal. The Directive therefore imposes a merely reputational constraint on the transnational group. This lack of effectiveness calls for remedies, the main one being restricting access to the European market in the absence of sufficient consolidated sustainability information. At the same time, the CSRD could be strengthened by the multiplication of “bottom-up” sustainability obligations, inviting the transnational group to rationalize the publication of information in order to meet the requirements of the various systems to which it is subject.

Le régime de l'information consolidée en matière de durabilité au sein des groupes de sociétés à l'aune de la directive CSRD - Miglietta, Emma (Revue Juridique de la Sorbonne, 2023)
The principle of independence of legal persons within corporate groups means that the rights and obligations of each company in the group are assessed individually, without taking account of the fact that they belong to the group. However, in terms of reporting obligations, the CSRD directive provides for a derogatory system of “consolidated sustainability reporting” for groups of companies. In essence, this requires the dominant company to provide sustainability information on behalf of all group companies under its control. This logic is not new, and has its origins in the system of consolidated accounts which, in terms of financial reporting, obliges the parent company to communicate on the financial position and results of group companies as if they were a single entity. This substantial approach to accounting law, which aims to communicate information that is useful for economic decision making, seeks to reflect the reality of transactions, beyond their legal form. From this point of view, the group is considered to be a single entity, due to the dominant company’s power of control over the resources of its subsidiaries. This logic has permeated company law, and the obligation to draw up consolidated financial statements is enshrined both in European Union directives and in the French Commercial Code. The legal basis for this is the control of the dominant company, i.e. the power of the parent company to impose its views on its subsidiaries at shareholders’ meetings, and to exert influence over the management of its subsidiaries. The consolidated reporting regime had been extended to non-financial information since the NFRD directive in 2014, at European level, and since the law of July 12, 2010, in domestic law. It is set out in Article 29 bis of the CSRD Directive, with a few changes. Consolidated sustainability information reveals an extension of the consolidation logic. Indeed, consolidated sustainability reporting requires the publication of strategic and qualitative information that goes far beyond the scope of financial data required for consolidated accounts. Moreover, unlike the obligation to draw up consolidated financial statements, the system provides for an exemption from the obligation to provide information, on an individual basis, at the level of each subsidiary, so that the obligation only weighs on the head company of the group. We have thus moved from a purely informative and descriptive consolidation logic to the obligation for the head company of the group to report on the environmental and social consequences of the activity of the companies in the group. As a result, the consolidation of information within groups obliges, to a certain extent, the head companies to assume the risks generated by the activity of all the companies included in the scope of consolidation and, above all, the measures implemented to deal with them. Stakeholders of the parent company or of one of the group’s subsidiaries will theoretically be able to have an overall view of the activities of the companies in the group, without the head company being able to conceal activities with harmful social and environmental consequences within a subsidiary. This is all the more true given that the scope of consolidation is broadly understood, since the consolidation thresholds are calculated and added up at the level of all the companies in the group, on the one hand, and that the CSRD directive provides for the inclusion of non-European parent companies which carry out an activity in the European Union through a subsidiary or branch, on the other. However, this observation must be tempered by the conditions under which the information obligation is implemented. Although the CSRD requires that information be traceable, this is hardly sufficient to ensure that the consolidated sustainability report remains comprehensive. The provision of global data on the environmental and social risks generated by the activities of group companies leaves considerable scope for concealing individual data, specific to the sustainability impacts of each subsidiary, and encourages deceptive transparency. It therefore seems essential to require that subsidiaries be exempted from the requirement to provide detailed information on a subsidiary-by-subsidiary basis, to ensure that the consolidated reporting system is not just a tool for optimizing information within groups.

La fiscalité foncière au Mali - N'Goro Koné, Idrissa (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Le foncier se trouve au centre des préoccupations de l’ensemble des acteurs nationaux. Toute personne propriétaire ou usufruitière d’un bien immobilier est redevable de la taxe foncière. Les impôts fonciers peuvent permettre aux pouvoirs publics d’obtenir des retours sur leurs investissements dans des services publics et des infrastructures. Ainsi, la mise en œuvre de ces imports fournit de façon relative aux pouvoirs publics des flux de recettes futurs grâce auxquels le financement de projets vis les marchés de capitaux peut devenir une réalité.

Preparing sustainability reporting: what framework? - Trebert, Carla (Revue Juridique de la Sorbonne, 2023)
Adoptée après la mise en application des textes relatifs à la finance durable, mais avant la proposition de directive sur le devoir de vigilance, la CSRD vient parfaire l’édifice législatif sur lequel l’Europe construit sa stratégie en matière de durabilité dans le prolongement du Green Deal. Elle est porteuse d’avancées majeures puisqu’elle renforce les exigences entourant le reporting de durabilité, mais reste laconique sur la phase pourtant cruciale d’élaboration de l’information préalablement à la publication. Cet article tente d’esquisser, à l’aune de l’obligation de s’informer pour informer, un régime afin d’encadrer ce travail préalable. Si cette piste soulève davantage de questions qu’elle n’apporte de réponses, elle permet au moins de mettre en lumière la manière dont la substance et le périmètre de l’information influent sur le comportement que l’on peut attendre de la part des entreprises assujetties. Adopted after the implementation of the texts relating to sustainable finance, but before the proposal for a directive on due diligence, the CSRD completes the legislative edifice on which the European Union is building its sustainability strategy in the wake of the Green Deal. It represents a major step forward, as it strengthens the requirements for sustainability reporting, but remains silent on the crucial phase of preparing information prior to publication. This article attempts to sketch out, in the light of the obligation to obtain information in order to inform others, a framework for this preliminary work. While this approach raises more questions than it answers, it does at least shed light on the way in which the substance and scope of the required information influence the behaviour that can be expected from the undertakings subject to the CSRD.
Keywords: Administrative burden; Arbitrariness; Charge administrative; Chaîne de valeur; Cost and efforts; Coûts et efforts; Directive CSRD; Double materiality; Double matérialité; EFRAG; Information de durabilité; Obligation de dire; Obligation to disclose; Potestativité; Qualitative information; Qualité de l’information; Reflexivity; Reporting de durabilité; Réflexivité; Sustainability information; Sustainability reporting; Transparence; Transparency; Value chain

What normativity for stakeholders' capitalism under CSRD? - Vuarnet, Théo (Revue Juridique de la Sorbonne, 2023)

تبني البنوك التجارية التقليدية للمعاملات المصرفية الإسلامية - زرفاط, خليدة; سوالمي, رحاب نور الهدى (جامعة ابن خلدون-تيارت, 2023)
تمثل البنوك التجارية الجزائرية المعبر الرئيسي للوساطة المالية والمصرفية في الاقتصاد الوطني، إذ تساهم بشكل كبير في أغلب المعاملات الاقتصادية داخل وخارج الوطن، وبالتالي فهي تساهم بعدة أدوار مهمة في التنمية الاقتصادية واستدامتها عبر الأجيال، قام ت الحكومة بإنشاء فروع ونواف ذ إسلامية للمعاملات المالية الإسلامية على مستوى هذه البنوك وطرح منتجات مصرفية إسلامية قرر ساعد على جذب المتعاملين بالسوق الموازية لضخ أموالهم بالبنوك الوطنية واستخدامها بصيغ تطبق احكام الشريعة الإسلامية، تعمل الصيرفة الإسلامية على نبذ الربا وتعزيز التكافل الاجتماعي والعدالة. إن استخدام مثل هذه الخدمات يهدف إلى تحقيق المشاركة في الأرباح والخسائر بين البنوك والزبائن. وفي دراستنا تبين لنا مدى تبني البنوك التقليدية الجزائرية للمعاملات المالية الإسلامية من خلال فتح نوافذ إسلامية تعمل وفق الشريعة الإسلامية لتحقيق رضا وإستقطاب الزبائن Algerian commercial banks represent the main catalyst for financial and banking intermediation in the national economy. They to contribute significantly the majority of economic transactions within and outside the country. Consequently, they play several crucial roles in economic development and its sustainability across generations. The government has established branches and windows for Islamic financial transactions in these banks and introduced Islamic banking products. This decision has helped attract participants in the parallel market to channel their funds into national banks and utilize them in accordance with Islamic law principles. Islamic banking aims to eliminate usury (riba) and promote social solidarity and justice. The use of such services aims to achieve profit and loss sharing between banks and customers. Our study has revealed the extent to which Algerian traditional banks have embraced Islamic financial transactions by opening Islamic windows that operate in accordance with Islamic law, aiming to achieve customer satisfaction and attract clients
Keywords: Commercial banks; Customer satisfaction; Financial transactions; Islamic Banking; Islamic windows

تحديات فرض الضرائب على معاملات التجارة الإلكترونية في الجزائر - مبخوت, رفيق; غول, حسين (Ibn Khaldun University of Tiaret, 2023)
لقد تطرّقنا في موضوع دراستنا على تحدّيات فرض الضّرائب على معاملات التّجارة الإلكترونية باعتبار موضوع التّجارة الإلكترونية من المواضيع الهامّة التي تلقى اهتماما كبيرا من قبل الكثير من الباحثين لما لها من انعكاسات على اقتصاديات دول العالم المتقدّمة والنّامية، حيث تعدّ إحدى النّظم الحديثة في إتمام وتنفيذ المعاملات التّجارية عبر شبكات الأنترنت. ولقد أسفرت دراستنا الميدانية في المركز الجواري للضّرائب دائرة السّوقر التي واجهت عدّة صعوبات لإخضاع المعاملات الإلكترونية بسب غياب قوانين والتّشريعات المتعلّقة بتنظيم الضّريبة الإلكترونية وغياب رقمنة القطاع وصعوبات تقنية تطبيق هذا النّوع من الضّرائب. هذا ما أوجب على الجزائر بذل مجهوداتها من أجل دعم وإرساء البنية التحتية للاتّصالات ومسايرة التّقدّم التّكنولوجي في العالم وتسليط الضّوء على القوانين والتّشريعات الجبائية الخاصّة بهذه التّجارة وسَنّها والعمل بها على أرض الواقع. In the subject of our study, we have addressed the challenges of imposing taxes on electronic commerce transactions, considering the issue of electronic commerce as one of the important topics that receive great attention by many researchers because of its implications for the economies of the developed and developing countries of the world, as it is one of the modern systems in the completion and implementation of commercial transactions. Via internet networks. Our field study resulted in the neighborhood tax center, in Sougueur Department, which faced several difficulties in subjecting electronic transactions due to the absence of laws and legislation related to the organization of electronic taxation, the absence of digitization of the sector, and the technical difficulties of applying this type of taxation. This is what required Algeria to exert its efforts to support and establish the telecommunications infrastructure, keep pace with the technological progress in the world, shed light on the laws and fiscal legislation related to this trade, enact them and implement them on the ground.
Keywords: Algeria; Algérie; Commerce électronique; Fiscalité; Internet; Taxe électronique; الأنترنت; التجارة الإلكترونية; الضريبة الإلكترونية; النظام الضريبي

Essai comparatif des comptes du Plan Comptable General Congolais (PCGC) à ceux du Système Comptable Ohada (SYSCOHADA) - Kawa Nkolo, Jacques (Mouvements et Enjeux Sociaux, 2023)
L’avènement du système comptable OHADA est une innovation de grande envergure dans l’organisation de la profession comptable dont l’importance pour les gestionnaires des plus petites entreprises de l’informel ne souffre d’aucune contestation. Aujourd’hui, mieux qu’hier, il s’avère impossible de s’en passer dans la mesure où ce nouveau système de gestion constitue une panacée aux maux qui rongent l’organisation comptable dans les entreprises, d’où l’adaptation au changement est plus que nécessaire.
Keywords: Comptabilité; SYSCOHADA

Saudi Banks Level of Compliance with Accounting Standards of Accounting and Auditing Organization for Islamic Financial Institutions - A. Al-Bogami, S. (Information Sciences Letters, 2023)

The Relation between Corporate Governance, Risk Management and Financial Performance: Theoretical and Analytics Framework - Ayoob Mohammed Hassan, Noora; Din, Badariah binti Haji; Senasi, Vally (Information Sciences Letters, 2023)
The paper aims to review the relation between Corporate Governance, Risk Management and Performance. We reviewed these variables and develop a Theoretical and Analytics framework. First introduction (study background, Problem Statement, Research Objectives and research questions). Second literature review (A) financial performance such as ROA, ROE, EPS and Tobin’s Q, (B) Corporate Governance as Board of Directors, Board Composition, CEO Duality and Board Size (C) Risk Management. Third, we discussed Underpinning Theories such as, Agency Theory and Institutional Theory. Fourth, we developed a Theoretical Framework where we illustrated (A) Corporate Governance and Financial Performance, (B) Risk Management and Financial Performance (C) Compliance with Accounting Standards and Financial Performance. Finally, we developed a comprehensive reviewing based on above variables.
Keywords: Corporate governance; Performance; Risk Management

Influence of Training, Experience, and Expertise on Quality of Financial Reporting in Dubai – Mediation of Adoption of International Public Sector Accounting Standards - IPSAS - El Haron, Esam O.; Haji Din, Badariah (Information Sciences Letters, 2023)

Accounting Choices During COVID 19 Pandemic: Does Corporate Strategy and Corporate Social Responsibility Matter? - T. Hassan, N. (Information Sciences Letters, 2023)
This study aims to understand the accounting effects of the Corona pandemic in more depth and clarity, where the study explores the accounting choices during the pandemic period and the impact of the firm's strategic orientation and its social responsibility performance on those choices. Using data from non-financial Saudi companies, the accounting choices divided into aggressive accounting strategy and conservative accounting strategy, and regression models used to examine the study hypotheses. The results of the study provide a clearer and in-depth vision about the nature of accounting practices during the pandemic and indicated that business strategy affects accounting choices, while corporate social responsibility does not affect. The results can imply useful information for the market regulators that help them in controlling and stabilizing the market, as well as for professional accounting organizations to help them issue guidelines for accounting work during crises.
Keywords: Accounting choices; CSR; Corporate Social Responsibility; Corporate strategy; Covid-19 pandemic; Saudi companies

O sistema de regulamentação contabilística e o relato financeiro na Guiné-Bissau - Candé, Mamadú (Instituto Politécnico de Santarém, 2023)
Esta dissertação analisa a evolução do sistema contabilístico da Guiné-Bissau, nomeadamente o processo de convergência do Sistema de Contabilidade da Organização para Harmonização do Direito dos Negócios em África (SYSCOHADA) com as normas internacionais de relato financeiro (NIRF). Pretende-se perceber em que medida os laços políticos e culturais influenciaram este processo de convergência no país, e ainda as ligações entre as dimensões culturais, sociais, económicas e financeiras, assim como as respetivas influências na fiscalidade, no ensino e na formação profissional, na organização da profissão contabilística, com base na classificação dos sistemas contabilísticos de Nobes (1998). A Guiné-Bissau é um país membro da Organização para Harmonização dos Negócios em África (OHADA), entidade responsável por edificar e oficializar as normas contabilísticas, que são aprovados através de ato uniforme que envolve dezassete países africanos, o que explica que seja influenciado ou influencie outros países membros daquela organização. Esta investigação contribui para a literatura no domínio da contabilidade e relato financeiro no continente africano, em geral, área ainda pouco explorada e pouco conhecida da comunidade académica, e da Guiné-Bissau, em particular, país independente desde 1973, depois de um período de vários séculos de existência como antiga colónia portuguesa.
Keywords: Contabilidade; Guiné-Bissau; ORNATOC; Relato financeiro; SYSCOA; SYSCOHADA; Sistema contabilístico; Técnicos Oficiais de Contas

Internacionalização Contábil: uma revisão da literatura sobre as IFRS na África - Issifou, Mourtala; Freire, Fátima de Souza; Niyama, Jorge Katsumi (Revista de Gestão e Secretariado, 2023)
O objetivo do trabalho foi identificar tendências de investigações científicas, publicadas no período de 2008 a 2020, sobre a aplicação das International Financial Reporting Standards (IFRS) nos países africanos. Por meio de uma revisão da literatura, foram analisados, em particular, os tópicos abordados, motivos e teorias aplicadas nos estudos. As fontes de recolha de dados foram as bases de dados da Emerald Insiht e Sience Direct. A amostra consiste em 31 artigos extraídos das revistas internacionais de contabilidade que publicaram sobre a adoção, compliance e consequências das IFRS no continente africano. Ainda que tenham ocorrido numerosas variações na aplicação dos normativos internacionais, principalmente relacionados à conformidade, a maioria dos países africanos tem adotado às normas IFRS. No entanto, mesmo que a maioria tenha prolongado a implementação das IFRS, os resultados apontam que a adoção das mesmas gera criação de vantagens competitivas e integração para os mercados globais. Concluiu-se que: (i) a regulamentação institucional limita a aplicação das IFRS na África; (ii) as práticas contábeis são influenciadas pelos ambientes externos e internos da organização institucional; (iii) elas devem ser baseadas em decisões racionais e nas crenças das instituições. Por fim, os achados apontam as influências culturais como justificativas da forma escalonada de como os países do mundo, não somente africanos, vem adotando às normas IFRS.
Keywords: Contabilidade; IFRS na África; Revisão da Literatura

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

Banking System Fragility in Nigeria: Hanging on the Precipice? - Kayode, Peter; Oluwole, Foluso (AAU Journal of Business and Law, 2023)
The health of a country’s banking system is a key determinant to the development of the country. A fragile banking system portends danger not only to the financial system but the entire economy. This study investigates the state of the Nigerian banking system in terms of stability or fragility from 1981 to 2020. We used the banking system fragility index (BSFI) proposed by Kibritçioğlu (2003) to analyze Nigerian banking industry aggregate data from three risk areas: credit, market and liquidity. We estimated that out of the 40 years examined, the banking system was fragile for 23 years given their BSFI less than 0 while it was not fragile for 17 years with BSFI = 0 or greater. We found that most of the years when the Nigerian banking system was fragile were periods of relaxed monetary policies, deregulation and credit expansion. Secondly, the years of banking system stability were when the county’s banking system was subjected to stiff regulation and consolidation. Given the number of years that the system was fragile, we observed that sustained economic growth and development requires that the banking system remain strong as long as possible, and that the Nigerian situation could not promote this important objective. We recommend that the financial regulatory authorities put in place more stringent policies as banks are more fragile during the deregulation of the banking industry.
AAU Journal of Business and Law مجلة جامعة العين للأعمال والقانون
Keywords: Banking system fragility; Precipice

Le droit de la résolution des défaillances bancaires : contribution à l'étude du traitement administratif des établissements de crédit peu solides ou défaillants - Moreau, Victoria (Université Côte d'Azur, 2023)
Si on eut un temps pu s'interroger sur la nécessité de régir les défaillances bancaires, l'intérêt de telles dispositions a été réaffirmé depuis les années 2000. Dans ce contexte, le législateur européen, désireux d'assurer la stabilité financière, a mis en place une véritable Union bancaire, dont le second pilier est composé d'un Mécanisme de résolution unique destiné à prévenir et à traiter les défaillances bancaires. Ont ainsi été conçus différentes procédures et instruments dits de résolution, pouvant être mis en œuvre par des autorités administratives spécialisées. Or, la notion de résolution bancaire est une notion qui semblait jusqu'alors inconnue. Pourtant, les dispositions qui la gouvernent ne semblent pas véritablement la définir, et lui octroient la nature de Mécanisme, qui parait inadaptée. En effet, en observant l'ensemble des éléments qui compose ce Mécanisme, il ne fait nul doute que le législateur ne s'est pas contenté de créer un dispositif de gestion des défaillances bancaires, mais est allé plus loin en élaborant un véritable droit sui generis. L'existence de ce droit doit être affirmée pour permettre à celui-ci d'être pleinement efficient. Il produit par ailleurs des effets considérables tant sur les sujets de droit qu'il gouverne, que sur les acteurs avec qui ceux-ci interagissent. Ces effets originaux participent à l'efficacité de la prévention et du traitement des défaillances bancaires. S'ils peuvent en ce sens être salués, certains risques doivent néanmoins être relevés, notamment à l'aune des droits fondamentaux. La jurisprudence naissante en la matière - mais déjà très instructive -, laisse présager un droit en évolution et aux enjeux multiples, qui fera sans nul doute l'objet d'un intérêt grandissant.
Keywords: Bank resolution; Banques (réglementation); Credit institution; Droits fondamentaux; Défaut de paiement; Entités systémiques; Etablissement de crédit; Faillites bancaires; Financial stability; Fondamental rights; Résolution bancaire; Stabilisation économique; Stabilité financière; Systemic entity

Le droit de visite et de saisie de l'article L. 16 B du Livre des procédures fiscales- contribution à l'étude de la protection du domicile par le juge judiciaire - Papagiannoulas, Anastasios (Université Paris-Saclay, 2023)
Le droit de visite et de saisie de documents de l'article L. 16 B du LPF constitue entre les mains de l'Administration fiscale une mesure d'enquête coercitive portant atteinte à l'inviolabilité du domicile. Validé par le Conseil constitutionnel, et par la Cour européenne des droits de l'homme, qui ont toujours considéré que les nécessités de la répression des infractions fiscales et de la fraude fiscale justifiaient l'attribution de telles prérogatives à l'Administration fiscale, le régime des visites fiscales se caractérise par les fortes garanties procédurales dont dépend la protection du domicile. Au premier rang de ces garanties se trouve le contrôle du juge judiciaire. L'ensemble des garanties en question a été particulièrement renforcé après l'arrêt Ravon de la Cour européenne des droits de l'homme, qui a subordonné le contentieux des visites fiscales au droit à un procès équitable. Leur aptitude à répondre aux exigences d'un équilibre subtil est la clé de la prépondérance des garanties procédurales en la matière. Celles-ci permettent, d'une part, de tempérer un déséquilibre structurel au stade d'autorisation et d'exécution des visites fiscales, qui se caractérisent par leur nature unilatérale et qui mettent sous pression le respect du domicile, tandis que, d'autre part, elles stimulent l'équilibre déjà présent après la visite fiscale, moment auquel la personne bénéficie du droit à un recours juridictionnel. A côté de ces garanties, les lacunes, tout aussi procédurales, du régime n'ont pas permis de davantage promouvoir cette difficile conciliation et de mieux protéger le domicile. A travers leurs effets négatifs, le renforcement des garanties procédurales réapparaît comme la condition indispensable d'amélioration de cette protection. Cette prépondérance des garanties procédurales se retrouve au sein du contrôle des visites fiscales par le juge judiciaire. Ce contrôle est réel et sérieux et peut ainsi être qualifié d'effectif. Pour autant, sa structure ne se calque pas pleinement sur les garanties de procès équitable. Ainsi, l'efficacité du contrôle du juge judiciaire est réduite. La prise en compte des garanties procédurales résurgit comme la condition indispensable de protection du domicile. Parallèlement avec le juge judiciaire civil, ad hoc compétent en matière de visites fiscales, le juge pénal renonce à contrôler cette mesure, bien que son contrôle soit une garantie indispensable et de nature à consolider les garanties procédurales et à mieux préserver le domicile. Son contrôle se caractérise également par une méconnaissance des garanties nécessaires pour assurer le caractère équitable du procès pénal.Le dénominateur commun de l'ensemble du régime des visites fiscales est la force des garanties procédurales, afin de protéger le domicile. Par ailleurs, ce régime a fonctionné comme un point de départ de leur extension, notamment en matière de perquisitions pénales. Un fond commun de garanties procédurales, assurant la protection du domicile, a priori et a posteriori, se forge progressivement et donne les garanties entourant les visites fiscales demeurent le noyau.
Keywords: Contrôle juridictionnel; Domicile (protection); Droits de la défense; Défense (procédure civile); Fraude fiscale; Fundamental defense rights; Garanties procédurales; Home protection; Inviolabilité; Judicial authority; Judicial control; Juge civil; Juge judiciaire; Juge pénal; Perquisition; Perquisitions et saisies; Procedural guarantees; Procès équitable; Respect du domicile; Saisie; Seizure; Visite fiscale

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
http://hdl.handle.net/10962/419230
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Le mobile de l'exclusion de la société unipersonnelle de l'Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA) dans la création de la banque en République Démocratique du Congo: une exigence prudentielle - Omoy, Alain-Alexis Musengie Kamanda (Recht in Afrika, 2023)
La banque est une entreprise dont les conditions de création et de fonctionnement sont fortement réglementées. Sa création est une démarche juridique à deux niveaux, dont la création d'une société commerciale d'abord, et ensuite la transformation de la société en banque. Le législateur de l'Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA) amène une innovation en matière des sociétés avec possibilité de la création d'une société unipersonnelle, celle-ci présente l'avantage de faciliter la création d'entreprises par les particuliers en réduisant le circuit informel qui caractérise le monde des affaires en Afrique. Pour préserver sa stabilité, seule la personne morale en général, et la société anonyme en particulier, est autorisée à se transformer en banque. Toutefois, les conditions liées à l'actionnariat peuvent limiter l'accès de la société à la profession bancaire; tel est le cas de la société unipersonnelle. Les normes prudentielles sont strictes en ce qui concerne la forme et les conditions de création d'une banque. La banque joue un rôle très important dans l'économie d'un pays, qu'elle ne peut être laissée à toute personne. Les normes prudentielles tiennent à la stabilité du secteur bancaire à travers l'actionnariat, celui-ci joue un rôle important dans le fonctionnement de la banque. La société unipersonnelle n'offre pas des garanties nécessaires de stabilité pour se constituer en banque, étant donné qu'elle est soumise à la volonté d'un seul individu représentant l'assemblée générale de la société.

L'indemnisation des préjudices boursiers en droit financier UEMOA - Passizi, Tchilalou (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
En droit financier UEMOA, le dispositif de protection des investisseurs se préoccupe beaucoup plus de la prévention des préjudices en ne s’intéressant à leur indemnisation que dans une moindre mesure. Prévoir la possibilité de recours aux modes alternatifs de règlement de conflit reste insuffisant pour régler la question de l’indemnisation des préjudices subis par les investisseurs sur le marché financier régional. En l’état actuel du droit UEMOA, il demeure toujours difficile d’assurer la réparation des préjudices boursiers en appliquant le droit commun de la responsabilité civile lorsque les investisseurs exercent leurs actions devant le juge civil. Pour une meilleure réparation des préjudices boursiers, il convient dans un premier temps de trouver des remèdes au mécanisme d’indemnisation existant et dans un second temps, de prévoir la possibilité de création d’un tribunal commun du marché financier régional.
Keywords: Action de groupe; Perte de chance; Préjudice boursier; Réparation intégrale

La protection des renseignements personnels du consommateur dans un système bancaire ouvert : étude comparative entre le droit canadien et le droit québécois ainsi que le droit de l'Union européenne et le droit français - Rakotomandimby, Lauriane (Université Laval, 2023)
Dans un marché bancaire oligopolistique, marqué par un nombre limité d'institutions bancaires et financières offrant des services bancaires de plus en plus innovants et attractifs à une quantité innombrable de consommateurs, le système bancaire ouvert a engendré la multiplicité de ces services, grâce aux entreprises de technologie financière qui se présentent comme des concurrentes de taille face aux banques traditionnelles. Désormais, le consommateur peut procéder à des transactions électroniques, dont celles relatives au paiement ou au transfert électronique de fonds, sans devoir passer au comptoir de sa banque traditionnelle. Depuis la mise en place du Règlement général sur la protection des données et de la Directive révisée sur les services de paiement au niveau de l'Union européenne, les entreprises commerciales peuvent avoir accès aux renseignements personnels, dont les données financières des clients de banques, notamment pour initier un paiement, par le truchement des interfaces de programmation d'applications. Toutefois, le traitement des renseignements personnels des consommateurs par les entreprises commerciales augmente le risque de vol d'identité, étant donné la présence d'une quantité impressionnante de données sur le Web, sans un contrôle adéquat pour en assurer la confidentialité. Les conséquences d'une fuite de ces données sont pourtant non négligeables, aussi bien à l'égard de la banque, de la personne concernée que de l'État qui doit en assurer une protection optimale. Devant ce phénomène où le consommateur est vulnérable, l'État intervient pour le protéger et contrebalancer le déséquilibre dans sa relation contractuelle avec les prestataires de services financiers.
Keywords: Approche comparée; Confidentialité des données; Consommateur; Droit comparé

Regard critique sur le recouvrement forcé de l’impôt au Cameroun - Tchatat Nya, Raoul (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
La préoccupation du recouvrement forcé de l’impôt au Cameroun ne date pas d’aujourd’hui. Elle a toujours retenu l’attention de la doctrine et de la jurisprudence au-delà des règles posées par le législateur fiscal. C’est la raison pour laquelle dans le cadre de notre démarche, une question essentielle nous est apparue fondamentale : compte-tenu des prérogatives de l’administration des impôts, peut-on affirmer que les procédures de recouvrement forcé telles qu’édictées dans les textes fiscaux et effectuées dans les faits, garantissent-elles l’épanouissement du contribuable ? la réponse à ce questionnement nous permettra d’évoquer une pratique du recouvrement forcé de l’impôt renforcée par les entorses avant d’analyser par la suite, une pratique du recouvrement forcé de l’impôt à améliorer par l’administration fiscale et le contribuable.
Keywords: Contribuable; Fisc; Impôt; Pratique; Recouvrement forcé

Regards sur l'ineffectivité de la sanction pénale des infractions fiscales au Cameroun - Tchatat Nya, Raoul (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
La préoccupation de l’ineffectivité de la sanction pénale des infractions fiscales au Cameroun ne date pas d’aujourd’hui. Elle a toujours retenu l’attention de la doctrine et de la jurisprudence au-delà des règles posées par le législateur fiscal. C’est la raison pour laquelle dans le cadre de notre démarche, une question essentielle nous est parue fondamentale : Au regard des atteintes liées à la mise en application de la sanction pénale des infractions fiscales et des incidences qui en découlent, peut-on encore dire que, celle-ci est effective ? la réponse à ce questionnement nous permettra d’une part, d’évoquer les raisons de cette ineffectivité, avant d’analyser d’autre part, les conséquences fiscales et les tentatives de solutions pour rendre cette sanction effective au Cameroun.
Keywords: Fisc; Impunité; Incivisme; Ineffectivité; Infractions fiscales; Sanction pénale

L'efficacité du recouvrement par l'Etat des recettes fiscales de la taxation sur la consommation : Etude du cas de la TVA au Togo - Tchitare, Mawèdéou (Université de Montpellier, 2022)
Le but de notre étude est de parvenir à un recensement puis à une typologie des difficultés en matière fiscale au Togo, précisément en termes de TVA, notamment le vécu quotidien entre l'Administration et les contribuables. Ainsi arriverons-nous, au travers des données tirées de nos différentes sources, à apporter des solutions aux difficultés ainsi répertoriées en incitant vivement l'Etat à la revalorisation et à la récupération des recettes fiscales inhérentes à la ressource TVA. L'intérêt porté à la TVA découle de l'importance de cet impôt au regard du volume des recettes fiscales étatiques. The aim of our study is to get to a census and to a typology of difficulties as far as fiscal system is concerned in Togo precisely concerning VAT, especially the experienced of relations between the Civil Service and the taxpayers. Thus, we will get trough some drawn data of our various sources, to bring solutions to problems thereby catalogued by urging vividly the state to the redress, to the revaluation, and to the recovery of fiscal incomes inherent to the VAT resource. The interest in VAT arises from the importance of this tax in relation to state's tax revenues.
Issue: 2022UMOND030
Keywords: Consumption taxing; Efficacité; Efficiency; Fiscal receipts; Recettes fiscales; Recouvrement; Recouvrement de l'impôt; Recovery; TVA; Taxation sur la consommation; Taxe sur la valeur ajoutée; Togo; VAT

Une analyse juridique comparative de la criminalité financière du point de vue du Royaume d'Arabie Saoudite et de la France - Radeef, Alhassan (Université Côte d'Azur, 2022)
La recherche s'est concentrée sur la lutte contre la criminalité financière, en interrogeant ce qu'est la criminalité financière et la pertinence de sa lutte. Dans ce contexte, l'examen critique des politiques anti-crimes financiers au Royaume part de l'hypothèse qu'initialement, les efforts internationaux pour lutter contre les crimes financiers se sont concentrés principalement sur certaines formes spécifiques. Il s'agit notamment du blanchiment d'argent et du financement du terrorisme, même si tout crime financier est presque certainement à un impact négatif sur les économies concernées. Pour se faire, notre recherche a adopté une approche comparative de la lutte juridique contre les crimes financiers dans l'Arabie Saoudite et la France, avec un accent particulier sur le rôle des intermédiaires financiers dans certaines formes spécifiques de crimes.Pour mener à bien l'analyse tout au long de cette recherche, nous avons présenté la situation de lutte contre le crime économique et de la législation qui les accompagne dans chaque pays dans une perspective à la fois historique et juridique, en fournissant si nécessaire une critique de leur efficacité. Afin d'explorer comment les stratégies de criminalité économique de l'Arabie Saoudite pourraient être améliorées, notre recherche a adopté une approche comparative analysant les réponses politiques et législatives à la criminalité économique en France sur quatre chapitres distincts.les chapitres traitent du cadre théorique pour les marchés financiers, où nous aborderons dans la première partie la définition et les rôles des marchés financiers, leurs origines et ses différentes phases de développement, aussi bien en France qu'en Arabie Saoudite. Elle portera également sur une catégorie particulière d'acteurs sur ces marches : les intermédiaires financiers.La seconde partie de ce chapitre nous allons examiner la question suivante: quels sont les crimes et délits des intermédiaires? La finance et ses sanctions dans le système saoudien? Quelles sont les points de convergences et de divergences dans la qualification des crimes et leurs sanctions entre le législateur saoudien et français pour limiter les crimes et délits sur le marché financier ? The research focused on the fight against financial crime, questioning what financial crime is and the relevance of its fight. In this context, the critical examination of anti-financial crime policies in the Kingdom starts from the assumption that initially, international efforts to fight against financial crimes focused mainly on certain specific forms. These include money laundering and the financing of terrorism, although any financial crime is almost certainly to have a negative impact on the economies concerned. To do so, our research adopted a comparative approach to the legal fight against financial crimes in Saudi Arabia and France, with particular emphasis on the role of financial intermediaries in certain specific forms of crime.To carry out the analysis throughout this research, we have presented the situation of the fight against economic crime and the legislation that accompanies them in each country from both a historical and legal perspective, providing if necessary a criticism of their effectiveness. In order to explore how Saudi Arabia's economic crime strategies could be improved, our research adopted a comparative approach analyzing policy and legislative responses to economic crime in France in four separate chapters.the chapters deal with the theoretical framework for financial markets, where we will discuss in the first part the definition and roles of financial markets, their origins and their different phases of development, both in France and in Saudi Arabia. It will also focus on a particular category of players on these markets: financial intermediaries.The second part of this chapter we will examine the following question: What are the crimes and misdemeanors of intermediaries? Finance and its sanctions in the Saudi system? What are the points of convergence and divergence in the qualification of crimes and their sanctions between the Saudi and French legislators to limit crimes and misdemeanors on the financial market?
Keywords: Arabie saoudite; Criminal law; Criminalité des affaires; Droit financier; Financial intermediaries; Financial law; France; Infractions économiques et financières; Intermediaires finançiers; Loi criminelle; Marché financier; Stock market

Situation of Earning Management After Revision of the Ohada Accounting Standards Adopted on January 26, 2017 - Georges, Wandji; Nebasi, Akoso Wilfred (Law and Economy, 2022)
Following the mandatory adoption of the revised OHADA Accounting Standards that have moved closer to the International Financial Reporting Standards (IFRS), this study examines whether the level of Earnings Management of Companies making public offers or listed firms, in the West African Stock Exchange Market Abidjan-Ivory Coast (BRVM) has reduced. The study avails of Financial Statement figures during pre-adoption (2014–2017) and post-adoption (2018–2021) periods, for 26 selected listed firms in the BRVM. Findings suggest that firms in the post-adoption period of the revised OHADA Accounting Standards (2018–2021) are less likely to smooth earnings compared to the pre-adoption period (2014–2017). This indicates that adopting accounting standards of higher quality can bring an improvement in Financial Reporting Quality, everything being equal.
Number: 4
Keywords: Earnings management; IFRS; International Financial Reporting Accounting Standards (IFRS); Revised OHADA Accounting Standards; SYSCOHADA

Les monnaies virtuelles : essai sur l'intégration d'une nouvelle classe d'actifs dans les concepts fondamentaux du droit privé - Guillebon, Thibaud (Université de Bordeaux, 2022)
Les États et leur droit sont concurrencés par l’émergence d’une grande diversité d’objets numériques, que l’on a pris l’habitude de considérer comme des monnaies virtuelles. L’expression de monnaie virtuelle est d’abord apparue pour désigner les monnaies et actifs de jeux en ligne puis les systèmes de soldes prépayés et de fidélisation en ligne créés dans le cadre de réseaux commerciaux. Pour autant, le phénomène a pris une ampleur considérable avec l’apparition des crypto-actifs, catégorie qui désigne les crypto-monnaies (bitcoin, ether, monero…) et les jetons émis en blockchain (jetons d’usage, jetons financiers, stablecoins). Bien qu’ils soient nés hors des cadres étatiques, les ordres juridiques se saisissent de ces objets qu’ils soumettent à des réglementations existantes ou sui generis afin de cantonner les risques posés par leur développement tout en bénéficiant des retombées économiques positives. Compte tenu de l’instabilité qui affecte tant le marché des monnaies virtuelles que leur environnement juridique, une étude juridique d’ensemble du phénomène impose de suivre une démarche conceptuelle qui consiste à partir des propriétés de l’objet à qualifier afin d’en réaliser l’intégration dans les ordres juridiques. Dans ce cadre, les monnaies virtuelles peuvent être envisagées comme une nouvelle classe d’actifs numériques, émis par un acteur privé dans le cadre d’un système informatique, qui peuvent servir de substitut monétaire. Certains de ces actifs sont représentatifs d’une promesse juridique d’un émetteur ou d’un tiers. D’autres sont des choses, constitutives de valeurs et objets de propriété. À cette dualité correspond la summa divisio des biens incorporels qui oppose les droits incorporels et les propriétés incorporelles. C’est sur la base de cette division fondamentale qu’il est proposé d’insérer cette nouvelle classe d’actifs dans les concepts fondamentaux du droit privé.
Keywords: Actifs numériques; Biens; Bitcoin; Blockchain; Commodity money; Crypto-Currency; Crypto-Monnaie; Digital assets; Electronic money; Goods; In-game currency and assets]; Jetons; Mondes virtuels; Monnaie représentative; Monnaie électronique; Monnaie-marchandise; Monnaies et actifs de jeux; Propriété virtuelle; Representative money; Token; Virtual property; Virtual worlds

Impact of Lack of Self-efficiency and Assets Evaluation on Resistance of IPSAS Implementation - Alhuda Tawffek Al-otoom, Nour; Alrabba, Hussein Mohammed (Information Sciences Letters, 2022)
This study examines factors influencing the international public sector accounting standards (IPSAS) implementation and presenting of accounting information related to the Jordanian public sector, also the information of reports is based on “Accounting principles and practices (No.39/1962) among government accountants. This study identified several important factors influencing the IPSAS implementation which are; lack of self-efficiency and assets evaluation. In addition, a quantitative approach was employed by distributed the questionnaires to 100 respondents enrolled at Jordanian General Budget Department using simple random sampling. The data were analyzed using SPSS to verify the relationships between the variables. The results found significant positive relationships between lack of self-efficiency and assets evaluation and IPSAS implementation resistance among government accountant in the public sector of Jordan. To sum up, this study contributes in expanding the literature concerning IPSAS implementation in Jordanian context, it’s also provides meaningful guideline to the government of Jordan for IPSAS implementation resistance. Finally, providing insights on the critical success factors to ensure successful implementation process.
Keywords: Accrual Accounting; Assets Evaluation; IPSASs; Public Sector Accounting; Self-efficiency

A interdisciplinaridade do Direito Societário e do Direito Tributário: da desvinculação do balanço societário para fins tributários. O lucro contábil das concessionárias de serviços públicos de transmissão de energia elétrica - Ippolito, Marcelo Baeta (Universidade de São Paulo, 2022)
O tema que envolve as diferenças entre o lucro contábil para fins societários e para fins tributários é sempre polêmico, ainda que o lucro, para fins societários, no Brasil, seja utilizado como ponto de partida para a determinação da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesta tese, entretanto, estas diferenças serão abordadas sob ângulos diferentes e com base em situações contemporâneas e pragmáticas que expõem, com maior profundidade e clareza, as razões e fundamentos delas, de modo que, a despeito da reconhecida contribuição da interdisciplinaridade envolvendo o direito societário e a contabilidade e, por outro lado, o direito societário e o direito tributário, tendo como objeto de conhecimento o referido lucro contábil, será possível, especialmente por conta das novas dificuldades trazidas pela introdução do novo padrão contábil no Brasil, provar a conveniência e a necessidade da desvinculação do lucro contábil e suas respectivas regras de apuração, nos termos da legislação societária, para efeito de consideração como ponto de partida, de acordo com as regras atuais, para apuração da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesse sentido, inicialmente, o caminho a ser trilhado no presente trabalho de pesquisa e desenvolvimento da tese de doutorado é determinado pela consideração do direito como objeto cultural, criado pelo homem e, como tal, para ser conhecido e apreendido, necessário se faz a sua expressão em linguagem. Por outro lado, importante abordagem do tema levará em consideração que há independência da linguagem em relação à realidade, bem como que a mesma linguagem constitui a realidade conceptual que, por sua vez, é a única passível de ser objeto de conhecimento. Portanto, é possível afirmar que uma das contribuições originais da tese corresponde a essa abordagem do lucro como uma realidade conceptual, constituída pela linguagem contábil, na medida em que será capaz de fornecer maiores subsídios e elementos para melhor se mensurar as dificuldades do compartilhamento desse objeto de conhecimento pelo direito societário e tributário, promovido pela interdisciplinaridade desses ramos do direito, especialmente quando a realidade conceptual que atende aos interesses específicos do direito societário se distanciou enormemente da realidade conceptual que se quer regular por meio do direito tributário, tendo em vista a aplicação de novas normas sintáticas, semânticas e pragmáticas da linguagem contábil. Para efeito de se demonstrar o distanciamento das realidades conceptuais correspondentes aos objetos de conhecimento do direito societário e tributário, a utilização das demonstrações financeiras das Concessionárias de Serviços Públicos de Transmissão de Energia Elétrica como parâmetro traz, também, originalidade à tese, correspondendo à prova efetiva de como a utilização do lucro contábil societário, também para fins tributários, pode gerar mais dificuldades para ambas as áreas do direito do que contribuições positivas.
Keywords: Accounting; Concessionaires; Concessionárias; Contabilidade; Interdisciplinaridade; Interdisciplinarity; Lucro; Profit; Public Utilities; Serviços Públicos

Os Títulos de Crédito de Securitização Setoriais: o caso das emissões de Certificados de Recebíveis Imobiliários e de Certificados de Recebíveis do Agronegócio - Cerqueira, Bruno Saraiva Pedreira de (Universidade de São Paulo, 2022)
Os Certificados de Recebíveis Imobiliários (CRI) e os Certificados de Recebíveis do Agronegócio (CRA) têm sido amplamente utilizados no mercado de capitais brasileiro nos últimos anos. Tais títulos, criados originalmente para o mercado de securitização imobiliária e do agronegócio, não necessariamente representam operações de securitização propriamente ditas mas integram uma forma de incentivo fiscal concedido aos referidos setores da economia brasileira. Com a edição da Lei nº 14.430, de 03 de agosto de 2022 passou a ser possível a emissão de outros títulos de crédito no âmbito das operações de securitização, persistindo ainda os CRA e os CRI e os seus respectivos incentivos. O presente trabalho procura estudar o regramento aplicável às emissões de CRA e de CRI, incluindo o enquadramento desses títulos como operações de securitização, considerando os conceitos clássicos existentes, e a avaliação dos atuais incentivos fiscais existentes. Adicionalmente, estudar-se-á os emissores dos CRA e dos CRI, as denominadas companhias securitizadoras, considerando a recente regulamentação editada pela Comissão de Valores Mobiliários, qual seja a Resolução nº 60, de 23 de dezembro de 2021.
Keywords: CRA; CRI; Certificat de créance; Créance agroalimentaire; Créance immobilière; Sectors securitization; Securitização; Titres de crédit; Titrisation; Títulos de crédito

Responsabilidade civil por falha informacional no mercado de valores mobiliários: pressupostos e análise crítica - Ferreira, Mariana Martins Costa (Universidade de São Paulo, 2022)
O presente estudo teve como objetivo analisar os pressupostos e efeitos do regime geral de responsabilidade civil aplicáveis às falhas informacionais no mercado de valores mobiliários. A tese sustenta que (i) a responsabilidade civil por falhas informacionais é extracontratual, (ii) a falha informacional - comissiva ou omissiva - pode causar danos residuais, em caso de dolo na subscrição, e danos informacionais, em caso de distorção do preço da aquisição ou da venda dos valores mobiliários, (iii) o dano informacional depende (a) da aquisição ou venda de valores mobiliário no período entre a falha informacional e a descoberta, e (b) da correção do preço dos valores mobiliários na descoberta da falha informacional, (iv) o nexo de causalidade pode ser demonstrado por meio de estudos econométricos, (v) com base em juízo de probabilidade lógica, o julgador deve determinar a suficiência do estudo econométrico para demonstrar o nexo de causalidade, (vi) o dano informacional é a diferença entre o preço de aquisição ou de venda e o preço hipotético que deveria ter se formado, se não tivesse ocorrido a falha informacional, (vii) tanto a companhia como os administradores podem ser responsabilizados por danos causados por falhas informacionais, (viii) os titulares de valores mobiliários que adquiriram valores mobiliários por preço inflacionado ou venderam valores mobiliários por preço deflacionado podem ser lesados pela falha informacional, (ix) a responsabilidade civil possui função compensatória e não dissuasória, (x) com base no regime geral, a responsabilidade civil por falha informacional no mercado de valores mobiliários não consegue nem atender à função compensatória, nem colaborar para o funcionamento do sistema de tutela dos investidores. Ao final, são apresentadas propostas de lege ferenda para aprimorar o sistema legal de tutela do investidor, em especial, as normas de direito processual e de direito material sobre a responsabilidade civil por falha informacional no mercado de valores mobiliários.
Responsabilité civile pour manque d'information sur le marché des valeurs mobilières : hypothèses et analyse critique
Keywords: Civil liability; Disclosure violations; Falha informacional; Mercado de valores mobiliários; Responsabilidade civil; Securities market

Comparison of IAS/IFRS and OHADA standards in terms of taking inflation into account in financial accounting - Matofali, Victoire (Revue du Contrôle de la Comptabilité et de l’Audit, 2022)
Financial accounting is one of the indispensable management tools in an organization, its objective is to present financial statements that reflect a true and fair view of the assets, financial position and results of the entity. In times of high inflation, however, money loses its purchasing power at such a rate that comparing amounts resulting from transactions and other events that occurred at different times, even during the same accounting period, can be misleading. This can cause the figures in the financial statements to be misleading. It is therefore essential to adjust these figures to the actual economic conditions in order to preserve a true and fair view of the company's assets, financial position and results. International financial standards such as those of OHADA analyze this problem of inflation in accounting through different methods of restatement of the figures of the financial statements to make them faithful and consistent with the economic reality. In this work, we will identify the points of divergence as well as the points of convergence between OHADA and IAS/IFRS accounting standards in terms of inflation accounting.
CERN European Organization for Nuclear Research
Keywords: Accounting; IAS/IFRS; Inflation; Standardization

L'effet des critères ESG sur les décisions d'investissement - Outouzzalt, Ahmed; Elouidani, Abdelkbir; Elouidani, Rania (Revue des Études Multidisciplinaires en Sciences Économiques et Sociales, 2022)
L’investissement durable, contrairement aux autres approches, ne requiert pas de rejeter des investissements au regard de leurs secteurs d’activité ou d’investir dans des instruments spécialisés. Il entraine simplement de prendre en compte les critères de l’environnement, le sociale et la gouvernance dans la prise de décision d’investissement. Les questions environnementaux, sociaux et de gouvernance sont considérées comme les trois piliers de la durabilité, et leur intégration dans les décisions d'investissement est en pleine croissance dans le monde entier. Au Maroc, la bourse de Casablanca a mis en place en 2018 un indice boursier nommé « Casablanca ESG 10 ». Cet indice calcule la performance des cours boursiers des entreprises socialement responsables sur la base de critères environnementaux, sociaux et de gouvernance. C’est un dispositif de reconnaissance et de prise en compte des engagements sociaux et environnementaux, ce qui entraine un terrain de recherche promoteur. Par conséquent, Cette étude nous a permis de mettre en évidence des facteurs environnementaux, sociaux et de gouvernance d’entreprise qui influencent la décision d’investissement chez les investisseurs individuels marocains. Les résultats ont montré que les critères sociaux et de gouvernance est parmi les facteurs jugés significatifs par notre modèle de recherche qui affecte directement l’intention d’investissement et indirectement la participation au marché boursier.
Keywords: Comportement des investisseurs; ESG; Investissement durable; Marché boursier

La naissance de la comptabilité patrimoniale en droit budgétaire du Cameroun - Meyampi Winco, Berlin (International Multilingual Journal of Science and Technology, 2022)
Des reformes entreprises dans le système de gestion des finances publiques (SGFP) au Cameroun, la comptabilité patrimoniale s’avère être le dernier né en 2022, qui complète le tri-type de comptabilité publique consacré par la loi portant Régime financier de l’Etat de 2007 notamment à son article 61. Cette naissance précédée d’une gestation d’un peu plus d’une décennie a atteint le terme en janvier notamment par le décret n° 2019/3199/PM du 11 septembre 2019 qui fixait l’obligation d’application de certaines dispositions contenues dans ce texte au 1er janvier 2022, dont celles de la comptabilité patrimoniale. Cet acte de naissance avait de ce fait une valeur temporelle immédiate et progressive, et présente après cette échéance des enjeux forts intéressants qui laissent poser la question de sa mise en œuvre à l’avenir. Of the reforms undertaken in the public finance management system (SGFP) in Cameroon, accrual accounting turns out to be the last born in 2022, which completes the tri-type public accounting enshrined in the law on the Financial Regime of the State of 2007 in particular in its article 61. This birth, preceded by a gestation period of just over a decade, reached completion in January, in particular by decree n° 2019/3199/PM of September 11, 2019 which set the obligation to apply certain provisions contained in this text as of January 1, 2022, including those of accrual accounting. This birth certificate therefore had an immediate and progressive temporal value, and presents after this deadline very interesting issues which raise the question of its implementation in the future.
Keywords: Cameroon; Cameroun; Comptabilité Patrimoniale; Finances Publiques; Financial Regime; Patrimonial Accounting; Public Finances; Régime Financier

آليات تقييم الصيرفة الاسلامية في البنوك التجارية وتحدياتها -دراسة حالة البنك الوطني الجزائري - ساعد, بن; الحميد, عبد (Ibn Khaldun University of Tiaret, 2022)
يعتبر النظام المصرفي من بين الأسس التي يعتمد عليها النشاط الاقتصادي لأي مجتمع و ذلك بالنظر لأهمية الدور الذي يلعبه في المساهمة في إمداد النشاط الاقتصادي بالأموال، اللازمة من اجل تنميته و تطوي ره ، وقد اجمع الباحثون الاقتصاديون على أن من بين أسباب الأزمات المالية ترجع إلى الأسلوب الربوي المتبع من طرف البنوك التقليدية، خصوصا بعد أن ضربت الأزمة المالية العالمية عصب الاقتصاد الرأسمالي سنة 2008 وهزت اقتصاديات الدول وأضعفت البنوك التجارية خلافا عن البنوك الإسلامية والبنوك التجارية ذات الشبابيك الإسلامية ، ومن هذا المنطلق ازدادت الحاجة إلى وجود بنوك تعمل وفقا للشريعة الإسلامية والتي تقوم على أساس إلغاء الفائدة وعدم التعامل بالربا في تعاملاتها، ومنه فقد أصبحت هذه البنوك لاعبا مؤثرا وبارزا في اقتصاديات الدول الإسلامية و العالمية و التي من بينها الجزائر التي اتجهت هي الأخرى للدخول إلى عالم الصیرفة الإسلامية باعتمادها لافتتاح نوافذ إسلامية على مستوى البنوك العمومية. ومن خلال دراستنا توصلنا الى أن البنوك العمومية الجزائرية تحاول خوض تجربة فتح شبابيك إسلامية وقد خلصنا بأن اعتماد هذه البنوك على آلية التعامل بشبابيك تعمل وفق قواعد الشريعة الإسلامية في معاملاتها المالية من شأنه أن يحقق استقطاب ورضا الزبائن. The banking system is considered one of the foundations on which the economic activity of any society is based, given the importance of the role, it plays in helping to supply economic activity with the funds necessary for its operation. Economic researchers have agreed that among the causes of financial crises are due to the usurious method adopted by banks, especially after the global financial crisis hit the backbone of the capitalist economy in 2008, shook the economies of the countries, and weakened commercial banks unlike Islamic banks and commercial banks with Islamic windows From this point of view, the need has grown for the existence of bank operating in accordance with Islamic law, which is based on the abolition of interests in their financial transactions, these banks have become an influential and leading actor in the economies of Islamic countries including Algeria, which has also tended to enter the Islamic banking world by adopting it to open Islamic windows at the level of public banks. Through our study, we concluded that Algerian public banks are trying to live with the opening of Islamic counters, and we concluded that the dependence of these banks on the processing mechanism of counters that operate according to the rules of Islamic Sharia law in their financial transactions, would attract and satisfy customers.
Keywords: Banques commerciales; Banques islamiques; Fenêtres islamiques; Satisfaction client; البنوك الإسلامية; البنوك التجارية; النوافذ الإسلامية; رضا الزبائن

L’influence des caractéristiques du système d’information comptable sur la performance financière des PME manufacturière en Côte d’Ivoire - Toure, Ousmane Aboubakar; Kouadio, Koffi Raymond (International Journal of Strategic Management and Economic Studies (IJSMES), 2022)
Notre étude vise à analyser l’influence des caractéristiques du Système d’Information Comptable sur la performance financière des PME en Côte d’Ivoire. La revue de la littérature a permis le développement d’un cadre conceptuel et la mise en exergue de la relation entre les caractéristiques du Système d’Information Comptable (SIC) et la performance financière des PME. La méthode des équations structurelles a été utilisée afin de tester les relations de cause à effet établies dans le cadre de notre modèle conceptuel. Les données de cette étude proviennent d’une enquête menée sur un échantillon de convenance composé de 216 PME installées à Abidjan. Les résultats des tests d’hypothèses obtenus par le canal d’équations structurelles sur AMOS 23 montrent que l’organisation comptable, la production des données comptables et l’utilisation des données comptables (trois dimensions du SIC) ont un effet positif et significatif sur la performance financière des PME étudiées. A l’instar de ces résultats, nous avons fait des recommandations en vue d’une meilleure gestion des PME en Côte d’ivoire.
Keywords: Performance financière; Petite et Moyenne Entreprise; Système d’information comptable

L'imposition des bénéfices des multinationales du numérique dans l'État de consommation - Rombourg, Florent (Université de Montpellier, 2022)
En cette année 2022, la création d'un nouvel ordre fiscal international semble se profiler. La solution OCDE Pilier 1 et Pilier 2 adoptée par près de 140 Etats marque en effet une rupture avec les cadres traditionnels de répartition des droits d'imposition. Les raisons ayant amené le Cadre inclusif de l'OCDE à agir sont connues. L'établissement stable et le principe de pleine concurrence ne permettraient plus dans une économie numérisée d'assurer une répartition équitable de la matière imposable entre États. Alors que les États à fiscalité privilégiée, abritant le siège de plus grands groupes d'entreprises, seraient les principaux bénéficiaires de cette situation, les États de consommation en seraient les principales victimes. L'entreprise d'une refondation du droit fiscal international serait d'autant plus urgente que la dégradation de l'alliance entre le citoyen et l'impôt ne cesse de s'accentuer à mesure que s'installent sur les marchés des acteurs puissants de l'Internet comme les GAFAM, NATU ou autres BATX. Le goût prononcé de ces entreprises multinationales « globales » pour le « libertarianisme », conduit en effet à douter du bien-fondé d'une centralisation des attributs régaliens au niveau de l'État, et laisse présager l'institution d'un monde nouveau qui se structurerait horizontalement en dehors de toute intervention étatique.Toutefois, il ne saurait être choisi la voie d'une rupture avec le système actuel sans une démonstration de l'obsolescence des bases juridiques de répartition des droits d'imposition. C'est ainsi que la présente thèse a pour objet d'étudier précisément les normes sur lesquelles reposent la répartition de la compétence fiscale et des profits entre sociétés apparentées, leur mobilisation par l'administration fiscale et leur interprétation par le juge administratif français, afin de déterminer si le jugement récurrent d'obsolescence dont elles sont victimes est fondé.
Keywords: Beps; Digital economy; Fairness; Permanent establishment; Pilier 1 et 2; Pillar 1 and 2; Prix de cession interne; Prix de transfert; Transfert pricing; Économie numérique; Équité; Établissement stable; Établissements stables

Banks responsibility in the collection of the commercial paper contract - Al-Shawabkeh, Wa’ed (Al-Balqa Journal for Research and Studies, 2022)
The importance of studying this contract is to establish the legal nature of the bank’s responsibility when it fails to collect the value of the commercial paper, and to know the role and direction of the judiciary in that respect. The study relied on the element of analysis and education in a brief scientific way. The purpose of the study is to examine the legal basis for the Bank’s responsibility in the collection contract and the general provisions for this responsibility resulting for it, and to cover that responsibility in all its aspects. The study relies on the analytical method in order to achieve the purpose and objectives of the research, where the legal texts will be analyzed and practical results will be reached. In this research legal texts will be analyzed to reach scientific results, the study also reached results, including that there was no regulation from the Jordanian legislator for the collection, in addition to the overlapping of the agency and deposit contracts in the collection contract and that the bank’s responsibility towards its client is a contractual responsibility due to the nature of the relationship between them. The research recommends that the Jordanian Trade law should include special texts dealing with the collection contract, and that the judiciary be more present while evaluating the nature of the relationship and the basis of responsibility between the bank and its client, and it should be clearly stated that the bank may require the disqualification of itself from the liability resulting from collection contract.

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

La confiance numérique dans le domaine bancaire - Julien, Marine (Université de La Rochelle, 2022)
La digitalisation progressive qu’ont connue les banques ces dernières années a permis a ces dernières d’offrir des services plus rapides, plus pratiques, et souvent plus proche des attentes de leur clientèle. Cependant, ces nouvelles pratiques sont également associées par certains à un accroissement des risques pour leurs données et patrimoines. Les banques sont ainsi contraintes de rechercher comment gagner, et garder, la confiance numérique de leur clientèle. Face à cette problématique, plusieurs leviers sont envisageables, mais c’est principalement par la règlementation qu’elle est actuellement traitée, au travers, notamment, du RGPD, du règlement eIdas et de la DSP 2. Mais la règlementation est-elle vraiment un vecteur de confiance numérique efficace ? Dans cette étude, il s’agit ainsi d’étudier le rôle de la confiance numérique et l’incidence de la règlementation sur celle-ci aux différentes étapes de la relation contractuelle. The progressive digitization that banks have experienced in recent years has enabled them to offer faster, more practical, services, and often closer to their customers’ expectations. However, these new practices are also associated by some of their clients with increased risks for their data and assets. Banks are thus forced to find ways to gain, and keep, the digital trust of their customers. Faced with this problem, several solutions are possible, but it is mainly by regulation that it is currently dealt with, through, in particular, the GDPR, the eIdas regulation and the PSD 2. But is regulation really an effective way to reinforce digital trust ? In this thesis, we study the role of digital trust and the impact of regulation on it at the different stages of the contractual relationship between a bank and its clients.
Issue: 2022LAROD002
Keywords: Banque électronique; Banques digitales; Confiance numérique; Digital Banking; Digital trust; ElDAS; GDPR; Identité numérique; Protection de l'information (informatique); RGPD

Innovative Approaches for Tackling Tax Evasion in the South African Minibus Taxi Industry: Lessons from Ghana, Zambia, and Zimbabwe - Ndlovu, Jane; Mohale, Enhle (Journal of Law, Society and Development, 2022)
In South Africa, minibus taxis are a crucial mode of public transport for many commuters and a vital informal business sector with an estimated value of R90 billion. Concerns have been raised that the South African Revenue Service (SARS) is not collecting the optimal amount of tax revenue from this industry, with estimated tax collection at only R5 million in 2021. As a result of concerns that this industry might be involved in tax evasion or massive tax avoidance, this study investigates the taxation of minibus taxis in South Africa and explores alternative tax regimes that could be implemented to improve revenue collection. The study compares the current South African turnover tax system for minibus taxi operators to other African tax systems and evaluates a viable alternative tax regime or tax collection system. To improve tax collection from the industry, South Africa could consider a tax system tailored to the industry’s informal nature, utilising metrics such as vehicle seating capacity or distance travelled. A standardised tax system for small, medium, and micro enterprises may not be suitable. Consultation with industry stakeholders is essential for the proposed tax system to be acceptable. The study’s findings could inform South Africa’s National Treasury in creating a tax structure or collection scheme targeting the minibus taxi industry. This could increase tax revenue collection from the industry and support government expenditure, including income and wealth redistribution. This study distinguishes itself from prior publications on the South African minibus taxi industry by addressing tax compliance and collection challenges. It offers recommendations for alternative tax regimes to mitigate these challenges.
Keywords: Informal sector; Micro-enterprises; Minibus taxi; Presumptive tax; Tax relief; Turnover tax

Compétence éthique des auditeurs: Facteurs d’influence dans un environnement en faillite de normalisation - Ateumo, Edith Christiane Grace; Yepgnou, Joseph NDASSI; Tonmo, Gael Simplice (Revue Française d'Economie et de Gestion, 2022)
L’objectif de cet article est de mettre en évidence, au delà des facteurs existant dans la littérature, ceux expliquant au mieux les éléments favorables à la compétence éthique des auditeurs, dans un environnement en faillite de normalisation. L’articulation de ce travail autour d’une phase quantitative, sur un échantillon de 45 cabinets d’audit inscrits à l’ONECCA a permis d’atteindre les objectifs visés. Il y ressort qu’au Cameroun les variables liées à la profession d’audit et la variable de contexte favorisent significativement la compétence éthique de l’auditeur. Plus spécifiquement, la compétence éthique de l’auditeur s’amoindrie lorsque l’engagement de l’auditeur pendant sa mission dépend du montant des honoraires qu’il a eu à négocier et entre autre, lorsqu’il entretien une relation de longue durée avec un même client. Elle est d’autant plus significative chez les auditeurs qui ont capitalisé les cours d’éthique reçus lors de leur formation pour résoudre une situation de dilemme. Par ailleurs, l’analyse ne révèle aucune relation significative entre la nature de la relation entre l’audité et l’auditeur et la compétence éthique de ce dernier.
Keywords: Audit; Compétence éthique; Facteurs contextuels; Facteurs liés à la profession d’audit; Faillite de normalisation

La réforme des administrations douanières : le cas du Tchad - Djargollo, Jairus (Université Côte d'Azur, 2022)
Cette thèse est consacrée à l’étude de la Réforme des administrations douanières pouvant se situer dans un contexte général, mais en s’affirmant tout de même sur un cas assez spécifique, concernant l’administration des douanes tchadiennes. C’est pourquoi, elle est intitulée : La Réforme des Administrations Douanières : Le Cas du Tchad.Les administrations des douanes à travers le monde, sont obligées de conduire des réformes, compte tenu de la mondialisation des échanges qui impose les principes de libre échange. C’est un combat en fait, engagé contre toute sorte des barrières douanières qui ont tendance à faire obstacle à ces échanges mondiaux. L’un des objectifs de ces réformes douanières est d’assoir une certaine politique de facilitation des échanges commerciaux internationaux. C’est pourquoi l’OMC et l’OMD collaborent étroitement dans ce sens. Elles sont aussi obligées de rechercher l’adhésion des Etats à travers le monde dans le but de mettre en œuvre le libre-échange. Cette adhésion s’exprime par la réforme des douanes qui sont au cœur des activités du commerce international. Le second objectif se situe sur le plan national, par rapport à l’objectif fixé par l’État Tchadien à travers cette réforme douanière. L’État du Tchad, cherche sur le plan national, la concrétisation de la réforme des douanes à travers un plan d’amélioration des finances publiques. Ce plan est appelé Plan d’Action pour la Modernisation de la Gestion des Finances Publiques(PAMFIP).Cette réforme est bien engagée, mais ne donne pas des résultats satisfaisants. Le choix de ce thème permet de comprendre les difficultés réelles qui se posent à cette réforme, afin de proposer des approches de solution. MOTS CLÉS: Réformes des douanes, Douane, Administration des douanes, Droit Douanier, Libre échange, Commerce International, pays en développement, intégration économique, accords internationaux, politisation et dépolitisation de l’administration. This thesis is devoted to the study of the Reform of customs administrations, which can be placed in a general context, but still asserting itself on a fairly specific case, concerning the Chadian customs administration. This is why it is entitled: The Reform of Customs Administrations: The Case of Chad.Customs administrations around the world are obliged to carry out reforms, given the globalization of trade which imposes the principles of free trade. It is a fight in fact, waged against all kinds of customs barriers that tend to obstruct this world trade. One of the objectives of these customs reforms is to establish a certain policy of facilitation of international trade. That is why the WTO and the WCO are working closely together in this regard. They are also obliged to seek the adhesion of states around the world in order to implement free trade. This adhesion is expressed by the reform of customs which are at the heart of international trade activities. The second objective is at the national level, in relation to the objective set by the Chadian state through this customs reform. The State of Chad is looking at the national level for the implementation of customs reform through a plan to improve public finances. This plan is called the Plan of Action for the Modernization of Public Finance Management (PAMFIP). This reform is well under way, but is not producing satisfactory results. The choice of this topic makes it possible to understand the real difficulties which arise with this reform, in order to propose approaches of solution.
Keywords: Administration (depoliticization); Administration (politicization); Administration douanière; Commerce international; Customs; Customs administration; Customs law; Customs officer; Customs reforms; Developing countries; Douanes; Douaniers; Droit douanier; Economic integration; Free Trade; International Agreements; International Trade

Minimiser le risque moral des établissements de crédit en République Démocratique du Congo : quid du rôle à jouer par les déposants bancaires ? - Mayembe Bin Mastaki, Gaston (Mouvements et Enjeux Sociaux, 2022)
Cette étude explique en quoi les établissements de crédit ne sont fondamentalement pas des entreprises comme les autres, de sorte que leur gouvernance devrait être spéciale. Pour que la prise de risque dans ces institutions ne soit pas excessive, cette étude propose au niveau de la supervision bancaire deux mesures qui s’attaquent à la racine du problème, autrement dit, qui traite directement la cause du problème, à savoir l’aléa moral des établissements de crédit associés aux filets de sécurité officiel, qu’il faut à tout prix réduire. En d’autres termes, d’une part, la Banque Centrale du Congo devra reconsidérer son rôle de prêteur en dernier ressort, de façon à inciter les déposants et surtout les plus grands d’entre eux à prendre en main, le contrôle et la discipline des établissements de crédit et, d’autre part, repenser le statut juridique conféré aux actionnaires dans ses institutions par le droit OHADA. Si la responsabilité des actionnaires vis-à-vis des déposants et autres créanciers reste illimitée, c'est-à-dire élargie sur leurs avoirs, ils seront plus prudents dans la gestion de l’établissement et se mettront à l’abri de toute incitation inverse en matière de politique d’octroi de crédit.

De quelques Innovations apportées par le Système comptable OHADA révisé - Mbumba Phambu, Richard; Nzila Nkuka, Hippolyte (Revue Internationale du Chercheur, 2022)
Avec l’adhésion tardive de la République Démocratique du Congo à l’espace OHADA, il s’est posé les problèmes de vulgarisation à grande échelle et d’appropriation de l’ancien acte par les différents utilisateurs. Avec la révision de l’ancien acte menant vers les IFRS, les mêmes problèmes se posent encore avec acuité. Dans le souci de faciliter l’appropriation du nouvel acte comptable de l’OHADA, cette étude tente de ressortir à l’attention des théoriciens et praticiens de la comptabilité exerçant dans l’espace OHADA, quelques innovations majeures et améliorations opérées dans l’acte uniforme relatif au droit comptable et à l’information financière. Celles-ci se rapportent aux traitements des charges immobilisées, des frais de recherche et développement, des contrats pluri-exercices, des frais accessoires d’achat, les instruments de monnaies électroniques, l’approche par composant et l’attribution gratuite d’actions au personnel et dirigeant. Nous procéderons par analyse comparative des traitements comptables de l’ancien acte à ceux de l’acte révisé.
Keywords: AUDCIF; AUOHCE; Comptabilité; OHADA révisé; Système comptable

La dématerialisation des valeurs mobilières dans l'espace OHADA : regard juridique et prospective - N'Tchatat Tounya, Fabrice Léonel (Actes de la troisième Conférence internationale sur la Francophonie économique, 2022)
Keywords: Dématérialisation; Dépositaire central; Société par actions; Valeurs mobilières

Arrimage des normes OHADA et IFRS: une analyse de la perception des dirigeants d'entreprises au Cameroun - Nyasseu, Emma Joachim; Tatsi Sop, Isidore; Yepdo, Florentin Gaël; Nkwabon, Fabrice William; Fotso Bopda, Thomas (Revue Internationale des Sciences de Gestion, 2022)
La révision du système comptable OHADA, symbole de l’évolution vers les normes IFRS, a marqué le point de réflexion de cette étude. Il est question de comprendre comment les dirigeants d’entreprises perçoivent l’évolution des normes OHADA vers les normes IFRS. Pour mener cette étude, nous avons opté pour une démarche qualitative. De ce fait, nous avons fait des entretiens semi-directs avec vingt-cinq dirigeants d’entreprises au Cameroun (18 dirigeants d’entreprises camerounaises et 7 dirigeants d’entreprises multinationales). Les données collectées ont été exploitées à travers l'analyse de contenu via le logiciel Nvivo 10. Cependant, les résultats montrent que, les innovations comptables du SYSCOHADA permettent la production et la communication d’une information comptable et financière plus pertinente pour les utilisateurs. De même les dirigeants d’entreprises multinationales pensent que l’OHADA doit converger totalement vers les normes IFRS. Cette perception est contraire à celle des dirigeants d’entreprises camerounaises qui citent le contraste contextuel comme principal obstacle et donc la prise en compte des spécificités de ce contraste sera un atout pour une convergence totale vers les IFRS.
www.revue-isg.com
Keywords: Comptabilité; Convergence; IFRS; Normes IFRS; Normes OHADA; Normes comptables; SYSCOHADA

Le secret bancaire : une institution en déclin - El Mir, Jalal (Université Paris-Panthéon-Assas, 2022)
Le secret bancaire, ou le secret professionnel du banquier, est l’obligation de l’établissement de crédit de tenir confidentielle, toutes les informations relatives aux soldes, opérations, et à l’identité de son client. Issu du devoir de confidentialité du banquier envers son client, il engendre aussi une valeur économique d’où son institutionnalisation économique comme moyen d’attirer les capitaux. Face à des pratiques abusives de dissimulation dans les réseaux bancaires, des fonds monétaires provenant de trafic de stupéfiants, de blanchiment de capitaux ou en dernier ressort de financement de terrorisme, son champ d’application s’est vu restreint par des lois lui imposant des exceptions pour ajuster son application, et menant de ce fait à l’institutionnalisation juridique de la notion. Après la crise financière mondiale de 2008, son domaine d’application se retrouve envahi par une vague de la transparence dans le monde des affaires. La notion juridique du secret bancaire qui s’était institutionnalisée se retrouve en déclin par des mouvements juridiques consécutifs de neutralisation de ses effets. Mais, son intérêt juridique demeure primordial, et sa valeur subsiste du fait de son rattachement au droit fondamental de respect de la vie privée, mais aussi pour son intérêt dans la confirmation de la confiance dans l’industrie bancaire, consacrant la notion du secret bancaire comme une valeur juridique et une nécessité. Banking secrecy, or the professional secrecy of the banker, is the obligation of the banks to keep confidential all information relating to balances, transactions, and the identity of its client. A derivative from the banker's duty of confidentiality towards his client, it also generates economic value, hence its economic institutionalization as a mean of attracting capital. Facing abusive practices of concealment in banking networks, of funds resulting from drug trafficking, money laundering or as a last resort the financing of terrorism, its scope has been restricted by laws imposing exceptions to adjust its application, and thereby leading to the legal institutionalization of the concept of bank secrecy. After the global financial crisis of 2008, its scope is vastly impacted and reduced by the wave of transparency in business environment. The legal notion of bank secrecy, which became institutionalized, is in decline due to the consecutive legal acts of neutralizing its effects. Nonetheless, its legal interest remains vital, and its value lays on the fact of its attachment to the fundamental right of respect for private life. Also, for its interest in the confirmation of confidence in the banking industry, enshrining the concept of banking secrecy, as a legal value and a necessity.
Keywords: Act of foreign sovereignty; Bank secrecy; Banques; Confidentiality; Confidentialité; Droit à la vie privée; Extraterritorial law; Fait du prince étranger; Financial Transparency; General Data protection regulation (GDPR); Law Foreign Account Tax Compliance Act (FATCA); Loi Foreign Account Tax Compliance Act (FATCA); Loi d'application extraterritoriale; Privacy; Règlement général de la protection des données (RGPD); Secret bancaire; Secret professionnel; Transparence (droit); Transparence financière; Vie privée

La production du droit par les entreprises en Afrique. Le cas du droit de la monnaie mobile dans la sphère publique camerounaise-CEMAC - Onchi Ngongang, Vanelle Dimitri (Université Côte d'Azur, 2022)
Symptomatique de la transformation technologique du droit d’hier et représentatif du droit de demain, le mobile money, ne bouleverse pas seulement le paysage financier (en l’occurrence par la remise en cause du monopole bancaire, la fragmentation des opérations bancaires et la pénétration des acteurs non bancaires notamment les Opérateurs de Télécommunication Mobile dans le paysage financier). Il heurte surtout la conception monocentrique du droit, encore omniprésente et omnipotente dans notre champ d’étude. En effet, le mobile money encore qualifié de monnaie mobile nous permet de témoigner de façon brute et factuelle de la réalité du pluralisme juridique et d’exposer dans une construction cohérente les raisons de la genèse des foyers normatifs privés ainsi que de comprendre la coexistence de plusieurs ordres juridiques dans un espace. C’est dans ce cadre que les multiples crises (crises des institutions étatiques, crises de la loi, carence et inadéquation de loi, inintelligibilité des lois, inefficacité et ineffectivité du droit étatique) qui touchent la sphère étatique ont été indexées comme sources de coûts de transaction, d’imprévisibilité, d’insécurité juridique, poussant les acteurs privés en quête d’un minimum de sécurité juridique et d’un droit adapté à leurs besoins à se livrer à une production normative. Les normes privées de la monnaie mobile ainsi produites ont, en raison de leur pertinence et de leur effectivité été incorporées dans la sphère publique, rendant par la même occasion difficile toute analyse (sans risque de se tromper) pertinente sur les sources réelles des normes en vigueur dans la sphère publique. Cette incorporation normative qui matérialise le dialogue normatif permanent entre la sphère privée et la sphère publique nous a conduit à esquisser une théorie d’interaction normative inter sphériques. Cette dernière nous semble indispensable non seulement pour rendre compte des rapports entre les ordres juridiques, entre les sources étatiques et les sources non étatiques du droit mais également pour penser la conception et la production du droit de demain. This paper defends the theory of legal pluralism in Cameroonian-CEEAC (Economic community central African States) legal order and aims to demonstrate that the omnipresence of monism in this area is incapable of describing the real legal world and the law as it is. A preliminary question not always considered in the debate, regards the existence of legal pluralism or private ordering is why private actors issue norms? The paper begins by looking at a variety of reasons why private actors produce norms and discusses in detail the concepts of the hierarchy of norms and their legal validity. The paper points out the fact that public space faced crises of state institutions regarding separation of powers, parliamentary time, terrorism and secession. These crises drawn all the attention of public space and affect its normative reactivity in the sense of regulating new activities, social practices. This legal ordering sometimes produces ineffective and unintelligible norms. There is no doubt that a poorly design law and ineffective access to the law can affect economic activities. The emergence of private norms can be explained in two different ways. It could be argued that, confront to an inadequacy law, private actors decide to subject their activities to non-state law. Produce norms is therefore a unique opportunity to private actors to free themselves from the constraints of the legal insecurity since the inadequacy or lack of state law expose them to additional transaction costs. This paper doesn’t or never claimed complete autonomy from legal system. I shall conclude that far to compete with legal space, private ordering help to discipline private actors and to organize new activities. The paper tries to explain why Mobile Network Operators (MNO) produce mobile money norms and intends to demonstrate that an increasing number of mobile money rules issued by GSMA, and MNO can be found within a corpus of rules of legal orders. We will try to identify, among layers of legal corpus rules, legal norms which originally come from private ordering. One could observe that mobile money private norms had been recognized by public actors through legal transplants. Other question not always considered in the debate, regards the existence of private norms which had not been incorporated to the contents of positive law. The importance of private norms in the regulation of mobile money system is undeniable. The mobile money private norms are an important source of public legislation, they structure mobile money operators’ agreement. It is important to be aware of their existence of private norms which has not be incorporated on state legal orders. This paper also outlines the impact of technology, more specifically of mobile money on the financial landscape and above all, the access of non-banking players MNOs in the financial landscape. By its characteristics, mobile money is on the way to change landscape of financial inclusion for unbanked countries. A financial market has born or raised around mobile money and now, Bank and other financial institutions must compete with MNOs, owners of the Unstructured supplementary service Data: which is a critical platform required to provide mobile financial services and to enable mobile financial service operators to access potential mobile money clients or to send responses to clients and confirm transactions. This relatively new roles for MNOs generate competition issues particularly in the case where one MNO in dominant position on the voice market also plays an active role in providing mobile money services or mobile financial services. Finally, this paper aims to describe and explain the various normative interaction between a private ordering and a state order especially regarding pure theory of law. To do so, we study a high number of sector (lex mercatoria) where we can verify normative interaction between legal norms and private norms. We therefore manage to theorize this normative interaction.
Keywords: Banking law; Banques; Cameroun; Communauté Economique et Monétaire de l'Afrique Centrale; Droit; Gsma; Legal pluralism; Mobile money; Mobile network operators; Monnaie mobile; Monnaie électronique; Pluralisme juridique; Responsabilité Sociale de l'Entreprise; Social Responsibility of Corporation; Sources du droit; Téléphonie mobile privée; Établissement de paiement

Stratégie(s) comptable(s) des dirigeants et détermination de la parité d’échange : cas des opérations de fusions acquisitions au Sénégal - Kandji, Mamadou (Finance & Finance Internationale, 2022)
Cette étude s’intéresse à la détermination de la parité d’échange dans les opérations de fusion acquisition effectuées au Sénégal et notamment à l’impact de la politique comptable des dirigeants des sociétés absorbantes sur la parité. Cette étude montre d’une part, que les gestionnaires des entreprises absorbantes gèrent les résultats comptables l’année qui précède la fusion. Les ajustements comptables à la discrétion des dirigeants représentent environ 17.67 % du total de l’actif économique. D’autre part, ces ajustements sont influencés par plusieurs facteurs tels que : le contrôle majoritaire qu’exerce la société absorbante sur l’absorbée, la part majoritaire des dirigeants et/ou de leur famille dans le capital de l’absorbante, le pourcentage des parts de l’Etat dans la société, l’influence des critères de nature comptable dans la détermination de la parité et la performance de la société absorbante.
Keywords: Earnings management strategy; Exchange rate; Fusion acquisition; Merger acquisition; Parité d’échange; Pouvoir; Power; Richesse; Stratégie de gestion des résultats; Wealth

Does the implementation of IFRS improve transparency regarding the company's financial conditions?: evidence from an emerging market - Ebaid, Ibrahim El-Sayed (PSU Research Review, 2022)
Purpose This study aims to examine whether there are differences between financial statements prepared in accordance with International Financial Reporting Standards (IFRS) and financial statements prepared in accordance with local accounting standards in terms of its ability to present the financial conditions of companies listed on the Saudi Stock Exchange as one of the emerging markets. Design/methodology/approach Data on study variables were obtained from the published financial statements of 67 of listed companies in the Saudi Stock Exchange during the period 2014–2019. The study addressed the research hypotheses by using Altman Z-score model. Both the T-test and Wilcoxon rank test were used to investigate the significance of differences between the values of Z-score and the individual variables included in the model in the pre- and post-IFRS mandatory adoption periods. Findings The results revealed a decrease in the values of Z-score as well as the values of the individual variables included in the model in the period following the adoption of IFRS than it was before the adoption of IFRS, which indicates the ability of IFRS to show the financial conditions of companies more transparently than local accounting standards. However, the results of the T-test and Wilcoxon test showed that these decreases were not statistically significant. Research limitations/implications This study has some limitations, including the small sample size as a result of the small size of the Saudi Stock Exchange, As well as the reliance of this study only on the Altman model with its five variables in assessing financial conditions without examining the impact of other factors that may affect the financial conditions of companies. Practical implications Financial conditions of the companies have important implications for multiple parties such as management, government, investors and others as an early warning sign that enables them to take the necessary measures early before the actual bankruptcy occurs and what results in costs. Originality/value Although assessing financial conditions of the companies is one of the basic uses of accounting information, this topic has not received sufficient attention as a means to test the benefits of adopting IFRS, especially in emerging markets such as Saudi Stock Exchange. This is the first study to examine the impact of adopting IFRS on the transparency of financial reporting in assessing financial conditions in Saudi Arabia.
Keywords: Financial conditions; IFRS; Saudi Arabia; Z-score

Does the impact of IFRS on audit fees differ between early and late adopters? - Tawiah, Vincent Konadu (International Journal of Accounting & Information Management, 2022)
Purpose This study aims to examine whether the impact of international financial reporting standards (IFRS) on audit fees differs between early and late adopters. Design/methodology/approach The authors use robust econometric estimation on a sample of 314 firms from both early and late IFRS adopting countries. Findings The authors find that IFRS is positively and significantly associated with an increase in audit fees for early adopters, but the impact is very weak for late adopters and insignificant in some cases. The results on auditing time suggest that increase in audit fees around IFRS adoption is due to an increase in audit reporting lags. After accounting for pre- and post-years, the authors find that the relationship between IFRS and audit fees, as well as audit time for late adopters, is significant only in the adoption year. However, early adopters experience a significant increase in audit fees and audit time in the transition year to one-year post-adoption. Practical implications The findings imply that countries that are yet to adopt IFRS are less likely to experience a significant increase in audit fees audit time. Hence, is probable that the benefit of IFRS will outweigh the cost. Originality/value The results, therefore, suggest that early adopters paid a premium for been the first users of IFRS, which is consistent with any innovation. The study provides new insights by demonstrating that the consequences of IFRS differ between early and late adopters.
Keywords: Africa; Audit fees; Audit reporting lags; Early adopters; IFRS; Late adopters

Accountability during the Incorporation of Public and Private Limited Companies under Ohada Law - Sama, Merinda Afanui (International Journal of Research and Innovation in Social Science, 2022)
This work sets out to evaluate the OHADA Uniform Act’s laws on accountability in Private and Public Limited Companies. Normally, laws which provide for effective accountability, guarantee the smooth functioning and stability of companies since its rules work at averting all forms of mismanagements. The inspiration of this work stems from the realization that, levels of accountability in these companies are still wanting. Hitherto, companies are plagued with vices of obscured activities, fake transactions, non-transparent reporting and acute dishonesty by its organs. It is therefore baffling that, these are still prevalent despite the existence of the Uniform Act’s laws which contains accountability mechanism aimed at dispelling all these forms of corporate transgressions. From this arose lingering doubts as to how these laws are.

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

Les compétences juridictionnelles en matière de répression des infractions douanières dans les Etats membres de la CEMAC : Réflexion sur la résolution stricte des litiges douaniers au regard du Droit Public Financier - Aminou Hamidou, Mohamadou (Revue Africaine des Réflexions Juridiques et Politiques, 2022)
Le franchissement des frontières dans le territoire douanier de la CEMAC (Communauté Economique et Monétaire de l’Afrique Centrale) peut se faire de manière régulière, c'est-à-dire en respect de la procédure prescrite à cet effet, ou alors de manière irrégulière en violation de cette dernière. La violation des lois et règlements douaniers donne naissance à des litiges opposant l’administration des douanes aux usagers auteurs des infractions douanières. Il s’agit donc là du contentieux douanier, un contentieux encadré par les règles propres au droit du contentieux douanier, lesquelles dans la zone CEMAC donnent compétence aux juridictions nationales des Etats membres ainsi qu’à la Cour de Justice de la CEMAC de réprimer sévèrement les infractions douanières.
Keywords: CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; Contentieux douanier; Infractions douanières; Juridictions; répression

A regulação macroprudencial no sistema monetário e financeiro internacional contemporâneo : características e externalidades - Baungarten, Bruna Teixeira (Universidade Federal do Rio Grande do Sul, 2022)
Com a Crise Financeira Global (CFG), dos anos 2007 e 2008, há espaço para inflexões na política macroeconômica dos países e nota-se a emergência da utilização de instrumentos macroprudenciais como meio para a limitação do risco sistêmico. Assim, forma-se um cenário onde a alta integração financeira e a atuação de bancos e outras instituições financeiras de forma transnacional se encontra com a crescente utilização de regulações financeiras em âmbitos nacionais, de forma descentralizada e não necessariamente harmonizada internacionalmente. Nesse sentido, esta tese busca investigar a ocorrência de externalidades, ou vazamentos financeiros internacionais que podem ocorrer a partir da implementação de medidas macroprudenciais em uma determinada economia. Assim, a pesquisa situa a temática no cenário do Sistema Monetário e Financeiro Internacional, identificando os movimentos que levaram à formação desse movimento regulatório. Uma análise exploratória acerca da experiência internacional com instrumentos macroprudenciais é conduzida de modo a identificar tendências temporais, continuidades, rupturas e diferenças entre grupos de países na condução da regulação financeira macroprudencial. Ademais, é realizada uma análise empírica que busca somar à literatura que investiga as externalidades internacionais associadas à implementação dessas regulações. Essa investigação é realizada utilizando técnicas de estimação de dados em painel para 40 países entre os anos de 2000 a 2018. Como principais resultados da tese destaca-se que: a) A partir da CFG há a emergência de uma agenda voltada para a estabilidade financeira que tem como pilar a utilização de instrumentos macroprudenciais e, esses instrumentos são largamente utilizados pelas economias nacionais; b) As Economias Avançadas aumentaram proporcionalmente mais a utilização de instrumentos macroprudenciais e, também, diversificaram mais a sua estratégia regulatória que as Economias Emergentes ou em Desenvolvimento; c) O exercício empírico encontra evidências que sugerem a ocorrência de externalidades internacionais decorrentes da implementação de medidas macroprudenciais e que estes efeitos se mantém e até ganham significância estatística de acordo com a relevância sistêmica da economia que implementa a regulação.
URI: https://lume.ufrgs.br/handle/10183/248038
Keywords: Financial Regulation; International Externalities; Macroprudential; Regulação econômica; Sistema Monetário Internacional; Sistema financeiro internacional

De la pertinence des chiffres comptables publiés par les sociétés cotées à la bourse régionale des valeurs mobilières (BRVM) avant et après la révision du système comptable OHADA (SYSCOHADA) - Diop, Ndiaga; Wade, Mouhamed El Bachir (Revue du contrôle, de la comptabilité et de l’audit, 2022)
L’objectif de notre étude est d’évaluer la pertinence du résultat net et des capitaux propres, selon le SYSCOHADA avant et après la révision. Particulièrement, nous vérifions si l'adoption du SYSCOHADA révisé améliore la qualité du résultat net et des capitaux propres publiés par les sociétés cotées à la Bourse Régionale des Valeurs Mobilières (BRVM) pour répondre aux besoins en informations des utilisateurs. A partir d’un échantillon de 21 sociétés cotées sur une période pré-SYSCOHADA révisé (2014-2017) et post-SYSCOHADA révisé (2018-2020). Des relations de type linéaire et quadratique sont testées entre les rendements boursiers et les chiffres comptables. Dans l’ensemble, nos principaux résultats montrent que par rapport à l’ancien SYSCOHADA, le SYSCOHADA révisé améliore nettement les contenus informationnels du résultat net et des capitaux propres des sociétés cotées à la BRVM. Ensuite, il ressort de nos résultats que le modèle non linéaire est plus pertinent que le modèle linéaire pour décrire de manière simultanée la relation entre le rendement boursier et les chiffres comptables.
Keywords: Chiffres comptables; Etudes d’association; Pertinence informationnelle; Rendement boursier

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Uluslararası muhasebe standartları ile OHADA muhasebe sisteminin karşılaştırılması - Moussa Hisseine, Amine (Sakarya Üniversitesi, 2022)
Ekonomilerin küreselleşmesi ve piyasaların globalleşmesi karşısında, ortak bir dile sahip olma arzusu giderek daha fazla hissedilmektedir. Bu ihtiyacı hafifletmek için dünya çapında, birçok ülke, kalite ve karşılaştırılabilir bilgiler için UFRS standartlarını benimsemenin uygun olduğunu düşünmüştür. Bu momentumda, SYSCOHADA muhasebe sistemi aracılığıyla OHADA alanı, 2017 yılında standartlarını UFRS ile uyumlu hale getirmeye karar vermiştir. Bu çalışmanın amacı, Uluslararası Muhasebe Standartlarını (UMS/UFRS), on yedi ülkedeki tüm varlıklarının muhasebesini yöneten Afrika'da Ekonomi Hukuku'nun Uyumlaştırılması Örgütü'nün muhasebe sistemi (SYSCOHADA) ile karşılaştırmaktır. Bu karşılaştırmalı analizin amacı, yukarıdaki iki muhasebe sisteminin benzerliklerini ve farklılıklarını ortaya koymaktır. Bu analiz UMS 1 : Finansal Tabloların Sunuluşu, UMS 2: Stoklar, UMS 7: Nakit Akış Tablosu, UMS 8: Muhasebe Politikaları, Muhasebe Tahminlerinde Değişiklikler Ve Hatalar, UMS 10: Raporlama Döneminden Sonraki Olaylar, UMS 12 :Gelir Vergileri, UMS 16 :Maddi Duran Varlıklar, UMS 19 :Çalışanlara Sağlanan Faydalar, UMS 20 :Devlet Teşviklerinin Muhasebeleştirilmesi Ve Devlet Yardımlarının Açıklaması, UMS 21 :Kur Değişiminin Etkileri, UMS 23 Borçlanma Maliyetleri, UMS 37 Karşılıklar, Koşullu Borçlar ve Koşullu Varlıklar, UMS 38 Maddi Olmayan Duran Varlıklar açısından yapılan muamelelere odaklanacaktır. Çalışma, her iki muhasebe standardı hakkında da iyi bir anlayışa sahip olmayı sağlayacaktır. Bu nedenle, yatırımcılar ve diğer tüm kişiler, SYSCOHADA ve Uluslararası Muhasebe Standartları ile ilgilenenler, bu iki muhasebe standardının finansal tablolarının karşılaştırılabilirliğini kolaylaştırmak amacıyla muhasebe düzenlemeleri hakkında iyi bir anlayışa sahip olabileceklerdir. Çalışma sonucunda SYSCOHADA ile Uluslararası Muhasebe Standartları arasındaki karşılaştırma birçok benzerlik ve çok az farklılık ortaya koymaktadır. Kıta Avrupası muhasebe sistemi ve Anglo-Sakson sisteminden kaynaklanan SYSOHADA hükümleri, kaynaklarını Uluslararası Muhasebe Standartlarında bulmaktadır. Ancak, bu iki standarttaki en büyük fark, SYSCOHADA için tarihsel maliyet ölçüm yöntemi ile UFRS için gerçeğe uygun değer arasındadır. In the face of the globalization of economies and the globalization of markets, the desire to have a common language is increasingly felt. To alleviate this need, many countries around the world have considered it appropriate to adopt IFRS standards for quality and comparable information. At this momentum, the OHADA field, through the SYSCOHADA accounting system, has decided to harmonize its standards with IFRS in 2017. The purpose of this study is to compare the International Accounting Standards (IAS/IFRS) with the accounting system of the Organization for the Harmonization of Economic Law in Africa (SYSCOHADA), which manages the accounting of all its assets in seventeen countries. The purpose of this comparative analysis is to reveal the similarities and differences of the above two accounting systems. This analysis will focus on the treatment of IAS 1 : presentation of financial statements IAS 2: Inventories IAS 7-cash flows IAS 8 accounting policies, changes in accounting estimates and errors IAS 10: events after the reporting period IAS 12 income taxes IAS 16 :property, plant and equipment assets IAS 19 :employee benefits IAS 20 :accounting for government grants and government assistance, description of TMS 21 :the effects of changes in foreign exchange rates IAS 23 borrowing costs, IAS 37 Provisions, Contingent Liabilities and Contingent Assets, IAS 38 intangible assets . The study will allow to have a good understanding on both accounting standards. Therefore, investors and all others persons interested in the SYSCOHADA and International Accounting Standards will be able to have a good understanding on the accounting regulations in order to facilitate the comparability of the financial statements of these two accounting standards. As a result of the study, the comparison between the SYSCOHADA and international accounting standards reveals many similarities and few differences. Originating from the continental European accounting system and the Anglo-Saxon system, the provisions of the SYSOHADA find their sources in International Accounting Standards. However, the major difference in these two standards is between the historical cost measurement method for the SYSCOHADA and the fair value for IFRS.
Keywords: Accounting; Accounting standards; African countries; Afrika Ticaret Kanunu Uyum Örgütü; Afrika ülkeleri; Comparative analysis; Comparison; International Accounting Standards; International accounting; Karşılaştırma; Karşılaştırmalı analiz; Muhasebe; Muhasebe standartları; Organization for the Harmonization of African Business Law; Uluslararası Muhasebe Standartları; Uluslararası muhasebe

Pratique comptable et succès entrepreneurial perçu des PME de Bukavu : rôle modérateur de l’orientation entrepreneuriale - Osea, Guillain Alyahobe; Kitenge, Jules; Lufuma, Jojo (Revue de l’Entrepreneuriat et de l’Innovation, 2022)
This study is to validate the measurement of accountancy practice, identifying the nature of its relationship to entrepreneurial success of SMEs and to identify the moderating role of the entrepreneurial orientation in the relation between the accountancy practice and entrepreneurial success. The data were collected using a maintenance guide and a survey questionnaire, managed at 250 SMEs of Bukavu of the service sector. Structural equations Modeling and the hierarchical regression were used to test the assumptions of research. The results show that the scale of countable measurement of practice is reliable and valid (KMO = 0.817 ; α = 0.847 ; χ2/df = 2.34 ; p = 0.000 ; RMSEA = 0.084 ; intervalle de RMSEA = 0.068 - 0.098 ; NFI = 0.93 ; CFI = 0.96 ; IFI = 0.97 ; GFI = 0.98 ; AGFI = 0.95) and that countable information and the accountancy practice of management are positively and significantly related to entrepreneurial success. Information accounting and the accountancy practice of management in respective interaction with the entrepreneurial orientation influence positively and significantly entrepreneurial success. This investigation could have profited from a longitudinal approach and a typological analysis or shaping. It’s showing at SMEs the accountancy practice importance and entrepreneurial orientation, providing indicators on what the leaders of SMEs should consider when they analyze their accountancy practice, orientation and entrepreneurial success. The study make progress in the existing knowledge by validating the accountancy practice measurement and joining the accountancy practice in interaction with the entrepreneurial orientation to success
Keywords: Accountancy practice; Bukavu; Entrepreneurial orientation; Entrepreneurial succès; Information; Orientation entrepreneuriale; PME; Pratique comptable; SMEs; Succès entrepreneurial

Os impactos da IFRS 16 e as suas determinantes – um estudo de caso, a TAP, Transportes Aéreos Portugueses - Xavier, Catarina Isabel (Universidade do Porto, 2022)

Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

Le droit souple en droit financier - Joly, Pauline (Université Paris-Dauphine, 2021)
Le droit financier régit des activités régulées et est caractérisé par l’intervention d’acteurs publics et privés, les régulateurs et communautés professionnelles. Ces acteurs de la régulation participent à bâtir le cadre normatif des activités financières. Certaines de leurs normes sont privées de la force obligatoire classiquement attachée au Droit. L’importance de ce droit souple, ensemble de normes juridiques non impératives, distingue l’architecture normative du droit financier. Marqué par la diversité de ses formes, modes d’élaboration et auteurs, il est complexe de les identifier. Leur caractère commun réside dans leur force normative, située sous le seuil de l’obligatoriété. Sans être impératif, le droit souple financier produit des effets juridiques. Il oriente les comportements au travers de mécanismes psychosociaux ou d’autres propres au secteur financier et à sa régulation. Il produit aussi des effets en s’articulant à des dispositifs de droits spéciaux ou du droit commun.
Keywords: Autorité de régulation financière; Autorité de surveillance financière; Droit souple; Financial market; Force normative; Marché financier; Normative force; Normativity; Normativité; Regulation; Régulation; Soft law; Source of law; Sources du droit

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale – Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

La concurrence fiscale étatique - Mondonneix, Alix (Université Côte d'Azur, 2021)
La concurrence fiscale étatique naît du climat de tension régnant entre les différents pays. En effet, les Etats n’ontpas les mêmes besoins budgétaires, ce qui engendre une bataille entre les systèmes fiscaux afin d’attirer le plusgrand nombre d’agents économiques. La concurrence fiscale étatique apparaît donc comme une compétition entreles Etats. Ce phénomène s’inscrit dans une économie mondiale globalisée et tend à se renforcer depuis une dizained’années. Pour les contribuables, cette concurrence fiscale permet de bénéficier d’avantages fiscaux dans la mesureoù elle conduit à une convergence des régimes fiscaux des Etats vers des taux d’imposition plus faibles.Toutefois, dans l’optimisation de leur imposition, certains opérateurs économiques utilisent des régimes fiscauxnationaux de manière déloyale. C’est ainsi qu’est née la concurrence fiscale dommageable. Celle-ci fait l’objet d’unelutte active par l’Union Européenne (UE), l’Organisation de coopération et de développement économiques(OCDE) et les Etats eux-mêmes.Une solution doit impérativement être trouvée, d’autant plus que le contexte évolue du fait notamment de la crisesanitaire et de l’essor de l’économie numérique. Si on assiste à un échec des tentatives d'harmonisation fiscale, desmesures de coordination pourraient réguler la concurrence fiscale étatique et l'amener vers plus de loyauté.La quête d'une concurrence fiscale loyale entre Etats n'est pas seulement une question d’équilibre des financespubliques, mais un enjeu majeur dans la survie des systèmes fiscaux et sociaux des pays.Si le concept de concurrence fiscale reposait sur des approches issues de doctrines économiques, celles-ci sontaujourd’hui insuffisantes. C’est alors que le droit s’affirme comme essentiel dans l’appréciation de cette notionnotamment pour l’encadrer, la contrôler et la sanctionner. The tax competition between States arises from the high level of tension between the different countries.Indeed, as States do not have the same budgetary needs, an intense rivalry grew between the tax systems.Their main goal is to attract the largest number of economic actors. The tax competition between Statesis a battle between countries for competitiveness. This phenomenon is a part of a global economy and isgaining increasingly in strength for over a decade. As a result of this, tax benefits are provided fortaxpayers because the tax competition between States leads to a race to the bottom.However, in order to reduce the amount of tax, some economic operators cheat and breach the nationaltax regimes. And so, the harmful tax competition is born. The European Union (EU), the Organisationfor Economic Cooperation and Development (OECD) and the States fight the latter fact.It is important to devise solutions that minimise harmful tax competition and remove the in-built biastowards taxation of less mobile basis, especially because the context is changing due to the health crisisand the development of the digital economy. Even though the tax harmonisation fails, somecoordination measures could be used to regulate the tax competition between States. Loyalty is the keyterm.The quest for a loyal tax competition between States is not a matter of government finances at least inbalance. It’s a major challenge to the durability of tax and social systems of each country.Although the concept of the tax competition between States is based on economic doctrines, thisapproach is now obsolete. The law approach is essential to apprehend this notion, particularly to frame,control and punish it.
Keywords: Capital mobility; Concurrence fiscale; Course vers le bas; Droit fiscal; Fiscalité; Household mobility; Mobilité des ménages; Mobilité du capital; Pays de l'Union européenne; Politique fiscale; Race to the bottom; Relations fiscales intergouvernementales; Tax policy; Taxation

Les non-dits scabreux des réformes du système comptable normal de l'OHADA de 2017 - Mvogo, Jean (Revue Française d’Economie et de Gestion, 2021)
Les états financiers sont des documents de synthèse qui fournissent des informations importantes à l’entreprise pour la prise des décisions de gestion et aux organismes habiletés à utiliser ces informations pour d’autres analyses au niveau national et international. Ils sont constitués du bilan, du compte de résultat, du tableau des flux de trésorerie et des notes annexes pour le système normal de l’OHADA. Or, les dispositions de ces états financiers ne laissent pas déconcerter. Ainsi, nonobstant leur amélioration au cours des précédentes réformes, certaines limites se sont retrouvées encore dans ces états financiers, à l’opposé aux perspectives. Cet article analyse les conséquences que la suppression des charges immobilisées entrainerait chez les parties prenantes de l’entité. Il présente aussi le problème de référence qui concerne le compte 318, « marchandises hors activités ordinaires ». Il fustige enfin l’instabilité du troisième état financier de l’OHADA. Les suggestions suivantes sont donc effectuées : la réinstauration des charges immobilisées dans le bilan, le rattachement du compte 318, « marchandises hors activités ordinaires » à la référence BA et l’adoption des bases de stabilisation du troisième état financier du système normal de l’OHADA
http://www.revuefreg.com/
Keywords: Charges immobilisées; Etats financiers; Instabilité; Référence; Suppression

Digital economy and international taxation : the digital revolution and its impact on the discourse of international tax law - Pereira da Silva Campos, Marcio Augusto (Université Paris 1 ; Universidade de Brasília, 2021)
The impacts of the economy’s digitalisation process on taxation have become the central theme of international tax law in recent years, causing several reactions among actors in this field. The OECD has become the main forum for debate, causing government bodies, taxpayers, and academia to gravitate around the organisation’s texts. Nonetheless, the digital economy tax debate has constantly changed, taking on new languages and adopting different perspectives. From a formal legal discussion concerned with characterising payments to apply international tax treaties, the debate moved to an economic perspective involving substance. Finally, it took on a manifest political connotation, resulting in a re-discussion of the international tax field itself. This thesis aims to understand how and why the digitalisation of the economy managed to impact the fundamentals that support the international tax field. The work adopts a legal, realistic, and discursive perspective to achieve its objective, understanding international tax law as a field formed from historically identifiable events. In this case, while a social phenomenon, international taxation is the central object of a project that manifests itself both in the institutional and intellectual plane. In turn, the digitalisation of the economy results from a technological revolution characterised by the centrality of informational phenomenology. Such centrality is responsible for a social transformation process affecting the tax field’s institutional and intellectual dimensions. In this scenario, actors in the field perceive their inability to deal with the new digital reality from the conceptual tools provided by the tax legal discourse. The result is a paradigm shift with the potential to affect not only the field’s social practice but its very significance within an intellectual project for constructing the human dimension.
Issue: 2021PA01D020
Keywords: Campo tributário internacional; Champ fiscal international; Digital economy; Digital revolution; Direito tributário internacional; Discours fiscal international; Discurso tributário internacional; Droit fiscal (droit international); Droit fiscal international; Economia digital; Economie numérique; Feno-menologia informacional; Fiscalité internationale; Informational phenomenology; International tax discourse; International tax field; International tax law; International taxation; Phénoménologie informationnelle; Revolução digital; Révolution numérique; Société numérique; Taxes internationales; Tributação internacional

La microfinance et appui au microentrepreneuriat : cas du Burundi - Nsengiyumva, Théogène (Normandie Université, 2021)
Les microentreprises (ME) jouent un rôle important dans les économies des pays en voie de développement (PVD). Elles constituent les sources principales de la création d’emplois et génèrent des ressources importantes pour leurs promoteurs. Elles contribuent aussi de manière non négligeable à la formation du produit intérieur brut (PIB) dans les PVD. L’accès au financement est alors un défi crucial à leur création et à leur développement. Malgré leur rôle indéniable dans le développement socioéconomique, elles accèdent toujours difficilement au financement bancaire, et ce, en dépit des politiques publiques de soutien menées à leur égard. Cette thèse vise à analyser les facteurs explicatifs du faible financement des microentreprises (ME) dans le cas du Burundi. Les données que nous avons exploitées dans cette thèse proviennent des deux bases. Celle issue des données collectées sur 3430 dossiers de crédits des institutions de microfinance (IMF) burundaises et celle réalisée auprès de 223 microentrepreneurs à partir d’une enquête. A l’aide du modèle probit, l’analyse économétrique a révélé que certaines caractéristiques des microentreprises et/ou de leurs promoteurs comme l’âge du microentrepreneur, la durée du crédit sollicité, la zone d’implantation de la microentreprise influent négativement sur l’accès au financement. D’autres caractéristiques telles que la nature de la garantie présentée, le profil du microentrepreneur ou son niveau de richesse jouent positivement sur le financement des microentreprises. L’étude a montré aussi que la microfinance reste un moyen efficace pour financer les microentreprises. Ainsi, la restructuration des fonds de garantie et l’engagement accru du gouvernement surtout en matière d’accompagnement sur le terrain améliorerait le financement des microentreprises. Microenterprises (ME) play an important role in the economies of developing countries (DCs). They are the main sources of job creation and generate significant resources for the formation of Gross Domestic Product (GDP) in these economies. Despite their undeniable role in development, they still have difficulty accessing external financing for debiting public support policies for them. This thesis aims to analyze the explanatory factors of the low funding of EM. It takes Burundi as a case study and assesses the key role of microfinance in supporting MOEs. To achieve this dual objective, this study used two databases: the one containing data collected on 3430 loan files of Burundian microfinance institutions and the one consisting of data collected from 223 microentrepreneurs by a survey. The analysis used the probit model and revealed that certain characteristics of microenterprises and / or their promoters such as the age of the microentrepreneur, the duration of the credit sought, the microenterprise location area have a negative impact on access to microenterprise financing. Other characteristics such as the nature of the guarantee presented, the profile of the microentrepreneur or its level of wealth play a positive role in financing microenterprises. The study also showed that microfinance remains in a strategically appropriate position to finance microenterprises. In final, the restructuration of the guarantee funds for nonagricultural microenterprises and the accompaniment of the government would make MFIs more effective in contributing to the financing of smallholder Enterprises.
Keywords: Burundi; Conditions économiques; Entrepreneurship; Financement; Financing; Microentrepreneuriat; Microentreprise; Microfinance; Microfinance institutions; Smallholder enterprises

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Caractéristiques de l’organisation comptable et qualité de l’information comptable et financière produite par les PME : le cas du Cameroun - Ngongang, Dagobert; Ngoe Mekando, Alex Cyrille (Revue Economie, Gestion et Société, 2021)
The purpose of this study is to analyze the impact of the characteristics of the accounting organization on the quality of the accounting and financial information produced by SMEs. A binary logistic regression analysis, a simple linear regression and a chi-square test on the data collected by administering a questionnaire from a sample of 73 SMEs constituted by reasoned choice allow, on the one hand, to observe that the SMEs Cameroonians are setting up an accounting organization in order to produce not only mandatory accounting information, but also accounting information intended for their own use. On the other hand, the empirical conclusions of this study show that the use of a service provider in the context of an outsourcing of the accounting function and the degree of computerization of the accounting activity positively and significantly influence the quality of accounting production. and finance for SMEs. Conversely, the feminization of the accounting function is found to be one of the characteristics of the accounting organization without influencing the quality of the accounting and financial product of SMEs.
Keywords: Accounting organization; Degree of computerization; Degré d’informatisation; Externalisation; Feminization; Féminisation; Organisation comptable; Outsourcing; Quality; Qualité

La comptabilité de l'OHADA face au choix des spécificités des activités économiques - Mvogo, Jean (Revue Internationale des Sciences de Gestion, 2021)
La prédominance des comptes spécifiques de l’activé commerciale, industrielle et agricole dans le plan des comptes de l’OHADA au détriment d’autres activités, accule de scruter les particularités de celles-ci. Car, la portée sociale et économique des autres activités telles que l’activité hôtelière, l’activité associative, l’activité d’enseignement…, nécessite déjà une attention particulière sur le plan comptable. La portée d’un tel exercice a pour objectif non seulement de répertorier les spécificités comptables des activités commerciales, industrielles et agricoles mais aussi et surtout de proposer les particularités des autres activités à forte demande d’intégration dans le plan des comptes de l’OHADA. En premier lieu, cet article montre, classe par classe, les différents comptes qui permettent d’entrevoir les spécificités comptables de l’activité commerciale, industrielle et agricole. En second lieu, l’étude observe des limites sur le principe de parallélisme et de correspondance comptable sur les comptes de l’activité agricole et du compte marchandises hors activités ordinaires, et trouve donc un intérêt certain dans l’appel à l’insertion des comptes spécifiques des autres activités importantes ayant des particularités établies à défaut de créer des plans de comptes spécifiques.
Keywords: Comptabilité; OHADA; Plan comptable; Plan des comptes; Spécificités comptables

L’éclatement du cadre personnel de la transaction douanière au Cameroun - Yougouda, Hadidjatou (International Multilingual Journal of Science and Technology, 2021)
L’éclatement du cadre personnel de la transaction douanière est lié principalement au nombre excessif des structures intervenant dans le déclenchement de cette procédure. Ce cadre recouvre une pluralité des autorités publiques et des bénéficiaires qui rend de ce fait difficile le travail de leur classification. Force est de constater qu’au niveau des autorités publiques, les pouvoirs de ces dernières sont déterminés par rapport à leur grade et suivant l’importance des affaires traitées. Le pouvoir de transaction est par conséquent attribué restrictivement à des fonctionnaires désignés suivant une compétence hiérarchique établie en fonction de l’importance de l’affaire. Ces compétences sont actuellement réglées dans le cadre de la CEMAC par l’article 328 du code des douanes. S’il est vrai que la transaction doit être conclu par l’autorité administrative compétente, il arrive qu’elle soit conclue par un subordonné habilité à le faire. En ce sens, les textes prévoient fréquemment l’approbation de la transaction par l’autorité hiérarchique. Cette approbation est, selon les cas, la condition de l’engagement de la personne publique qui contracte ou la condition de l’application de la transaction. Ainsi, le déclenchement de la procédure transactionnelle relève, à titre principal, de la compétence des autorités nationales et communautaires, et, subsidiairement, de celle des services extérieurs et du ministère public. La situation est sensiblement plus complexe en ce qui concerne les bénéficiaires. Théoriquement, l’article 327 alinéa 1 du code des douanes CEMAC ouvre le recours à la transaction douanière à tous contrevenant qui la sollicite. Il est admis que cette expression vise aussi bien les auteurs que les complices ; les intéressés à la fraude, les civilement responsables, les cautions, les propriétaires des marchandises ou des moyens de transport dont la confiscation est encourue.

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

La taxation des frais généraux en droit fiscal nigérien - Kimba Moussa, Hamidou (Université Cheikh Anta Diop, 2021)
Keywords: Droit fiscal; Frais généraux; Niger; Taxation; Taxe

Le juge fiscal camerounais : unité ou pluralité de juridictions ? - Fermose, Janvier (Les Annales de droit, 2021)
Le développement du contentieux fiscal moderne a conduit à un passage du dualisme juridictionnel à un pluralisme juridictionnel fiscal. S’il n’est pas évident d’avoir un juge unique qui statue sur l’ensemble de la matière fiscale, la préoccupation centrale est celle de savoir comment les juges fiscaux coexistent-ils dans l’ordre juridictionnel camerounais. Suivant l’hypothèse que cette coexistence est manifeste, l’étude privilégie l’analyse des textes juridiques et des décisions rendues par les juridictions fiscales camerounaises. D’une part, pour vérifier le bien-fondé de l’analyse, il ressort que, de par son identification, le juge fiscal camerounais est désormais un juge multiple, pluriel et diversifié : il est dual, en se référant au juge fiscal classique (administratif ou judiciaire), et spécial, si l’on fait allusion aux juges fiscaux constitutionnel, communautaire et régional. La diversité du juge fiscal permet alors d’observer que toutes les juridictions sont, à un titre plus ou moins, à compétences fiscales. Si pendant longtemps, le dualisme juridictionnel a été le socle institutionnel du contentieux fiscal, la notion de juge fiscal s’est aujourd’hui enrichie avec l’apparition des nouveaux juges fiscaux. D’autre part, comme corollaire, la pluralité des juges fiscaux pose le problème de leur cohabitation : l’on note une collaboration organique et fonctionnelle entre les juges intervenant en contentieux fiscal, mais cette coexistence n’est pas sans conséquence, car elle entraîne des incidences légales et jurisprudentielles.
Number: 15
Keywords: juge fiscal; juridiction; pluralité; unité

Les récentes réformes des finances sociales au Cameroun - Tekendo, Gaétan Siewe (Les Annales de droit, 2021)
Alerte sécu ! C’est par cette exclamation que l’on peut mettre en garde sur les potentielles menaces qui pèsent sur les finances sociales en Afrique en général et au Cameroun en particulier. Les régimes de sécurité sociale des pays d’Afrique noire francophone font face à de sérieuses difficultés financières. Ceux-ci éprouvent des difficultés à fournir à temps des prestations sociales aux travailleurs salariés et leurs familles. De prime abord, la mission d’une caisse de sécurité sociale est d...

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

L'arbitrabilité des litiges en droit des marchés financiers - Megam, Nadège Flore (International Multilingual Journal of Science and Technology, 2021)
Keywords: Arbitrage; Arbitration; Financial markets; Marchés financiers

Création d'un fonds Zakât international : nécessités et faisabilité d’une internationalisation du droit de la Zakât - Abrighach, Safae (Université de Strasbourg, 2021)
La Zakât, aumône légale des musulmans, fait partie des cinq piliers de l’Islam. Le verset 60 de la Sourate Tawbah fixe 8 catégories d'attributaires au profit desquels la Zakât peut être versée. En l'occurrence, il s'agit des pauvres, nécessiteux, personnes chargées de collecter la Zakât, personnes dont les sympathisants à l’islam, les esclaves, les insolvables, les voyageurs en détresse, et le sentier d'Allah. L’intitulé de « Création d’un Fonds Zakât International : Nécessités et faisabilité d’une internationalisation du droit de la Zakât » est une analyse d’un projet datant de 2008 et qui n’a pas abouti à sa réalisation. C’est pour inciter à la création d’un Fonds Zakât International que cette thèse a été rédigée. Il s’agit d’étudier les carences en question et d’en proposer des solutions efficaces. L’optique est de collecter la Zakât à l’international pour une meilleure éradication de la pauvreté. Zakat, legal alms for Muslims, is one of the five pillars of Islam. The Verse 60 of Sura Tawbah sets out eight categories of beneficiaries for whose benefit Zakât may be paid. In this case, it is the poor, needy, persons responsible for collecting the Zakât, persons whose sympathizers to Islam, slaves, insolvent, travelers in distress, and the path of Allah. The title ''Creation of an International Zakât Fund : Necessities and feasibility of an internationalization of the law of Zakat'' is an analysis of a project dating from 2008 and that did not lead to its realization. It is to encourage the creation of a Zakât International Fund that this thesis has been written. It is a question of studying the deficiencies in question and proposing effective solutions. The vision is to collect Zakât internationally for a better eradication of poverty.
Keywords: Dotation funds; Droit international (droit islamique); Fonds Zakât International; Fonds de dotation; Gouvernance; International Zakât Fund; Non-governmental organization; Oeuvres de bienfaisance; Organisation non gouvernementale; Waqf; Zakāẗ

Tributação na economia compartilhada - Braz, Jacqueline Mayer da Costa Ude (Universidade de São Paulo, 2021)
Este trabalho se propõe a estudar a tributação dos modelos de negócio que envolvem o conceito de economia compartilhada, que se liga à ideia de mercados de redistribuição, estilos de vida colaborativos e o sistema de produto e serviço, que busca substituir a propriedade pela posse dos bens. Esses modelos utilizam-se da tecnologia para aproximar pessoas que dificilmente se encontrariam offline para que elas possam firmar negócios jurídicos relacionados ao ideal de compartilhamento. As plataformas digitais, nesse contexto, funcionam como marketplaces, que agregam demanda e oferta e potencializam os resultados desses modelos de negócio. Desse modo, a partir da definição do conceito de economia compartilhada, os modelos de negócio foram mapeados, para que, em seguida, se pudesse compreender o papel das plataformas digitais, nesse contexto, e os negócios jurídicos que são celebrados por intermédio delas. Foram estudados os contratos firmados entre os usuários da plataforma e deles com a plataforma para, com base nisso, fosse examinada a tributação incidente. Concluiu-se pela impossibilidade de se estudar a tributação incidente sobre as atividades desenvolvidas pelas plataformas digitais de economia compartilhada apenas com a verificação do que ocorre com negócios jurídicos offline parecidos, estabelecendo a atividade preponderante e a tributação incidente por analogia. É preciso compreender o modelo de negócio, os contratos que são celebrados por seus usuários, além da relação jurídica que eles estabelecem com a plataforma e a consistência material do negócio jurídico, para, somente então, analisar a tributação incidente sobre as atividades econômicas desenvolvidas por intermédio dela. This work proposes to study the taxation of business models that involve the concept of sharing economy, which is linked to the idea of redistribution markets, collaborative lifestyles, and product and service system, which seeks to replace ownership of assets by their usage. These business models use technology to bring together people who would hardly meet offline so that they can establish legal business relationships that are connected to the idea of a sharing economy. In this context, digital platforms act as marketplaces that aggregate demand and supply, enhancing the results of these business models. This work defines the concept of a sharing economy and maps the existing business models so that one could understand the role of digital platforms in this context and the legal businesses that are concluded through them. The contracts signed between the users of the platform and theirs with the platform were studied and, based on this, the incident taxation could be examined. It was concluded that it is impossible to study the taxation on the activities developed by making an analogy between the digital platforms of sharing economy with similar offline legal businesses. It is necessary to understand each unique business model, the contracts that are signed by its users, the legal relationship that users establish with the platform, and the material consistency of the legal arrangement, only then to analyze the taxation on the economic activities developed through it.
Keywords: Contratos; Cooperativismo; Inovações tecnológicas; Negócio juridico; Sharing economy; Taxation; Tributação

Droit OHADA et développement économique au Cameroun de 1995 à 2020 : contribution historique à une théorie de l'analyse économique du droit en Afrique subsaharienne - Otabela Atangana, Hugues (Aix-Marseille Université, 2021)
Dans la décennie 1995 à 2005, 17 États d’Afrique subsaharienne se sont regroupés pour former une organisation d’intégration juridique, afin d’uniformiser leur droit des affaires et d’instaurer un courant de confiance pour les investissements. L’OHADA (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) devait en découdre avec la situation d’insécurité juridique qui sévissait dans le continent en renforçant son attractivité économique, afin de faire émerger un pôle de développement en Afrique. Animée de l’idéologie panafricaniste, cette institution devait résolument se mettre au service du développement économique et de l’entreprise. Mais plus d’un quart de siècle après, on est en droit de se demander si elle atteint ses objectifs économiques. Les revendications des avocats anglophones de novembre 2016 au Cameroun qui fustigeaient l’imposition du droit OHADA au détriment de la Common Law, permet de jauger de la profondeur de la question. Ces mouvements corporatistes qui ont marqués le début de la crise sécessionniste, dévoilent le mimétisme juridique qui anime l'OHADA. Ce panafricanisme juridique qui l’incarnait, devait résolument se mettre au service de l’économie et de l’entreprise. Finalement, il a été supplanté par le mimétisme juridique. L’apport de l’OHADA dans le processus de développement économique du Cameroun reste faible et l’émergence d’un pôle de développement en Afrique est loin d’être amorcée. Cette réalité s’expliquerait par le fait que l’OHADA incarne une sorte d’acculturation juridique, d’où ses performances médiocres. L’opportunité d’une refonte profonde de ce modèle de communautarisation du droit des affaires mérite d’être soulevée
Keywords: Acculturation juridique; And legal mimicry.; Banks; Banques; Cameroun; Competencia; Competition law; Competitiveness; Compétitivité; Concurrence; Droit des affaires; Développement économique; Economic development; Entreprises; Financial markets; Incentive; Incitation; Innovation; Integration and economic agents; Intégration et agents économiques; Investissements; Investments; Legal acculturation; Legal pan-Africanism; Marchés financiers; OHADA; PIB réel; Panafricanisme juridique et mimétisme juridique.; Real GDP; Sécession

L'intermédiation financière et la théorie de la représentation - Gérard, Thomas (Université Paris Cité, 2021)
La réforme du droit des obligations a fait naître une distorsion entre la vision que le droit positif et la science juridique adoptent du mécanisme de la représentation. Afin d'y remédier, les activités ressortissant à l'intermédiation financière sont apparues comme un matériau d'étude approprié. Le vocable réunit les prestations prodiguées par les professionnels habilités à opérer sur les plates-formes de négociation d'instruments financiers et d'actifs numériques dans le cadre du traitement des ordres émanant de leurs clients. Si les intermédiaires financiers ne peuvent être considérés comme des mandataires dans la mesure où ils n'agissent pas au nom d'autrui mais en leur propre nom, les contrats qu'ils concluent avec leurs donneurs d'ordres n'en demeurent pas moins des contrats de représentation. Ces prestataires agissent en effet pour le compte d'autrui, mode d'action qui constitue l'essence du mécanisme de la représentation. En considération du principe de correspondance entre l'expression de l'intérêt du sujet et l'exercice d'un droit subjectif, il en résulte que celui qui, tel l'intermédiaire financier, exprime par sa volonté l'intérêt d'un autre sujet de droit exerce des prérogatives qui se rapportent aux droits subjectifs d'autrui. L'assise spécifique du pouvoir ainsi mis en œuvre éclaire le processus d'imputation à autrui des effets de l'action, que l'on présente comme le second versant de l'action pour le compte d'autrui. Compte tenu de la corrélation instaurée entre la titularité du droit subjectif exercé et l'imputation des conséquences qui en résultent, c'est en effet l'exercice des droits subjectifs d'autrui qui justifie l'imputation au titulaire de ces droits des effets de l'action. Fondée sur une dissociation entre la titularité et l'exercice des droits subjectifs, cette analyse de l'action pour le compte d'autrui la fait coïncider avec la conception moderne de la représentation. Si l'essence de la représentation se loge dans le mécanisme de l'action pour le compte d'autrui, le fait que l'agissement soit mené en nom propre ou au nom d'autrui doit être tenu pour une simple variable d'ajustement du phénomène représentatif. La teneur des obligations assumées par les prestataires habilités envers leurs donneurs d'ordres est inextricablement liée à leur qualité de représentant. L'obligation faite à l'intermédiaire financier d'exécuter la mission qui lui est confiée par son donneur d'ordres dépend étroitement de ce que le premier agit pour le compte du second, dont il met en œuvre les droits subjectifs. En tant qu'il constitue la traduction technique du pouvoir de représentation dévolu à cet intermédiaire, le mécanisme de l'action pour le compte d'autrui conduit à lui imposer des obligations de diligence et de loyauté partagées par tout représentant. Agissant pour le compte d'autrui, l'intermédiaire financier exerce un pouvoir de représentation ayant pour assise les droits subjectifs du représenté, ce dont il résulte qu'il assume des obligations communes à tout représentant. Préalablement analysée comme une simple variable d'ajustement du phénomène représentatif, l'intervention en son propre nom de l'intermédiaire financier ne saurait en altérer l'essence, ainsi que le confirme l'étude de l'influence d'un tel mode d'action sur le régime de l'obligation d'exécuter la mission assignée à l'intermédiaire. L'obligation de rendre compte incombant à l'intermédiaire financier obéit à la même logique. Si l'analyse de l'intermédiation financière atteste du particularisme du droit la régissant, la conception renouvelée de la représentation qu'elle a permis de formuler confirme dans le même temps l'absence d'autonomie du droit financier. Nous formons ainsi le vœu que l'étude ici menée puisse constituer le socle d'une réconciliation entre la science juridique et le droit positif susceptible d'éclairer la compréhension du mécanisme de la représentation à l'œuvre dans d'autres branches du droit. The reform of the law of obligations created a distortion between the vision that positive law and legal science adopt of the mechanism of representation. In order to remedy this, financial intermediation activities have emerged as suitable study material. The term combines the services provided by professionals authorized to operate on trading platforms for financial instruments and digital assets as part of the processing of orders from their clients. While financial intermediaries cannot be considered as agents insofar as they do not act in the name of others but in their own name, the contracts they conclude with their principals nonetheless remain representation contracts. These service providers act on behalf of others, a mode of action which constitutes the essence of the mechanism of representation. Considering the principle of correspondence between the expression of the subject's interest and the exercise of a subjective right, it follows that the one who, such as the financial intermediary, expresses by his will the interest of another subject of law exercises prerogatives which relate to the subjective rights of others. The specific base of power thus implemented sheds light on the process of attributing the effects of action to others, which is presented as the second aspect of action on behalf of others. In view of the correlation established between the ownership of the subjective right exercised and the attribution of the resulting consequences, it is in fact the exercise of the subjective rights of others which justifies the attribution to the holder of these rights of the effects of the action. Based on a dissociation between ownership and the exercise of subjective rights, this analysis of action on behalf of others makes it coincide with the modern conception of representation. If the essence of the representation is lodged in the mechanism of the action on behalf of others, the fact that the action is carried out in own name or in the name of others must be considered as a simple variable of adjustment. of the representative phenomenon. The content of the obligations assumed by authorized service providers towards their principals is inextricably linked to their quality of representative. The obligation imposed on the financial intermediary to perform the mission entrusted to it by its principal depends closely on whether the first acts on behalf of the second, whose subjective rights it implements. In so far as it constitutes the technical translation of the power of representation vested in this intermediary, the mechanism of action on behalf of others leads to the imposition of obligations of diligence and loyalty shared by all representatives. Acting on behalf of others, the financial intermediary exercises a power of representation based on the subjective rights of the principal, which means that he assumes obligations common to all representatives. Previously analyzed as a simple adjustment variable of the representative phenomenon, the intervention in its own name of the financial intermediary cannot alter its essence, as confirmed by the study of the influence of such a mode of 'action on the regime of the obligation to perform the mission assigned to the intermediary. The obligation to render account incumbent on the financial intermediary follows the same logic. If the analysis of financial intermediation attests to the particularism of the law governing it, the renewed conception of the representation that it has made it possible to formulate confirms at the same time the absence of autonomy of financial law. We therefore hope that the study conducted here may constitute the basis for a reconciliation between legal science and positive law capable of shedding light on the understanding of the mechanism of representation at work in other branches of law.
Keywords: Commission; Droit financier; Financial intermediation; Financial law; Intermédiation financière; Mandat; Representation; Représentation

Compliance et soft law en matière bancaire et financière - Bonnigal, Agathe (Université de Nantes, 2021)
Les normes de soft law, règles ou principes entendus comme les actes non-contraignants pouvant émaner des autorités publiques comme des acteurs privés, permettent d’appréhender ce qu’on appelle communément le droit souple. Classiquement écartées de la panoplie des sources formelles du droit, les normes de soft law sont reléguées le plus souvent au rang de sources nées de la pratique. Cependant, face aux nombreux effets juridiques qu’elles produisent et à la variété de leurs manifestations, on peut raisonnablement penser que les normes de soft law dont la compliance prend sa source, ont une réelle utilité pour encadrer l’activité bancaire et financière. La pertinence de recourir au soft law comme outil de conception de la compliance et de régulation du secteur bancaire et financier fera ainsi l’objet de notre réflexion dans une première partie. Après avoir démontré la diversification des sources dans l’encadrement normatif des activités bancaires et financières, nous analyserons le passé de la régulation. Nous nous interrogerons à cet effet, sur l’intégration du soft law dans l’ordre juridique interne. Puis, nous prolongerons notre réflexion en étudiant plus précisément la pratique de la compliance, qui dissimule un arsenal normatif complexe et des obligations éthiques visant à prémunir les établissements bancaires et financiers contre tout risque de non-conformité. Dès lors, nous tenterons de mesurer l’efficacité du système normatif de régulation dans la défense d’intérêts privés mais également d’enjeux nationaux et déterminerons les progrès restant à parcourir pour lutter contre ses insuffisances. Pour ce faire, nous nous intéresserons dans une seconde partie à la compliance comme expression de la densification normative du soft law en matière bancaire et financière.
Keywords: Banques; Compliance; Conformité; Droit souple; Finances

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
URI: https://repository.up.ac.za/handle/2263/82750
Keywords: Immovable property; Income tax; South Africa; Tax treatment

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled “Corporate Finance”, focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).
Accepted: 2022-01-11T13:28:27Z

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
URI: https://repository.up.ac.za/handle/2263/80388
Keywords: Bank failure; Bank supervision; Zimbabwe

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Identifier: https://escholarship.mcgill.ca/concern/theses/rf55zd52x
Keywords: International tax; International tax policy

Le tourisme des Antilles françaises saisi par le droit économique - Liroy, Axel (Université Côte d'Azur, 2020)
Objet à multiples dimensions juridiques – le commerce, la concurrence, la fiscalité, l’environnement, le salariat, l’urbanisme, les droits et libertés fondamentaux, la valorisation du folklore et des traditions, la formation, la police, la construction notamment –, le tourisme est le terrain de synergie d’acteurs et d’activités publics et privés en lien direct ou indirect avec l’économique. Un lien de subordination ordonnée caractérisé par la privation, relativement motivée, de l’acteur économique d’un accès libre et direct au marché. C’est l’office du pouvoir économique public. Aux Antilles françaises, il est l’artisan d’un protectionnisme juridique, irradiant, variablement éloigné des nécessités économiques par opposition franche à une Caraïbe plus libérale et lacunaire, aux méthodes distorsives de concurrence, éminemment connectée aux nécessités économiques. Propulsées dans la modernité du droit par leur nationalité politique et ses corollaires – il est une identité de droits entre les Antilles françaises, la France continentale et, résolument, l’Union européenne –, les Antilles françaises sont, au niveau de leur région d’extraction, marginales. La conjuration, au moins partielle, de leur marginalité et, par ricochet, de celle de leur tourisme passerait par un changement de paradigme obtenu notamment d’un mouvement de décentration (« sortir de soi »). Ce dernier tire sa subsistance d’une société devenue mondialisée et interdépendante exhortant les petites économies au regroupement pertinent. Un mouvement qui, matériellement confronté à l’ombre menaçante de l’assimilation juridique dans le cas des Antilles françaises, requiert une fine précision. L’intégration régionale, dont la formule contractuelle – méthode alternative d’organisation de l’économie –, en ses force, intensité, diversité, flexibilité et massivité, est la figure de proue, sans prétendre à la panacée, emporte un effet décentriste. Il naît du contrat économique, plus justement de sa force normative. Porté par l’acteur économique public – l’Etat et/ou ses démembrements territoriaux –, le traité ou l’accord international vise notamment la conduite de politiques communes telle qu’en matière environnementale, les optimisation et fluidité circulatoires – des personnes, des biens, des services –, la réduction des écarts de développement, la protection de la concurrence. Porté par l’acteur économique privé – l’exemple des parties à un contrat de franchise –, sous couvert de la poursuite de la satisfaction d’intérêts particuliers, il organise des rapports d’économie confinant au transfert de technologie, au partage de marque, au renforcement de l’offre et de la demande, à la diminution du coût de la vie par la réalisation d’économie d’échelle, de gamme notamment. Maîtrisé, l’effet décentriste de l’intégration régionale pourrait, dans une certaine mesure, constituer un outil efficace pour une économie durable du tourisme des Antilles françaises en marge ou, quand cela est possible, en alternative aux procédés traditionnels. Objet à multiples dimensions juridiques – le commerce, la concurrence, la fiscalité, l’environnement, le salariat, l’urbanisme, les droits et libertés fondamentaux, la valorisation du folklore et des traditions, la formation, la police, la construction notamment –, le tourisme est le terrain de synergie d’acteurs et d’activités publics et privés en lien direct ou indirect avec l’économique. Un lien de subordination ordonnée caractérisé par la privation, relativement motivée, de l’acteur économique d’un accès libre et direct au marché. C’est l’office du pouvoir économique public. Aux Antilles françaises, il est l’artisan d’un protectionnisme juridique, irradiant, variablement éloigné des nécessités économiques par opposition franche à une Caraïbe plus libérale et lacunaire, aux méthodes distorsives de concurrence, éminemment connectée aux nécessités économiques. Propulsées dans la modernité du droit par leur nationalité politique et ses corollaires – il est une identité de droits entre les Antilles françaises, la France continentale et, résolument, l’Union européenne –, les Antilles françaises sont, au niveau de leur région d’extraction, marginales. La conjuration, au moins partielle, de leur marginalité et, par ricochet, de celle de leur tourisme passerait par un changement de paradigme obtenu notamment d’un mouvement de décentration (« sortir de soi »). Ce dernier tire sa subsistance d’une société devenue mondialisée et interdépendante exhortant les petites économies au regroupement pertinent. Un mouvement qui, matériellement confronté à l’ombre menaçante de l’assimilation juridique dans le cas des Antilles françaises, requiert une fine précision. L’intégration régionale, dont la formule contractuelle – méthode alternative d’organisation de l’économie –, en ses force, intensité, diversité, flexibilité et massivité, est la figure de proue, sans prétendre à la panacée, emporte un effet décentriste. Il naît du contrat économique, plus justement de sa force normative. Porté par l’acteur économique public – l’Etat et/ou ses démembrements territoriaux –, le traité ou l’accord international vise notamment la conduite de politiques communes telle qu’en matière environnementale, les optimisation et fluidité circulatoires – des personnes, des biens, des services –, la réduction des écarts de développement, la protection de la concurrence. Porté par l’acteur économique privé – l’exemple des parties à un contrat de franchise –, sous couvert de la poursuite de la satisfaction d’intérêts particuliers, il organise des rapports d’économie confinant au transfert de technologie, au partage de marque, au renforcement de l’offre et de la demande, à la diminution du coût de la vie par la réalisation d’économie d’échelle, de gamme notamment. Maîtrisé, l’effet décentriste de l’intégration régionale pourrait, dans une certaine mesure, constituer un outil efficace pour une économie durable du tourisme des Antilles françaises en marge ou, quand cela est possible, en alternative aux procédés traditionnels.
Keywords: Antilles françaises; Droit économique; French West Indies; Intégration régionale; Legal Protectionism; Protectionnisme juridique; Tourism; Tourisme

La reporting extra-financier en voie de se faire : Une étude herméneutique de l’appropriation d’une comptabilité socio-environnementale - Carn, Clément (Université de Poitiers, 2020)
Le développement de la comptabilité socio-environnementale au cours des dernières années représente un profond changement dans le champ de la comptabilité. Ses promoteurs proposent d'intégrer des éléments concernant le développement durable dans la communication des entreprises. Cette situation offre la possibilité d'étudier les pratiques comptables à un moment où elles ne sont pas encore figées et font encore l'objet de controverses. Notre recherche profite de cette situation pour étudier les processus sociaux qui concourent à façonner les institutions comptables. Nous questionnons plus précisément l'intégration du processus d'appropriation de l'une de ces nouvelles méthodes comptables (la méthode CARE) dans la construction socio-historique. Cette recherche s'inscrit alors logiquement dans le cadre de la théorie de l'appropriation, à laquelle nous proposons d'ajouter une dimension herméneutique. En effet, c'est par cette dimension qu'il est possible d'étudier la compréhension d'un outil à partir des cadres d'interprétations hérités de l'histoire. Cette attention portée à l'historicité nous conduit à proposer une généalogie des méthodes de comptabilité socio-environnementale. Celle-ci nous permet de distinguer le cadre dominant de la comptabilité prométhéenne – qui a vocation à garantir le maintien d'une capacité de production – du cadre critique de la comptabilité orphique qui permet de maintenir les entités écologiques pour elles-mêmes. À partir de cette compréhension théorique, notre étude empirique permet de montrer que, malgré la sensibilité écologique des acteurs, une comptabilité orphique fait systématiquement l'objet de tentative de détournement. Nous en déduisons l'importance des préjugés néoclassiques, c'est-à-dire des précompréhensions de certains concepts au travers du cadre dominant. Les débats scientifiques et politiques semblent toutefois permettre de réduire ces préjugés et conscientiser les choix opérer par les acteurs.
Keywords: Appropriation theory; Comptabilité; Comptabilité socio-Environnementale; Ecological economics.; Environmental economics; Hermeneutics; Herméneutique; Socio-Environmental accounting; Sociologie de la comptabilité; Sociology of accounting; Théorie de l’appropriation; Économie de l'environnement; Économie de l’environnement; Économie écologique

Les saisies de comptes bancaires en matière civile et commerciale : études de droit international - Guerreiro, Elodie (Université Paris 1, 2020)
La thèse est une étude de droit international portant sur le droit français des saisies de comptes bancaires en matière civile et commerciale. Elle définit le principe de territorialité du droit (au sens subjectiviste, normativiste et savignien). Elle distingue l’aspect procédural de la saisie d’un compte bancaire (la signification) de ses aspects substantiels (injonction de communiquer des données, indisponibilité et/ou transfert du solde du compte bancaire). Par observation du droit positif, elle soutient qu’en chacun de ces aspects, ladite saisie commande l’application de principes (subjectivistes) de territorialité distincts (territorialité des voies d’exécution, territorialité des traitements de données, territorialité des opérations de paiement) ; que seule l’analyse différenciée de ces principes permet de comprendre le régime synthétique des saisies des comptes bancaires en droit international. Cette approche analytique est riche d’enseignements. D’un point de vue pratique, elle permet de dégager des conditions potentielles d’invalidité et/ou d’illégitimité des saisies françaises de comptes bancaires étrangers. Par ailleurs, elle contribue à l’étude du régime international : des significations réelles faites à, et des transferts de données réalisés au sein d’une, personne morale ; du statut réel du compte bancaire. D’un point de vue théorique, elle révèle l’existence de conflits hétérogènes de lois et suggère une méthode pour leur résolution ; elle exige que l’approche subjectiviste du droit international, la lecture personnaliste du compte bancaire et des opérations de paiement, et l’analyse fonctionnelle de la monnaie, soient présentées et développées.
Keywords: Bank accounts; Bank secrecy; Banques; Comptes bancaires; Comptes en banque; Conflict of laws (public law); Conflits de lois (droit public); Data processing; Droit international et droit interne; Droit international privé; Droit monétaire; France; Gouvernance des établissements de crédit; Governance of credit institutions; Mesures conservatoires; Money; Monnaie; Opérations de paiement; Payment transactions; Principe de territorialité; Protection de l'information (informatique) – France; Saisie conservatoire; Secret bancaire; Secret professionnel; Seizure proceeding; Service of process to legal entity; Signification à personne morale; Territoriality principle; Theories of international law; Théories du droit international; Traitement de données

Blockchain, criptoativos e os títulos circulatórios do Direito Comercial - Micheli, Leonardo Miessa De (Universidade de São Paulo, 2020)
Na presente tese, busca-se analisar o fenômeno da blockchain e dos criptoativos, desde sua perspectiva genética relacionada ao comportamento social que explicam e justificam seu surgimento e o exponencial crescimento de sua utilização, passando pelas características e soluções técnicas existentes e propostas para as tecnologias de registro distribuído, denominadas Distributed Ledger Technologies, ou simplesmente DLTs, para, finalmente, observar os instrumentos de reflexo econômico suportados em tais plataformas, aqui denominados títulos circulatórios, sob o ponto de vista teórico do Direito Comercial. Para tal objetivo, é proposta uma estruturação teórica sobre os criptoativos, sua natureza jurídica, classificação e o estudo de seu posicionamento em relação a outros institutos do direito, como a moeda, os valores mobiliários e os títulos de crédito, a fim de identificar possíveis enquadramento dos ativos virtuais na tutela jurídica já existente sobre tais tradicionais instrumentos, tanto por sua teoria quanto por sua regulação. Por fim, ainda são analisadas possíveis aplicações da infraestrutura blockchain na criação e circulação de títulos circulatórios tradicionais do Direito Comercial, como valores mobiliários e mercado de capitais, além dos títulos de crédito desmaterializados. Foram utilizadas para o desenvolvimento da pesquisa as metodologias exploratória e empírica, estruturando-se o conteúdo da tese de forma retórica por meio das seguintes grandes premissas: (i) por quê; (ii) como; e (iii) para quê, identificadas nos subtítulos dos 04 Capítulos como: Por que estas tecnologias disruptivas vieram para ficar? Como é possível a tecnologia conferir o elemento essencial da confiança? O que são e em que se aplicam os ativos virtuais e as redes descentralizadas? Quais outros usos das tecnologias de registro descentralizado podem ser úteis aos instrumentos circulatórios de Direito Comercial? Conclui-se, ao final da pesquisa, que a tutela dos criptoativos deve ser considerada com base na função econômica de cada espécie, conforme sugerido nas conclusões, adequando-se as respectivas tutelas regulatórias às peculiaridades de tais instrumentos, tanto genéticas quanto estruturais, sob pena de esvaziamento da própria causalidade existencial dos ativos virtuais.
Keywords: Banco de dados distribuídos; Blockchain; Brasil; China; Circulatory instruments; Criptologia; Crypto-assets; Cryptoactif; Cryptocurrencies; Currency; DLT; Dinheiro eletrônico; Direito Comercial; Direito Comparado; Droit commercial; Estados Unidos; Europa; Mercado de capitais; Moeda (Economia); México; Negotiable instruments; Securities; Título de crédito; Valeurs mobilières

Les enjeux managériaux des entreprises et des organisations culturelles en contexte de diversité culturelle : le cas du Cameroun. - Loembet, Eric (Université Paris-Saclay, 2020)
La question du développement des entreprises et des organisations culturelles (EOCs) s'est intégrée dans les discours des acteurs-entrepreneurs culturels, dans plusieurs pays africains en vue, d'une appropriation des normes les caractérisant. Un discours qui mérite une clarification dans un environnement fusionnant le formel et l'informel dans la création de richesses. Face à une diversité culturelle favorisant la croissance économique et le développement humain, la création des richesses devient une opportunité de rentabilité et du développement de l’économie culturelle, le cas du Cameroun. Ainsi, les EOCs deviennent et se présentent comme des outils de capitalisation des valeurs et des richesses économiques. À cet effet, analyser et évaluer le secteur de l'économie de la culture, c'est définir le rôle, l’importance et l’impact des EOCs à contribuer à la création de richesses et à la croissance économique au Cameroun. Moteur des échanges des biens et des services culturels, ainsi que des capitaux, les EOCs contribuent au développement de l'économie nationale (PIB). En prenant part active à la croissance économique intérieure d'une nation, elles apportent une valeur ajoutée dans la valorisation des richesses, dans la création d'emploi et le développement de l’humain. Le rôle très capital qu'elles jouent dans l'appropriation et la valorisation des richesses, détermine l'intérêt économique dans la créativité artistique et culturelle. De ces transformations qui agissent au sein des EOCs, il est question de déterminer les enjeux managériaux de développement en contexte de diversité culturelle au Cameroun. Ainsi, la réflexion de cette étude se fonde sur ce paradoxe de la pluralité des richesses et de sa faible contribution à la création de richesses, ainsi qu'au développement de l'économie de la culture camerounaise. The question of the development of enterprises and cultural organisations (EOCs) has been integrated into the discourse of actor cultural contractor in several African countries, with a view to appropriating the standards characterising them. A discourse which deserves clarification in an environment merging the formal and the informal in the creation of wealth. Faced with cultural diversity favoring economic growth and human development, the creation of wealth becomes an opportunity for profitability and the development of the cultural economy, the case of Cameroon. Thus, the EOCs become and present themselves as tools for capitalising on economic values and wealth. To this end, analysing and evaluating the cultural economy sector means defining the role, importance and impact of the EOCs in contributing to the creation of wealth and economic growth in Cameroon. Driving the exchange of cultural goods and services, as well as capital, the EOCs contribute to the development of the national economy. By taking an active part in the internal economic growth of a nation, they bring added value in the valuation of wealth, in job creation and human development. the very crucial role that they play in the appropriation and enhancement of wealth, determines the economic interest in artistic and cultural creativity. of these transformations that are taking place within the EOCs, it’s a question of determining the managerial stakes of development in the context of cultural diversity in Cameroon. the reflection of this study will be based on this paradox of the plurality of wealth and it’s low contribution to the creation of wealth, as well as to the development of the economy of Cameroonian culture.
Keywords: Cameroon; Cameroun; Cultural Diversity; Cultural Enterprises; Cultural and Creative; Culture; Diversité culturelle; Diversité culturelle – Cameroun; Economics of Culture; Economie de la culture; Enjeux managériaux; Entreprises (développement); Entreprises culturelles; Industries culturelles; Industries culturelles et créatives; Managerial Issues

Double taxation treaty interpretation : lessons from a case down under - Du Plessis, Izelle (Potchefstroom Electronic Law Journal, 2020)
In the Australian case of Bywater Investments Ltd v Commissioner of Taxation; Hua Wang Bank Berhad v Commissioner of Taxation (the Bywater case) the Australian High Court dealt with the question of whether certain companies were resident in Australia for income tax purposes. The majority answered this question by applying Australian domestic law. In a separate but concurring judgement, Gordon J also discussed the interpretation and application of the relevant double taxation treaty. This contribution analyses Gordon J's judgment to extract guidance from it for the South African courts on their interpretation of double taxation treaties. It is submitted that South African courts should also follow the "first step" proposed by Gordon J when interpreting double taxation treaties. South African courts may find Gordon J's judgment "instructive" when dealing with the interpretation of the "place of effective management" concept in both domestic law and double taxation treaties. In his judgment Gordon J favours the goal of common interpretation and it is argued that South African courts should follow this example and explicitly support this notion in applicable cases. From Gordon J's judgment and the judgement in Krok v Commissioner, South African Revenue Service, it is deduced that the positions in South Africa and Australia are similar in that the courts in both countries will be bound by the principles of Articles 31 and 32 of the Vienna Convention on the Law of Treaties when interpreting double taxation treaties. Moreover, Gordon J's judgment indicates that the domestic principles of interpretation should not be used in the interpretation of double taxation treaties. Recent South African cases have suggested that there are no differences between the South African domestic principles of interpretation and those contained in Articles 31 and 32 of the Vienna Convention on the Law of Treaties. This contribution submits that there are many similarities between the two, but that the rules are not exactly the same. South African courts should be aware of these differences and rather apply the rules of public international law, including those contained in the Vienna Convention on the Law of Treaties, when they interpret double taxation treaties. Gordon J specifically identifies the category of the Vienna Convention on the Law of Treaties in which he places the Commentary on the OECD Model Tax Convention, to rely on it for his interpretation of the relevant double taxation treaty. South African courts may well learn from this approach, to create more certainty in the process of interpreting a double taxation treaty.
http://hdl.handle.net/10019.1/124068

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Le secret bancaire à l'épreuve du respect de la vie privée du client de la banque au Cameroun - Levy, Koah Serge (International Multilingual Journal of Science and Technology, 2020)
Les relations entre la banque et ses clients peuvent être de divers ordres, mais le point le plus sensible est celui relatif au secret bancaire qui par ricochet concerne le respect de la vie privée du client de la banque. Le respect du secret bancaire est consacré par le législateur Camerounais à travers la loi du 21 avril 2003 relative au secret bancaire, cette loi énumère les sanctions liées à la violation dudit secret, tout en déterminant les sujets et objet y relatifs. Toutefois, dans la pratique, un constat alarmant a été fait, celui de certaines restrictions du secret bancaire qui conduit inexorablement à la violation de la vie privée du client de la banque. C’est ainsi que dans le cadre de la lutte contre le blanchiment des capitaux, et dans le cadre des rapports entre la banque avec les autorités publiques et de contrôle, la violation du secret bancaire devient autorisée, et jouit d’une double consécration de l’exemption de responsabilité en cas de violation dudit secret. Cette double consécration est le fait des législateurs Camerounais et communautaire CEMAC. Ce qui ne tend pas à favoriser le respect de la vie privée du client de la banque dans la mesure où les suspicions qui conduisent à communiquer les informations relatives au secret bancaire peuvent ne pas être fondées, et malgré cela, il y aurait déjà eu violation du secret bancaire. The relations between banks and their clients are of various natures, but the most sensible point is that of banking secret which by ricochet concerns the privacy of the bank client. The respect of the banking secret is provided for by the Cameroon legislator through the Law of 21 April 2003 regulating Banking Secret. This law enumerates the sanctions imposed when this bank secret is violated, at the same time determining the parties and objects involved. Meanwhile an alarming note has been taken. There are certain restrictions to the banking secret that leads inexorably to the violation of the privacy of the bank client. In the aim to fight against money laundering and in the relations between banks and public authorities and of control, the violation of banking secret becomes authorized and benefits from a double consecration of exemption from responsibility in case of violation of the right to banking secret. This double consecration is provided by Cameroon and community CEMAC legislators. This does not favors the respect of the privacy of the bank client given that the suspicions leading to the communication of these information regarding the banking secret may not be founded and despite this, the right to banking secret would already be violated.
Keywords: Bank Client; Banking Secret; Blanchiment de capitaux; Client de la banque; Money Laundering; Private life; Secret bancaire; Vie privée

The Ability of Short-term Accounting Accruals to Predict Cash Flows of Algerian Companies - Bilal, Kimouche (An-Najah University Journal for Research - B (Humanities), 2020)
هدفت الدراسة إلى استكشاف مدى قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية، حيث شملت 14 شركة جزائرية بين 2003 و،2015 ليبلغ عدد المشاهدات الكلية خالل الفترة 117 مشاهدة. وقد تم قياس التدفقات النقدية بصافي التدفقات النقدية التشغيلية، وتم التعبير عن المستحقات المحاسبية قصيرة األجل بـ: التغير في حسابات الزبائن والمدينين، التغير في حسابات الموردين والدائنين، والتغير في المخزونات. وقد أثبتت النتائج ضعف قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية للفترة المقبلة، حيث كانت عالقة هذه األخيرة ببنود المستحقات المحاسبية قصيرة األجل غير معنوية، باستثناء عالقتها بالتغير في حسابات الموردين والدائنين This study aims to explore the ability of short-term accounting accruals to predict cash flows. It included 117 observations during 2003 to 2015, which concern 14 Algerian companies. Cash flows have been measured by operating cash flow (OCF). However, short-term accounting accruals have been expressed by change of accounts receivable and debtors, change of accounts payable and creditors, and change of inventories. The results indicated a failure of current short-term accounting accruals to predict cash flows of next period. Except for change of accounts receivable and debtors, the correlations of future operating cash flows with other Short-term accounting accrual items are not significant.
Keywords: Cash flows; Change of accounts payable and creditors; Change of accounts receivable and debtors; Change of inventories; Long-term accounting accruals; Short-term accounting accruals

L'évolution de la gestion de fait en comptabilité publique camerounaise - Nguimfack Voufo, Théophile; Beyene Belingue, Hermann Franklin (International Multilingual Journal of Science and Technology, 2020)
En comptabilité publique camerounaise, l’évolution du régime de la gestion de fait paraît contrastée. Tandis que son champ d’application s’étend dans la législation récente, l’on assiste paradoxalement à la restriction de l’office contentieux de la juridiction des comptes. In Cameroonian public accounting, the evolution of the de facto management regime appears to be contrasted. While its scope of application has been extended in recent legislation, paradoxically, we are witnessing the restriction of the contentious office of the Audit Bench.

Protesto notarial no âmbito do contrato de mútuo bancário - Santos, Reinaldo Velloso dos (Universidade de São Paulo, 2020)
As instituições financeiras exercem um papel de extrema relevância na economia contemporânea, intermediando recursos para concessão de crédito à produção e ao consumo. Para melhor desempenhar essa função precisam de meios que assegurem o cumprimento das obrigações. Dentre esses meios está o protesto notarial, ato de incumbência de um profissional do Direito dotado de fé pública, que documenta solenemente a manifestação da insatisfação do credor, sendo revestido de ampla publicidade. É precedido de intimação do devedor, a quem se concede a oportunidade de voluntariamente adimplir a obrigação. Esse instituto, arraigado na tradição jurídica brasileira, tem-se revelado como uma alternativa ao processo judicial, permitindo a recuperação do crédito de forma mais célere e com custo reduzido. No trabalho é apresentado um panorama dos contratos bancários, incluindo o mútuo, bem como do protesto notarial. Além disso, trata dos principais aspectos relativos ao protesto do contrato de mútuo bancário e da cédula de crédito bancário. Ao final, são apresentadas reflexões do autor sobre o tema. As características peculiares do protesto notarial reforçaram seu papel histórico no Brasil. E as recentes modificações na disciplina do instituto certamente contribuirão para sua utilização de forma mais eficiente pelas instituições financeiras, com a perspectiva de redução das taxas nos empréstimos, beneficiando a produção e circulação de riquezas e, por conseguinte, permitindo o desenvolvimento econômico do país. Financial institutions play a relevant role in contemporary economy, by intermediating credit facilities for production and consumption. Availability of efficient enforcement measures is of the essence in such process. Among these providences is the protest, which consists on a formal proof of dishonor, drawn by a public notary, who is a legal professional vested with public faith. Information about protests is public and can be provided to anyone. The notary sends prior notice to the debtor, thus offering a last opportunity to pay the overdue amount to prevent the protest. This institution, rooted in the Brazilian legal tradition, became an alternative to judicial procedure, making the protest a quick and inexpensive debt recovery tool. This thesis presents an overview of banking agreements, including loans, as well as the notarial protest. In addition, the main aspects related to the protest of loan agreements and the cédula de crédito bancário - a negotiable instrument issued by the borrower - are also contained herein. At the end, the author presents his reflections on the topic. The peculiar characteristics of the notarial protest reinforced its historical role in Brazil. And the recent regulatory changes will certainly contribute to increase the protest's effectiveness, especially for financial institutions, with the prospect of reducing interest rates in loan agreements, thus benefiting the production and circulation of wealth, and bringing forth economic development to Brazil.
Keywords: Banking agreement; Banking loan; Contrat; Contrato bancário; Default; Direito notarial; Inadimplemento das obrigações; Notarial law; Notarial protest; Protesto de título; Protêt notarié; Prêt bancaire

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Tax Competition: Global but Virgin under Rwandan Law - Habimana, Pie (Recht in Afrika, 2020)
This paper’s foundation is the global character of (harmful) tax competition. While this phenomenon’s global existence is widely recognised alongside the…

Essais sur l'efficience et la fiscalité pétrolière dans les pays en développement - Gab-Leyba, Guy Dabi (Université Clermont Auvergne, 2020)
L’objectif de cette thèse est de mettre en évidence les déterminants de l’efficience des politiques publiques dans les pays en développement. Les résultats relèvent que les pays dotés de ressources naturelles et en situation de fragilité ont tendance à avoir des dépenses publiques d’éducation primaires moins efficientes. Les résultats révelent aussi que l’accroissement de la part des dépenses de santé dans les dépenses totales des ménages, du taux d’incidence de la pauvreté, du taux d’alphabétisation et la localisation en zone considérée comme austère réduisent l’efficience des structures de santé. A l’inverse, la hausse du taux d’incidence du paludisme, du taux de prévalence de la malnutrition améliorent l’efficience des structures de santé. S’agissant de l’efficience des établissements de crédits, les résultats mettent en exergue une amélioration du score d’efficience sur la période 2000-2015 en dépit du fait qu’en moyenne, l’efficience des banques de la zone CEMAC se situe autour de 33 %. Les estimations montrent aussi qu’une taille importante et une forte liquidité améliorent l’efficience technique des établissements de crédits tandis qu’un accroissement du risque bancaire la réduit. Enfin, l’évaluation des régimes fiscaux pétroliers en application au Tchad révèle que les contrats de partage de production permettent à l’Etat de capter une part plus importante de la rente pétrolière comparativement aux contrats basés sur le système de concession. En outre, les contrats basés sur le partage de production présentent la caractéristique d’être progressif. Ces résultats ont des implications en matière de politique économiques. Ainsi, les pays en developpement devraient en priorité améliorer la qualité des dépenses sociales en promouvant la transparence et la bonne gouvernance dans la mise en œuvre des projets de developpement et politiques publiques. En particulier, dans le secteur de la santé, il est urgent d’améliorer la qualité du personnel de santé et une meilleure programmation des dépenses de fonctionnement visant à rendre les infrastructures de santé opérationnelles. Ensuite, pour accroitre la rentabilté des banques dans les pays de la zone CEMAC, il conviendrait de diversifier les structures bénéficiaires des crédits et mettre en œuvre des réformes visant à améliorer le climat des affaires. Enfin, le Gouvernement tchadien devrait réactiver une politique contra-cyclique en vue de se prémunir des fluctuations des recettes pétrolières. The aim of this thesis is to highlight the determinants of the efficiency of public policies in developing countries. The results show that countries with natural resources and in fragile situations tend to have less efficient public spending on primary education. The results also reveal that the increase in the share of health expenditure in total household expenditure, the poverty incidence rate, the literacy rate and the location in areas considered as isolated reduce the efficiency of health structures. Conversely, the increase in the incidence rate of malaria and the prevalence rate of malnutrition improve the efficiency of health structures. Regarding the efficiency of credit institutions, the results highlight an improvement in the efficiency score over the period 2000-2015 despite the fact that on average, the efficiency of banks in the CEMAC zone is around 33%. Estimates also show that a large size and high liquidity improve the technical efficiency of credit institutions while an increase in banking risk reduces it. Finally, the assessment of petroleum tax regimes in force in Chad reveals that production sharing contracts allow to Government to capture a higher share of oil rent compared to contracts based on the concession system. In addition, contracts based on production sharing have the characteristic of being progressive. These results have implications for economic policy. Thus, developing countries should give priority to improving the quality of social spending by promoting transparency and good governance in the implementation of development projects and publics policy. In particular, in the health sector, there is an urgent need to improve the quality of health personnel and better programming of operating expenditure aimed at making health infrastructures operational. Then, to increase the profitability of the banks in the countries of the CEMAC zone, it would be advisable to diversify the structures beneficiary of the credits and to implement reforms aiming at improving the business environment. Finally, the Chadian Government should reactivate a counter-cyclical policy in order to guard against fluctuations in oil revenues.
Keywords: Cash flow model; Concession contrat; Contrat de concession; Contrat de partage de production; Dépenses publiques; Education; Efficency; Efficience; Health; Impôts; Industrie et commerce; Modèle de flux de trésorerie; Natural ressources; Order m; Pays en voie de développement; Politique fiscale; Politique publique; Production sharing contrat; Public spending; Pétrole (exploitation); Ressources naturelles; SFA; Santé

Le SYSCOHADA révisé à l’épreuve de transparence des entreprises : une étude exploratoire en contexte camerounais - Nga Nga, Félicien; Wanda, Robert (Revue du contrôle, de la comptabilité et de l’audit, 2020)
L’objectif de ce papier est de vérifier si le SYSCOHADA révisé va améliorer la transparence des informations comptables dans les entreprises au Cameroun. Pour atteindre cet objectif, nous avons diligenté des entretiens semi-directifs auprès de 06 experts camerounais (expert-comptable, expert banquier, directeur des impôts, comptables) suffisamment informés des réformes OHADA et faisant usage régulier des états financiers fournis par les entreprises camerounaises. Au terme des analyses, les premiers résultats suggèrent que, le SYSCOHADA révisé ne pourra pas améliorer la transparence des états financiers fournis par les entreprises locales camerounaises (PME, PMI). Par contre, les seconds résultats montrent que, le SYSCOHADA révisé va améliorer la transparence des états financiers des entreprises multinationales installées au Cameroun et faisant appel public à l’épargne. Ces résultats montrent que, malgré la morosité des entreprises camerounaises à s’engager en bourse, le marché financier pourrait être un atout de transparence et par ricochet de performance via la confiance dans le financement dont elles pourraient en bénéficier.
Keywords: Cameroun; Entreprise; SYSCOHADA; Transparence

Transition to the Revised OHADA Law on Accounting and Financial Reporting: Corporate Perceptions of Costs and Benefits - Fossung, Micheal Forzeh; Ntoung, Lious Agbor Tabot; Santos de Oliveira, Helena Maria; Pereira, Cláudia Maria Ferreira; Bastos, Susana Adelina Moreira Carvalho; Pimentel, Liliana Marques (Journal of Risk and Financial Management, 2020)
This paper examines the ongoing transition to the revised Organisation for the Harmonisation of Business Law in Africa Act on Accounting and Financial Reporting for companies in general and to the International Financial Reporting Standards for listed and group companies with a particular focus on recent institutional developments and corporate concerns. The study used 80 professional accountants, most of whom were members of the Institute of Chartered Accountants of Cameroon and academics. Using the descriptive statistics, the study shows that the transition to the revised OHADA brings about a high level of comparability and transparency of the financial statements, that the International Financial Reporting Standards can be implemented in Cameroon (but not fully), and that the benefit of the transition exceeds the cost.
Number: 8
Keywords: Comparability; IFRS; OHADA accounting; perception; transition

L'interventionnisme par les dépenses fiscales en droit pubilic financier camerounais - Oumarou, Mohamadou (International Multilingual Journal of Science and Technology, 2020)
L’expression de l’interventionnisme par le biais des dépenses fiscales s’est considérablement développée dans notre système fiscal. En effet, ce mode d’utilisation de l’instrument fiscal dans un but autre que la couverture des charges publiques poursuit une pluralité des finalités à travers les dépenses fiscales. Ceci étant dit, nous avons d’une part, la finalité économique des dépenses fiscales et d’autre part, la finalité socio-politique. Relevons aussi que cette forme d’interventionnisme demeure perfectible en ce sens qu’il dispose des imperfections qui sont susceptibles d’être corrigé pour plus d’efficacité dans son recours dans notre environnement fiscal en proie à la performance. The expression of interventionism through tax expenditures has grown considerably in our tax system. Indeed, this method of using the fiscal instrument for a purpose other than covering public charges pursues a plurality of purposes through tax expenditures. That being said, we have on the one hand the economic purpose of tax expenditures and on the other hand the socio-political purpose. Note also that this form of interventionism can still be improved in the sense that it has imperfections that are likely to be corrected for more efficiency in its use in our tax environment plagued by performance.
Keywords: Cameroon; Cameroun; Droit public financier; Dépenses fiscales; Financial public law; Interventionism; Interventionnisme; Tax expenditure

Le Système Comptable OHADA face aux défis de la finance verte : une analyse conceptuelle - Ousmanou, Alim (Journal of Academic Finance, 2020)
Environmental issues and awareness of climate change are pushing companies today to adapt to a new context, limiting their harmful emissions and investing in sustainable projects that respect the environment. Thus, they can benefit from manna of financing, called green financing, adapted to their commitment. The emergence of this new method of financing challenges both professionals and researchers. As such, the purpose of this work is to make a conceptual analysis of the contribution of the OHADA accounting system in the reduction of information asymmetry under the green financing contract. To do this, two theories have been mobilized: signal theory and transaction cost theory. In a first, based on signal theory, it appears that the OHADA accounting system can be a signaling tool capable of acting on the risk of adverse selection. Secondly, based on the theory of transaction costs, it can be considered as an institutional arrangement equivalent to internalization capable of reducing the risk of moral hazard and the opportunism of managers in the context of the financing contract green.Key Words: OHADA Accounting System, Information Asymmetry, Green Funding
Number: 1
Keywords: Asymétrie Informationnelle; Financement Vert; Système Comptable OHADA

La dématérialisation des valeurs mobilières en zone CEMAC - N'Tchatat Tounya, Fabrice Léonel (Université de Yaoundé 2, 2020)
La dématérialisation des valeurs mobilières a été amorcée par l’OHADA depuis son Acte Uniforme de 1997 où le mécanisme qui jusque-là n’était optionnel que pour les sociétés faisant appel public à l’épargne, a été étendu à toutes les valeurs émises dans l’espace OHADA de façon obligatoire en faveur de l’Acte Uniforme de 2014. Cette réforme d’envergure a également été posée en zone CEMAC de manière ambivalente. D’un côté par le règlement communautaire N° 01/14 du 25 avril 2014 qui limite la portée de cette dématérialisation aux valeurs mobilières qui sont émises dans le cadre d’un appel public à l’épargne et de l’autre par la loi camerounaise N° 2014/007 du 23 avril 2014 et son décret d’application N° 2014/3763 du 17 novembre 2014, ainsi que la loi gabonaise n°027/2016 du 06 février 2017 fixant le régime de la dématérialisation des valeurs mobilières en République Gabonaise qui étendent la dématérialisation à toutes les valeurs mobilières émises sur le territoire national. Aux termes de l’article 1er alinéa 2 de la loi camerounaise précédemment citée, la dématérialisation des valeurs mobilières est une opération de substitution des certificats physiques des titres, par l’inscription en compte des titres sous forme électronique. Il s’agit d’une révolution économique qui facilite la circulation et la conservation des titres, initialement détenus sous la forme matérielle. La dématérialisation des valeurs mobilières est un processus, elle est donc prescriptible. C’est-à-dire que sa mise en œuvre est limitée dans le temps. Ainsi, compte tenu du fait que la dématérialisation est une opération délicate, qui a une échéance et qui affecte le régime juridique des valeurs mobilières, l’étude d’un tel sujet invite à s’interroger sur les effets de la dématérialisation sur les valeurs mobilières et la pertinence des normes ayant vocation à les encadrer dans la sous-région tant dans sa mise en œuvre que dans la gestion des valeurs mobilières dématérialisées. Cette réflexion trouve tout son sens dans la mesure où d’une part, le législateur communautaire restreint le mécanisme de dématérialisation des valeurs mobilières tandis que les législateurs nationaux en font une portée large. D’autre part, les législateurs tant communautaire que nationaux ont ficelés les modalités de dématérialisation sans prendre en compte les réalités de l’activité économique sous régionale telle que l’inexistence des titres physiques. Enfin, à l’instar de l’AUDSCGIE du 30 janvier 2014, les textes en vigueur dans la sous-région rendent désormais obligatoire le régime d’inscription en compte des valeurs mobilières, lequel n’est pas sans effet sur le mode de détention et de circulation de celles-ci en zone CEMAC. The dematerialization of securities has been initiated by OHADA since its Uniform Act of 1997 where the mechanism which until then was optional only for companies making public offerings, has been extended to all the securities issued in the OHADA area on a mandatory basis in favor of the Uniform Act of 2014. This major reform was also applied in the CEMAC zone in an ambivalent manner. On the one hand by Community regulation N ° 01/14 of April 25, 2014 which limits the scope of this dematerialization to transferable securities which are issued within the framework of a public offering and on the other by law Cameroonian N ° 2014/007 of April 23, 2014 and its implementing decree N ° 2014/3763 of November 17, 2014, as well as the Gabonese law n ° 027/2016 of February 06, 2017 establishing the dematerialization regime for securities in Gabonese Republic which extend the dematerialization to all the securities issued on the national territory. Under the terms of article 1, paragraph 2, of the Cameroonian law cited above, the dematerialization of securities is a substitution operation for the physical certificates of the securities, by registering the securities in electronic form. It is an economic revolution which facilitates the circulation and conservation of securities, initially held in physical form. The dematerialization of securities is a process, so it can be prescribed. That is to say, its implementation is limited in time. Thus, given the fact that dematerialization is a delicate operation, which has a deadline and which affects the legal regime of transferable securities, the study of such a subject invites us to wonder about the effects of dematerialization on securities and the relevance of the standards intended to guide them in the sub-region both in its implementation and in the management of dematerialized securities. This reflection finds all its meaning insofar as, on the one hand, the Community legislator restricts the mechanism of dematerialization of securities while the national legislators make a broad scope of it. On the other hand, both Community and national legislators have tied up the dematerialization modalities without taking into account the realities of sub-regional economic activity such as the absence of physical titles. Finally, like the AUDSCGIE of January 30, 2014, the texts in force in the sub-region now make compulsory the system of registration in securities account, which is not without effect on the method of holding and circulation of these in the CEMAC zone.

Le contrôle de gestion dans les activités de services : contribution à la délimitation des facteurs critiques de son utilisation - Elqouri, Abdelouahed (La Revue Marocaine de la Pensée Contemporaine, 2020)
Cette recherche, basée sur une méthodologie qualitative au sens de YIN auprès de quatre entreprises des services au Maroc, nous a permis de délimiter les facteurs critiques de l’utilisation de contrôle de gestion dans les activités de services. Elle s’inscrit dans le cadre d’une mission qui nous a été confiée par deux cabinets du conseil : « ABH gestion » et « Fiscalist ».Les résultats de notre recherche nous ont permis de valider l’hypothèse de notre problématique. Nous avons abouti à ce que la réussite ou l’échec d’utilisation de contrôle de gestion dans les activités de services dépend de plusieurs facteurs critiques comme les spécificités des activités de services, la responsabilisation, la contractualisation, décentralisation, l’approche partenariale, la coordination et la formalisation des activités, le système d’information, les pratiques de transmission des informations, la légitimation de l’instrumentalisation de la gestion, la formation de personnel, l’apprentissage et l’appropriation des outils de gestion, les facteurs de contingence, la place de contrôle de gestion et le statut du contrôleur de gestion. Abstract :This research, based on a qualitative methodology in the sense of YIN with four service companies in Morocco, allowed us to delimit the critical factors of the use of management control in service activities. It is part of a mission entrusted to us by two consulting firms: "ABH gestion" and "Fiscalist".The results of our research allowed us to validate the hypothesis of our problem. We have achieved that the success or failure of using management control in service activities depends on several critical factors such as the specifics of service activities, empowerment, contractualization, decentralization, the partnership approach, coordination and formalization of activities, the information system, information transmission practices, legitimization of the management instrumentation, staff training, learning and appropriation of management tools, factors contingency, the management control place and the status of the management controller.
Keywords: Activités de services; Contrôle de gestion

La protection des marchés boursiers par le contrôle des intermédiaires financiers en zone OHADA - Djouakep, Jado (International Multilingual Journal of Science and Technology, 2020)
La réglementation des marchés financiers a fait des intermédiaires un maillon essentiel sur les places boursières. L’obligation d’intermédiation qui en découle contraint les investisseurs et les émetteurs à faire appel aux services d’un intermédiaire lorsqu’ils interviennent sur les marchés financiers. Cet impératif met ainsi en relation un intermédiaire supposé professionnel et un intervenant financier considéré comme étant moins aguerri contre les risques du marché financier. Une telle relation n’est donc pas à l’abri d’un abus. Régulièrement, des comportements abusifs ou aventureux de certains ont gravement lésé les épargnants, provoquant des scandales financiers nuisibles à l’intérêt général. Le contrôle des intermédiaires apparait de ce fait comme une nécessité. Il faut protéger les investisseurs et par ricochet l’ensemble du marché. Le contrôle constitue en effet une solide garantie de l’application effective des contraintes posées par la réglementation. C’est une composante essentielle de l’activité des régulateurs financiers, qui sont à la base de la protection des marchés. Leur mission de contrôle étant permanente, elle commence dès l’instant où l’intermédiaire sollicite un agrément et se poursuit après son installation sur les marchés financiers. Le contrôle porte ainsi sur la qualité des produits et des services financiers proposés. Il concerne également les actes susceptibles d’avoir une incidence sur le cours des titres ou ceux pouvant compromettre les intérêts des investisseurs. Le contrôle des intermédiaires est donc une nécessité à l’édification d’un marché financier sécurisé et efficient. The regulation of the financial markets has made intermediaries an essential link on the stock exchanges. The resulting intermediation obligation obliges investors and issuers to use the services of an intermediary when they intervene in the financial markets. This imperative thus puts a supposed professional intermediary in contact with a financial player considered to be less seasoned against the risks of the financial market. Such a relationship is therefore not immune to abuse. Regularly, abusive or adventurous behavior by some has seriously harmed savers, causing financial scandals harmful to the public interest. The control of intermediaries therefore appears to be a necessity. It is necessary to protect the investors and by extension the whole market.
Keywords: Financial markets (protection); Intermediary (control); Intermédiaire (contrôle); Investisseur; Investor; Marché financier (protection)

Deveres de informação e adequação: responsabilidade civil dos intermediários financeiros - Paiva, Rafael Bianchini Abreu (Universidade de São Paulo, 2020)
O objetivo desta tese é apresentar, em perspectiva comparada entre Brasil e União Europeia, quais deveres devem ser impostos aos intermediários financeiros para que seus clientes não profissionais adquiram produtos e serviços adequados aos seus conhecimentos, experiências, necessidades, objetivos e situação financeira e, em caso de descumprimento desses deveres, as hipóteses e a extensão da responsabilidade civil dos intermediários financeiros. Nesse sentido, a crise financeira internacional de 2008 foi um divisor de águas por evidenciar problemas na distribuição de diversos instrumentos financeiros e resultar em diversos processos administrativos e judiciais, bem como reação de reguladores em diferentes jurisdições. Este trabalho está dividido em quatro Capítulos, cuja estrutura é a seguinte: I. Processo decisório e mercados financeiros: 1. As decisões individuais segundo a Teoria Neoclássica; 2. Risco, retorno e a Hipótese dos Mercados Eficientes (HME); 3. Falhas de mercado; 4. Racionalidade limitada: vieses cognitivos e emocionais do processo decisório; 5. Agentes quase racionais e Hipótese da Instabilidade Financeira (HIF); II. Intermediação e inovações financeiras: 1. A atividade de intermediação financeira; 2. Inovações financeiras de primeira geração e ciclo de endividamento privado; 3. Inovações financeiras recentes: moeda eletrônica, pagamentos instantâneos, criptoativos e stablecoins; III. Deveres de informação e adequação (suitability): 1. Princípios gerais e recomendações das organizações internacionais; 2. Deveres de informação e adequação na União Europeia; 2.1. Antes da crise financeira de 2008; 2.2. Reformas a partir da crise financeira de 2008; 3. Deveres de informação e adequação no Brasil; 3.1 Crédito rotativo; 3.2 Jurisprudência; 3.3 Decisões da CVM; IV. Responsabilidade civil. Considerações finais.
Keywords: Complex financial products; Cryptoassets; Cryptocurrencies; Dinheiro eletrônico; E-money; Financial innovations; Financial institutions; Instituição financeira; Intermédiaire financier; Marché financier; Mercado financeiro; Responsabilité civile; Stablecoins; Suitability

La commande publique en droit camerounais - Batoum-Ba-Ngoue, Samuel Théophile (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2020)

دور البنوك التجارية في مكافحة عمليات غسيل الأموال - بومدين, نبية (Ibn Khaldun University of Tiaret, 2020)
تعتبر البنوك التجارية من أهم المحطات المالية التي تقوم بعمليات قبول الودائع ودفعها عند الإستحقاق كما تساهم في عملية خلق النقود بكميات كبيرة هذا ما جعلها الأكثر عرضة لجريمة غسيل الأموال والغاية من هذا هو معرفة كيف تكافح هذه البنوك لجريمة خطيرة مثل هذه والتي سادت كل العالم هذا ما أدى إلى دراستنا لهذا الموضوع الذي إعتمدنا فيه على المنهج الوصفي التحليلي و بالتالي عند دراستنا له توصلنا إلى مجموعة من النتائج تتجلى في معرفة الظاهرة بأنها ظاهرة خطيرة سريعة الإنتشار ،عرضة البنوك بهذه الظاهرة كونها تقوم بعدة عمليات ،وجوب على الدولة أن تكافح هذه الجريمة وذلك بوضع قوانين تشريعية تعاقب كل من قام بإرتكاب هذه الظاهرة الخطيرة. Commercial banks are considered one of the most important financial stations that carry out the processes of accepting and paying deposits at maturity and also contribute to the process of creating money in large quantities. This led to our study of this subject, in which we relied on the descriptive and analytical approach, and therefore upon our study of it, we reached a set of results that are evident in the knowledge of the phenomenon that it is a dangerous and rapidly spreading phenomenon. The banks are exposed to this phenomenon as they carry out several operations. Legislative laws punishing anyone who committed this dangerous phenomenon.
Keywords: Banques commerciales; Blanchiment d'argent; Système bancaire; البنوك التجارية; الجهاز المصرف; جريمة غسيل الاموال

The Opportunity for Convergence of SYSCOHADA towards IFRS Standards: An Effect of Coercitive and Mimetic Isomorphism - Souleymanou, Kadouamaï; Mouafo, Cédrick Nzokouo (Journal of Modern Accounting and Auditing, 2020)
The last few years have been marked by the increase in power of IFRS international accounting standards. From the full or partial adoption to the gradual convergence, many countries have displayed a strong preference for these standards. Meanwhile, the implementation of International Financial Reporting Standards (IFRS standard) in the context of developing countries is not trivial. We are witnessing an unprecedented clash between the authors who support the interest of these standards for developing countries, and those who conversely demonstrate that these norms are not well adapted to the context of those countries. Falling within this problematic, this thesis analyses the issues and determinants of the convergence of the Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) accounting system towards IFRS international accounting standards in view of the reforms introduced by the last revision. From a sample of 10 companies, among which two local firms, two international firms, three publicly traded companies, and three not listed other companies, we show that the current convergence towards international accounting standards follows an effect of coercitive and mimetic isomorphism. In so doing, the timely implementation of these standards in the context of Cameroon is contingent with a number of structural and environmental factors that call their pertinence into question.
Keywords: Convergence; Developing countries; IFRS; SYSCOHADA; Système Comptable OHADA

Structure de gouvernance et performance des entreprises :une analyse comparative des grandes entreprises performantes (GEP) et non performantes (GENP) au Cameroun - Kengni Fomo, Gildas Alex; Tchitchoua, Jean (Revue Economie, Gestion et Société, 2020)
L’objet de cette étude est d’analyser l’impact des caractéristiques de l’organisation comptable sur la qualité de l’information comptable et financière produite par les PME. Une analyse de régression logistique binaire, une régression linéaire simple et un test de khi-deux sur les données recueillies par administration du questionnaire auprès d’un échantillon de73 PME constitué par choix raisonné permettent, d’une part, de constater que les PME camerounaises mettent en place une organisation comptable aux fins de produire non seulement des informations comptables obligatoires, mais également des informations comptables destinées à leur propre usage. D’autre part, les conclusions empiriques de cette étude renseignent que le recours à un prestataire dans le cadre d’une externalisation de la fonction comptable et le degré d’informatisation de l’activité comptable influencent positivement et significativement la qualité de la production comptable et financière des PME. A contrario, la féminisation de la fonction comptable se trouve être une des caractéristiques de l’organisation comptable sans influence sur la qualité du produit comptable et financier des PME. The purpose of this study is to analyze the impact of the characteristics of the accounting organization on the quality of the accounting and financial information produced by SMEs. A binary logistic regression analysis, a simple linear regression and a chi-square test on the data collected by administering a questionnaire from a sample of 73 SMEs constituted by reasoned choice allow, on the one hand, to observe that the SMEs Cameroonians are setting up an accounting organization in order to produce not only mandatory accounting information, but also accounting information intended for their own use. On the other hand, the empirical conclusions of this study show that the use of a service provider in the context of an outsourcing of the accounting function and the degree of computerization of the accounting activity positively and significantly influence the quality of accounting production. and finance for SMEs. Conversely, the feminization of the accounting function is found to be one of the characteristics of the accounting organization without influencing the quality of the accounting and financial product of SMEs.
Keywords: Actionnariat; Administrateurs Indépendants; Conseil d'administration; Firm performance; Foreign shareholders; Independent director; Institutional shareholders; Size of the board of directors

La protection des intervenants commerciaux sur le marché financier CEMAC par leurs droits de savoir - Lehwa, Léon (International Multilingual Journal of Science and Technology, 2020)
Il existe différents acteurs qui interviennent sur la place boursière CEMAC. Ces acteurs sont constitués de ceux qui ont un statut institutionnel et de ceux qui ont un statut des commerciaux. Parmi ces divers intervenants, une place de choix a été réservée aux intervenants commerciaux qui jouent des rôles importants dans le circuit de l’activité boursière. Les émetteurs, en tant que personnes morales de droit privé ou public, sont ceux qui offrent au public des Valeurs Mobilières ou autres produits de placement négociables ouvrant des droits à leur encontre. Lorsqu’ils procèdent à une opération par appel public à l’épargne, ils sont tenus de produire un document dénommé « Document d’Information ». Celui-ci doit contenir l’ensemble des éléments nécessaires sur le patrimoine, la situation financière, les résultats, les perspectives de l’émetteur et les droits attachés aux titres offerts. Il doit suffisamment préciser les caractéristiques des titres dont l’admission est demandée, le pourcentage en capital et en droit de vote qu’ils représentent et la répartition du capital avant et après l’opération. Tous ces éléments permettent aux investisseurs de fonder leurs jugements sur le patrimoine de l’émetteur, par voie de conséquence protégé son consentement. L’investisseur, quant à lui, est toute personne, physique ou morale, qui souscrit aux titres financiers émis par un émetteur. Il est lié à l’émetteur par un contrat d’investissement. Leurs droits à la protection se justifient en ce sens qu’ils confient la destinée d’une quote-part de leur patrimoine à la société émettrice. Or, il est naturel que celui qui donne mandat d’administrer un bien obtienne un compte-rendu de gestion aussi exact et fidèle que possible. On voit mal comment un investisseur mettra son fond dans une société sans être informé. Toutes ces personnes ont besoin d’un minimum d’information d’ordre juridique, économique ou financier pour défendre leurs intérêts catégoriels.
Keywords: Acteurs commerciaux; CEMAC; Commercial stakeholders; Droit de savoir; Financial exchange; Financial markets; Marchés financiers; Right to know

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

La technologie de la blockchain : le futur de la commande publique des États de l’UEMOA ? - Ahouissou, Muriel (Revue Burkinabè de Droit, 2020)

Critical reflections on the development of integrated reporting: Are integrated reporting and IFRS competing frameworks? - Barker, R.; Teixeira, A. (The Routledge Handbook of Integrated Reporting, 2020)
Although integrated reporting emphasizes the contemporaneous relationship between financial and non-financial capitals, its primary purpose is to explain how an organization creates value over time. This is similar to the purpose of management commentary, which is part of a general-purpose financial report. We compare and contrast the information requirements of an integrated report with the type of information that supplements the primary financial information in general purpose financial reports, prepared in accordance with International Financial Reporting Standards (IFRS). We examine whether the information in those reports is intended to be forward-looking and predictive, whether non-financial capitals can (and should) be monetized in order to facilitate integration, and whether the reporting boundary should be drawn in different ways to serve different purposes. We find that the International Integrated Reporting Framework and IFRS do not serve different purposes or apply different approaches, but that – in essence – they are competing frameworks. While IFRS has highly developed standards for reporting financial capital, neither has a well-developed approach for reporting any other capital.

Political business cycles, bank pricing behaviour and financial inclusion in Africa - Iddrisu, Abdul Ganiyu; Turkson, Festus Ebo (Cogent Economics & Finance, 2020)
This paper analyses financial inclusion in Africa focusing on the role of political business cycles and pricing behaviour of banks. We employ a sample of 330 banks operating in 29 African countries to test for two related hypotheses. Panel fixed and random effects were estimated for the period 2002 to 2013. The regression results that ensued suggests first that loan price increases in pre-election and election years. Building on this result and employing various specifications of financial inclusion, the second results suggest that, high bank loan prices in election years tend to increase financial access more, compared to non-election years, and that, high deposit price reduces financial usage but increases financial access in election years, compared to non-election years. By extension, these results have important policy implications for policymakers.
Publisher: Abingdon: Taylor & Francis https://www.econstor.eu/handle/10419/245317
Keywords: Africa; Banks' pricing behaviour; Election; Financial inclusion; Political business cycles

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

IFRS compliance, corporate governance and financial reporting quality of GSE-listed nonfinancial firms - Mbir, Deborah Esi Gyanba; Agyemang, Otuo Serebour; Tackie, George; Abeka, Mac Junior (Cogent Business & Management, 2020)
The adoption of International financial reporting standards (IFRS) has been presented in several empirical literature as a factor that could improve the quality of financial reports. However, Ghana has not attained the desired levels of financial reporting quality after the adoption of IFRS. Literature reveals that lack of proper enforcement of these high-quality standards may result in limited compliance and will undermine the effectiveness of these standards in terms of attaining high-quality financial reports. This study therefore argues that the relationship between IFRS compliance and reporting quality revolves around some enforcement mechanisms like corporate governance structures. In view of that, by using random effect estimation technique, this study examined the role of corporate governance in the relationship between IFRS compliance and the reporting quality of firms listed on the Ghana Stock Exchange (GSE). The study found that the right corporate governance mechanisms will enhance the positive effect of IFRS compliance on reporting quality. This study further recommends that to gain an appreciable level of public confidence in the annual reports of firms listed on the GSE, the audit committee’s independence and the board’s independence should be strengthened to ensure that management does not only adopt IFRS, but that the standards are actually complied with.
Keywords: Compliance; Corporate governance; IFRS; Reporting quality

The Effect of IFRS Adoption on Foreign Direct Investment in Africa - Musah, Alhassan; Adjei, Eunice; Ahmed, Ibrahim Anyass (Journal of Applied Accounting and Taxation, 2020)
Adoption of International Financial Reporting Standards (IFRS) is supposed to help enhance comparability of financial statement, improve the quality of financial reporting and accounting information of businesses in a country. This is expected to help improve Foreign Direct Investment (FDI) in the adopting countries. This study examined the effect of IFRS adoption on FDI inflows in Africa. Unlike previous studies that sample both adopting and non-adopting countries, this study sampled only Africa countries that have adopted IFRS to determine whether the adoption has improved FDI inflows. To achieve this objective, 20 African countries that have adopted IFRS were sampled covering a period 1980 to 2015. Data was sourced from The World Bank financial and Economic Data. Control variables such as GDP growth, openness of the economy, government debt and population growth were included in the model. The correlation and regression analysis showed that IFRS adoption has a positive and significant influence on FDI inflows in Africa. On the other hand, open economy, government debt and population growth had a positive and significant association with FDI. Overall, the results show that African countries that want to improve FDI inflows must improve the quality of their reporting environment by adopting IFRS.
Keywords: Africa; FDI; Foreign direct investment; IFRS; IFRS adoption; Investments; Macroeconomic variables

Fiscal Potential and Political and Institutional Constraints to Increasing Domestic Revenues - Niang, Birahim Bouna; Mbaye, Ahmadou Aly (Center for Global Development, 2020)

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework

Les mécanismes d'incitations fiscales à l'investissement des entreprises étrangères en France et au Gabon - Engone, Kénaelle Cyndie (Université de Limoges, 2019)
L’attractivité territoriale des Etats se trouve au centre des préoccupations tant au niveau national qu’international. Les mesures fiscales dérogatoires destinées à attirer des investissements étrangers s’avèrent nombreuses et complexes, en raison non seulement de l’influence internationale, mais également des hésitations et de l’accumulation des règles nationales. Au Gabon et en France, les incitations fiscales d’attraction territoriale ont été instruites dans des domaines d’activités clés de l’économie. Elles participent ainsi à l’industrialisation de ces pays. Cependant, au-delà de l’industrialisation, ces mesures dérogatoires visent à développer certaines zones du territoire, et surtout à lutter contre le chômage. Néanmoins, loin de toujours parvenir aux résultats escomptés, ces mesures finissent parfois, au fil des années et des modifications successives à se complexifier, les rendant illisibles. The territorial attractiveness of states is at the center of national and international. Derogatory tax measures designed to attract foreign investments are numerous and complex, not only because international influence, but also hesitations and the accumulation of national rules. In Gabon and France, territorial attraction tax incentives have been educated in key activity areas of the economy. They thus participate industrialization of these countries.However, beyond industrialization, these derogations aim to develop certain areas of the territory, and especially to combat unemployment. Nevertheless, far from always achieving the expected results, these measures end up sometimes, over the years and successive modifications to become more complex, making them unreadable.
Keywords: Aides d’Etat; Attractivité (géographie); Competitiveness; Compétitivité; Emploi; Employment; Fiscalité; Gabon; Impôt; Incitations fiscales; Industrialisation; Investissements; Investments; State aids; Tax incentives; Taxe

L'introduction des entreprises à la Bourse régionale des Valeurs Mobilières (BRVM) dans la zone UEMOA : cas de la Société Ivoirienne de Banque (SIB) - Fegbo, Ahonon Emmanuella Ines; Fassoukoye, Safi (Université Mouloud Mammeri, 2019)
Cette étude a pour objectif de connaitre les différentes étapes de l’introduction à la Bourse régionale des valeurs mobilières (BRVM) en tant que place financière régionale de l’UEMOA, régulé par le conseil régional de l’Epargne Publique et des marchés financiers. Pour atteindre cet objectif, nous avons émaillés l’organisation du marché financier dans une approche visant à définir les différents intervenants et leur rôle. Ensuite, nous avons analysés l’activité boursière du marché. Les indicateurs de performance principalement relevés sont le rendement, la liquidité, le volume de transactions et le risque du marché. Le potentiel de la BRVM est encore à exploiter au regard de l’activité économique de la sous-région. Toutefois, le dynamisme du marché boursier est intéressant surtout du fait qu’il offre un rendement intéressant auprès des intéressés. Nous avons soumis les différents indicateurs du marché à une analyse comparative de son évolution à l’échelle des Bourses africaines, afin d’évaluer son degré d’attractivité. Nous recommandons des ajustements sur les différents points relevés visant l’essor de la place financière de la BRVM tout en démontrons les résultats de notre recherche.
Keywords: BRVM; Banque; Bourse; Bourse régionale; Indices boursiers; Marché financier

Le crédit réel individuel : problèmes juridiques et éthiques - Poaty, Marie-Laure (Université de Bordeaux, 2019)
Ce travail se propose d'étudier les aspects juridiques du crédit dit réel dans une confrontation implicite au crédit bancaire qui semble aujourd'hui l'emporter dans le domaine des échanges, en utilisant un système de garantie tiré des suretés réelles. La comparaison engagée est destinée à montrer quel rôle occupe en particulier la réserve de propriété et la fiducie dans le domaine classique de la vente civile et commerciale à destination des particuliers. Au-delà d'une approche technique, il s'agit de restituer un sens aux définitions des droits personnels et réels dans le langage des sources du droit. Il s'agit aussi de s'attacher aux valeurs de justice en terme éthique qui fondent le support de ces droits : dignité des personnes et droit des biens qui tiennent au mécanisme synallagmatique engagé (équivalence des prestations). Mais, il sera aussi tenu compte du rôle parfois déstabilisateur d'éléments économiques extérieurs dans la mesure où ils déséquilibrent les mécanismes juridiques classiques en mettant en concurrence crédit bancaire et crédit réel, alors même qu’il semble que le dernier soit d’avantage justifié. This work proposes to study the legal aspects of trade credit in the case of an implicit impasse with bank credit that seems to prevail today in the field of trade, by using a guarantee system derived from real collateral. The comparison undertaken is intended to show the role played in particular by the retention of title and the trust in the classic field of retail sale to individuals. Beyond a technical approach, it’s about restoring a meaning to definitions of personal and real rights in the language of the law or regulations. It is also a question of attaching to the values of justice in ethical terms which are at the foundation of these rights: the dignity of people and the right to possess goods which are linked to the equality of benefits. But it will also be taken into consideration the sometimes-destabilizing exterior economic elements, in the measure that they destabilize the classic legal mechanisms by putting bank credit and trade credit in competition, even though it seems that the latter is more justified.
Keywords: Bank credit; Collateral; Crédit (droit); Crédit bancaire; Crédit réel; Ethic; Property; Propriété; Sûretés; Sûretés (droit); Trade credit; Éthique

Les prix de transfert et le principe de pleine concurrence dans les pays en développement - Randriamanalina, Tovony (Université Paris-Dauphine, 2019)
La fixation du prix de pleine concurrence par les administrations fiscales des pays en développement soulève des questions singulières. L’objectif fondamental recherché à travers la fixation des prix de transfert est l’affectation de la juste assiette de l’impôt à chaque État concerné par les transactions intragroupes, c’est-à-dire au sein des groupes multinationaux de sociétés. L’OCDE et ses pays membres estiment que le meilleur moyen pour parvenir à cet objectif est de vérifier que le prix de transfert en cause respecte le principe de pleine concurrence, lequel repose sur une comparaison entre les prix pratiqués par les sociétés appartenant à un même groupe et ceux pratiqués pour des opérations similaires, par des entreprises indépendantes. Toutefois, cet objectif n’est pas toujours atteint dans la pratique. Favorisé par l'OCDE, le principe de pleine concurrence suppose la mise en œuvre d’une analyse des faits et circonstances des transactions de chaque contribuable. L’OCDE recommande cinq méthodes pour cette analyse, jugée très subjective, donnant aux multinationales une grande liberté pour se structurer afin de minimiser les coûts fiscaux qu'elles encourent. A l’issu du projet BEPS de l'OCDE/G20, le principe de pleine concurrence continue d’être le standard international pour l'évaluation des prix de transfert. Toutefois, ce principe n’est pas suffisamment pragmatique pour les administrations fiscales que l’on peut considérer comme faibles, car il comporte de nombreuses échappatoires qui peuvent compromettre la détermination de l'assiette fiscale. Pour une imposition effective des groupes multinationaux de sociétés, notre thèse suggère deux arguments principaux. D’abord, elle propose des mesures à court terme qui reposent sur la simplification des règles actuelles afin de permettre aux administrations fiscales de collecter des recettes fiscales avec les moyens dont elles disposent. Néanmoins, ces mesures sont provisoires et transitoires étant donné qu’elles reposent sur des méthodes unilatérales jugées défaillantes. Ensuite, notre thèse soutient l’idée que la taxation unitaire avec la répartition formulaire est, à long terme, la meilleure solution, car elle est plus équitable pour toutes les parties. Our thesis addresses taxation of transfer pricing and the arm’s length principle (ALP) in developing countries. Transfer pricing rules aim to accurately reflect the economic contribution of a multinational company (MNC) in each of the various jurisdictions in which it operates. The objective of the TP rules is to ensure that the various entities of an MNC report the real corresponding taxable profits in their jurisdiction.However, this objective is not always attained in practice. Favored by the OECD, the ALP approach requires an individual analysis of the facts and the situation of each taxpayer. There are five approved methods for this analysis, therefore it is eventually highly subjective, giving MNCs much freedom to structure themselves to minimize the tax costs they incur. Following the OECD/G20 BEPS Project, ALP has continued to be the international standard for assessing TP. However, the ALP is not a practical approach for developing countries, as it has many loopholes that can jeopardize the tax base. This thesis has two main arguments. First, it proposes some short-term strategies to make the ALP framework workable for developing countries’ tax administrations, although they are only a stopgate solution since they are still based on a flawed approach. Second, this chapter supports the judgment that unitary taxation with Formulary Apportionment (FA) is the best long-term solution that is fair to all parties.
Keywords: Administration fiscale; Arm’s length principle; Developing country; Droit fiscal (droit international); Droit fiscal international; Impôt (administration); Impôt (procédure); International tax law; Pays en développement; Principe de pleine concurrence; Prix de cession interne; Prix de transfert; Soft law; Tax administration; Taxation unitaire; Transfer pricing; Unitary taxation

Vers une maîtrise du risque bancaire systémique - Maurin, Alexandra (Université Paris-Dauphine, 2019)
L'essor de la RSE, tant au sein des sociétés qu'au travers des concertations internationales, illustre l'importance qu'ont pris l'éthique et la morale dans les relations d'affaires. Le banquier y tient une place centrale puisqu'il est « le moteur de toutes les activités de son temps ». Du fait de son rôle prépondérant, aussi bien pour l'économie réelle que sur les marchés financiers, il devrait agir en précurseur du développement de la RSE. Pourtant, lors de la crise de 2007, l'incitation déraisonnée au surendettement des particuliers et le recours à la titrisation pour faciliter la diffusion d'actifs toxiques ont démontré une amoralité générale des banques dans la conduite de leurs affaires. De cette crise de grande ampleur ressortent des questionnements sur l’impact de l’aléa moral sur la stabilité des États et la volonté d’apporter des réponses juridiques au risque bancaire systémique, afin de responsabiliser les banquiers et d’éviter que l’Histoire ne se répète.
Keywords: Aléa moral; Banks' liability; Banque universelle; CSR; Corporate Social Responsibility; Crise économique; Droit des affaires; Economic crisis; Moral hazard; RSE; Responsabilité du banquier; Responsabilité sociétale; Responsabilité sociétale des entreprises (RSE); Risque financier; Risque systémique; Systemic risk; Universal banks

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Essai d'une théorie juridique de la monnaie à partir de la notion de cours - Zanolli, Romain (Université Paris Cité, 2019)
Les mutations monétaires du XXIe siècle alimentent un renouvellement de la pensée monétaire. Qu'il s'agisse de la monnaie unique européenne, de l'invention de la monnaie électronique, de l'adoption d'un droit européen des monnaies (services de paiement, réserves intégrales), le législateur a façonné de nouvelles règles monétaires. Pour rationaliser ces règles disparates, cette thèse propose une théorie juridique de la monnaie construite à partir de la définition de la notion de « cours ». Pour isoler puis définir l'objet du cours, les sciences juridiques présentent l'avantage de dissocier le fait du droit. Cette logique permet de faire le départ entre le phénomène monétaire qui relève du fait (« fait social total » selon Durkheim) et sa manifestation dans la société au moyen des règles formalisées. Un classement doctrinal permet de distinguer, depuis la fin du XXe siècle, deux catégories de règles : celles de la « monnaie abstraite » qui président à la définition de l'unité de compte, et celles des « monnaies concrètes » qui organisent l'émission et la circulation monétaire. Seules ces dernières peuvent être l'objet d'un cours. Or une définition restrictive du cours (le cours légal) n'admet comme monnaies concrètes que les monnaies matérielles (billets et pièces). L'admission des monnaies immatérielles parmi les monnaies concrètes oblige à rompre avec la doctrine classique qui les assimile à des créances. Les monnaies immatérielles sont des objets du droit monétaire dont la remise (des fonds) éteint les promesses (les créances). Face à l'impérative nécessité de distinguer dettes et monnaies, on propose de créer une nouvelle catégorie nommée « monnaie civile ». Cette catégorie accueille les règles gouvernant les pratiques monétaires (les dettes et les créances) qui ne relèvent pas du fonctionnement du système monétaire (monnaies abstraite et concrètes). Le fonctionnement des monnaies concrètes, notamment entre le détenteur de monnaies et le banquier, prend la forme d'un triptyque : les fonds (1) sont stockés sur des supports monétaires (2. Billets, comptes...) et transférés d'un support à l'autre au moyen d'instruments de paiement (3. Chèques, cartes...). La différenciation entre les monnaies concrètes matérielles (espèces) et immatérielles (comptes) repose sur le lien entre les fonds et leur support monétaire : indissociable pour les premières, articulé pour les secondes. Ont cours de monnaies, les seules monnaies concrètes, à l'exclusion des monnaies abstraite et civile. Le dispositif cours légal (dès le Code pénal de 1810) traite distinctement la définition et la circulation des monnaies concrètes matérielles, ce qui dans les sciences juridiques traduit la notion et le régime. On nomme ces deux versants du cours légal respectivement « cours d'émission » et « cours de circulation ». Le premier désigne les règles juridiques qui font qu'une chose devient monnaie (du papier au billet). Quant au second, suivant la dualité du terme de cours, il définit les modalités de circulation. Il se subdivise en un « cours d'acceptation », qui définit les conditions de réception et un « cours de valeur », qui définit la valeur de réception. Ces règles du cours ont été au fondement de la définition juridique des monnaies. Cette thèse a recours au même fondement pour donner cours aux monnaies immatérielles (scripturales et électroniques). Le prisme du cours permet alors d'unifier les règles éparses qui régissent le cours d'acceptation et de valeur des monnaies immatérielles. Il en résulte une théorie renouvelée de la monnaie qui n'est plus centrée sur une compréhension restrictive du dispositif juridique du cours légal. Après avoir été « démétallisées », les monnaies dématérialisées s'offrent au XXIe siècle dotées d'un fondement juridique. Libéré du poids du cours légal des billets, le cours des monnaies immatérielles ouvre la voie à la définition des monnaies communes d'une société sans espèces.
Keywords: Banking law; Banque; Banques; Comptes; Cours légal; Currencies; Currency; Droit; Droit monétaire; Instruments de paiement; Legal tender; Monetary system; Monetary value; Money; Monnaie; Monnaie électronique; Monnaies virtuelles; Système monétaire; Systèmes de paiement; Valeur monétaire; Virtual currencies

Personal Property Security Law: International Ambitions and Local Realities - Castellano, Giuliano; Tosato, Andrea (International Business Law, 2019)
Personal property security law is a key element of “access to credit” and “financial inclusion”. The prevailing view is that a legal framework enabling the effective use of personal property as collateral markedly benefits both lenders and borrowers. Lenders can offer financing at a lower cost thanks to reduced credit risk; borrowers can access funding by leveraging the otherwise unavailable value of the assets integral to their operations. Over the past century, the priorities of personal property security law have evolved fundamentally. As small and medium-sized enterprises (SMEs) and individual entrepreneurs have become the growth engine of both developed and developing economies, legislators have grown sensitive to the financing needs of these entities. In parallel, the advent of the information society has demanded that lawmakers address squarely the rules governing the use as collateral of intangibles such as “receivables”, “intermediated securities”, “non-intermediated securities”, and “intellectual property rights”, rather than confine their gaze to tangibles such as industrial machinery, mobile equipment and inventory. Concurrently, the increasingly transnational nature of both economic development policies and commercial activity have engendered the need for global principles and standards for asset-based lending. To address these novel priorities and promote a healthy and vibrant credit ecosystem, international and regional organizations have undertaken projects aimed at modernizing and harmonizing personal property security law. Over time, these efforts have yielded a panoply of legal instruments. Binding conventions have been adopted to unify the rules of discrete facets of personal property security law, while soft-law texts, such as model laws and legislative guides, have been formulated to supply comprehensive legal templates to lawmakers keen to revise their domestic legal regimes. Nevertheless, states have struggled to assimilate these international efforts into their domestic legal systems. Common law jurisdictions have been loath to abandon the familiarity and safety of the path paved by centuries of case law; in similar vein, civil law jurisdictions have resisted inducements to renovate the normative infrastructure erected by the codifications of the 19th century. This Chapter explores the tension between international ambitions and local realities, with a special focus on the issues encountered in civil law jurisdictions. To this end, the case of Italy is examined as a living experiment in comparative personal property security law. In this jurisdiction, the recent enactment of a non-possessory security device, absent a comprehensive reform of the country’s civil code affords important lessons for any civil law system which might be pondering personal property security law reforms. More profoundly, it epitomizes the gap that separates the aspirations of international legal instruments from their effective implementation in domestic contexts. This analysis is divided into two parts. The first reviews international and regional legal initiatives that have shaped the personal property law landscape and then identifies a set of core tenets shared among them. In the second part, attention shifts to Italy, scrutinizing both the personal property security legal edifice originally constructed in this jurisdiction and the attempts to overhaul it that have taken place over the past three decades. This is followed by a critical appraisal of the current state of the law, by reference to the aforementioned core tenets of personal property law reform.
Keywords: Commercial Law; Law Reform; Non-possessory Pledge; Personal Property Security Law; Secured transactions

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
OpenAlex: https://openalex.org/W2998516176
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Harmonisation des normes comptables internationales et OHADA : une analyse critique des parties prenantes - Yepdo, Florentin Gaël; Nyasseu, Emma Joachim; Tatang Atabonfack, Pulchérie Léonie (Revue du Contrôle de la Comptabilité et de l’Audit, 2019)
Face à la mondialisation des économies et la globalisation des marchés, le désire d’avoir un langage commun s’est de plus en plus fait ressenti. Pour assoupir ce besoin plusieurs pays ont jugé opportun d’adopter les normes IFRS pour des informations de qualité et comparable à travers le monde. C’est dans cet élan que l’espace OHADA décide en 2017 d’harmoniser ses normes à celles d’IFRS. L’objectif de cet article est d’analyser la perception des acteurs sur l’harmonisation des normes OHADA et IFRS. Cette étude qualitative s’appuie sur une population de 16 individus composés d’académiciens et de praticiens de la comptabilité. Les résultats de l’étude révèlent que l’harmonisation du SYSCOHADA aux IFRS était souhaitable mais que certains points de convergences restent questionnable. De plus on ne saurait parler dans le processus d’harmonisation des normes OHADA et des normes IFRS, d’une adoption pure et simple des normes IFRS, mais plutôt d’une adaptation des normes OHADA aux normes IFRS en tenant compte des caractéristiques des pays de l’espace OHADA.
Keywords: Harmonisation; Normes comptables OHADA; Normes comptables internationales; Parties prenantes

Les entreprises françaises et la commande publique en Afrique - Perichon, Lukas (Université Paris-Saclay, 2019)
Les relations contractuelles entre les États africains francophones et les entreprises françaises dans la commande publique se nouent dans un cadre juridique et institutionnel constitué d'un enchevêtrement complexe de normes nationales, régionales et internationales en rupture progressive avec le modèle historique français. Ces relations se formalisent dans des contrats hybrides, aux caractères mal définis, entre contrats publics et contrats internationaux. Ils s'insèrent dans des montages juridiques et financiers où sont mis en balance la profitabilité, l'intérêt général, et les enjeux environnementaux et sociaux du développement. Contractual relationships between french-speaking african countries and french companies in the public procurement sector are formed under a complex network of national, regional and international rules breaking away from the historical french legal and administrative model. These relationships are maintained through ill-defined hybrid contracts that draw from public and international contractual laws and practices. They are integrated into legal and financial frameworks balancing profitability, public interests, environmental and social matters.
Keywords: Africa; Afrique; Afrique francophone; Commande publique; Contrats administratifs; Droit international; Droit public; International law; Marché public; Public law; Public procurement

The Influence of IAS/IFRS on the New OHADA General Chart of Accounts - Tchokoté, Ivan Djossa (Journal of Modern Accounting and Auditing, 2019)
Accounting standardization in black African French-speaking countries is presented through two streams of research. The first stream presents the general chart of accounts common to all these countries as an accounting model which reconciles the divergences between the Anglo-Saxon and continental approaches to accounting, and thereby satisfies the requirements of users of accounting information. The second stream considers that the convergence towards IAS/IFRS is a vital way of attracting international investors and increasing development. This article stands by the second perspective and analyzes the changes introduced in the PCG-OHADA (2017) compared to the PCG-OHADA (2000). It shows that the new provisions of the PCG-OHADA are mainly inspired by IAS 1, IAS 16, IAS 19, IAS 36, IAS 38, IAS 40, and IFRS 6.
Keywords: Accounting harmonization; Accounting standards; IFRS; PCG

Ehe und Familienschutz in Zeiten des demografischen Wandels : ein Rechtsvergleich zwischen dem deutschen und ivorischen Einkommensteuerrecht : mit Überlegungen zur Besteuerung von Ehe und Familie in Entwicklungsländern südlich der Sahara angesichts des „juristischen Erbes Frankreichs“ Vorgelegt von - Kra, Patric Kouassi (Université Paris 10 ; Universität Potsdam, 2019)
De cette étude comparée sur la Côte d’Ivoire et l’Allemagne, il est ressort des similitudes au niveau des garanties juridiques et constitutionnelle de la protection du couple et de la famille en droit fiscal à laquelle s’ajoute la situation de changement démographique. De l’évaluation de la retranscription en droit fiscal de la protection du couple et de la famille il est ressorti que la transcription allemande est élargie, mais désuète. En particulier en raison De l’inadéquation de l’imposition commune des époux avec fractionnement en raison du caractère obsolescent et injuste de la mesure. Concernant la Côte d’Ivoire, l’on constate une transcription ivoirienne ciblée sur le couple et la famille, mais lacunaire du fait de l’inadaptation de la protection pro-nataliste au moyen du quotient familial, la difficulté de recensement effectif des contribuables et le défaut de déduction d’impôts du fait de la famille élargie. Pour le perfectionnement et la modernisation de la transcription fiscale il faut pour l’Allemagne une entière déductibilité des frais de garde d’enfants en raison de l’ activité professionnelle et application du quotient familial sur le modèle français tout en conservant le montant des allocations familiales allemande. Pour la Côte d’Ivoire il est nécessaire de suspendre l’application du quotient familial pour instaurer une imposition individuelle des conjoints tout en autorisant la déductibilité des charges exceptionnelles occasionnées par la famille. From this comparative study on Côte d'Ivoire and Germany, similarities in the legal and constitutional guarantees of the protection of the marriage and the family in tax law are apparent, as well as the situation of demographic change. From the evaluation of the transcription of the protection of the couple and the family into tax law, it emerged that the German transcription is broadened, but outdated. In particular because of the inadequacy of the joint taxation of spouses with splitting due to the obsolescence and unfairness of the measure. Concerning Côte d'Ivoire, there is an Ivorian transcription targeted at the couple and the family, but incomplete because of the inadequacy of pro-natalist protection by means of the family quotient, the difficulty of effectively recording taxpayers and the lack of tax deduction due to the extended family. For the improvement and modernisation of the tax transcription, Germany needs a full deductibility of childcare costs due to professional activity and the application of the family quotient on the French model, while maintaining the amount of German family allowances. For Côte d'Ivoire, it is necessary to suspend the application of the family allowance in order to introduce individual taxation of spouses while allowing the deductibility of exceptional expenses caused by the family.
Thèse en cotutelle franco-allemande: Universität Potsdam et Université Paris Nanterre
Keywords: Allemagne; Comparative law; Countries south of the Sahara; Côte d'Ivoire; Droit comparé; Droit fiscal; Droit fiscal allemand; Droit fiscal de la famille; Droit fiscal ivoirien; Famille; Famille (droit); Family quotient; Family tax law; German couple's quotient; German tax law; Ivorian tax law; Pays au sud du Sahara; Quotient du couple allemand; Quotient familial

A comparative appraisal of debt relief measures for no income no assets (NINA) debtors in Nigeria - Osunlaja, Tobi Titilayo (University of Pretoria, 2019)
Nigeria currently has a non-functioning insolvency system; it is yet to record a successful insolvency case. This failure principally is attributable to the weak laws and enforcement policies in existence. The problem is exacerbated by burgeoning consumer debt in the formal sector. The causal factors for this increase in debt are negative economic growth indices such as rising inflation, interest rates and unemployment. With these indices predicted to worsen, a new Bankruptcy and Insolvency Act (BIA) was proposed in 2016. The BIA seeks to regulate individual insolvency proceedings in Nigeria. However, the BIA (as currently conceptualized) does not make provision for debtors with neither income nor assets, often referred to as No Income No Assets (NINA) debtors who, it can be argued, are in the majority in the Nigerian state. The aim in this thesis is to propose debt relief measures that cater for NINA debtors in Nigeria. This proposal aims to prevent further discrimination against these debtors in terms of the current law and the proposed BIA. It envisages that catering for NINA debtors in Nigeria will boost the Nigerian government’s drive to encourage entrepreneurship. In providing for NINA debtors it will provide a safe landing for poor debtors in the event of entrepreneurial failure. The thesis achieves its stated aim by studying international principles and guidelines as espoused by leading bodies. Furthermore, the thesis performs a comparative analysis of relevant NINA provisions in South Africa, Sweden, France, Ireland and Canada. The thesis proposes amendments to the proposed BIA in light of the aforementioned analysis and posits that procedures that are formal and extra-judicial, which have no financial requirements and are easily accessible to debtors should be incorporated.
https://repository.up.ac.za/handle/2263/92927
Keywords: Debt relief measures; Insolvency; Insolvency system; Laws and enforcement policies; No Income No Assets (NINA)

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

What Process is Due – Sanctions Regimes of Multilateral Development Banks - Madir, Jelena (University of Westminster, 2019)
Much has been written about the consequences for companies of criminal convictions for bribery and other corrupt practices. However, less attention has been paid to the sanctions regimes that have been developed by multilateral development banks in order to combat fraud and corruption in their operations. This is likely to change in view of the fact that on 9 April 2010, the heads of five leading multilateral development banks (MDBs) – the African Development Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the Inter-American Development Bank and the World Bank Group – signed the Agreement for Mutual Enforcement of Debarment Decisions, which provides for mutual and reciprocal enforcement of debarment decisions taken by any one of them against parties that engage in fraud, corruption, coercion or collusion in connection with MDB-financed projects. For parties that are seeking financing form an MDB or are competing for contracts funded by an MDB, this means that a sanctionable practice committed in a single country could result in global sanctions. Against this background, this thesis examines the type of due process rights that should characterise MDBs’ sanctions procedures. More particularly, the thesis analyses the extent to which MDBs’ sanctions regimes should be bound by the rules of law, analogous to those of national judicial bodies, and the level of due process and transparency that should be required from these ever-evolving regimes. In other words, (how) can the tension between the administrative and business considerations of MDBs’ sanctions regimes (coupled with their immunity from judicial review) be reconciled with due process considerations and principles of fairness that underpin a national judicial model?

Block Chain Accounting: The Face of Accounting and Auditing in Industry 4.0 - Antoney, Laly; Augusthy, Theresa Josephine (International Multilingual Journal of Science and Technology, 2019)
Keywords: Accounting Education; Block Chain Accounting; DLT; Future Audit; Tripple Entry Book Keeping

La responsabilité des ordonnateurs dans le système financier public contemporain : étude comparée des droits camerounais et français - Djeya Kamdom, Yves Gabriel (Université de Lille, 2019)
Comme la France, le Cameroun a hérité du système dit de « budget de moyens» qui met l’accent sur la régularité juridique dans la gestion des finances publiques. Des réformes engagées au cours de la décennie 2000, réorientent leurs systèmes financiers vers la recherche de performance de la dépense publique. En se fondant sur une approche globale des innovations introduites dans le droit public financier des systèmes considérés, ce travail tente de démontrer que la responsabilité des ordonnateurs, certes de nature et d’effectivité variables, ne répond plus uniquement à une logique juridique fondée sur le respect des règles de droit, mais davantage à une logique managériale guidée par la recherche de la performance sur la base d’objectifs établis et de résultats mesurables. Le projet se structure en deux phases. D’une part, la faute sanctionnable, quis’apprécie au regard des obligations qui incombent à l’ordonnateur, est tournée vers la préoccupation de la régularité juridique. D’autre part, cette préoccupation ne prend pas en compte l’exigence de performance, qui est à la base de la loi organique relative aux lois des finances. Just like France, Cameroon inherited what is known as the ''budget by means''system which places emphasis on legal regularity in the management of public finances. However, reforms initiated in the 2000s, gave a fresh orientation to their financial systems by focusing more towards the search for the performance of public expenditure. Based on a global approach to the innovations introduced in the public financial law of the systems under consideration, this work attempts to demonstrate that the responsibility of the authorizing officers, although with some variances as to its nature and effectiveness, no longer only responds to a legallogic based on the respect of the rules of law, but more to a managerial logic guided by the search for performance on the basis of established objectives and measurable results. The project is structured in two phases. On the one hand, the reprehensible fault, which is assessed in the light of the obligations incumbent on the authorizing officer, is directed towards the preoccupation with legal regularity. On the other hand, this concern does not take into account the performance requirement, which is the basis of the organic law bearing on finance laws.
Keywords: Authorizing officers; Cameroun; Comptables publics; Contentieux financier; Finances publiques; Financial litigations; France; Gestionnaires publics; Ordonnateurs; Performance publiques; Public finances; Public performance; Public smanagers; Responsability; Responsabilité; Responsabilité professionnelle

La contribution de l'audit interne dans la gouvernance d'entreprise - El Harchaoui, Es-sahli (Finance & Finance Internationale, 2019)
La gouvernance d’entreprise est une matière vivante, riche, foisonnante qui a connu au cours des dernières années des développements de grande ampleur, tant dans la littérature académique que dans les guides pratiques. L’audit interne constitue un mécanisme de grande importance dans le processus de gouvernance de l’entreprise. De ce fait, considérant le poids et l’importance du rôle de cette fonction sur l’efficacité du système de gouvernance de l’entreprise, nous nous sommes intéressés, dans le cadre de notre étude, aux enjeux et à l’importance de l’audit interne en tant qu’instrument au service de la gouvernance d’entreprise et à l’analyse de sa contribution dans la performance du présent processus. The Corporate governance is a living, rich and abundant subject, which has experienced in recent years major developments, both in academic literature and practical guides. Internal audit is an important mechanism in the process of corporate governance. Therefore, considering the weight and the importance of this function on the efficiency of corporate governance, we will consider, in our study, the issues and the importance of internal audit as a tool serving the corporate governance and analyze its contribution in the performance of this process.
Keywords: Audit committee; Audit interne; Comité d’audit; Contrôle interne; Corporate governance; Gouvernance d'entreprise; Internal audit; Internal control

Le refinancement d'entreprises en difficulté : contribution à l'optimisation juridique du concept de capital-retournement - Feydel, Romain (Université de Limoges, 2019)
Le refinancement d’entreprises en difficulté est entouré d’une grande part de mystification. Aux yeux du grand public, il s’agit avant tout d’un moyen efficace de faire fortune pour les investisseurs s’y aventurant. Cette activité, connue également sous le nom de capital-retournement, est pourtant le domaine d’exercice exclusif de hauts techniciens de la finance et du droit. Le vaste droit de l’ingénierie financière encadre le refinancement d’entreprises en difficulté. Plongeant son lecteur au coeur de la haute finance d’entreprise, cette thèse démystifie le capital-retournement tout en voulant améliorer sa pratique. Pour cela, l’aspect juridique de la levée des fonds et de leur investissement fait l’objet d’une profonde analyse. À partir de celle-ci et de l’inspiration du droit étranger, de nouveaux outils dédiés à l’optimisation du refinancement d’entreprises en difficulté sont proposés. Cette thèse démontre le rôle prépondérant du droit de l’ingénierie financière dans le sauvetage d’emplois en France.
Keywords: Banking and financial law; Droit bancaire; Droit de l'investissement; Droit financier; Droit privé; Fiscalité; Ingénierie financière; Investment Law; Taxation

Electronic Tax System As A Panacea For Tax Revenue Leakages In Nigeria - Nwamgbebu, Obinna; Oketa, Chiamake; Odom, Amarachi; Nwambe, Cynthia; Nweke–Charles, Uchenna (African Journal of Politics and Administrative Studies, 2019)
The broad objective of the study is to assess the problems of the traditional tax system in Nigeria and establish electronic taxation as a solution to these problems. The study adopted content analysis in analyzing text books, journals, newspapers and other essential materials that were used to obtain the needed information for the study. Extensive review of the literature showed that electronic tax system solves the problem of low tax collection, unavailability of tax statistics and poor record keeping, complex of payment and high cost of tax compliance. The implication of these findings is that an adoption of electronic tax system is an intelligent means of achieving a system of tax administration that allows for the collection and accountability of required taxes at a minimum cost. The study concluded that there are some challenges with the manual system of administering taxes and that modern technology could simplify these challenges and alienate them in the form e-tax. The study therefore recommended that government should support with everything on their disposal the establishment of e-tax administration so as to start ripping the benefit of high rate of compliance among taxpayers at all levels of government in Nigeria.

Les règles prudentielles et les immobilisations incorporelles dans l’UEMOA - Alemdjrodo, Richard (Les Annales de droit, 2019)
Les fonds propres (entre autres, les bénéfices non distribués et les autres réserves tels qu’ils figurent au bilan) doivent servir à renforcer les banques. Ainsi, parmi les mesures introduites par Bâle III se trouvent les normes sur le risque de liquidité qui obligent les banques à sélectionner des actifs facilement cessibles sans perte de valeur pour alimenter leur trésorerie en cas de difficulté à cause de retraits massifs de la clientèle ou de l’assèchement du marché interbancaire. En outre, ces mêmes banques ont l’obligation de pondérer leurs actifs selon la qualité du risque. L’une des conséquences de cette obligation de pondération est qu’une augmentation du risque de contrepartie ou le développement des activités de marché devront être compensés par plus de fonds propres. Il est connu que beaucoup d’institutions bancaires à travers le monde ont du mal à respecter les règles prudentielles de Bâle (même les États-Unis ont tardé à adopter Bâle III), cet article a pour but d’analyser le respect du cadre réglementaire de Bâle III par l’Union Économique et Monétaire Ouest-Africain (UEMOA) et sa banque centrale, la Banque Centrale des États de l’Afrique de l’Ouest (BCEAO). Pour y parvenir, il est analysé un exemple de composant des fonds propres, les immobilisations incorporelles, et la politique de la BCEAO (vis-à-vis des institutions de crédit de la zone UEMOA) par rapport à leur prise en compte dans les risques pondérés. Une analyse qui porte à la fois sur le droit bancaire et le droit comptable.
ISBN: 9791024012933 Number: 13
Keywords: banque; fonds propres; immobilisation; incorporel; prudentiel

Adoption, compliance, and consequences of International Financial Reporting Standards in Africa - Tawiah, Vincent K. (Griffith University, 2019)
This thesis investigates the adoption, compliance and consequences of International Financial Reporting Standards (IFRS) in Africa, a continent which has mostly been ignored in prior studies due to the use of generic proxies. Drawing on DiMaggio and Powell (1983), this thesis examines the institutional pressures of IFRS adoption in Africa. Stakeholder salience theory, developed by Mitchell, Agle and Wood (1997), is employed to analyse the determinants of IFRS compliance outside the traditional capital market settings. As regards to the consequences of IFRS in Africa, this thesis analyses the impact of IFRS on audit fees, audit reporting lags and auditor switch. The study used panel data from 54 countries and 205 firms covering the financial years 2003-2016. Secondary data was sourced from reputable database and annual reports of sample companies. Different analytical tools such as ordinary least squares, logit and multinomial regressions were used based on their suitability to address the research questions. The study found that only 18 out of the 54 countries required all listed and large companies to report per IFRS, while 25 did not permit IFRS. The results supported the theoretical prediction that coercive, mimetic, and normative isomorphism influenced IFRS adoption in Africa. Specifically, the World Bank (WB) and International Monetary Fund’s (IMF) influence on African countries in adopting IFRS was not through foreign aid and grants; instead, their recommendations made in the Report on Observance of Standard and Codes (Accounting and Auditing) initiatives. The finding(s) also demonstrated that the presence of global audit firms and the number of years of IFAC membership had a strong association with a country’s decision to adopt IFRS. Moreover, countries with strong professional accounting organisations (PAO) were more likely to adopt IFRS. On IFRS compliance, the study found that the average compliance score among the companies over the period was 70.94%, with a minimum score of 58.59% and a maximum of 83.55%. The findings reported a significant positive association between audit committee competence (ACC) and compliance, and between chartered accountants on board (AOB) and compliance. The thesis also documented that compliance has been increasing over the years. Regarding the impact of IFRS on the audit market, the findings suggested IFRS was positively and significantly associated with an increase in audit fees regardless of early or late adoption. Also, on average, ARL increased by 26% across all samples, with late adopters experiencing 28% and earlier adopters 22% during the adoption year. Contrary to the late adopters, early adopters experienced a significant increase in audit fees during the pre-IFRS period due to the set-up and implementation at the time. In addition, IFRS adoption was likely to cause companies to switch from small audit firms to the Big 4. The findings on adoption suggest that global accounting agencies such as IFAC and IASB should focus on building vibrant national level accounting institutions such as PAOs to facilitate the adoption of IFRS in Africa. The thesis, therefore, adds to the adoption literature the finding that the isomorphic pressures in Africa are different from those suggested in prior studies. The results on compliance imply that companies that appoint more professional accountants to their boards are more likely to comply with the requirement of IFRS. Therefore, it is suggested that companies should engage more chartered accountants in their governance. Also, corporate boards must strive to strengthen their audit committees by appointing more NEDs and CAs to the committee. The findings also provide valuable information for professional accounting organisations on the role of its members (professional accountants) in the effectiveness of IFRS compliance. The findings of the consequences of IFRS on the audit market alert small and medium practitioners (SMPs) in non-IFRS countries of the possible loss of clients to the Big4 due to the adoption of IFRS. To mitigate this effect, the national PAO should build the capacity of their local accountants through training and education to handle the complexities and continuous upgrading of IFRS. Such training is seen as being crucial for SMPs in OHADA countries, Ethiopia, Djibouti and other countries which are in the process of implementing IFRS.
Keywords: Adoption; Africa; Audit market; Compliance; Consequences; IFRS; Institutional pressures; International Financial Reporting Standards; Stakeholder salience

The definitions of ‘inside information’ and ‘insider’ in the Financial Markets Act 19 of 2012 - Van Der Walt, Johann Nico (Stellenbosch University, 2019)
The definitions of ‘insider’ and ‘inside information’ in the Financial Markets Act 19 of 2012 are, as is the case with their international counterparts, central to the Act’s regulation of insider trading. It has long been recognised, however, that those definitions, inherited from repealed companies and market abuse legislation, are cumbersome and counter-intuitive. This state of affairs obtains as the South African legislature has failed to undertake the most fundamental enquiry in formulating a coherent regulatory scheme aimed at prohibiting supposedly wrongful conduct: identifying a single theory of wrongfulness upon which to base its prohibitions. Instead, the definitions include elements of all possible regulatory bases for insider trading, including those having as their object the protection of proprietary rights in information and born out of the fiduciary doctrine. It is argued that the definitions, part of legislation aimed at addressing a financial market wrong, should be formulated with reference to the rights and obligations at play in those markets and the legislature’s objectives for those markets. A proposal is made in that regard.
URI: http://hdl.handle.net/10019.1/105745
Keywords: Finance; Financial Markets Act; 2012; Insider trading in securities; Markets; South Africa

Le régime fiscal des implantations internationales d'entreprises : le cas de l'Algérie - Chaouche, Nassima Yelles (Université de Cergy Pontoise; Université d'Oran, 2019)
Depuis longtemps, le critère de rattachement retenu en droit interne et en droit conventionnel pour imposer les entreprises étrangères se fondait sur un principe simple d’application, celui de la territorialité et son corollaire l’établissement stable. Mais avec le phénomène de la globalisation et la numérisation de l’économie, ces règles classiques se révèlent de plus en plus désuètes.Aujourd’hui, les entreprises recourent soit à l’économie numérique, une économie, qui jusque-là reste affranchie de toute taxation ; soit aux transferts indirects de bénéfices pour réduire artificiellement leur bénéfice imposable ou pour transférer des bénéfices vers des pays à faible fiscalité. Cette situation ne fait que stimuler le marché de l’évasion fiscale, d’autant plus que les solutions proposées afin de remédier à ces insuffisances restent pour l’instant embryonnaires vu la résistance de certains Etats et surtout des entreprises. For a long time, the standard of attachment used in domestic law and treaty law to tax foreign enterprises was based on a simple principle of application, that of « territoriality » and its corollary « the permanent establishment ». But with the phenomenon of globalization and the digitization of the economy, these classic rules are proving increasingly obsolete.Today, companies use either the digital economy, an economy that until now has been freed from taxation ; or indirect transfers of profits to artificially reduce their taxable profit or to transfer profits to low-tax countries. This situation stimulates tax evasion, especially since the solutions proposed to remedy these shortcomings remain for the moment embryonic given the resistance of some states and especially companies.
Keywords: Commerce électronique; Prix de transfert

La fiscalité face à l'impératif du développement de la République centrafricaine - Mbounou-Ngopo, Mathurin (Aix-Marseille Université, 2019)
La préoccupation majeure de tout État moderne est d’assurer son développement économique et social. Chaque État définit ses stratégies de développement en fonction de ses réalités. C’est le cas de la République centrafricaine (RCA). L’économie du pays est fragile et demeure marquée par une faible capacité à générer des revenus. En dépit d’un potentiel naturel très important, la RCA pâtit de son enclavement qui pèse sur le développement économique du pays. Or, l’un des problèmes-clés du développement économique est celui de son financement endogène. Si les capacités contributives font défaut, il est impossible d’assurer un développement harmonieux. En effet, le financement du développement d’un État reste tributaire de la performance des ressources fiscales et douanières. La politique fiscale a un rôle important à jouer dans le développement économique d’un pays. En Centrafrique, comme dans les pays en développement, la politique fiscale est la locomotive du développement. Car, l’outil essentiel de toute politique de mobilisation de ressources et de financement adéquat du développement est la fiscalité, véritable instrument de politique économique et sociale. La fiscalité est à ce titre la carte maîtresse des programmes économiques de ce pays qui, non seulement, est enclavé mais doit relever le défi de la reconstruction à la suite des troubles politiques qui l’ont secoué durant des décades. Ainsi, la question du financement endogène du développement en Centrafrique se situe dans un contexte nouveau et doit prendre en compte plusieurs paramètres, en vue d’améliorer la mobilisation des ressources financières nationales permettant d’assurer le financement du développement. The major concern of every modern State is to ensure its economic and social development. Since living conditions are not the same, each State sets its development strategies according to its realities. This is the case of the Central African Republic (CAR). The economy remains fragile and is marked by a low capacity to generate income. Despite its huge natural potential (dense water network, large forest, vast mineral resources, extensive arable land etc.), CAR suffers from its hemmed-in position which weighs on the country's economic development. Yet, one of the key problems of economic development is endogenous funding. If the contributory capacities of citizens are limited, it is impossible to ensure a harmonious development. Indeed, the funding of any State development remains dependent on the performance of tax and customs resources. Thus, fiscal policy has an important role to play in the economic development of a country. In Central Africa, as in developing countries, fiscal policy is the locomotive of development. Since the essential tool of all resource mobilisation and adequate development funding policy is taxation, which is the real instrument of economic and social policy. Taxation is as such the trump card of economic programs of this country which, not only is landlocked but must face the challenge of rebuilding following the political unrest that shook it for more than two decades. In this sense, the question of endogenous financing of Central Africa’s development lies within a new context and must take into account several factors in order to improve the mobilization of domestic financial resources to ensure development growth.
Keywords: Central African Republic; Development; Développement; Développement économique; Financement endogenous; Financement endogène; Fiscalité; Mobilisation des ressources fiscales; Mobilization of tax resources; Politique fiscale; Recettes fiscales; République Centrafricaine; Taxation

Les opérations de regroupement de l'endettement du consommateur - Sawadogo, Rélouindé Béatrice (Université Clermont Auvergne‎, 2019)
Le crédit de regroupement destiné aux ménages et aux particuliers fait aujourd’hui partie intégrante des crédits régis par le code de la consommation. Dans un contexte de multi-endettement le plus souvent inadapté à la situation financière des débiteurs, le recours au regroupement de crédits s’inscrit dans la recherche de solutions par le débiteur pour résorber son malendettement ou mieux gérer son budget. Favorisée entre autres par la baisse des taux d’intérêt, l’offre de crédit de regroupement tend à devenir un outil de conquête de parts de marché. Demeuré longtemps sans encadrement précis, le regroupement de crédits bénéficie désormais d’un cadre strict et contraignant initié par la loi n°2010-737 du 1er juillet 2010 portant réforme du crédit à la consommation. Un encadrement dont la substance porte sur la définition des régimes des opérations de regroupement et leurs conditions de formation très formalistes et de nature consumériste. Cela traduit des avancées innovantes en la matière mais cette règlementation tient insuffisamment compte des spécificités du regroupement d’où la nécessité d’évoluer vers un cadre juridique spécifique plus approprié. Il est en effet nécessaire d’intégrer dans l’encadrement du regroupement la définition de l’opération, son procédé de mise en œuvre et d’autres aspects tenant au processus de restructuration. Ce qui permettra de définir des droits et des devoirs pour les parties prenantes aux crédits regroupés et de mieux tenir compte de la fragilité du consommateur-emprunteur par des mesures de prévention d’un nouvel engrenage dans l’endettement excessif. Le mécanisme du regroupement étant néanmoins susceptible de résorber efficacement le malendettement, il pourrait être utilisé comme mesure de traitement du malendettement dans le cadre des procédures de désendettement. Cela nécessite la définition de conditions d’ouverture du droit du surendettement aux situations de malendettement et de trouver des sources de financement du réaménagement de l’endettement via le crédit de regroupement que proposerait la Commission de surendettement. A propos, se tourner vers l’un des créanciers prêteurs est préconisé, mais il faudrait envisager la mise en place d’un fonds public spécifique de soutien aux particuliers qui financerait subsidiairement ledit crédit en cas d’exercice par le banquier de sa liberté de refuser le crédit. In fine, même si les différentes mesures de traitement du malendettement et du surendettement sont utiles, il est nécessaire et primordial de trouver de meilleurs outils pour les prévenir. The Consolidation of Debts to households and individual customers is now part of the Credit Offer regulated by the French Consumption Code Law.In the framework of multiple debts unfit to the financial situation of the Debtors, the use of debts consolidation is geared towards the search of solutions by Debtors to solve bad debts or better manage their budget. Favored by the decrease of interest rates, the consolidation of debts has evolved as a tool to gain additional market shares. Long Time without any structured monitoring, the consolidation of debts is now structured in a strict and binding framework initiated by the law n°2010-737 of July 2010 amending the consumption debt Law. A framework which is grounded on defining the different types of debts consolidation and the conditions of their creation – This process being very formal and of consumerist type. This entails innovative progress in this area field, but these rules do not take into account the peculiarities of debts consolidation, thus, implying the necessity to evolve towards a more specific legal framework. It is now compulsory to integrate within the framing of Debts Consolidation, the definition of the nature of these operations, their methods of implementation and additional aspects related to the restructuring process. This will allow to define the rights and obligations of the stakeholders to debts Consolidation and take into account the fragility of the consumer-borrower through prevention measures against the threat of falling back into the traps of excessive debts. The mechanisms of debts consolidation is however a potential way to solve excessive debts, it could be used as a healing measure to treat excessive Debts in the framework of deleveraging processes. For that purpose, leveraging one of the creditors can be advocated, but one should also contemplate the setup of a Public Fund to support individual customers, and that would finance alternatively such a credit, if not accepted by the bank.In fine, even though the different treatment measures against excessive and bad debts are useful, it is highly important to find out better tools to prevent those situations.
Keywords: Bad debt; Borrower; Consommateur (protection); Consumer; Consumer protection; Contractual freedom; Credit; Crédit; Crédit de substitution; Debts consolidation; Débiteur et créancier; Emprunteur; Fonds spécifique; France; Information spécifique; Legal framework; Lender; Liable credit; Liberté contractuelle; Malendettement; Multi-debt; Multi-endettement; Prêt responsable; Prêteur; Prêts personnels; Re-negotiation; Reframing; process; Regroupement de crédits; Renégociation; Restructuration; procédé; Risk of excessive debt; Risque de surendettement; Régime juridique; Specific fund; Specific information; Substitution credit; Surendettement

La crise des subprimes : vers un meilleur encadrement des risques financiers et juridiques liés à la titrisation des créances - Akiobé Songolo, Michèle Patricia (Université Laval, 2019)
La titrisation des créances est une opération qui permet aux banques de se financer sur les marchés financiers à moindre coût et sans trop de risques. Pour réaliser l’opération, les banques cèdent les prêts qu’elles ont octroyés à une structure qui se chargera ensuite de les placer auprès des investisseurs. De plus, la titrisation permet également aux banques de gérer les risques liés aux prêts. Avec l’avènement de cette opération, les banques se soucient moins de la qualité et de la capacité financière des emprunteurs. Une fois le prêt accordé, les banques vont créer des portefeuilles de créances qui seront cédés par la suite. Une autre forme de titrisation permet de transférer uniquement le risque lié aux prêts sans toutefois sortir ces prêts du bilan de la banque: c’est la titrisation synthétique. Ces deux formes de titrisation, classique et synthétique, ont été utilisées auxÉtats-Unis et ont contribué à l’explosion de la bulle immobilière qui a entraîné une crise financière en 2008 : la crise des subprimes. La titrisation a donc occasionné le mouvement de contagion des risques qui s’en est suivi sur les marchés financiers. Les subprimes sont des prêts hypothécaires à risque accordés à un taux variable aux ménages américains à faible capacité financière. Le taux est bas les premières années, mais augmente progressivement. Titriser ce type de prêts revient à propager le risque de non-remboursement des emprunteurs à tous les différents intervenants de la chaîne. Et c’est ce qui s’est produit: les taux ont été relevés et les emprunteurs n’ont pas été capables d’assurer le paiement des différentes mensualités entraînant un blocage de tout le circuit. Les choses se sont passées de cette façon parce que, sur les marchés à cette période, l’appât du gain l’avait emporté sur le respect des règles d’encadrement des marchés, quasi inexistantes. Cette thèse propose des solutions d’encadrement du marché financieret de l’opération de titrisation en particulier. Entre la loi du marché, le droit et l’éthique, les recommandations faites dans cette dissertation se veulent complémentaires aux actions des différents régulateurs, nationaux et internationaux.
Keywords: 2008 Financial Crisis; Crise financière 2008; Finances; Marché financier; Morale des affaires; Régulation (Théorie économique); Titrisation

Finansal tabloların tutulması ve hukuksal sonuçları - Aksu Özkan, Raziye (Akdeniz Üniversitesi, 2019)
"Bu çalışmada finansal tabloların işlevleri, çeşitleri, düzenlenmesi ve tutulmasından kaynaklanan hukuksal sonuçlar incelenmiştir. Finansal tablolar, işletmenin finansal durumunun ve finansal performansının biçimlendirilmiş sunumudur. Bu tablolar aracılığıyla, şirketin finansal durumu hakkında bilgilendirme yapılmaktadır. Finansal tablolar, özellikle yabancı yatırımcının şirketlere güvenip yatırım kararı alması açısından önem arz etmektedir. Bu bağlamda, Türk Ticaret Kanunu'nun (TTK) genel gerekçesi beşinci paragrafında, uluslararası piyasaların bir parçası olmak hedefi ortaya konulmuştur. Hedefe ulaşmak için, finansal tabloların uluslararası standartlara göre düzenlenmesi gerekliliğine yer verilmiştir. Hedefe ulaşmada yeterli düzenleme yapılması konusunda Kamu Gözetimi, Muhasebe ve Denetim Standartları Kurumu görevlendirilmiştir. Kurum tarafından yapılan düzenlemeler, uluslararası muhasebe standartlarının çevirisinden ibaret olup, yeterli değildir. TTK ile muhasebe uygulaması arasında köprü kurulamamıştır. Ticaret ve vergi hukuku alanında yer alan düzenlemeler kapsamında iki ayrı uygulama yürütülmektedir. Finansal tabloların işletmenin finansal durumunu, finansal performansını ve nakit akışlarını gerçeğe uygun olarak sunması gereklidir. Kural olarak standartlara uygunluk, bilgilerin gerçeğe uygun şekilde açıklanması için yeterlidir; ancak bu uygunluk gerçek durumunu yansıtmıyorsa standartlar uygulanmayabilecektir. Finansal tablolar bilanço, döneme ait kar veya zarar ve diğer kapsamlı gelir tablosu, özkaynak değişim tablosu, nakit akış tablosu, önemli muhasebe politikalarını ve diğer açıklayıcı bilgileri içeren dipnotlardan oluşur. Bilanço, işletmenin hazırlandığı tarih itibariyle varlık, yükümlülük ve özkaynaklarını gösteren finansal tablodur. İşletmenin sahip olduğu her türlü malvarlığı unsuru veya katlandığı her sorumluluk bilançoda muhasebeleştirilemez. Bunun için standartlarda sayılan koşulları taşımaları gerekmektedir. Bilanço dışındaki diğer finansal tablolar, ya bilançonun hazırlanması açısından birer araçtır ya da bilançonun tamamlayıcısıdır. Tabloların içeriğinde yer alan bilgilerin birbiriyle ilişkisi, bunların bir bütün olarak değerlendirilmesi gerektiğini ortaya koymaktadır. Finansal tabloların tutulmasının yönetim kurulu, denetim ve genel kurul açısından hukuki sonuçları bulunmaktadır. Yönetim kurulu finansal tabloları hazırlar ve genel kurula sunar. Bununla birlikte, denetim finansal tablolar esas alınarak yapılacaktır. Buna bağlı olarak, denetçi şirket hakkında denetim raporunu oluşturacaktır. Genel kurul, denetimden geçmiş finansal tablolara dayanarak şirkete ve yönetim kuruluna ilişkin kararlar alacaktır. In this study, the legal results arising from the functions, types, regulation and retention of the financial statements are examined. Financial statements are a structured representation of the financial position and financial performance of an entity. These tables provide information on the financial position of the company. Financial statements are especially significant for foreign investors to trust companies and make investment decisions. In this context, the fifth paragraph of the general justification of the Turkish Commercial Code (TCC) aims to be a part of international markets. In order to reach the target, it is necessary to arrange the financial statements according to international standards. The Public Oversight, Accounting and Auditing Standards Authority has been appointed to ensure adequate regulation to reach the target. The regulations made by the institution consist of translation of international accounting standards and are not sufficient. No bridge could be established between the TCC and the accounting practice. Within the scope of the regulations in the field of trade and tax law, two different applications are carried out. Financial statements shall present fairly the financial position, financial performance and cash flows of an entity. As a rule, compliance with standards is sufficient for the information to be truthfully disclosed; however, if this compliance does not reflect the actual situation of the company, the standards may not apply. The financial statements comprises balance sheet, a statement of profit or loss and other comprehensive income for the period, a statement of changes in equity, a statement of cash flow, notes, comprising significant accounting policies and other explanatory information. The balance sheet is the financial statement showing the assets, liabilities and equity of the entity. Any asset that the entity owns or any liability that it endures cannot be recognized in the balance sheet. For this, they must meet the requirements listed in the standards. Other financial statements, other than the balance sheet, are either tools for the preparation of the balance sheet or complementary to the balance sheet. For this reason, the relationship between the information contained in the content of the tables suggests that they should be evaluated as a whole. The holding of the financial statements has legal consequences for the board of directors, auditing and general assembly. The Board of Directors shall prepare the financial statements and present them to the General Assembly. However, the audit will be performed on the basis of financial statements. Accordingly, the auditor will establish an audit report on the company. The General Assembly shall take decisions regarding the company and the board of directors on the basis of audited financial statements."
Keywords: Commercial law; Compliance with laws; Financial statements; Finansal tablolar; Hukuka uygunluk; Hukuksal esaslar; International Accounting Standards; Legal aspects; Standards; Standartlar; Ticaret hukuku; Turkish Accounting Standarts; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Türkiye Muhasebe Standartları; Uluslararası Muhasebe Standartları

The tax trade interface : an investigation of the influence of the Nigerian income tax incentives on taxpayer behaviour - Aniyie, Ifeanyichukwu Azuka (University of Pretoria, 2019)
The Companies Income Tax Act provides the architecture for corporate income taxation (CIT) in Nigeria. It specifies the rate, the tax base and contains the bulk of the incentives to which qualified corporate taxpayers are entitled. This thesis investigates the influence of incentives on the compliance behaviour of micro and small companies (MSCs) in Nigeria. By Nigeria’s standard, these are companies which: (1) employ between 1 to 49 persons and/or own assets (excluding land and building) valued at less than NGN 100million; or (2) are either private limited companies or one-man businesses. In the context of the Nigerian tax system, MSCs are corporate taxpayers with turnover of less than NGN 200 million. This choice of research population is a consequence of the globally acknowledged niche occupied by MSCs vis-à-vis the of the socio-economic objectives of any state. In the course of the study, the formulated research questions were resolved using a multi-stage mixed methods framework which allowed for the fusion of qualitative and quantitative epistemology as well as facilitated the introduction of pragmaticism into the research process. The thesis, inter alia, identified gaps in the administrative regime of CIT incentives in Nigeria and highlighted the fact that they have the potential to introduce uncertainty into the tax system. In addition, it revealed that the regulatory regime for the role and services of tax intermediaries within the tax system, in terms of current standards and reality, is sub-optimal. On the basis of a survey of a small sample of MSCs, it was concluded that the influence of tax intermediaries with regard to the compliance behaviour of MSCs was marginal. Reason for this was traced to the fact that the role and services of the latter vis-à-vis clients who are MSCs are actuated by variables which are within the psycho-social space of the tax intermediairies and the desires/requests of the MSC. This dismisses, in the context of Nigeria, the notion that the tax intermediary is the initator of every tax dodge. Based on the findings, the thesis, inter alia, recommended a re-orientation in the conceptualisation of tax compliance as the prevailing theoretical premise for the extant tax law and policy does not contemplate that non-economic factors and referents outside the realm of taxation are capable of influencing tax compliance behaviour. In addition, recommendations with the capacity to change the law, policy and administrative regime relating to CIT incentives as well as the role and services provided by tax intermediaries were made after an examination of the situation in Kenya and South Africa.
URI: https://repository.up.ac.za/handle/2263/72637
Keywords: Companies Income Tax Act; Corporate income taxation; Income tax; Nigeria; Tax trade; Taxpayer

Amélioration de la méthodologie de construction de la courbe des taux sans risque dans la zone UEMOA - Gbongué, Florent (Assurances et gestion des risques / Insurance and Risk Management, 2019)
Dans la zone de l’Union économique et monétaire ouest-africaine (UEMOA), la construction d’une courbe des taux sans risque est un objectif pour les décideurs publics. En effet, elle permet d’accompagner les mutations réglementaires actuelles, ainsi que le processus de développement du marché financier régional (MFR). En s’appuyant sur les conclusions de Gbongué et Planchet (2015) et Gbongué (2019), nous proposons une nouvelle méthodologie de construction de la courbe des taux sans risque, adaptée aux particularités de cette zone, dans l’optique de réduire les erreurs d’estimation de la valeur théorique des obligations souveraines. Notons qu’elle s’appuie sur les fondamentaux du modèle de Nelson et Siegel, dans le but de faciliter la prévision de cette courbe dans le futur.
Keywords: Nelson and Siegel; Nelson et Siegel; UEMOA; courbe des taux sans risque; erreurs d’estimation; estimation errors; fondamentaux; fundamentals; marché financier régional; mutations réglementaires; prediction; prévision; regional financial market; regulatory changes; risk-free interest rate curve

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations

Curbing transfer pricing manipulation in South Africa : lessons from selected jurisdictions - Mboweni, Abel Mabawuzeni (University of Pretoria, 2019)
Transfer pricing manipulation is a worldwide problem which results in a massive loss of revenue which is meant to finance government socio-economic programmes. South Africa is not immune to this problem. South Africa is losing billions of Rands in tax revenue due to this scourge. This research is an attempt to find ways and means which can be employed to combat or control the problem. In order to find the envisaged solutions, this research investigates the causes of the problem by analysing the weaknesses and the strong points of the arm’s length principle which is the basis of transfer pricing practice in South Africa and elsewhere. The research also investigates and analyses the corporate reasons for Multinational Enterprises (MNEs) to engage in transfer pricing with a view to demonstrating that transfer pricing is a neutral tax avoidance concept if it is applied for genuine business considerations. The investigation also entails analysing the legal framework of transfer pricing in South Africa which is embodied in section 31 of the Income Tax Act 58 of 1962. The research analyses the efficacy of section 31 in dealing with the sophisticated transfer pricing manipulation schemes. In addition, an extensive reference to the Organisation for Economic Co-operation and Development (OECD) Transfer Pricing Guidelines is made as South Africa relies heavily on the guidelines. A comparative analysis of selected topics is also conducted with the United States (US) and India with a view to drawing lessons from those jurisdictions. Based on the outcome of the analysis and the lessons drawn from the comparative analysis, findings are presented followed by legislative proposals or recommendations which will help to eradicate the problem. It is hoped that implementation of the recommendations taking into account the socio-economic conditions of South Africa will help to deal with the problem.
URI: https://repository.up.ac.za/handle/2263/69915
Keywords: Loss of revenue; South Africa; Tax Revenue; Transfert pricing

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

L'image fidèle dans les sociétés commerciales de la République Démocratique du Congo : Vérifications empiriques au regard du système comptable OHADA - Halimana Hangi, Bernard (Université Protestante au Congo, 2018)
Le mobile de notre recherche est d’analyser les facteurs ou pesanteurs qui ont empêché les dirigeants sociaux et les professionnels du chiffre (directeurs administratifs et financiers, chefs comptables et comptables, auditeurs et contrôleurs de gestion, experts comptables et commissaires aux comptes)à produire, voire à certifier des états financiers de synthèse qui reflètent l’image fidèle des sociétés commerciales de la RD Congo. L’étude s’est effectuée au cours de deux premières années de mise en application du Système comptable de l’OHADA (SYSCOHADA), soit 2014 pour les comptes personnels et 2015 pour les comptes consolidés et les comptes combinés. Nous avons fait un tour rétrospectif sur l’exercice social 2013 ainsi qu’un regard projectif sur l’exercice 2016, dans le cadre de vérifications empiriques à ce sujet. En grosso modo, nos analyses se sont appuyées sur les données comptables et fiscales de 4 exercices sociaux (2013 à 2016). La toile de fond de notre étude était de savoir pourquoi les états financiers n’ont pas donné l’image fidèle du patrimoine, du résultat et de la situation financière. Cette notion d’image fidèle est consacrée par les articles 2 à 11 de l’Acte uniforme portant organisation et harmonisation des comptabilités des entreprises (AUOHCE), tel que révisé par l’Acte uniforme relatif au droit comptable et à l’information financière (AUDCIF) du 26 janvier 2017 ainsi que les articles 137 à 141 de l’Acte uniforme relatif aux Sociétés commerciales et au Groupement d’intérêt économique (AUSCGIÉ) ; à condition que les états financiers soient établis et présentés conformément aux dispositions des articles 25 à 34 de l’AUDCIF susvisé. Notre analyse est partie des vérifications empiriques sur les informations financières et fiscales de 173 sociétés commerciales et des réponses de 357 dirigeants sociaux des sociétés commerciales et des professionnels du chiffre qui ont répondu à notre questionnaire d’enquête. Les résultats de cette enquête, tout comme ceux des vérifications empiriques ont été recoupés et confirmés à partir de l’entretien semi-directif avec 38 informants qui ont vécu la transition du Plan Comptable Général Congolais (PCGC) vers le SYSCOHADA. De nos analyses, il a été démontré que les états financiers et d’autres documents comptables et de gestion courante des sociétés commerciales de la RD Congo n’ont pas reflété l’image fidèle des patrimoines, des résultats et des situations financières. Pour cause, il a été révélé que les dirigeants sociaux ainsi que les professionnels du chiffre ont établi et/ou certifié des informations financières influencées par des facteurs et pesanteurs politico-contractuels, conventionnels et socio-institutionnels. Ainsi, nous avons suggéré, qu’au-delà du formalisme mettant en relation les éléments de principaux états financiers (Bilan, Compte de résultat et Tableau des flux de trésorerie), il faille instaurer des mécanismes de durcissement de la réglementation comptable par un contrôle du niveau d’application du SYSCOHADA. Ce contrôle doit partir de l’examen des postes du Bilan à celui des soldes intermédiaires de gestion du Compte de résultat pour arriver à tirer les conséquences de la vérification de la comptabilité produite par les gestionnaires (dirigeants sociaux) et/ou certifiée par les professionnels du chiffre (consultants, auditeurs et commissaires aux comptes). Tous ces acteurs devront être invités au respect du Code d’éthique et de la Clause de conscience.
Keywords: AUDCIF; AUOHCE; AUSCGIE; Plan Comptable Général; SYSCOHADA

La surveillance internationale en matière monétaire et financière - Ondongo, Sagesse Aimé (Université de Poitiers, 2018)
Il ressort de la pratique institutionnelle que la surveillance internationale en matière monétaire et financière peut être définie comme l'ensemble des procédés de suivi et de contrôle permettant de s'assurer du bon fonctionnement du système monétaire et financier international. Celle-ci se caractérise non seulement par la recherche active d'une cohérence, mais également par le fait qu'il s'agit en pratique d'un exercice relativement respectueux de la souveraineté des États.De manière générale, la surveillance telle qu'exercée à l'heure actuelle comporte des résultats très encourageants. Seulement, son influence sur les politiques nationales est surtout palpable lorsque l'évaluation est effectuée dans le cadre d'une assistance financière. Pour consolider et renforcer cet effet juridique en toute circonstance, il convient donc de pallier les insuffisances constatées. La principale piste de solution préconisée est l'adoption d'une approche plus contraignante en modifiant la nature juridique des normes internationales de référence et le régime juridique [pouvoirs et statut juridique] des acteurs compétents. Or, cela implique un transfert des compétences nationales qui n'est possible que si les États accordent leur pleine confiance au nouveau système de surveillance qui serait mis en place. C'est pourquoi, nous recommandons également la mise en place d'un véritable système de responsabilisation des acteurs compétents qui seront ainsi amenés à répondre de leurs actes.
Keywords: Compétence; Finances internationales; Institutions internationales; Souveraineté; Stabilité; Surveillance; Système monétaire et financier international; Système monétaire international; États

Recherche sur le droit du financement des entreprises sociales et solidaires - Rasolonoromalaza, Kristina (Aix-Marseille Université, 2018)
Le financement de l’économie sociale et solidaire (ESS) se trouve actuellement au centre des préoccupations des acteurs et des observateurs de celle-ci. La question de savoir comment le droit peut faciliter le financement des entreprises de l’ESS mérite donc qu’on y consacre une analyse systémique. Le cadre juridique du financement de l’ESS est posé par les normes impératives en droit des sociétés et des groupements de l’ESS. La loi n°2014-856 du 31 juillet 2014 relative à l'ESS dresse une liste limitative des formes juridiques appartenant à l’ESS : associations loi 1901, fondations, coopératives, mutuelles et sociétés commerciales sous certaines conditions. Afin de discuter les normes impératives ayant un impact sur le financement des entreprises de l’ESS, la première partie de cette thèse reconstitue l’offre éparse de statuts et leur régime juridique. En découle, dans la seconde partie, une critique ordonnée de l’accès aux ressources financières, selon qu’elles sont destinées aux organisations sans but lucratif (OSBL) ou aux sociétés, libérales ou avec une contrepartie, qu’elles soient le fruit d’un investissement ou qu’elles proviennent d’une des parties prenantes. Cette thèse aboutit à cinq séries de propositions de réformes : la redéfinition de l’ESS pour un fléchage plus affûté des ressources financières dédiées ; la révision des normes impératives entravant la performance financière des OSBL ; la stimulation de l’investissement dans l’ESS ; la sécurisation des ressources des entreprises de l’ESS au moyen de l’évaluation de l'impact social ; la pérennisation des aides d’État, eu égard à l’utilité sociale, et des compensations pour obligation de service public
Keywords: Business law; Comparative law; Competencia; Competition law; Concurrence (droit); Contract Law; Corporate law; Droit comparé; Droit de l’entreprise; Droit des biens; Droit des obligations; Droit des organismes sans but lucratif; Droit des sociétés et des groupements; Droit du financement; Droit financier; Droit fiscal; ESS; Entreprise d'économie sociale; Entreprise d'économie solidaire; Finance Law; Financement; Finances d'entreprise; Financing; Impôts; Not-For-Profit Law; Property Law; Social and Solidarity Economy; Statut juridique; Tax law; Économie sociale et solidaire

Les contradictions de la norme dans la maîtrise des risques bancaires : résultats d'une recherche-action conduite en position de praticien réflexif dans une banque régionale - Abdou, Imen (CNAM, 2018)
Les crises financières successives qu’a connues récemment le monde et qui ont failli mettre en péril l’économie mondiale et ébranler le système économique et financier international ont obligé les autorités politiques et les institutions à renforcer les législations en la matière et à multiplier les normes. Ce renforcement et cette multiplication des normes ont pour but de limiter l’apparition de crises et de risques pour le système financier. La présente thèse vise à décrire l’impact de la multiplicité des normes dans le secteur bancaire qui se traduit par des contraintes, contradictions et coût important pour la banque. Il s’agit dans ce travail de présenter les dispositifs mis en place par l’établissement bancaire pour répondre aux exigences réglementaires ainsi qu’analyser les conséquences, cohérences et enjeux des normes sur la maitrise des risques et sur l’organisation interne de l’établissement. Les résultats soulignent l’intérêt de la gestion complète et intégrée des normes dans ce secteur d’activité. En effet, les résultats de la recherche montrent que la performance d’une banque de détail dépendra directement de sa capacité à anticiper et à gérer les divers corpus de normes auxquelles elle est confrontée. La gestion de la « norme » devient actuellement un sujet majeur dans le secteur bancaire au même titre que la gestion des risques. Les deux étant intrinsèquement liés.Le fondement de ce travail repose sur une étude de cas longitudinale de quatre années construite à partir d’une recherche-action auprès d’une banque de détail. Cette approche se base sur des entretiens semi-directifs, analyse de contenu des documents internes, réunions… Nous avons mobilisé la théorie du contrôle et du risque ainsi que la théorie de la tétranormalisation afin d’analyser la gestion de la norme dans l’établissement bancaire.
Keywords: Adapted normative; Banking risks; Banques (réglementation); Contradiction normative; Gestion de la norme; Inflation normative; Ingénierie normative adaptée; Norm management; Normative contradiction; Normative inflation; Ratios réglementaires; Regulatory ratios; Risque financier; Risques bancaires; Tetranormalisation; Tétranormalisation

The Implementation of Provisions of IFRS Framework and Financial Perfomance of Banks - Anichebe, Alphonsus Sunday; Okpala, Ngozi Eugenia (International Journal of Trend in Scientific Research and Development, 2018)
The need for global financial language gave birth to International Financial Reporting Standards (IFRS). The adoption of IFRS has been argues to have changed the manner in which the financial statements are prepared, presented and reported. IFRS represents a single set of high quality, globally accepted accounting standards that can enhance comparability of financial reporting across the globe. The significant disparities between the Nigerian Statement of Accounting Standards and International Financial Reporting Standards have resulted in the Statement of Accounting Standards being regarded as outdated and incomplete as an authoritative and internationally accepted guide to the preparation of financial statements. The study however examined the extent to which Nigerian banks have implemented the provisions of IFRS frameworks. The sample comprises of fourteen quoted deposit money banks in Nigeria. Specifically, financial statement figures of 2007 – 2011 (pre-adoption period) and 2012 – 2016 (post-adoption period) were utilized. The study adopted the ex-post facto research design. Annual panel data were collected from the financial statements and accounts of 14 deposit money banks quoted on the Nigerian Stock Exchange as well from the Securities and Exchange Commission statistical bulletin from 2007 to 2016. The findings revealed that the return on shareholders’ funds has improved since implementation of International Financial Reporting Standards (IFRS) on Nigerian banks. IFRS implementation has significant effect on the profitability of quoted banks in Nigeria. The implementation of International Financial Reporting Standards (IFRS) has significantly influenced banks’ earnings and it was concluded that IFRS has positive impact on equity and earnings of banks. It was recommended that government and regulatory authorities should organize more quality training to get bankers informed.
Keywords: Banks; Financial performance; IFRS

Le droit et la régulation des prix de transfert - Jaune, Renaud (Université Paris 1, 2018)
La présente thèse de doctorat porte sur la fiscalité des prix de transfert. Dans un contexte mondial propice à la remise en cause des législations et des pratiques fiscales, elle traite de la question des instruments de régulation appropriés et du rôle du droit dans un tel édifice. En effet, nombre d'observateurs imputent les désordres majeurs de la régulation des prix de transfert à l'imprécision des règles qui la sous-tendent et à l'absence d'autorité mondiale contre la concurrence fiscale dommageable. En réponse, nous supposons que le principe de pleine concurrence ne se limite pas à la définition usuelle qui en est donnée. Nous montrons qu'il peut être considéré comme élément d'une norme universelle destinée à neutraliser les effets des particularismes fiscaux sur les échanges économiques internationaux. Une telle hypothèse fournit le critère d'évaluation des législations nationales et de a pertinence des politiques de prix de transfert des groupes. Nous analysons ensuite la législation et la jurisprudence française, et montrons qu'une transposition réelle du principe de pleine concurrence ne peut se résumer à copier l'article 9 § 1 des conventions modèles, mis suppose d'en traduire le contenu et l'esprit en instaurant les conditions d'une coopération réelle entre les acteurs. Nous exposons également la dialectique entre les lacunes de la régulation des prix de transfert et les tendances normatives à l'œuvre dans le monde entier, qui malgré leur hétérogénéité sont parfois présentées en réponse à la question des prix de transfert Nous fournissons une grille de lecture du plan BEPS et du développement des limitations légales imposées par les Etats ainsi que des obligations de conformité fiscale (compliance). Enfin, nous montrons que la reconstruction d'une régulation des prix de transfert en référence à la nonne universelle donnerait l'occasion d'instaurer un véritable partenariat entre l'Etat et les parties prenantes, ouvrant la voie vers une nouvelle manière de discuter la loi.
Issue: 2018PA01D076
Keywords: Banques (réglementation); Compliance; Documentation de prix de transfert; Droit fiscal; Evasion fiscale; Méthodes de prix de transfert; Principe de pleine concurrence; Ruling; Transfer pricing policies; Transfert de bénéfices; Évasion fiscale

Le traitement des établissements de crédit en difficulté en zone CEMAC - Piih, Dieudonné (Sorbonne Paris Cité, 2018)
Depuis 2014, le législateur CEMAC a institué un droit spécifique des défaillances bancaires. Un an plus tard, le législateur OHADA, en réformant le droit commun des procédures collectives, a reconnu le traitement particulier des difficultés bancaires. Le problème de la pertinence de ce régime spécifique nous a amenés à démontrer que la notion de difficulté est le critère principal de sa spécificité. En effet, le droit commun a une conception patrimoniale des difficultés. Elles sont essentiellement économiques ou financières. La cessation de paiements en constitue la notion incontournable. Incontournable en droit commun, elle est une notion à géométrie variable en droit spécifique. Elle n'est plus l'état où l'établissement de crédit se trouve dans l'impossibilité de faire face à son passif exigible avec son actif disponible, mais plutôt lorsqu'il ne peut plus assurer ses paiements immédiatement ou dans un délai de trente jours. Au-delà de cette adaptation de la définition de la cessation de paiements, le législateur CEMAC considère de manière inédite que le retrait d'agrément vaut cessation de paiements. Or, il existe deux procédures de retrait d'agrément, notamment le retrait d'agrément disciplinaire et prudentiel. Ainsi, la cessation de paiements peut être disciplinaire ou prudentielle selon la procédure de retrait d'agrément. Sur le plan processuel, la cessation de paiements n'est pas la condition d'ouverture des procédures collectives en droit CEMAC. En matière de redressement judiciaire, la procédure sera déclenchée par l'avis conforme de la COBAC. En ce qui concerne la liquidation des biens, le retrait d'agrément ouvre d'office la procédure. Aujourd'hui, on n'est en droit de se poser la question de savoir que reste-t-il de la cessation de paiements. En vérité, rien ne reste plus de la cessation de paiements puisque même en définissant un établissement de crédit en difficulté, le législateur CEMAC n'y fait pas référence. Il considère qu'un établissement de crédit est en difficulté lorsque la COBAC constate les dysfonctionnements majeurs de toute nature ayant un impact immédiat ou prévisible sur sa gestion et/ou sa structure financière. Il en résulte que la conception des difficultés en droit CEMAC est plus extensive qu'en droit commun. C'est pourquoi, nous proposons une réforme du droit commun pour une appréciation plus objective de la notion de difficulté, notamment par la notation ou par la classification des créances inspirée de la réglementation bancaire et une extension aux difficultés extra-économique ou financière telles que le retrait d'agrément ou la cessation d'activités. Le problème de la pertinence du régime spécifique conduit également à s'interroger sur les conditions de sa cohabitation avec le droit commun. Il en résulte de manière générale que la COBAC contrôle l'ouverture de la procédure de droit commun, soit par l'autorisation préalable, soit par l'avis conforme, soit par la désignation d'un liquidateur bancaire, une sorte de « janus biface », soit enfin par la scission du patrimoine de l'établissement de crédit en compartiment bancaire et non bancaire. Mieux, la COBAC détient un droit de veto. Aucune procédure collective ne peut être ouverte à l'égard d'un établissement de crédit sous administration provisoire ou sous restructuration. Le droit de contrôle de la COBAC se justifie par le fait qu'elle est dotée des pouvoirs et dispose des mesures plus efficaces, notamment le Fonds de garantie, pour éviter le risque systémique. Since 2014, the CEMAC legislator has instituted a specific right of bank failures. A year later, the OHADA legislator, in reforming the common law of insolvency proceedings, recognized the special treatment of banking difficulties. The problem of the relevance of this specific regime has led us to show that the notion of difficulty is the main criterion of its specificity. Indeed, common law has a patrimonial conception of difficulties. They are essentially economic or financial. The cessation of payments is the essential notion. Incontournable in common law, it is a concept with variable geometry in specific law. It is no longer the state in which the credit institution is unable to meet its due liability with its available assets, but rather when it can no longer provide its payments immediately or within thirty days. Beyond this adaptation of the definition of the cessation of payments, the CEMAC legislator considers in an unprecedented way that the withdrawal of approval constitutes cessation of payments. However, there are two procedures for withdrawal of approval, including the withdrawal of disciplinary and prudential approval. Thus, the cessation of payments can be disciplinary or prudential according to the withdrawal procedure. On a procedural level, the cessation of payments is not the condition for opening collective proceedings in CEMAC law. In judicial redress, the procedure will be triggered by the assent of COBAC. With regard to the liquidation of property, withdrawal of approval automatically opens the procedure. Today, we are not entitled to ask ourselves the question of what remains of the cessation of payments. In truth, nothing remains of the cessation of payments since even by defining a credit institution in difficulty, the legislator CEMAC does not refer to it. It considers that a credit institution is in difficulty when COBAC notices major malfunctions of any kind having an immediate or foreseeable impact on its management and / or its financial structure. As a result, the conception of difficulties in CEMAC law is more extensive than in common law. This is why we propose a reform of the common law for a more objective assessment of the notion of difficulty, notably by the rating or classification of claims inspired by banking regulations and an extension to extra-economic or financial difficulties such as withdrawal of approval or cessation of activities. The problem of the relevance of the specific regime also raises the question of the conditions of its cohabitation with common law. As a general result, COBAC controls the opening of the ordinary law procedure, either by prior authorization, by the assent, or by the appointment of a bank liquidator, a kind of ''janus biface''. '', Or finally by the division of the assets of the credit institution into banking and non-banking compartments. Better still, COBAC holds a right of veto. No collective proceedings may be opened in respect of a credit institution under provisional administration or under restructuring. COBAC's right of control is justified by the fact that it has powers and has more effective measures, notably the Guarantee Fund, to avoid systemic risk.
Keywords: Cohabitation; Collective proceeding; Communauté Economique et Monétaire de l'Afrique Centrale; Credit institutions; Difficulties; Difficulté; Etablissement de crédit; Mesures d'assainissement; Procédure collective; Reorganization measures; Traitement; Treatment; Établissements de crédit

L’évaluation comptable et financière de la capacité à entreprendre du dirigeant de PME : enjeux, modalités et proposition d'un modèle - Lopez, Jean-Claude (Université de Reims Champagne-Ardenne, 2018)
Nous proposons, à l’aide d’une approche pluridisciplinaire, de mieux rendre compte des compétences entrepreneuriales d’un dirigeant de PME, de jeter les bases d’un modèle d’évaluation de la capacité à entreprendre à partir de l’analyse des cycles d’exploitation. Ce modèle sera construit sur les bases d’une enquête exploratoire, puis testé au sein d’une PME de négoce afin d’en vérifier la pertinence et d’en améliorer l’applicabilité.Une estimation pertinente de la capacité à entreprendre pourrait rendre possible une meilleure évaluation de la valeur ajoutée des dirigeants de PME et une esquisse plus précise de la stratégie de soutien aux actions entrepreneuriales. Evaluer la capacité à entreprendre est tout autant un défi pour la communauté financière et comptable que l’est l’évaluation du capital humain. La présente propose une nouvelle approche pour mieux aborder la "vraie" valeur d’une entreprise, avec l’espoir que notre modèle sera utile aux parties prenantes de l’entrepreneuriat. We suggest, by means of a multidisciplinary approach, reporting better entrepreneurial skills of a leader of SME, to lay the foundations for a model of evaluation of the capacity to be undertaken from the analysis of the cycles of exploitation. This model will be built on the bases of an exploratory investigation, then tested within a trade SME to verify the relevance and improve the applicability.A relevant estimation of the capacity to be undertaken could make possible a better evaluation of the added value of the leaders of SME and a more precise sketch of the strategy of support for the entrepreneurial actions To estimate the capacity to be undertaken is just as much a challenge for the financial and accounting community than is it the evaluation of the human resources. The present proposes a new approach to approach better the ''real'' value of a company, with the hope than our model will be useful for the stakeholders of the entrepreneurship.
Keywords: Accounting; Aptitude pour la direction; Capital humain; Capital humain specifique; Chefs d'entreprise (évaluation); Comptabilite; Entrepreunariat; Human resources; Specific human capital

La gestion du risque de contrepartie en matière des dérivés de gré à gré : approche juridique - Brouillou, Guerric (Université Paris 1, 2018)
Au lendemain de la crise financière de 2008, les autorités se sont emparées de la question du risque de contrepartie associé aux produits dérivés de gré à gré. Les dix années qui se sont écoulées depuis permettent de dresser le bilan de l’efficacité du cadre règlementaire alors mis en place. Cette étude s’attache à cartographier les différents éléments qui composent ou alimentent le risque de contrepartie en matière de dérivés de gré à gré et analyse l’efficacité des diverses techniques déployées pour le gérer. Les outils de gestion utilisés en matière de dérivés de gré à gré afin d’atténuer le risque de contrepartie reposent sur une pluralité de mécanismes juridiques (légaux ou contractuels). Si certains sont à la libre disposition des parties, d’autres leur sont imposés par la règlementation. Tous ces instruments participent – seuls ou conjointement – à atténuer réellement le risque de contrepartie. Mais chacun d’eux ne traite néanmoins qu’un aspect particulier de ce risque et aucun ne permet de l’annihiler totalement. Certaines situations viennent même parfois perturber l’efficacité des outils de gestion du risque de contrepartie et anéantissent leurs effets bénéfiques. On comprend in fine que la gestion efficace du risque de contrepartie suppose le respect de trois étapes : l’identification des risques attachés à chaque opération en présence doit précéder l’élaboration des outils de gestion en vue de leur atténuation, laquelle suppose enfin la prévention du risque d’inefficacité des outils utilisés. Dans tous les cas, la gestion du risque de contrepartie en matière de dérivés de gré à gré s’avère non seulement imparfaite mais aussi éminemment fragile.
Issue: 2018PA01D056
Keywords: Compensation centrale; Contrats; Contrats financiers; Counterparty risk management tools; Droit des affaires; Droit privé; Dérivés; Finances; Garanties financières; Instruments financiers à terme; OTC derivatives; Risque de contrepartie; Risque systématique; Résilitation-compensation

Les marchés financiers de matières premières agricoles à la lumière du droit des contrats - Hugou, Brice (Université de Nantes, 2018)
Afin que la sécurité alimentaire soit garantie, il faut que tous puissent avoir accès à de la nourriture en quantité et en qualité suffisante. Cela suppose que le prix des denrées alimentaires soit à la fois assez élevé pour les producteurs, et suffisamment bas pour les consommateurs. Suite aux émeutes de la faim qui ont démarré en 2008 lors de l'augmentation du prix des denrées alimentaires, des inquiétudes relatives à l’influence que les marchés financiers pourraient avoir eue sur cette hausse ont été exprimées. Afin d’apporter un éclairage juridique sur cette question, ce travail vise à examiner les différentes caractéristiques de ces marchés, comment ils se sont développés et comment ils fonctionnent. Une attention toute particulière sera portée aux contrats qui servent de support aux opérations financières. En effet le législateur a réuni l’ensemble des contrats financiers sous une même qualification, qu’ils portent sur des marchandises ou sur des actifs financiers. Pourtant, les contrats financiers relatifs à des marchandises pouvant faire l’objet d’une délivrance physique, dont font partie les matières premières agricoles, présentent de véritables spécificités. Ils appartiennent à la fois à la sphère commerciale et à la sphère financière, ce qui justifie que leur soient accordés une qualification autonome et un régime distinct de celui des autres contrats financiers. Food security requires that each inviduals can obtain food in sufficient quantity and quality. This means that food prices must be neither too high for consumers nor too low for producers. After the food riots that started in 2008 following the increase of food prices, many concerns have been expressed about the impact of financial makets toward this rise. In order to shred some light on this issue from a legal point of view, this work aims to review differents aspects of the developpment and functionning of financial markets. Special attention will be given to the contracts which are used to into financial opérations Indeed, the legislator reunited all of the various financial contracts under the same legal qualification, without regards for their underlying. However, non financial commodities are different from financial commodities as they can lead to a physical delivery, and be regarded as commercial transactions or financial operations. Thus, they should get an autonomous legal status.
Keywords: Contracts; Contrats; Marché financier; Produits commerciaux

Inopérance du contrôle de gestion dans les entreprises publiques béninoises : un problème de cohérence entre le mode de contrôle et les valeurs organisationnelles - Houngbo, Mauricette Sonia (Université Toulouse 1 Capitole, 2018)
Cette thèse porte sur l’inopérance du contrôle de gestion qui est définie comme la déconnexion d’un modèle de ses pratiques réelles. Ce problème empirique nous a paru digne d’intérêt, car le mode de contrôle instauré sous la pression des bailleurs de fonds ne semble pas donner les résultats escomptés, notamment en matière d’influence des comportements. La présente étude vérifie d’abord, par une démarche scientifique de nature essentiellement qualitative que le contrôle de gestion instauré est bien inopérant. Ensuite, ce travail propose une matrice de cohérence entre le mode de contrôle et les valeurs organisationnelles. La thèse revisite ainsi les fondamentaux du mode de contrôle qui apporte un éclairage en mobilisant une typologie orientée sur l’activité – l’individu – l’organisation. La quête d’un caractère opérant conduit à interpréter l’implantation du contrôle de gestion à l’aide des théories institutionnelles. Ce cadre repose sur l’idée selon laquelle, l’institutionnalisation est le processus de reconnaissance formelle d’une manière de faire, de son incorporation dans les pratiques quotidiennes et nécessite non seulement les normes, les pratiques mais surtout les valeurs organisationnelles. Les résultats montrent une institutionnalisation inaboutie que l’horizon de temps ne peut justifier. Le processus d’institutionnalisation du mode de contrôle par les résultats se trouve ainsi bloquer à la théorisation. Ce blocage se comprend car à cette étape, les acteurs ne sont pas convaincus que le contrôle de gestion par les résultats soit la solution irrémédiable au problème posé. Un découplage s’observe ainsi entre les pratiques de ce mode de contrôle et les discours. L’inopérance se comprend encore mieux lorsque les analyses révèlent un problème de cohérence entre le mode de contrôle par les résultats et les valeurs organisationnelles des entreprises publiques béninoises. L’observation des valeurs organisationnelles des entreprises publiques béninoises reposant sur la matrice de cohérence proposée, seraient plus en adéquation avec le contrôle par le clan et la hiérarchie.
Keywords: Bénin; Contrôle de gestion; Engagement envers l'entreprise; Entreprises publiques; Inopérance

Business combinations and group of companies : perspectives from accounting, law and corporate finance - Coda, Stefano (Université Paris 1, 2018)
Dans le cadre général des regroupements d'entreprises et des groupes de sociétés, cette thèse porte sur des questions d'intérêt à la croisée de la comptabilité, du droit (notamment les dispositions légales et la réglementation comptable) et de la finance d'entreprise. En ce qui concerne la théorie comptable, le chapitre 2 étudie comment les chercheurs en économie d'entreprise ont compris les groupes d'entreprises, les comptes de groupe et le processus de leur préparation, en particulier par rapport aux juristes italiens. Ensuite, le chapitre 3 reconstruit le processus politique et législatif qui a engendré la naissance du concept de groupe de sociétés dans le corpus juridique italien.Concernant le droit et la politique comptable, une analyse comparative est effectuée au chapitre 4qui montre clairement l'évolution de la notion de contrôle et de son utilisation dans les comptes consolidés (comptes de groupe) et les regroupements d'entreprises (I) en droit européen, (II) selon les normes comptables internationales publiées par l'IASB (International Accounting Standards Board) et (III) par rapport aux principes comptables généralement admis aux États-Unis («USGAAP»). De plus, les chapitres 5 et 6 étudient les effets du lobbying sur les normes comptables concernant les états financiers consolidés et les regroupements d'entreprises publiés par l'IASB. Fait intéressant, les résultats concordent avec une forme de capture du normalisateur comptable international par une catégorie d'institutions financières. En effet, confrontées à un modèle de consolidation prétendument basé sur le contrôle, ces dernières ont plaidé en faveur d'une exception de consolidation fondée sur un modèle de propriété et documentée comme ayant été proposée par les sociétés d'audit américaines dans ce contexte au moins depuis 1995. Ce modèle s’avère avoir trouvé un terrain fertile au sein de l'IASB. En conséquence, d'autres catégories d'institutions financières,telles que les fonds d'investissement à long terme et ceux gérés par une famille tout en préférant un modèle de consolidation différent, ne sont plus autorisées à présenter des états financiers consolidés. En ce qui concerne la finance d’entreprise, le chapitre 7 analyse les implications de différentes décisions de financement dans un nouveau échantillon de fusions et acquisitions entre institutions financières (banques et assurances) consommées dans le monde entier au cours des deux dernières décennies. En particulier, il étudie (I) la relation entre la méthode de choix de paiement (si le prix est payé en cash, en actions ou une combinaison des deux) et le choix du mode de financement d'un regroupement d'entreprises (y compris les instruments hybrides) et (II) la réaction des investisseurs à l'annonce de la combinaison. En ce qui concerne ce dernier point, l'utilisation de deux tests non paramétriques permet de détecter une relation intéressante entre la réaction du marché à l'annonce et les différents modes attendus de financement de la transaction.
Keywords: Accountings standard setting; Comptabilité; Consolidation exemption; Egroupements d'entreprises; Finance d'entreprise; Finances; Financial institutions; Gestion d'entreprise; Groupes de sociétés; IASB; IFRS 10; IFRS 3; Mergers and acquisitions; Method of payment; Politics; Politique comptable; Sources of fundings; Économie d'entreprise

De la contrainte économique : Essai d'une théorie générale de la contrainte économique en droit économique - Zafar, Arooj (Université de Montpellier, 2018)
La contrainte économique fait l’objet en Droit d’une forte contradiction. Elle est très présente dans les relations contractuelles et à l’aune des relations contractuelles. Toutefois, la notion de contrainte économique n’a jamais été définie et il n’existe pas de régime propre à cette notion. De même, elle est traitée indirectement par de nombreux régimes mais ces régimes sont en pratique peu sollicités et lorsqu’ils sont appliqués, ils sont très décevants. Aussi, la contrainte économique est une problématique récurrente en Droit mais elle reste encore aujourd’hui une énigme pour la communauté juridique. Malgré l’inflation législative, son traitement reste un échec. La présente étude a pour objectif de comprendre et d’exposer les raisons de cet échec afin d’y apporter les aménagements nécessaires pour un traitement cohérent et efficace des situations de contrainte économique. L’analyse transversale des différents régimes connaissant indirectement de ces situations met en exergue les particularités et les incohérences du traitement et notamment l’impact négatif du particularisme des droits spéciaux sur le traitement de la contrainte économique. Les enseignements tirés de cette analyse dictent la nécessité d'un régime commun à la notion de contrainte économique et imposent de plaider pour une généralisation du traitement de ces situations. Economic duress is subject to strong contradictions in Law. The concept is prevalent in contractual relations and in pre-contractual relations. However, the concept of economic duress has never been defined and there is no specific regime for this term. Similarly, the concept is addressed indirectly by many regimes, but these regimes are in practice rarely used and when applied, they can be quite disappointing. As a result, economic duress is a recurring issue in law and remains to this day, a puzzler for the legal community. Despite the legislative inflation, the methods to address economic duress remains a failure. The aim of this study is to understand and explain the reasons for this failure in order to make the necessary adjustments for a consistent and effective tackling of economic duress cases. The cross-cutting analysis of the various regimes indirectly affected by these cases, highlights the peculiarities and the lack of consistency of the current approach and in particular the negative impact of the distinctive identity of special rights with regards to addressing economic duress.The lessons learned from this analysis indicate a need for a shared framework for economic duress and call for a broadening of the response to these cases.
Keywords: ABUS DE FAIBLESSE; Abus de dépendance économique; Abus de position dominante; Abuse of dominant position; Abuse of economic dependence; Competencia; Concurrence; Contrainte économique; Dominant position abuse; Economic dependence abuse; Economic duress; Sanctions économiques; Violence économique

Effect of IFRS on Value Relevance of Accounting Information: Evidence from Quoted Manufacturing Firms in Nigeria - Ezejiofor, Raymond Asika (International Journal of Trend in Scientific Research and Development, 2018)
This study evaluated the extent to which value relevance of financial information in Nigerian manufacturing firms has improved after the implementation of International Financial Reporting Standards (IFRS). Specifically, the study intended to: Ascertain the extent the adoption of IFRS has significantly improved the book value per share of manufacturing companies in Nigeria; Determine the extent the adoption of IFRS has significantly improved the Earnings Per Share of manufacturing companies in Nigeria and Examine the extent the adoption of IFRS has significantly improved the cash flow of manufacturing companies in Nigeria. Ex-post facto research design was adopted for the study. A sample of 54 manufacturing companies was randomly selected from manufacturing companies quoted on the Nigerian Stock Exchange for the periods of 2008-2015. Data for the study were obtained from the annual reports and accounts of the sampled companies. Specifically, a modified price model for detecting value relevance of accounting data for two different periods was employed. Regression Analysis and Chow test statistical tools were used to analyze and validate the data with aid of SPSS version 20.0. The study found that the adoption of IFRS has improved the book value per share, market share price, Earnings Per Share and cash flow of manufacturing companies in Nigeria. The implication of findings is that the value relevance of accounting information of manufacturing companies is more sensitive during Post-IFRS era than the Pre-IFRS era. The findings also imply that the book value per share, market price, earnings and cash flow have become informative to equity investors in determining the value of firms following IFRS adoption. The study recommends among other things that the accounting information for book value per share should be communicated to the investing public; and such information should be of high quality to avoid negative consequences on the part of investors.
Keywords: Accounting information; Manufacturing company; Value relevance

Marchés financiers de l'Afrique centrale : changements structurels et performances - Babagnack, Paul (Université Paul-Valery Montpellier 3, 2018)
La sous-région Afrique centrale, dans la perspective de poursuivre la construction de son espace économique et monétaire commun (CEMAC) conforté, a décidé de mettre en place une bourse des valeurs mobilières de l’Afrique centrale (BVMAC) pour le développement de son système financier commun à compétence sous régionale.Parallèlement, l’un des pays membres de la CEMAC, le Cameroun en l’occurrence dispose d’une bourse des valeurs mobilières, la Douala Stock Exchange (DSX), ayant les mêmes objectifs, mais à compétence nationale. Il se pose dès lors, des problèmes de concurrence, de compétitivité et d’efficacité. Bref un problème de performance des deux places boursières fragilisant ainsi le financement de son économie par le marché financier au détriment des potentiels bénéficiaires majeurs que sont les entreprises.Comment restructurer et réorganiser les marchés financiers de l’Afrique centrale (CEMAC) afin d’améliorer leurs performances dans le financement de son économie? Cette interrogation pose alors la problématique de la reconstruction des marchés financiers de la CEMAC. Pour répondre à cette question principale, il y a lieu de prendre en compte deux déterminants constitutifs de la CEMAC: L’Union Economique de l’Afrique centrale (UEAC)Et L’Union Monétaire de l’Afrique centrale (UMAC).Afin de s’appuyer sur quatre théories à savoir : La théorie de la zone monétaire optimale ; La Théorie de la centralité ; La théorie de la mutualisation ; La théorie du changement structurel (organisationnel).Mais aussi de manière empirique, pour savoir comment s’organise selon les modèles actuels, c’est-à-dire les standards internationaux, les différents marchés financiers à travers le monde.Pour démontrer la contrainte d’une consolidation de ces deux marchés financiers dans un même espace communautaire sur la base du modèle CODERE conforté selon le modèle organisationnel de Kurt Lewin (1940), et analyser leur performance actuelle. Le chemin emprunté de l’intégration financière de ces marchés financiers conduit vers une spécialisation bipolaire ou multipolaire de cet acteur privilégié de développement qu’est le marché financier
Keywords: Afrique centrale; Ajustement structurel; Bipolarisation; Centrality; Centralité; Changement structurel; Consolidation; Intégration économique; Marché financier; Mutualisation; Performance; Sharing; Structural change

Le SYSCOHADA : Un véritable outil d’harmonisation comptable - Tahar, Makhloufi; Hamza, Taibi (حوليات جامعة بشار في العلوم الاقتصادية, 2018)
L’objectif de cette étude est de déterminer les caractéristiques de la cohérence africaine dans l’environnement des affaires (OHADA ) appliquées aux 17 pays de l’Afrique noire francophone qui vise l’unification des efforts et de visions permettant l’amélioration de transparence ( transparence des affaires, transparence financière, transparence du marché,…) notamment la production d’une information de haute qualité à travers d'un référentiel comptable unique (inspiré fortement du plan comptable général Français) et d’apprécier si ce système est inspiré des normes comptables internationales IAS/IFRS. Après l’achèvement de cette recherche, nous avons atteint un ensemble de résultats. Parmi ces résultats, le système OHADA est un cadre philosophico-légal et institutionnel qui encourage les pays membres à une convergence et une harmonisation comptable. Toutes les circonstances sont prêtes et incitent les pays membres d’aller ou d’adopter l’intégration économique dans l’espace Africain dont l’intégration comptable fait partie. Aucun pays de l’espace OHADA ne peut bénéficier des avantages que donne le système comptable de cet espace sans qu’il y ait une volonté politique pouvant assurer de l’intégration pour confronter les mutations et les défis mondiaux.

Le dirigeant de PME face à l’information comptable : une étude empirique au Sénégal - Tanor Dieng, O. (La Revue Gestion et Organisation, 2018)
Résumé Cet article examine l’influence du profil du dirigeant de PME sur l’utilisation de l’information comptable dans le contexte Sénégalais. Les résultats obtenus à partir d’une enquête sur 59 PME mettent en évidence les types d’informations comptables exploitées par cette catégorie d’entreprise. Il s’agit, entre autres, de l’information sur les coûts, les comptes annuels et le budget. Les données empiriques exploitées confirment que le degré d’utilisation de certaines informations comptables est influencé par le profil du dirigeant de PME.
Keywords: Comptabilité; Degré d’utilisation; Informations comptable; Profil du dirigeant

Facteurs déterminants la comptabilisation des actifs immatériels par les dirigeants des entreprises de l'espace OHADA : cas du Togo - Koumagnanou, Komivi (Transitions numériques et informations comptables, 2018)
The OHADA accounting framework is not immune from the choice of accounting policies for intangible assets. The need to make an accounting choice for intangible assets depends on a number of factors. This article aims to identify the motivations of managers in the choice of accounting for intangible assets. In a second step, we described the methodological approach of our work. Thus, we proceeded to the empirical study which is both qualitative and quantitative. The collected data was then analyzed. From the companies' case, it was found that the tax reasons, the accounting principles, the logic of obtaining the loans, the follow-up of the practice of the competitors, the implementation of the recommendations of audit, the sense of limiting the wage demands are pushing executives to make accounting choices for intangible assets.
Keywords: Accounting choice; Actif immatériel; Choix de comptabilisation; Intangible assets; OHADA

Delimitação constitucional do conceito de renda - Fonseca, Fernando Daniel de Moura (Universidade de São Paulo, 2018)
O conceito jurídico de renda para fins de tributação suscita debates no Brasil há décadas, o que se pode verificar por meio dos diversos trabalhos doutrinários exclusivamente dedicados ao assunto, bem como por vários acórdãos proferidos pelo Supremo Tribunal Federal (STF). Essa constatação parece afastar qualquer possibilidade de que essa temática seja abordada de forma inédita, com a capacidade de contribuir originalmente à ciência do direito. No entanto, o atual momento reclama uma nova análise acerca da definição de renda tributável. Em primeiro lugar, porque a edição da Lei n° 11.638/07 determinou que a contabilidade brasileira se alinhe ao padrão contábil aceito internacionalmente, representando pelas International Financial Reporting Standards - IFRS. Sendo assim, se o resultado contábil representa o ponto de partida para a apuração do lucro tributável das pessoas jurídicas, qualquer alteração sobre o lucro líquido tem o potencial de causar efeitos tributários, a menos que o legislador se encarregue de neutralizá-los ou discipliná-los. A singeleza dessa constatação esconde o fato de que as recentes (e contínuas) alterações contábeis não representam apenas uma mudança de entendimento acerca do registro de determinadas operações, mas verdadeira alteração no paradigma adotado pelas regras contábeis. O padrão IFRS trabalha essencialmente com expectativas, por meio de uma intensa relação entre eventos passados e o valor presente dos prováveis efeitos futuros. Para tanto, há uma forte preocupação com a substância econômica, que deve prevalecer sobre a forma jurídica sempre que se verificar a presença de um conflito. De acordo com o padrão contábil internacional, accounting follows economics, o que significa dizer que o registro contábil passa a ter como referência a visão da contabilidade sobre a realidade econômica. Como consequência, a contabilidade passa a se distanciar do direito, seja porque os negócios jurídicos já ocorridos serão escriturados de acordo com premissas essencialmente contábeis, seja porque não mais se reporta a situação patrimonial relativa a um momento pretérito, mas à melhor estimativa atual sobre o que se espera que irá ocorrer no futuro. Veja-se que enquanto o imposto de renda tem como fato gerador uma renda adquirida no passado, a contabilidade passa a considerar os efeitos de uma capacidade de auferir renda no futuro, ainda que ela não tenha se realizado, sendo suficiente a expectativa de que isso venha a acontecer. Esse pressuposto conflita diretamente com a realização, que passa a não mais ser necessária para o reconhecimento de mutações patrimoniais contábeis, situação idêntica a que acontece com a economia. Por essa razão, é necessário que a histórica relação entre o resultado contábil e a base de cálculo do imposto de renda seja (re)avaliada, de modo a se estabelecer um critério seguro a respeito da possibilidade (e de quais seriam os limites) de as novas regras contábeis afetarem a base de cálculo do imposto de renda das pessoas jurídicas. Esse propósito somente pode ser atingido se todos os atributos do conceito jurídico de renda tiverem sido previamente definidos, única forma de analisar, com rigor científico, se determinadas características da tributação da renda, tradicionalmente presentes na legislação tributária, podem ser relativizadas. Em outras palavras, é necessário que se identifique quais são os atributos indissociavelmente ligados ao conceito jurídico de renda. O momento não poderia ser considerado mais oportuno, pois a existência de um processo internacional de convergência ao padrão contábil internacional faz com que a doutrina estrangeira também discuta esse assunto, o que pode enriquecer o debate nacional. The legal definition of income taken into account for tax purposes has been a very controversial matter in Brazil for over decades. The innumerous works exclusively dedicated to the subject produced by tax scholars, as well as the several decisions handed down by the Brazilian Supreme Court (STF) endorse the debate regarding the legal concept of taxable income. This fact could seem to rule out any possibility of addressing the subject in an unprecedented way, that is, with the ability of being an original contribution to the science of law. However, the current moment calls for a new analysis over the definition of taxable income. Initially because the enactment of the Brazilian Law n. 11.638/11 determined that Brazilian accounting should be in line with the internationally accepted accounting standards, stated by the International Financial Reporting Standards - IRFS. Therefore, if the accounting result is the starting point for obtaining the taxable income of legal entities, any accounting changes over the net income has the potential of causing tax effects, unless the legislator frames norms to neutralize these effects. It is important to mention that the simplicity of this remark hides the fact that the recent (and continuous) accounting changes represents not only a modification of the understanding regarding the accounting records of certain transactions, but a true change of the paradigm adopted by the accounting rules. In essence, the IFRS has an 'expectation approach' in the setting of standards, through an analysis of the relationship between past events and the present value of probable future events. As a result, the IFRS has a solid concern with the economic substance, which, under the framework, shall prevail over the legal form whenever there is a conflict between them. According to the international accounting standards, accounting follows economics, that is, the accounting record should reflect the economic reality. As a consequence, the accounting results will differ from the tax law concepts, either because legal transactions that have already occurred in the past will be recorded in accordance with essentially accounting premises, or because the accounting results will no longer report wealth with reference to a moment in the past, yet with reference to the current best estimate of what it is expected to occur in the future. It is worth highlighting that the taxable event for income tax purposes is the income earned in the past, while the accounting result takes into account the effects of a future income-earning capacity, even though the income has not yet been realized. Therefore, for the accounting assessment it is sufficient that the mere expectation of earning the income will occur. This last assumption conflicts directly with the realization principle, due to the fact that under accounting premises, realization is no longer necessary for the recognition of changes in wealth, likewise the measurement is made in the field of economics. For this reason, it is necessary to (re)evaluate the historical relationship between the accounting result and the taxable base of the income tax, as to establish a reliable criteria regarding the possibility (and the eventual limits) of having the new accounting rules as a basis for the assessment of the taxable income base of corporations. This purpose can only be achieved if the law has previously defined all the attributes of the legal concept of income, the only way to analyze, with scientific rigor, if certain characteristics of income taxation, traditionally present in the tax legislation, can be relativized. In other words, it is necessary to identify the attributes inextricably linked to the legal concept of income. The moment could not be considered more convenient, considering that the existence of a global process of convergence to the international accounting standards raises debates about the subject in the foreign academic literature, which can enhance the national debate as well.
Keywords: Accounting; Concept of taxable income; Contabilidade; Fiscal Neutrality; Imposto de renda; Renda (Teoria econômica); Tax Impacts; Tributação

A crise de 2008 sob o prisma da análise econômico-comportamental do direito - Okumura, Andre Luis (Universidade de São Paulo, 2018)
Quase 10 anos após a eclosão da Crise de 2008, seguimos insistindo em velhas soluções para problemas econômicos recorrentes, e os remédios regulatórios que têm emergido em resposta à crise continuam fundamentalmente baseados no tradicional paradigma econômico neoclássico que pressupõe que o ser humano é um agente econômico infalivelmente racional, conforme o modelo do Homo economicus, desconsiderando-se as evidências empíricas em sentido contrário que nos trazem as ciências cognitivas em geral, e a economia comportamental em particular. Pois, lançando mão dessas descobertas, nossa tese é a de que a análise econômico-comportamental do direito deve ser usada como instrumento para prescrever políticas públicas capazes de aprimorar a regulamentação do mercado financeiro. Para tanto, dividimos nosso trabalho em três grandes capítulos. No primeiro capítulo, tecemos uma narrativa da Crise de 2008, com ênfase nas circunstâncias em que foi engendrada, e discorremos sobre como a economia neoclássica explica suas causas. No segundo capítulo, explicamos a economia comportamental e a análise econômico-comportamental do direito, contrapondo-as à economia neoclássica e à análise econômica do direito. No terceiro capítulo, defendemos que a explicação neoclássica da crise é incorreta, e tecemos uma narrativa alternativa da Crise de 2008 com base na economia comportamental. Finalmente, criticamos as principais respostas regulatórias que têm sido dadas à Crise de 2008, demonstrando que continuam se baseando quase que exclusivamente na economia neoclássica, e fazemos propostas alternativas de regulamentação inspiradas na análise econômico-comportamental do direito, a fim de provar nossa tese de que esta disciplina realmente deve ser usada para prescrever políticas públicas a fim de aprimorar a regulamentação do mercado financeiro.
Keywords: 2008 Financial Crisis; Behavioral analysis of law; Behavioral economics; Behavioral law and economics; Crise econômica; Crise économique; Droit économique; Economia; Financial markets; Marché financier; Mercado financeiro

Application of the OHADA Accounting System by Companies in DRC, Current Status and Prospects: Case of the City of Bukavu - Kulondwa, Safari; Nshobole Bahirwe, Nathalie (Journal of Accounting, Finance and Auditing Studies, 2018)
The objective of this research was to determine the current status of the application of the OHADA accounting system in DRC, five years after its adoption. A survey was conducted on thirty small and medium-sized enterprises in Bukavu to determine the level of compliance with the SYSCOHADA principles, the degree of harmonization of accounting practices and the difficulties related to the application of this system. The results shown consistently that compliance with Syscohada principles is not absolute, the level of Harmonization is still low and finally companies in DRC still need time to fit into the OHADA accounting system.
Keywords: Accounting Practices; Accounting Principles; Harmonization

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

L’évasion fiscale des multinationales dans les pays de l’UEMOA - Adetonah, Ghislain Serge Odon (Aix-Marseille Université, 2018)
Les pays de l’UEMOA, longtemps hostiles aux investissements directs étrangers, sous l’effet conjugué de la globalisation de l’économie et de la pression des institutions de Brettons Woods, ont d’une part, favorisé un accès intérieur aux flux financiers internationaux et d’autre part, offert des incitants fiscaux aux multinationales. Grâce à la libéralisation financière et l’idéologie économique dominante, les multinationales, par différents subterfuges et profitant aussi des handicaps institutionnels et organisationnels des administrations fiscales respectives des pays membres de l’espace UEMOA, échappent à leurs responsabilités fiscales envers ces États. Pour résorber les effets néfastes de l’évasion fiscale des multinationales, les pays de l’espace communautaire UEMOA, doivent mettre un accent particulier sur la modernisation de leurs administrations fiscales d’une part, et d’autre part, insérer dans toutes leurs conventions fiscales, des clauses anti-abus. Enfin, ces États doivent renforcer la lutte contre l’évasion fiscale par une action concertée basée sur une coopération fiscale dans le cadre d’une assistance administrative. The WAEMU countries, long hostile to foreign direct investment, under the combined effect of the globalization of the economy and the pressure of the institutions of Brettons Woods, have in the one hand, favored an internal access to International financial flows and on the other hand, offered tax incentives to multinationals. Thanks to financial liberalization and the prevailing economic ideology, the multinationals, by various subterfuges and taking advantage also of the institutional and organizational handicaps of the respective tax administrations of the member countries of the UEMOA space, escape their fiscal responsibilities towards these states. In order to reduce the harmful effects of tax evasion by multinationals, WAEMU countries must place particular emphasis on the modernization of their tax administrations on the one hand, and on the other hand, to include in all their agreements tax rules, anti-abuse clauses. Finally, these states must strengthen the fight against tax evasion by concerted action based on tax cooperation in the context of administrative assistance
Keywords: Afrique occidentale; Attractivité fiscale; Clause anti abus; Convention fiscale; Entreprises multinationales; Indirect transfert of benefits; Multinational company; Multinationale; Politique économique; Tax convention; Tax evasion; Transfert indirect de benefices; Union économique et monétaire Ouest africaine; Évasion fiscale; Évasion fiscale (Lutte contre)

Le contrôle international des agences de notation financières - Bergier, Charles (Université Côte d'Azur, 2018)
Alors qu'il ressort de la volonté de contrôler les agences de notation financière des initiatives nationales et régionales concrètes, elles ne restent toutefois pas harmonisées. Cette situation n'est cependant pas rédhibitoire. A titre d'exemple, alors que l'UE et les États-Unis disposent tous deux d'un système d'enregistrement distinct des agences afin qu'elles puissent exercer sur leur territoire, il apparaît logique de penser, et donc à terme d'envisager, qu'un enregistrement ou une agrégation universelle constituerait un premier pas fort vers l'harmonisation des réglementations. Il est dans ce cadre possible d'affirmer que l'harmonisation des réglementations américaine et européenne pourrait constituer un premier pas vers un cadre supra-étatique de réglementation des agences de notation financière. Il resterait dès lors à définir si ce sont les standards européens qui s'appliqueraient, ou ceux de la réglementation américaine potentiellement moins ambitieuse. Et encore, cette piste de réflexion serait parfaitement juste si il ne fallait pas également prendre en compte la montée des économies des pays émergents qui souhaitent changer la donne. Il serait donc nécessaire de s'accorder avant tout sur un système convenant à tout un chacun, hypothèse fort difficile mais qui mérite des questionnements. En outre, pour contrôler les agences de notation financière de manière efficace et contraignante (ce que n'est malheureusement pas le Code de bonne conduite de l'OICV), il ne faut pas non plus négliger la possibilité de voir émerger un droit international économique issu de standards financiers. Ce processus ne serait ainsi pas seulement bénéfique dans le cadre de la création d'un contrôle international des agences de notation, il le serait également dans le développement d'un droit international financier contraignant. Dans le cadre des agences de notation, le développement des standards financiers s'est fait en réponse aux besoins des autorités de régulation nationales à la recherche d'un équilibre entre le maintien de la compétitivité de leur place financière et la nécessité d'une stabilité du système financier. Ces standards permettent aux institutions de coopération de se positionner comme des autorités internationales de standardisation pour les secteurs concernés. Ils constituent indubitablement la piste de réflexion la plus sérieuse pour un contrôle international efficace des agences de notation financière.
Keywords: Agences de notation financière; Autorité de régulation financière; Autorité de surveillance financière; Banques (réglementation); Contrôle international; Contrôle prudentiel; Droit international économique; Notation financière; Études comparatives

The Impact of Private Securities Lawsuits on Accounting Conservatism and the Moderating Influence of Corporate Governance - Kerr, Ryan (Victoria University of Wellington, 2018)
This study investigates the impact of conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit, on the level of accounting conservatism in financial reporting. This study also investigates the moderating influence of corporate governance on the level of accounting conservatism following conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit. The study uses a sample of 617 privately enforced disclosure-related securities lawsuits against listed US firms, taken under SEC rule 10b-5 of the 1934 Securities Exchange Act, over the period 2002 to 2010. The results of the study indicate that following both the conduct that gives rise to a securities lawsuit, and the filing of a securities lawsuit, firms adopt higher levels of accounting conservatism. However, the study finds no evidence that corporate governance moderates the impact of securities lawsuits on the level of accounting conservatism.
Keywords: Accounting Conservatism; Governance; Securities Lawsuits

An evaluation of market responses to corporate disclosures in a continuous disclosure environment - Li, Hanqiao (Victoria University of Wellington, 2018)
Corporate disclosure has attracted the attention of researchers from the accounting and capital markets. Researchers have been trying to better understand how capital markets respond to corporate disclosures. This study explores the short- and the long- term market effects of corporate disclosures in a continuous disclosure environment. This study aims to find the answers to the following research questions. (1) How market (price/volume) sensitive is the information contained in each disclosure category in a continuous disclosure environment? (2) How quickly is the value-relevant information incorporated into share prices before the annual earnings announcement is released, and how can company announcements promote this timeliness of price discovery? Specifically, this study examines the extent to which the Australian share market reacts to new public information immediately after the information is released, and the impacts of announcement frequency as to different continuous disclosure categories on the timeliness of price discovery (also known as the speed of price discovery). Prior research has mostly concentrated on a single type of information event to examine the information’s market consequences by monthly, weekly or daily data. Instead, by covering all public announcements and using tick (transaction) data to calculate intraday abnormal returns and abnormal trading volumes, this study examines which type of announcement has the largest immediate market responses, and compares the magnitude (with positive/negative signs) of market reactions to different announcement categories on the Australian Securities Exchange (ASX). This study is more attractive under the Australian Continuous Disclosure Regime (CDR) because of the classification system regarding the market-sensitive announcements. Whether or not an announcement is market-sensitive is predetermined by ASX ‘specialist staff’ before the announcement is released on the market. This study investigates how the market interprets the announcement, examining market sensitivity from both the share price and trading volume movements after the announcement is available to the market. In other words, to some extent, the ‘market sensitivity tag’ shows the announcement that the market should react to, and this study reveals the announcement that the market does react to. Focusing on market-sensitive announcements, except for the ASX Query, the significant results show a positive association between announcement categories and intraday Cumulative Abnormal Returns (CARs). Share prices react the most to Progress Reports and to Asset Acquisition & Disposal, and the least to Periodic Reports and Issued Capital. Share price reactions to Distribution Announcements and Other are in the middle. There are at least two possible reasons for the different market reaction magnitudes. One is the information materiality nature: if one type of information is more important to investors than other information, this may cause higher abnormal returns on the market. The other is the information predictability: if there has been a lot of relevant information available in previous days or months, share prices could adjust to the information more smoothly. In terms of the trading volume reactions, intraday Abnormal Trading Volumes (ATVs) are observed after the release of Progress Reports, Asset Acquisition & Disposal, Issued Capital and Periodic Reports. After separating good and bad news subsamples, the results show that Progress Reports and Asset Acquisition & Disposal tend to indicate good signs to the market and cause larger trading volumes. Periodic Reports and Issued Capital could contain either good or bad news, but the trading volumes are driven by bad news. The results also reveal that company size is an important factor. Large companies tend to have relatively small market responses after information is released, which confirms that the larger companies are more stable. This study also evaluates long-term market effects of corporate disclosures by examining the timeliness of price discovery (also known as the speed of price discovery). It is the timeliness with which the full value relevant information is priced over a year before the annual earnings announcement is released. Previous literature has revealed that earnings announcements convey information, because significant stock returns or increased trading volumes are observed around the time that earnings announcements are released. However, it has also been suggested that there are other more timely information sources available that contain essentially similar or even the same value-relevant information. By the time preliminary final reports become available to the market, any potential value-relevant information has been included in the share price. The CDR again provides an attractive environment to examine the impact of corporate disclosures on the timeliness of price discovery, because listed companies have to disclose to the market before any other media sources. This enables an exploration of the relationship between the timeliness and the frequency of continuous disclosures. If the CDR is efficient in keeping investors fully informed, there should be no stock price surprise after the earnings announcement is released. Given the importance of the Preliminary Final Reports to the timeliness metric and the fact that the immediate market reaction tests only cover announcements released during trading hours, this study investigates in depth the Preliminary Final Reports and finds some evidence that companies tend to release bad news after the market closes and/or on Fridays. In terms of the impacts of announcement frequency on the timeliness of price discovery, following the step ‘All announcements – Periodic/Non-periodic announcements – Detailed categories of Non-periodic announcements’, the findings reveal that only earnings-related and cash flow announcements (Periodic Reports, Distribution Announcements and Quarterly Cash Flow Reports) can accelerate the timeliness of price discovery. Unfortunately, the results do not confirm that more announcements on the market could promote the timeliness with which the value-relevant (i.e. earning/income) information is incorporated into share prices. In addition to announcement frequency influences, the price discovery process is faster for companies with better share performance, are larger or have greater profitability. Financial companies have a timelier price discovery process than other companies; the price discovery process of financial companies was affected more by the 2008 – 2010 Global Financial Crisis than that of other companies. This study contributes to the market reaction literature by covering all categories of company announcements and comparing immediate market consequences for each type of announcement, and builds upon the timeliness of the price discovery literature by linking the announcement frequency of each continuous disclosure category to the timeliness with which annual earnings information is incorporated into share prices.
Keywords: Announcement categories; Announcement frequency; Continuous Disclosure Regime; Immediate market reactions; Market sensitivity; Timeliness of price discovery

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (European Investment Bank, 2018)

La perception du processus de normalisation OHADA au Sénégal - Bampoky, Boniface (Vie & sciences de l'entreprise, 2018)
Cette tribune repose sur la réalisation d’un recueil des points de vue de professionnels de la comptabilité ainsi que des organes intervenant dans la normalisation comptable Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) au Sénégal. Les résultats de l’investigation sont confrontés à la réglementation comptable en vigueur, afin de mieux cerner les grands axes de normalisation comptable dans l’espace OHADA. Ce travail est novateur dans le sens où peu de travaux académiques portent sur cette thématique à l’échelle de l’OHADA.
Keywords: Droit comptable; Normalisateur comptable; Norme comptable; SYSCOHADA

Gaps in the IFRS Conceptual Framework - Barker, Richard; Teixeira, Alan (Accounting in Europe, 2018)
The stated purpose of the IFRS Conceptual Framework is to assist the IASB to develop Standards that are based on consistent concepts, and also to assist preparers to develop consistent accounting policies when Standards either do not apply or allow a choice of accounting policy. Yet, the Framework actually does surprisingly little to help the IASB (or preparers) determine which assets, liabilities, income and expenses should be recognised, and how they should be measured. The Framework’s focus on assets and liabilities implies that the accounting can, and should, be determined from the balance sheet. Yet, many current financial reporting requirements focus initially on the income statement, and so they are not so much derived from the Framework as instead in need of being reconciled back to it. At its heart, the problem here is that, while the Framework states that accrual accounting provides a better basis for assessing past and future performance than cash-based information, it does not explain why. To do so would require a conceptualisation of how entities’ business models are employed to create value, and of the strengths and limitations of accounting data in enhancing investors’ understanding of that value-creation. The lack of explanation of the purpose and informational objectives of accruals, how they relate to business models and how they cause the income statement and the balance sheet to interact are gaps in the Framework. Filling those gaps would provide a more robust, and natural, way for the IASB to develop recognition and measurement requirements in its Standards.
Keywords: Accruals; Conceptual framework; IFRS; Measurement; Unit of Account

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (European Investment Bank, 2018)

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

Financial Accounting: International Financial Reporting Standards - Harrison Jr., Walter T.; Horngren, Charles T.; Thomas, C. William (Bill); Tietz, Wendy M.; Suwardy, Themin (Pearson, 2018)

Accounting Translation of Corporate Social and Environmental Expenditures in Small and Medium Industry: What Evaluation Approach and what Accounting Scheme? - Missomba, Jean Christian Ewane; Hanko, Osée (Research Journal of Finance and Accounting, 2018)
The question remains whether societal reporting integrates the field of financial reporting. This old debate is repeated to scrutinize the case of African companies with strong cultural roots, which do not publish alternative societal documents to traditional financial reports. Through stakeholder theory (Jones and Wicks, 1999), this study aims to analyze the phenomenon, by describing the process of accounting recordings for social and environmental information (SEI) identified by the ISO 26 000 standard in an oil Company operating within OHADA Jurisdiction. The results indicate the presence of mandatory SEIs in the financial statements, which visibility depends on the pressure exerted by the State and the accounting regulations in force. Voluntary SEIs are not visible.
Keywords: Financial reporting; ISO 26000; Social and Environmental Information (SEI); Stakeholder Theory

L’arbitrage des litiges relatifs à la finance islamique - Alyaqout, Yousef (Université de Lorraine, 2017)
L’essor de la finance islamique moderne va poser logiquement la question de la résolution des litiges. En effet, le recours à la justice étatique aboutit à des impacts négatifs sur la réalisation des objectifs de la finance islamique et sur le développement de ce secteur d’activité. Dans cette optique, l’application de la législation nationale par le juge étatique aboutit à la requalification des contrats de financement islamique en des contrats de financement conventionnel. En outre, ce recours au juge étatique conduit à la neutralisation de la Charia en tant que droit applicable. Tout cela conduit à la dénaturation de la finance islamique. Cette dénaturation est une source de contradictions. On sait bien que les institutions financières islamiques reposent sur une obligation fondamentale, selon laquelle toutes les opérations financières effectuées doivent être conformes à la Charia. De plus, les personnes ayant recours à la finance islamique visent principalement à exercer des activités financières en toute conformité avec leurs principes religieux et éthiques issus de la législation islamique. L’étude a également montré que les modes amiables de règlement des litiges contribuent à prendre en considération la particularité de la finance islamique. Cependant, cette prise en compte reste insuffisante. En effet, ces modes ne présentent pas un mécanisme complet, homogène et cohérent de règlement des litiges relatifs à la finance islamique. Leur contribution à la construction d’un système juridique propre à la finance islamique est très limitée. De ce fait, ils ne peuvent pas participer efficacement à la promotion de l’industrie financière islamique. De plus, ils souffrent d’un défaut majeur au niveau de la force de la solution proposée : l’efficacité de cette solution dépend en principe de la bonne volonté des parties. Face à ce dysfonctionnement de la justice étatique et des modes amiables, la solution a été recherchée du côté de l'arbitrage. En effet, l’arbitrage connaît une expansion spectaculaire dans le monde actuel au point de devenir le mode normal de règlement des litiges. Cet essor exceptionnel de l’arbitrage se constate notamment dans la vie économique et financière. A l’heure actuelle, cette vie est devenue inconcevable sans l’arbitrage. En matière de finance islamique, l’arbitrage en tant que mécanisme reposant sur la liberté et la volonté apparaît comme la meilleure voie permettant la prise en considération de la spécificité de cette activité, l’application de la Charia dans le domaine de la résolution des litiges. C’est pourquoi, ce mode alternatif de règlement des litiges s’adapte parfaitement aux exigences des litiges relatifs à la finance islamique et pourrait contribuer à la promotion de ce secteur d’activité. Grâce aux avantages qu’il offre aux opérateurs de la finance islamique, l’arbitrage s’affirme comme la justice naturelle des litiges relatifs à la finance islamique. Pour renforcer le rôle de l’arbitrage dans le domaine de la finance islamique, un projet de réforme a été présenté. Ce projet vise à moderniser l’arbitrage dans toutes ses étapes. Dans cette optique, l’accent a été mis sur la convention d’arbitrage, le statut de l’arbitre, le droit applicable et la sentence arbitrale. Tout cela a été achevé par l’élaboration d’un projet de charte éthique de l’arbitrage en matière de finance islamique. Une fois modernisé et renouvelé, l’arbitrage peut devenir un pilier essentiel de l’industrie financière islamique, en participant efficacement à la promotion de cette activité. Avec une justice équitable, pratique, efficace, conforme à la Charia et adaptée, la finance islamique se trouve renforcée et consolidée. The rise of modern Islamic finance will logically raise the issue of dispute resolution. Indeed, recourse to state justice leads to negative impacts on the achievement of the objectives of Islamic finance and on the development of this sector of activity. In this context, the application of national legislation by the state judge results in the reclassification of Islamic financing contracts into conventional financing contracts. In addition, this recourse to the State Judge leads to the neutralization of Shariah as an applicable law. All this leads to the denaturation of Islamic finance. This denaturing is a source of contradictions. It is well known that Islamic financial institutions are based on a fundamental obligation that all financial transactions must conform to Sharia law. In addition, people who use Islamic finance primarily aim to conduct financial activities in accordance with their religious and ethical principles derived from Islamic legislation. The study also showed that amicable dispute resolution modes help to take into account the peculiarity of Islamic finance. However, this consideration remains insufficient. Indeed, these modes do not present a complete, homogeneous and coherent mechanism for resolving disputes relating to Islamic finance. Their contribution to the construction of a legal system specific to Islamic finance is very limited. As a result, they can not participate effectively in promoting the Islamic financial industry. In addition, they suffer from a major flaw in the strength of the proposed solution: the effectiveness of this solution depends in principle on the good will of the parties. Faced with this dysfunction of state justice and amicable modes, the solution was sought on the side of arbitration. Indeed, arbitration is expanding dramatically in today's world to the point of becoming the normal mode of dispute resolution. This exceptional growth of arbitration can be seen in particular in economic and financial life. At present, this life has become inconceivable without arbitration. In the area of Islamic finance, arbitration as a mechanism based on freedom and will appears as the best way to take into account the specificity of this activity, the application of Shari'a in the field of the resolution of litigation. For this reason, this alternative dispute resolution method is perfectly suited to the demands of Islamic finance litigation and could contribute to the promotion of this sector of activity. Thanks to the advantages it offers to operators of Islamic finance, arbitration is asserting itself as the natural justice of disputes relating to Islamic finance. To strengthen the role of arbitration in the field of Islamic finance, a reform project was presented. This project aims to modernize arbitration in all its stages. From this perspective, the focus was on the arbitration agreement, the status of the arbitrator, the applicable law and the arbitration award. All this has been completed by the elaboration of a draft ethical charter of arbitration on Islamic finance. Once modernized and renewed, arbitration can become an essential pillar of the Islamic financial industry, effectively participating in the promotion of this activity. With fair, practical, effective, Sharia-compliant and responsive justice, Islamic finance is strengthened and consolidated.
Keywords: Arbitrage; Arbitragem; Arbitration; Droit commercial; Droit financier islamique; Droit procédure; Litiges; Marché financier; Règlement de conflits

Le patrimoine fiscal du sylviculteur personne physique et personne morale - Arnaud-Emery, Alexandra (Université de Bordeaux, 2017)
Etablir la fiscalité applicable aux bois et forêts, de leur acquisition à leur transmission, en passant par leur détention et leur exploitation. L’étude fiscale de la vie d’une forêt permettra ainsi de mettre en exergue que l’investissement dans la forêt constitue un véritable placement rentable et attractif, en raison des nombreux régimes de faveur fiscaux propres à la matière sylvicole. Le particularisme fiscal touchant les bois et forêts ne trouve aucun équivalent, il se justifie uniquement par la volonté d’éviter la disparition de cette activité économique et d’en favoriser le développement et l’attrait pour de nouveaux investisseurs. La personne physique ou morale qui devient propriétaire de bois et forêts, pour se constituer un patrimoine forestier, acquiert la qualité de sylviculteur et entre alors dans une oasis fiscale.
Keywords: Bois; Fiscalité; Forest; Forêt; Impôts; Patrimoine; Propriétaires forestiers; Tax; Wood

Nécessité et éfficacité du contrôle des établissements de crédit en France - Agbessi, Germaine (Sorbonne Paris 13, 2017)
En raison du rôle et de l’importance particulière dans l’économie des établissements de crédit, leur activité est soumise à des obligations spécifiques découlant de règles dites « prudentielles » et à un contrôle de leur respect exercé par les pouvoirs publics pour assurer la stabilité financière et la protection des clients. La crise de 2008 a mis en exergue le rôle des banques dans l’économie réelle et la conséquence de leur prise de risque excessive. L’étude de l’évolution de la réglementation soumise aux établissements de crédit montre que le législateur a tardé à intervenir pour réglementer et mettre en place des organes indépendants et efficaces et des règles gouvernementales de supervision. Les contrôles sont nécessaires pour sauvegarder la stabilité et la sécurité financière qui supposent de plus en plus d’interventions de l’État français, d’ailleurs en coordination avec d’autres instances européennes et internationales pour faire face à l’aggravation des risques bancaires. Face à l’impossibilité pour l’État de tout réguler lui-même dans le secteur bancaire, il a fait le choix d’une délégation de pouvoirs à l’ACPR, autorité administrative indépendante chargée du contrôle bancaire. Mais le contrôle est rendu difficile car les règles à respecter sont trop nombreuses et parfois techniques. Elles sont élaborées par les professionnels du secteur bancaire. Elles évoluent et se renforcent en fonction des crises économiques. La multiplicité et le champ d’application très large de la réglementation compliquent encore la mise en œuvre du contrôle des établissements. De surcroît, les décisions de l’ACPR, font l’objet de recours pour faire obstacle aux sanctions prononcées par cet organe de contrôle. Le contrôle fait donc apparaître des insuffisances qui sont parfois comblées par d’autres autorités administratives chargées de la surveillance du secteur bancaire : Autorité des marchés financiers (AMF), Autorité de la concurrence, CNIL1). Pourtant des solutions existent : responsabilité des établissements de crédit dans la prise en charge de leur capital, renforcement des pouvoirs de l’ACPR, aggravation de la répression et des sanctions de certaines infractions économiques…
Keywords: Achats par levier; Auto-contrôle; Change – Droit; Contrôle prudentiel; Contrôle prudentiel (droit européen); Cotes de solvabilité; Crédit – Droit; Droit souple; Investissements bancaires; Prudent regulations; Ratio de solvabilité; Réglementation prudentielle; Self controlling; Épargne

L’impact du droit et de la régulation sur les institutions financières : trois essais - Haddad, Christian (Université Lille 2, 2017)
Quels sont les effets du droit et de la régulation sur les institutions financières? Cette thèse propose d’apporter des réponses à cette question tout au long de trois chapitres. Le premier chapitre étudie l’impact du droit des entreprises en difficulté sur la prise de risque des banques. Les principaux résultats montrent qu’une meilleure protection des créanciers augmente le risque systémique des banques. Ces résultats sont observés dans les pays développés où les banques sont davantage engagées dans les instruments complexes, elles sont plus grandes et plus interconnectées que celles dans les pays en voie de développement. Le second chapitre expose l’émergence des startups fintechs et présente la première étude empirique consacrée aux déterminants technologiques et économiques de ce secteur. Les résultats indiquent que les pays présentent davantage de créations de startups fintech quand les marchés de capitaux sont bien développés, que les nouvelles technologies sont facilement accessibles et que les personnes possèdent plus d’abonnements de téléphonie mobile. Le troisième examine les déterminants juridiques de l’implantation des banques à l’étranger à travers les investissements directs. L’étude constate que certains pays accueillent plus de banques étrangères quand les restrictions réglementaires sur l’investissement étranger direct sont limitées, que le coût lié au paiement des impôts est plus bas et les gouvernements moins corrompus.
Keywords: Bank systemic risk; Créditor rights; Droit des créanciers; Finances; Financial institutions; Fintech; Foreign direct investment; Institutions financières; Investissement direct étranger; Investissements étrangers; Risque financier; Risque systémique bancaire

Les agences de notation : l’appréhension juridique d’un pouvoir privé économique - Marsaud, Guillaume (Université Côte d'Azur, 2017)
Révélées au grand jour à partir de l’année 2007, par leur implication dans la crise des subprime puis parleur rôle procyclique dans celle des dettes souveraines, les agences de notation ont été l’objet d’une attention toute particulière du législateur qui se devait d’assurer l’intégrité des marchés et de restaurer la confiance des investisseurs au lendemain d’un véritable cataclysme financier. Conflits d’intérêts, opacité, méthodologies défaillantes, crédibilité équivoque, comportements anti-concurrentiels, les critiques adressées à l’encontre de l’oligopole, dominant l’industrie de notation, étaient nombreuses. L’adoption successive de dispositifs règlementaires n’a pu permettre un affranchissement de l’influence de ce pouvoir privé économique, dont l’enracinement règlementaire date du lendemain de la Grande Dépression de 1929 et le développement est étroitement lié à celui de la titrisation. Bien au contraire, les nouvelles règlementations qui auraient dû encadrer «l’activité» plutôt que les «structures» n’ont eu, au coté de certaines initiatives louables, eu pour effet principal que la consécration d’un régime spécial. Même les affronts à l’ordre public économique n’ont été que rarement lavés par une justice qui se trouvait, sauf rares exceptions, en manque d’armes adéquats et par un régulateur encore trop balbutiant. Rattrapés par des enjeux en constante mutation, les quelques acquis liés à la transparence et au contrôle des agences de notation tendent déjà à être remis en cause. Le législateur, quant à lui, semble déjà être passé à autre chose, et ce, alors que point à l’horizon des nouveaux marchés de nouvelles bulles où agissent encore les agences de notation.
Keywords: Agences de notation financière; Banques (réglementation); Conflits d’intérêts; Crises financières; Marché financier; Oligopole; Opacité

L'imposition des bénéfices des entreprises en France et au Sénégal - Ba, Elhadji Cheikh Gueye (Université Jean Moulin Lyon 3, 2017)
Résumé : L’imposition des bénéfices des entreprises en France et au SénégalL’objectif de toute politique fiscale est de répondre à des préoccupations économiques et sociales. Le phénomène de la mondialisation des échanges a très rapidement modifié les relations entre les systèmes fiscaux nationaux. Aujourd’hui avec l’interpénétration des économies, les États ne peuvent plus ignorer la nécessité d’agir de concert vers une convergence des systèmes fiscaux. Mais la France et le Sénégal n’ont pas attendu l’apparition du phénomène de la mondialisation pour se rapprocher juridiquement et fiscalement. En effet, l’histoire de la colonisation ne s’est pas construite en dehors de la trajectoire fiscale. Ressource d’enrôlement, de contrôle des indigènes, la fiscalité a été le canal historique de l’imposition et de légitimation des ordres coloniaux. S’il existe des similitudes et des différences dans l’imposition des bénéfices des entreprises entre les deux États, c’est tantôt dû à l’héritage colonial, dans ce cas, le mimétisme fiscal a un sens, tantôt dû à la protection jalouse de leur souveraineté, dans ce cas chaque État cherche à spécifier sa législation fiscale et une dissociation nouvelle s’impose. Contrairement au système dit de la mondialité pratiquée par la majorité des pays, la France et le Sénégal font figure d’exception en choisissant d’imposer leurs entreprises selon le principe de territorialité. Ils appliquent au traitement fiscal des résultats de leurs entreprises un principe identique d’imposition des bénéfices aux plans des règles d’assiette, de liquidation et de recouvrement. Toutefois, il reste possible de mettre en valeur d’une part, les différences au niveau des assiettes et des recettes fiscales, d’autre part la concurrence des mesures fiscales incitatives en droit national et des mesures préventives prise en droit conventionnel afin d’éliminer les doubles impositions.Mots clés : Impôt, Entreprise, Territorialité, Convention fiscale.
Keywords: Benefits; Bénéfices; Company; Convention; Double taxes; Doubles impositions; Droit fiscal; Entreprises; France; Impôt; Profits; Sénégal; Tax; Territoriality; Territorialité

Essays on Bank risk, capital and Lending - Alraheb, Tammuz (Université de Limoges, 2017)
Cette thèse examine trois questions importantes dans le secteur bancaire, à savoir le risque, les fonds propres et le crédit. Elle comprend trois essais empiriques. Le premier chapitre analyse l'impact du «printemps arabe» et de la crise financière mondiale de 2007-2008 sur la stabilité du secteur bancaire dans la région MENA. Les résultats montrent que le «printemps arabe» n'a pas eu d'effet négatif sur la stabilité des banques, alors que la crise financière mondiale a considérablement réduit leur stabilité. Le deuxième chapitre étudie le rôle joué par l'environnement institutionnel dans la mise en place de coussin de fonds propres par les régulateurs ou par les banques en interne. D’après les résultats, pour que les ratios de capital réglementaire soient efficaces, l'environnement institutionnel ne doit pas être négligé lors de la mise en place de ces ratios. Le troisième chapitre étudie les différents effets des droits des consommateurs et des créanciers sur le coût des prêts. Les résultats révèlent que le coût des prêts augmente en présence de lois strictes sur la protection des consommateurs, tandis que l'augmentation des droits des créanciers réduit ce coût.
Keywords: Bank Capital Structure; Bank foreign expansion; Bank loan growth; Banque expansion à l'étranger; Banques; Consommateur (protection); Cost of intermediation; Coût de l'intermédiation; Creditors' rights; Crise économique (2008); Croissance du crédit bancaire; Droits des créanciers; Structure du capital de la Banque

Le droit à l'épreuve du flux financiers illicites dans le secteur extractif : entre manipulation et double discours - Lemaître, Sophie (Université de Rennes 1, 2017)
Le pétrole, le gaz et les minerais sont des ressources indispensables pour le bon fonctionnement de nos économies et sont très convoitées. Elles sont, en outre, particulièrement propices à l’émergence de flux financiers illicites tels que la corruption, l’évitement fiscal ou encore le blanchiment de capitaux. La prise de conscience relative à l’ampleur des pratiques illicites dans le secteur extractif est relativement récente. Depuis une vingtaine d’années, diverses mesures formant un régime juridique ambitieux ont été adoptées pour endiguer ce phénomène. Malgré l’existence de ce régime juridique, les pratiques illicites perdurent au sein de ce secteur. Les acteurs du secteur extractif, entreprises et agents publics, ont su s’adapter et faire preuve de créativité pour contourner, détourner et manipuler ce régime juridique, afin de préserver leurs avantages et de perpétuer les flux financiers illicites. Ils peuvent également recourir à l’ingénierie juridique et financière qui leur fournit un arsenal d’outils juridiques et mobilise des experts maîtrisant à la perfection l’environnement juridique, politique et financier dans lequel les acteurs du secteur extractif évoluent. Ainsi le droit peut-il être propice aux flux financiers illicites et même au service de ceux-ci tout en voulant les combattre.
Keywords: Blanchiment de capitaux; Corruption; Criminalité des affaires; Evasion fiscale; Industries extractives; Industries minières; Lutte contre le blanchiment de l'argent; Transparence; Évasion fiscale

Faut-il plus de capital en assurance ? - de Bandt, Olivier; Hervo, Frédéric (Revue d'économie financière, 2017)
Dans le contexte des crises financières récentes, le capital en assurances s’est régulièrement accru et le secteur apparaît suffisamment capitalisé dans l’Union européenne. L’entrée en vigueur de Solvabilité II constitue une nouvelle étape, avec l’introduction d’une mesure du capital plus adaptée à la réalité économique et à la nature des risques. En utilisant une valorisation économique du bilan des organismes d’assurance, la nouvelle mesure du capital introduite par Solvabilité II représente une vision de la juste valeur, mais rend son contrôle plus délicat, car potentiellement plus complexe et plus volatil. En effet, les fonds propres prudentiels sont désormais le fruit de calculs sophistiqués, reposant sur de nombreuses hypothèses qui appellent l’organisme et le superviseur à une vigilance accrue et un regard plus critique. Enfin, le capital en assurance nécessite aussi une certaine flexibilité dans sa gestion. Particulièrement dans l’univers économique actuel, caractérisé par un niveau des taux durablement bas avec le risque d’une plus grande volatilité, la gestion du capital est primordiale, tant sur la politique de distribution que sur les moyens de financement. À ce titre, les organismes pourront affiner leur politique de gestion du capital en utilisant les nouveaux outils apportés par la réglementation, et notamment leur évaluation propre des risques (l’ORSA) et renforcer le dialogue entre leurs instances de direction et le superviseur.

Los contratos de financiación bancaria con Administraciones Públicas: reflexiones sobre el principio de prudencia financiera y la interconexión del derecho privado y el derecho público - Comellas Goberna, Anna (Universitat de Barcelona, 2017)
Las Administraciones Públicas también interactúan en el mercado con la finalidad de obtener financiación y servicios de las entidades financieras, al igual que las personas físicas y las empresas. Se les puede considerar, por tanto, como clientes bancarios públicos en contraposición a los privados. En efecto, tales Administraciones están legalmente habilitadas para contraer obligaciones de endeudamiento con entidades financieras que luego se formalizarán a través de contratos bancarios. Sin embargo, cuando la Administración Pública, regida idiosincrásicamente por el Derecho Administrativo, interactúa con entidades financieras, regidas por el Derecho Mercantil y Bancario, ello provoca que los contratos bancarios habituales en el tráfico negocial no puedan serle directamente aplicables sin una previa adaptación de los mismos a la peculiaridad del cliente bancario público. Dicha adaptación se halla justificada en nuestro ordenamiento jurídico por la preferente protección de los intereses públicos, como demuestra por ejemplo la introducción del principio de prudencia financiera, que limita el coste de endeudamiento de las operaciones de financiación para Comunidades Autónomas y Entidades Locales, a la vez que prohíbe algunas, y afecta al normal ejercicio de la autonomía de la voluntad. Además, dicha adaptación de los contratos bancarios a la parte contratante pública, también alcanza al régimen de garantías aplicable a la concreta operación financiera, siendo ambos extremos los que constituyen las peculiaridades de los mcontratos de financiación bancaria con Administraciones Públicas. De hecho y en lo que a garantías se refiere, se parte de que el dinero público no puede ser objeto de compensación ni de embargo. Así, la Administración Pública, a pesar de estar sujeta al principio de legalidad, en la actualidad sigue manteniendo una posición de supremacía en determinados aspectos en el ámbito de los contratos bancarios, y éste es el más destacable. También, figuras como la prenda y cesión de créditos deberán ser matizadas, u otras como los avales y cartas de conformidad someterlas a una adecuada valoración de conveniencia, jurídica y práctica. Pues bien, el estudio de estas peculiaridades constituye el objeto de la presente tesis. Son contratos en los que se produce claramente la interconexión entre el Derecho público y el Derecho privado por la interacción que se produce entre la Administración Pública, como parte deudora contratante, y la entidad financiera, como parte acreedora contratante. La fusión y conexión entre ambas ramas del Derecho es necesaria para el fin pretendido por ambas partes, siendo el estudio de dicha interacción y el alcance del Derecho público y del Derecho privado en estos casos lo que se analiza en la presente tesis. También aportando una perspectiva práctica y finalista mediante el presente estudio, bajo la consideración de que el Derecho debe ser aplicable a una realidad, que en este caso es mixta o basada en una relación público-privada, aunque sin olvidar que se está ante un estudio académico en el ámbito del Derecho cuya rigurosidad teórica resulta esencial. Adicionalmente, se hará alusión también a otra tipología de contratos que pueden convenir Administraciones Públicas con entidades financieras distintas a los de financiación: los contratos de servicios bancarios. Están sujetos a Derecho público en gran medida y su objeto es la gestión de cobros y pagos del cliente público para el desarrollo normal la actividad financiera y de la hacienda pública. En ambas tipologías contractuales las partes son las mismas pero el régimen jurídico es distinto, que se va a contraponer y comparar a efectos discursivos, sin perjuicio de centrar el objeto de análisis en los contratos de financiación bancaria. En definitiva, se trata de un estudio contextualizador de la realidad de los contratos de financiación bancaria que conciertan las Administraciones Públicas con las entidades financieras, que partirá del estudio de los contratos bancarios habituales en este ámbito, continuará por la explicación de la peculiaridad del cliente bancario público, el análisis de la evolución normativa habida en la materia, hasta culminar con el detalle del régimen y limitaciones del endeudamiento bajo nuestro ordenamiento jurídico, a través de un examen crítico del status quo y con ánimo de ofrecer una visión jurídico-práctica de la realidad de estos contratos de financiación bancaria.
URI: https://www.tdx.cat/handle/10803/457424
Keywords: Administrative law; Banking law; Ciències Jurídiques; Commercial law; Derecho administrativo; Derecho bancario; Derecho financiero; Derecho mercantil; Dret administratiu; Dret bancari; Dret financer; Dret mercantil; Econòmiques i Socials; Finance law

Outils actuariels adaptés au pilotage technique des risques en Afrique subsaharienne francophone : application aux régimes de retraite - Gbongue, Kanga Florent (Université Claude Bernard Lyon 1, 2017)
Le pilotage technique des risques en Afrique subsaharienne francophone est une notion souvent absente dans la pratique. En effet, dans cette zone, il est très facile de rencontrer des banques, compagnies d'assurance et institutions de retraite, menées leurs activités sans intégrer le risque1 au coeur de leur gestion. Cette situation explique, a priori, l'absence des bases de données fiables pour des études quantitatives. La présente thèse, qui se veut complémentaire aux travaux de KAMEGA A2., s'intéresse à la conception des outils actuariels pertinents adaptés au pilotage technique des risques en Afrique subsaharienne francophone, qui peuvent être utilisés aussi bien par les gouvernements de cette zone que dans l'industrie des assurances et des banques. Au regard du développement progressif des pays de la zone CIPRES, nous estimons que le générateur de scénarios économiques (GSE) est l'outil commun au pilotage technique des risques liés aux activités des États et de l'industrie des banques et des assurances. Notons que le GSE est un outil capable de projeter les variables économiques et financières dans un système cohérent. Cette information riche permettra, par exemple, aux gouvernements de ces pays, d'élaborer leurs budgets, de mobiliser des ressources sur le marché financier local et de piloter techniquement la dette publique. Dans le contexte de la conception du GSE, l'apport de cette thèse consiste à spécifier dans un premier temps des modèles mathématiques, adaptés au contexte de la zone CIPRES, couvrant un nombre important de variables économiques et financières. Dans un second temps, des méthodes de calibrage sont présentées dans le contexte d'absence de données (avis des experts) ou de présence des données (approches statistiques). Une attention particulière est accordée à l'extension du GSE dans l'optique de prendre en compte les besoins futurs des professionnels de la zone CIPRES. Cette thèse accorde également une importance aux application du GSE dans le développement des pays de la zone CIPRES à travers l'apport de la courbe des taux dans l'analyse et la conduite de la politique monétaire, la prévision des grandeurs économiques et financières, l'estimation des probabilités de défaut implicites et des taux de recouvrement des États et des entreprises dans un contexte de notation en monnaie locale et d'application du dispositif Bâle II/III dans le courant de 2018. Dans le cadre des régimes de retraite, ces outils actuariels sont utiles pour déterminer les paramètres de pilotage du régime, notamment l'évaluation « best estimate » des engagements du régime, le financement et la stratégie d'allocation des actifs. The technical management of risks in Francophone Sub-Saharan Africa is often lacking in practice. In fact, in this zone, it is very easy to meet banks, insurance companies and pension institutions, doing their activities without integrating risk at the core of their management. This situation explains, a priori, the absence of reliable databases for quantitative studies. This thesis, which is complementary to work of KAMEGA A., focuses on the design of relevant actuarial tools adapted to technical risk management in sub-Saharan Africa, which can be used by both the governments of this zone and the insurance and banks industry. In view of the gradual development of the countries in the CIPRES zone, we believe that the economic scenario generator (ESG) is the common tool for the technical management of risks linked to the activities of the states and the banking and insurance industry. Note that the GSE is a tool able to forecast the economic and financial variables into a coherent system. This rich information will allow, for example, the governments of these countries to draw up their budgets mobilize resources on the local financial market and manage technically the public debt. In the context of the design of the GSE, the contribution of this thesis consists to specify initially mathematical models, adapted to the context of the CIPRES zone, covering a large number of economic and financial variables. In a second step, calibration methods are presented in the context of lack of data (expert opinion) or presence of data (statistical approaches). Particular attention is given to the extension of the GSE in order to take into account the future needs of professionals of the CIPRES zone. This thesis also gives importance to the application of the GSE in the development of the countries of the CIPRES zone through the contribution of the yield curve in the analysis and conduct of monetary policy, the forecasting of economic and financial quantities, Estimation of the probabilities of implicit defaults and the recovery rates of states and firms in the context of a local currency rating and the application of the Basel II / III framework in the course of 2018. Under the pension plans, these actuarial tools are useful in determining of the management parameters of the plan, including the "best estimate" of plan commitments, funding and asset allocation strategy.
Keywords: Actuarial tools; Assurance; CIPRES; Courbe des taux; Economic scenario generator; Gestion du risque; Générateur de scénarios économiques; Management parameters; Mathématiques; Outils actuariels; Paramètres de pilotage; Pilotage technique; Régimes de retraite; Technical management; Yield curve

La régulation des matières premières agricoles - Huguet, Stephane (Université Côte d'Azur, 2017)
La régulation des marchés des matières premières agricoles est un travail qui vise à évaluer les conséquences de l‘évolution de notre société sur ce produit essentiel. En effet, son prix est soumis à de nombreuses influences. Pourtant le droit a décidé pour le moment de s‘en détourner dans la majorité. Ce travail doctoral tente ainsi de déterminer quelles sont les points faibles des législations dans plusieurs domaines afin de sécuriser ce produit dont la valeur inconsciente est essentielle pour obtenir la paix social que le droit tend à obtenir. The regulation of agricultural commodity markets is a academic‘s work that evaluates the consequences of the evolution of our society on this essential product. Indeed, its price is subject to many influences. Yet the Law has decided for the moment to turn away from it in the majority. This doctoral work thus tries to determine what are the weak points of the legislations in several fields in order to secure this product whose unconscious value is essential to obtain the social peace that the Law tends to obtain.
Keywords: Agricultural commodity; Banking law; Commerce; Droit bancaire; Industrie et commerce; Marché financier; Matières premières (commercialisation); Matières premières agricoles; Prix; Prix agricoles; Produits agricoles (commercialisation); Regulation; Régulation

Les financements structurés et le droit des entreprises en difficultés - Benhamou-Gabriel, Archibald (Université Paris 1, 2017)
Les financements structurés semblent se construire comme des instruments de neutralisation de la procédure collective. Ces montages, utilisés tant en matière de financement d'acquisition (LBO) qu'en matière de financement de projet, ont vocation à influencer tant lu saisie collective que les répartitions qui en découle (première partie). Face au caractère d'ordre public de la procédure collective, le nombre de stratégies permettant d'assurer l 'efficacité des financements structurés en cas de restructuration est limitée. Les montages pourront s'appuyer sur deux méthodes s'appuyer sur des textes dérogatoires (ex : titrisation) ou s'appuyer sur les limites des procédures collectives pour éviter les effets de la faillite (ex : les double Lux co). L'utilisation des limites du droit des procédures collectives ou de régimes spécifiques sera-t-elle suffisante pour échapper aux contraintes des procédures collectives? Cette question se posera tant durant la phase de saisie collective que durant celle des répartitions. Il conviendra donc d'étudier la résistance de financements structurés face à l'épreuve de la procédure collective (seconde partie). Structured finance seems to be design as a tools to neutralize insolvency procedures. Those financing agreement, used in LBO and in project finance, are intended to influence both the assets seizure and the resulting distributions during the restructuring process (Part 1 ). Most of the time, rules of insolvency procedures are considered binding and should not be impacted by contracts. Therefore, the number of efficient strategies for structured finance in the event of restructuring ore limited. The structure can be based on specific legal status (e.g: securitization) or rely on the limits of insolvency procedures (c.g.: schemes implying Luxemburgish holding). Will contractual forecast defined by structured finance be enforceable during the restructuring process? It will therefore be necessary to study the resistance of structured finance to the constrained or insolvency procedures (second part).
Keywords: Entreprises – Droit; Entreprises en difficulté; Financement de projet; Financement structuré; Finances; Insolvency procedures; LBO; Montages; Procédures collectives; Project finance; SPV; Securitization; Structured finance; Subordination de créances; Titrisation

Le principe de solidarité et la gestion des crises dans le secteur bancaire - Polito, Gabriele Maria (Université de Strasbourg, 2017)
Cette thèse est destinée à démontrer l’existence d’un principe de solidarité dans le cadre de l’Union bancaire européenne (UBE). Ce travail est divisé en trois chapitres. Le premier chapitre vise à retracer les différentes nuances qui caractérisent la sémantique du mot ‘solidarité’. Le deuxième chapitre est consacré à l’évaluation des dispositions des traités qui se réfèrent à la notion de solidarité. Le troisième chapitre analyse la façon dont le principe de solidarité est développé dans l’UBE. En conclusion, la thèse tente de prouver que dans ce nouveau cadre juridique européen, la « règle » continue d’être la non-solidarité; en revanche, l’ « exception » continue d’être la solidarité, comme cela a été confirmé par les nouveaux outils, qui pourraient être déclenchées par l’autorité compétente uniquement en présence de difficultés sérieuses dans le secteur bancaire.
Keywords: Aide d'Etat; Bail-in; Banque centrale européenne; Banques – Droit européen; Crises financières; European Banking Union; Renflouement interne; Resolution of the banking institution; Résolution des établissements de crédit; Solidarity; Solidarité; Solidarité (droit); State aids; Union Bancaire européenne

La normalisation comptable internationale par l’IASB - Danjou, Philippe (INSEE, 2017)
Cette note, préparée pour le 16ème colloque de l’ACN, a pour objet d’exposer de façon succincte les origines du mécanisme d’harmonisation internationale des normes comptables IFRS dans le secteur privé, les modalités de fonctionnement de l’organisme qui édicte ces normes, la façon elles sont transposées dans la règlementation. On y présentera l’état des lieux en matière d’adoption internationale. Enfin, le processus d’élaboration d’une norme IFRS sera illustré par un survol des travaux ayant abouti à la publication récente de la norme IFRS 16 « Contrats de location ».

L'évolution institutionnelle du capital risque dans l'environnement du Web 2.0 : une étude comparative et transdisciplinaire - Ausiandra, Yusuf (Université de Strasbourg, 2017)
Le sujet développé dans cette thèse pose comme objectif de répondre à trois problématiques résumables par une corrélation entre trois points principaux :(a) la relation entre l'usage des nouveaux outils des plateformes 2.0 dans l’intermédiation de la finance et l’émergence d’un nouvel archétype de financement ; (b) la distinction observée entre le capital-risque conventionnel et les financements opérant actuellement dans un environnement 2.0 et (c) l’approche optimale pour construire un environnement juridique modulé à l’évolution récente introduite par les outils 2.0 dans le financement de l’innovation. La recherche aborde la problématique en déconstruisant la dynamique institutionnelle de l’évolution économique contemporaine. Par cela la recherche tente de déterminer la nature et l’étendue des changements subis par l’économie en interaction constante avec le progrès technologique des nouvelles technologies d’information et de communication. La méthodologie du fond adoptée dans cette recherche fait partie de l’analyse économique de droit (Law and Economics). Néanmoins, l’analyse est enrichie par une référence aux outils théorétiques du courant économique néo-institutionnaliste américain et la sociologie économique critique française. Cette transdisciplinarité permet ainsi de comprendre la nature de l’évolution d’une manière plus élaborée. Le fil conducteur de cette recherche réside dans le phénomène de la financiarisation de l’économie. Cette recherche supporte l’idée selon laquelle les bouleversements du format et fonctionnement économiques actuels sont majoritairement le résultat d’un double mouvement institutionnel de nature financière et technologique. La recherche identifie trois institutions de nature économique et juridique au cœur du modèle de financement de l’innovation américain : la gouvernance par la flexibilité contractuelle fondée sur la notion du private ordering, la liquidité financière et l’externalisation du processus de l’innovation par rapport à la firme. Une analyse comparative de différents cadres règlementaires portant sur le capital risque en vigueur à travers le monde confirme la centralité de ces trois institutions. En conclusion de la recherche, il est ainsi nécessaire pour un Etat de reconnaître la nature institutionnelle du modèle de financement par lequel il compte supporter l’innovation. Pour le modèle de financement par capital-risque dominant aux Etats-Unis, un point d’équilibre entre d’une part un cadre règlementaire visant la protection des investisseurs et d’autre part des mesures favorisant la création de la liquidité financière devient indispensable. Néanmoins,l’oscillation règlementaire entre des mesures de support de liquidité et des règlements restrictifs reste en effet inévitable. L’évolution de la financiarisation de l’économie en alliance avec une concurrence pour l’innovation technologique ramènera les acteurs privés à assurer eux-mêmes la création de la liquidité. L’émergence des nouveaux types de contrats de financement par fonds propres allégés aux Etats- Unis (KISS contracts) puis reconfigurés pour le système juridique français (Contrats AIR) sert de preuve à cette hypothèse. La tâche la plus signifiante aujourd’hui pour les législateurs sera ainsi la création d’un ensemble de mesures protectrices contre les risques déraisonnables et démesurés. Ceci tout en assurant que les deux éléments irréductibles propres à l’institution du capital-risque – la spéculation conditionnelle et l’autonomie contractuelle – soient assurés par une marge de manœuvre suffisante requise pour supporter l’innovation. The present doctorate research thesis attempts to resolve three correlated problematics summarized as following: (a) the relation between the use of new tools provided by the 2.0 platforms especially in the field of financial intermediation and the advent of a new financial archetype; (b) the difference between venture capital 2.0 and the conventional venture capital and (c) the concern over the utmost optimum approach in constructing a legal environment adapted to the current evolution introduced by the use of 2.0 tools in the financing of innovation. The research confronts the problematic by conducting a preliminary deconstruction of the ongoing institutional dynamic in regards to the current economical transformation. Subsequently, the research would attempt to define the nature and extent of the economical mutations in constant exposure to the new technologies in information and communication. This research fundamentally adopts a law and economics (L&E) analysis. In addition, the research would complement the traditional L&E analysis with further theoretical instruments by referral to the American neo-institutionnalist school of thought along with the French critical socio-economic theories. This transdisciplinarity would grant the possibility of attaining a more indepth understanding of nature of the economical mutation. The central unifying theme throughout the research resides on the concept of financialization of the economy. The research attributes the major disruption in the form and functioning of contemporary economy to an institutional financial and technological wave of change. The research identifies three economical and legal institutions residing at the core of the American financing of innovation model : the governance through contractual flexibility based on the notion of “private ordering”, financial liquidity and the externalization of the innovation process. A comparative analysis of different venture capital regulatory framework in various national jurisdictions confirms the major importance of the three stated institutions. In sum, the institutional nature of the financing model adopted by the government in support of innovation should be fully considered by national governments. For the case of the US venture capital model, an equilibrium point should be attained between two main regulatory framework objectives: the protection of investors and the creation of financial liquidity. A regulatory oscillation between liquidity creation and regulation would always prevail. Nonetheless, the financialization of the economy in conjunction with IT innovation would oblige private actors to maintain the creation of financial liquidity through private initiative. The emergence of new types of simplified equity financing model contracts such as the KISS contracts and the French variant, AIR contracts confirms this statement. Legislators would have to provide protection against unreasonable risk taking while ensuring that the two main elements of venture capital rest unhindered : conditional speculation and sufficient contractual autonomy to support innovation.
Keywords: Capital investissement; Capital risque; Capital-risque; Contractual flexibility; Entreprises innovantes; Finances; Financial liquidity; Financialization; Financiarisation; Flexibilité contractuelle; IT; Innovation; Internet; Internet (aspect économique); Liquidité financière; NTIC; Private equity; Regulation; Venture capital; Études comparatives

Sortie des pays africains de la zone Franc : entre le mythe et la réalité - Mbaye, Ahmadou Aly; Diop, Ibrahima Thione; Gueye, Fatou (Revue Interventions économiques, 2017)
La Zone Franc est une séquelle de l’économie coloniale, mais confondre dévaluation et sortie de la zone Franc est un amalgame. Depuis un certain temps, on observe une résurgence des prises de position sur l’opportunité des pays africains des zones UEMOA et CEMAC de sortir ou non de la zone Franc. A vrai dire, rien dans les termes de ce débat n’est nouveau. Depuis l’émergence de la zone, à l’aube des indépendances, un très fort courant nationaliste a porté en Afrique et dans la diaspora, les a...

Réforme de la structure fiscale et Intégration régionale - Nguimkeu, Pierre (Revue Interventions économiques, 2017)
L'Afrique semble s'être intégrée au reste du monde bien plus rapidement qu'avec elle-même. Pour la plupart des pays, le plus important partenaire commercial se trouve de l'autre côté de la frontière. La logique économique dicte qu’un produit doit parcourir la distance la plus courte possible pour atteindre son marché - puisque les coûts augmentent avec la distance. L'Afrique postcoloniale est une exception récalcitrante à cette règle fondamentale de l’économie. La structure des économies afri...

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

The taxation of small business in developing countries - AKM, Atiqul Haque (Monash University, 2017)
The thesis attempts to explore an efficient policy and administrative framework to tax the small businesses in developing countries. In order to approach the policy and administrative problems concerning the taxation of small business in developing countries this thesis asks How can small businesses be efficiently taxed in developing countries? This thesis over eight chapters qualitatively explores this research question. The analyses conclude that first, in a typical developing country a well-designed simple to follow presumptive tax regime is more efficient than the actual account based tax system. Second, this thesis argues that the noncompliance of small businesses in developing countries may not be adequately explained by the standard expected utility based compliance models. The leading tax compliance models which mainly emphasise on the perceived reward from evasion might ignore some crucial factor that constitutes the tax compliance environment of small businesses in developing countries. This thesis illustrates broadly the typical tax compliance environment of small businesses. It argues that a simple to follow tax system that requires a minimal level of taxpayer compliance would attract a section of small taxpayers into the formal tax net. Third, this thesis demonstrates that there are crucial differences between typical urban and rural businesses. A small business tax regime should have a separate set of presumptive instruments for each class of small business in order to make an efficient estimate of their economic activities. Fourth, this thesis analytically examines the presumptive methods and their practical applications. The findings suggest that in developing countries presumptive tax methods have been adopted mostly in arbitrary manner, without the objective considerations to many crucial design issues. Fifth, this thesis has developed a focused analysis on the taxation of urban small businesses in the contexts of developing countries. This thesis analyses some crucial characteristics of urban small businesses and stresses that enterprise formalization should be a key element of urban small business tax policy. For a meaningful expansion of the tax net, tax administration should put more focus on urban small businesses as these businesses have relatively more potential to grow as more stable and sustained taxpayers. This thesis concludes that a turnover based presumptive taxation is more efficient to tax the urban small businesses. Lastly, this thesis explores the issues concerning the taxation of rural small businesses. This thesis reports that the overall tax burden on the agricultural income had substantially declined over the last few decades. Developing countries should not ignore the tax potential of the rural taxpayers. In a typical developing country an asset based presumptive tax system is more efficient to tax the agricultural income of the rural small businesses. This thesis has argued that it would be more efficient to adopt a single asset based presumptive income tax replacing all the prevailing taxes on the agricultural income such as agricultural land tax, wealth tax and income tax.
Keywords: Fiscal policy; Small business taxation; Taxation administration; Taxation in developing countries; Taxation law; Taxation of rural small business; Taxation of shadow economy; Taxation of urban small business; Taxation policy

La lutte contre la délinquance économique et financière dans l'Union Economique et Monétaire Ouest Africaine (UEMOA) et dans l'Organisation pour l'Harmonisation du Droit des Affaires en Afrique (OHADA) : état des lieux et perspectives - Diakhate, Serigne Modou (Université Paris 1, 2017)
La délinquance économique et financière, constituée par l'ensemble des activités illégales, qui peuvent être commises de manière individuelle, en entreprise ou bande organisée, a des méthodes d'action différentes de celles des infractions de droit commun. Le plus souvent, elles se commettent par des procédés astucieux (tromperie), ou frauduleux (faux par exemple), par l'exploitation des secrets commerciaux ou des données confidentielles (délits d'initiés), exigeant pour cela des connaissances et un savoir-faire propres au monde des affaires, voire une ingénierie financière, à l'encontre des particuliers, d'entreprises. de l'Etat ou d'organisations internationales. Généralement, leur finalité est la recherche du gain facile, donc de l'argent sale ou noir, fruit d'activités illégales ou criminelles. Cet argent est au centre de la délinquance économique et financière. Il en est le moteur. C'est une des raisons pour lesquelles la lutte contre cette forme de délinquance doit avoir comme principale finalité la saisie des avoirs d'origine criminelle ou délictuelle. A cette fin. nous avons fait dans cette étude, des propositions de réforme dans les codes pénaux et de procédure pénale des Etats appartenant à la sphère UEMOA-OHADA et d'y inclure des dispositions permettant de procéder efficacement à cette saisie. Cette question de saisie des avoirs d'origine illicite montre à quel point il est difficile de lutter contre cette forme de délinquance. Car, aujourd'hui, l'action des Etats, pris individuellement. pour combattre ce fléau, a perdu son efficacité. C'est pourquoi, le traitement de cette délinquance devrait nécessairement passer par une harmonisation du droit pénal des affaires de l'OHADA et une uniformisation du droit pénal économique et financier de l'UEMOA. Cependant. ce combat au niveau communautaire n'est pas sans poser quelques difficultés dans la mesure où les Etats membres de ces deux organisations ne veulent pas se départir, au profit des Institutions communautaires, du pouvoir d'élaborer des sanctions pénales contre les incriminations communautaires applicables sur leur territoire. D'où la nécessité de tenir compte de l'impératif d'harmonisation des règles pénales de sanction contre les violations du droit communautaire, d'un côté, et de l'impératif du respect de la souveraineté des Etats, de l'autre, même si ces deux impératifs sont difficilement conciliables. En tout état de cause, pour rendre efficace la lutte contre ce phénomène criminel, les dispositifs actuels doivent évoluer vers de nouveaux instruments plus adaptés. Ainsi des typologies de mesures relatives au droit pénal de forme et de fond sont elles proposées tant au niveau national et régional. En effet, une lutte envisagée à un seul niveau est d'avance vouée à l'échec. C’est ainsi qu'il faut instaurer un véritable coopération judiciaire dans l'espace UEMOA-OHADA pour une lutte efficace contre la délinquance économique et financière dans cet espace.
Keywords: Acte uniforme; Afrique; Criminalité des affaires; Difficulties of unification or harmonization; Difficultés d'unification ou d'harmonisation; Droit (réforme); Délinquance économique et financière; Economic and financial criminality; Etat des lieux et perspectives; Lois uniformes; OHADA; UEMOA; Uniform Act; WAEMU

L'impact de la pression fiscale sur le comportement financier des dirigeants des PME au Cameroun - Djeudja, Rovier; Tedomzong, Aimerance Ladouce (Finance & Finance Internationale, 2017)
Dans cette recherche, nous postulons l’hypothèse de la manipulation des données comptables et de fraude fiscale comme stratégies de contournement adoptées par les PME dans un environnement fiscal répressif. Par rapport à l’environnement spécifique des PME camerounaises présenté, l’étude se situe quelques années après l’adoption d’un nouveau cadre comptable, en l’occurrence le système comptable OHADA. Deux conclusions importantes méritent d’être immédiatement présentées. En premier lieu et conformément aux prédictions de Watts et Zimmerman (1978-1990); de Allingham et Sandmo (1972), le nombre de contrôle ainsi que le nombre des impôts et taxes sont des facteurs susceptibles de favoriser l’instrumentalisation des données comptables et la fraude fiscale. En second lieu, le type d’activité exercé conditionne la capacité à manipuler les données et à frauder. This research is based on the main idea that manipulation of accounting data and fiscal fraud can be used as surviving strategy by small firms facing a repressive fiscal context. In relation with the particular case of Cameroon where empirical observations have been realised, two main conclusions need to be recall immediately. Firstly, as suggested by Watts and Zimmerman (1978-1990), Allingham and Sandmo (1972), the size can create incentive to manipulate accounting data and fraud. Secondly, the type of activity sometimes contributes to accounting data manipulation and fraud.
Keywords: Accounting data manipulation; Comportement financier des dirigeants; Financial attitude of managers; Fiscal evasion; Fraude fiscale; Instrumentalisation des données comptables; PME; Pression fiscale; SMEs; Small and medium sized enterprise; Tax pressure

L’obligation générale d’information du banquier à l’égard du client dans la zone U.E.M.O.A à la lumière du droit français - Dolo, Yamadou (Université Cheikh Anta Diop, 2017)
Keywords: Banquier; Client; Droit français; Information; UEMOA

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
URI: https://repository.up.ac.za/handle/2263/65659
Keywords: Consumer credit; Debt; Namibia

International Accounting Standards in Africa: Selective Recursivity for the 'Happy Few'? - Botzem, Sebastian; Quack, S; Zori, Solomon George (Global Policy, 2017)
This study explores recursivity in international accounting standard-setting, focusing on participation of actors from African countries. While the International Financial Reporting Standards (IFRS) Foundation bases its legitimacy claims as a global standard-setter on a combination of expertise and a formally transparent set of recursive procedures for consultation of stakeholders, empirical results show that participation in the latter is geographically very uneven. The article argues that conceptual mismatch between the standard-setter's objectives on the one hand and the socio-economic, cultural and political conditions in many African countries on the other leads to selective recursivity that is problematic for the former's legitimacy and effectiveness. These findings are of wider relevance for debates on global standard-setting and development.
Keywords: Accounting Standard; Africa; Economics of Culture; IFRS; International Accounting

La fiscalité des groupes de sociétés : étude comparée - Boumeddane, Zaza (Université d'Oran 2 Mohamed Ben Ahmed, 2017)
La fiscalité des groupes de sociétés intéresse le monde des affaires et tout contribuable. Le régime fiscal des sociétés est très incitatif à la création de groupes. Cela dit, c’est un régime fiscal récent en Algérie, son application nécessite des conditions. Il peut faire l’objet d’une révision. Le code fiscal algérien s’est ressourcé beaucoup du Code General des Impôts français. La détermination du résultat fiscal d’ensemble est restée une très grande problématique. Le résultat fiscal nécessite différents retraitements. Les transferts de bénéfices et le régime des restructurations donnent eux aussi droit à des impositions. Le régime de consolidation fiscale vise avant tout l’impôt sur les bénéfices des sociétés, cela dit les droits d’enregistrements, la taxe sur la valeur ajoutée, les cas de cessation du régime et les cas de sortie entrainent elles aussi des retraitements. Le groupe de sociétés peut être soumis à un contrôle fiscal en cas d’anomalies dans les déclarations fiscales. Company group’s taxation interests the business world and every taxpayer. Companies’ fiscal regime is very incentive to company creation. This type of regime is recent in Algeria. Its application regimes conditions, it is susceptible of revision. Algeria’s fiscal code has taken much from France’s general fiscal one. The determination of overall tax result is still a very large problematic. Tax result requires different adjustments. The transfer of profits and the regime of restructuring gives right to taxation. The tax consolidation regime aims primarily at taxing companies on their profits. Registration fees, the added tax value and cases of regime cessation, and cases of output causes retreatment. Company groups may be subject to tax control in case of anomalies in tax declaration.
Keywords: Account consolidation; Acte anormal de gestion; Consolidation des comptes; Consolidation fiscale; Division of taxation; Droit des sociétés commerciales; Fiscal consolidation; Fiscalité; Fiscalité des apports partiels d’actifs; Fiscalité des fusions; Fiscalité des scissions; Group of companies; Groupe de sociétés commerciales; Management act; Opérations de restructuration; Result owerall taw; Régime fiscal; Résultat fiscal d’ensemble; Tax; Tax asset partial contributions; Tax regime for restructuring commercial companies; Tax treatment of abnormal; Taxation of mergers; Taxe sur la valeur ajoutée; Transfer of profits to abroad; Transfert de bénéfices vers l’étranger; Value added tax

O sigilo bancário no direito guineense : uma perspetiva integrada de análise, compreensão e construção do regime jurídico quanto a sua extenção, limites e problemas atuais - Correia, Januário Pedro (Universidade de Lisboa, 2017)
A temática do sigilo bancário objeto da nossa dissertação, para além de atual e rica, comporta a enorme complexidade interdisciplinar e teleológica que, por si só, justifica e alimenta a interminável problemática em torno da fixação do seu regime e âmbito. A referida complexidade do sigilo bancário resulta, por um lado, do facto da configuração e regulamentação do seu regime se conformar aos limites e ao quadro constitucional e, por outro, ao cruzamento de vários princípios fundamentais: de ordem jurídica, que impõem a conjugação das necessidades práticas e interesses legítimos das instituições financeiras, na fidelização à clientela e captações de fundos; de âmbito estatal, na afirmação da política económica do Estado; dos clientes, no resguardo da sua vida económica privada ou do direito fundamental à reserva da intimidade. A requerida interdisciplinaridade reclamada e provada nesta tese, deixa patente a ideia de que a compreensão e a fixação do regime do sigilo bancário, quanto à sua extensão e limites, não se esgota no estrito âmbito do Direito Bancário, antes pressupõe vários outros ramos do Direito os quais regulam de forma direta ou indireta a matéria in casu, e com os quais apresenta a conexão, sobretudo a sua contextualização constitucional, da política económica e fiscal do Estado, traduzida, por exemplo, no suporte fundamental da definição do sistema de crédito, ao favorecimento do aforo e ao invés do entesouramento, a prevenção da fuga de capitais para o estrangeiro, promoção do investimento nacional e estrangeiro, luta contra a evasão fiscal, etc... Assim, ambos dependem em maior ou menor medida, da relevância que se dá ao regime do sigilo bancário. O estudo referente ao regime do sigilo bancário no direito guineense tem a virtualidade de mostrar e provar que a garantia da segurança e da certeza da observância não passa sempre pelas exigências normativas, mas também pela sua configuração e conformação da praxis social bem como das garantias adicionais por parte das outras normas jurídicas, quanto à imposição de deveres éticos e jurídicos, que contribuem de modo significativo para a definição do conteúdo e da fronteira do sigilo bancário em relação aos outros valores ligados à defesa do interesse do fisco, da luta contra evasão e fraude fiscais, branqueamento de capitais e terrorismo internacional. Na atualidade, a proteção do sigilo bancário deve partir da premissa de que existem outros valores com os quais ora se confluem ora se conflituam, no entanto, devendo-se encontrar um ponto de equilíbrio sem prejudicar o essencial destes valores, mediante uma ponderação séria e objetiva, designadamente da luta contra evasão fiscal, branqueamento de capital, terrorismo mundial e da administração da justiça criminal. Nesta ordem de ideias, na ordem jurídica guineense, o regime do sigilo bancário, quanto ao seu conteúdo e extensão, compagina-se com os tais valores, pelo que a compressão do seu conteúdo deve conformar-se com o princípio geral da “reserva do juiz”, contrariamente ao sistema da “reserva da administração” vigente em Portugal, em matéria da administração tributária. Neste sentido, podemos dizer que a solução atualmente vigente no domínio da União Europeia (UE) e no âmbito específico dos países membros da Organização para a Cooperação e Desenvolvimento Económico (OCDE) – pautada na lógica de inoponibilidade do sigilo bancário à administração tributária, no sentido de permitir o acesso direto à informação bancária como condição sine qua non da garantia da justiça e da distribuição equitativa da carga fiscal e luta contra evasão fiscal –, não deverá corresponder uma imposição ao nosso sistema, antes, deverá constituir, ab initio, um galgar de patamares exigentes e suficientemente definidos, de forma faseada, mediante controlos rígidos e segundo autorização do juiz – reserva do juiz. De igual modo, o grau de tal exigência da ponderação é muito mais elevado quando esteja em causa outros interesses ligados à investigação criminal e à prossecução do interesse público relevante ou injuntivo. Postulando, exclusivamente, do Juiz, a tarefa de preenchimento do conceito indeterminado consagrado ao abrigo do art. 135º, n.º 3, do CPP, correspondente à norma do art. 120º, n.º 3, do nosso CPP (ex vi arts.417º/3, al.c) do CPC, e do nosso 519º do CPC), conforme o princípio da proporcionalidade (vide os arts. 18º, da CRP, 30º, n.º 3, da CRGB), de forma a garantir a maior dignidade ao sigilo bancário, mediante a sua quebra na justa medida, em situação de extrema necessidade e na garantia da eficácia, da idoneidade e do efeito útil do interesse a prosseguir. Destarte, a salvaguarda do sigilo bancário, como regra de ouro, requer e exige de todos, um esforço adicional, para que o público e o cliente se sintam protegidos pelo sistema, caso contrário, a continuar a tendência e a postura atual pouco favorável ao sigilo bancário - sobretudo das nossas autoridades judiciária e tributária, que por tudo ou nada recorrem à quebra do sigilo bancário e assim encarando as instituições bancárias como se de agências de informações se tratassem ou como prestadores dos serviços dos tribunais e da administração tributária -, obviamente que os bancos seriam forçados a fechar as suas portas e o setor bancário condenado a desaparecer, pois ninguém confiaria os seus haveres aos bancos. Portanto, a sobrevivência do direito e da nossa ciência jurídica, concebida para facilitar a nossa sã convivência social, depende e exige respeito de cada um e de todos, v.g, aos cultores de direito, magistrados, legisladores, governantes, políticos, empresários, e até a um simples cidadão. Assim sendo, o direito ao sigilo bancário não foge à regra, de cuja efetiva tutela requer a sua transposição do plano jus positivo e constitucional e prático para uma vertente social, a qual, a consciencialização da sociedade em geral sobre a sua necessidade e a sua justificação, revela-se fundamental, mais que a enfática proliferação de normas consagradoras do seu conteúdo positivo ou negativo.
Keywords: Bank secrecy; Guinée-Bissau; Secret bancaire

L'apport du contrôle interne et d'audit interne à la bonne gouvernance des entreprises : une étude quantitative sur les entreprises marocaines - El Idrissi, Taoufik (International Review of Economics, Management and Law Research, 2017)
La gouvernance d’entreprise, est apparue comme le sujet qui a soulevé le plus de débats en matière de management au cours de ces dix dernières années, dans le monde des affaires, politique et académique. Sans aucun doute, une bonne gouvernance d’entreprise, est un levier indispensable au développement de la nation.De nombreux efforts sont à noter, visant à encourager et à inciter les nationaux à développer la culture de la gouvernance. Très clairement, cette communication s'inscrit dans cette vision de contribuer à l'amélioration de l'efficacité du système de contrôle et de développement de la culture de la gouvernance tout en mettant en avant un cadre théorique expliquant la contribution du contrôle interne et d’audit à la bonne gouvernance d’entreprise.Les résultats ont permis de tirer deux grandes conclusions. Premièrement, l’impact toujours aussi conséquent du contrôle interne et d’audit sur la gouvernance d’entreprise.Deuxièmement, cette recherche a pu avoir porté un éclairage assez important sur un autre type de mécanismes assez pesant sur le comportement des dirigeants notamment en matière d’organisation et de clarification des responsabilités. Corporate governance has emerged as the subject that created the most debate in management over the last decade in the business, political and academic world. Undoubtedly, good corporate governance is an essential lever to the development of the nation. Many efforts are noteworthy, to encourage and stimulate the national economic agents to develop the culture of governance. Clearly, this communication is part of this vision to contribute to improving the effectiveness of the control system and development of the culture of governance while highlighting a theoretical framework explaining the contribution of internal control and audit to good corporate governance. The results yielded two main conclusions. First, the impact still as a result of internal control and audit of corporate governance. Second, this research may have brought a sizable lighting on another type of mechanisms quite heavy on the behavior of such leaders in organizing and clarifying responsibilities.
Keywords: Agency theory; Asymétrie d’information; Audit; Contrôle interne; Corporate governance; Gouvernance d'entreprise; Information asymmetry; Internal audit; Internal control; Maroc; Morocco; Théorie de l’agence

An appraisal of selected tax-enforcement powers of the South African revenue service in the South African constitutional context - Fritz, Carika (University of Pretoria, 2017)
There is tension between the South African Revenue Service’s duty to collect taxes on the one hand, and its duty to respect taxpayers’ rights on the other. An environment where there is clearly respect for the rights of the taxpayer may indeed result in increased voluntary compliance. This thesis constitutes a comparative appraisal of whether the following enforcement powers of the South African Revenue Service (“SARS”) in the South African constitutional context, namely (i) SARS’ power to conduct searches and seizures in order to verify compliance and investigate the commission of offences; (ii) the “pay now, argue later” rule; and (iii) the appointment of a third party on behalf of a taxpayer are in accordance with the Constitution of the Republic of South Africa, 1996 (“Constitution”). It is argued that these powers do not necessarily conform to the Constitution’s values and the fundamental rights contained in the Bill of Rights in Chapter 2 of the Constitution. To address the apparent shortcomings in the current dispensation, the thesis compares these enforcement powers of SARS with similar powers afforded to the revenue authorities of Canada, Australia, New Zealand and Nigeria. Important conclusions are drawn from this comparative review and a number of recommendations for law reform are proposed which, if implemented, would align these enforcement powers with the provisions of the Constitution. The recommendations entail, inter alia, that the seizure component of a search and seizure process should be treated separately, that half of the payment obligation should be suspended until the dispute is heard by an impartial forum, and that an objective measure must be in place to ensure that a taxpayer is able to afford basic necessities when a third party appointment is made.
URI: https://repository.up.ac.za/handle/2263/62233
Keywords: Recouvrement fiscal; South Africa; Tax-enforcement power

Örtülü kazanç aktarımı - Günay, Ece Deniz (Galatasaray Üniversitesi, 2017)
Sermaye Piyasası Kanunu'nun amacı, sermaye piyasasının işleyişinin güvenli bir biçimde sağlanmasına ve yatırımcıların hak ve menfaatlerinin korunmasıdır. Bu amaçla yatırımcıların(halka açık anonim ortaklık pay senedi sahiplerinin); yatırımlarını gerçekleştirirken kararlarını doğru bilgilere dayanarak vermelerini sağlamak, şirketin kontrolüne sahip olan şahısların kişisel menfaatlerinden bağımsız olarak sadece şirketin menfaatleri doğrultusunda hareket etmelerini temin etmek üzere SerPK kendi içinde düzenlemeler barındırmaktadır. Bunlardan biri de SerPK madde 21 hükmüdür ve SerPK'nın amaçları doğrultusunda bir özel hüküm niteliği taşımaktadır. Söz konusu hükmün ratio legis'inin, halka açık anonim ortaklığın; ilişkili kişiler ile yapılan işlerde emsallere, piyasa teamüllerine uygun, ticari hayatın basiret ve dürüstlük ilkelerine uygun işlemler gerçekleştirmesini sağlamak suretiyle, ortaklık pay sahiplerinin menfaatlerinin korunması olduğu anlaşılmaktadır. SerPK madde 21'de sayılan yapılan işlem sonucu; halka açık ortaklığın, kolektif yatırım kuruluşunun, bunların iştirak ve bağlı ortaklıklarının; kârlarını azaltmak, malvarlıklarını azaltmak, kârlarının artmasını engellemek, malvarlıklarının artmasını engellemek, kârlarını korumak veya artırmak için yapmaları beklenen faaliyetleri yapmamak, malvarlıklarını korumak veya artırmak için yapmaları beklenen faaliyetleri yapmamak suretiyle ilişkili oldukları kişilerin kârlarının ya da malvarlıklarının artmasını sağlamak şeklinde aktif veya pasif davranışlarla kazanç aktarımında bulunmaları yasaklanmıştır. Konunun vergi hukukunda, Kurumlar Vergisi Kanunu m. 13'te transfer fiyatlandırması yoluyla örtülü kazanç dağıtımı adıyla düzenlenmekte olduğu görülmektedir. Şüphesiz vergi hukukunda gözetilen amaçlarla sermaye piyasası hukukunun izlediği amaçlar arasındaki farklılık, maddi unsurları benzeyen bu iki düzenlemeyi birbirinden ayırmaktadır. Konunun vergi hukuku ve maliye boyutu bağlamında eserler mevcuttur. Buna mukabil bu tez ile SerPK düzenlemesinin ardından konunun özel hukuktaki yeri ve sonuçları ile spesifik olarak konunun Borçlar Hukuku, Ortaklıklar Hukuku ve Sermaye Piyasası Hukuku yönlerinden araştırılması hedeflenmektedir. [...] Related-party transactions include the routine forms of abusive insider behavior that have come to be dubbed tunneling in the economic literature a category that includes all forms of misappropriation of value by corporate insiders. Prohibited related party transactions are the ones which contain transfer prices that contradict the arm's length principle. SerPK article 21/4 say that parties which have received an income transfer are obliged to return the transferred amount with its legal interest within the period to be determined by the Board. Sweeping prohibitions of related-party transactions were once common in company law. Apart from bans on loans, prohibitions tend to focus on transactions between managers and third parties that are thought to divert the value of information that the law assigns, implicitly or otherwise, to the company or its shareholders. It is forbidden that publicly- held corporations and collective investment schemes and their subsidiaries and associates to transfer income to real persons or legal entities with whom they have a direct or indirect relationship in terms of management, audit or capital by decreasing their profits or their assets or by preventing the increase of their profits or their assets via performing transactions such as making contracts or commercial practices containing different prices, fees, costs or conditions producing a trading volume in violation of the conformity with market practices and comparability to similar transactions prudence and honesty principles of commercial life.
475523
Keywords: Borçlar hukuku; Camouflage of earning distribution; Camouflaged capital; Capital Market Law; Commercial law; Kar aktarımı; Law of obligations; Profit shifting; Sermaye Piyasası Kanunu; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku; Örtülü kazanç dağıtımı; Örtülü sermaye

Özel Hukuk sözleşmelerinin Vergi Hukukunda geçerliliği - Kurtulmaz, Nihan (Marmara Üniversitesi, 2017)
Vergi hukuku kurum ve işlemlerini iktisadi hayatın işleyişi üzerine kurmuştur. İktisadi hayat ise ticaret hukuku, borçlar hukuku ve medeni hukuk gibi özel hukuk kurallarının denetimindedir. Bu durumun doğal bir sonucu olarak da vergi hukuku vergiyi doğuran olayları tanımlarken özel hukukun kurum ve kavramlarından faydalanmaktadır. Hukuki işlemlerin en önemlilerinden biri olan özel hukuk sözleşmeleri de vergilendirmenin sebep unsurunu oluşturabilmektedir. Çalışmamızda vergi hukukunun özel hukuk ile ilişkisi açıklanmış ve özel hukuk sözleşmelerinin vergi hukukundaki geçerlilikleri literatürdeki farklı görüşlere, yargı kararlarına ve İdare'nin görüşlerine yer verilerek araştırılmıştır. Özel hukuk sözleşmeleri ile ortaya çıkartılabilen sayısız durumda her iki hukuk dalının aynı olaya farklı bakış açıları mükellefler ve İdare'nin sıklıkla karşı karşıya gelmesine sebep olmaktadır. Vergiyi doğuran olayın sözleşmelerle ortaya çıkması halinde adil bir vergilendirme bu sözleşmelerin hukuki nitelendirmelerinin doğru yapılmasıyla mümkün olmaktadır. Ayrıca vergi hukukunun özel hukuk kavramlarına atfettiği anlamlar verginin yasallığı ilkesi çerçevesinde kanunlarla şekillenmelidir. Anahtar Kelimeler : Vergi Hukuku, Özel Hukuk Sözleşmeleri, Verginin Yasallığı. Tax law establishes its institutes and procedures as based on the operation of the financial life. Financial life is under the control of the rules of the private laws such as trade law, obligations law and civil law. As a natural consequence of this, when tax law defines the events that give rise to tax, it also benefits from the institutions and concepts of the private law. Private law contracts, which are among the most important legal procedures, may also result in taxation. In our study, the relation of the tax law with private law is explained and the validity of the private law contracts in tax law is examined by inclusion of different opinions in the literature, judicial decisions and the opinions of the Administration. The different points of views of both branches of law about the same event in countless number of cases, which occur as a result of private law contracts, cause the tax payers come up against the Administration frequently. If the event giving rise to taxation is a result of the contracts, then a fair taxation is possible through correct legal identification of such contracts. Moreover, the meanings referred by the tax law to the private law concepts should be shaped by the laws within the frame of the principle of the legality of tax Keywords : Tax Law, Private Law Contracts, Legality of Tax
464385
Keywords: Compliance with laws; Contracts; Droit fiscal; Fiscal law; Geçerlik; Hukuka uygunluk; Kanunilik; Legality; Mali hukuk; Private law; Sözleşmeler; Tax law; Validity; Vergi hukuku; Özel hukuk

Three Essays in Bank Financial Reporting - Liu, Yi (McMaster University, 2017)
This thesis investigates three important issues on bank financial reporting quality: 1) the impact of banks’ retail versus wholesale funding structure on their earnings quality, 2) the implications of economic and monetary policy uncertainty for banks’ earnings opacity, and 3) the relationship between banks’ bad time history and accounting conservatism. In the first essay, we examine the implications of banks’ funding strategies for banks’ earnings quality. We find that banks’ greater reliance on retail deposits over wholesale funds is negatively and significantly associated with the magnitude of earnings management through discretionary loan loss provisions, the likelihood of meeting-or-beating earnings benchmark, and the extent of income smoothing through loan loss provisions. This finding is consistent with the arguments that retail deposits are relatively more stable and information-insensitive, represent a more conservative business model, and attract more intensive monitoring from the Federal Deposit Insurance Corporation (FDIC) than wholesale funds, thereby improving banks’ financial reporting quality. In the second essay, we investigate whether economic and monetary policy uncertainties affect banks’ earnings opacity. When economic and monetary policies are relatively uncertain, it is easier for bank managers to distort financial information, as unpredictable policy changes make assessing the existence and impact of hidden “adverse news” more difficult for investors and creditors. Policy uncertainty also increases the fluctuation in banks’ earnings and cash flows, providing additional incentives for bank managers to engage in earnings management. Our results show that uncertainty in economic and monetary policy is associated with greater magnitude of discretionary loan loss provisions, higher likelihood of just meeting-or-beating the prior year’s earnings, and lower levels of accounting conservatism, suggesting that economic and monetary policy uncertainties lead to higher banks’ earnings opacity. In the third essay, we examine the impact of banks’ bad times on the conservatism of accounting policy. Specifically, we investigate two types of bad times: banks’ own past experiences of undercapitalization and their experiences of witnessing the failures of other banks in state-wide and county-wide crises. We find that both types of banks’ bad times are positively related to timelier recognition of earnings decreases versus earnings increases in accounting income. We also find that following exposure to bad times, banks increase their allowance for loan losses. Collectively, our results suggest that bank-specific bad times and macro-level banking crises lead to greater bank accounting conservatism. These findings support the arguments that banks exposed to past crises overweight their bad time history, and become more cautious and pessimistic about their future earnings performance and loan quality.

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.

Non-discrimination in international economic law - Risvas, Michail (University of Oxford, 2017)
This thesis examines the jurisprudence of the World Trade Organization (WTO) Panels and Appellate Body (AB) and investment tribunals on non-discrimination clauses contained in the WTO agreements and investment agreements respectively. The thesis puts forward an alternative conceptual perspective through which the interpretation of non-discrimination provisions in international economic law could be analysed. It is argued that nondiscrimination obligations (as every legal rule to a greater or lesser extent) are inherently indeterminate. This is a fortiori the case in regard to non-discrimination provisions due to their link to the concept of equality. The concept of equality is open-ended and value-laden: its content depends on the prioritisation of different values. Thus, equality in the economic sphere can accommodate different conceptions which reflect different ideological approaches in relation to regulation, economic development and the proper role of the State in the economy. International courts and tribunals enjoy broad discretion in selecting which conception of equality to adopt when interpreting non-discrimination clauses. This indeterminacy is a positive characteristic of international economic regimes. Both the WTO and the investment arbitration regime are equipped with institutional characteristics which enable the contestation of different ideological approaches and promote pluralism. In the WTO context, this role is fulfilled by the institutional structure of the organization which facilitates the dialogue between the WTO members and the WTO Dispute Settlement System. In the realm of international investment arbitration, the mechanism of party-appointed arbitrators, despite its shortcomings which can be addressed, ensures value pluralism.
https://ora.ox.ac.uk/objects/uuid:23e7e195-c657-46d0-9a21-bde0c793dc45

Açık kambiyo senetleri - Tüzemen Ati̇k, Ebru (Selçuk Üniversitesi, 2017)
"Açık Kambiyo Senetleri" başlıklı bu çalışmada, 6102 sayılı Türk Ticaret Kanunu'nun 680. maddesinde yer alan düzenlemeden hareketle Türk hukukunda açık kambiyo senetleri; yani açık bono, açık poliçe ve açık çek ele alınmıştır. Açık kambiyo senetleri, senedi verenin, ileride unsurları tamamlanarak geçerli bir kambiyo senedi şeklinde ortaya çıkmak üzere, karşı tarafa bir doldurma yetkisi ile birlikte vermiş olduğu, imza dışındaki unsurlarının tamamı ya da bir kısmı boş bırakılmış olan, unsurları tam kambiyo senetlerinin ön aşaması niteliğindeki senetlerdir. Açık kambiyo senetlerinde imza sahibi, senedin anlaşmaya aykırı doldurulması rizikosunu üstlenmektedir. Bu nedenle ortaya çıkan hukuki görünüşe güvenerek senedi devralan kötüniyeti veya ağır kusuru bulunmayan hamil iktisabında korunur. TTK'nın 680. maddesinde açık kambiyo senetleri yalnız def'i yönünden ele alınmıştır. Oysa konuya ilişkin olarak üzerinde durulması meseleler bundan ibaret değildir. Bu nedenle üç ana bölümden oluşan bu çalışmanın birinci bölümünde açık kambiyo senetlerine ilişkin genel açıklamalara; ikinci bölümünde açık kambiyo senetlerinde doldurma hakkı, devri ve sona ermesine; üçüncü bölümünde ise açık kambiyo senetlerinin anlaşmaya aykırı doldurulmasının taraflar arası ilişkilerde ileri sürülmesi, ispatı ve cezai sonuçları konularına yer verilmiştir. In this study titled "The Blank Bills of Exchange", starting from Regulation in Article 680 of the Turkish Commercial Code no 6102, The Blank Bills of Exchanges; namely, blank bills, blank notes, and the blank cheques have been evaluated in Turkish law. The Blank Bills of Exchange are the preliminary notes of the full bill of exchange that the singer gave it to the opposing party with a filling entitlement to be revealed in the form of a valid bill of exchange in the future; all or some of the elements outside the signature are left blank. In the Blank Bills of Exchange, the owner of the signature undertakes the risk of filling the notes contrary to the agreement. For this reason, the person takes over the bill of exchange relying on the revealed legal appearance is protected as holder without bad faith or gross negligence. In the 680th article of the Turkish Commercial Code, the blank bills of exchange are dealt with only in terms of exceptions. However, this is not the only issue to focus on. For this reason, in the first part of this study, which consists of three main parts, general explanations about the Blank Bills of Exchange are given while the right to fill, turnover and termination in exchange notes are discussed in the second part. In the last chapter, the submission, prove and criminal consequences of the fulfilment of the Blank Bills of Exchange contrary to the agreement at the inter-party relations are introduced.
492164
Keywords: Bill of exchange; Bills; Exchange; Kambiyo; Kambiyo senetleri; Kanunlar 6102 sayılı; Laws 6102 numbered; Senetler; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Le partage en droit fiscal - Molinier, Juliette (Université de Bordeaux, 2016)
L’indivision prend fin par le partage. Le partage substitue des droits privatifs à une propriétécollective sur un bien ou une masse de biens qui est fractionnée.L’indivision est présentée traditionnellement comme un état éphémère, mauvais, auquel il fautmettre fin. Des règles juridiques spécifiques au partage ont alors été mises en place ; lafiscalité de l’enregistrement a assuré l’accompagnement de ces règles.Aujourd’hui le partage se conçoit en valeur. Les règles du partage ont donc évolué.Cette évolution n’est pas appréhendée par le droit fiscal. Le traitement des soultes, desindemnités de réduction ou de rapport est parfois contestable.En outre, l’administration fiscale maintient encore la distinction entre partage pur et simple etavec soulte, distinction qui n’emporte aucune conséquence en droit civil et qui ne se justifieplus aujourd’hui.Le partage a un effet déclaratif et rétroactif. Chacun des attributaires est réputé avoir été seulpropriétaire du bien mis dans son lot.Le régime des plus-values des particuliers s’est calqué sur cette analyse qui par voie deconséquences, fait fi du partage et des soultes ou indemnités qui sont versées par l’attributairedu bien. L’analyse juridique du partage ignore l’aspect économique du partage.Quant à la fiscalité professionnelle, les règles sont complexes et disparates, pasnécessairement fondées sur l’analyse juridique ; le traitement fiscal du partage est alorsd’autant plus compliqué.
Keywords: Actif net; Declarative effect; Droit de partage; Droit fiscal; Effet déclaratif; Indivision; Joint possession; Net-assets; Partage; Partage (droit); Plis-values professionnelles; Plus-values privées; Private capital gains; Rapport; Reduction; Report; Retroactivity; Right to share; Réduction; Rétroactivité; Sharing; Work-related capital gains

La taxation des étrangers non-résidents en France - Ravaz, Florian (Université de Toulon, 2016)
Les étrangers non-résidents représentent une catégorie juridique très particulière de contribuables. Deux conditions sont nécessairement réunies pour taxer ces opérateurs économiques : un critère de territorialité qui tient à la localisation de leur obligation fiscale, il s'agit du domicile fiscal ; et puis un critère de nationalité. La définition de ce contribuable est négative car il s'agit ainsi d'une personne qui n'a pas la nationalité française, et qui n'a pas son domicile fiscal en France. Le législateur ne fait que très rarement référence explicitement aux étrangers non-résidents dans le Code général des impôts, le principe étant l'assimilation avec les non-résidents français. Néanmoins, lorsqu'il y fait directement référence, c'est notamment pour le discriminer par rapport aux nationaux. Il en résulte une différence de traitement fiscal le plus souvent contraire aux normes communautaires et internationales lesquelles agissent efficacement contre toute dérive protectionniste du législateur français. En effet, le principe d'égalité et son corollaire le principe de non-discrimination constituent des principes fondamentaux du droit communautaire et international, lesquels se chargent de neutraliser les dispositifs fiscaux nationaux qui font application du critère de nationalité dans la taxation des étrangers non-résidents en France. En définitive, la rupture du principe d'assimilation envers les nationaux non-résidents crée des contentieux juridiques qui forcent l'Etat français à s'aligner sur la législation externe et qui tendent par conséquent à aboutir à la fin des discriminations. Non-resident aliens represent a very specific legal category of taxpayers. Two conditions are necessarily met in order to tax these economic operators : a territoriality criterion relating to the location of their tax liability, it is the fiscal domicile; and then one of nationality. The definition of taxpayer is negative, as a matter of fact, it is a person who does not have French nationality, and who does not have tax domicile in France. The French legislature makes explicit references to non-resident foreigners in the Tax Code, the principle being the assimilation with the French non-residents. However, when there is a direct reference, it is to discriminate against national. This results in a difference in tax treatment most often contrary to EU and international standards which effectively act against any protectionist drift of the French legislator. Indeed, the principle of equality and its corollary, the principle of non-discrimination are fundamental principles of EU and international law, which are responsible for neutralizing the national tax systems which apply the criterion of nationality in the taxation of non-resident aliens in France. At last, breaking the principle of assimilation to national non-residents creates legal disputes that force the French legislator to align with the external legislation and which therefore tend to lead to an end to discrimination.
Keywords: Aliens; Contentieux fiscal; Discrimination; Domicile fiscal; Droit fiscal; Egality; Egalité; Etrangers; Foreigners; France; Nationalité; Non-resident; Non-résidents; Tax law; Tax residence; Taxation; Territoriality; Territorialité de l'impôt

Les difficultés rencontrées par les PME lors de la mutation comptable PCGC/OHADA : étude exploratoire des PMEcongolaises - Diwavova, Justin Kamavuako; Mayimbi Ekuli Ngokana, Patrick (1ère Journée d'Etude Africaine en Comptabilité et Contrôle (JEACC), 2016)
Cette communication a pour objectif d'appréhender les difficultés rencontrées par les PME congolaises à l'aube de la mutation comptable PCGC/OHADA et les facteurs qui les causent. L'enquête par questionnaire mené auprès d'un échantillon 99 PME opérant dans la partie Ouest de la RD Congo a permis de mettre en évidence deux faits saillants suivants : (i) la mutation comptable PCGC/OHADA s'implémente avec difficulté en contexte des PME. Ces difficultés sont plus ressenties lors des travaux d'inventaire (application difficile de la convention de la prééminence de la réalité sur la forme), dans la tenue des livres comptables (tenue manuelle, traitement approximatif des opérations sur la TVA) ainsi que dans la confection de certains tableaux de synthèse (notamment le TAFIRE); (ii) les facteurs de contingence structurelle (la taille de l'entreprise et son organisation comptable) et les facteurs de contingence comportementale (les profils de dirigeants et de teneur de livres comptables) se révèlent significativement comme étant les causes de ces difficultés.
Keywords: Facteurs de contingence; Mutation comptable; OHADA; PCGC; PME

Le contrôle de la réglementation prudentielle de la microfinance : Cas de la CEMAC (Communauté économique et monétaire de l'Afrique centrale) - Elobo, Roger Claude (Université Paris Est, 2016)
La microfinance connaît un développement considérable dans le monde de longue date. Elle est restée insignifiante jusqu’aux années 1990 au sein des Etats membres de la Communauté Economiques et Monétaire de l'Afrique Centrale (CEMAC) avant de connaître, sous l’effet conjugué du rôle actif de la Banque mondiale dans la lutte contre la pauvreté, un contexte juridique mal codifié et des politiques économiques exclusives, son essor et une expansion rapide marquée par une certaine anarchie et beaucoup de faillites aux conséquences négatives sur les économies et le moral des populations pauvres clientes des institutions de microfinance (IMF).Conscients des enjeux politiques et incités par les experts de la Banque mondiale, les chefs d’Etats de la CEMAC ont recherché des solutions visant à réglementer ce secteur en confiant à la Commission bancaire de l'Afrique centrale (COBAC) la mission d’édifier un cadre réglementaire et d’en assurer la supervision.Malgré cette réglementation, le taux de défaillance des IMF demeure élevé ce qui laisse à penser qu’il existe de failles structurelles qui nuisent à l’applicabilité des textes et/ou à l’exercice d’une bonne supervision.A partir d’une étude empirique construite autour d’un échantillon d’organisations de microfinance, il est mis en évidence des défaillances dont l’analyse des caractéristiques permet de dégager des stratégies appropriées pour y remédier.L’étude écarte l’absence de patrimoine des clients des IMF comme facteur risque justifiant une réglementation prudentielle. Elle montre à cet effet que les IMF ont un fonctionnement adapté au contexte d’information imparfaite avec les prêts de groupe à responsabilité conjointe et les prêts individuels renouvelés. Par conséquent, elle incite à se concentrer sur l’objet même de la réglementation et les pratiques de sa supervision.Cette réglementation de la microfinance dans la CEMAC tend à se conformer aux standards prudentiels internationaux. Mais il s’avère qu’elle nécessite des corrections pour plus d’efficacité et d’efficience.
Keywords: Banking commission of central africa; CEMAC; Cobac; Collectivités territoriales; Commission Bancaire de l'Afrique Centrale; Communauté Economique et Monétaire de l'Afrique Centrale; Control of prudential rules; Economic and monetary community of central african states; Microfinance

La lutte contre le blanchiment d'argent dans la sous-région de l'Afrique centrale CEMAC: Analyse à la lumière des normes et standards européens et internationaux - Ngapa, Théophile (Université de Poitiers ; Université de Dschang, 2016)
Le blanchiment d'argent représente une réelle menace pour l'économie mondiale. Les États sont appelés à coordonner leurs efforts pour combattre efficacement ce fléau. C'est la raison pour laquelle les États de la Communauté économique et monétaire de l'Afrique centrale (CEMAC) se sont engagés dans cette lutte au début des années 2000. Ils ont adopté un cadre institutionnel et normatif anti-blanchiment qui a vocation à se hisser au niveau des standards européens et internationaux dans ce domaine. Les textes normatifs supranationaux adoptés comportent des incriminations et des sanctions pénales du blanchiment. Pourtant, l'analyse des textes organiques ne laisse percevoir aucune compétence pénale dévolue à la CEMAC ou à ses institutions et organes. Plus encore, le processus décisionnel conduisant à l'adoption de ces textes soulève des questions de légalité et de légitimité. Aussi, en recherchant la conformité de son dispositif anti-blanchiment aux normes et standards européens et internationaux, la CEMAC a perdu de vue ses propres réalités régionales de sorte qu'une domestication de l'approche de la lutte anti-blanchiment s'impose pour une meilleure efficacité.
Keywords: Blanchiment de capitaux; Blanchiment de l'argent; CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; Coopération internationale; Crime organisé; Criminalité organisée; Droit pénal communautaire; Entraide judiciaire internationale; Professionnels assujettis; Saisie et confiscation (droit pénal); Secteur informel; Souveraineté

Pour une réforme de la solidarité du dirigeant au passif fiscal - Grevet, Alexandre (Université Paris-Dauphine, 2016)
Le mécanisme de solidarité traverse le droit fiscal. D’essence civile, la solidarité est intimement liée aux moyens de recouvrement dont dispose l’administration. S’agissant du dirigeant de société, sa « responsabilité pécuniaire » ou « solidarité patrimoniale » est actuellement suspendue à la décision du juge. Or, deux textes prévoient la solidarité du dirigeant selon qu’il s’agisse du juge de la responsabilité (LPF, art. L. 267) ou du juge répressif (CGI, art. 1745). Si ces deux dispositions sont indépendantes l’une de l’autre au motif qu’elles n’ont ni la même cause, ni le même objet, ni le même demandeur, il y a lieu de s’interroger sur leur portée respective, souligner leurs écueils et présenter les voies d’une réforme de la solidarité du dirigeant au passif fiscal. Il s’agit à la fois à rendre davantage efficace l’action en recouvrement de l’administration et garantir les droits dont dispose le dirigeant. La prégnance de la situation actuelle impose le pragmatisme : recouvrer le passif fiscal formé essentiellement par la TVA et suspendre la solidarité à l’intentionnalité des manquements à l’origine du passif fiscal dès la procédure d’assiette.
Keywords: Administrateurs de sociétés; CGI; Civil court; Corporate manager; Debt; Dgfip; Dirigeant; Dispositions pénales; Droit fiscal; France. Direction générale des finances publiques; Fraude fiscale; Impôts; Impôts sur les sociétés; Joint liability; Juge; LPF; Majorations fiscales; Passif; Passif (comptabilité); Penal; Procédures fiscales; Pénal; Recouvrement de créances; Responsabilité; Responsabilité (droit); Réforme; Sociétés; Solidarité; Solidarité (droit); Tax; Tax code; Tax liabilities; Taxe sur la valeur ajoutée; Tva

Le contrôle bancaire au regard des enjeux actuels des activités des banques privées en RDC – Entre la protection des clients, l’encouragement et la promotion des banques et la sécurité de l’Etat - Nsambana Bonkako, Juslain (KAS African Law Study Library, 2016)
Keywords: Banque; Banque privée; Client (protection); Contrôle bancaire; Promotion; RDC; Sécurité

L'exploitant de banque et le droit au Tchad - Dingamgoto, Thomas (Université Toulouse 1 Capitole, 2016)
Les activités économiques à l’instar de toute œuvre humaine ont besoin d’une réglementation, a fortiori les entreprises qui jouent un rôle majeur et crucial dans la vie économique d’un pays, d’une région, d’un continent. En effet, les actionnaires ou associés de ces entreprises y tirent des dividendes, les employés des salaires, les prêteurs des intérêts sur les crédits consentis, l’Etat des impôts et la création des emplois. Cette réglementation peut couvrir divers domaines. Outre la règlementation générale, les sociétés ont besoin d’une réglementation propre à leurs activités. Comme toute entreprise, la banque elle aussi a besoin d’une réglementation. Celle-ci est générale et spécifique. Outre les avantages généraux et particuliers suscités que peut faire procurer une entreprise, la banque fait circuler de l’argent en mettant à la disposition des agents économiques des moyens de paiement, par les crédits qu’elle octroie. Elle participe à l’émission monétaire, considérée comme un privilège régalien. La réglementation couvre deux aspects. Elle est d’abord l’œuvre des autorités étatiques puis communautaires. A cet effet, deux textes seulement ont été depuis lors adoptés : le décret du 4 février 1965, un texte purement organisationnel et la loi du 19 mai 1995 relative au secret bancaire. Les institutions communautaires que sont la BEAC et la COBAC ont mis en place des organes et des normes lesquels ont presque supplanté ceux créés par les autorités nationales. Le second aspect de la réglementation concerne les autres règles juridiques applicables à toute entreprise fonctionnant dans une économie libérale. Mais celles-ci fragmentaires et parcellaires s’avèrent insuffisantes. En effet, selon le principe de la permanence législative, le Tchad a adopté lors de son accession à l’indépendance en 1960, la législation alors en vigueur en métropole. Mais l’incertitude demeure quant à l’application des normes car cette permanence législative se voit réduite par un autre principe, celui de la spécialité législative. L’OHADA qui prétendait lors de sa création en 1993 remédier au vide juridique en matière de droit des affaires dont le droit bancaire s’est désistée en 2010 au profit des institutions sous régionales. A défaut des normes adéquates, le banquier tchadien se sert des règles récentes issues des lois françaises à titre de « raison écrite », de droit comparé ou des usages. Ainsi, tant au niveau local, sous régional que régional, le vide juridique, prélude à l’insécurité judiciaire est patent. Cette insécurité judiciaire est encore aggravée par l’insuffisance des règles procédurales, la défaillance des institutions judiciaires, le foisonnement des justices parallèles et la persistance de la mauvaise gouvernance.
Keywords: Banques; Droit; Justice (administration); Organisation pour l'harmonisation en Afrique du droit des affaires; Politique et gouvernement; Tchad; État de droit économique

L'effet modérateur de l'intelligence émotionnelle dans la relation entre le niveau de divulgation de l'information comptable relative aux provisions dans le contexte IFRS et les jugements et décisions des directeurs de comptes - Lagrange, Bruce (Université du Québec à Montréal, 2016)
L'évolution de certains facteurs comme l'augmentation de l'incertitude et de l'instabilité dans les environnements financiers et d'affaires, combinée à un changement de normalisation comptable sans précédent au Canada, ont contribué à l'augmentation de plus en plus importante de la complexité du processus décisionnel des utilisateurs professionnels comme les directeurs de comptes (DC). Par conséquent, il apparait important d'examiner si des variables autres que celles déjà étudiées dans la littérature pourraient avoir une influence sur le processus décisionnel des DC. Cette étude est une recherche expérimentale qui, en premier lieu, montre la différence qu'a eue la constatation aux résultats d'une charge relative aux provisions par rapport à la divulgation par voie de note de la même information sur les jugements et décisions de DC, et en second lieu, innove en examinant la présence d'un effet modérateur d'une variable correspondant à une caractéristique personnelle des DC, l'I.E. Après avoir analysé les informations fournies, les participants ont indiqué leurs jugements et leurs décisions quant à quatre variables que sont : (1) la cote de risque globale de l'entreprise, (2) la cote de tendance globale de l'entreprise, (3) la décision d'octroi du prêt et (4) la décision sur le taux d'intérêt exigé. La variable indépendante manipulée correspond aux différents niveaux de divulgation de l'information relative aux provisions : (1) évaluation et présentation selon le chapitre 3290, impliquant l'évaluation de la provision selon le montant le plus probable et présentation regroupée au bilan; (2) évaluation et présentation selon l'IAS 37, impliquant l'évaluation de la provision selon le montant le plus probable et présentation séparée au bilan; (3) évaluation et présentation selon l'ES-IAS 37, impliquant l'évaluation de la provision selon la valeur actuelle attendue des différentes sorties de ressources possibles et présentation séparée au bilan. Le but de cette recherche étant d'examiner si l'I.E. des DC modère l'impact de la manipulation expérimentale du niveau de divulgation de l'information relative aux provisions sur leurs jugements et si elle modère l'impact de ces jugements sur leurs décisions, le niveau d'I.E. des DC a été considéré comme variable modératrice. Les résultats indiquent que les façons de divulguer l'information relative aux provisions affectent le jugement de la CT mais pas celui de la CR. Les DC établissent une CT plus optimiste lorsque les états financiers sont basés sur la norme IFRS proposée par l'exposé-sondage. Les résultats indiquent que la décision d'octroi du prêt est significativement influencée par le jugement de la CR, soit que le pourcentage de DC acceptant le prêt est plus important plus la CR est optimiste. Les résultats n'indiquent qu'un effet plutôt marginal du jugement de la CT sur cette décision. Les résultats indiquent que la décision relative au taux d'intérêt est significativement influencée par le jugement de la CR, confirmant l'hypothèse que plus la prime demandée pour l'établissement du taux d'intérêt est petite plus le jugement de la CR est optimiste. La décision sur le taux d'intérêt est également influencée significativement par le jugement de la CT, mais seulement lorsque l'on compare les deux positions extrêmes de ce jugement (positive vs négative). En ce qui a trait à l'effet modérateur anticipé de l'I.E., les résultats indiquent que les jugements de la CR et de la CT ne sont pas influencés par le niveau d'I.E. des DC. Aussi, l'impact du niveau de divulgation de l'information relative aux provisions sur les jugements de la CR et de la CT n'est pas influencé par le niveau d'I.E. des DC. En ce qui a trait à la relation entre les jugements de la CR et de la CT avec la décision d'octroi du prêt, les résultats indiquent que le niveau d'I.E. des DC ne contribue pas à expliquer cette décision. Aussi, l'impact des jugements de la CR et de la CT sur la décision d'octroi du prêt n'est pas influencé par le niveau d'I.E. des DC. Finalement, pour ce qui est de la relation entre les jugements de la CR et de la CT avec la décision sur le taux d'intérêt, les résultats indiquent que la décision sur le taux n'est pas influencée par le niveau d'I.E. des DC. De plus, l'impact des jugements de la CR et de la CT sur la décision relative au taux d'intérêt n'est pas influencé par le niveau d'I.E. des DC.
Keywords: Banquier; Comptabilité; Disclosure; Divulgation; IAS 37; IFRS; Information comptable; Intelligence émotionnelle; Processus décisionnel; Provision comptable

Tax Mobilization in Sub-Saharan Africa: The Impact of Tax and Business Law Reforms - Bertinelli, Luisito; Bourgain, Arnaud (Economics Bulletin, 2016)
This paper contributes to measuring the influence of business (and tax) law reforms on sub-Saharan African countries tax mobilization ability. Relying on a new business law reform indicator, our results validate the significant impact of corporate law modernization on governmental revenue, and unearth a complementary effect between business and tax law reforms.

Analyse des causes des impayés dans le processus d'octroi de crédit dans les institutions de microfinance au Cameroun : cas de la Bourse d'Epargne et de Crédit (BEC) - Voukeng, Ghislain-Blaise (Université de Liège, 2016)
Microfinance institutions are specialized in the financing of economic activities of small sizes. They have a social role to target many excluded from the traditional financial system, including poor households, sole proprietorships, small and medium enterprises and mutual aid associations by offering to them suitable financial services (Kobou et al. 2009). In doing so, they are perceived by the vast majority of public opinion internationally as a useful lever for poverty reduction. They must nevertheless obtain sufficient economic and financial results to ensure their viability and sustainability. But in recent decades, there is a certain fragility of MFIs with cases of cascading bankruptcy in Cameroon, where one of the major causes of this bankruptcy remains the unpaid. This study examines the causes of the unpaid loan in the microcredit process in second category of microfinance institutions in Cameroon through the specific case of the "Bourse d’Epargne et de Credit" (BEC). To do this, a multi-variables analysis based on logistic regression method was performed on 195 individuals who have benefited the credit based on six factors, including the sex of the applicant (male or female), the socio professional category of applicant (trader, employee, and very small business-man), the credit period, the number of times an individual has benefited a credit, interest expenses borne by the applicant and the time to study and reply one credit demand. After analysis and discussion, it emerges that: the very small business-man, credit duration, the number of times an individual has benefited the loan; the interest charges borne by the customer are risk factors that increase the level of unpaid with a significant level of 5%. Other factors of the professional category (trader and employee); the credit applicant customer's gender (male or female) and the time to study and reply to a credit demand are factors that have low risk for unpaid. These factors are considered as protective factors of unpaid, also at the significant level of 5%. In addition, it also shows that certain portion of the target where credit is granted is unsuited to the context of the institution's objectives; there is a managerial problem in the structure in question.
Keywords: Credit; Microfinance institution; Risk; Sustainability; Unpaid loan

Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds

Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.
Number: 3

Le rôle de la supervision des banques islamistes, approche islamo-juridique - Madkhali, Aasem (Université de Nice Sophia-Antipolis, 2016)
Cette étude couvre les institutions financières islamiques en général, avec une attention particulière accordée aux banques islamiques. L’intérêt est suscité par la relation directe avec notre sujet traitant de la surveillance de conformité avec la charia, réglementaire et légale, des banques islamiques. Les institutions financières et banques islamiques proposent divers produits de financement et développent plusieurs produits classiques en les adaptant aux principes de la finance islamique, dont l’absence de l’usure (interdiction du riba). Par ailleurs, nous notons que d’une part, certaines institutions financières et banques islamiques commencent à détourner à leur avantage les principes et les règles de base qui ont justifié l’existence même de la finance islamique en tant que substitut à la banque classique, et que d’autre part, même quand lesdites institutions se dotent d’instance de surveillance, leurs prérogatives se limitent à conseiller sans intervention pour réparer les défaillances et sans que leurs décisions et recommandations n’aient de force obligatoire. Ces constats nous amènent plus loin dans notre analyse, et nous poussent à nous interroger sur le fait d’assumer les implications de la responsabilité civile sous ses deux formes ; contractuelle et délictuelle ainsi que les implications de la responsabilité pénale pour les membres de ces instances. Le rôle de ces organes peut être plus effectif et plus efficace, comme nous le montrerons grâce à une approche réglementaire légale des activités et travaux des instances de surveillance de la charia. De ce fait, le sujet de la thèse implique une comparaison et un parallélisme entre les activités bancaires islamiques et la surveillance réglementaire du point de vue de la loi islamique charaique et la surveillance réglementaire des activités bancaires islamiques d’un point de vue légal.
Keywords: Aspect religieux; Banque (réglementation); Droit bancaire islamique; Droit islamique; Finance islamique; Islam; Organes de supervision charaïque

La contribution du droit à l'accès au financement du secteur privé en Afrique de l'Ouest : le cas des pays de l'UEMOA - Tamboura, Ousseni (Université Cheikh Anta Diop, 2016)

Les difficultés de normalisation comptable dans l'espace OHADA - Bampoky, Boniface (Accountability, Responsabilités et Comptabilités, 2016)
A comprehensive history of African, Malagasy, Mauritian and from the Comoros accounting standards, has not yet been established to allow to make a summary of all the past and current difficulties arising from it and to propose the conditions for a suitable accounting standard normalization which backs up the development of the OHADA members states. Following a chronology which sums up the major historical facts based on the lack of accounting doctrine coming from the OHADA ground realities, the competent authorities are widely invited to give their opinions about the matter. History, as another research method in accounting and control, is concerned.
Keywords: Accounting doctrine; Accounting plan; Accounting standards; Doctrine comptable; Norme comptable; Plan comptable; SYSCOA; SYSCOHADA

De la pertinence informationnelle des chiffres comptables publiés par les sociétés cotées sur les Bourses d'Afrique de l'Ouest (B.R.V.M et Ghana Stock Exchange) - Casta, Jean-François; Mbengue, Alioune Badara (Accountability, Responsabilités et Comptabilités, 2016)
This paper examines the value relevance of accounting numbers published by listed companies on the markets BRVM (SYSCOHADA) and the GSE (IFRS). This study is part of the problem of the quality of accounting in emerging markets and of the current debate on the adoption of IFRS in the OHADA space. Through the methodology of the studies of associations, the results show: (1) The model (linear/non-linear) the most adequate for to write the relationship between accounting numbers and stock performance according to the indicator used; (2) The accounting earnings is more relevant on the BRVM by report to the GSE. And, the book value of equity is more informative on the GSE; (3) the effect of the presence of auditor(s) external(s) Big is not significant on this relationship.
Keywords: BRVM; GSE; IFRS; Référentiel SYSCOHADA; SYSCOHADA; Value-Relevance

Les instruments de la convergence des politiques budgétaires dans la zone UEMOA - Sawadogo, Elvis Flavien (Université de Bordeaux, 2016)
Les études juridiques portant sur les Finances publiques africaines n’abordent que très rarement les questions depolitiques budgétaires. Le caractère économique de la matière n’y est sans doute pas étranger. Or, la constitution d’espacesd’intégration économique entre Etats, partageant une même monnaie, conduit le droit, notamment communautaire à s’emparerdes questions de politiques budgétaires. Tout laxisme budgétaire de la part d’un Etat, se répercute sur les autres Etats membreset sur la stabilité de l’Union monétaire. Le renforcement de l’intégration économique, en Afrique de l’ouest, avec le TraitéUEMOA de 1994, a ainsi été accompagné de la mise en place d’un dispositif de convergence des politiques budgétaires desEtats membres. Celui-ci consiste, à travers un cadre institutionnel communautaire, à surveiller le respect par les Etats, decertains critères essentiellement budgétaires. La convergence des politiques budgétaires renvoie donc à la discipline budgétairecommune que devront respecter les Etats membres de la zone UEMOA. L’instauration d’un tel dispositif, aboutitnécessairement sur le plan normatif, à la transformation du droit public financier des Etats. Le respect de la discipline budgétairecommunautaire passe par une autodiscipline que les Etats doivent s’imposer dans la gestion de leur Finances publiques. Cenouveau pouvoir communautaire influence donc les Finances nationales au travers de leur contenu, choix de politiquespubliques comme de techniques de gestion. L’objectif de cette étude est de s’intéresser à l’un des facteurs déterminants destransformations des systèmes nationaux de gestion des Finances publiques dans les Etats membres de la zone UEMOA. Legal studies on African Public Finance rarely address fiscal policy issues. The economic nature of this subject isprobably the reason. Yet the creation of economic integration space between states sharing the same currency led the law,including community law, to take a firm hold on fiscal policy issues. Any fiscal laxity from a state has repercussions on theothers and the stability of the monetary Union. The strengthening of economic integration, in west Africa, with the WAEMUTreaty of 1994 has been accompanied by the setting up of a converging measures of budgetary policies of states members. This consists in monitoring, through a community institutional framework, compliance by states with some criteria, mainlybudgetary. The convergence of budgetary policies thus refers to common budgetary discipline to be observed by the statesmembers of the WAEMU area. The establishment of such measures necessarily ends at the normative level by thetransformation of public finance law of states. The compliance with community budget discipline goes through self-discipline that states must self-impose in the management of their public finances. This new community power has an effect on national finance through their content, their public policy choices and management techniques. The aim of this study is to take an interest in one of the determining transformations factors of national public finance management systems in the states members of the WAEMU area.
Keywords: Afrique occidentale; Ajustement structurel; Budgetary discipline; Budgetary law; Discipline budgétaire; Droit budgétaire; Droit de la comptabilité publique; Fiscal policies; Fiscal sovereignty; Monetary Union; Politique des dépenses publiques; Politiques budgétaires; Public accounting; Souveraineté budgétaire; Structural adjustment; UEMOA; Union monétaire; Union économique et monétaire Ouest africaine; WAEMU

L'harmonisation des législations de l'insolvabilité bancaire : utopie ou nécessité ? - Zhou, Yuanzhi (Université Paris 1, 2016)
Les risques systémiques des défaillances financières des établissements bancaires bouleversent les limites de compétence des législations nationales. De très grandes disparités entre les systèmes sont de nature à perturber les marchés, nationaux et internationaux, en raison de la spécificité de l’activité bancaire qui est de servir l’intérêt général. Toutefois, les grands systèmes normatifs qu’ils soient chinois, européens ou des Etats-Unis, révèlent des convergences d’ensemble pour prévenir ou résoudre les risques de défaillance des établissements bancaires, au sein d’une « lex argentariae » d’un milieu professionnel homogène. Une analyse comparée de ces législations qui privilégient l’intervention d’autorités administratives montre clairement la prise en considération des nécessités économiques et financières, alors que le juge judiciaire même subsidiairement imposera des solutions ayant autorité erga omnes et conservera ses missions essentielles notamment de protection des droits et des libertés individuels. L’analogie des solutions pose alors une question essentielle, celle de la coordination internationale des interventions administratives et judiciaires, afin de surmonter l’utopie d’une législation mondiale unifiée. Ces réflexions sont confirmées par l'évolution de l'Union bancaire européenne et de l'activité des banques chinoises à l'international. The systemic risk of the financial failure of the banking institutions has overturned profoundly the limits of the competence of the national legislations. Though the banking activities have the characteristics that serve the general interest, the great disparity between those jurisdictions creates the instability of the national and international markets. However, the major jurisdictions whichever the Europe, the UnitedStates or the China, have revealed overall convergence in preventing or resolving the risk of the bank failure, in a “lex argentariae” of a group of professionals that are homogeneous. The comparative analysis of those legislations that prevails the intervention of the administrative authority has clearly indicated the economic and financial needs, while the judges on bench, though of being subsidiary, continue to impose the solutions that has the authority erga omnes, and maintain their core functions, particularly the protection of the individual rights and freedoms. In order to surmount the utopia of a unified international legislation, the analogy of the solution has raised another important question, which is, the global coordination of the administrative and judicial intervention. These thoughts are confirmed by the evolution of the European Banking Union and of the activities of Chinese banks abroad.
Keywords: Administrative authority; Autorités administratives; Bank; Banques; Chine; Collective procedure; Comparative law; Droit chinois; Droit économique; Economic law; Etablissement de crédit; Faillites bancaires; France; Insolvabilité; Insolvency; Législation comparée; Procédure collective; Union bancaire européenne; États-Unis; Études comparatives

Les systèmes financiers publics des Etats de l'UEMOA à l'épreuve de la nouvelle gouvernance financière publique - Batonon, Serge B. (Université Paris 1, 2016)
L'examen des systèmes financiers publics des États de l'UEMOA a permis de constater que ces systèmes ont évolué dans le contexte contemporain de la nouvelle gouvernance financière publique. Le souci de la transparence, de la sincérité, de la responsabilité et de l'efficacité, principes cardinaux de la nouvelle gouvernance financière publique, a permis aux États de l'UEMOA sous l'égide de la Commission communautaire de renouveler les bases normatives et institutionnelles de leurs systèmes financiers publics. Les nouvelles normes introduisent une gestion financière publique axée sur les résultats avec une plus grande responsabilisation des acteurs. Elles confortent la suprématie budgétaire du Ministre des finances tout en investissant la direction du budget d'un rôle d'avant-gardiste programmatique en matière budgétaire et le contrôle financier d'une fonction d'évaluation de la dépense publique. Elles ont mis en perspective l'action du Parlement et des juridictions des comptes des États qui doivent mettre la veille à l'efficacité de la dépense publique au cœur de leurs actions. La mise en œuvre des nouvelles normes financières publiques change l'architecture et la méthode d'élaboration du budget qui passe d'une approche de moyen à une approche de résultat. Un ensemble de technicité et de rigueur entour désormais l'élaboration du budget dont les documents de programmation et les mécanismes de conception requièrent plus d'exigences. Les mécanismes et outils de pilotage de la gestion financière des États ont également changé. L'introduction de la responsabilité managériale a rendu nécessaire la mise en œuvre des outils de pilotage empruntés au secteur privé. Mais l'analyse des réalités sociologiques et des capacités internes des États révèle que la corruption, la non application délibérée des textes et l'insuffisance qualitative et quantitative des ressources humaines, matérielles et informationnelles constituent un blocage au bon fonctionnement des systèmes financiers publics. De même, au lieu d'être du "sur mesure" les nouvelles normes paraissent encore être du ''prêt à porter'' et ne tiennent pas toujours compte des réalités sociologiques des États. C'est pourquoi, la présente thèse propose de passer de l'imitation à l'innovation institutionnelle. Elle fait de la consolidation endogène des systèmes financiers publics une condition de réussite qui passe, entre autres, par l'instauration dans les États de la bisannualité budgétaire ; des profils des députés, du comité ordonnateur dans les ministères, de la responsabilisation solidaire du comptable et de l'ordonnateur et de l'instauration d'une responsabilité morale à travers l'implication de la chefferie traditionnelle et des confessions religieuses à la discipline financière.
Keywords: Afrique occidentale; Communauté économique des États de l'Afrique de l'Ouest; Finances publiques; Gouvernance financière publique; Nouvelles normes financières; Politique économique; Public financial governance; Public financial systems; Systèmes financiers publics; UEMOA; Union économique et monétaire Ouest africaine; WAEMU

Reflections on the Nexus Between Public Procurement Reforms and Economic Development in Nigeria - Okolie, Aloysius-Michaels; Nnamani, Kelechi (African Journal of Politics and Administrative Studies, 2016)
Corruption has widely been recognized as one of the impediments to the socio-economic cum political development of Nigeria. By 2000, it was observed that the conduct of government business in Nigeria had become difficult and expensive due to pervasive corruption, particularly procurement fraud. Although procurement fraud is one of the most common avenues of corruption in most countries, its incidence in Nigeria by 2000 was particularly widespread. To reverse this ugly trend, the Nigerian government initiated the public procurement reforms with a view that a corrupt-free procurement process will among other things, promote economic development in the country. Consequent upon the reform, the Public Procurement Act was enacted while the Bureau of Public Procurement was established to ensure due process, accountability and transparency in the award of government contract. In this light, this study evaluated the impact of the public procurement reforms on the economic development of Nigeria. We relied on documentary method of data collection and content analysis of data. Meanwhile, employing the basic propositions emanating from the Marxist theory of the Post-Colonial State, this study noted that the nature and character of Nigerian state undermined the procurement reform from achieving its expected goals. We however, recommended for the removal of the immunity in the constitution and strengthening of the anti-graft agencies in Nigeria.
Keywords: Corruption; Economic Development; Public Procurement; Reforms; Transparency

The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

Los paraísos fiscales como herramienta de planificación tributaria - Picón Gonzales, Jorge Luis (Universidad de Sevilla, 2016)
Los paraísos fiscales son territorios que se caracterizan por tener una baja o nula imposición a determinados vehículos para canalizar inversiones, tener una atractiva legislación comercial y financiera, así como otorgar una confidencialidad a los inversionistas. Sin embargo, legislaciones como la peruana y la española, regulan diversos aspectos de las inversiones realizadas a través de estos territorios o de las operaciones que la empresas locales realizan con residentes de dichos territorios; es decir, desarrollan normas defensivas “anti paraíso” para evitar perjudicar su recaudación tributaria ante el uso de dicho vehículos. Estas normas parten por la difícil tarea de definir qué países o territorios son considerados paraísos fiscales para esta legislación, lo que en sí mismo es una labor compleja por la multiplicidad de criterios utilizados para tal fin, como el uso de tasas referenciales o listados. Incluso en el caso de listados que enumeran las jurisdicciones que se considerarán paraísos fiscales, encontramos variaciones ya que las cifras varían en cada ordenamiento. Así, la legislación peruana sólo identifica 43 paraísos fiscale y la legislación española 33. Una vez que la legislación pasa por la tarea de identificarlos, la segunda etapa consiste en la regulación de normas que previenen los principales usos de los paraísos fiscales: a) Domicilios de conveniencia, b) Sociedades Instrumentales, c) Sociedades Base y las d) Sociedades de servicios. Los paraísos fiscales tienen sus antecedentes más próximos en la segunda mitad del siglo XX. Su notoriedad y crecimiento obedece al desarrollo industrial y económico que se producen después de la Segunda Guerra Mundial así como al proceso de independización de colonias que se encontraban como nuevos Estados en la búsqueda de la atracción de capital extranjero. Actualmente a ello se le suma, entre otros aspectos, la globalización que ubica a los paraísos fiscales en una sociedad de la tecnología e información. Así, en un contexto cada vez más globalizado, los territorios de baja o nula imposición se convierten en una alternativa para optimizar los flujos de la empresa, no sólo por los beneficios fiscales que otorga a la inversión extranjera, sino además, porque ofrecen facilidades financieros, económicas y practicidad en las operaciones. Asimismo, ante estas alternativas se produce también el endurecimiento de las normas frente a las operaciones con paraísos fiscales por lo que se hace imperioso tener claras las características, ventajas y desventajas de este instrumento de planificación tributaria. Bajo la premisa propuesta se hace necesario identificar, las contingencias que podrían derivarse de su utilización e implementación, considerando la creciente regulación anti-paraíso. A través de esta investigación, analizaremos la figura de los paraísos fiscales como una herramienta legal en el Planeamiento Tributario Internacional, cuya utilización dependerá de los inversionistas que estructuren un correcto planeamiento a través de la utilización de estos territorios, la cual es una actividad lícita si se cumplen con los requisitos y condiciones establecidas para su constitución y operatividad. El Planeamiento Tributario, al constituir una estrategia para aminorar la carga tributaria, puede contar con la utilización de estos territorios, asumiendo las consecuencias legales que imponga el país de residencia, ponderando estas restricciones con los beneficios que se obtendrán por invertir en países con una imposición muy baja. En ese contexto, con la elaboración de esta tesis se busca graficar las características de los paraísos fiscales, los principales mecanismos de utilización de estos; así como las medidas anti – paraíso fiscal; igualmente consideramos relevante indicar la proyección del uso de paraísos fiscales de Centroamérica y El Caribe; todo ello a fin de hacer más eficiente su utilización en el empresariado mediante proyectados de los beneficios y riesgos de su uso.
Keywords: Droit fiscal; Paradis fiscal

An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis

Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.

Contracts as regulation model : applications and legal implications in over-the-counter financial markets - Borowicz, Maciej Konrad (European University Institute, 2016)
We develop a conceptual model of contracts as regulatory instruments in over-the-counter (OTC) financial markets. The model is informed by the functional understanding of financial regulation as addressing problems of counterparty risk, liquidity, information and systemic risk and structural understanding of regulation as a process of standard-setting, monitoring and enforcement. The justification of conceptualization contracts as regulatory instruments is found in the nature of the political economy considerations that inform the definition of certain contracts used in OTC financial markets. While many scholars rely on conceptualization of the said contracts as boilerplate, we argue that there exist important qualitative differences between boilerplate and regulatory contracts, which we link to a broader spectrum of interests taken into account in their definition in the process of standard-setting. The model and its application to loan and derivatives markets help to highlight the impact of governance features of the organization developing the contract and the regulatory competition to which the organization is exposed on the scope of the regulatory function. We also use a number of indicators and attributions to examine the effectiveness of regulatory contracts. While the contractual model displays some weaknesses in terms of both standard-setting (conflicts of interest) and enforcement (reliance on delegation) compared to its better established counterpart – the organizational model associated with exchanges – the contractual model helps to account for important self-regulatory features of OTC financial markets and offers suggestions as to how the structure of OTC financial markets can be improved.
Accepted: 2016-06-21T15:10:25Z
Keywords: Derivative securities; Financial risk management; Over-the-counter markets

The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation

Le rôle de la micro finance dans la réduction de la pauvreté dans les pays en voie de développement : cas du Tchad - Levy, Nanque; Mahamat, Haroun Abba (Université Mouloud Mammeri, 2016)
La micro finance vise à permettre aux exclus de système bancaire d’accéder à des services financiers adaptés à leurs besoins, en premier lieu des microcrédits. Mais elle offre aussi la possibilité d’épargner des parts montants, et aussi des systèmes plus développées tels que les services de transferts de fonds et de proposer des instruments de paiement.
Keywords: Développement; Finance; Micro finance; Pauvreté; Produit financier

Les spécificités de la règlementation bancaire au regard du droit OHADA des sociétés commerciales - Zerbo épouse Hien, Mariame (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2016)

Le droit des marchés publics au Mali - Dicko, Amadou dit Abdehrimou (Université Cheikh Anta Diop, 2015)
Keywords: Commande publique; Droit des marchés publics; Mali

La responsabilité civile du banquier en droit malagasy - Chaminah, Loulla (Université Paris 1, 2015)
La banque centrale de Madagascar recense aujourd'hui douze banques territoriales, sept établissements financiers et vingt-neuf institutions de microfinance. Madagascar a en tout deux cent vingt agences de banques sur tout le territoire. C'est ainsi un secteur qui est en pleine expansion. L'étude se portera sur l'analyse des opérations que les établissements de crédit établis à Madagascar effectuent, tout en s'attachant à ce qui se pratique déjà dans d'autres pays comme la France et que Madagascar suivrait probablement. De cette manière on étudiera à la fois les cas effectifs, c'est-à-dire la pratique bancaire malgache et en même temps on essaiera d'anticiper certains cas jugés nécessaires. Tout cela en faisant une étude approfondie de la situation actuelle de Madagascar afin de relever la spécificité et les lacunes du droit bancaire malgache et subsidiairement on parviendra à montrer dans une étude comparative l'écart qui se trouve entre le droit bancaire malgache et le droit bancaire des pays évolués à l'instar de la France. En effet, il n'est pas aisé de décrire une règle juridique sans réfléchir ne serait-ce qu'accessoirement, en faveur faveur de telle ou telle solution meilleure inspirée des enseignements du droit comparé ou d'une prise en considération plus réaliste des besoins de la pratique. A l'inverse, il est très difficile d'argumenter en faveur de telle ou telle réforme législative sans d'abord réaliser un état des lieux aussi exact que possible. Par conséquence cette thèse fait état d'un tableau le plus exhaustif possible des cas de responsabilité civile de banquier susceptible d'intéresser le droit malagasy.
Keywords: Banques; Banquier; Droit malagasy; Madagascar; Responsabilité civile

Qualité perçue de l'information comptable et décisions des parties prenantes - Djongoué, Guy (Université de Bordeaux, 2015)
L’objectif de cette recherche était de comprendre la perception de l’utilité del’information comptable dans l’optique d’une prise de décision et de l’évaluation durisque de crédit aux entreprises. Le questionnement d’actualité centré sur la qualité del’information comptable dans le contexte des récents scandales financiers nous ainterpellé sur la nécessité de comprendre ce qu’il en est dans le contexte camerounais.Pour ce faire, nous avons conceptuellement proposé un modèle issu de la revue de lalittérature et ajusté par une recherche exploratoire (16 entretiens).Méthodologiquement, les observations issues de l’expérience (134 répondants) sontopérationnalisées à l’aide des analyses de corrélation et de régression. Les résultatsindiquent que pour la dimension prise de décision, le lien est, statistiquementsignificatif entre les qualités globales de l’information comptable, l’utilisation del’information comptable, la taille de l’entreprise et, son utilité perçue. Par contre, pourla dimension évaluation du risque de crédit, la variable utilisation de l’informationcomptable n’est pas statistiquement un élément significatif de son utilité perçue. Lesrésultats nous font observer que si l’information comptable est jugée utile, elle est plusestimée pour la dimension de la prise de décision que pour celle de l’évaluation durisque de crédit. Par ailleurs, il est apparu que c’est la grande entreprise qui possèdeune utilité perçue plus favorable en regard de ces deux dimensions. Objective of this research was to understand the perception of the usefulness ofaccounting information in the perspective of decision making and assessment of creditrisk for companies. Recently, related to some notorious financial scandals, the qualityof accounting information has been seriously questioned. This has challenged us toexamine what is going on in this respect in the Cameroonian context.376In order to do so, we have conceived a model starting from a literature survey andadjusted it on the basis of an exploratory research (16 interviews). Methodologically,the observations from the experiment (134 respondents) are operationalized usingcorrelation and regression analyzes. The results indicate that, in the decision makingprocess, the links between overall quality of accounting information, the use ofaccounting information, the company's size and the perceived usefulness isstatistically significant.However, for the assessment of credit risk, the use of accounting information is notstatistically significant as a variable factor of its perceived usefulness. We observe asresults that, if accounting information is considered useful, it is rather in terms ofdecision making in terms of the evaluation of credit risk. Furthermore, it was foundthat in big corporations business high quality accounting information is perceived asuseful in both dimensions.
Keywords: Accounting information; Bank; Banque; Comptabilité; Credit risk; Crédit; Decision making; Information comptable; Partie prenante; Perception-Qualité; Prise de décision; Quality perception; Risque de crédit; Shareholders

Les instruments de lutte contre le blanchiment d'argent en Algérie - Mehdi, Djazira (Université de Nice Sophia-Antipolis, 2015)
Le blanchiment de capitaux est actuellement le délit qui connaît la plus importante croissance. Par ailleurs, la lutte contre ce phénomène reste un thème actuel et global. Consciente du caractère essentiellement transfrontalier de ce fléau et ses conséquences néfastes qu’il présente particulièrement pour les pays en voie de développement dont les systèmes financiers sont réputés fragiles, l’Algérie a mis en place divers instruments afin de combattre le blanchiment d’argent. Outre sa participation aux instruments internationaux, elle a mis en place des moyens nationaux permettant de lutter contre cette forme de délinquance financière. Nous avons analysé ces instruments et les modifications récentes apportées en la matière par les autorités algériennes.
Keywords: Algérie; Blanchiment de l'argent; Criminalité des affaires; Délinquance financière; Infractions financières; Infractions économiques; Instruments; Money laundering

Le refus du banquier - Chossis, Jennifer (Université de Montpellier, 2015)
L'activité bancaire comporte nécessairement certains risques. Or, face au risque, le refus possède fondamentalement une vertu protectrice et est source de sécurité. Parce que le banquier est le premier à s’exposer aux risques, il semble naturel que la matière bancaire soit dominée par un principe de liberté, liberté de contracter, liberté d'entreprendre, liberté de prendre des risques et, partant, liberté de refuser. Toutefois, une propension du banquier à se surprotéger se révèlerait nocive pour le public, le refus étant naturellement source d’exclusion économique et sociale. En effet, il est impossible de nier le caractère indispensable des services bancaires pour tous les acteurs de la société. La liberté de refus du banquier doit donc être tempérée par la recherche d’un équilibre entre sa propre protection et la protection de sa clientèle réelle ou potentielle. De cette recherched’équilibre résultera alors une restriction certaine mais délimitée de sa liberté de refus de sorte qu'il sera, dans certaines hypothèses, débiteur d'un devoir de ne pas refuser. Dès lors, la liberté demeure le principe auquel il est dérogé par exception.Pour autant, le banquier n'est pas seul à prendre des risques. En effet, les contrats bancaires comportent des risques supportés par les cocontractants mais également par leurs créanciers, pourtant tiers aux contrats. C’est pourquoi, les cocontractants, souvent moins rompus que le banquier aux risques inhérents aux opérations de banque, et les tiers, ignorant généralement l’existence de ces risques, méritent d'être protégés. La recherche de sécurité pourrait alors prendre la forme d'une obligation au refus à la charge du banquier. Or, toute obligation au refus porte une atteinte évidente aux libertés du banquier et de ses cocontractants que seule la protection de l'intérêt général est véritablement en mesure de justifier. Toutefois, s’il existe, en droit positif, des hypothèses obligeant le banquier à refuser certaines opérations trop risquées, il semble qu’une obligation au refus en matière de crédit soit difficile voire impossible à dégager. Du reste, une telle obligation, pour morale qu’elle paraisse, ne serait pas souhaitable en ce qu’elle pourrait avoir pour conséquence de porter atteinte aux intérêts qu’elle prétendrait protéger.
Keywords: Banques; Banquiers; Droit bancaire; Gestion du risque; Liberté contractuelle; Obligations professionnelles; Refus de contracter; Responsabilité professionnelle; Risques bancaires

La réception par la jurisprudence de la législation sur le crédit à la consommation - Franc, Patricia (Université de Saint-Etienne, 2015)
Le consommateur, lorsqu’il souscrit un contrat de crédit pour les besoins de sa vie courante, achat d’une automobile par exemple, bénéficie d’un certain nombre de protections. Différentes sources du droit sont susceptibles d’être articulées : les mécanismes du droit commun des contrats présents dans le Code civil, mais aussi une législation spéciale, née de la loi dite SCRIVENER I du 10 janvier 1978, présente dans le Code de la consommation. Cette législation spéciale, bien que récente, a été modifiée à plusieurs reprises, la dernière modification d’importance étant la transposition en droit français de la directive européenne du 23 avril 2008 par la loi du 1er juillet 2010. Le droit du crédit à la consommation est un droit jeune, dense, foisonnant, ambitieux, qui revendique un haut degré de protection du consommateur et fait du formalisme son cheval de Troie. Mais c’est aussi un droit de passion, élaboré souvent dans l’urgence, sensible politiquement, médiatisé, objet de lobbies, parfois maladroitement rédigé ou transposé, approximatif, lacunaire. Au sein de la Cour de cassation, c’est à la Première Chambre civile qu’il appartient de connaître des questions en lien avec le droit de la consommation. Dès lors, comment la Première Chambre civile parvient-elle à manipuler ce droit spécial du crédit à la consommation ? Parvient-elle à en gommer les défauts, à en pallier les manques ? Comment articule-t-elle les protections en présence ? Doit-elle faire face à des résistances de la part des juridictions du fond ? Dans cette tâche unificatrice, le droit commun lui apporte-t-il un secours bienvenu ? Et la CJUE ? In fine, le consommateur emprunteur est-il protégé efficacement ?
Keywords: Code de la consommation; Consommateur (protection); Consumer credit; Consumer protection; Credit law; Crédit à la consommation; Droit commun; Loi Scrivener

La subsidiarité des conventions fiscales - Trindade Marinho, Anapaula (Université Paris 1, 2015)
L’Étude porte sur un principe prétorien érigé par le Conseil d’État au travers de ses décisions et des conclusions rendues sous ses décisions par les Rapporteurs Publics. Depuis 1975 le Conseil d’État exerce le contrôle de la compatibilité d'un acte d'imposition vis-à-vis de conventions fiscales contre la double imposition et l'évasion fiscale qui est fait sous l'égide du principe de subsidiarité. En vertu de ce principe, au préalable du contrôle de «conventionnalité» de l'acte d'imposition, les juridictions doivent impérativement exercer un contrôle de la légalité de l'acte d'imposition, en prenant appui sur les seules dispositions du droit d'origine purement nationale, c'est-à-dire, du droit dit « domestique». Ce principe, tout juste nommé comme tel par le Conseil d’État dans une décision rendue en 2014, a longtemps fait l'unanimité au sein de la doctrine. Le principe de subsidiarité serait un principe conforme au bon sens et à la logique. Nous tentons au cours de ce travail de démontrer que le principe de subsidiarité des conventions fiscales pose problème à la fois d'un point de vue, strictement théorique, et à la fois d'un point de vue pratique. D'un point de vue théorique d'abord, il sera démontré que le principe de subsidiarité des conventions fiscales est particulier, il ne correspond à aucune autre application juridique de la subsidiarité, la similitude n'est que enveloppe terminologique. La version fiscale soulève un véritable problème théorique et pratique que la thèse tente de démontrer.
Keywords: Conventions fiscales; Double imposition (traités); Droit fiscal (droit international); Praetorian principle; Principe de subsidiarité; Principe prétorien; Principle of subsidiarity; Subsidiarité; Tax treaties

Les compétences nationales en matière fiscale et la communautarisation des règles dans l'espace ouest-africain - Ouedraogo, Sylvain (Université de Bordeaux, 2015)
Les Etats d’Afrique de l’Ouest, après une expérience non réussie à travers la CEAO, sesont engagés dans un processus d’intégration, à l’image de l’Union européenne, avec lasignature du traité de l’UEMOA le 1er janvier 1994.Ce processus qui a pour objectif d’harmoniser les règles fiscales implique que désormaisdes compétences fiscales soient dévolues aux organes communautaires et remettent encause les compétences exclusives des Etats membres prônées par les constitutionsnationales en la matière. Ainsi donc, pour accompagner la politique monétaire commune etcelle commerciale, l’UEMOA s’est évertuée à encadrer les compétences fiscales des Etatsmembres en légiférant dans le domaine fiscal, tantôt en encadrant les pouvoirs des Etats,tantôt en confisquant entièrement ces pouvoirs.Cette étude se donne pour objectif de faire le bilan de l’intégration en Afrique de l’Ouesten faisant ressortir les forces et les faiblesses après une vingtaine d’années d’expérience del’intégration. West African states, after an unsuccessful experience through ECWA, engaged in aprocess of integration in the image of the European Union with the signing of the UEMOATreaty on 1st January 1994. This process, which aims to harmonize tax rules mean thatnow powers of taxation are assigned to Community institutions and challenge the exclusivecompetence of the Member States advocated by national constitutions in the matter.Therefore, to accompany the common monetary policy and the commercial, UEMOA hasstrived to frame the fiscal powers of the Member States through legislation in the tax area,sometimes bordering the powers of States, now fully taking these powers. After twentyyears of experience, the study's objective is to take stock of integration in West Africa,highlighting the strengths and weaknesses.
Keywords: Afrique occidentale; Assiette; Budget; Collection; Common market; Communautarisation; Communitarization; Compétence fiscale; Fraude fiscale; Harmonistation; Harmonization; Imposition; Impôt; Integration; Intégration; Intégration économique; Liquidation; Marché commun; Plate; Politique fiscale; Prélèvement; Recouvrement de créances; Recovery; Souveraineté étatique; Standardization; State sovereignty; Tax jurisdiction; Taxation; Uniformisation; Union; Union douanière; Union économique et monétaire Ouest africaine; Évasion fiscale

La sécurisation du marché des services de paiement - Diop, Mame Mariama (Université Lille 2, 2015)
La transposition de la directive relative aux services de paiement du 13 novembre 2007 en droit français est à l’origine de la création d’une nouvelle catégorie d’acteurs bancaires : l’établissement de paiement. La fourniture de services de paiement cesse ainsi d’être du domaine exclusif des établissements de crédit pour devenir l’activité principale des établissements de paiement. S’il est vrai que cette nouvelle répartition des activités bancaires ébranle le monopole bancaire, elle n’y met cependant pas fin. Pour une meilleure lisibilité et un contrôle plus efficace des acteurs, il est proposé une mutation du système bancaire grâce à d’une part une scission complète des activités bancaires, et d’autre part une indépendance des établissements de paiement face aux établissements de crédit. La sécurisation du marché des paiements dépend également de l’encadrement des opérations de paiement. La préservation de la confiance du consommateur est essentielle au bon fonctionnement du marché des services de paiement.
Keywords: Banque; Commissions interbancaires; Compte de paiement; Espace unique de paiement en euros; Mesures de sécurité; Monnaie électronique; Opération de paiement; Paiement; SEPA; Service de paiement; Établissement de crédit; Établissement de paiement

Aanspreeklikheid van maatskappy-ouditeure teenoor derdes op grond van wanvoorstelling in die finansiële state - Pretorius, Joseph Thomas (University of Johannesburg, 2015)
Keywords: Auditing; Auditors; Commissaires aux comptes; Etat financier; Fausse déclaration; Financial statements; Liability (Law); Malpractice; Negligence; Responsabilité; South Africa

Les obligations financières - Colin, Audrey (Université Sorbonne Paris Cité, 2015)
La notion d’ « obligation financière » est issue de la directive 2002/47/CE du Parlement européen et du Conseil du 6 juin 2002 concernant les contrats de garantie financière. Il s’agit de la directive Collateral. L’obligation financière est l’obligation garantie par un contrat de garantie financière. La transposition française est intervenue par voie d’ordonnance en 2005. Cette sûreté réelle conventionnelle qui garantit l’exécution des obligations financières bénéficie d’un régime spécial et dérogatoire. Cette garantie est spéciale parce qu’elle vise des personnes spécifiques, celles qui sont soumises à des obligations prudentielles, et des opérations spécifiques, les opérations financières. Cette garantie est dérogatoire, car son efficacité implique de lui conférer une immunité. En effet, la garantie des obligations financières ne saurait être remise en cause en raison de l’application des dispositions de droit des procédures civiles d’exécution et de droit des procédures collectives. En outre, le dispositif Collateral prévoit une règle de conflit de lois désignant la loi de l’État dans lequel est ouvert le compte au crédit duquel les titres financiers sont inscrits. L’étude de l’obligation garantie subit une double influence. La première est celle de la garantie puisque l’obligation financière a été conçue en contemplation de celle-ci. La seconde est celle de la logique collective de l’opération de marché. L’objectif du dispositif est d’assurer la stabilité du système financier, c’est-à-dire des entités qui le composent : les marchés, les intermédiaires et les infrastructures. The locution "financial obligations" is issued from the directive 2002/47/EC of the European Parliament and of the Council of 6 june 2002 on financial collateral arrangements. The financial obligation is the obligation which is secured by a financial collateral arrangement. The directive has been implemented in France in 2005. The financial collateral arrangment presents a special and derogatory legal system of financial collateral arrangements must be immune to all provisions which couldannhilate its efficiency. Indeed, the provisions of insolvency law and of civil enforcement procedures law, those that wouldinhibit the effective realisation of financial collateral or cast doubt on the valitdity of current techniques such as bilateral close out netting, do not apply to such arrangements. Besides, the directive contains a special conflict law rules. The law of the country where the financial collateral is located, that is to say the law of country in which the relevant account is maintained, is applicable. Thisstudy demonstrates that the financial obligations are impacted by two main influences : first, by this specialguarance, then, by the capital markets multilateral approach. The goal is to protect the performance of the financial obligations in order to protect all the financial system, by insuring its stability.
Issue: 2015USPCD044
Keywords: Code monétaire et financier; Directive 2002/47/CE; Directive 2002/47/EC; Financial guarantees; Financial markets; Garanties financières; Marchés financiers; Monetary and financial code

L’apport de l’audit opérationnel interne dans la réduction des abus de la rémunération des dirigeants : Etude exploratoire dans les sociétés par action en Algérie - Belhachemi, Amina (Université Abou Bekr Belkaid, 2015)
تواجه حوكمة الشركات عدة مخاطر بالأخص فيما يتعلق بمسألة تعويضات المديرين التنفيذيين، و التي تتمثل اساسا في النزاعات القائمة بين المساهمين و المديرين التي قد تهدد كل مستويات الاداء و جودتها. في هذا الصدد تأتي استراتيجية حوكمة الشركات لضمان التوازن بين صلاحيات المساهمين ومسؤوليات المديرين التنفيذيين من خلال تحسين سير مختلف آليات المراقبة و تعزيزها. في هذا السياق، يأتي هدف هذه الأطروحة المتجسد في التركيز على اظهار مدى نجاعة التدقيق التشغيلي فى حوكمة الشركات، من خلال التدقيق في الكيفية أو الطريقة المتبعة في تحقيق الأهداف المتعلقة بتعويضات المديرين و بالتالي الحد من التلاعب و السلوكيات المنحرفة التي تعمل على حساب غيرهم من اصحاب المصلحة عموما و المساهمين على وجه الخصوص في شركات المساهمة بالجزائر . La gouvernance d’entreprise a toujours été confrontée à des aléas multiples et divers et notamment celui de la problématique de la rémunération des cadres dirigeants. Ceci, étant, dans un sens, où le risque de conflit d’intérêts entre ces derniers et les actionnaires, qu’il soit potentiel ou réel, peut menacer d’une façon ou d’une autre les niveaux de performance attendus. Ainsi, une stratégie de gouvernance d’une société par action doit nécessairement promouvoir, entre autre, une politique des équilibres entre les pouvoirs des actionnaires et les responsabilités des cadres dirigeants, tout en faisant valoir un bon fonctionnement des différents mécanismes des contrôles nécessaires. A ce titre, notre travail de recherche s’est focalisé, justement, sur l’audit opérationnel que nous avons jugé comme étant l’un des principaux moyens de contrôle qui puisse, à la fois, stimuler la dynamique de l’effort de gestion des cadres dirigeants à travers un contrôle sur leurs rémunérations qui risquent d’être abusives et contribuer à assurer un climat des affaires positif pour les actionnaires dans les sociétés par action en Algérie.

Derivativos de crédito: aspectos jurídicos - Rodrigues, Rodrigo Alves (Universidade de São Paulo, 2015)
A presente tese objetiva estudar o Credit Default Swap (CDS) e o Total Return Swap (TRS), que são os derivativos de crédito cuja negociação é permitida no país. Analisaremos a utilização destes instrumentos financeiros no sistema bancário, seus efeitos deletérios no mercado financeiro, o modo como são regulados no direito brasileiro, bem como as recentes alterações legislativas nos Estados Unidos e União Europeia pós crise de 2008.
Keywords: Credit derivatives; Crédito; Derivativos (aspectos legais); Direito comercial; Financial markets; Mercado financeiro; Regulation

Finances publiques et gestion par la performance dans les pays membres de l'UEMOA : étude de cas du Sénégal - Ba, Boubacar Demba (Université de Bordeaux ; Université Cheikh Anta Diop, 2015)
A la suite de beaucoup d’autres pays, ceux de l’Union économique et monétaire ouest africaine (UEMOA) ont adopté le système de gestion par la performance des politiques publiques. Il s’agit d’un système global qui inclut, en phase d’élaboration des politiques publiques – déclinées en missions, programmes et actions -, de reconnaître la contrainte budgétaire qui s’impose partout, de définir le périmètre de ces politiques, d’en dégager les priorités et d’envisager leur exécution dans un cadre pluriannuel. En phase d’exécution, la gestion par la performance implique d’accorder plus de liberté aux gestionnaires, notamment dans l’utilisation des ressources tant humaines que matérielles. En contrepartie de cette liberté, se trouve la responsabilité des gestionnaires. En phase de contrôle enfin, la gestion par la performance suppose la modernisation des contrôles a posteriori traditionnels par leur inclusion dans les contrôles préventifs managériaux que sont le contrôle interne, le contrôle de gestion, l’audit. Elle suppose enfin un usage plus systématique de l’évaluation.
Cotutelle : Université de Bordeaux; Université Cheikh Anta Diop
Keywords: Accountability; Audit; Budgetary restriction; Contrainte budgétaire; Contrôles managériaux; Evaluation; Finances publiques; Freedom of management; Gestion par la performance; Internal control; Liberté de gestion; Management by performance; Mission; Pluriannualité; Politique publique – Sénégal; Priorities; Priorités; Program; Programme; Public policies framework; Périmètre des politiques publiques; Responsabilité; Sénégal; Union économique et monétaire Ouest africaine; Évaluation

La liberté contractuelle à l'épreuve du droit des marchés financiers - Bobillier, Charlie (Université Jean Moulin Lyon 3, 2015)
La liberté contractuelle est un principe fondateur du droit civil français, en vertu duquel chaque sujet de droit est libre, non seulement de décider de s’engager ou non, mais également de déterminer les conditions de son engagement contractuel et la personnalité de son cocontractant. Malgré ses apparentes particularités, dues à son objet, le droit des marchés financiers ne constitue pas une branche autonome du droit, de telle sorte que le droit civil a toute vocation à s’appliquer sur les marchés financiers. Pour autant, un rapide examen du droit des marchés financiers fait apparaître des atteintes à la liberté contractuelle, en premier lieu à la libre détermination du contenu du contrat. Ce constat est d’autant plus frappant lorsque l’on approfondit l’étude des marchés financiers, les offres publiques étant en effet l’occasion de multiples atteintes. Plus particulièrement, l’initiative contractuelle est lourdement affectée par les offres publiques obligatoires, qu’elles soient d’acquisition ou de retrait. Cette thèse a pour objet d’examiner ces diverses atteintes portées par le droit des marchés financiers à la liberté contractuelle afin d’en déterminer le fondement.
Keywords: Contratual freedom; Droit civil; Droit des affaires; Financial instruments; Financial markets; Instruments financiers; Liberté contractuelle; Mandatory buyout offer; Mandatory public bid; Marché financier; Marchés financiers; Offre publique d'acquisition; Offre publique de retrait

Empowerment et économie sociale et solidaire : étude de cas d'organisations féminines en Afrique de l'Ouest - Ben Lazrak, Asma (Université Grenoble Alpes, 2015)
L'objectif de ce travail est d'analyser les différentes formes de pratiques de l'économie sociale et solidaire qui permettent aux femmes africaines d'aller au delà de leur vulnérabilité. Ces activités génératrices de revenus entraînent à la fois une augmentation de l'empowerment individuel et collectif des femmes ainsi que le développement de leurs communautés. Les femmes africaines sont des agents incontournables du changement par le biais des actions individuelles, mais surtout, collectives. En Afrique comme dans les différents pays du sud, les associations féminines constituent non seulement un lieu pour les femmes pour acquérir une certaine autonomie économique mais un véritable espace de liberté et d'échange qui permettent aux femmes de sortir de l'isolement, d'avoir de nouvelles compétences, d'avoir plus d'estime et confiance en soi en tant qu'un individu à part entière au même titre qu'un homme dans des sociétés à dominance patriarcale. C'est à travers ces activités que les femmes confirment leur rôle, affirment leur statut social et renforcent toute leur féminité en terme d'avoir, d'être et surtout de paraître. Les groupements féminins avec des degrés différents, ont acquis un certain succès. L'impact positif de la participation des femmes dans ces groupements permet de penser que l'empowerment individuel ou collectif des femmes pauvres est possible en optant pour des solutions alternatives basées sur des pratiques et actions collectives qui permettent d'acquérir plus de capacités et de liberté. Dans ce sens, l'approche des capacités de Sen est pertinente dans la mesure où elle renforce le poids des activités féminines issue de l'économie sociale et solidaire, permettant ainsi de renforcer les gains en terme d'empowerment.La principale fonction des groupements économiques féminins est de permettre aux femmes membres de pouvoir subvenir à leurs besoins par une mobilisation et une redistribution des ressources et par conséquent sortir de la précarité. Ces femmes qui s'activent dans les groupements et qui sont souvent responsables de famille, cherchent les moyens surtout financiers de pouvoir s'acquitter de leurs obligations familiales et sociales. A travers notre travail, nous avons relevé d'autres gains pour les femmes sur le plan individuel et collectif qui sont aussi importants et moins quantifiables. Le contexte de crise et de précarité confère aux activités féminines un rôle social très important surtout dans les pays du sud, où la féminisation de la pauvreté est importante. The objectives of this work are to analyse different practices of social and solidarity economy that enable African women to move beyond vulnerability. Income generating activities involve both an increase in individual and collective empowerment of women, and in addition - further development of their communities. African women are key agents of change through individual actions, but most of all - though collective once. In Africa, as well as in various countries of the South, female organisations are not only a place for women to gain some economic independence, but a genuine areas of freedom and exchange, that allow them to come out of isolation, to learn new skills, and to have more esteem and self-confidence as individuals in their own rights alongside the men in a patriarchal societies. It is through these activities that women strengthen their role, their social status, and reinforce their femininity and presence Women's organisations, in different degree, manage to gain some success. The positive impact of women's participation in these groups suggests that the individual or collective empowerment of poor women is possible by opting for alternative solutions based on practical and collective actions that develop more capacity and greater freedom. In this sense, Sen's capability approach is relevant to the extent, that it reinforces the importance of women's activities within the social economy, thereby strengthening the gains in terms of empowerment. The main function of female economic organisations is to enable women members to be able to support themselves through mobilisation and redistribution of resources and therefore help them out of poverty. These women who are active in organisations and are often responsible for the family, often seek most financial means to meet their family and social obligations. Through our work, we have identified further significant gains for women as individuals, as well as in a collective, but these gains are less quantifiable. The context of crisis and insecurity gives women's activities a very important social role especially in the South, where the feminisation of poverty is important.
Keywords: African women; Afrique subsaharienne; Autonomisation; Capabilities; Capabilités; Conditions sociales; Conditions économiques; Empowerment; Feminisation of poverty; Femmes africaines; Féminisation de la pauvreté; Social and solidarity economy; Économie sociale et solidaire

Les paradis fiscaux dans la concurrence fiscale internationale - Molé, Antoine (Université Paris-Dauphine, 2015)
Dans le cadre de l’internationalisation puis de la mondialisation de la sphère économique et financière, les paradis fiscaux se sont développés tout au long du XXe siècle. Emergent à l’abri de la cage de l’Etat-Nation, ce phénomène de déconnexion de la sphère résidente de la sphère d’activité économique effective, a donné lieu à l’émergence de centres offshore, de manière embryonnaire durant la première moitié du XXe siècle, puis à une échelle industrielle sur l’ensemble des secteurs de l’activité économique à partir des années 1950. Les observateurs et les acteurs politiques des pays industrialisés se sont progressivement saisi du sujet dans le cadre de l’appréhension des effets dommageables de la concurrence fiscale internationale. Les difficultés rencontrées dans la lutte engagée à différentes échelles contre ces territoires traduisent l’ambiguïté des relations qu’entretiennent les grands pays industrialisés avec la sphère offshore.
Keywords: Concurrence internationale; Conventions fiscales; Coopération; Double imposition (traités); Finance offshore; Fraude fiscale; Fraude fiscale (droit international); Game theory; Harmful competition; Offshore finance; Optimisation fiscale; Paradis fiscal; Paradis fiscaux; Rapports de force; Tax agreements; Tax competition; Tax cooperation; Tax evasion; Tax fraud; Tax haven; Tax optimisation; Théorie des jeux; Évasion fiscale

Contribution à l'amélioration de la performance en matière d'imposition sur le revenu en République de Guinée - Monemou, Ouo-Ouo Waïta (Université Paris 9 Dauphine, 2015)
L’imposition sur le revenu en République de Guinée héritée du système fiscal français, constitue l’un des éléments importants de la structure fiscale guinéenne. Mais paradoxalement, cette imposition, par rapport à la TVA, reste de nos jours très peu rentable au budget de l’Etat. Or, le potentiel fiscal autant vaste, prenant en compte les revenus provenant des activités commerciales, industrielles, artisanales, agricoles, professionnelles, etc., réalisées par les contribuables y existe ; mais non encore « judicieusement exploité ». En effet, parler d’imposition sur le revenu revient à se pencher aussitôt sur les deux dimensions fondamentales qui sous-tendent cette notion : l’impôt sur le revenu (IR) des particuliers et l’impôt sur le revenu des entreprises ou sociétés dont les enjeux contributifs caractérisant véritablement la problématique de cette imposition s’enchevêtre dans une série de réalités complexes d’ordres politique, socio-économique, environnemental, juridique, etc., différentes d’un pays à un autre et d’une communauté à une autre.Le but ultime visé par cette thèse est de faire un constat diagnostic pertinent afin de retracer les causes et les effets de la faible part de l’imposition sur le revenu dans les recettes fiscales intérieures et de proposer des solutions efficaces en vue d’améliorer la rentabilité de l’IR et de l’impôt sur les bénéfices des sociétés qui impacterait tant soit peu la performance des services du fisc, du budget de l’Etat, de l’économie nationale et du système fiscal en République de Guinée.
Keywords: Budget; Contribution; Entreprises; Improving; Impôt sur le revenu; Impôts; Income tax; Performance; Performance financière; Politique fiscale; Republic of Guinea; République de Guinée

Les banques et la mise en oeuvre du dispositif de lutte contre le blanchiment des capitaux au Cameroun et en France - Tsobgni Djoumetio, Nathalie Laure (Université de Strasbourg, 2015)
La préservation de la bonne santé du secteur bancaire a toujours été au cœur des préoccupations de la profession bancaire mondiale. La lutte contre le blanchiment des capitaux constitue un moyen pour les banquiers de préserver cette santé. En effet, les banques camerounaises et françaises bien qu’assujetties à la lutte contre le blanchiment des capitaux, ont plus d’un intérêt à mettre en œuvre le dispositif préventif anti-blanchiment. D’une part, au niveau organisationnel, les banques camerounaises et françaises se sont dotées d’un service anti-blanchiment et de dispositifs informatiques qui veillent à stopper leur utilisation à des fins de blanchiment de capitaux. Au plan fonctionnel, les obligations de vigilance imposées aux banques au titre de la lutte contre le blanchiment des capitaux rejoignent et renforcent les règles bancaires déjà instaurées en vue d’une saine pratique des activités bancaires. Cependant, le dispositif préventif anti-blanchiment n’a pas été bien accueilli au sein de la profession bancaire. Pour cause, celui-ci s’attaquait à des principes chers à la profession bancaire notamment, le secret bancaire et le devoir de non-ingérence. De même, la mise en œuvre du dispositif a fait naître de nouvelles obligations dont la violation fait l’objet de sanctions.
Keywords: Agence Nationale d’Investigation Financière; Approach risks; Approche par les risques; Argent sale; Autorité de contrôle Prudentiel et de Résolution; Banques; Blanchiment de l'argent; Blanchiment des capitaux; Bleaching; Cameroun; Cartographie des risques; Compliance officer; Déclaration de soupçon; Entraide judiciaire internationale; France; Infractions économiques et financières; Lutte contre le crime organisé; National Agency for Financial Investigation; Personne politiquement exposée; Politically exposed person; Prudential Control Authority and resolution; Responsabilité; Risk mapping; Réglementation; Suspicion Declaration

Titrisation, Afrique : le cas du Maroc et de l’Union Economique et Monétaire Ouest Africaine (UEMOA) » - Abbour, Abdelali (Revue Interdisciplinaire, 2015)
Sous l’effet de des phénomènes de mutations dans les sociétés, on a assiste à une floraison de nouvelles activités ou de nouveaux instruments financiers. Concomitamment à cette prolifération de nouveaux produits ou techniques financières ; il est tout aussi apparu nécessaire d’adapter le secteur bancaire et financier de certains pays africains aux évolutions liées principalement aux nouveaux besoins de financement de leur économie nationale, à l’ouverture sur l’extérieur et aux opérations internationales et à l’introduction de l’innovation financière et technologique… Ceci est le cas pour le Maroc.
Number: 1
Keywords: Afrique; Maroc; Titrisation; UEMOA; Union Economique et Monétaire Ouest Africaine

A comparative reappraisal of debt relief measures for natural person debtors in South Africa - Coetzee, Hermie (University of Pretoria, 2015)
The purpose of this thesis is to do a comparative reappraisal of debt relief measures available to natural person debtors in the South African insolvency law. Although the broader South African natural person insolvency system currently includes three statutory debt relief procedures, namely, the sequestration procedure regulated by the Insolvency Act 24 of 1936, the administration order procedure in terms of the Magistrates Courts Act 32 of 1944 and the debt review procedure found in the National Credit Act 34 of 2005, not all natural person debtors have access to the system. The majority of this marginalised group are debtors with no income and no assets (the so-called No Income No Asset (NINA) debtors). Also, only one measure provides real debt relief in the form of a statutory discharge of debt. Furthermore, the existing measures have developed in a haphazard fashion which has led to a multiplicity of procedures, regulators and forums that resulted in ineffectiveness, inequality and uncertainty. The larger system therefore lacks proper policy considerations. This thesis provides the reasons for reform by, amongst others, arguing that the present situation is unconstitutional as it unreasonably and unfairly discriminates against the NINA group of debtors in particular. It measures the broader South African system against internationally accepted principles of efficient and effective natural person insolvency regimes. In this regard it is found that the system as a whole is seriously deficient. With reference to international principles and guidelines as well as suitable attributes found in foreign jurisdictions, the thesis concludes with suggestions for real law reform. Both substantive and procedural recommendations are made.
URI: https://repository.up.ac.za/handle/2263/52372

A Comparative Study on Customs Tariff Classification - Colesky, Theo (University of Pretoria, 2015)
The field of customs is commonly referred to as that of imports and exports. It is perceived as a maze of processes, procedures, and forms required to enable a customs administration to perform their wide range of responsibilities. One of the responsibilities of a customs administration is the collection of duties, which necessitates classification of the goods in question. This study sets out to determine the extent of customs control in relation to tariff classification in South Africa. The starting point is the establishment of the foundations of customs, both internationally and in South Africa. After origin and valuation, tariff classification is the third technical customs-related focus area. An analysis of the responsibilities of the customs administration in South Africa confirms the importance of revenue collection and, subsequently, tariff classification. As a result of South Africa’s membership of the World Customs Organization, specific obligations in relation to tariff classification are incurred. The implementation and application of the international provisions are considered and compared in South Africa, Australia, and Canada. Not only is South Africa’s existing legislation considered, but also two new Acts. It is found that despite similarities in the implementation of the Harmonized System Convention into the legislation of the three countries, South Africa’s existing legislation makes the most detailed provision for the Harmonized System and its aids. This is based on the finding that the legislation in Australia and Canada, as well as the two new Acts in South Africa, do not have the same comprehensive provisions. A critical review of the varying processes of classification in the three countries suggests that more suitable and effective processes could be implemented in South Africa. In addition, a synopsis of some of the principles developed in case law is provided and compared. In relation to facilitation, the access to relevant information and the adequacy thereof, as well as the availability of rulings, are considered. Differences in the approach to dispute resolution in the three countries are furthermore provided. Proposals are made to address the discrepancies in the implementation and application of the legislation, the process of classification, the principles developed in case law, the enhancement of related guides, the publication of tariff classification rulings, and the extent of facilitation and dispute resolution. Finally it is recommended that an independent and expert tribunal is established to adjudicate technical customs matters.
URI: https://repository.up.ac.za/handle/2263/42838
Keywords: Comparative study; Customs tariff classification

The Disclosure and Use of Social and Environmental Information by Libyan Banks - Elsakit, Omer M (Griffith University, 2015)
There is increasing interest in social and environmental issues throughout the world, especially in developed countries, where governments, organizations, and society well recognise the impact of business activities on the environment and society. Consequently, companies have potentially no alternative but to behave in a responsible manner, socially and environmentally, and to prove this by disclosing information about their related conduct. In this regard, banks play two important roles: first, as providers of social and environmental information in much the same manner as nonfinancial companies; and second, as providers of finance, by encouraging—if not obliging—bank customers to consider society and the environment in their bank-financed projects. Banks fulfil the latter role by requiring social and environmental information from companies when making lending decisions. Only a few Libyan studies have examined social and environmental issues in relation to economic activity, and these have generally revealed low levels of disclosure practice by organisations, including banks, in these areas. In addition, many changes have taken place in the Libyan economy and banking sector in recent years, including the establishment of a market exchange; decreased government participation in economic activities; and increased growth of the private sector that results, especially in the banking sector, with the entrance of foreign investors. These changes have placed a new emphasis on bank operations and the participation of banks in the Libyan economy. Thus, studying Libyan banks, in terms of their role in the environment and society, has attracted growing interest. As such, the core objective of this thesis has been to investigate the position of Libyan banks in relation to social and environmental issues and disclosure by considering their dual role as both providers and users of such information.
Keywords: Banks and banking; Environmental policy; Finance and environment; Libya

La cuestión prejudicial y la fiscalidad directa - García Antón, Ricardo (European University Institute, 2015)
This dissertation purports to connect the preliminary reference procedure with direct taxation. The aim of my dissertation is to lay down how this essential mechanism for the development of EU law – the preliminary reference procedure – deals with the cases in the field of direct taxation. By analyzing the preliminary rulings in the particular field, this thesis will shed light on the meaning of judicial cooperation between the Court of Justice of the European Union (“Court”) and the national courts. The almost absence of harmonized direct taxation reached at the European level enables the Court throughout the preliminary reference procedure to become the only available actor to safeguard the rights conferred to the individuals by EU law. In the area of direct taxation, it encompasses the rights of the individuals to exercise the fundamental Treaty freedoms of circulation. Therefore, the entrenchment of the rights of the individuals requires national courts requesting questions for preliminary rulings whereby national tax law in breach of EU law is challenged. Accordingly, this narrative of “protection of EU rights” which is embedded within article 267 TFEU enables the Court to adopt the role of a constitutional court assessing the compatibility of national law with EU law. The current asymmetries and conceptual mismatches of the substantive case law in the field of direct taxation are firmly anchored in a preliminary reference procedure in which the Court, as a constitutional court, is endowed with discretionary powers to drive it.
Accepted: 2015-05-07T14:37:51Z
Keywords: European Union countries; Fiscalidad directa; Fiscalité directe; Jurisdiction; Taxation

International taxation of cross-border digital commerce - Kadikov, Artem (University of Oxford, 2015)
This thesis discusses jurisdiction to tax cross-border digital commerce. The primary objective is to consider the reasons for the erosion of jurisdictional links, or nexus, between countries and taxpayers' digital activities and evaluate possible solutions for addressing such nexus erosion. Whilst it is argued that digital commerce is impossible to ring-fence due to digital technologies transcending all industries, the main focus of this research is on automated business models as case studies for the broader tax issues applicable across the entire digital economy. Using cloud computing, online advertising and e-tailing models as examples of digital commerce in the narrow sense, this thesis demonstrates that the proxies for establishing jurisdictional nexus have become increasingly fluid, thereby challenging the traditional international tax regimes for profits and consumption taxation. Numerous policy solutions have been proposed in order to rectify nexus erosion, including global and territorial tax models. Unlike the previous research in this area, this thesis focuses on the nexus elements of such proposals and assesses their viability in the light of the wider Internet governance jurisprudence. Global tax solutions, such as global e-commerce taxes and formulary apportionment, are analysed in the context of the international governance regime for the technical Internet infrastructure. Territorial virtual tax solutions, such as virtual permanent establishments, withholding taxes and destination cash flow taxes, are considered in the light of the Internet jurisprudence on the 'effects' and 'targeting' nexus standards. It is argued that, given the lack of technical and political infrastructure, none of the proposed routes would be viable from a practical perspective in the near future. It is concluded, therefore, that a practical solution would involve retaining the traditional profits and consumption tax models, whilst testing a narrow version of the digital targeting nexus standard as a backstop anti-abuse measure. It is envisaged that the limited anti-avoidance provision would subsequently pave the way for a comprehensive long-term solution, as digitisation continues to transform global commerce.
Keywords: Corporations; Digital commerce taxation; Double taxation; E-commerce taxation; Electronic commerce; International Trade; International business enterprises; Internet governance; Internet jurisdiction; Internet taxation; Jurisdiction to tax; Taxation

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (Conference Proceedings, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing

Le commissaire aux comptes et le ministère public en droit OHADA des sociétés commerciales - Taita, Taita (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2015)

Synthetic securitisation in South African law - Wessels, Francois Claassens (University of Pretoria, 2015)
The objective of this thesis is to critically analyse synthetic securitisation schemes in South African law as synthetic collateralised debt obligations using primarily credit default swaps (CDSs). This transpires from the perspective of primarily company law, and secondarily securities law and the law of contract. It includes a contextualised study of these schemes with regards to their origins, their significance regarding the recent financial crisis, and their rationales micro-economic influence and Basel capital requirements. Not only are the participants, such as parties acting in a primary role and secondary role and special-purpose institutions, studied, but also the obligations between these parties, such as the CDS contract, and the meaning of commercial paper, the legal nature of credit-linked notes, the business of a bank, and the influence of recent case law. It also includes a consideration of synthetic securitisation schemes in terms of the Collective Investment Schemes Control Act 45 of 2002. Furthermore, the role of systemic risk and moral hazard is explained, as well as the interaction between synthetic securitisation schemes, credit rating agencies and the function of risk management. The CDS is compared with insurance contracts, and a discussion of the 2014 International Swaps and Derivatives Association Credit Derivative Definitions is incorporated. For legal comparison, the South African model is compared with Canadian law and its unfunded credit derivatives in the light of recent regulation, and compared to German law and its prevalence of funded credit derivatives. Finally, suggestions are made as to the future of synthetic securitisation schemes.
URI: https://repository.up.ac.za/handle/2263/53208
Keywords: Company law; Debt obligation; Securities Law; Securitisation; South Africa; Titrisation

Contingence de la normalisation comptable pour les banques islamiques entre le légitime et le légal : une étude des convergences comptables des IFAS vers les IAS/IFRS. - Rezgui, Hichem (Le CNAM, 2014)
La finance islamique connaît depuis trois décennies une croissance soutenue. La problématique de recherche consiste à vérifier si l’existence de normes de comptabilité financière spécifiques aux institutions financières islamiques peut être un obstacle à l’objectif d’harmonisation comptable internationale entrepris depuis une quarantaine d’années avec la création de l’IASC. Une première phase de recherche normative suggère que les valeurs comptables issues d’une morale « islamique » seraient incompatibles avec les valeurs comptables portées par les normes internationales d’information financière (IAS/IFRS). Cependant, une deuxième phase descriptive et comparative confirme la convergence des normes comptables islamiques (IFAS) vers les IAS/IFRS illustrant un comportement « schizophrénique » du normalisateur comptable islamique (AAOIFI). En effet, cet organisme érige des normes conformes à la jurisprudence islamique pour les règles comptables de présentation mais qui convergent vers les IAS/IFRS pour les règles d’évaluation, mettant, alors, en relief la fonction « communication relationnelle » des données comptables. Afin d’étudier les facteurs de cette convergence, nous adoptons, dans une troisième phase explicative, une double approche théorique (Sociologie néo-institutionnelle et théorie de la dichotomie sacré-profane) et nous réalisons des entretiens avec les membres de deux comités opérationnels de l’AAOIFI : le comité Charia et le comité comptable (AASB). Ainsi, la convergence comptable s’expliquerait par le mimétisme des banques islamiques et de l’AAOIFI qui adoptent les mêmes réflexions et comportements que les banques classiques et le normalisateur comptable international (IASB). De même, des « luttes professionnelles » entre les deux comités opérationnels de l’AAOIFI aboutissent à la domination des membres du comité comptable plus influencés par une « culture IFRS » orientant, alors, certains choix de normalisation vers un renforcement de la convergence des IFAS vers les IAS-IFRS. De ce fait, des conflits entre « juridictions » professionnelles aux frontières mal définies permettent l’établissement d’une échelle de pouvoir et facilitent l’agissement d’effets mimétiques, coercitifs et normatifs. Islamic finance has grown steadily for three decades now. The research question consists inchecking whether the existence of specific standards of financial accounting for Islamicfinancial institutions can be a hindrance to the goal of international accounting harmonization undertaken over the last forty years with the creation of the IASC. A first normative phase of research suggests that accounting values resulting from Islamic moral are incompatible with the accounting values of International Financial Reporting Standards (IAS / IFRS). However, a second descriptive and comparative phase confirms the convergence of Islamic Financial Accounting Standards (IFAS) to IAS / IFRS illustrating a "schizophrenic" behavior of the Islamic accounting standard-setting body (AAOIFI). Indeed, this organization sets up standards in compliance with Islamic jurisprudence for accounting presentation rules but that are converged with IAS / IFRS for valuation rules, while highlighting the "relational communication" of accounting data. To study the factors of this convergence, we take in a third explanatory phase, a dual theoretical approach (neo-institutional sociology and theory of sacred-profane dichotomy) and perform some interviews with members of two operational committees of AAOIFI: the Shariah Board and the Accounting Board (AASB). Thus, the accounting convergence is explained by the mimicry of Islamic banks and Islamic accounting standard-setting body that adopt the same thoughts and behaviors than conventional banks and the International Financial Accounting Standards Board (IASB). Similarly, "professional struggles" between the two operational committees of AAOIFI lead to the domination of the accounting committee members that are more influenced by an "IFRS culture" while directing some decisions of standard-setting process towards greater convergence of IFAS to the IASIFRS.Thus, conflicts between professional jurisdictions with ill-defined borders allow theestablishment of a scale of power and facilitate the conduct of mimetic, coercive andnormative isomorphism.
Keywords: Finance islamique; International Financial Reporting Standards; Islamic accounting regulation; Luttes professionnelles; Neo institutional sociology; Normalisation comptable Islamique; Normes Internationales d’Information Financière; Normes comptables; Professional struggles; Sociologie néo-Institutionelle

A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, Izelle (Stellenbosch University, 2014)
Trusts are used for a variety of purposes, both in South Africa and abroad. Like so many other entities, trusts often do not function only in one jurisdiction and may therefore be exposed to international double taxation. South Africa, like most other states, enters into bi-lateral double taxation treaties, to limit the effects of international double taxation. Most of these treaties are based on the OECD Model Tax Convention on Income and on Capital (the OECD MTC). The South African trust is a unique creature. It is not based on the dual ownership concept on which most common law trusts are based, yet, it is not a juristic person either. The question that this research aims to address is how South Africa will interpret and apply certain provisions of the OECD MTC to trusts. Although the South African position is investigated, it is compared to the positions of the United Kingdom, Canada and the Netherlands. The dissertation starts with an analysis of the trust law in each of the relevant states, followed by an overview of the taxation regime governing trusts (and the parties thereto) in each state. The status of double taxation treaties and their interpretation are examined before certain critical provisions of the OECD MTC are analysed to determine how South Africa will apply these provisions to trusts. Hence it is explored whether a trust will be regarded as a person, whether it may be a resident and a beneficial owner for purposes of the OECD MTC. Furthermore, possible solutions for conflicts of attribution in the application of double tax conventions to trusts are investigated. The dissertation concludes that South Africa will regard a trust as a person for purposes of the OECD MTC. Moreover, some types of trusts may be viewed as residents and as beneficial owners for purposes of the OECD MTC. The solution proposed in the OECD’s Partnership Report should be applied to resolve conflicts of attribution involving trusts.
URI: http://hdl.handle.net/10019.1/95878
Keywords: Double taxation; Income tax; International taxation; OECD Model Tax Convention; South Africa; Taxation; Treaties; Trusts and trustees

Les mesures de prévention du surendettement des particuliers : à la croisée des chemins des droits commun et spécial - Loyer, Clémentine (Université de La Rochelle, 2014)
De création récente, la législation sur le surendettement a toujours eu pour ambition de prévenir et de traiter les situations de surendettement des particuliers. Présenté à son origine comme le droit « de ne pas payer ses dettes », le droit du surendettement a été intégré au Code de la consommation. Essentiellement envisagées comme la conséquence d’une consommation s’exerçant à crédit, les mesures préventives ont, de ce fait, été développées dans le cadre des règles de formation et d’exécution des contrats de crédit et de cautionnement. Face aux insuffisances de cette réglementation préventive, le droit commun des obligations est, à son tour, venu édicter des règles en vue de pallier les lacunes des mesures légales. Malgré les bénéfices apportés par la jurisprudence, l’efficacité de la prévention reste toutefois relative. En effet, tant la difficile conciliation des sources préventives que l’approche restrictive qui est envisagée du phénomène, mettent un frein à l’élaboration d’une prévention efficace. C’est au travers des règles de procédure de traitement du surendettement mais également, dans la redéfinition des notions d’endettement et de la personne vulnérable face au risque de surendettement, que les réponses à une prévention plus efficiente apparaissent. Recently created the overindebtedness legislation has always aimed to prevent and cure individual indebtedness situations. To his origin as the “right not to pay its debts” the indebtedness law has been integrated into the French consumer Code. Essentially seen as a consequence of consumption exerted on credit, preventive measures have been developed in the framework of the rules of formation and execution of credit agreements and surety. Given the inadequacies of this preventive legislation, the common law of contract is, in turn, came to make rules for any shortcomings of legal action. Despite the benefits of the law, the effectiveness of prevention, however, is relative. Indeed, as the difficulty of reconciling preventive sources that the restrictive approach proposed of the phenomenon, have no benefit on the development of effective prevention. It is through procedural overindebtedness rules but also in redefining the concepts of debt and the vulnerable person to the risk of debt distress, that the answers to more efficient prevention appear.
Issue: 2014LAROD004
Keywords: Cautionnement; Consommateur (protection); Consommation (droit); Contract; Credit; Creditor; Créancier; Crédit; Crédit à la consommation; Debtor; Débiteur; Obligation; Overindebtedness; Prevention; Prévention; Surendettement

La sécurité juridique en droit fiscal : étude comparée France-Côte d’Ivoire - Okou, Urbain (Université Paris 5, 2014)
La France et la Côte d’Ivoire sont deux États qui présentent des similitudes dues principalement à leur passé colonial commun ; mais il s’agit également de deux États qui présentent de nombreuses différences tenant notamment à leur niveau de développement. Si les règles de droit fiscal substantiel au sein de chacun de ces deux États permettent d’étudier les exigences de sécurité juridique et les moyens par lesquels elles sont prises en compte, c’est en réalité la pratique processuelle qui révèle de manière plus substantielle l’effectivité de cette prise en compte. Au demeurant, la problématique de la sécurité juridique n’est bien souvent réduite qu’aux seules exigences d’accessibilité, de stabilité ou de prévisibilité de la norme. Ce qui témoigne au fond d’une approche partielle de l’exigence de sécurité juridique tendant à en limiter l’étude à la qualité formelle et à l’évolution temporelle des actes juridiques. La prise en compte d’une pluralité de systèmes juridiques différents révèle cependant que la notion de sécurité juridique ne ramène pas nécessairement à un contenu univoque. En effet, l’insécurité juridique ne s’exprimant pas toujours en des termes identiques d’un cadre juridique à un autre, la sécurité juridique pourrait se révéler polysémique, voire antinomique, d’un système juridique et fiscal à un autre. Ainsi donc, au-delà de la norme, la sécurité juridique s’applique également au cadre et au système juridique ainsi qu’à la pratique juridique et juridictionnelle. La sécurité juridique apparaît donc, en droit fiscal, comme l’expression de la fiabilité d’un cadre et d’un système juridiques et fiscaux, à travers des normes de qualité offrant une garantie d’accessibilité et d’intelligibilité ainsi que des moyens pour le contribuable de bâtir des prévisions ou donner satisfaction à celles légitimement bâties. En outre, au-delà du cadre imposé par la présente thèse, il convient d’aborder la problématique de la sécurité juridique dans une approche moins restrictive, afin de ne point en occulter les aspects historiques, philosophiques, sociologiques et juridiques essentiels à une étude d’ensemble de la question. France and Côte d'Ivoire are two countries with similarities mainly due to their common colonial past; but they are also two countries with many differences especially due to their level of development. While the rules of substantive tax law within each of these two countries make it possible to study the requirements of legal certainty and the means whereby they are taken into account, it is actually the procedural practice that reveals more substantively the effectiveness of this consideration. It should also be noted that the issue of legal certainty is often reduced to the only requirements of accessibility, stability or predictability of the standard. This actually reflects a partial approach to the requirements of legal certainty that tends to limit its study to the formal quality and the temporal evolution of legal acts. Taking into account a plurality of different legal systems, however, reveals that the concept of legal certainty does not necessarily lead to an unequivocal content. Indeed, since legal certainty is not always expressed in identical terms from one legal framework to another, legal certainty could prove to be polysemic, or even antinomic, from one legal and fiscal system to another. Thus, beyond the norm, legal certainty also applies to the legal framework and system as well as to the legal and judicial practice. Legal certainty thus, appears in tax law, as an expression of the reliability of a legal and fiscal framework and system, through quality standards, offering a guarantee of accessibility and intelligibility, as well as means for the taxpayer to build predictions or satisfy those legitimately built. Moreover, beyond the framework imposed by the present dissertation, it is important to deal with the problem of legal certainty in a less restrictive way, so as not to obscure the historical, philosophical, sociological and legal aspects essential to a holistic study of the issue.
Keywords: ACCESSIBILITE; ACCESSIBILITY; Africa; Afrique; Arbitraire; Arbitrary; Bonne foi; Changements de doctrines; Changes in doctrines; Charte du contribuable; Charter of the taxpayer; Colonial era; Confiance légitime; Contentieux fiscal; Contrôle fiscal; Côte d'Ivoire; Droit fiscal; Dualism; Dualisme; Etat de droit; France; Implication du juge; Incertitude; Inflation normative; Intelligibility; Intelligibilité; Interpretation; Interprétation; Involvement of the judge; Juge de l’impôt; Legitimate expectations; Masse normative; Monism; Monisme; Non-retroactivity; Non-rétroactivité; Normative inflation; Normative mass; OHADA; Origines de la sécurité juridique; Origins of legal certainty; Penalty; Predictability; Prévisibilité; Rechtsstaat; Repression; Rule of law; Répression; Sanction; Sincerity; Stability; Stabilité; Sécurité juridique; Tax audit; Tax judge; Tax litigation; Uncertainty; Ère colonial

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

Les procédures de règlement de la double imposition résultant de la correction des prix de transfert entre entreprises associées - Hublot, Marie-Laure (Université Paris 2, 2014)
Avec l’accroissement des échanges transfrontaliers entre entreprises associées et des moyens de contrôles des transactions internationales par les administrations fiscales, les risques de différends en matière de prix de transfert augmentent nécessairement. Si ces conflits ne sont pas résolus, ils peuvent entraîner des doubles impositions, principalement économiques, et constituer des obstacles pour la libre circulation des biens et des services dans une économie globalisée. Les contribuables et les Etats ont donc besoin de procédures efficaces pour résoudre ces situations, unanimement dénoncées par les organisations internationales et les contribuables. Or les procédures actuelles ne sont pas totalement satisfaisantes. La Commission européenne, puis l’O.C.D.E ont récemment mené des travaux d’envergure visant à en améliorer les mécanismes. Le règlement de la double imposition en matière de prix de transfert est incontestablement un sujet d’actualité. Ces travaux invitent à une analyse critique de l’ensemble des mécanismes internationaux de règlement de la double imposition résultant de la correction des prix de transfert. Ces procédures sont étudiées, les causes de dysfonctionnement recherchées et des mesures d’amélioration sont proposées, notamment à la lumière des récents travaux des organisations internationales. La première partie est consacrée à la procédure amiable dans le cadre des conventions fiscales bilatérales. L’analyse menée suit une approche chronologique des étapes de la procédure, depuis son ouverture jusqu’à la mise en oeuvre de l’accord amiable. La seconde partie traite des voies nouvelles de règlement des doubles impositions que constituent la médiation, la conciliation et l’arbitrage en matière fiscale. Une large place est consacrée à l’arbitrage qui est analysé tant sur le plan conventionnel, puisqu’il a été récemment intégré dans les conventions modèles O.C.D.E. et O.N.U., que dans le cadre de la convention européenne d’arbitrage. Cette étude fait largement référence à l’approche de l’O.C.D.E. et des principaux Etats partenaires de la France. Néanmoins, il ne s’agit pas là d’un exercice de droit comparé mais seulement d’une mise en exergue d’autres pratiques pour servir le propos. With increasing cross-border trade between associated enterprises and means of control of international transactions by the tax authorities, the risk of disputes over transfer pricing necessarily increase. If these conflicts are not resolved, they can lead to double taxation, mainly of economic nature, and constitute obstacles to the free movement of goods and services in a globalised economy. Taxpayers and States therefore need effective procedures to resolve these situations, unanimously denounced by international organizations and taxpayers. However, current procedures are not entirely satisfactory. The European Commission and the O.E.C.D. have recently completed extensive work to improve the mechanisms. Dispute resolution in transfer pricing is certainly a hot topic. A critical analysis of all international settlement mechanisms of double taxation arising from transfer pricing adjustments is conducted. These procedures are examined, the causes of dysfunction sought and improvement measures are proposed, particularly in light of recent work of international organizations. The first part is devoted to the mutual agreement procedure under bilateral double tax treaties. The analysis is carried out following a chronological approach of the stages of the procedure, from its opening till the implementation of the mutual agreement. The second part deals with the new ways of resolving transfer pricing double taxation that are mediation, conciliation and arbitration in tax matters. Emphasis is on arbitration that is analysed both in conventional terms, as it has recently been integrated into the O.E.C.D. and U.N. model conventions, and as part of the European arbitration convention. This work makes extensive reference to the O.E.C.D and France key partners’ approaches. Nevertheless, it is not a work of comparative law but only examples to illustrate other practices
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2014PA020032
Keywords: Ajustement corrélatif; Arbitrage; Arbitrage commercial international; Arbitration; Conciliation; Double imposition; Droit international privé; Entreprises associées; Entreprises communes; Impôt; MARD; Mediación; Mediation; Mediação; Médiation; OCDE; Prix de cession interne; Prix de transfert; Procédure amiable; Procédure d'arbitrage

Le droit positif à l'épreuve du droit douanier : réflexions sur le droit douanier - Faye, Malick (Université Cheikh Anta Diop, 2014)
Keywords: Customs; Douanes; Droit douanier

Análise comparativa de modelos de governação corporativa no sector bancário moçambicano: os casos dos 3 maiores bancos - Mucheca, Elisa Vicente; Costa, Jeremias Cardoso Da (Universidade Eduardo Mondlane, 2014)
This paper aims to identify corporate governance models adopted by commercial banks in Mozambique. Firstly, it reviews the literature on Corporate Governance evolution, concept, models and practices at international level. It then makes an approach to internal control systems, some corporate governance arrangements such as Board of Directors, audit committees, internal and external auditing. The paper goes ahead to identifying the corporate governance practices both at country and banking sector levels. An explanatory analysis was applied as the research method covering three major commercial in terms of business volume, net profit and liquid assets. In order to gather information pertaining Corporate Governance models as well as on internal control systems, a questionnaire was sent to some commercial banks’ senior managers and to Banco de Moçambique as the monetary and supervisory authority of the credit institutions and financial societies in the country. Virtual and documental source were reviewed to assess the problem. The paper’s main finding is that commercial banks in Mozambique adopt the Anglo-Saxon model in which the Board of Directors is comprised of two types of directors, board committees and an array of information disclosure. Based on the main finding it was recommended a review and update by the competent authorities of the Aviso 11/GGBM/99 that prescribes internal control rules to be observed by credit institutions and financial societies in Mozambique. This paper aims to identify corporate governance models adopted by commercial banks in Mozambique. Firstly, it reviews the literature on Corporate Governance evolution, concept, models and practices at international level. It then makes an approach to internal control systems, some corporate governance arrangements such as Board of Directors, audit committees, internal and external auditing. The paper goes ahead to identifying the corporate governance practices both at country and banking sector levels. An explanatory analysis was applied as the research method covering three major commercial in terms of business volume, net profit and liquid assets.In order to gather information pertaining Corporate Governance models as well as on internal control systems, a questionnaire was sent to some commercial banks’ senior managers and to Banco de Moçambique as the monetary and supervisory authority of the credit institutions and financial societies in the country. Virtual and documental source were reviewed to assess the problem.The paper’s main finding is that commercial banks in Mozambique adopt the Anglo-Saxonmodel in which the Board of Directors is comprised of two types of directors, board committees and an array of information disclosure. Based on the main finding it was recommended a review and update by the competent authorities of the Aviso 11/GGBM/99 that prescribes internal control rules to be observed by credit institutions and financial societies in Mozambique
Keywords: Bancos comerciais; Controlo interno; Governação corporativa; Moçambique

La privatisation des missions douanières en République Centrafricaine (RCA) : une opportunité d'amélioration des finances publiques ? - Pascal, Lionel (Université de Bordeaux, 2014)
Pour assurer ses missions les États ont besoin de prélever l’impôt afin de s’assurer des ressources. Lacaractéristique des États en développement est, en matière de Finances Publiques, d’avoir des recettesbasées essentiellement sur les taxes prélevées en frontière sur les marchandises. Malheureusement dansces pays là, l’efficacité des Organisations Douanières est rarement au rendez-vous, notamment du faitd’une corruption très importante parmi les douaniers.Aussi les Organisations Internationales recommandent une privatisation partielle des missions afind’améliorer les recettes. Les sociétés privées se sont spécialisées dans cette forme de recouvrement etainsi la plupart des pays africains ont recours à l’une ou l’autre des sociétés dites de " pré-inspection ".Après des années de pratique peut-on évaluer l’efficience de cette privatisation ? L’exemple de la RCAest particulièrement pertinent pour étudier cela puisque d’une part ce pays a poussé la privatisation àl’ensemble des missions douanières, ce qui est unique au monde et d’autre part la situation actuelle de cepetit pays découle au moins en partie de l’absence d’une administration des douanes solide.Dans l’écroulement des structures administratives de ce pays, assisté depuis sa création par toutesles Organisations Internationales, ces dernières, sont-elles exemptes de reproches ? States collect revenue from taxes to provide necessary financial resources to the accomplishmentof their missions. Developing states have a common characteristic namely to collect revenue mainly onimported goods. Unfortunately customs administrations of these countries are generally inefficient due toa very high level of corruption of their personnel.Faced to this situation, internationals organisations advised to outsource some of the customs func-tions in order to improve the collection of revenue. Private companies developed new activities in thisarea and today most African countries have contracted out one or several of these companies usuallycalled preshipment inspection companies. After several years is it feasable to assess the efficiency of thatoutsourcing ? CAR is an excellent and pertinent study case to perform this assessment. On one hand,this country has outsourced all of the customs fonctions, which is a unique exemple in the world. Onthe other hand, there is a strong link between the existing situation of this country and the lack of anefficient customs administration.Can we blame these international organisations, which have assisted CAR since it’s creation, for thecollapse of the administrative structures of this country ?
Keywords: Central African Republic; Corruption; Customs; Douanes; International organizations; Organisations internationales; Outsourcing; Privatisation; République Centrafricaine

La fiscalité des aides interentreprises - Andriamanantenasoa, Andotiana (Université de Reims Champagne-Ardenne, 2014)
Les entreprises ont une place importante dans l’économie française, pourtant la notion d’« entreprise » n’a jamais été définie par le législateur. Une entreprise peut être une structure privée ou publique. Elle a le choix entre diverses formes juridiques, mais quelle que soit son activité, sa taille, son régime d’imposition, une entreprise doit se préserver et doit toujours agir dans son propre intérêt. C’est cet « intérêt » de l’entreprise que l’Administration fiscale s’évertue à contrôler dans les opérations qu’elle effectue. Or, cette notion est elle-même difficile à appréhender. En la matière, les débats doctrinaux sont venus nourrir une jurisprudence peu abondante. Les règles relatives de la fiscalité des aides interentreprises ne distinguent pas selon qu’elles soient consenties entre sociétés sur le territoire français, ou qu’elles soient transfrontalières. Toutefois, les enjeux des aides interentreprises en matière internationale sont incontestablement différents de ceux des aides interentreprises nationales. Ce mémoire traite d’abord de la question du régime général de la fiscalité des aides interentreprises, pour ensuite étudier l’encadrement particulier des aides interentreprises transfrontalières.
Keywords: Aides interentreprises; Droit des affaires; Fiscalité des entreprises

Transparência como estratégia regulatória no mercado de valores mobiliários: um estudo empírico das transações com partes relacionadas - Dias, Luciana Pires (Universidade de São Paulo, 2014)
O presente trabalho se propôs três tarefas: (i) responder algumas perguntas teóricas a respeito da transparência como estratégia regulatória no mercado de valores mobiliários; para tanto, revisitou a literatura jurídica e econômica sobre o papel da informação nos processos de tomada de decisão econômica; (ii) mapear o regime jurídico aplicável a transações com partes relacionadas no Brasil, analisando se as estratégias regulatórias adotadas são aquelas que seriam mais recomendáveis; para tanto, sistematizou as regras legais, regulamentares e os precedentes da Comissão de Valores Mobiliários, comparando-os ao desenho regulatório mais adequado sob o ponto de vista teórico; e (iii) conduzir um teste empírico para averiguar em que medida as reformas realizadas em 2009 no regime de prestação compulsória de informações periódicas foram capazes de mudar o comportamento dos emissores de valores mobiliários e, consequentemente, contribuir para o aperfeiçoamento de sua governança corporativa. O teste empírico demonstrou que, em um período de apenas 3 anos, o número de companhias no mercado brasileiro que adotou conduta mais estrita que a prevista em lei para lidar com transações com partes relacionadas praticamente dobrou (de 16% para 31,5%). Esse número é ainda mais expressivo nos segmentos especiais de listagem, que são os que mais cresceram nos últimos 10 anos. No Novo Mercado esse número passou de 19,5% para 46% e, no Nível 2, de 37% para 62,5%. No entanto, regras de transparência não parecem ser suficientes para lidar com transações com partes relacionadas porque, apesar da mudança de conduta percebida, as políticas adotadas pelas companhias ficaram muito aquém daquilo que seria recomendável sob o ponto de vista teórico.
Keywords: Conflict of interest; Information; Mercado de capitais; Mercado financeiro (regulação); Operação financeira; Parties liées; Regulation; Related-party transactions; Screening; Search; Securities market; Signaling; Transactions; Transparence; Transparency; Valeurs mobilières

Venture capital: valor da informação, riscos e instrumentos para sua mitigação - Silva, Fernando César Nimer Moreira da (Universidade de São Paulo, 2014)
Venture capital é espécie de empreendimento que vincula dois agentes econômicos, empreendedor e investidor, visando ao desenvolvimento de uma ideia inovadora para posterior comercialização no mercado. O empreendedor é detentor de conhecimento sobre a ideia e o investidor possui os recursos para desenvolver o projeto. O negócio se diferencia dos demais pelo alto grau de incerteza e risco do empreendimento e requer o uso de tipos contratuais adequados para sua limitação. O projeto se inicia com a etapa de contratação, na qual as partes negociam a divisão de riscos e retorno do negócio, seguindo-se a etapa de monitoramento do desenvolvimento das atividades. Ao final ocorre o desinvestimento, com a saída do investidor e venda do negócio. Do ponto de vista da Economia, utilizamos a Teoria dos Jogos e apresentamos os problemas informacionais, riscos e incertezas do negócio, e os incentivos para organizar a cooperação entre as partes. Do ponto de vista de Finanças, debatemos a decisão de financiamento do negócio e as alternativas para diversificação dos riscos do investimento, isto é, a possibilidade de limitação dos riscos pela adoção de estratégias de contenção, que aumentam o interesse em contratar o negócio. Do ponto de vista do Direito, avaliamos qual a estrutura contratual ideal para organizar esse tipo de empreendimento. Analisamos as principais formas usadas para organização do negócio, em especial as sociedades limitadas e as sociedades anônimas fechadas. Avaliamos o suporte normativo aplicável, com destaque para a possibilidade de limitação dos riscos do projeto pela aplicação das normas de Direito Societário a esses empreendimentos. Os principais riscos aplicáveis são os riscos de contratação do negócio, os riscos de alocação do poder de decisão entre os sócios e os riscos de interrupção prematura do projeto. Devido à natureza e características do negócio de venture capital, concluímos que esse tipo de projeto é mais bem organizado como um contrato plurilateral e que não há tipo contratual ideal para alinhar os interesses. Dos tipos existentes, a sociedade anônima fechada é o mais adequado, mas incapaz de limitar todos os riscos do negócio. A conclusão é confirmada, parcialmente, pelas evidências empíricas apresentadas. Venture capital is a business that links two economic agents, entrepreneur and investor, aiming to develop an innovative idea for future sale on the market. The entrepreneur holds knowledge about the idea and the investor has the resources to develop the project. It is distinguished from others by the high degree of uncertainty and risk of the project and requires the use of appropriate contract types for its restriction. The project begins with the contracting stage, in which the parties negotiate the division of risks and return business, followed by the monitoring of the development of the business activities. At the end occurs the divestment, in which the finished business is sold by the investor. From the point of view of Economics, we use Game Theory to present the informational problems, business risks and uncertainties, and the incentives to organize the cooperation between the parties. From the standpoint of Finance, we discuss the decision to finance the business, and alternatives for risk diversification, that is, the possibility of limiting the risks by adopting containment strategies that may increase the interest in contracting. From the point of view of Law, we evaluate the ideal contractual structure for organizing this kind of project. We analyze the main existing contract types, in particular, the limited liability companies and the closed corporations. We present our concerns about the normative support applicable to that type of business, emphasizing the Corporate Law problems. We evaluate the normative support applicable, emphasizing the possibility of limiting the project risks by applying the Corporate Law rules to such ventures. The main risks are the risks applicable to the contracting phase, the risk of incorrect allocation of decision rights between the partners and the risk of premature termination of the project. Due to the nature and characteristics of the venture capital business, we conclude that this type of design is best organized as a plurilateral agreement and that there is no contract type that can be considered ideal to align the interests. Considering all the existing types, the private corporation contract is the most appropriate form, but also unable to limit all the business risks. The conclusion is partially supported by the empirical evidence presented.
Keywords: Capital de risco; Capital-risque; Closed company; Closed corporation; Contract; Corporate finance; Direito comercial; Game theory; Instruments; Investimentos; Investment fund; Law and economics; Limited liability company; Mercado de capitais; Risk; Risque; Uncertainty; Venture capital

Effets d'un usage d'ERP sur les pratiques comptables normées dans le contexte de l'OHADA - Bampoky, Boniface; El Bachir, Mouhamed (Mesure, évaluation, notation : les comptabilités de la société du calcul, 2014)
Tested answers through the use of an exploratory approach (with IT experts in ERP and accounting users) are brought to the issue of the impact of ERP use on standardized accounting practices. The OHADA (Organization for the Harmonization of Business Law in Africa) was used as an adjunct to conduct the study. The classic business accounting is changing as well as the paradigm of accounting teaching. Some accounting standards increasingly disappear.
Keywords: Bookkeeping; Comptabilités normées; Gestion intégrée; Integrated Management Software Packages; Métier de comptable; OHADA; Progiciel; Standardized Accounting

Contribution à l'étude de la qualité de l'audit légal : évaluation de la pertinence des spécificités réglementaires françaises - Chihi, Hamida (Université Paris 9 Dauphine, 2014)
La promulgation de la loi de la sécurité financière (LSF) en 2003 a modifié l’architecture institutionnelle et la pratique d’audit en France. Au travers l’adjonction de nouvelles règles imposées par cette loi aux spécificités persistantes depuis 1966 comme le co-commissariat aux comptes et la durée du mandat de six ans, le marché d’audit se montre unique. Cette recherche examine l’impact de cette fusion réglementaire sur la qualité et le coût de l’audit en France. En se basant sur un échantillon composé par 888 observations du SBF 250 sur la période 2005-2010, nous avons révélé l’apport de la rotation des équipes signataires dans la restriction de la discrétion managériale. Outre son avantage dans la promotion de la qualité de l’audit, ce dispositif favorise la négociation à la baisse des honoraires d’audit. Nous avons aussi souligné l’évolution sous forme parabolique de la composante discrétionnaire sur la durée de mandat. En effet, la qualité de l’audit est inférieure pendant la première et la dernière phase de l’engagement. Ce postulat renvoie au renforcement de la compétence dans le temps et l’érosion de l’esprit critique à la fin du mandat. Le décalage, issu de la fusion réglementaire, favorise le maintien du niveau de la qualité élevé sur le marché français. L’association des deux équipes avec des durées auditeur-audité différentes est une contrainte à la discrétion managériale. Toutefois, ce décalage ne doit pas être excessif pour limiter la domination du plus ancien. Cet inconvénient du régime du co-commissariat aux comptes s’est trouvé limité sur le marché français. Nos résultats confirment son efficacité, essentiellement dans le cas d’un collège composé par deux Big 4. In 2003, the promulgation of the financial security act (LSF) has changed the institutional architecture and audit practice in France. Through the addition of new rules imposed by this act to the persistent specificities since 1966 as the joint audit and tenure of six years, the audit market shows unique. This research examines the impact of this regulatory merger on the quality and the cost of the audit in France. Based on a sample composed by 888 observations of the SBF 250 over the 2005-2010, we found the contribution of rotation audit partners in restricting managerial discretion. Besides its advantage in promoting audit quality, this device supports the negotiation of lower audit fees. We also emphasized the evolution in the parabolic form of the discretionary accruals over tenure. Indeed, the audit quality is lower during the first and last phase of the engagement. This assumption refers to strengthening the skills over time and erosion of critical appraisal at the end of audit tenure. The shift from regulatory fusion helps to maintain the level of high quality on the French market. The combination of the two teams with different listener-audited tenures is a constraint to managerial discretion. However, this shift should not be excessive to limit the oldest’ domination. This drawback of the system of joint audits is limited in the French market. Our results confirm its effectiveness, mainly in the case of two Big 4.
Keywords: Accruals; Audit partners’ rotation; Audit partners’ tenures; Audit quality; Co-Commissariat aux comptes; Commissaires aux comptes; Durée de mandat; Earning management and audit fees; Gestion du résultat et honoraires d’audit; Joint audit; Mandat – Vérification comptable; Mandats décalés; Mandats synchronisés; Qualité de l’audit; Rotation interne; Staggered partners’ tenures; Synchronized audit partners’ tenures; Vérification comptable; États financiers

Les dysfonctionnements de l'impôt au Maroc: cas des revenus professionnels - Saddougui, Mohammed (Université Mohamed Premier d'Oujda, 2014)
La présente étude vise l’évaluation des marges d’incertitude des techniques et modalités d’imposition des revenus des contribuables, notamment ceux qui ne tiennent pas une comptabilité conformément au plan comptable en vigueur. Malgré l’apparente technicité des techniques et modalités d’évaluation de la matière imposable, elles ne présentent pas le même degré de rigueur comparativement aux instruments de mesure en sciences expérimentales. L’origine de ces incertitudes est due dans une large mesure à la structure dualiste du tissu socioéconomique, à l’impertinence de la norme fiscale et à la divergence entre la fiscalité et la comptabilité. En effet, dans notre système d’évaluation de la matière imposable coexistent deux systèmes diamétralement opposés : des régimes plus ou moins rigoureux tels le régime du bénéfice net réel et le régime du bénéfice net simplifié et des régimes rudimentaires tel le régime forfaitaire. Certes, les progrès entrepris dans le sens d’une modernisation du système d’évaluation sont louables, mais une large population fiscale continue à ignorer partiellement ou totalement la tenue d’une comptabilité même dans sec aspects les plus élémentaires. Cette situation a évidemment des incidences négatives, voire arbitraires, sur l’appréhension de la base imposable. L’élargissement de l’assiette fiscale est crucial pour garantir les recettes stables nécessaires au financement du développement, notamment dans le contexte de la crise économique et financière actuelle. Une telle situation doit inciter les gouvernements à lutter contre l’évasion et la fraude fiscale, à fiscaliser certains secteurs qui demeurent en marge de toute fiscalisation, notamment l’agriculture, à intégrer dans le champ d’application de l’impôt sur le revenu le secteur informel , à rationaliser les dépenses fiscales et à faire preuve de création pour imposer les richesses. D’une manière générale, tout politique qui se veut efficace doit s’orienter dans le sens d’une promotion de la gouvernance fiscale qui devait en principe s’appuyer sur la rationalisation du système d’évaluation de la matière imposable.
Keywords: Comptabilité; Contribuable; Droit fiscal; Fiscal; Fiscalité; Forfait; Fraude; Gouvernance; Impôt; Informel; Matière imposable; Recettes; Revenu; Régime

Les établissements de paiement : un nouvel acteur dans le système bancaire - Jemali, Mouna (Université de Nice Sophia-Antipolis, 2014)
L’Europe des paiements a connu une incontestable avancée avec l’instauration de la monnaie unique mais il y’avait une réelle nécessité d’aller au-delà de cette simple monnaie en créant un véritable espace unique de paiement européen. Le législateur européen a voulu créer un cadre commun et homogène en matière de services de paiement à l’ensemble des acteurs bancaires et financiers de la zone économique européenne. De ce souhait d’harmonisation est née la volonté de diminution des coûts. A cet effet, le législateur européen a introduit un nouvel acteur dans le système bancaire et financier : l'établissement de paiement. Cette nouvelle structure a donc été créée avec un objectif clairement affiché : celui de favoriser la mise en concurrence sur le marché des services de paiement afin d’aboutir à cette baisse des coûts. Afin de favoriser le développement des établissements de paiement, le législateur européen leur a consacré un cadre spécifique avec des conditions prudentielles assouplies et une procédure d’agrément dédiée. En contrepartie de ce cadre allégé, ces nouveaux établissements de paiement ne pourront proposer que des services de paiement restreints. Dès lors, la mise en concurrence avec leurs prédécesseurs ne pourra être que limitée.Par ailleurs, en présence de ces nouveaux acteurs et des services de paiement innovants pouvant être proposés, il était nécessaire d'offrir aux utilisateurs de services de paiement une protection spécifique. Mais le cadre réglementaire européen établi semble être incomplet. De même, notre réglementation nationale paraît inadaptée soulevant ainsi une nécessité de réforme générale.
Keywords: Competencia; Competition law; Concurrence; Directive SEPA; Monnaie électronique; Paiement; Pays de l'Union européenne; Responsabilité; Services de paiement; Virement; Virtual currency

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

An evaluation of the predictive value of bank fair values - Ehalaiye, Oludimu Oluseun (Victoria University of Wellington, 2014)
This thesis examines whether the net asset fair values of banks possess predictive ability for the banks’ future cash flows and earnings. This is an important issue considering the arguments for and against the wider use of fair value accounting for banks’ financial instruments and the claim by some that fair values during economic recessions (where markets may be illiquid) are irrelevant and largely unreliable. A number of studies have found that the explanatory power of bank fair values when compared to traditional historical cost are more value-relevant based on capital market reactions. However, there is a very limited literature on how bank fair values are related to the future performance (e.g. earnings and cash flow) of banks. This study fills this gap by providing empirical evidence on the relationship between U.S. bank fair value disclosures and banks’ future performance as measured by operating cash flows and earnings over a three-period future horizon. Furthermore, the thesis provides evidence on the relationship between bank fair values, in terms of the levels classification introduced during the 2008 global financial crisis, and the future performance of banks, thus showing whether market illiquidity affected the underlying relationships. The study examines two distinct periods. The first study period, 1996-2005, was based on annual data of banks with minimum total assets of $US150 million as of year 1996. The second study period from 2008-2010 (this period encompassed the global financial crisis period and also the levels classification of bank fair values according to SFAS 157), was based on quarterly data of banks with minimum total assets of $US150 million as of the first quarter of 2008. The thesis provides strong evidence that there is a predictive relationship between bank fair values and future bank performance. The evidence is strong during the first study period from 1996 to 2005 where the current net asset fair values of on-balance sheet financial instruments of banks were significantly associated with future operating cash flows and operating earnings of such banks over a three-year future time horizon. However, the predictive relationship between net asset bank fair values and operating cash flows is stronger than the predictive relationship between net asset bank fair values and operating earnings. In the second study period, from 2008 until 2010 the empirical results show strong evidence that there is a predictive relationship between level 1 and level 2 bank fair values and future operating cash flows. The findings from the empirical results were that the current quarter’s level 1 and level 2 net asset fair values of banks were significantly associated with the future quarters’ operating cash flows of such banks. The level 3 net asset fair values of such banks in most cases were not significantly associated with the banks’ future quarterly operating cash flows. The corresponding relationships for operating earnings were that the current quarter’s level 1 net asset fair values of banks were positively associated with the future quarters’ operating earnings of such banks. However, the level 2 net asset fair values of banks were negatively associated with the future quarters’ earnings of such banks. This result is in contrast to the results obtained when the predictive relationship between level 2 bank fair values and future operating cash flows was evaluated, where it is found that both level 1 and level 2 net asset bank fair values are positively related to future quarterly bank cash flows. Further empirical analysis showed that a possible reason behind this disparity was that there was a structural change in the relationship between bank operating cash flows and operating earnings over the course of the first and second study periods, where, in particular, for the second study period (which includes the period of the global financial crisis) there was a systematic downward bias in operating earnings relative to the operating cash flows of the sampled banks. This in turn makes operating earnings a poor proxy for operating cash flows during the second study period. The findings from this study provide confirmation that net asset fair values have predictive ability as argued by Ball (2008); Barth (2006b) and Tweedie (2008). The study findings that net asset fair values have predictive ability is consistent with the FASB’s view that the asset values shown in firm financial statements should communicate information about the potential future financial performance of the affected firms (FASB 2010:17). Furthermore, the study also confirms that objectively determined bank fair values based on market prices rather than model based bank fair values provide greater predictive value in relation to future performance as measured by operating cash flows. Lastly, this thesis showed that during the first study period (where there was no financial crisis) that bank size, capital adequacy and growth prospects, had little impact on the results obtained, while for the second study period, there were cases where bank size and bank capital ratios did have a significant impact on the predictive relationship between bank fair values and future cash flows. The study contributes to the fair value accounting and accounting standard-setting literature and highlights that fair values have predictive ability, especially with respect to future operating cash flows of banks, both during and outside of periods of financial crisis.
Keywords: Economic forecasting; Fair value; Predictive value

A macro-financial theory of corporate financing and forecast modelling of market movements - Sutton, David (Victoria University of Wellington, 2014)
This thesis identifies a gap in existing theories of corporate finance. This gap is an implication of a Keynesian-Minskian analysis of markets and market-based economies. From a founding theoretical perspective rooted in the view that markets are not reliably efficient the case is developed that past price trend extrapolation is an important factor in corporate financing decisions. At a macro-financial level, companies repurchase equity over periods of strong market rises, while increasing debt at the same time. During periods of sustained, substantial market decline debt is retired and large new equity issues occur. This change in corporate financing is implicitly expensive as relatively low prices are realised for the new stock issued at these times. These factors suggest that conventional theories of corporate financing decisions that rely on corporate rationality and optimisation do not provide a compelling fit with observations in the period 1980-2012. Moreover, inference to Minsky’s (1986) argument that companies are compelled through market declines to shore up their balance sheets provides a better fit with the evidence. These arguments form the basis for the development of the ‘extrapolative expectations’ theory of corporate finance. The second major development in this thesis draws on the theoretical development outlined above to create market movement description and prediction models. These models operate on data drawn from the US Standard & Poors 500 index over the period 1980-2012. Two primary models are developed using binomial logistic regressions. The dichotomous dependent variables are drawn as quarters of market rise (1) or no rise (0), and market falls (1) or no fall (0), respectively for the ‘buy’ model and the ‘sell’ model. Variables tested and those found to add to an explanation of the dependent variables include: corporate debt flows, corporate equity flows, corporate dividend flows, interest rates, market volumes, and historical market levels. Each variable is tested for up to ten lags (two-and-a-half years). Collectively, the variables add to our understanding of those factors influencing (or at the least, signalling) market levels, enabling quarter ahead market forecasts to be made with greater accuracy than arises from an assumption of a random walk. This conclusion crystallises the view that company macro-financial flows and prices are an important cause or signal of future market direction.
Keywords: Corporate financing; Financial Accounting; International Accounting; Macro-financial; Minsky

Les leviers fiscaux à la disposition des transporteurs maritimes français de marchandises - Dauphin, Ogier (Aix-Marseille Université, 2014)

Quelles formes doit prendre l'activité bancaire transfrontalière en Afrique ? - Mminele, Aaron Daniel (Revue d'économie financière, 2014)
Après un aperçu de la croissance de l’activité bancaire transfrontalière en Afrique, cet article souligne certains aspects du contexte opérationnel des banques africaines avant d’examiner quelques-uns des défis que pose leur activité transfrontalière aux autorités africaines de réglementation et de supervision financière et les mesures qui devraient être prises pour remédier à ces difficultés.

Réflexion sur le système de régulation institutionnelle de l’activité bancaire dans la CEMAC - Sunkam Kamdem, Achille (Revue libre de Droit, 2014)
Parfois perçu comme un concept flou voire incertain ou encore comme un concept valise, le mot régulation fait partie de ces concepts qui font l’objet d’usages multiples dans le domaine juridique. Notion polysémique par excellence, la régulation est susceptible d’acceptions diverses. D’abord, elle s’identifie au droit lui-même en ce qu’elle apparaît comme l’une de ses fonctions essentielles. Ensuite, la régulation peut être entendue comme une limite imposée dans l’exercice des pouvoirs et comme rééquilibrage des rapports de force. Enfin, la régulation est un moyen dynamique de maintenir les grands équilibres d’un secteur. Ce dernier sens dont la considération s’avère plus indiquée pour la présente réflexion, permet de mettre en évidence l’avènement d’un droit de la régulation. L’activité bancaire dans la CEMAC (qui est l’un des secteurs principaux sur lesquels s’exerce la régulation) n’échappe donc pas aux règles ou principes qui la gouvernent. Etant donné que l’objet spécifique de la régulation bancaire est d’assurer la solidité du système bancaire, le rôle des institutions chargées de l’assurer est fondamental. Vu la place centrale qu’occupe le système bancaire dans le financement des économies des Etats membres de la CEMAC, une réflexion sur le système de régulation institutionnelle de l’activité bancaire dans la CEMAC s’avère d’une importance incontestable.
Keywords: Droit bancaire; Droit de la régulation; Production normative de la CEMAC; Régulation financière

Le rôle de la chambre de compensation dans l'usage du chèque au regard de la bancarisation : une étude de droit comparé Canada - France - UEMOA - Yao, Odile (Université Laval, 2014)
Le paiement par chèque par le biais de la chambre de compensation jouit d’une importance capitale pour tout pays, en ce sens qu’il favorise – s’il est généralisé à l’ensemble d’une société donnée – la «bancarisation» de la population, laquelle bancarisation conduit inéluctablement au développement économique du pays dans lequel un tel système est implanté. C’est autour de cette affirmation que se fera la démonstration de notre thèse de doctorat portant sur «le rôle de la chambre de compensation dans l’usage du chèque, au Canada, en France et dans l’UEMOA , au regard de la bancarisation». Il s’agit d’une étude de droit comparé qui, tout en mettant en exergue la place qu’occupe le paiement par chèque dans les pays visés par l’étude, démontrera que, quelles que soient les solutions adoptées par chacun de ces pays, ce postulat reste indéniable : selon que la population d’un pays donné l’accepte bien ou mal – à cause de la méfiance qu’il peut susciter et des incidents de paiement qui peuvent l’accompagner –, le paiement par chèque via la chambre de compensation conduit immanquablement, ou devient une entrave, à la bancarisation de cette population. Or, sans bancarisation, il ne saurait y avoir, dans un pays donné, de solutions durables d’implantation d’une telle chambre, et partant, d’un système bancaire efficient, sève nourricière de l’économie nationale. Car il est établi que la solidité et la fiabilité du système bancaire sont toujours à la racine de l’essor du développement économique du pays dans lequel la chambre de compensation est implantée.
Keywords: Afrique occidentale; Approche comparée; Banques (automatisation); Canada; Chambres de compensation; Chèques (encaissement); France

L'importance et l'avenir du coton en Afrique de l'Ouest : cas du Mali - Bagayoko, Karim (Université de Grenoble, 2013)
Cette thèse vise à démontrer l'intérêt du coton dans l'économie africaine particulièrement malienne basée à 70% sur le secteur primaire dans lequel la part de l'agriculture est estimée à environ 60 à 70% avec un taux d'employabilité dépassant plus de 60% de la population active. Aussi, elle soulève des interrogations quant au devenir de cette culture au regard des perturbations que connaît depuis plus d'une décennie le marché mondial du coton. Ce faisant, dans un premier temps, et sur plusieurs périodes, l'analyse des données statistiques à travers les tableaux, les graphiques, les figures et mêmes des cartes a permis de mettre en évidence l'importance pluridimensionnelle (économique, socioculturelle et environnementale, etc.) de cette culture au triple plan mondial, africain et notamment malien. Face, au grand intérêt suscité par la production du coton, des divergences vont naître à plusieurs niveaux conduisant à ce qu'on a appelé la guerre du coton. Ensuite, si d'une part les raisons historiques et géopolitiques ont été avancées pour justifier cette guerre autour du coton, d'autre part, il a été rappelé que celle-ci se manifeste à travers les nombreuses négociations et discussions qui s'enlisent sur le dossier coton notamment au niveau de l'Organisation Mondiale du Commerce qui, peine à faire respecter, ses propres règles de base (visant la suppression des barrières tarifaires et non tarifaires ) par certains pays appelés «Price makers». Autre manifestation de la guerre du coton a été expliquée par le volume important des subventions américaines, européennes et chinoises versées sous toutes les formes par les pays développés à leurs producteurs au détriment de ceux des pays pauvres singulièrement africains. Plusieurs études à l'appui des modèles et outils d'analyse d'impacts ont confirmé la corrélation négative entre les subventions et le cours mondial du coton exprimé par l'indice Cotlook A. A cet effet, il s'avère que les subventions versées par les pays développés se traduisent par une baisse du cours mondial du coton en moyenne de 15% (entre 3 à 28% selon les cas). Pour arrêter cette pratique des subventions, plusieurs ententes se sont constituées au premier chef, l'Initiative Sectorielle Africaine constituée des pays du C4 depuis la conférence ministérielle de Cancun en septembre 2003 et au second, viennent les initiatives au sein de l'UEMOA et du partenariat UE-Afrique autour du dossier coton. Enfin, dans la dernière partie de ce travail, le problème du coton va au-delà des questions de subventions et de prix qui semblent conjoncturelles. Ainsi, certains chercheurs proposent, outre l'abandon des subventions, une réforme structurelle des filières cotonnières en passant par la libéralisation du secteur et la valorisation (transformation) du coton et de ses sous produits, l'opportunité de cultures alternatives au coton conventionnel, sans oublier la formalisation des aides bilatérales et multilatérales afin de soutenir en perspective les actions envisagées. This thesis shows the interest of cotton in African economy particularly in Malian one founded about 70% on primary sector in that agricultural part is estimated between 60 and 70%. This last also employees 70% of working population. Following many perturbations ten years ago, on cotton world market, several questions appear concerning the future of this product. Therefore, in the first time, the historic analysis of statistic data with tables, graphics, pictures prove the cotton importance in Mali, Africa and the world in multiple dimensions (economic, social , cultural and in environment). In this situation, appear many conflicts which conduct to a called phenomenon “cotton war “. Many historic and geopolitics reasons, explain this cotton world war which main characteristics are no limit discussions and negotiations at the World Trade Organization which is unable to oblige members to respect its main rules that are to forbid tariffs and trade barriers and others specially by “price makers “ countries. Another characteristic of cotton war is the question of important American, European and Chinese subsidies paid by developed countries in favor of its producers in an error to disadvantage of poor countries producers singularly Africans. Several studies based on models and corporate assets certificate negative impacts between subsidies amount and world cotton price estimated by index A “cotlook”. This direct politics effect bears the world market of cotton about an average rate of 15% (between 3 to 28% by cases). In order to stop these subventions distortions, many agreements are founded about the cotton question, in first African Sector Initiative, a group of four cotton producer countries, since Cancun Ministry Conference in 2003, September, in the second position are UEMOA actions in favor it's cotton areas and the partnership European Union (EU)-Africa on cotton. Finally, in the third and last party of this thesis, cotton problem is highest than price and aids simple questions which are issue as temporary. Thereby, many scientists suggest, after giving up subsidies, structural reforms of African cotton sectors by liberalizing , creating transformation cotton factories, opportunity to farm others products without conventional cotton and without forgetting formal bilateral and multilateral aids in order to help strongly in the future actions undertaken in favor of cotton.
Keywords: African Sector Initiative; Afrique occidentale; Conditions économiques; Coton; Cotton; Cotton war; Guerres et négociations sur le coton au plan national; Industrie et commerce; Initiative sectorielle africaine; Mali; Prix agricoles; Reforms; Réformes structurelles; Subsidies; Subventions

Approche microéconomique de l'analyse de la performance des systèmes financiers dans les pays en développement : cas du Burkina Faso - Sombié, Issiaka (Université d'Orléans, 2013)
L’objectif de l’étude est de proposer, suivant une approche microéconomique, des outils d’analyse théorique et empirique permettant de savoir si le système financier d’un pays en développement tel que le Burkina Faso contribue à la création des richesses de la meilleure manière possible. Au terme des travaux, quelques enseignements se dégagent. D’abord, sur le plan théorique, à partir d’un premier modèle proposé, il ressort que, compte tenu de leur nombre dans les pays en développement, les PME sont un maillon essentiel du dispositif de création de richesse et qu’alors, ils constituent le meilleur canal par lequel le système financier peut avoir le plus grand impact sur la croissance économique. Ensuite, un second modèle théorique montre comment dans les pays en développement, caractérisés par un environnement légal et institutionnel de mauvaise qualité, la performance du système financier est compromise. Sur le plan empirique, les résultats révèlent qu’au Burkina Faso, le fonctionnement du système financier n’est pas performant en ce sens que les branches d’activités de petite taille et par transitivité les PME, étant le meilleur canal de transmission du développement financier sur la croissance économique au Burkina Faso, ne sont pas conséquemment financées par les banques. Par ailleurs, il apparaît que dans ce pays, les banques butent dans leur fonctionnement sur le problème de la prédominance du secteur informel dans lequel se retrouve une grande partie des entreprises. C’est pourquoi, malgré le fait que les PME contribuent fortement à la création de richesses intérieures, les banques ne parviennent pas à faire d’elles, des partenaires privilégiés en termes de financement. Ces enseignements appellent à des recommandations de politiques ou de réformes à faire pour encourager la mise en place de structures d’intermédiation informationelle telles que les Centres de Gestion Agréée, les agences de reporting, les agences spécialisées en matière de communication financière des entreprises. Cela permettra de rendre optimale l’interaction entre les PME et le système financier.
Keywords: Burkina Faso; Croissance économique; Developing countries; Développement financier; Développement économique; Economic growth; Financial development; Financial system; Informational intermediation; Intermédiation informationnelle; Marché financier; Optimalité; Optimaly; PME; Pays en développement; Performance; SMI; Système financier; Économie politique

Une expérience africaine de coaching : le coaching des PME par les experts-comptables dans le processus de changement OCAM-OHADA en Afrique - Feudjo, Jules Roger; Tchankam, Jean-Paul (Recherches en Sciences de Gestion, 2013)

Les déterminants du délai de publication des états financiers annuels : une étude empirique au Cameroun - Tikire, Oumar; Feudjo, Jules Roger; Kaoutoing, Sadjo (La Revue Gestion et Organisation, 2013)
L’objectif de cette communication est d’apporter un éclairage sur les facteurs qui président à la définition de la date d’annonce dans les entreprises. Il s’agit ici, de l’ampleur des travaux postérieurs à la clôture, de l’intention de maquiller les comptes et des facteurs de contingence liés au contexte de l’organisation. L’étude porte sur un échantillon de 63 entreprises qui exercent leurs activités au Cameroun. Nous avons après analyse pu dégager qu’un lien significatif existait entre l’ampleur des travaux postérieurs à la clôture, la date d’annonce et la majorité des facteurs de contingence. L’intention de maquiller les comptes et l’âge de l’entreprise semblent eux n’avoir aucun lien significatif sur la définition du délai de publication des états financiers.
Keywords: Délai de publication Facteurs de contingences Travaux postérieurs à la clôture Intention de maquiller les comptes

Le contentieux du marché boursier : entre régulation et juridiction - Rouimy, Michaël (Université Paris 1, 2013)
Le régulateur des marchés financiers, en réponse à l'augmentation progressive de ses pouvoirs de sanction, s'est vu enfermé dans un carcan procédural si étroit qu'il risque à terme d'en paralyser le fonctionnement. Cette thèse vise à démontrer comment le couple formé par l'AMF et l'autorité judiciaire se complète pour animer le système français de régulation des marchés financiers. La première partie détaille l'évolution historique de la régulation française qui a vu ses régulateurs successifs étendre leurs champs de pouvoirs, de sanction notamment. Pour légitimer ses nouvelles attributions quasi juridictionnelles le régulateur a été contraint de se voir doté d'un socle procédural de droit commun, qu'il partage avec les juridictions qui sous certains aspects semblent avoir absorbé sa fonction régulatrice des marchés financiers, ramenant l'AMF à un rôle d'auxiliaire de justice. La seconde partie montre que le contrôle judiciaire des décisions de l'AMF tient néanmoins compte de la spécificité de sa mission, adoptant une vision globale des différents niveaux de régulation, au risque parfois de perdre en sécurité juridique pourtant attendue par les acteurs des marchés financier. En effet, le juge participant à l'œuvre générale de régulation aux cotés de l'AMF, se voit doté d'un pouvoir quasi régulationnel. Pour que l'AMF réintègre pleinement sa fonction régulatrice qui fait sa raison d'être nous plaiderons pour un renforcement de ses pouvoirs spécifiques.
Issue: 2013PA010326
Keywords: Autorité des marchés financiers; Commission des opérations de bourse; Contrôle judiciaire; Droits de l'homme; Financial Markets; Financial regulation; France; Judicial review; Marché financier; Procédure (droit); Régulation financière

Les opérations de financement et d'investissement dans le droit musulman - Bessedik, Abdelkader (Université Paris-Est, 2013)
L’activité bancaire est le moteur de l’économie. Dans les systèmes juridiques de type occidentaux, les banques utilisent le droit des contrats pour proposer leurs services, que ce soit la banque commerciale ou la banque d’affaires. De même, les banques redoublent d’imagination pour augmenter leurs marges et la rentabilité des placements qu’elles font à partir des fonds qui sont déposés par les épargnants. Enfin, les banques participent au financement de grands projets et permettent ainsi leur réalisation, généralement avec une intervention des autorités publiques. Toutes les activités bancaires font l’objet d’une réglementation stricte et d’ordre public pour garantir la solvabilité des banques et protéger le crédit. La finance islamique s’inscrit dans ce schéma juridique, cependant elle doit intégrer des nombreuses contraintes engendrées par l’application et le respect de la Chari’a. En effet, il semble qu’à première vue l’interdiction de l’intérêt, riba, et de l’aléa, gharar, constituent des obstacles insurmontables pour pouvoir exercer le métier de banquier. En réalité, la finance islamique peut parfaitement se développer, à des conditions et dans un cadre qu’il faut expliquer.
Keywords: Banking law; Banques; Droit bancaire; Droit islamique; Islamic law

Le gouvernement d'entreprise dans les sociétés familiales non côtées - Kitsou, Anthi (Université de Strasbourg, 2013)
L’objectif de cette thèse est de discerner les originalités des sociétés familiales non cotées par rapport au gouvernement d’entreprise. On s’intéresse aux sociétés non cotées parce que les préoccupations sur le gouvernement d’entreprise se focalisent plutôt sur les grandes entreprises multinationales. Cependant, les sociétés familiales non cotées, actuellement la forme la plus répandue de l’initiative privée, posent de problèmes particuliers de gouvernement d’entreprise, parce que le lien entre famille et entreprise génère de conflits d’intérêts que la grande société cotée ne connaît pas. Premièrement, on expose les raisons pour lesquelles le gouvernement d’entreprise prend une importance plus cruciale dans ces sociétés. Il s’agit de montrer l’existence d’un particularisme s’agissant de la configuration de propriété, de gestion et de contrôle, puisque ces sociétés comportent la particularité de se trouver au croisement de deux systèmes ; la famille et l’entreprise (TITRE I). L’entreprise familiale se comporterait différemment vu que la composante familiale prédomine et influence le processus de prise de décision et les mécanismes de contrôle de la direction. LE TITRE II est consacré à la proposition d’ un ensemble de mesures susceptibles, à notre avis, de rendre son efficacité au système de gouvernance de la société familiale non cotée : une modification de la culture qui prévaut au sein des conseils; un renforcement de l’expertise et une amélioration de l’information des administrateurs ; la stricte séparation des fonctions de direction et de contrôle. This thesis aims to discern the particularities of family non -listed companies in relation to corporate governance. It isspecially focussed in non-listed companies, because research on corporate governance has been so far focussed on largemultinational firms. Non-listed family firms, nowadays the most common form of private initiative, pose particular problems of corporate governance, since the interconnection between family and company is a source of conflicts of interest that a public company does not face. Initially, the reasons why corporate governance has a crucial importance in this type of enterprise – due to its unique nature- are presented. This is to demonstrate the existence of uniqueness with regard to the configuration of ownership, management and control, as these companies have the distinction of being at the crossroads of two divergent systems: family and enterprise (Part I). The family business behaves differently because the family component predominates and undoubtedly influences the processes of decision making, control mechanisms and overall management. Part 2 is devoted to the proposal of a set of measures which, make ensure the effectiveness of the governance system of a non-listed family enterprise. It essentially entails a step change in the prevailing culture of the boards, a strengthening of expertise and improved information and management. The strict separation of management and control is also proposed.
Keywords: Actionnaires; Conseil d'administration; Corporate governance; Entreprises familiales; Famille; Family companies; Gouvernement d'entreprise; Minoritaires; Non cotées; Non-listed; Sociétés familiales; Valeurs mobilières

La modernisation du cadre budgétaire des pays de l'UEMOA - Zoure, Daouda (Université Paris 1, 2013)
La recherche porte sur la modernisation du cadre budgétaire des pays de l’UEMOA. Il s’agit d’évaluer la portée des réformes budgétaires développées dans chacun de ces pays. On s’est essayé à mettre en évidence la nécessaire mise en place d’une standardisation de certains dispositifs ainsi que d’une adaptation des procédures ayant fait leurs preuves non seulement dans certains États de la zone mais également dans d’autres pays confrontés à des problèmes similaires. On s’est appuyé sur les comparaisons internationales existantes et l’on a évalué la pertinence des solutions proposées notamment par les bailleurs de fonds. This research relates to the transformation of budgetary framework of West African Economic and Monetary Union (WAEMU) countries. It is a question of evaluating the extent of the budgetary reforms undertaken in each respective country. The research has tried to highlight the necessary installation of certain standard devices as well as adapting proven reliable procedures not just for certain zones of specific countries but also other countries confronted with similar issues. This exercise was based on existing international comparisons and the evaluation examined the relevance of the solutions suggested in particular by the financing institutions.
Keywords: Afrique occidentale; Budget framework; Budgetary framework; Contrôle judictionnel; Finance publique; Loi des finances; Processus budgétaire; Public finance; UEMOA; Union économique et monétaire Ouest africaine – 1990-2020; WAEMU

Mercado de capitais: formas de atuação do Estado - Tanji, Márcia (Universidade de São Paulo, 2013)
A observação do mercado de capitais brasileiro revela a constante presença do Estado: autoridade reguladora; acionista controlador de companhia aberta; sociedade de economia mista emissora de valores mobiliários; originador de ativos subjacentes a valores mobiliários; integrante do sistema de distribuição de valores mobiliários, por exemplo, bancos de investimento e corretoras sob controle estatal; cotista de fundo de investimento; entidade patrocinadora de fundos de pensão, os quais são relevantes investidores institucionais neste mercado. Os estudos sobre mercado de capitais focam a função regulatória estatal. Porém, outro aspecto merece ser abordado: o Estado não prescinde do mercado de capitais na implementação das políticas públicas. A atuação do Estado no processo econômico encontra fundamentos e limites na Constituição da República Federativa do Brasil. A exposição sistemática das formas de atuação do Estado pode contribuir para o controle que a sociedade deve realizar sobre a correção da atividade estatal e sobre a implementação das políticas públicas. Dessa forma, o objetivo do presente trabalho é sistematizar as diversas formas de atuação do Estado no mercado de capitais à luz de seus fundamentos constitucionais e legais e analisar de forma crítica as contradições, imprecisões, perspectivas e os desafios advindos da interação dinâmica entre as formas de atuação estatal. An analysis of the Brazilian capital markets reveals the constant presence of the State in numerous capacities: regulatory authority; controlling shareholder of public companies; mixed-capital issuer of securities; originator of underlying assets for securities; participant in the security distribution system, such as through investment banks and brokers under state control; shareholder in investment funds; and sponsor of pension funds that are significant institutional investors in this market. Studies regarding the capital makets focus on the State's regulatory function. Another aspect, however, deserves to be addressed: the State does not leave aside the capital markets in the implementation of public policy. The actions of the State in the economic process has foundations and limits in the Constitution of the Federative Republic of Brazil. The systematic exposure of the forms of State action can contribute to the control that society should wield to correct State action and the implementation of public policy. In this sense, the objective of this work is to examine the various forms of State action in the capital markets in light of constitutional and legal foundations and analyze the contradictions, faults, perspectives and challenges arising from the dynamic interaction of such forms of action.
Keywords: Acionista; Capital markets; Comissão de Valores Mobiliários; Comissão de Valores Mobiliários CVM; Direito comercial; Mercado de capitais; Políticas públicas; Public policy; Regulation; State

Contribution à la connaissance de la gestion du résultat des sociétés cotées en bourse : cas de la Bourse Régionale des Valeurs Mobilières - Diallo, Mouhamadou Saliou (Université Cheikh Anta Diop, 2013)
Cette recherche porte sur les déterminants de la gestion des résultats au sein des entreprises cotées en BRVM. Nous étudions la relation entre la gestion des résultats (mesurée à partir des accruals) et les motivations du dirigeant (rémunération, sécurité de l'emploi et réputation ou évaluation correcte du cours des titres) afin de tester deux hypothèses de gestion des résultats. Les analyses confirment plusieurs hypothèses de gestion des résultats et suggèrent que les déterminants de la gestion des résultats dépendent plus dans une perspective informationnelle que dans une perspective opportuniste.
Keywords: Accruals; BRVM; Bourse; Earnings management; Société commerciale; Valeurs mobilières

Comment assurer une information financière de qualité sous le système comptable OHADA ? - Bampoky, Boniface (Comptabilité sans Frontières...The French Connection, 2013)
The quality financial information is useful for forecasting, monitoring and the development of performance within a company, the effectiveness of the optimal investment choices, risk management, the economic policy choices. After more than a decade of implementation by business, OHADA Accounting System has not changed significantly, which does not mean absence of difficulties in its practical application. This article is the status of these difficulties.
Keywords: Accounting standards; Consolidation; Contrôle interne; Internal control; Normalisation comptable; SYSCOHADA; UEMOA

Les relations fiscalo-comptable : vers un passage de l'ère juridique à l'ère économique ? - Sambou, Siankoloute (Université Nice Sophia Antipolis, 2013)
Les divergences entre comptabilité et fiscalité ont largement contribué à obscurcir la véritable nature de leur relation. Pourtant l’article 38 quater de l’annexe III au Code Général des Impôts institue une relation complémentaire entre les deux disciplines. En réalité, cette relation complémentaire n’est qu’apparente car dans la plupart des cas de divergences, la fiscalité semble instaurer une domination arbitraire sur la comptabilité. Cette situation, que l’on peut qualifier de compromis s’est inversée au profit de la comptabilité depuis l’avènement des normes comptables internationales dont les règles, particulières en plusieurs points, ont permis au droit comptable un développement sans précédent, ce qui permet de qualifier la relation entre comptabilité et fiscalité de relation de compromis. Se faisant, les normes comptables internationales ont renforcé la tendance qui se dessine dans les sociétés contemporaines : le passage de l’ère juridique à l’ère économique. Les relations entre comptabilité et fiscalité ne sont que le témoin de cette évolution. Les principes de juste valeur et de substance économique au-delà de la forme juridique ont mis à l’ordre du jour des débats doctrinaux classiques tels que l’autonomie du droit fiscal par rapport au droit comptable et le liens qu’entretiennent ces disciplines avec d’autres, qu’elles soient juridiques (droit civil, droit commercial) ou non-juridiques (consolidation, finance). La nouvelle définition des actifs porte la marque de cette interdisciplinarité. Pourtant le système fiscal français n’est pas encore prêt à accueillir ces normes dans leur intégralité. Leur transposition totale dans le Plan Comptable Général entrainerait un abandon du système fiscal actuel pour une évolution vers les systèmes fiscaux anglo-saxons tout en entraînant des difficultés sources d’insécurité pour le droit fiscal. Oppositions between accounting and taxation have led into some difficulties regarding the qualification of the real relation between accounting and taxation in France. Article 38 of the FTC seems to impose a complementary relation between accouting and taxation. In fact, this complementary relation is not true, since Tax rules often have an influence on accounting rules when they are in opposition. This particular situation can be qualified as a compromise between Accounting and Tax rules. Since the introduction of International Accounting Standards rules in The French Accounting System, the compromise between accounting and Taxation seems to benefit from the accounting rules. It does exit a huge influence of accounting on tax rules: accounting rules are becoming more relevant than in the past. By the way, the International Accounting Standards have reinforced the trend that is emerging in contemporary societies. This trend is the passage from a legal area to an economic area. The relationship between accounting and taxation is the witness of this evolution. Principles of fair value and substance over form have uploaded the debate over the relationship between Tax and Accounting and how they interact with other disciplines such as civil law, commercial law, finance and accounting. The new definition of Assets due to the IFRS influence on tax is the proof of the connection existing between the different disciplines. The French tax system is not ready yet to accept the full version of IFRS. Their full implementation would lead into an unsecured tax law system.
Keywords: Autonomie du droit comptable; Autonomy of Tax Law; Autonomy of accounting Law; Comptabilité; Comptabilité patrimoniale; Droit fiscal; Financial Accounting; France; International Financial Reporting Standards; Normes comptables internationales; Politique fiscale; Relation fiscalo-comptable

The collection of value added tax on online cross-border trade in digital goods - Van Zyl, Stephanus Phillipus (University of South Africa, 2013)
Technological advances have had a major impact on traditional retail shopping changing it from a physical undertaking to a completely digitised experience where consumers buy digital media online. VAT systems that do not specifically provide for, or which have not been adapted to cope with, technology-driven advances, generally do not provide for the adequate levying and collection of VAT on cross-border digital trade. The South African VAT system is no different. The taxation of e-commerce should not artificially advantage or disadvantage e-commerce over comparable traditional commerce, or unnecessarily hinder the development of e-commerce. This thesis determines whether the South African VAT Act 89 of 1991 in its current form, can be applied adequately to raise and collect VAT on cross-border digital transactions. Where shortcomings in the VAT Act are identified, the harmonised VAT rules of the European Union (EU), together with the Organisation for Economic Cooperation and Development (OECD) proposals on consumption taxes, are analysed and discussed to seek possible solutions and make recommendations.
Keywords: Anonymising technology; B2B transactions; B2C transactions; BIT-rate tax; Banker-customer confidentiality; Blocked VAT account; Consumption taxes; Cross-border digital trade; Electronic commerce; Electronically supplied services; European Union; European Union countries; Fractionated VAT; OECD; South Africa; Taxation; VAT collection model; Value-added tax

Ömsesidiga överenskommelser enligt skatteavtal - Sallander, Ann-Sophie (Jönköping International Business School, 2013)
Ömsesidiga överenskommelser (eng. mutual agreement procedures) återfinns huvudsakligen i artikel 25 OECD:s modellavtal. Syftet med sådana överenskommelser är att undvika internationell dubbelbeskattning. Överenskommelserna kan antingen utgöra ett rättsmedel, som är ett alternativ till domstolsförfarande, eller verka som ett medel för att få skatteavtalen att fungera bättre mellan de avtalsslutande staterna. De rättsliga svårigheter som uppkommer i samband med överenskommelserna beror huvudsakligen på att överenskommelserna utgör en internationellt, av OECD, konstruerad företeelse som ska anpassas till och tillämpas på ett nationellt, redan befintligt regelsystem. Det kan härmed uppkomma spänningar och motsättningar mellan olika bestämmelser. Det övergripande syftet med denna studie är att kartlägga och utvärdera en internationellt konstruerad företeelse, dvs. ömsesidiga överenskommelser, för att undersöka om ändamålet med sådana överenskommelser uppfylls inom ramen för det svenska regelsystemet. Studien företas inom rättsområdet internationell skatterätt, men har emellertid en interdisciplinär ansats. Härav analyseras även bestämmelser inom folkrätt, konstitutionell rätt, förvaltningsprocessrätt, allmän förvaltningsrätt och sekretess. The focal point of this study is mutual agreement procedures, which are found in tax treaties, and derived from Art. 25 OECD Model Tax Convention (OECD MTC). The overall purpose of the mutual agreements is to avoid international double taxation. The agreements can either constitute an alternative to court proceedings, or constitute a means for improving the functioning of tax treaties. Provisions regarding mutual agreements can be found, in various forms, in all Swedish tax treaties. Since Sweden is a dualistic state tax treaties are incorporated into the Swedish legal system by legislation. This means that the provisions regarding mutual agreements are incorporated into Swedish legislation. Legal difficulties that arise regarding the agreements are mainly due to the fact that mutual agreement procedures constitute an internationally, by the OECD, constructed phenomenon, which is to be applied on a nationally, already existing, legal system. It may hereby occur tensions and conflicts between different provisions. The overall aim of this study is to identify and evaluate mutual agreements from a Swedish perspective. This includes identifying a relatively unexplored area, i.e. mutual agreements and their place within the Swedish legal system. In order to meet the overall objective, three research tasks are formulated. First, which internal provisions apply to mutual agreements, and how are they to be applied? Secondly, it is examined if the Swedish legal system, regarding mutual agreements, is consistent from three evaluation criteria: the constitutional principles of separation of powers and legal competence, legal certainty aspects, and the provisions of the Vienna Convention of the Law on treaties (VCLT). If there are any inconsistences in the legal system, may these be solved? Thirdly, it is studied if the Swedish legal system, regarding mutual agreements, provides for fulfillment of the purpose of mutual agreements or if there are any legal obstacles to this. The thesis is carried out in the field of tax law. However, the study has an interdisciplinary approach, which means that aspects of other areas of law are considered, such as international law, constitutional law, administrative judicial procedural law, administrative law, and secrecy.
JIBS Dissertation Series, ISSN 1403-0470 ; 089 URN: urn:nbn:se:hj:diva-20921 OAI: oai:DiVA.org:hj-20921 DiVA, id: diva2:615410
Keywords: Convention fiscale; Model Tax Convention; Mutual Agreement Procedure (MAP); Tax treaties

Essays on bank PME finance, banking structures and governance mechanisms in emerginig and less developed economies - Tacneng, Ruth (Université de Limoges, 2013)
The aim of this thesis is to examine several issues that banks confront in emerging and less developed economies such as SME financing and bank governance mechanisms. We first provide an overview of the level of bank SME financing in an economy where banks are mandated by law to lend to SMEs. We find large banks, foreign-owned, and well-managed ones to have low small firm financing exposures. Using a newly-gathered survey data of Philippine banks, we find that all banks perceive the SME market to be profitable. However, banks lend less to SMEs because of their opacity and that lending technologies are largely underdeveloped to serve small firms. Moreover, our results show that credit scoring and factoring are the arms-length lending technologies that are most suited to small firm lending. Examining the impact of income diversification on profitability on Philippine commercial banks, we find smaller banks, foreign banks and banks that lend less to SMEs to derive larger gains from a shift towards non-interest income. Investigating the effects of different governance mechanisms on bank risk taking in an economy where foreign ownership restrictions exist, our results indicate that minority foreign owners have a positive impact on bank performance, particularly, at lower levels of control manifested by dominant domestic shareholders. We also tackle the impact of ownership concentration on bank risk in less developed economies using an institutional approach. The results show that an increase in ownership concentration is associated with higher risk but better quality of institutions mitigates the negative impact of ownership concentration, notably in reducing credit risk. L'objectif de cette thèse est d’examiner les problèmes des banques dans les pays émergents et moins développés, tel que le financement des PME et les mécanismes de gouvernance bancaire. Nous étudions l’état de financement bancaire des PME dans un pays où les banques sont obligées d’allouer une part de leurs prêts aux PME. Nous trouvons que les grandes banques et les banques étrangères allouent moins de crédits aux PME. En utilisant un sondage que nous avons réalisé auprès des banques philippines, nos résultats montrent que le secteur des PME est perçu comme un marché rentable. Les banques sont contraintes à prêter aux petites entreprises à cause de l’opacité de ces PME. Le credit scoring et le factoring sont les techniques de financement les plus adaptées pour financer les petites entreprises. En examinant l’impact de la diversification du revenu sur la rentabilité des banques commerciales, nous trouvons que les banques étrangères et les petites banques bénéficient de l’augmentation des revenus hors intérêts. Nous testons l’impact des actionnaires étrangers minoritaires sur le risque bancaire dans un pays où les actions détenues par les étrangers sont limitées. Nous trouvons que les banques domestiques peuvent diminuer leurs créances douteuses lorsque le droit de vote des actionnaires minoritaires étrangers augmente. L’étude de la structure actionnariale des banques dans les pays moins développés montre qu’une augmentation de la concentration de la structure actionnariale est associée à un niveau de risque plus élevé. Toutefois, de meilleures institutions peuvent atténuer l’impact de la concentration de la structure actionnariale en réduisant le risque de crédit.
Keywords: Banques; Pays en voie de développement; Petites et moyennes entreprises

Bridging the GAAP? : IFRS in accounting practice - Hartmann, Berit (Jönköping International Business School, 2013)
This thesis investigates how International Financial Reporting Standards (IFRS) come to act within an organizational context. In particular, the thesis explores how the requirements for goodwill accounting and leasing influence organizational calculative practices, transforming and shaping operations management. Drawing on actor-network theory, this study moves away from a priori distinctions, following the construction and mobilization of accounting numbers across institutionalized boundaries within and around the organization. The empirical investigation took place in a large, worldwide active media group that is listed on a European stock exchange. The group is a particular interesting setting because of its diverse business structure and its German code-law accounting roots. Business combinations are a major growth factor within the industry and a high degree of decentralization in the organization placed responsibility for investment decisions at low hierarchical levels. Goodwill accounting and impairment testing were therefore highly significant calculative practices in the group. The study finds that the constitutive role of the financial reporting standards in the organization both solves tensions and dilemmas around the number and creates new ones when crucial interests are lost in translation. These tensions and dilemmas arise between the aim of standardization and closure for the construction of a legitimate value of the future, and the aim to mobilize numbers in order to motivate and create value for a future. Originally intended for the financial representation of organizational substance and performance, the standards become associated with operations management activities, helping to create the faithful records that sum up the organization. This interrelation helps to close concern around the representation of the future in a ‘fair’ value by distributing the calculative practices over a wide network of actors spanning inside and outside the organization. However, the relationship also forces a connection between calculations and ambitions that otherwise would have preferred to stay separate. This thesis offers a new perspective on IFRS implementation by emphasizing organizational activities. Through a focus on integration and the link between financial and management accounting, the ‘implementation problems’ highlighted in previous literature gain a refined theorization. When taking organizational practice seriously, integration becomes a process that may find temporal stability but will never be final. In the process, conflicts might be solved but new dilemmas will arise. In turn, concepts like decision usefulness, comparability and earnings management cannot exist in a stable form but are rather constructed in networks that disregard commonly assumed boundaries inside and around the organization.
JIBS Dissertation Series, ISSN 1403-0470 ; 094 URN: urn:nbn:se:hj:diva-23148 OAI: oai:DiVA.org:hj-23148 DiVA, id: diva2:689238
Keywords: IFRS; International Financial Reporting Standards

A Comparative Analysis of the Efficacy of the General Anti-Avoidance Rule as a Measure Against Impermissible Income Tax Avoidance in South Africa - Kujinga, Benjamin Tanyaradwa (University of Pretoria, 2013)
This thesis comparatively analyses the SA income tax general anti-avoidance rule (GAAR) in s 80A-L of the Income Tax Act 58/1962 and similar rules in Australia, Canada, the UK and the judicial doctrines in the US and the UK. It is argued that, while the SA GAAR may serve as a deterrent, it is going to have limited efficacy against impermissible tax avoidance due to the uncertainty it creates. It is argued that uncertainty will cause judicial activism to protect permissible tax avoidance, extensive and inconsistent judicial interpretation and confusion amongst taxpayers and SARS as to what constitutes permissible or impermissible tax avoidance. This thesis ends by recommending certain amendments, based on the comparative analysis, to the SA GAAR which can reduce uncertainty and thus improve it efficacy.
URI : https://repository.up.ac.za/handle/2263/33430
Keywords: General Anti-Avoidance Rule; Income tax; South Africa

Direct taxation and the internal market: assessing possibilities for a more balanced integration - Yevgenyeva, Anzhela (University of Oxford, 2013)
The role of the Court of Justice of the European Union in the process of direct tax integration in the European Union (EU) has been widely discussed in the academic literature, while another important actor, the European Commission, has attracted much less attention. The Commission’s input is commonly perceived to be limited to the right of legislative initiative. This study questions such an oversimplified interpretation and draws a more nuanced picture of EU tax harmonisation by integrating an analysis of the complex regulatory approaches adopted by the Commission for the establishment and smooth functioning of the Internal Market. It is argued that the past decade brought a notable change in the Court-dominated pattern of direct tax integration. This change is apparent first in the evolution of enforcement strategies under Articles 258 and 260 TFEU; and second, in the increased reliance upon non-binding regulatory measures. Both developments have strengthened the role of the Commission, supplying it with more possibilities for influencing national direct tax systems, despite the reluctance of Member States to agree upon legislative harmonisation. Against this background, the procedural and substantive problems associated with these instruments require closer examination. The normative scope of this research covers the key procedural problems related to the infringement procedure and non-binding regulatory measures. The empirical component explores the Commission’s enforcement and coordination practices, drawing particular attention to two case studies: the tax treatment of losses in cross-border situations and exit taxation. Following the analysis of enforcement and coordination in the field of direct taxation, the study argues the need and proposes potential solutions for (i) the developing of a more comprehensive procedural framework for the infringement procedure and non-binding regulatory acts; (ii) the strengthening of accountability mechanisms; and (iii) the enhancing of the effectiveness of their application.
Keywords: Direct taxation; EU Law; Enforcement; European Law; Exit tax; Good governance; Infringement procedure; Internal Market; Non-binding coordination; Soft law; Tax coordination; Tax integration; Tax treatment of losses; Taxation

The State of IFRS in Africa: Is IFRS in Disarray? - Zori, Solomon George (Governance across borders transnational fields and transversal themes, 2013)

La protection du consommateur des services bancaires et des services d'assurance - Hammoud, May (Université Paris 2, 2012)
Une des conséquences de la crise économique et financière de 2008 réside dans des tentations incessantes et continues de récupérer la confiance ébranlée du consommateur vis-à-vis des professionnels du secteur des services financiers. Alors que la protection du consommateur constitue un thème fréquent en droit français -et récent en droit libanais- une telle recherche fait défaut en matière spécifique aux services bancaires et aux services des assurances en droit comparé. En effet, le sujet est souvent présenté sous des angles séparés de la protection du consommateur dans chacun des deux services, dans chacun des deux droits. Il en découle qu’un approfondissement global, mais non exhaustif, sur « la protection du consommateur des services bancaires et des services d’assurance » dans une perspective comparative entre les deux droits, français et libanais, nous permettrait de mieux connaître les caractéristiques d’une telle combinaison. Ainsi, une série de questions se pose : Quels sont les contours des protections octroyées à ces consommateurs ? Comment leurs intérêts collectifs et individuels sont-ils défendus par les gouvernements, les législateurs, les juges, et la société civile ? Quelles sont les conséquences juridiques d’une telle protection qui s’avère être parfois « irrationnelle » ? Cette recherche a donc pour finalité de tenter de répondre à toutes ces questions, à travers deux parties. Dans la première, il s’agit d’analyser la protection octroyée aux intérêts collectifs et individuels des consommateurs des services bancaires et d’assurance. Dans la seconde, l’attention sera portée sur la mise en oeuvre d’une protection curative, parfois « déraisonnable » des consommateurs des services bancaires et d’assurance.
Keywords: Assurance; Banking services; Banques; Consommateur; Consommateur (protection); Consumer; Droit français; Droit libanais; France; French law; Insurance services; Lebanese law; Lebanon; Liban; Professionals; Professionnels; Protection; Services bancaires; Services d'assurance; Études comparatives

Regulação financeira, poder no mercado e crise financeira - Ribeiro, Ivan César (Universidade de São Paulo, 2012)
Os bancos nunca foram tão grandes como depois da Crise de 2008. No momento de maior pânico, logo após a quebra do Lehman Brothers, autoridades do mundo inteiro autorizaram fusões e aquisições antes vetadas. Era preciso garantir a estabilidade do sistema financeiro alegava-se e tentar preservar a concorrência nesse instante apenas aumentaria o pânico. O Brasil não ficou imune a esse movimento. Fusões como a do Itaú com o Unibanco e aquisições como a da Nossa Caixa pelo Banco do Brasil levaram o setor a um grau de concentração nunca visto antes. A discussão entre o Conselho Administrativo de Defesa Econômica (CADE) e o Banco Central, sobre quem deve julgar tais concentrações, faz parecer que existe uma contradição entre a disciplina constitucional da defesa da concorrência e a garantia da segurança e estabilidade das instituições financeiras. O resultado é a proliferação de instituições hipertrofiadas, os megabancos, em prejuízo desses mesmos princípios da ordem concorrencial estabelecidos constitucionalmente. Os principais argumentos em favor dos megabancos seriam, primeiro, o de que as rendas derivadas de poder no mercado que estes auferem (o chamado valor de franquia) formaria um colchão que aumentaria a sua resistência no caso de choques como o de 2008. Em segundo lugar, sugere-se que esses bancos, ao crescerem, acumulariam ganhos de escala, de escopo e de eficiência custo. Este trabalho propõe que não existe nenhum antagonismo entre a defesa da concorrência e a regulação bancária tradicional, de cunho prudencial e sistêmico. Propõe ainda que o modelo dos megabancos coloca um grande risco para a sociedade, tratando-se na realidade de um movimento estratégico de grandes instituições para acumular mais poder no mercado. São dois os motivos pelos quais se defende que não existe nenhum ganho no crescimento dessas instituições. Em primeiro lugar, as economias de escala se esgotam muito cedo, proposição com amplo suporte teórico e empírico. Na previsão mais otimista, bancos com mais do que 25 bilhões de dólares em ativos já estão na área de deseconomias de escala. Tampouco existem economias de escopo que autorizem a concentração de atividades tão diversas como as de banco comercial e de investimento. Bancos que concentram muitas atividades são, na realidade, avaliados negativamente pelo mercado. Mesmo os ganhos de eficiência custo, resultantes de uma melhor gestão de instituições mal administradas, não tem suporte empírico relevante. Em segundo lugar, uma estrutura moderna do setor bancário pressupõe bancos especializados e concentrados nas áreas em que têm maior eficiência. São bancos menores, que dividem com os mercados financeiros e outros intermediários a tarefa de prover o crédito. A concorrência do mercado de capitais, de instituições não bancárias (como gestores de fundos e financeiras) e de instituições não financeiras (como redes de supermercados, correios e empresas comerciais) forçou esses bancos a fazer o descruzamento de subsídios e a abandonar as atividades em que eram menos eficientes. Os megabancos vão na contramão dessa modernização, negando os princípios da Ordem Concorrencial. A reação dessas instituições, entretanto, é contundente. Os bancos procuram o crescimento excessivo, de forma a criar as megainstituições, para colher ganhos que não vêm de uma operação mais eficiente. São ganhos provindos das inconsistências na atuação do regulador. Este trabalho propõe a extensão das doutrinas de comportamento estratégico, de forma a incluir três categorias novas de comportamentos adotados pelos megabancos: 1. Expansão Não-Eficiente de Participação no Mercado: Bancos operam muito além da escala eficiente para obter as vantagens da garantia de socorro aos grandes bancos (o too big to fail), para influenciar a regulação e aumentar lucros e, por fim, para explorar os acionistas não controladores. 2. Saturação Anticompetitiva de Mercados: Bancos acumulam produtos para além do recomendado pelos ganhos de escopo, e também agências além do que geraria ganhos de escala, para bloquear a entrada de novos concorrentes. Mostra-se neste trabalho como o excesso de agências e produtos funciona como uma barreira à entrada, o que explicaria essas expansões como um movimento preventivo. 3. Bloqueio de Modernização Pró-Competitiva: Como uma estrutura moderna do setor obriga uma redução do tamanho dos bancos e, também, uma redução da participação do setor bancário nas atividades de crédito, os bancos tentam bloquear a modernização. O bloqueio é feito através de práticas anticoncorrenciais já conhecidas, como o bloqueio ao acesso de bens essenciais (por exemplo, ao sistema de pagamentos) e as ações concertadas, entre outros. A resposta do regulador para esses comportamentos estratégicos seria a aplicação pura e simples das ferramentas do Direito Concorrencial. Este deve aplicar medidas ordenando a desconcentração de mercados e deve investigar e punir as práticas anticompetitivas. É uma atuação que difere, portanto, da regulação bancária tradicional, em que constantemente se consideram os aspectos prudenciais e sistêmicos. Isso ocorre porque, no caso desses comportamentos, o restabelecimento da livre concorrência é condição necessária e suficiente para garantir a segurança e a higidez dos mercados financeiros. Essa conclusão, aplicada ao Brasil, leva a que se deve proceder à desconcentração no setor, com a adoção de medidas compensatórias para a maioria das fusões recentemente aprovadas. Essas medidas encontram precedente significativo naquelas adotadas tanto na Europa quanto nos Estados Unidos durante a Crise de 2008. Finalmente, algumas das previsões das hipóteses desenvolvidas no trabalho são testadas empiricamente. Foi desenvolvido um modelo jurimétrico que mostra que mais competição resulta em maior estabilidade financeira. O modelo também confronta a abordagem da Nova Economia Institucional com a NeoEstruturalista, mostrando que esta última resulta em mais competição e maior estabilidade financeira.
Keywords: Bank Competition; Competencia; Competition law; Concorrência Bancária; Concurrence bancaire; Crise financière; Estrutura de Mercado; Financial System; Marché financier; Market Structure; Régulation financière; Sistema Financeiro; Système financier

Les actes de disposition sur les titres intermédiés - Leibenson, Joël Philippe Gérard (Université de Genève, 2012)
La présente thèse traite des actes de dispositions sur les titres intermédiés.
Keywords: Bankenrecht; Banques; Bucheffekten; Comptes de titres; Derivative Finanzinstrumente; Droit; Effektenhandel; Schweiz; Sicherstellung; Suisse; Titres intermédiés (droit financier); Valeurs mobilières; Verfügungsgeschäft; Wertpapier

Les garanties réelles dérogatoires du code monétaire et financier - Nader, Jad (Université de Strasbourg, 2012)
La construction des garanties réelles dans le Code monétaire et financier s’est faite sans approche coordonnée. Le législateur s’est limité à produire des réponses pragmatiques aux besoins des praticiens, dotant ces garanties d'une souplesse et d'une sécurité renforcées. Or, seul le caractère dérogatoire des mesures qui visent à renforcer la sécurité, face aux procédures collectives notamment, caractérise ce que nous identifions comme des garanties réelles dérogatoires tant des garanties réelles de droit commun que des autres garanties sur actifs financiers. Il convient alors d’en tirer les conséquences pour proposer une construction rationnelle d’une garantie réelle financière unique mais protéiforme. C’est l’entrée en vigueur de la directive 2002/47/CE et sa transposition en droit français qui invitent à envisager un remodelage des garanties sur actifs financiers. Une approche commune et unitaire inspirée par cette directive paraît inévitable pour la cohérence de la matière.
Keywords: Code monétaire et financier; Collateral; Directive 2002/47/CE; Financial and Monetary Code; Financial collateral arrangements; Financial guarantees; Garanties financières; Garanties réelles; Marché financier; Monnaie; Sûretés; Sûretés financières; Sûretés réelles

Regole di comportamento e rimedi nella disciplina dell'intermediazione finanziaria - Teti, Antonio (Università di Pisa, 2012)
La tesi analizza, nel primo capitolo, le regole di condotta poste in capo all'intermediario finanziario. L'indagine ha ad oggetto, in primo luogo, la natura degli interessi coinvolti nella disciplina dell'intermediazione finanziaria, soffermandosi sul rapporto fiduciario che lega l'intermediario e l'investitore. Viene quindi sottoposta ad analisi la tecnica normativa cui si è fatto ricorso per disciplinare le regole di comportamento imposte all'intermediario e, quindi, il rapporto tra clausole generali e norme di dettaglio. La parte conclusiva del primo capitolo ha cura di indagare la natura giuridica della cosiddetta "Know your customer rule" ed il nesso di strumentalità tra la citata regola ed il principio di adeguatezza delle operazioni finanziarie; infine, viene analizzata la struttura delle operazioni contrattuali relative alle operazioni di investimento. Nel secondo capitolo, dopo una breve panoramica delle soluzioni accolte dalla giurisprudenza, viene condotta un'analisi avente ad oggetto il florilegio dei rimedi esperibili in caso di violazione delle regole di condotta da parte dell'intermediario, nel solco del principio di "non interferenza" tra regole di validità e regole di comportamento.
Keywords: Intermediazione finanziaria; Regole di comportamento

Títulos e valores mobiliários escriturais: aspectos decorrentes de sua internacionalização - Pereira Filho, Valdir Carlos (Universidade de São Paulo, 2012)
A liquidação das operações internacionais com valores mobiliários suscita questões de grande relevância em decorrência das diferenças entre os sistemas jurídicos envolvidos e a pluralidade de participantes. O objetivo desta tese é analisar as normas jurídicas brasileiras em relação às estrangeiras relevantes, por força de operações transfronteiriças que tenham por objeto valores mobiliários escriturais, notadamente operações de compra e venda de ações, para verificar a situação do sistema jurídico brasileiro e sua estrutura de pós-negociação em relação a outros países. Haverá descrição e análise da estrutura de liquidação de operações domésticas e da estrutura envolvida em operação com componente estrangeiro. Como aspectos necessários para a compreensão do tema, abordam-se as consequências jurídicas decorrentes da imobilização e desmaterialização dos valores mobiliários e da interposição de intermediários entre o investidor final e o emissor dos valores mobiliários usual nas operações transfronteiriças. Todo o trabalho considera as tendências e esforços de harmonização das normas aplicáveis que vem ocorrendo no plano internacional, podendo-se verificar que as normas e estruturas brasileiras para liquidação de operações com valores mobiliários são sólidas, adequadas e precisam apenas de aprimoramentos pontuais para atingir os melhores padrões internacionais.
Keywords: Ações nominativas; Book entry shares; Central securities depository; Clearing; Comissão de Valores Mobiliários CVM; Cross-border transactions; Internationalisation; Legislative harmonization; Mercado de capitais; Securities; Settlement; Titre dématérialisé; Título de crédito; Valeurs mobilières

A falência e a preservação da empresa: compatibilidade? - Gardino, Adriana Valéria Pugliesi (Universidade de São Paulo, 2012)
O fenômeno da crise das empresas é universal. Acrescente-se a esse fato, que a globalização das relações empresariais é uma realidade a qual, a cada dia, vincula, sem encontrar fronteiras, um incontável feixe de negócios e contratos que movem a economia, promovendo a circulação de riquezas, bens e serviços. Desses dois fatos incontestáveis resulta a inafastável importância do tema escolhido para análise nesta tese: a falência. Os efeitos da crise da empresa espraiam-se ao redor de um extenso leque de interesses correlatos (trabalhadores, fornecedores, fisco, agentes financeiros e outros), justificando análise com a finalidde de aprofundar o tema e aprimorar o regramento do direito concursal. Assim, a análise desenvolvida nesta tese consiste em demonstrar que, sob a vigência da Lei brasileira n. 11.101/2005, o instituto da falência foi inteiramente renovado. A originalidade do trabalho (Nota1048), assim, repousa na circunstância de analisarse a falência sob a ótica do direito concursal moderno, inaugurado no sistema brasileiro pela Lei n. 11.101/05, e em como esse antigo instituto do direito concursal reformulou seus objetivos, resultando em um tratamento diferenciado das prioridades da empresa em crise cuja inviabilidade, ou algum outro percalço, impeça-a de valer-se do instituto da Recuperação. Com efeito, a nova disciplina jurídica em estudo evidencia uma ruptura com a tradição dos primórdios da falência, nascida no direito medievo como um procedimento liquidatório voltado precipuamente ao pagamento dos credores, no qual o devedor insolvente era considerado um verdadeiro réprobo social, pois a quebra em si mesma era considerada delito. A mudança que se faz sentir na falência resulta do fato de que o direito concursal brasileiro alargou seu foco de tutela (partindo da estrtita relação: devedor e credores), para centrar-se na empresa: esse feixe de negócios e contratos que movem a economia. Note-se, o estudo da letra dos artigos 47 e 75 do diploma concursal brasileiro evidencia que tanto a recuperação judicial quanto a falência estão informadas pelo mesmo princípio e diretriz, que é o da preservação da empresa. Essa aparente contradição faz nascer a seguinte indagação: em que medida existiria compatibilidade entre dois institutos cujas finalidades e funções parecem ser tão diferentes, a ponto de serem informados pelo mesmo princípio? Na pesquisa desenvolvida verifica-se que esse intrigante aspecto do direito concursal brasileiro não é uma resposta isolada, mas encontra eco em soluções similares em outros sistemas analisados. É verdade, cada sistema possui suas particularidades, amalgamadas à sua própria cultura, regime econômico, e tradição jurídica. Todavia, ainda assim, é possível neles identificar traços coincidentes e que têm origem no mesmo foco de tutela: garantir o aproveitamento das organizações empresariais, sempre que possível. Realmente, o direito brasileiro abandonou em definitivo a visão de caráter meramente procedimental da falência (como processo de execução coletiva) e foca a tutela nos efeitos da crise das empresas, disciplinando tanto a possibilidade de superação (com a recuperação judicial e extrajudicial), quanto os meios de liquidação (falência) que possam resultar no aproveitamento da organização empresarial. Assim, a falência, conquanto mantenha seu caráter de procedimento liquidatório, passa a ter também o objetivo de criar mecanismos de manutenção e otimização dos ativos organizados e preexistentes à quebra, sempre que possível. Esse novo objeto revela, como acima mencionado, a compatibilidade de manutenção da empresa, na falência. Desse modo, mesmo na falência a lei brasileira estabelece mecanismos de possível manutenção da organização econômica pré-estabelecida, pois o art. 75 da LRE fixa um novo objetivo do processo falimentar: A falência, ao promover o afastamento do devedor de suas atividades, visa a preservar e otimizar a utilização produtiva dos bens, ativos e recursos produtivos, inclusive os intangíveis, da empresa. Aliás, é esse mesmo fenômeno, embora com particularidade e distinções próprias de cada um dos sistemas analisados, que é identificado no direito concursal estrangeiro. Daí porque se torna possível afirmar que a falência — essa antiga conhecida do direito concursal, em particular no direito brasileiro, como fica pontuado no trabalho — ingressou em uma nova fase do direito concursal moderno. Pode-se dizer, assim, que a novidade da legislação concursal brasileira não está apenas na criação dos institutos recuperatórios, mas, encontra-se também na falência, pois muito além da introdução dos institutos de recuperação, foram atingidas as raízes da falência, na medida em que seu objetivo foi reformulado e disto resultaram modificações expressivas. A tese demonstra que a atualização do instituto da falência é de tal ordem que, sob sua égide, é possível não apenas estabelecer uma solução de pagamento dos credores (chegando à liquidação da devedora) mas, também, preservar a organização de bens pré-existentes. Portanto, o estudo desenvolve-se com a análise geral de alguns sistemas estrangeiros e, após, do sistema brasileiro com enfoque nos métodos encontrados pela Lei para tornar efetivo o princípio insculpido no art. 75, ou seja, de que o afastamento do devedor não será óbice à preservação e otimização da utilização produtiva dos bens da devedora, mas, ao contrário, estimula esta solução. Em decorrência da análise, questiona-se a adoção de um sistema dualista, no direito brasileiro, quanto aos procedimentos concursais pois havendo um único objetivo final (liquidar ou preservar), parece que não se justifica a mencionada dualidade. Realmente, a identidade de princípio que a lei brasileira adota tanto na Recuperação judicial quanto na falência (preservação da empresa), não justifica a existência de dualidade procedimental. Parece-nos, ao final da análise, que a unificação procedimental, do ponto de vista substancial, traria melhor aproveitamento dos atos processuais e maior celeridade; e, no plano sistemático, implicaria o fim da dicotomia quebra versus recuperação para busca de soluções para a crise das empresas. Enfim, há uma nova falência no direito brasileiro pelo modo como este instituto foi recepcionado na lei agora em vigor. Além disso, esse não é um movimento isolado do direito brasileiro, o que se demonstra com as referências feitas a outros sistemas. Portanto, a tese evidencia de modo incontroverso que a falência deixou de ser um mero método de pagamento de credores (execução coletiva) que resulta na liquidação do devedor, e passou a ser um modelo de quitação das obrigações compatível com a preservação da empresa, mediante manutenção da organização de bens preexistentes do devedor, para exploração por um novo empresário, sempre que possível.
Keywords: Concurso de credores; Direito falimentar; Estabelecimento comercial; Fallimento; Falência; Impresa; Preservazione dimpresa

Financial liberalisation and economic growth in ECOWAS countries - Owusu, Erasmus Larbi (University of South Africa, 2012)
The thesis examines the comprehensive relationship between all aspects of financial liberalisation and economic growth in three countries from the Economic Community of West African States (ECOWAS). Employing ARDL bounds test approach and real GDP per capita as growth indicator; the thesis finds support in favour of the McKinnon-Shaw hypothesis but also finds that the increases in the subsequent savings and investments have not been transmitted into economic growth in two of the studied countries. Moreover, the thesis also finds that stock market developments have negligible or negative impact on economic growth in two of the selected countries. The thesis concludes that in most cases, it is not financial liberalisation polices that affect economic growth in the selected ECOWAS countries, but rather increase in the productivity of labour, increase in the credit to the private sector, increase in foreign direct investments, increase in the capital stock and increase in government expenditure contrary to expectations. Interestingly, the thesis also finds that export has only negative effect on economic growth in all the selected ECOWAS countries. The thesis therefore, recommends that long-term export diversification programmes be implemented in the ECOWAS regions whilst further investigation is carried on the issue.
Keywords: ARDL-Bounds testing approach; Capital accounts liberalisation; Co-integration; ECOWAS; Economic Community of West African States; Economic growth; Economic stablization; Financial crises; Financial liberalisation; Ghana; Interest rates liberalisation; Ivory Coast; Monetary Policy; Nigeria; Stock market developments

Essai sur les fonctions de l'information en droit des instruments financiers - Chacornac, Jérôme (Université Paris 2, 2012)
L’information constitue l’élément ou l’enjeu de nombreuses règles juridiques en droit financier. Ces règles imposent des obligations d’information aux émetteurs, aux intermédiaires financiers et aux investisseurs. Elles sanctionnent en outre les abus de marché en ce qu’ils constituent des atteintes aux qualités de l’information, et encadrent l’élaboration des opinions émises par les analystes financiers et les agences de notation. Dans un ensemble aussi hétérogène de règles, l’information reçoit diverses qualifications juridiques. La cohérence en la matière provient de la nécessité d’informer l’ensemble des acteurs du risque inhérent aux instruments financiers. L’information peut être étudiée à partir de ses fonctions intellectuelles, comme savoir communicable permettant de connaître le risque attaché aux instruments financiers. Alors que certaines données permettent de décrire le risque d’investissement, d’autres en servent l’appréciation dans la durée en vue de la réalisation de prédictions. Le droit positif évolue ainsi en s’appuyant sur ces deux fonctions intellectuelles de l’information : sa fonction descriptive et sa fonction prédictive. Cette analyse permet de renforcer l’intelligibilité d’un dispositif en évolution constante, qui suppose l’articulation du droit des sociétés, du droit des contrats et du droit répressif. Le droit des instruments financiers peut ainsi faire l’objet d’une analyse ordonnée à partir de l’information comme exigence permettant la prise d’un risque d’investissement. Information constitutes the element or the stake of many a legal rule in financial Law. These rules dictate disclosure obligations to issuers, financial intermediaries and investors. Furthermore, they sanction market abuses, insofar as they undermine the qualities of the information, and provide a legal framework for the elaboration process of opinions voiced by financial analysts and credit rating agencies. In such a heterogeneous body of rules, diverse legal qualifications are applicable to information. The conistency of the discipline lies in the necessity to inform the participants of the risk inherent to financial instruments. From its intellectual functions, information can be studied as transmittable intelligence permitting a better understanding of the risk financial instruments entail. While some data allows for the description of the investment risk, other data enables its assesment over time in order to realize predictions. Substantive law evolves by drawing on the two intellectual functions of information: its descriptive function and its predictive function. This analysis helps to reinforce the intellegibility of constantly evolving legislation, which implies the joint study of company law, contract law and criminal business law. The law of financial instruments can thus be the subject of an analysis stemming from information as a requirement to the taking an investment risk.
Keywords: ABUS DE MARCHE; Agences de notation; Divulgation d'informations; Droit financier; Emetteurs; Fonction; Information financière; Instruments financiers; Obligation d'information; Prestataires de services d'investissement

La répartition des compétences entre la loi et le réglement en droit fiscal sénégalais - Kebe, Abdou Aziz Daba (Université Cheikh Anta Diop, 2012)
Keywords: Compétence; Droit fiscal; Sénégal

Les prestations financières en ligne - Bayssa, Fatima Zahra Boulaich (Université Paris 1, 2012)
A l'instar des autres secteurs du droit, le secteur financier a incontestablement subi de profondes transformations dues à l'évolution profonde et rapide des nouvelles technologies au cours de ces dernières décennies. L'activité bancaire et financière s'est fortement dématérialisée, et s'est trouvée facilitée, avec le recours grandissant à Internet qui est devenu le nouveau canal de commercialisation des services financiers. Le site Internet, support de cette commercialisation a permis, aussi bien la conclusion du contrat en ligne, que le règlement des conflits qui peuvent en découler, grâce à l'intervention des législateurs européen et français. Tout nouveau est désormais le cadre dans lequel s'inscrit l'offre des services financiers en ligne. Cette offre nouvelle a réussi à gagner, puis à renforcer la confiance des consommateurs, grâce à un dispositif sécuritaire efficace, parfaitement adapté au contexte électronique qui sécurise le paiement en ligne. Une nouvelle évolution se dessine avec l’évolution de plus en plus massive des téléphones mobiles, dans la mesure où demeure garantie la protection des données personnelles numériques.
Keywords: Banque sur Internet; Consommateur; Consumers; Données personnelles; Financial services; France; Internet; Monnaie électronique; Online payment; Paiement en ligne; Personal data; Protection de l'information (informatique); Security; Services financiers; Sécurité

Cari hesap sözleşmesi - Durgut, Ramazan (İstanbul Üniversitesi, 2012)
Keywords: Banka hukuku; Banking law; Cari hesap sözleşmesi; Commercial law; Current account agreement; Faiz; Interest; Ticaret hukuku

Effectiveness of the Beneficial Ownership Test in Conduit Company Cases - Jain, Saurabh (Victoria University of Wellington, 2012)
Countries enter into double tax agreements with the economic objective of preventing double taxation of cross-border transactions. To achieve this objective, the contracting states agree reciprocally to restrict their substantive tax law. That is, a major policy of double tax agreements is to reduce double taxation of residents of states that are parties to the agreement. Residents of third states sometimes contrive to obtain treaty benefits typically by interposing a person or a conduit entity in one of the contracting states. In order to ensure that a resident of a contracting state who claims treaty benefits is entitled to them in substance, double tax agreements should be interpreted according to their substantive economic effect. Generally, double tax agreements follow the pattern of the OECD Model Tax Convention. The OECD Model Convention addresses the double taxation of dividends, interest and royalties, commonly collectively known as "passive income", in Articles 10, 11 and 12 respectively. These provisions usually operate by reducing withholding tax imposed by a source state on passive income that flows from the source state to a resident state. In order to prevent a resident of a third state from obtaining a source state withholding tax reduction by interposing a person or a conduit entity in the resident state, the OECD Model Convention requires the immediate recipient of passive income to be the "beneficial owner" of that income. That is, the OECD Model Convention requires the immediate recipient to be an owner in a substantive economic sense. Courts and commentators have difficulty in interpreting and applying the concept of beneficial ownership to conduit entities that are corporations, commonly referred to as "conduit companies". They have attributed the cause of the difficulty to the absence of a definition of the term "beneficial owner" in the OECD Model Convention. This thesis argues that the difficulty in applying the beneficial ownership concept to conduit companies has arisen not because of the absence of the meaning of the concept, but because logically and from an economic perspective the concept cannot be applied to companies in general, not to conduit companies in particular. The beneficial ownership test was meant to be a test of economic substance. From an economic perspective, the benefit or the burden of a contract entered by a company is economically enjoyed or borne by its shareholders. That is, in substance a company cannot be considered as owning income beneficially. From this consideration, it follows that conduit companies can never be considered entitled to treaty benefits. Nevertheless, the OECD Model Convention applies the beneficial ownership test to conduit companies pursuant to an assumption that at least in some cases conduit companies can be the beneficial owners of passive income. The Model Convention's assumption is based on the legal perspective that courts conventionally adopt. According to this legal perspective, companies hold income beneficially because they exist as separate legal entities from their shareholders. Courts find themselves battling these opposing perspectives when applying the beneficial ownership test to conduit companies. In order to make income tax law work efficiently, courts that are obliged to determine whether to honour claims to treaty benefits made by conduit companies have preferred to employ the legal perspective. Courts have justified this approach by adopting surrogate tests for the actual beneficial ownership test. Most of the surrogate tests do not relate to the concept of ownership at all. This thesis categorises the surrogate tests as "substantive business activity" and "dominion". By analysing reported cases, the thesis identifies deficiencies in these tests. One of the proposed outcomes of the thesis is to suggest an alternative approach for deciding conduit company cases. The thesis suggests that courts should consider an arrangement as a whole and investigate reasons for the existence of an immediate recipient of passive income in the specific corporate structure. The thesis also recommends amendments in the official commentary on Articles 10, 11 and 12 of the OECD Model convention in order to address the conceptual shortcomings inherent in those Articles.
Keywords: Double taxation; OECD Model Tax Convention; Tax law

Sermaye azaltımı ve vergisel sonuçlarının analizi - Öztürki, İlham (Gazi Üniversitesi, 2012)
Ekonomi, finans ve hukuk bilimleri açısından farklı anlamlara gelen sermaye, başta pay sahipleri ve ortaklık alacaklıları olmak üzere, ileride pay sahibi olması muhtemel kişileri, ortaklıkla ilişki halinde olan diğer gerçek ve tüzel kişileri ve şirketlerin vergi mükellefi olması nedeniyle de devleti yakından ilgilendiren bir kavramdır. İktisadi faaliyetlerin yürütülmesinde hayati önemi haiz sermayenin çeşitli ekonomik nedenlerle ihtiyari ya da sermaye kaybında olduğu gibi zorunlu nedenlerle azaltılması mümkündür.Sermaye azaltımı müessesesi Türk Ticaret Kanunu'nun (TTK) 473, 474 ve 475'inci maddelerinde düzenlenmiştir. Sermayenin şirket alacaklıları için güvence oluşturma fonksiyonu dikkate alınarak, özü itibariyle bir esas sözleşme değişikliği mahiyetinde olan sermaye azaltımı diğer esas sözleşme değişikliklerinden farklı birtakım düzenlemelere ve sıkı kurallara tabi tutulmuştur.Ülkemizde uzun yıllar süren enflasyonist etkiler ve ağır işleyen maliyetli bir süreç gerektirmesi nedeniyle yaygınlık kazanamayan yapının; enflasyon oranlarındaki düşme eğilimine ve sermaye azaltımı sonucunu doğurabilecek şirket bölünmelerinin TTK ile yasal alt yapıya kavuşturulmasına paralel olarak eskiye oranla daha sık kullanılması beklenmektedir. Bu itibarla sermaye azaltımı müessesesinin, uygulamada yaygınlık kazanması öncesinde vergisel sonuçlarıyla birlikte ele alınması, irdelenmesi, tereddüt ve belirsizliklerden arındırılmış daha etkin işleyen esnek bir yapıya kavuşturulması önem arz etmektedir.Vergi kanunlarımızda sermaye azaltımının vergilendirilmesi hususunda açık bir hüküm bulunmamasına rağmen, uygulamada sermaye azaltımı neticesinde ortaklara yapılan ödemelerin kâr payı olarak nitelendirilmesinin ve kâr paylarının tabi olduğu vergilendirme rejimi kapsamında vergilendirilmesinin anayasal bir ilke olan vergilerin kanuniliği ilkesine uygunluğu tartışmalıdır.Bu çalışmada, ticaret hukuku, sermaye piyasası hukuku ve vergi hukuku bileşenleri dikkate alınarak eski ve yeni ticaret kanunu, vergi kanunları ve vergilendirme ilkeleri, sermaye piyasası mevzuatı, konuya ilişkin yargı kararları, vergi uygulamaları bir arada değerlendirilerek sermaye azaltımı müessesesi ve bunun vergilendirilmesi incelenmiş, başta sermaye azaltımının vergilendirilmesine ilişkin açık bir kanun hükmünün bulunmamasından kaynaklananlar olmak üzere uygulamada karşılaşılan sorunlara değinilerek bunların çözümüne yönelik öneriler geliştirilmiştir. Capital is defined differently in economics, finance and law and it is a subject of interest to various natural and legal persons such as shareholders, creditors, possible future shareholders and other stakeholders of the firm. Firms being tax payers, firms? capital is also a subject of interest to the state. Capital can be reduced voluntarily due to various economic reasons, or as a mandatory process in case of a loss of capital.In the Turkish legislation, capital reduction is regulated in Articles 473, 474, and 475 of the Turkish Commercial Code (TCC). Taking into consideration the protective role of capital for the creditors, capital reduction, which is in essence, a change in the Articles of Incorporation, is regulated with stricter rules than other changes to the Articles of Incorporation.Capital reduction has not been widely used in Turkey, due to the long lasting high inflation periods, and the process being slow and costly. Currently, with substantially lowered inflation rates, and the newly introduced changes to the TCC, setting the rules for corporate spin offs, which might result in capital reductions, the process is expected to be used much more frequently than before. Consequently, before it becomes widely used, it is important to analyze the process of capital reduction together with its tax impacts, and to suggest any revisions to the existing process, for eliminating any uncertainties and making the process more effective.Although there is no explicit provision in our tax laws related to the taxation of capital reduction, in practice, when there is a payment to the shareholders due to capital reduction, for tax purposes this payment is treated as dividend and taxed accordingly. However, it is debatable that this practice is in line with the constitutional principle that taxes can only be levied through laws.This study analyses capital reduction and issues related to its taxation, taking into consideration their relevance to commercial law and capital market law. Thus, the analysis collectively evaluates the provisions in the old and the new Commercial Codes, Tax Codes, Capital Market Legislation, related court decisions and taxation practices, identifies and suggests solutions to the problems encountered in practice, which mainly arise due to the fact that there is no explicit provision in the tax laws for taxation of capital reduction.
Keywords: Capital decrease; Dividend; Kar dağıtımı; Kar payı; Profit distribution; Sermaye azaltma; Tax responsibility; Tax system; Taxation; Vergi sistemi; Vergi sorumluluğu; Vergilendirme

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.

Understanding fiduciary duties: conflict of interest and proper exercise of judgment in private law - Valsan, Remus (McGill University, 2012)
This dissertation analyses the content and justification of the notion of fiduciary duties in private law relations. The thesis promotes the following understanding of fiduciary duties: in a legal relation where one party undertakes to act in the interests of another, and acquires decision-making authority over the other's interests, such party undertakes a core duty to exercise his best judgement in the other's interests. The core judgement duty requires a fiduciary to exercise judgement based on relevant considerations. While what constitutes a relevant consideration can be determined objectively, the weight to be ascribed to each relevant factor is left at the fiduciary's subjective appreciation.Due to the existence of this core duty, the law imposes a set of proscriptive duties. The proscriptive duties require a fiduciary to manage situations of conflict of interest. Their purpose is prophylactic: they aim to prevent self-interest (or another duty to exercise proper judgement) from affecting the reliability of fiduciary's judgement in a conscious or subconscious way. The proscriptive duties protect the core duty to exercise judgement and, as a result, the beneficiary's right to a proper exercise of judgement by the fiduciary.
https://escholarship.mcgill.ca/concern/theses/wd376141g
Keywords: Conflict of interest; Fiduciary duties; Judgment; Private law

Corporate Governance and the Relationship between Default Risk and the Earning Response Coefficient - Zakaria, Nor Balkish (Victoria University of Wellington, 2012)
This study examines the effect of corporate governance on the relationship between default risk and the earnings response coefficient (ERC). Using a sample of 2,004 firm-years comprising 334 firms listed on the Bursa Malaysia over a six year period from 2002 to 2007, this study tests whether corporate governance mitigates the effect of default risk on ERC while controlling for the established determinants of ERC — beta, growth, earnings persistence and size. Using reverse regression, the study confirms that beta is negatively related to ERC and that growth, earnings persistence and size are positively related to ERC. Default risk is found to be negatively related to ERC thus confirming that beta is only a partial measure of risk relevant to ERC. Corporate governance — as indicated by audit quality, audit committee expertise and independence, and board independence and board shareholding — mitigates the negative effect of default risk on ERC. The results of the study hold both for the pooled sample of 2,004 firm-year observations and on a year by year basis for the 334 firms in the sample. The results are also found to be robust to various sensitivity tests including to alternative measures of the variables. The study thus provides systematic and comprehensive additional evidence on the determinants of ERC. Of itself this is an important contribution to the literature but especially so given that the evidence comes from Malaysia — an emerging economy — whereas the existing empirical literature relates mainly to developed countries.
Keywords: Corporate governance; Default risk; Earnings response coefficient

Les garanties du contribuable dans le cadre du contrôle fiscal en droit marocain - Haloui, Khalil (Université de Grenoble, 2011)
La thèse a pour objet d'examiner la question cruciale des garanties légales du contribuable face aux prérogatives importantes de contrôle fiscal dévolues à l'administration à la suite de la mise en place du nouveau régime d'imposition déclaratif au Maroc. Elle se propose alors de rendre compte de l'état du droit positif sur cette problématique et de répondre à la question de savoir dans quelle mesure les nouvelles procédures de contrôle fiscal instituées permettent-elles de protéger les droits du contribuable vérifié. The thesis aims at examining, following the introduction of new tax declaration regime in Morocco, the paramount issue in respect the taxpayer legal safeguards against the tax authorities prerogatives during tax audit . This work intends to report on the applicable law on this issue and to answer the question on how the newly established tax audit procedures may protect the audited taxpayer's rights.
Keywords: Audit powers; Contentieux d'établissement; Contentieux fiscal; Contrôle fiscal; Court appeals; Droit fiscal; Garanties du contribuable; Imposition; Maroc; Pouvoirs de contrôle; Prior administrative appeals; Recours administratif préalable; Recours administratifs; Recours juridictionnels; Tax audit; Tax settlement litigation; Taxpayer’s guarantees

O mercado de títulos públicos: desmaterialização e circulação - Catapani, Marcio Ferro (Universidade de São Paulo, 2011)
O Estado, para obter recursos com o objetivo de financiar suas atividades, recorre ao mercado por meio de dois mecanismos: a obtenção de empréstimos individualizados e o lançamento de títulos públicos. Na realidade atual, a dívida mobiliária alcança volume muito superior ao da contratual, tendo em vista algumas vantagens do mecanismo dos títulos públicos. Entre essas vantagens, pode-se citar um universo maior de potenciais compradores, a possibilidade de execução de política monetária, a maior facilidade de controle, o menor custo de negociação e escrituração. Fenômeno também observado nas últimas décadas, em escala mundial, é de que os títulos públicos sejam emitidos de modo escritural e eletrônico. Nesse contexto, não pode ser aplicado a esses valores o ferramental teórico e normativo dos títulos de crédito. Com efeito, se a doutrina tradicional considerava os papéis emitidos pelo Estado como uma espécie desses títulos, tal constatação não mais se sustenta, em especial diante da completa inexistência de um suporte documental dos ativos eletrônicos. As características e institutos próprios dos títulos de crédito, como a cartularidade, a literalidade, o endosso e o aval não são compatíveis com a realidade negocial que hoje conforma os títulos públicos. Um conceito jurídico que pode explicar a natureza atual dos títulos públicos e permitir o regramento das operações que os envolvem é o de instrumento financeiro. Desenvolvido no âmbito do ordenamento comunitário europeu, esse conceito não se encontra perfeitamente delimitado no ordenamento jurídico brasileiro, mas nada impede a sua construção em sede doutrinária. Tomando por base a noção de instrumento financeiro, o foco da normatização deixa de ser cada título considerado em si, para recair sobre o mercado em que eles são negociados. Assim, ganha relevo o estudo da estrutura institucional desses mercados, bem como das principais operações que neles são travadas. Tais operações incluem a emissão e a oferta inicial, a negociação secundária, o resgate, a rolagem da dívida, bem como eventuais renegociações e alterações unilaterais nas características dos títulos. Para o desenvolvimento de mercados líquidos e eficientes, algumas condições são imprescindíveis, como, por exemplo, a existência de graus mínimos de estabilidade, previsibilidade e segurança, de uma imagem sólida e confiabilidade das instituições participantes, em especial dos entes estatais emissores etc. Além disso, todo o arcabouço normativo deve ser construído levando-se em consideração os interesses de cada grupo de agentes econômicos envolvidos, como forma de tornar atrativa para estes a alocação de recursos na aquisição de títulos públicos. When the State needs to obtain resources in order to finance its activities, it resorts to the market through two main mechanisms: individual loans or public securities. Nowadays, the debt securities total amount is much higher compared to the debts founded on individual loans, due to some advantages of the technology of public securities. Among such advantages, it can be mentioned a larger universe of potential buyers, the possibility of implementing monetary policy, the easier control, and the lower costs of trading and bookkeeping. In recent decades, it has also been noticed that the public bonds are worldwidely issued in both book-entry and electronic ways. In this context, the theoretical and normative tools regarding negotiable instruments can not be applied to these bonds anymore. Indeed, if the traditional doctrine used to consider the public bonds as negotiable instruments, such understanding can no longer take place, specially taking into account the complete absence of any supporting documentation of electronic assets. The peculiar characteristics and rules related to the negotiable instruments, such as the need of the document to enforce the rights, the respect to the terms of the document, the endorsement, and the guaranty are no longer compatible with the present reality of public bonds. A legal concept that can explain the current nature of the public securities and allows the regulation of operations envolving them is the financial instrument. Developed under the European Community law, this concept is not well defined in the Brazilian legal system yet, but nothing prevents its development in our doctrine. Based on the concept of financial instruments, the focus of regulation is no longer each title considered itself, but the markets in which the financial instruments are traded. Thus it becomes important to study the institutional structure of such markets, as well as the leading operations that are performed in the markets scope. Such operations include the issuance and the initial offering, the secondary trading, the redemption, the debt rollover, the renegotiations of the bonds, and the unilateral changes of their characteristcs. In order to develop efficient and liquid markets, certain conditions are essential, such as the existence of minimal degrees of stability, predictability and security; a solid image and reliability of the participating institutions, in particular of the public issuing bodies etc. Moreover, any regulatory framework should be built taking into consideration the interests of each economic agents groups involved, in order to make the allocation of resources in government securities attractive for them.
Keywords: Dematerialization; Dématérialisation; Government bonds; Market; Mercado de capitais; Negotiable instruments; Titres publics; Título de crédito; Títulos públicos

Le traitement du contentieux bancaire - Nemadeu Djuitchoko, Eric Bertrand (Université de Saint-Etienne, 2011)
Notre travail, qui s’inscrit en droite ligne des recherches du CERCRID sur les marc consistait a étudier cette question, dans un secteur particulier. Il s’est agi d’aller au-delà du discours général sur les modes alternatifs de règlement des conflits, pour voir précisément ce qu’il en est en matière bancaire. La recherche du GIP droit et justice confiée au CERCRID, et portant sur la baisse générale du contentieux de l’impayé depuis le début des années 1990, a constitué un élément supplémentaire de notre champ d’investigation. A la conjonction de ces deux préoccupations principales, s’est greffée une grave crise économique mondiale née du crédit hypothécaire aux États-Unis d’Amérique. Tous ces facteurs nous ont conduit a nous intéresser à la prévention et au règlement du contentieux bancaire. Le travail a donc consiste en une large recherche sur le contentieux bancaire, le mot traitement ayant été choisi pour englober a la fois la prévention et le règlement. On comprend ainsi que le sens contextuel du mot traitement va au-delà de l’acception habituelle de ce terme. Trois principaux constats se dégagent de l’étude du contentieux bancaire : il s’agit d’une matière éminemment marquée du sceau de la prévention, d’une matière limitativement marquée du sceau de la médiation et de l’adjudication, d’une matière rarement marquée du sceau de l’arbitrage. La prévention du contentieux bancaire repose sur deux axes majeurs : la réduction des occasions de contentieux, ainsi que la limitation des espaces de discussion. La négociation précontentieuse apparait comme le mécanisme prééminent permettant d’éviter le litige et de régler les différends. En cas de litige, les parties peuvent saisir le médiateur bancaire. Il est également possible de recourir au juge. En cette matière, c’est essentiellement le juge étatique que les parties saisissent. Il va sans dire que l’arbitrage est rare, notamment du fait de l’absence d’imperium de l’arbitre. Our work was done in the framework of CERCRID research on ADR (alternative dispute resolution). the goal was to study this question in a specific sector. we had to go beyond general knowledges on ADR, in order to discover precisely what it was about in the bank sector. the research of the Center « droit et justice », on the falling of the unpaid litigation since the beginning of 1990, which was assigned to the CERCRID, constituted an additional element for our investigations. furthermore, we had to take the sup-primes crises in the USA into consideration. all these factors lead us to work on the prevention and the settling of banking conflicts. the job therefore consisted to do a large research on banking litigation. the word treatment was chosen to include both the prevention and the settling. this is to say that the sense of the word treatment hier goes beyond the common meaning of this word. three main conclusions can be made about the research on banking litigation : it is a matter in which the prevention of conflicts plays a very important role. the mediation and the settling by the judicial court are less important hier. the arbitration is rare.the prevention of conflicts lies on two majors axis : the reduction of conflicts occasions, and the limitation of space for discussions. the negotiation appears to be the most important mechanism to settle disagreements, the banks trying to avoid judicial proceedings. in case of failure, the conflict can be solved by mediation, or by the court. the judicial court is usually the one chosen by the parties at this stage.
Keywords: Banks; Banques; Cautionnement; Contentieux; Crise économique (2008); Investissements; Investments; Litigation; Overindebtedness; Surendettement

Le contrôle au sein des OPCVM : étude comparative entre le droit français et marocain - Madmoun, Fatiha (Université de Strasbourg 3, 2011)
L'impressionnante évolution de l'industrie de la gestion au cours de ces quinze dernières années, notamment par l'utilisation des techniques de gestion ct de financements novatrices ainsi que le recours à des produits structurés de plus en plus complexes, a conduit l'industrie des d'OPCVM à vivre de profondes mutations. En effet, le caractère puhlic de l'épargne collective et le rôle stratégique que jouent les OPCVM en matière de sa canalisation vers le secteur productif, ont conduit le législateur à confier le contrôle de ces organismes à divers organes. L'efficacité, la productivité et la transparence sont de nos jours les maîtres mots dans les milieux financiers. Tous les opérateurs se trouvent dans l'obligation de mettre en œuvre des règles plus pertinentes et plus rigoureuses pour gagner cette bataille. L'étude du contrôle des OPCVM, revient à occulter l'un des principes essentiels des marchés financiers : la nécessité de sécurité et de confiance. En effet, les investisseurs ne s'engageront dans des placements financiers, que si les produits proposés offrent des garanties suffisantes. Cette confiance peut être établie par le contrôle exercé sur ces derniers, ce contrôle est réglementaire ou légale, il s'agit du commissaire aux comptes, en tant qu'organe classique des sociétés, le contrôle interne comme atout des OPCVM, le dépositaire comme organe original de ces derniers et enfin l'organe clef de la protection des marchés financiers qui est l'autorité de tutelle. The impressive evolution of industry management over these past fifteen years, including by the use of the techniques for managing and funding innovative and the use of more structured products increasingly complex, has led the industry and of UClTS to live profound changes. Indeed, the public nature of the collective savings and the strategic role of UCITS in the pipe to the productive sector, led the legislature to entrust the control of these agencies in various organs. Efficiency, productivity and transparency are the watchwords of our days in the financial community. All operators are obliged to implement the more relevant and more stringent rules to win this battle. The study of the control of the UCITS, returned to obscure one of the fundamental principles of the financial markets : the need for security and confidence. Indeed, investors commit in financial investments, that if the proposed products offer sufficient guarantees. This trust can be established by the control exercised over thcse last, this control is regulatory or legal, is the Commissioner of accounts, just as classical organ of the companies, the internal control as UCITS asset, the depositary as original body of the latter and finally the body key to the protection of the financial markets is the supervisory authority.
Keywords: Autorité de tutelle; Autorité des marchés financiers; Commissaires aux comptes; Conseil Déontologique des Valeurs Mobilières (CDVM); Dépositaire; Etude comparative; Marché financier; Maroc; Sociétés d'investissement; Valeurs mobilières; Vérification interne

Vergi Hukukunda birleşme, bölünme ve hisse değişimi işlemleri - Göktuna, Hamdi Deniz Ege (Marmara Üniversitesi, 2011)
Kurumların birleşme, bölünme, kısmi bölünme ve hisse değişimi yoluyla yeniden yapılandırılma işlemleri başta ticaret hukuku olmak üzere, rekabet hukuku, sermaye piyasası hukuku ve vergi hukuku gibi birçok hukuk dalını ilgilendiren çok disiplinli bir alandır. Ticaret hukuku, genel olarak yeniden yapılandırma işlemlerinde şirket alacaklarının ve ortaklarının haklarının korunmasını amaçlamaktayken, vergi hukuku söz konusu işlemler sonucunda ortaya çıkan kâr ile ilgilenmektedir. Yeniden yapılanma işlemlerin vergisel maliyeti, bunların önündeki en önemli engeli teşkil etmektedir. Bu sebeple, tüm hukuk sistemlerinde vergisel açıdan tarafsızlığı sağlayıcı hükümler yer almaktadır.Çalışmamızda, özellikle, üye devletler arasındaki ekonomik ilişkilerin artırılarak, ekonomik gelişmenin ve refahın sağlanması yoluyla güçlü bir topluluk yaratma amacı taşıyan Avrupa Birliği Hukuku ve Türk Hukukunda yeniden yapılandırma işlemlerinin vergisel boyutu incelenmiştir. Avrupa Birliği Mevzuatına uyum sağlama çalışmaları çerçevesinde dolaysız vergiler alanında yapılması gereken düzenlemelerden birisi de vergi kanunlarında şirketlerin bölünmesini ve hisse değişimini kolaylaştırıcı, kalıcı mahiyette hükümler getirmek olmuştur. Dolayısıyla Avrupa Birliği Birleşme mevzuatı, tam üyelik sürecindeki ülkemiz açısından önem arz etmektedir.Çalışmamızın birinci bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerinin kavramsal esasları, Kurumlar Vergisi Kanunu, Türk Ticaret Kanunu ve Yeni Türk Ticaret Kanunu ile ilgili Avrupa Birliği mevzuatı çerçevesinde ortaya konulmaya çalışılacaktır. İkinci bölümde, birleşme, bölünme, kısmi bölünme, aktif transferi ve hisse değişimine ilişkin temel Avrupa Birliği düzenlemesi olan Birleşme Direktifi, Avrupa Birliği Adalet Divanı kararları çerçevesinde incelenecektir. Son bölümde ise Türk vergi mevzuatındaki, birleşme, bölünme ve hisse değişimine ilişkin hükümler tereddütlü noktalara da değinilmek suretiyle ele alınacaktır. Sonuç bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerine ilişkin değerlendirmelerimize yer verilmiştir. Transactions concerning the restructuring of companies through mergers, divisions, partial divisions and exchanges of shares relate to a multi disciplinary domain, including commercial law, competition law, capital markets law and tax law. While commercial law generally aims at the protection of rights of company's creditors and shareholders, tax law is mostly interested with the profit generated through these transactions. The tax cost of restructuring transactions, constitutes the main obstacle for those. For this reason, all legal systems include provisions providing tax neutrality regarding these transactions.In this study, we have analysed the tax law dimension of restructuring transactions especially in Turkish Law and Law of European Union which aims at the creation of a strong community through the development of economic relations between member states. Within the context of harmonisation to the European Union Legislation, one of the necessary regulations concerning direct taxes has been the enactment of tax law provisions enabling the division of companies and exchanges of shares thereof. Consequently, EU Merger Legislation is of utmost importance for Turkey as a candidate state.The first chapter of this study presents the conceptual basis of the transactions in question within the context of Corporate Tax Law, Commercial Law and the New Commercial Law and EU Legislation. The second chapter examines the Merger Directive within the framework of jurisprudences of European Court of Justice. The last chapter deals with problematic issues in Turkish Tax and Commercial laws. We conclude by presenting our evaluations based on previous chapters.
Tez N° 291505
Keywords: Avrupa Birliği hukuku; Avrupa Topluluğu hukuku; Birleşmeler; Change; Corporate Tax Law; Değişim; Division of company; European Community law; European Union law; Hisse senedi devri; Hisse senetleri; Kurumlar Vergisi Kanunu; Mergers; Stock transfer; Stocks; Tax harmonisation; Tax law; Vergi hukuku; Vergi uyumlaştırması; Şirket birleşmeleri; Şirket bölünmesi

Reformulating corporate residence: a coherent response to international tax avoidance - Loomer, Geoffrey (University of Oxford, 2011)
This thesis analyzes the concept of corporate residence, with particular reference to the law in the UK and Canada. It explores why corporate residence is relevant in tax policy, how corporate residence is understood in law, and how revenue authorities respond to the use and alleged 'abuse' of residence rules. Part I argues that the residence of taxpayers generally (individual or corporate) remains a relevant factor in international tax design, that taxation of corporations on the basis of residence has some justification, but that there is a disjunction between meaningful residence-based taxation and current definitions of corporate residence in domestic law and tax treaties. The formulations of residence based on incorporation, central management and control, and place of effective management, particularly as applied to multinational enterprises, are considered and are found to be deficient. Part II critically analyzes the major policy responses of the UK and Canadian governments to the exploitation of corporate residence. It argues that key legislative and administrative responses to international tax avoidance activities, for both outbound and inbound investment, are purportedly based on the acceptance of formal corporate residence yet undermine that concept in an effort to impose tax or refuse treaty relief based on where economic interests actually exist. The responses considered are the application of controlled foreign companies legislation to offshore subsidiaries, the invocation of treaty anti-abuse rules with respect to offshore intermediaries, and the use of overarching general anti-avoidance measures to challenge varied structures that rely on offshore entities. These haphazard anti-avoidance rules are overlaid with revenue authorities' indignation at the motivations that underlie many corporate relocations. It is argued that a more coherent approach would be to focus on the objective reality or unreality of corporate establishment, by reformulating corporate residence in domestic law and tax treaties.
Keywords: Economics Law; International business; International taxation; Multinational enterprises; Resident companies; Tax avoidance; Tax planning; Taxation

La fiscalité maritime - Lopez, Cynthia (Aix-Marseille Université, 2011)

Le Système Comptable OHADA : Une réconciliation des modèles « européen continental » et « anglo-saxon » ? - Ngantchou, Alexis (Comptabilité Contrôle Audit, 2011)

A auditoria externa e as demonstrações contábeis no direito comercial - Pereira, Alexandre Demetrius (Universidade de São Paulo, 2010)
A auditoria externa de demonstrações contábeis é um dos instrumentos mais importantes para o desenvolvimento do mercado, pelo fato de adicionar credibilidade e segurança às informações financeiras prestadas pelos agentes econômicos que buscam captar recursos junto ao público investidor. A doutrina jurídica pátria, entretanto, ao contrário do que ocorre em outros países, tem relegado o estudo do assunto a um papel secundário, quase não abordado nas obras nacionais, deixando sua pormenorização integralmente sob o domínio da ciência contábil. Esta postura causa um afastamento do jurista da realidade das circunstâncias em que a auditoria se desenvolve, fazendo com que, pela falta de compreensão das peculiaridades da matéria, haja a aplicação inadequada de muitos institutos a uma realidade específica e, muitas vezes, diversa daquela para as quais referidos institutos foram concebidos. Como a matéria abrange tanto o Direito quanto a Contabilidade, tencionamos fazer aqui uma abordagem conjunta, a fim de possibilitar a comunicação das duas ciências e compartilhar os problemas que o tema apresenta. Passamos em revista a natureza dos principais institutos de auditoria; seu relacionamento e importância na economia; as características jurídicas do contrato, suas obrigações, as partes contratantes e os terceiros interessados; o desenvolvimento contábil de sua execução; e seu relacionamento com os sistemas de governança corporativa. Além disso, verificamos as atuais tendências quanto ao sistema de riscos e responsabilidade civil do auditor, matéria amplamente discutida no âmbito internacional.
Keywords: Accounting and legal repercussions; Audit contract; Audit externe; Auditoria; Auditoria externa; Auditors liability; Balance comptable; Balanço contábil; Comptabilité; Contratos; Demonstração financeira; Direito comercial; Droit commercial; Etat financier; External audit; Governança corporativa; Responsabilidade civil; Responsabilité de l'auditeur

National legislative systems and foreign standards and regulations: The case of International Financial Reporting Standards adoption - Dima, Bogdan; Dima (Cristea), Stefana Maria; Moldovan, Nicoleta; Pirtea, Marilen Gabriel (MPRA Paper, 2010)
This study is focused on the linkages between the legislative families as descriptors of national legislative systems and International Financial Reporting Standards (IFRSs) issued by the International Accounting Standards Board (IASB). We consider such analysis as a case study for the more general issue of explaining the preferences of national regulators in the adoption of foreign norms, rules, standards and practices. By using a dataset of 162 jurisdictions and dummy variables designed to capture the current stage of IFRSs adoption and, respectively, the taxonomy of their legislative systems, we find that a full IFRSs adoption is more likely to occur in countries which have principles-based on legislative mono-systems. In addition, we observe that a strong rule of law, with an effective mechanism of property rights reinforcement, as well as the pre-adoption existence of a pro-growth set of public policies can contribute to the encouragement of IFRSs adoption.
Keywords: IFRSs adoption; Legislative families

Teoria palco-platéia: a interação entre regulação e autorregulação do mercado de bolsa - Calabró, Luiz Felipe Amaral (Universidade de São Paulo, 2010)
A tese a ser defendida é a de que a autorregulação institucionalmente estruturada e legitimada pela regulação é um eficiente arranjo para tratar as falhas e riscos inerentes ao mercado de bolsa. O trabalho se inicia com a descrição da atual estrutura da autorregulação do mercado de bolsa, destacando seu novo formato institucional decorrente do processo de desmutualização e abertura de capital das entidades administradoras do mercado de bolsa e concluindo pela necessidade de adoção de novas perspectivas sobre o tema que transcendam o aparente antagonismo entre concepções liberais e intervencionistas. A partir dessa premissa, o trabalho apresenta uma visão panorâmica da evolução histórica da autorregulação do mercado de bolsa e considerações sobre os conceitos de autorregulação em outras áreas do conhecimento, a fim de identificar suas variações e seus elementos mais marcantes que constituirão a base a partir da qual serão apresentadas as novas perspectivas de análise do tema. As perspectivas propostas enfocam a natureza jurídica da autorregulação do mercado de bolsa como atividade paraestatal destinada a concretizar o modelo teórico neoclássico de justa formação dos preços segundo a livre atuação das forças de oferta e demanda e, também, melhorar os padrões de conduta praticados no mercado. Para tanto, o trabalho propõe que as decisões tomadas no âmbito da autorregulação se pautem por critérios materiais baseados nas premissas teóricas da concorrência perfeita e na exigência de cumprimento dos deveres derivados da boa-fé objetiva (informação, lealdade e proteção). Por fim, é apresentada uma especulação teórica, preliminar e não definitiva, denominada teoria palco-platéia, que visa situar o desenvolvimento da estrutura de autorregulação do mercado de bolsa como parte de uma questão essencial de interação entre indivíduo e sociedade representada nas diversas situações comunicativas envolvidas nos processos decisórios individuais e coletivos que modelam os padrões de conduta e as instituições públicas e privadas.
Keywords: Autorégulation; Bolsa de valores; Direito comercial; Equities; Exchange market; Marché boursier; Mercado de capitais; Mercado futuro; Regulation; Régulation; SRO; Securities; Self-regulation; Self-regulatory organizations; Stage-audience; Stock Exchange

The suitability of the South African corporate tax regime for the use of South African resident intermediary holding companies - Legwaila, Thabo (University of Pretoria, 2010)
An Intermediary Holding Company (“IHC”) is a company that is interposed between an ultimate holding company and the operating subsidiaries of a group of companies. The IHC operates at an international level such that either its holding company or its subsidiaries or both are located in a country foreign to the IHC. Its main functions are to acquire, manage and dispose of the assets of the group of companies and to facilitate structural flexibility of a group of companies. Investors have tax and non-tax reasons for conducting business using an IHC, and, depending on the reasons, they determine the location of the IHC based on the characteristics of potential host countries. This thesis analyses the suitability of the South African corporate tax regime for the use of South African-resident Intermediary Holding Companies. The South African government has the objective of promoting South Africa as a gateway for investment in Africa and for this reason the present research is important. Such an objective could be adversely affected by a corporate tax regime that is not suitable for the operations of an IHC. Furthermore, the Katz Commission recommended in 1997 that South Africa should consider introducing a regime that is suitable for the location of holding companies. In discharging its functions the IHC attracts liability for corporate income tax, capital gains tax, controlled foreign company tax and dividends tax. It also exposes itself to anti-avoidance measures such as thin capitalisation and transfer pricing provisions. The existence of such taxes and anti-avoidance measures in the tax system of a country may deter investors from locating an IHC in such country. Exchange control regulations could also adversely affect the ability of the IHC to perform its functions effectively, as their purpose is to restrict the movement of capital out of the country. The South African legal system contains all these taxes and anti-avoidance measures as well as exchange control provisions. However, it also contains tax instruments that alleviate the tax burden on an investor using an IHC such as the participation exemption, advance tax rulings and a network of tax treaties. Against this background this thesis analyses the South African corporate tax system to determine whether it is suitable for locating an IHC. In the analysis, a comparative study is done of the tax systems of two of the most effective IHC host countries, namely the Netherlands and Mauritius. In addition, a brief discussion of the special features contained in the tax systems of Belgium, Ireland and the United Kingdom outlines why these jurisdictions are not necessarily successful in attracting IHCs. The thesis also discusses harmful tax practices and the attitude of the international community towards countries that engage in harmful tax competition in order to determine the limits to which a country should use the tax system to attract investment. Finally, the thesis makes recommendations as to what adjustments could be made in order to enhance the suitability of South Africa to host an IHC. The thesis recommends a special dispensation as regards corporate income tax and exchange control that would apply to wholly-owned South African companies that own foreign subsidiary shares and loans that consist of 80% of the gross asset total of these companies.
Keywords: Intermediary Holding Company; South Africa; Tax; Taxation

On the Development of West African Accounting System - Moussa, Boka (International Journal of Business and Management, 2010)
The authorities of the West African Economic and Monetary Union UEMOA fully understand that accounting plays the significant role in the process of economic development and regional integration in the member states. They decided to establish a common new accounting system, called West African Accounting System (SYSCOA). The accounting system has been developed on the initiative of the Central Bank of West African States
Number: 5

La régulation des marchés financiers dans l'espace OHADA - Keuffi, Daniel Ebénézer (Université de Strasbourg ; Université Dschang, 2010)
L'apparition des marchés financiers dans le paysage économique et financier des États membres de l'espace OHADA vers la fin des années 1990 a débouché sur la nécessité de mettre sur pied des règles et des structures d'encadrement à la fois nouvelles et fonctionnelles. Soucieux de faire des marchés financiers des facteurs clés de leurs politiques de développement, les pouvoirs publics se sont très tôt imposés comme des maillons incontournables des processus de création et de fonctionnement de ces marchés. Cette omniprésence des pouvoirs publics a contribué à l'émergence d'un schéma novateur et sans précédant, à savoir la mise sur pied de marchés financiers et d'organes d'encadrement à vocation communautaire. Toutefois, pour atteindre l'efficacité recherchée, les nouvelles structures d'encadrement doivent trouver à s'articuler avec les dispositifs juridiques et institutionnels existant tant aux niveaux régionaux qu'aux niveaux nationaux. De même, un juste équilibre doit être trouvé entre les intérêts légitimes des investisseurs étrangers et les ambitions de développement économique des États concernés. The appearance of financial markets in the economic and financial landscape of the Member states of the OHADA space towards the end of 1990s resulted in the necessity of setting up rules and supervisory structures at once new and functional. Worried of making financial markets a leading instrument of their development policies, public authorities very early positioned themselves as essential actors of the processes of creation and functioning of these markets. This omnipresence of public authorities contributed to the emergence of an innovative and unprecedented scheme: The setting up of financial markets and supervisory structures with community vocation. However, to achieve the desired efficiency, the new supervisory structures must be adapted to the legal and institutional arrangements existing both at regional and national levels. Also, a just balance must be found between the legitimate interests of foreign investors and the ambitions of economic development of the concerned States.
Cotutelle : Université Dschang et Université de Strasbourg

Impact of Macro and Micro Governance Structures on Earnings Management - Houqe, Muhammad Nurul (Victoria University of Wellington, 2010)
This study examines the macro and micro level determinants of the quality of reported earnings. The prior literature suggests that both micro and macro variables impact on discretionary accruals choice in managing earnings. However, most of the studies on earnings management have been single country studies that have focussed only on micro variables as all firms within the samples examined have been subject to the same interplay of macro economic, legal, cultural and institutional frameworks. This study addresses this gap in the literature by using a sample of 156,906 firm year observations from 63 countries over the period 1998-2007 to examine the role of thirteen micro and macro variables in determining earnings quality. The macro variables studied include legal enforcement, political system, and control of corruption, culture and adoption of IFRS. Earnings management is estimated using the modified Jones model (Dechow et al. 1995) in a cross section (DeFond and Jiambalvo 1994; Francis et al. 1998). The results of the study indicate that macro and micro level variables have a strong impact on earnings management behaviour and thus earnings quality. The limits imposed by a country's legal, cultural and institutional setting on managerial discretionary accruals choices, strongly impact the quality of reported earnings. Future research on earnings management should therefore control both micro and macro level variables.
Keywords: Earnings management; Macro governance; Micro governance

Le traitement fiscal du financement des sociétés dans les relations intragroupes en droit comparé français, allemand et camerounais. - Tassi, Jules Alain Petengoue (Trajectoires. Revue de la jeune recherche franco-allemande, 2009)
Un des problèmes les plus fréquents auxquels les entreprises se confrontent est sans doute celui relatif à la dotation des moyens financiers. Le problème de financement des entreprises est plus qu’actuel au regard du scandale des subprimes aux USA en 2007 ayant conduit au crash boursier de septembre 2008 mieux encore, l’affaire Maldoff. Ce phénomène financier qui touche sans exception toute la vie économique n’a pas pour autant épargné les groupes de sociétés. En fait, les groupes constituent...

Les fondements épistémologiques du mouvement Law & Economics - Lanneau, Régis (Université Paris 10, 2009)
La présente thèse vise à montrer que l'analyse économique du droit est une philosophie du soupçon, un système logique d'interprétation des phénomènes juridiques qui peut nous apporter des connaissances si nous prenons bien en compte sa qualité de système d'interprétation. Les propositions économiques étant largement analytiques, elles peuvent nous informer uniquement par les questions qu'elles suscitent. Le raisonnement économique est tout d'abord un code de perception qui se fonde sur deux concepts : la rationalité et l'efficience. Ce code de perception nous donne des intuitions qui « semblent » pertinentes pour l'étude du droit (à la fois sur ce qu'est le droit l'approche du raisonnement juridique). Se pose alors la question de ce qui fait la « validité » des connaissances proposées. Des considérations a priori ou des considérations empiriques semblent insuffisantes pour rendre compte de la pertinence de ce type d'analyse. Nous proposons finalement une approche en termes de renversement : ce n'est qu'en que le code n'est qu'un code et en confrontant ses propositions à d'autres points de vue que nous pouvons espérer gagner des « connaissances ». L'analyse économique du droit pose aussi la question de l'analyse juridique du droit.
Keywords: Analyse économique du droit; Droit (aspect économique); Droit (philosophie); Logique juridique; Pragmatisme (philosophie); Épistémologie des sciences sociales

Estudo das condições de regulação das normas do IASB em países membros da Organização para a Harmonização do Direito dos Negócios em Africa (O.H.A.D.A) - Arrio, Kouadio (Universidade de Brasília, 2009)
O International Accounting Sstandards Board-IASB vem buscando meios de regular a atividade contábil pela adoção de pronunciamentos contábeis International Financial Reporting Standard-IFRS para proteger os parceiros econômicos e facilitar o funcionamento do mercado de capital no mundo financeiro. Neste processo mundial de convergência internacional, vários países do continente africano parecem indiferentes. Entretanto, dezesseis países da África Ocidental e Central formaram o bloco econômico: a Organização para a Harmonização do Direito de Negócios na África-OHADA, que criou um Sistema contábil de aplicação comum - o Sysco-OHADA. Antigas colônias francesas, esses países ficaram muito tempo fechados e mal conhecidos no exterior, bem como suas práticas contábeis. Isso levanta a pergunta: quais são as condições econômicas, políticas e sociais dos países da OHADA frente à regulação da contabilidade internacional? O objetivo principal deste estudo é analisar as condições de regulação contábil interna dos países-membros da OHADA ao se alinhar às normas contábeis internacionais emitidas pelo IASB. Para alcançar este objetivo, foi analisado o ambiente legal e regulamentar do bloco OHADA; foi comparado o referencial conceitual do Sysco-OHADA e o do IASB; algumas normas, bem como o âmbito sócio-econômico da OHADA, com os demais países que possuem processo de convergência avançado. As análises mostraram que a contabilidade da OHADA é de tipo europeu-continental baseada em regras. A estrutura conceitual do Sysco-OHADA diverge do IASB em vários níveis e suas normas apresentam menos detalhamento e é sujeito a interpretações diversas. O bloco OHADA apresenta um mercado de ações fraco, um baixo nível de desenvolvimento humano, um nível de abertura comercial fechado em relação aos demais países comparados. O nível de desenvolvimento econômica e social do bloco OHADA não pode proporcionar uma convergência às normas IFRS em curto prazo.
Keywords: Contabilidade internacional; Convergência; Framework; IASB; Normas internacionais de contabilidade; Regulação Contábil; Sistema Contábil OHADA

Libyan Attitudes towards Islamic Methods of Finance: An Empirical Analysis of Retail Consumers, Business Firms and Banks - Gait, Alsadek Hesain Abdelsalam (Griffith University, 2009)
Libya is a predominately Muslim country where Islamic finance has not yet been established. However, given the current extensive program of financial reform in Libya and the rapid growth and appeal of Islamic finance in comparable economies, there is growing pressure for a system of Islamic finance to be provided. There is then a pressing need for research into the prospects for Islamic finance from a consumer and provider perceptive to inform this debate and thereby meet the needs of policymakers, financial service providers and prospective users. Accordingly, this study of Libyan attitudes towards Islamic methods of finance, the first study attempted in the Libyan context and one of few studies globally, applies a model derived from the Theory of Reasoned Action to analyse attitudes towards Islamic finance. The particular focus is to understand how the Theory of Reasoned Action can be used for predicting and understanding attitudes towards the potential use of Islamic methods of finance by Libyan retail consumers, business firms and banks. Four main research questions are posed to address this objective. First, does awareness of Islamic methods of finance influence attitudes towards the use of Islamic finance? Second, do socioeconomic, demographic and other factors influence attitudes towards Islamic finance? Third, what are the principal motivating factors towards the potential use of Islamic finance? Finally, is religion the major influence on the likelihood of engaging in Islamic finance? Three surveys of 385 retail consumers, 296 business firms and 134 bank managers in Libya are conducted in 2007/08 to achieve this objective. Descriptive analysis and multivariate statistical analysis (including factor analysis, discriminant analysis and binary logistic regressions) are used to analyse the data. The principal findings are that awareness of Islamic methods of finance and socioeconomic, demographic and business characteristics are key determinants of the likelihood of the use of Islamic finance. Further, religion plays a key, though not the only, role in influencing these attitudes. The thesis findings are of key importance in informing future financial industry practice and financial policy formation in Libya.
Accepted: 2018-01-23T02:48:08Z
Keywords: Finance; Financial policy; Financial reform; Islam; Islamic finance; Libya

Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, Glen (Oxford University, 2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.
Keywords: Family taxation; Husband and wife; Income splitting; Settlements; Taxation

Performances des entreprises cotées et perspectives de croissance économique : cas de la bourse régionale des valeurs mobilières de l'Afrique de l'Ouest - Zogning Nguimeya, Joseph Félix (Université du Québec à Montréal, 2009)
Les pays africains de la zone franc ont entrepris, il y a maintenant deux décennies, des réformes de leurs secteurs financiers, avec pour ambition non seulement de restaurer les équilibres nécessaires à leur efficacité et la confiance des agents économiques envers les institutions financières, mais aussi de favoriser la mobilisation des épargnes et la diversification des canaux de financement. L'objectif final étant la relance d'une croissance économique stable et durable. Au sein de la zone UEMOA (Union Économique et Monétaire Ouest-Africaine), le projet majeur au coeur de ces réformes fut la création d'un marché financier commun dont la mission est de doter les entreprises des moyens de financement à long terme, qui leur permettraient de réaliser leurs projets les plus productifs et d'accroitre leurs performances. L'autre mission dévolue à ce marché est d'attirer des capitaux étrangers dans la sous-région. Notre étude a pour but de déterminer si, une décennie après sa création, le marché financier a atteint ses objectifs en termes d'amélioration des performances des entreprises et de relance de la croissance économique. Globalement, nous observons que les entreprises cotées à la Bourse Régionale des Valeurs Mobilières (Place boursière du marché financier de l'UEMOA) ont vu leurs performances opérationnelles s'améliorer, notamment au cours de la seconde moitié de la décennie. Le développement du marché boursier semble également avoir eu un impact positif sur la croissance économique de la Côte d'ivoire, Pays phare de l'Union, qui détient 34 des 38 entreprises cotées. Cependant, le marché n'a pas réussi à attirer des capitaux étrangers; mais à l'inverse, l'écrasante majorité des entreprises qui lèvent des fonds sur le marché financier de UEMOA sont des filiales des multinationales occidentales. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Introduction en bourse, Croissance économique, Performance, Marché financier, Entreprises cotées.
Place: Montréal (Québec, Canada)
Keywords: Croissance économique; Entreprises cotées; Introduction en bourse; Marché financier; Performance

Le déséquillibre des relations de crédit entre la banque et les usagers - Sow, Djibril (Université Cheikh Anta Diop, 2008)
L’examen des relations de crédit entre la banque et les usagers révèle que ces dernières sont déséquilibrées au profit du banquier. Le déséquilibre en question est essentiellement un déséquilibre en pouvoir, fondé principalement sur la nature même de la convention de crédit en tant que contrat d’adhésion et contrat intuitu personae. À l’aide de l’approche systémique, de l’analyse, de la synthèse et de la ponctuation, sans oublier la méthode comparative, notre étude a consisté à l’examen des différentes manifestations de ce déséquilibre et des réactions qu’il a suscitées. Ce déséquilibre se manifeste d’abord par la prépondérance de la volonté du banquier, conséquence du déclin de l’autonomie de la volonté. Cette prépondérance se manifeste aussi bien dans les préalables, que dans la naissance des relations de crédit. Dans les préalables, elle s’exprime à travers l’exigence de compte en banque ainsi qu’à travers l’exigence de solvabilité, dont la satisfaction est une condition sine qua non vers la naissance des relations de crédit. Ensuite, dans la naissance desdites relations, la prépondérance de la volonté du banquier réside dans la détermination unilatérale des clauses de la convention de crédit par ce dernier. L’usager dont le choix est également limité par plusieurs contraintes, est réduit à adhérer à ces clauses, d’autant plus que le dernier mot revient au banquier, compte tenu de l’absence de droit au crédit tenant à l’intuitus personae. Cette prépondérance de la volonté du banquier se concrétise par la conclusion de la convention de crédit. Au delà de la prépondérance de la volonté du banquier dans la mise en place des relations de crédit, le déséquilibre de ces dernières se manifeste aussi par le rôle considérable des techniques et pratiques bancaires qui, n’étant pas neutres, constituent une forme de domination indirecte du banquier. D’abord, les techniques de gestion bancaire dominent les relations de crédit aussi bien objectivement, que subjectivement devant une impuissance marquée de l’usager. Ensuite, les usages bancaires, forgés par la pratique bancaire, reflètent la volonté du banquier qui est à leur source. Ils dominent les relations de crédit à plusieurs niveaux, malgré certaines limites tenant à l’ordre public. Le déséquilibre des relations de crédit, compte tenu de ses conséquences, a nécessité des réactions. Celles-ci consistent dans sa modération aussi bien par les règles du droit commun, qu’à travers celles du droit du crédit. Dans la première hypothèse, la modération s’obtient par les obligations et la responsabilité du banquier, face à celles de l’usager. Dans la seconde hypothèse, elle s’obtient à travers des règles du droit du crédit protégeant les usagers ; à côté des politiques publiques de protection spécifique des usagers les plus vulnérables en matière de crédit. L’étude du déséquilibre des relations de crédit entre la banque et les usagers permet de conclure que ce dernier tient à l’essence même de la convention de crédit. C’est pourquoi les réactions tentant d’y faire face n’aboutissent qu’à sa modération, ce qui l’atténue fortement. De ce constat, on peut estimer que l’amélioration des relations de crédit et de l’accès au crédit nécessite une révision de la convention de crédit.
Keywords: Banque; Client; Crédit

As novas estruturas organizacionais das bolsas - Dutra, Marcos Galileu Lorena (Universidade de São Paulo, 2008)
O presente trabalho investiga as novas estruturas organizacionais das bolsas de valores e das bolsas de mercadorias e futuros, implementadas após os processos de desmutualização. É feita uma análise da importância das bolsas para o desenvolvimento econômico, bem como do seu papel de entidades auto-reguladoras. São ainda apresentados os principais fatores que motivaram a conversão das bolsas de associações mutualísticas para sociedades anônimas, bem como as conseqüências dessa alteração organizacional. O trabalho explora também as alterações regulamentares ocorridas no exterior, que buscaram evitar o surgimento de conflitos de interesses entre o papel de entidades auto-reguladoras das bolsas e seu objetivo de maximização do valor das ações. Realiza-se, por fim, uma análise crítica da Instrução CVM n.O 461/07, norma editada pela Comissão de Valores Mobiliários (CVM) que regula a organização, o funcionamento e as atividades das bolsas no Brasil. O trabalho conclui que a norma editada pela CVM utiliza diversos mecanismos de controle que objetivam evitar a ocorrência de conflitos de interesses, com o estabelecimento de práticas de governança corporativa internamente às bolsas, na esteira das experiências observadas em outros países. The present work examines the new organizational structure of the stock and derivatives exchanges, implemented after their demutualization process. It analyses the importance of the stock exchange for the economical development, as well as its role as self-regulatory organization. There are also presented the main factors that motivated the conversion of the stock exchange, from mutual associations to corporations, as well as the consequences of this organizational change. The work also explores the regulatory changes made in foreign countries, that aim to avoid the conflict of interests between the role of the exchanges as selfregulatory entities and their goal of maximizing value. Finally, a critical analysis is made, regarding CVM´s Instruction n.º 461/07, rule issued by the Brazilian Securities and Exchange Comission (Comissão de Valores Mobiliários - CVM) that deals with the structure and functioning of the Brazilian exchanges. The work concludes that the rule issued by the CVM uses many mechanisms of control that aim to avoid the conflict of interests, settling high level corporate governance practices inside the stock exchange, in accordance to international regulatory standards.
Keywords: Bolsa de valores; Bourse; Derivatives Exchange; Governança corporativa; Mercado de capitais; Sociedade por ações; Stock Exchange; Valeurs mobilières; Valores mobiliários

La responsabilité bancaire à l'égard des entreprises en difficulté - Capoen, Anne-Laure (Université Toulouse 1 Capitole, 2008)
L'article L 650-1 du Code de commerce, issu de la loi de sauvegarde du 26 juillet 2005, procède à un allègement de la responsabilité du banquier : celui-ci n'est plus responsable des préjudices subis du fait des concours accordés à une entreprise en difficulté. Si la légitimité de la mesure a été remise en cause, elle répond néanmoins à un objectif d'intérêt général : promouvoir la fourniture de crédit. La recevabilité de l'action en responsabilité est toutefois admise dans trois cas : la fraude, l'immixtion caractérisée dans la gestion du débiteur et la prise de garanties disproportionnées, qui constituent les trois seuls cas d'ouverture de l'action pour soutien abusif. Ainsi les banquiers bénéficient-ils désormais d'une immunité dont les causes de déchéance tendent à la moralisation du droit des affaires. Mais cet allègement ne saurait concerner les autres hypothèses de mise en cause de la responsabilité du banquier. Celui-ci reste responsable en cas de rupture abusive de crédit ou de non respect de ses obligations contractuelles en particulier envers les emprunteurs non avertis. La direction de fait est également source de responsabilité civile. Enfin, la fourniture de moyens ruineux pour éviter ou retarder l'ouverture d'une procédure collective engage la responsabilité pénale du banquier, devenu complice. Les conséquences de la responsabilité sont en outre particulièrement dissuasives, en particulier la nullité des garanties constituées. Cet allègement de la responsabilité constitue donc une chance pour les banquiers de s'investir dans le financement des entreprises, encore faut-il que cette occasion soit saisie, sans toutefois tomber dans l'excès de crédit.
Keywords: Banques; Crédit; Droit des affaires; Entreprises en difficulté; France; Responsabilité

Crossing the Wires: the Interface between Law and Accounting and the Discourse Theory Potential of Telecommunications Regulation - Carter, David Bernard (Victoria University of Wellington, 2008)
Regulating telecommunications is complex: international experience indicates that there is no 'successful' regulatory framework due to the balancing of industry and regulatory interests (Laffont & Tirole, 2000, p. 13). The New Zealand 'light-handed' regulatory experiment failed and the 1999 General Election presented an opportunity for change in telecommunications. The Labour-led Government in implementing a policy of 'responsible re-regulation' enacted the Telecommunications Act 2001, signalling the passage of "landmark telecommunications legislation ..." (Swain, 2001d). Within the Telecommunications Act 2001, 'cost' assumed a central regulatory role. It is this move to cost that this thesis considers in identifying, developing, and critiquing the interface of law and accounting. The thesis examines the increasing call for accounting information in law and regulation by interrogating the use, presentation, and reception of accounting to examine the interface between law and cost in the regulation of telecommunications. The Telecommunications Act 2001 incorporates total service long run incremental costing as the 'costing technique' for interconnection access and annual net costing for the Telecommunications Service Obligation. Through interrogating 'cost' as an accounting technology, in contrast to the economic and legal conception of cost as a simple, objective concept, the thesis illustrates the role of cost at methodological, technical, and political levels, and the challenges that this poses for telecommunications regulation. The thesis articulates the relevance of discourse theory to the interface of law and accounting. Consequently, the thesis investigates the formation and discursive enunciation of standpoints of political identities characterised by antagonism and uncertainty. This includes identifying attempts by interested parties, including industry actors, stakeholders, and the Government and its agents, to articulate 'new' discourses centred on nodal points around 'cost'. The rhetorical analysis examines how actors articulate the metaphorical element of 'cost' in agitating for particular costing methods to be included in the legislation. The empirical analysis examines the process of rhetorical condensation as arguments for and against the incorporation of total service long run incremental costing and net costing came to signify the complete failure of the light-handed regulation. Then, by examining the politics following the enactment of legislation, this condensation is unpacked. The analysis of the contestation over interpreting and implementing the regulation illustrates displacement of the 'common' signifier resulting in confusion and disappointment in relation to the aims of the new regulatory regime.

Bağımsız denetim sözleşmesi - Köksal, Aytaç (Ankara Üniversitesi, 2008)
Bağımsız denetim sözleşmesi, bağımsız denetçiler ile denetime tabi müşteriler arasında yapılan bir sözleşmedir. Bağımsız denetim sözleşmesi, düzenlemelerde belirtilen unsurları içermelidir. Bağımsız denetçi ile denetim müşterisi, sözleşmenin unsurları üzerinde anlaşmalıdırlar. Bir bağımsız denetim sözleşmesi yapıldığında, bağımsız denetçiler ile denetim müşterileri karşılıklı borç altına girerler.Bağımsız denetçi, denetim müşterisinin finansal tablolarını denetleme ve finansal tabloların, finansal raporlama standartları ile düzenlemelere uygunluğu konusunda bir görüş açıklama borcu altındadır. Bağımsız denetçi, denetimi yürütürken, uluslararası denetim standartlarını, etik standartları ve düzenlemeleri dikkate almalıdır. Bağımsız denetçiler, bağımsız denetim faaliyetinde her zaman mesleki özeni göstermek zorundadırlar. Eğer, denetim raporu gerçeği yansıtmaz ise, bundan zarar gören denetim müşterisi ile üçüncü kişilerin uğradıkları zararlardan, bağımsız denetçiler sorumlu olurlar. Bağımsız denetçi, ayrıca, bağımsız denetim raporunu zamanında denetim müşterisine teslim etmelidir. Bunun yanında, bağımsız denetçi, düzenlemelerde belirtilen süre içerisinde çalışma kâğıtlarını saklamalılar ve bu süre sona ermeden, çalışma kâğıtlarını yok etmemeli veya atmamalıdırlar. Bağımsız denetçi, denetim müşterisine ait sırları açıklamamalı, kendisinin veya bir diğer kişinin yararına kullanmamalıdır.Denetim müşterisi, bağımsız denetçilere, denetim ücretini ödemeli ve ayrıca, denetim ile ilgili kayıt, belge ve diğer bilgileri bağımsız denetçiye vermelidir. The independent audit agreement is made between independent auditors and the clients who are dependent on audit. The agreement should include terms which are showed by regulations. The auditors and the audit clients must agree on the terms of the agreements. When to be acted the agreement, the auditors and the client? have mutually liablity.The auditors are liable to audit the clients? financial statements and to express an opinion on if the financial statements are suitable the financial reporting standards and the regulations. While performing audit, the auditors should observe in international auditing standards, the ethical standards and regulations. The auditors should always have a duty to provide professional care when performing audit. If the auditors prepare a misleading audit reports, they will liable to the clients and third parties because of their loss was incurred. Also, the auditors should deliver the audit report to the client on time which they agree on. Besides, the auditors should save the audit documentation some time which is showed by regalitations and shouldn?t the delete and discard audit documentation before the end of that time. The auditors also shouldn?t disclose confidential information of the clients? or not use this information for the personal or the other persons? advantage.The audit clients? pay the audit fee and also give the records, documentation and other information requested in connection to with the audit to the independent auditors. Finally, when the auditors deliver the audit report to, the audit clients should accept it.
Keywords: Audit reports; Auditing standards; Banka hukuku; Banking law; Bağımsız denetim; Bağımsız denetim kuruluşları; Bağımsız dış denetim; Capital Market Law; Commercial Code; Commercial law; Denetim raporları; Denetim standartları; Independent audit; Independent auditing companies; Independent external auditing; Responsibility; Sermaye Piyasası Kanunu; Sorumluluk; Ticaret Kanunu; Ticaret hukuku

Recentrage du cadre comptable, durcissement de l'environnement fiscal et persistance de la gestion des données comptables : Une étude du comportement des Petites et Moyennes Entreprises camerounaises - Ngantchou, Alexis (2008)
Dans cette communication, nous postulons l'hypothèse de la manipulation des données comptables comme stratégie de contournement adoptée par les PME dans un environnement fiscal répressif. Par rapport à l'environnement spécifique des PME camerounaises présenté, l'étude se situe quelques années après l'adoption d'un nouveau cadre comptable, en l'occurrence le système comptable OHADA. Deux conclusions importantes méritent d'être immédiatement présentées. En premier lieu et conformément aux prédictions de Watts et Zimmerman, la taille est un facteur susceptible de favoriser l'instrumentalisation des données comptables. En second lieu, le type d'activité exercé conditionne la capacité à manipuler les données.
Keywords: Aménagement du cadre comptable; Durcissement de l'environnement fiscal; Instrumentalisation des données comptables; PME

Generalklausul mot skatteflykt - Rosander, Ulrika (Internationella Handelshögskolan, 2007)
Skatteflykt motverkas i många rättssystem genom åtgärder på olika nivåer. I Sverige är en av de metoder som används en lagstiftad generalklausul mot skatteflykt, skatteflyktslagen. Såväl rättssäkerhet som skattesystemets effektivitet anses vara grundläggande värden att upprätthålla i det svenska skattesystemet. Skatteflyktsproblematiken innebär dock att dessa båda värden i vissa situationer inte samtidigt kan uppfyllas fullt ut, vilket innebär att ett rättsligt område skapas där det blir nödvändigt att göra kompromisser och avvägningar. Det är den här balansen som är den stora utmaningen gällande åtgärder mot skatteflykt och som blir mycket tydlig gällande skatteflyktslagen. Avhandlingen analyserar generalklausuler mot skatteflykt ur ett rättssäkerhets- och effektivitetsperspektiv. Denna analys genomförs i form av en komparativ studie av Sveriges, Kanadas och Tysklands generalklausuler mot skatteflykt. Användandet av en generalklausul jämförs också med användandet av en praxismetod, vilket är den andra repressiva metoden mot skatteflykt som är frekvent förekommande i olika rättssystem världen över. Det konstateras att det är många olika frågor vid sidan av den konkreta rekvisitkonstruktionen och tillämpningsområdet som påverkar vilken rättssäkerhet och effektivitet som en generalklausul mot skatteflykt uppnår. Hur domstolssystemet ser ut, vilken inställning som finns till lagtolkning och hur domstolarna och skattemyndigheten väljer att tillämpa klausulen är exempel på mer generella frågor som har stor betydelse. Men även t.ex. relationen till andra metoder mot skatteflykt, möjligheten att erhålla förhandsbesked och vilka administrativa specialregler som används påverkar. I avhandlingen framför författaren sin uppfattning om vilka områden som är av störst vikt att utveckla i svensk rätt för att stärka skatteflyktslagens rättssäkerhet och effektivitet i framtiden.
JIBS Dissertation Series ; 40 URN: urn:nbn:se:hj:diva-911 OAI: oai:DiVA.org:hj-911 DiVA, id: diva2:4664
Keywords: Fraude fiscale; Skatterätt; Tax fraud; Tax law

Quinze ans de restructuration bancaire dans la CEMAC : qu’avons-nous appris ? - Avo, Désiré; Eyeffa Ekomo, Sylvie Marie-Louise (Revue d'économie financière, 2007)
Les pays de la Communauté économique et monétaire de l’Afrique centrale (CEMAC) ont connu, à partir du début des années 1980, une grave crise économique. Les conséquences de celle-ci se sont traduites, sur le secteur bancaire, par une dégradation rapide et brutale du portefeuille des banques. En réponse à cette crise, les autorités monétaires, avec l’appui de la communauté financière internationale ont engagé une politique de restructuration bancaire. Cette politique avait pour objectif d’assurer un retour à la stabilité bancaire en améliorant les circuits de financement. L’objectif de cet article est de montrer, après avoir présenté les différentes réformes qui ont été mises en oeuvre, que les restructurations bancaires, au lieu d’assurer le financement de l’économie, ont plutôt conduit à des paradoxes dont trois sont particulièrement développés. Il s’agit de : la surliquidité et le rationnement du crédit ; la concentration bancaire et le développement de la microfinance et enfin l’internationalisation bancaire sans développement des innovations financières. Fifteen years of banking restructuring in CEMAC : what have we learnt ? Member countries of the Central African Economic and Monetary Community (CEMAC) experienced a severe economic crisis since the 80’ s. As a consequence of this prolonged crisis, the portfolio of commercial banks dramatically deteriorated, therefore pushing monetary authorities and international community to envisage a restructuring strategy for the banking sector. The aim of this strategy was to stabilize the banking sector by improving financing channels and mechanisms. In this paper we show that the reforms implemented to restructure the banking sector, far from having improved financing mechanisms, have led to the emergence of three paradoxes : excessive liquidity of the system coupled with credit rationing, banking concentration and contemporaneous development of microfinance structures and foreign penetration in the banking sector without development of financial innovations.

Accounting for financial instruments: An analysis of the determinants of disclosure in the Portuguese stock exchange - Lopes, Patrícia Teixeira; Rodrigues, Lúcia Lima (The International Journal of Accounting, 2007)
In this paper we analyse the determinants of disclosure level in the accounting for financial instruments of Portuguese listed companies. Considering the mandatory adoption of International Accounting Standards after 2005, our ultimate objective is to analyse the characteristics of companies that are closest to the disclosure requirements of IAS 32 and IAS 39. We have constructed an index of disclosure comprising 54 items based on IAS 32 and 39 disclosure requirements and computed the index score for each Portuguese listed company based on the analysis of the companies’ annual reports. We tested the relation between the index score and several firm-specific characteristics: size, industry, auditor type, listing status, multinationality degree, relationship shareholders/creditors and importance of shareholders. We conclude that larger companies and companies listed in more than one exchange market show higher levels of disclosure, meaning that they are closer to IAS 32 and 39 requirements. We argue that the agency theory, the signalling theory and the political costs theory do not fully explain Portuguese reality, where there is a large degree of family ownership and bank-oriented financing policies. We therefore advocate that the introducing variables related to specific characteristics of Portuguese companies and managers, in the context of other theoretical frameworks, notably the contingency theory, brings important insights to this type of analysis.

Le démarchage par les établissements de crédit - Forner, Thierry (Université Jean Moulin Lyon 3, 2006)
Le démarchage par les établissements de crédit ne peut se résumer à l'étude de la seule loi de 2003, réformant le démarchage bancaire et financier. En effet, ce texte n'intègre nullement dans son champ d'application les produits et services non bancaires ainsi que les produits d'assurances que distribuent pourtant les banques. Des règles différentes peuvent donc trouver à s'appliquer, alternativement selon l'objet du démarchage, ou par cumul, lorsqu"il précède par exemple une vente à distance, transfrontière. Avec la transposition en France de la directive « vente à distance de services financiers », cette superposition de régimes protecteurs n'est plus justifiée. En effet, la protection de la personne démarchée est assurée, comme en matière de vente à distance, par une information précontractuelle renforcée et par l'introduction d'un délai de rétractation de quatorze jours. La définition du démarchage, limitée au démarchage « en face-à-face » à domicile, pourrait ainsi être harmonisée.
Keywords: Assurance; Banques; France; Marketing; Services financiers; Télémarketing; Vente à domicile

L'impact du nouveau système comptable OHADA sur les jugements et décisions des agents de prêt : Le cas du Cameroun - Saidatou, Hamidou Dicko (Université du Québec à Montréal, 2006)
Pour répondre à la mouvance des mutations économiques dues à la mondialisation, 16 États africains ont signé le Traité relatif à l'Harmonisation du Droit des Affaires en Afrique, créant ainsi l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) le 17 octobre 1993. L'objectif de l'OHADA est de créer des droits relatifs aux affaires, droits modernes et adaptés au contexte africain, afin de permettre une meilleure intégration économique et un développement harmonieux de l'Afrique. Ainsi, l'Acte Uniforme portant Organisation et Harmonisation des comptabilités des entreprises des États parties du Traité a été adopté le 24 mars 2000. Le 1er janvier 2001, toutes les entreprises étaient donc tenues de passer au système comptable OHADA pour les comptes personnels (d'entreprises), et le 1er janvier 2002 pour les comptes consolidés. Avant l'adoption de cette nouvelle normalisation comptable, les pays de l'Afrique Noire Francophone (dont le Cameroun), dans leur majorité, utilisaient le plan comptable OCAM, calqué des plans comptables généraux français de 1947 et 1957. L'objectif de notre recherche est de comparer l'impact du format de présentation et du contenu informationnel des deux modes de divulgation de l'information comptable sur les jugements et décisions des banquiers. La question est de savoir si l'information résultant du nouveau système comptable OHADA modifie les jugements et décisions des agents de prêt, comparativement à celle résultant de l'ancien plan comptable OCAM. Le changement de norme comptable a principalement amené les agents de prêt camerounais à modifier leurs jugements initiaux relatifs à la rentabilité et à la structure financière ainsi que leurs jugements sous-jacents (bénéfice d'exploitation, bénéfice net, endettement, liquidité et capacité d'injection de ressources); par contre, les différences notées pour ces jugements sous-jacents et initiaux ne les ont pas conduit à modifier leurs jugements principaux de la cote de risque et de sa tendance, ni les décisions de prêt et de fixation du taux d'intérêt. Lorsque le changement considère aussi le TAFlRE (tableau financier des ressources et emplois), les agents de prêt ne modifient que leur jugement initial de la rentabilité et leurs jugements sous-jacents du bénéfice d'exploitation, du bénéfice net, des flux de trésorerie ainsi que celui de l'endettement. Lorsque les deux groupes expérimentaux sont comparés, on constate un effet relativement Iimité du TAFIRE puisque seuls les jugements sous-jacents du bénéfice d'exploitation, de l'endettement, de la liquidité, de la capacité d'injection de ressources ainsi que le jugement initial de la structure financière sont différents. De plus, les états financiers du SYSCOHADA semblent avoir eu un effet relativement positif sur les jugements sous-jacents (bénéfice d'exploitation, bénéfice net et flux de trésorerie) et le jugement initial de la rentabilité pour les participants des deux groupes expérimentaux ainsi qu'un effet relativement positif sur les jugements sous-jacents (endettement, liquidité et capacité d'injection de ressources) et le jugement initial de la structure financière uniquement pour les participants du premier groupe.
https://archipel.uqam.ca/3193/
Keywords: Attitude; Banquier; Cameroun; Comptabilité; Norme comptable; Organisation commune africaine et malgache; Organisation pour l'harmonisation du droit des affaires en Afrique; Prise de décision; Prêt; Système d'information comptable

Les coopératives face aux normes comptables internationales : le cas de l’IAS 32 - Detilleux, Jean-Claude; Naett, Caroline (Revue internationale de l'économie sociale, 2005)
Cet article retrace deux années de campagne et de mobilisation du mouvement coopératif face à une norme comptable internationale qui représentait une menace pour l’avenir des coopératives. Le projet d’amendement à la norme IAS 32 préconisait que tout instrument financier pouvant faire l’objet d’un remboursement à la demande du porteur soit considéré comme une dette, quelle que soit sa nature juridique. Les parts sociales des coopératives, remboursables sous certaines conditions en vertu du principe de libre adhésion et de retrait, se trouvaient donc concernées : dans les termes de la nouvelle norme, elles ne devaient plus apparaître dans le capital, mais dans les dettes. Les auteurs soulignent les effets pénalisants pour les coopératives, avant de développer l’argumentaire apporté pour faire évoluer le texte. Le processus d’élaboration des normes comptables internationales est complexe, impliquant de multiples instances. L’article éclaire particulièrement le rôle joué par le mouvement coopératif pour améliorer la connaissance de la réalité et de la spécificité coopératives auprès des acteurs concernés par le dossier. This article recounts the cooperative movement's two years of campaigning and mobilization when its future was threatened by an international accounting standard. The proposed amendment to IAS 32 recommended that any financial instrument that could be refunded at the bearer's request be considered as a debt regardless of its legal status. Shares in a cooperative, which can be sold back under certain conditions by virtue of the principle of free admission and demission, were thus affected. According to the new accounting standard, they would no longer appear as part of the cooperative's capital but rather as part of its debts. The authors first show how this penalizes cooperatives and then develop the case that was made for changing the text. The process of drafting international accounting standards is complex and involves many different bodies. The article highlights the role the cooperative movement played in making the actors involved in the process more aware of the reality and specificities of cooperatives as well as the educational value of the campaign.

L'émergence des marchés financiers dans l'espace OHADA - Kalieu Elongo, Yvette Rachel; Keuffi, Daniel Ebénézer (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2004)
L‘observation de Yves Guyon selon laquelle l‘épargne populaire s‘investit (aujourd’hui) en valeurs mobilières exprime le fait que ces instruments sont devenus au courant du XXe siècle le moyen le plus usité par bon nombre d’entreprises en quête de financement. En effet, grâce aux avantages pratiques qu’elles présentent sur le plan individuel, les valeurs mobilières constituent sur le plan collectif un moyen de financement efficace pour les entreprises. Au XIXe siècle, par exemple, elles ont permis aux sociétés anonymes de collecter les capitaux nécessaires à la mise en place du potentiel industriel des pays occidentaux. Cette collecte des capitaux n’est possible que s’il existe un cadre approprié où les entreprises à la recherche des capitaux et les investisseurs désireux d’obtenir des placements rentables peuvent se rencontrer.

Le champ d'application territoriale des monopoles des établissements de crédit et des prestataires de services d'investissement - Coudert, Patrice (Université d'Auvergne Clermont-Ferrand 1, 2004)
Le prestataire de services bancaires ou financiers et son client doivent savoir si le professionnel agit dans la zone d'activité attribuée par l'agrément des autorités compétentes, l'exercice irrégulier étant passible de sanctions. L'étude procède en première partie à une délimitation spatiale de la zone d'efficacité internationale des dispositions françaises relatives aux monopoles bancaires et financiers, et rattache les activités déployées audit marché en seconde partie. La délimitation spatiale de la zone d'activité conduit à celle du marché ouvert au prestataire qui souhaite exercer en France et hors de France. Sans omettre l'influence des textes communautaires et internationaux, il faut vérifier que tous ces textes s'appliquent de façon territoriale et non pas personnelle. C'est la pluriterritorialité. Ensuite, il faut examiner l'éventuelle application hors des limites spatiales primitives de chaque texte, soit l'extraterritorialité ou la territorialité par prolongement. The banking or financial service provider and his customer must know if the professional acts in the zone of activity allotted by the approval of the proper authorities, the irregular exercise being liable to sanctions. The study carries out in first part a space delimitation of the zone of international effectiveness of the French provisions relating to the banking and financial monopolies, and attaches the activities deployed to that the market in second part. The space delimitation of the zone of activity leads to that of the market open to the person receiving benefits who wishes to exert in France and out of France. Without omitting the influence of the Community and international texts, it should be checked that all these texts apply in a territorial and not personal way. It is the pluriterritoriality. Then, it is necessary to examine the possible application out of the primitive space limits of each text, that is to say the extraterritoriality or the territoriality by prolongation.
Keywords: Banques (droit); Droit international privé

Des marchés publics à la commande publique : l'évolution du droit des marchés publics - Kalflèche, Grégory (Université Paris 2, 2004)
Les contrats que l'on regroupe sous le terme générique de " marchés publics " correspond aujourd'hui à de nombreuses modalités contractuelles différentes. Depuis la Révolution, et à la suite d'une évolution par sédimentation ou accumulation de textes, les contrats soumis à des procédures de passation ont subi une double extension : non seulement, matériellement, l'ensemble des biens doit, en principe, faire l'objet de " marchés publics ", mais en plus, organiquement, l'ensemble des personnes publiques, ainsi que certaines personnes sous influence publique, doivent respecter des procédures. Celles-ci imposent une publicité des futurs contrats ou une mise en concurrence des offres reçues. Le contrat de cette extension permet de conclure que les différentes qualifications contractuelles imposant des procédures sont trop diverses et confuses. Ces contrats peuvent par conséquent être utilement regroupés sous une notion juridique de Commande publique. Cette nouvelle qualification engloberait les qualifications actuelles - marchés publics, délégations de service public, contrats de partenariat -, avec pour objectif la rationalisation de l'ensemble de la matière. Cette rationalisation passe notamment par la reconnaissance et le développement de " principes de la commande publique ". Ces principes sont la liberté d'accès, l'égalité d'accès et de traitement, le principe de mise en concurrence, mais aussi les principes de transparence, d'efficience économique et ceux de protection de l'environnement. Ces principes constituent la base d'un régime commun minimum applicable à tous ces contrats.
Keywords: Commande publique; Délégations de service public; Marchés publics

La fiscalité directe des prestations de services dans les relations internationales - Lazimi, Vincent (Université Paris 9 Dauphine, 2004)
Dans un contexte de tertiarisation de l’économie mondiale, la fiscalité internationale des prestations de services apparaît comme une matière complexe et source d’insécurité pour les investisseurs. Elle soulève en effet des problématiques aussi bien au regard de la qualification fiscale des revenus que de l’imposition de ces revenus. Au regard de la qualification fiscale des revenus de services et dans un cadre conventionnel, la frontière entre les redevances et les bénéfices industriels et commerciaux est floue et les risques de double imposition due à une différence de qualification importants. Les difficultés de qualification culminent en matière de prestations intellectuelles du fait de leur convergence avec des transferts de technologies et de la volonté des pays en voie de développement d’élargir la définition classique des redevances en y incluant certaines rémunérations de services techniques. Elles sont également importantes dans le cadre de contrats mixtes ou de contrats dont la nature juridique n’est pas certaine (transferts internationaux de logiciels, contrats de crédit-bail mobilier transfrontaliers). Les revenus des prestations de services suivront, dans la plupart des conventions, le régime classique des bénéfices industriels et commerciaux. Or, le concept d’établissement stable qui est au cœur du mécanisme d’imposition des bénéfices industriels et commerciaux est fluctuant et revêt une acception plus ou moins large en fonction des conventions. De plus, ce concept tend à s’affaiblir et perdre de sa pertinence en raison de la dématérialisation des prestations de services. L’introduction des nouvelles technologies de l’information permet d’accélérer le processus de réalisation des prestations mais perturbe également les critères traditionnels de rattachement de la masse imposable. Enfin, le développement du commerce intra-groupe et les difficultés d’évaluation des prestations de services rendues entre sociétés liées conduisent les fiscalistes à s’interroger sur les modalités d’exécution des prestations de services intra-groupe, les conditions de déductibilité de ces rémunérations et la pratique des prix de transferts en matière d’activités de services
Keywords: Biens incorporels; Droit; Droit fiscal (droit international); Impôts; Politique fiscale; Établissements stables

Reflexiones sobre la transparencia en la información en el mercado primario de bonos corporativos - García Mori, Luis Miguel (Universidad Nacional Mayor de San Marcos, 2004)
El presente trabajo tiene como objetivo plantear algunas reflexiones sobre la transparencia en el mercado primario de bonos corporativos, dentro de un contexto posterior a la crisis asiática de 1997, la crisis rusa de 1998, la crisis del Brasil de 1999, y los escándalos corporativos de los años 2001 y 2002 de Enron, Worldcom y Tyco, que incrementaron la preocupación por las prácticas de Buen Gobierno Corporativo, que se fundamentan en la transparencia de la información que es proporcionada a los mercados financieros. La referencia que se ha tomado en el mercado financiero corresponde a las 18 emisiones de bonos corporativos colocados durante el año 2001, complementando el análisis con una muestra de seis emisiones, tres en dólares y tres en soles, para cada unos de los años siguientes 2002, 2003 y 2004. Los mercados financieros pueden ser clasificados en función al plazo: en mercado de dinero y de capitales, en función a la entrega: en mercado al contado o a plazo, en función a la emisión: en primario y secundario, en función a la obligación: en mercado de deuda y de acciones, en función al ámbito geográfico: en mercado local e internacional, en función al mecanismo centralizado de negociación: en mercado bursátil y extrabursátil, en función de la oferta: la misma puede ser pública o privada. Los mercados financieros permiten la transferencia de fondos, la redistribución del riesgo, determinan el precio y el rendimiento, proporcionan liquidez y reducen costos de búsqueda e información. Un mercado es el encuentro de ofertantes y demandantes, y en el caso de los mercados financieros, estamos ante el encuentro de ofertantes y demandantes de instrumentos financieros. Un instrumento financiero o activo financiero representa un derecho sobre un activo real o sobre el patrimonio o sobre los flujos futuros que genere, en tal sentido, su valor se obtiene al traer al presente, mediante una tasa de descuento, los flujos futuros que genere. La tasa de descuento es la tasa de interés que corresponde el rendimiento exigido por el inversionista en función al riesgo del valor, y representa el costo del dinero. En tal sentido, a mayor información respecto al instrumento financiero menor riesgo, y por ende, mayor valor del mismo, por consiguiente la transparencia que significa mayor información crea valor para el instrumento financiero y para el inversionista. La constitucionalización del Derecho del mercado ha sido un largo proceso histórico, ha representado la evolución del Derecho mercantil, desde el Derecho del comerciante, y los actos de comercio, hasta el derecho del mercado. En la actualidad, si bien se ha incluido la referencia al mercado de bienes en la Constitución, aún está ausente el mercado de capitales del texto constitucional. Recién con la Constitución de 1979 se incorporó al Banco Central en el texto constitucional, y se le encargó la estabilidad monetaria, la cual es la base para la emisión de instrumentos financieros, dado que la tasa de interés nominal incluye el riesgo de inflación. Sin embargo, no obstante este “deber constitucional”, su grado de incumplimiento alcanzó la cúspide en 1990 cuando la inflación superó el rango del siete mil por ciento anual. Las reflexiones que se presentan en el presente trabajo tratan de evidenciar los “conflictos de interés” y la “falta de transparencia” en el mercado primario de bonos corporativos y en la administración de las sociedades, en un tiempo en que el mercado de capitales en nuestro país es aún incipiente, pero que muestra una tendencia al crecimiento, lo que en el breve plazo exigirá un replanteamiento o perfeccionamiento de su regulación.
https://cybertesis.unmsm.edu.pe/item/76245703-7129-41dc-9c50-45a9fe80fbf9
Keywords: Bolsas de valores; Bonos; Inversiones

Les modes d'évaluation de la dignité de crédit d'un emprunteur - Salgueiro, Albert (Université d'Auvergne Clermont-Ferrand 1, 2004)
Le contrat de prêt est fondamentalement marqué par la confiance. Cependant, celle-ci ne peut se confondre avec de la crédulité. Le prêteur est donc celui qui, avant d'accorder un crédit, recherche si le demandeur de crédit, entreprise ou particulier, pourra et voudra rembourser ce crédit. En d'autres termes, le banquier va rechercher s'il est digne de confiance, s'il est digne de crédit. Bien évidemment, au cours du temps le banquier a su développer des techniques aptes à évaluer cette dignité. Reste qu'aujourd'hui nous sommes loin du temps où il faisait appel aux sens pour accorder un crédit. Cela était sans doute possible dans un temps où les demandeurs de crédit étaient peu nombreux, cela ne l'est plus aujourd'hui avec une distribution du crédit en masse. Face à ce phénomène, et afin d'assurer la rapidité des transactions et la sécurité du crédit, le banquier a donc développé des techniques d'évaluation de la dignité basées sur l'usage de l'outil informatique. . . Loan is fundamentally a contract marked by trust. However, the latter should not be mistaken with credulity. Therefore, the lender is the one who, before granting someone a credit, searches if the person who requests a credit, a firm or an individual, will wish and manage to pay back this credit. In other words, the banker will inquest if this person is trustworthy and creditworthy. Obviously, the banker has been developing during years means to assess that worthiness. The fact remains that today the banker no longer appeals to his common sense to grant a credit. This was probably possible at the time when few people were requesting credit. Today it is no longer possible because of mass credit distribution. Faced to such phenomenon and in order to assure the quickness of the transactions and the security of the credit, the banker has, in this way, developed, means to assess the worthiness based on the use of the computer tool...
Keywords: Banques; Crédit; Droit de l'informatique

Le contentieux du recouvrement de l’impôt - Masclet de Barbarin, Marie (Aix-Marseille Université, 2003)

Law of money, value and payment - Eitelberg, Eduard (University of Durban-Westville, 2002)
Societies have, since time immemorial, traded real goods and services for expectations of goods and services in some future. These expectations have been associated with tangible and, lately, intangible property - which is generally called money. From the crude quantity theory of money, the purchasing power of a monetary unit is given as 1/ P = T/(Mv). P is the price of the traded goods and services T, M is the total money supply and its turnover rate is v. The total money supply M is dominated by bank credit. In the South African law (and elsewhere) the judicial recognition given to bank credit (1) as money seems to have happened as an unintended side-effect to accepting cheques as delivery vehicles in a cash transfer without any tangible money moving from the transferor to the transferee. In payment of money, the law of property and the law of contract overlap and become inseparable. Both the English and South African laws define payment as performance of a preceding duty. The Supreme Court of Appeal, in the Vereins- und Westbank case seems to have declared an abstract transfer of ownership of money to be payment even though no preceding duty to pay was found. The profit of a financial investment is called interest and is calculated from a simple or compound interest formula. Despite medieval legal, theological and ethical objections, neither is illegal in the South African positive law. The last remnant of the medieval protection of a guilty debtor (often the ruler) at the expense of an innocent creditor is the in duplum rule. This is particularly obnoxious during modern rampant inflation that was unknown and could not be predicted when only metallistic money was in use. The influence of the in duplum rule is being limited by recent restrictive judgments in South Africa and in Zimbabwe. In South Africa, the Government has a constitutional duty to ensure that its subjects are not deprived of property. Specifically, the Constitution prescribes in Section 224(1) that the South African Reserve Bank must 'protect the value of the currency'. It is shown that the recent Reserve Bank policies, unless urgently modified, are in conflict with the publicly promised inflation rate of no greater than 6%. The exchange rates depend fundamentally on the price levels of the traded or tradable goods and services in the respective economies. This leads to the concept of purchasing power parity, which is most accurately reflected in the relationship between interest rates in different states and their relative foreign exchange depreciation rates. It is submitted that the South African Exchange Control Regulations have outlived their usefulness (if ever they had any) and are unconstitutional - at least in so far as they interfere with the South African Reserve Bank's obligation to pursue its primary object 'independently and without fear'. In the main, the South African Courts have applied restrictive interpretation to the Exchange Control Regulations and they have justifiably ignored the public international law obligation of the Republic to recognise the Exchange Control Regulations of fellow IMF members extraterritorially. (1) To money related claims on banks - see the body of the thesis for the two-creditor-two-debtor legal aspects in the 'bank credit'.

Taken en aansprakelijkheden van commissarissen en bedrijfsrevisoren - Aerts, Koenraad (Larcier, 2002)